1,25-dihydroxyvitamin-D3 but not the clinically applied marker 25-hydroxyvitamin-D3 predicts survival after stem cell transplantation - Peter, Katrin; Siska, Peter J.; Roider, Tobias; Matos, Carina; Bruns, Heiko; Renner, Kathrin; Singer, Katrin; Weber, Daniela; Güllstorf, Martina; Kröger, Nicolaus; Wolff, Daniel; Herr, Wolfgang; et al. (Bone Marrow Transplantation, 2020)
The serum level of 25-hydroxyvitamin-D3 is accepted as marker for a person’s vitamin D status but its role for the outcome of allogeneic hematopoietic stem cell transplantation (HSCT) is controversially discussed. The impact of 1,25-dihydroxyvitamin-D3 on HSCT outcome, however, has never been studied. In a discovery cohort of 143 HSCT patients we repeatedly (day −16 to 100) measured 1,25-dihydroxyvitamin-D3 and in comparison the well-established marker for serum vitamin D status 25-hydroxyvitamin-D3. Only lower 1,25-dihydroxyvitamin-D3 levels around HSCT (day −2 to 7, peritransplant) were significantly associated with higher 1-year treatment-related mortality (TRM) risk (Mann–Whitney U test, P = 0.001). This was confirmed by Cox-model regression without and with adjustment for baseline risk factors and severe acute Graft-versus-Host disease (aGvHD; unadjusted P = 0.001, adjusted P = 0.005). The optimal threshold for 1,25-dihydroxyvitamin-D3 to identify patients at high risk was 139.5 pM. Also in three replication cohorts consisting of altogether 365 patients 1,25-dihydroxyvitamin-D3 levels below 139.5 pM had a 3.3-fold increased risk of TRM independent of severe aGvHD compared to patients above 139.5 pM (Cox-model unadjusted P < 0.0005, adjusted P = 0.001). Our data highlight peritransplant 1,25-dihydroxyvitamin-D3 levels but not the commonly monitored 25-hydroxyvitamin-D3 levels as potent predictor of 1-year TRM and suggest to monitor both vitamin D metabolites in HSCT patients.
CRIS-Team Scopus Importer:2020-09-04

2-Deoxyglucose induced unfolded protein response enhances efficacy of immunotoxin Moxetumomab pasudotox against lymphoma and leukemia xenografts - Wagner, Franziska; Meier, C.; Krumbholz, Manuela; Metzler, Markus; Mackensen, Andreas; Müller, Fabian (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

4-1BB/CD137 triggering on human monocytes leads to differentiation into macrophages with increased metabolic support and tumoricidal capacity - Stoll, Andrej; Bruns, Heiko; Gamali, S.; Saul, Domenica; Mackensen, Andreas; Mougiakakos, Dimitrios (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

5-Azacytidine prevents relapse and produces long-term complete remissions in leukemia xenografts treated with Moxetumomab pasudotox - Müller, Fabian; Cunningham, Tyler; Stookey, Stephanie; Tai, Chin-Hsien; Burkett, Sandra; Jailwala, Parthav; Stevenson, Maryalice Stetler; Cam, Margaret C.; Wayne, Alan S.; Pastan, Ira (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Moxetumomab pasudotox (Moxe) is a chimeric protein composed of an anti-CD22 Fv fused to a portion of Pseudomonas exotoxin A and kills CD22-expressing leukemia cells. It is very active in hairy-cell leukemia, but many children with relapsed/refractory acute lymphoblastic leukemia (ALL) either respond transiently or are initially resistant. Resistance to Moxe in cultured cells is due to low expression of diphthamide genes (DPH), but only two of six ALL blast samples from resistant patients had low DPH expression. To develop a more clinically relevant model of resistance, we treated NSG mice bearing KOPN-8 or Reh cells with Moxe. More than 99.9% of the cancer cells were killed by Moxe, but relapse occurred from discrete bone marrow sites. The resistant cells would no longer grow in cell culture and showed major chromosomal changes and changes in phenotype with greatly decreased CD22. RNA deep sequencing of resistant KOPN-8 blasts revealed global changes in gene expression, indicating dedifferentiation toward less-mature B cell precursors, and showed an up-regulation of myeloid genes. When Moxe was combined with 5-azacytidine, resistance was prevented and survival increased to over 5 months in the KOPN-8 model and greatly improved in the Reh model. We conclude that Moxe resistance in mice is due to a new mechanism that could not be observed using cultured cells and is prevented by treatment with 5-azacytidine.
EVALuna2:34163

A20 as a novel prognostic factor for recurrence and patients' survival in oral squamous cell carcinoma - Spörl, Silvia; Erber, Ramona; Gerken, M.; Fischer, R.; Taxis, J.; Meier, J. K.; Geppert, Carol-Immanuel; Hartmann, Arndt; Beckhove, P.; Mackensen, Andreas; Reichert, T.; Spanier, G.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

A20 as a Potential New Tool in Predicting Recurrence and Patient’s Survival in Oral Squamous Cell Carcinoma - Spoerl, Steffen; Erber, Ramona; Gerken, Michael; Taxis, Juergen; Ludwig, Nils; Nieberle, Felix; Biermann, Niklas; Geppert, Carol-Immanuel; Ettl, Tobias; Hartmann, Arndt; Beckhove, Philipp; Reichert, Torsten E.; et al. (Cancers, 2023)
A20, known as a potent inhibitor of NF-κB signaling, has been characterized in numerous clinical as well as preclinical studies. Recently, especially in various malignant diseases, the prognostic and therapeutic relevance of A20 was investigated. In oral squamous cell carcinoma (OSCC) however, the characterization of A20 is uncharted territory. We analyzed a tissue microarray (TMA) of 229 surgically-treated OSCC patients (2003–2013). Immunohistochemical (IHC) stainings were performed for A20 and CD3; additionally, standard haematoxylin-eosin staining was applied. IHC findings were correlated with a comprehensive dataset, comprising clinical and pathohistological information. A20 expression was analyzed in tumor cells as well as in tumor infiltrating lymphocytes (TILs) and correlated with the overall survival (OS) and recurrence-free survival (RFS) using uni- and multivariable Cox regression. The median follow-up time was 10.9 years and the A20 expression was significantly decreased in CD3+ TILs compared to mucosa-infiltrating lymphocytes (MILs). In the Kaplan–Meier analyses, higher A20 expression in TILs was correlated with better OS (p = 0.017) and RFS (p = 0.020). In the multivariable survival analysis, A20 overexpression correlated with improved OS (HR: 0.582; 95% CI 0.388–0.873, p = 0.009) and RFS (HR 0.605; 95% CI 0.411–0.889, p = 0.011). Our results indicate a novel prognostic role for A20 in OSCC. Due to its elevated expression in TILs, further research is highly desirable, which therefore could offer new therapeutic opportunities for patients suffering from OSCC.
CRIS-Team Scopus Importer:2023-02-24
Keywords: A20; oral squamous cell carcinoma; OSCC; tissue microarray; TNFAIP3

Aberrant expression of glyceraldehyde-3-phosphate dehydrogenase (Gapdh) in warthin tumors - Mandic, Robert; Agaimy, Abbas; Pinto-Quintero, Daniel; Roth, Katrin; Teymoortash, Afshin; Schwarzbach, Hans; Stoehr, Christine; Rodepeter, Fiona R.; Stuck, Boris A.; Bette, Michael (Cancers, 2020)
The Warthin tumor represents the second most frequent benign tumor of the parotid gland and is characterized by the presence of oncocytes rich in structurally and functionally altered mitochondria. Next to its role in metabolism, glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is also implicated in cellular mitophagy. Immunohistochemistry was carried out on Warthin tumor and normal control (parotid gland with striated ducts) tissues, using anti-GAPDH specific antibodies followed by digital image analysis. Laser capture microdissection was used to isolate the oncocytic tumor cell and normal control striated duct compartments for RNA extraction and qPCR. Warthin tumor oncocytes exhibited a markedly spotted GAPDH staining pattern exhibiting cells with cytoplasmic and nuclear, only nuclear or none GAPDH staining. A significantly lower (p < 0.0001) total GAPDH signal was detected in Warthin tumor oncocytes. Similarly, significantly lower (p < 0.005) GAPDH mRNA levels were seen in oncocytes compared with normal ductal cells. To exclude the possibility of this GAPDH staining pattern being a general feature of oncocytic neoplasms of different organs, we tested a cohort of renal oncocytoma and oncocytic chromophobe carcinoma; none showed this type of staining. The observed progressive GAPDH loss in Warthin tumor oncocytes could be implicated in the pathogenesis of Warthin tumors.
CRIS-Team Scopus Importer:2020-06-02
Keywords: GAPDH; Mitophagy; Oncocyte; Warthin tumor

Abnormally differentiated CD4+ or CD8+ T cells with phenotypic and genetic features of double negative T cells in human Fas deficiency - Rensing-Ehl, Anne; Voelkl, Simon; Speckmann, Carsten; Lorenz, Myriam Ricarda; Ritter, Julia; Janda, Ales; Abinun, Mario; Pircher, Hanspeter; Bengsch, Bertram; Thimme, Robert; Fuchs, Ilka; Ammann, Sandra; et al. (Blood, 2014)
Accumulation of CD3(+) T-cell receptor (TCR)??(+)CD4(-)CD8(-) double-negative T cells (DNT) is a hallmark of autoimmune lymphoproliferative syndrome (ALPS). DNT origin and differentiation pathways remain controversial. Here we show that human ALPS DNT have features of terminally differentiated effector memory T cells reexpressing CD45RA(+) (TEMRA), but are CD27(+)CD28(+)KLRG1(-) and do not express the transcription factor T-bet. This unique phenotype was also detected among CD4(+) or CD8(+) ALPS TEMRA cells. T-cell receptor ? deep sequencing revealed a significant fraction of shared CDR3 sequences between ALPS DNT and both CD4(+) and CD8(+)TEMRA cells. Moreover, in ALPS patients with a germ line FAS mutation and somatic loss of heterozygosity, in whom biallelic mutant cells can be tracked by absent Fas expression, Fas-negative T cells accumulated not only among DNT, but also among CD4(+) and CD8(+)TEMRA cells. These data indicate that in human Fas deficiency DNT cannot only derive from CD8(+), but also from CD4(+) T cells. Furthermore, defective Fas signaling leads to aberrant transcriptional programs and differentiation of subsets of CD4(+) and CD8(+) T cells. Accumulation of these cells before their double-negative state appears to be an important early event in the pathogenesis of lymphoproliferation in ALPS patients.
EVALuna2:25697

Accumulation of T-cell-suppressive PD-L1 high extracellular vesicles is associated with GvHD and might impact GvL efficacy - Baur, Rebecca; Karl, Franziska; Böttcher-Loschinski, Romy; Stoll, Andrej; Völkl, Simon; Gießl, Andreas; Flamann, Cindy; Bruns, Heiko; Schlötzer-Schrehardt, Ursula; Böttcher, Martin; Schewe, Denis M.; Fischer, Thomas; et al. (Journal for ImmunoTherapy of Cancer, 2023)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) represents the only curative treatment option for a number of hemato-oncological disorders. In fact, allo-HSCT is considered as one of the most successful immunotherapies as its clinical efficacy is based on the donor T-cells' capacity to control residual disease. This process is known as the graft-versus-leukemia (GvL) reaction. However, alloreactive T-cells can also recognize the host as foreign and trigger a systemic potentially life-threatening inflammatory disorder termed graft-versus-host disease (GvHD). A better understanding of the underlying mechanisms that lead to GvHD or disease relapse could help us to improve efficacy and safety of allo-HSCT. In recent years, extracellular vesicles (EVs) have emerged as critical components of intercellular crosstalk. Cancer-associated EVs that express the immune checkpoint molecule programmed death-ligand 1 (PD-L1) can suppress T-cell responses and thus contribute to immune escape. At the same time, it has been observed that inflammation triggers PD-L1 expression as part of a negative feedback network. Here, we investigated whether circulating EVs following allo-HSCT express PD-L1 and tested their efficacy to suppress the ability of (autologous) T-cells to effectively target AML blasts. Finally, we assessed the link between PD-L1 levels on EVs to (T-)cell reconstitution, GvHD, and disease relapse. We were able to detect PD-L1 + EVs that reached a peak PD-L1 expression at 6 weeks post allo-HSCT. Development of acute GvHD was linked to the emergence of PD-L1 high EVs following allo-HSCT. Moreover, PD-L1 levels correlated positively with GvHD grade and declined (only) on successful therapeutic intervention. T-cell-inhibitory capacity was higher in PD-L1 high EVs as compared with their PD-L1 low counterparts and could be antagonized using PD-L1/PD-1 blocking antibodies. Abundance of T-cell-suppressive PD-L1 high EVs appears to also impact GvL efficacy as patients were at higher risk for relapse. Finally, patients of PD-L1 high cohort displayed a reduced overall survival.Taken together, we show that PD-L1-expressing EVs are present following allo-HSCT. PD-L1 levels on EVs correlate with their ability to suppress T-cells and the occurrence of GvHD. The latter observation may indicate a negative feedback mechanism to control inflammatory (GvHD) activity. This intrinsic immunosuppression could subsequently promote disease relapse.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Immune Evation; T-Lymphocytes; Transplantation Immunology

A Comparison of Aspergillus and Mucorales PCR Testing of Different BAL Fractions from Patients with Suspected Invasive Pulmonary Fungal Disease - Springer, Jan; White, P. Lewis; Kessel, Johanna; Wieters, Imke; Teschner, Daniel; Korczynski, Daniel; Liebregts, Tobias; Cornely, Oliver A.; Schwartz, Stefan; Elgeti, Thomas; Meintker, Lisa; Krause, Stefan; et al. (Journal of Clinical Microbiology, 2017)
In patients with haematological malignancies, bronchoalveolar lavage fluid specimens (BALF) are commonly used for the diagnosis of mould infections. However, it is not clear whether the cellular pellet (P) or the supernatant fraction (S) of the BALF is optimal for molecular diagnostic testing. Thus, 99 BALF specimens from 96 haematology patients with or without allogeneic hematopoietic stem cell transplant were collected. Pellets and supernatants were processed alone and in combination (S/P) by two fungal-specific real-time PCR assays compliant with international recommendations. S/P revealed superior results in comparison to S and P alone, both single fractions showed reduced sensitivity for the detection of Aspergillus DNA (82% (S) and 43% (P), respectively). In 57% of the samples, the combination of S/P generated a lower Cq value compared to S or P testing alone. Five and 16 out of 28 samples would have been missed if only S or P was analysed, respectively. No sample was positive in S or P only. Similar results were obtained for the detection of Mucorales DNA in BALF (reduced sensitivity of 67% (S) and 50% (P), respectively). Study patients were categorized according to the current EORTC/MSG classification for invasive fungal disease (IFD), revealing 35 patients with proven/probable IFD (36%), 47 patients with possible IFD (49%) and 14 cases of undetermined IFD (15%).
EVALuna2:25778

Acute And Chronic Graft-Versus-Host-Disease Impair B-Cell Reconstitution in Allogeneic-Transplanted Patients at Different Maturation Stages - Fante, Matthias Alexander; Weigert, Verena; Hoffmann, Petra; Fehn, Ute; Winkler, Thomas; Winkler, Julia; Herr, Wolfgang; Edinger, Matthias; Wolff, Daniel (BONE MARROW TRANSPLANTATION, 2021)
CRIS-Team WoS Importer:2021-07-23

A Day 14 Endpoint for Acute GVHD Clinical Trials - Spyrou, Nikolaos; Akahoshi, Yu; Kowalyk, Steven; Morales, George; Beheshti, Rahnuma; Aguayo-Hiraldo, Paibel; Al Malki, Monzr M.; Ayuk, Francis; Bader, Peter; Baez, Janna; Capellini, Alexandra; Choe, Hannah; et al. (Transplantation and Cellular Therapy, 2024)
The overall response rate (ORR) 28 days after treatment has been adopted as the primary endpoint for clinical trials of acute graft versus host disease (GVHD). However, physicians often need to modify immunosuppression earlier than day (D) 28, and non-relapse mortality (NRM) does not always correlate with ORR at D28. We studied 1144 patients that received systemic treatment for GVHD in the Mount Sinai Acute GVHD International Consortium (MAGIC) and divided them into a training set (n=764) and a validation set (n=380). We used a recursive partitioning algorithm to create a Mount Sinai model that classifies patients into favorable or unfavorable groups that predicted 12 month NRM according to overall GVHD grade at both onset and D14. In the Mount Sinai model grade II GVHD at D14 was unfavorable for grade III/IV GVHD at onset and predicted NRM as well as the D28 standard response model. The MAGIC algorithm probability (MAP) is a validated score that combines the serum concentrations of suppression of tumorigenicity 2 (ST2) and regenerating islet-derived 3-alpha (REG3α) to predict NRM. Inclusion of the D14 MAP biomarker score with the D14 Mount Sinai model created three distinct groups (good, intermediate, poor) with strikingly different NRM (8%, 35%, 76% respectively). This D14 MAGIC model displayed better AUC, sensitivity, positive and negative predictive value, and net benefit in decision curve analysis compared to the D28 standard response model. We conclude that this D14 MAGIC model could be useful in therapeutic decisions and may offer an improved endpoint for clinical trials of acute GVHD treatment.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Acute GVHD; Biomarkers; Classification and regression tree; Competing risk; Competing risks; Composite; Decision curve analysis; Endpoints; Immunosuppression; Machine learning; Nonrelapse mortality; Surrogate; Time-dependent AUC; Treatment response

Addition of sorafenib versus placebo to standard therapy in patients aged 60 years or younger with newly diagnosed acute myeloid leukaemia (SORAML): a multicentre, phase 2, randomised controlled trial - Rollig, Christoph; Serve, Hubert; Huettmann, Andreas; Noppeney, Richard; Mueller-Tidow, Carsten; Krug, Utz; Baldus, Claudia D.; Brandts, Christian H.; Kunzmann, Volker; Einsele, Hermann; Kraemer, Alwin; Schaefer-Eckart, Kerstin; et al. (Lancet Oncology, 2015)
Preclinical data and results from non-randomised trials suggest that the multikinase inhibitor sorafenib might be an effective drug for the treatment of acute myeloid leukaemia. We investigated the efficacy and tolerability of sorafenib versus placebo in addition to standard chemotherapy in patients with acute myeloid leukaemia aged 60 years or younger.This randomised, double-blind, placebo-controlled, phase 2 trial was done at 25 sites in Germany. We enrolled patients aged 18-60 years with newly diagnosed, previously untreated acute myeloid leukaemia who had a WHO clinical performance score 0-2, adequate renal and liver function, no cardiac comorbidities, and no recent trauma or operation. Patients were randomly assigned (1:1) to receive two cycles of induction therapy with daunorubicin (60 mg/m(2) on days 3-5) plus cytarabine (100 mg/m(2) on days 1-7), followed by three cycles of high-dose cytarabine consolidation therapy (3 g/m(2) twice daily on days 1, 3, and 5) plus either sorafenib (400 mg twice daily) or placebo on days 10-19 of induction cycles 1 and 2, from day 8 of each consolidation, and as maintenance for 12 months. Allogeneic stem-cell transplantation was scheduled for all intermediate-risk patients with a sibling donor and for all high-risk patients with a matched donor in first remission. Computer-generated randomisation was done in blocks. The primary endpoint was event-free survival, with an event defined as either primary treatment failure or relapse or death, assessed in all randomised patients who received at least one dose of study treatment. We report the final analysis. This trial is registered with ClinicalTrials.gov, number NCT00893373, and the EU Clinical Trials Register (2008-004968-40).Between March 27, 2009, and Nov 28, 2011, 276 patients were enrolled and randomised, of whom nine did not receive study medication. 267 patients were included in the primary analysis (placebo, n=133; sorafenib, n=134). With a median follow-up of 36 months (IQR 35·5-38·1), median event-free survival was 9 months (95% CI 4-15) in the placebo group versus 21 months (9-32) in the sorafenib group, corresponding to a 3-year event-free survival of 22% (95% CI 13-32) in the placebo group versus 40% (29-51) in the sorafenib group (hazard ratio [HR] 0·64, 95% CI; 0·45-0·91; p=0·013). The most common grade 3-4 adverse events in both groups were fever (71 [53%] in the placebo group vs 73 [54%] in the sorafenib group), infections (55 [41%] vs 46 [34%]), pneumonia (21 [16%] vs 20 [14%]), and pain (13 [10%] vs 15 [11%]). Grade 3 or worse adverse events that were significantly more common in the sorafenib group than the placebo group were fever (relative risk [RR] 1·54, 95% CI 1·04-2·28), diarrhoea (RR 7·89, 2·94-25·2), bleeding (RR 3·75, 1·5-10·0), cardiac events (RR 3·46, 1·15-11·8), hand-foot-skin reaction (only in sorafenib group), and rash (RR 4·06, 1·25-15·7).In patients with acute myeloid leukaemia aged 60 years or younger, the addition of sorafenib to standard chemotherapy has antileukaemic efficacy but also increased toxicity. Our findings suggest that kinase inhibitors could be a useful addition to curative treatment for acute myeloid leukaemia. Overall survival after long-term follow-up and strategies to reduce toxicity are needed to determine the future role of sorafenib in treatment of this disease.Bayer HealthCare.
EVALuna2:25715

A defined metabolic state in pre B cells governs B-cell development and is counterbalanced by Swiprosin-2/EFhd1 - Stein, Merle; Dütting, Sebastian; Mougiakakos, Dimitrios; Boesl, Michael R.; Fritsch, Kristin; Reimer, Dorothea; Urbanczyk, Sophia; Steinmetz, Tobit; Schuh, Wolfgang; Bozec, Aline; Winkler, Thomas; Jäck, Hans-Martin; et al. (Cell Death and Differentiation, 2017)
B-cell development in the bone marrow comprises proliferative and resting phases in different niches. We asked whether B-cell metabolism relates to these changes. Compared to pro B and small pre B cells, large pre B cells revealed the highest glucose uptake and ROS but not mitochondrial mass, whereas small pre B cells exhibited the lowest mitochondrial membrane potential. Small pre B cells from Rag1;33.C9 μ heavy chain knock-in mice revealed decreased glycolysis (ECAR) and mitochondrial spare capacity compared to pro B cells from Rag1 mice. We were interested in the step regulating this metabolic switch from pro to pre B cells and uncovered that Swiprosin-2/EFhd1, a Ca-binding protein of the inner mitochondrial membrane involved in Ca-induced mitoflashes, is expressed in pro B cells, but downregulated by surface pre B-cell receptor expression. Knockdown and knockout of EFhd1 in 38B9 pro B cells decreased the oxidative phosphorylation/glycolysis (OCR/ECAR) ratio by increasing glycolysis, glycolytic capacity and reserve. Prolonged expression of EFhd1 in EFhd1 transgenic mice beyond the pro B cell stage increased expression of the mitochondrial co-activator PGC-1α in primary pre B cells, but reduced mitochondrial ATP production at the pro to pre B cell transition in IL-7 cultures. Transgenic EFhd1 expression caused a B-cell intrinsic developmental disadvantage for pro and pre B cells. Hence, coordinated expression of EFhd1 in pro B cells and by the pre BCR regulates metabolic changes and pro/pre B-cell development.Cell Death and Differentiation advance online publication, 19 May 2017; doi:10.1038/cdd.2017.52.

A distinct CD38+CD45RA+ population of CD4+, CD8+, and double-negative T cells is controlled by FAS - Maccari, Maria Elena; Fuchs, Sebastian; Kury, Patrick; Andrieux, Geoffroy; Bengsch, Bertram; Lorenz, Myriam Ricarda; Heeg, Maximilian; Rohr, Jan; Jägle, Sabine; Castro, Carla N.; Groß, Miriam; Warthorst, Ursula; et al. (Journal of Experimental Medicine, 2021)
The identification and characterization of rare immune cell populations in humans can be facilitated by their growth advantage in the context of specific genetic diseases. Here, we use autoimmune lymphoproliferative syndrome to identify a population of FAS-controlled TCRαβ+ T cells. They include CD4+, CD8+, and double-negative T cells and can be defined by a CD38+CD45RA+T-BET- expression pattern. These unconventional T cells are present in healthy individuals, are generated before birth, are enriched in lymphoid tissue, and do not expand during acute viral infection. They are characterized by a unique molecular signature that is unambiguously different from other known T cell differentiation subsets and independent of CD4 or CD8 expression. Functionally, FAS-controlled T cells represent highly proliferative, noncytotoxic T cells with an IL-10 cytokine bias. Mechanistically, regulation of this physiological population is mediated by FAS and CTLA4 signaling, and its survival is enhanced by mTOR and STAT3 signals. Genetic alterations in these pathways result in expansion of FAS-controlled T cells, which can cause significant lymphoproliferative disease.
CRIS-Team Scopus Importer:2020-12-18

A Dual Role for TNF-Producing T Cells in the Fetal Intestine - Leppkes, Moritz; Neurath, Markus (Immunity, 2019)
The role of tumor necrosis factor (TNF) in the fetal intestine is poorly understood. In this issue of Immunity, Schreurs et al. (2019) identify important roles of TNF-producing T cells as both regulators of gut development and potential inducers of colitis.
CRIS-Team WoS Importer:2019-03-06

A dual-targeting triplebody mediates preferential redirected lysis of antigen double-positive over single-positive leukemic cells - Schubert, Ingo; Saul, Domenica; Nowecki, Stefanie; Mackensen, Andreas; Fey, Georg; Oduncu, Fuat S. (Mabs, 2014)
The single-chain triplebody HLA-ds16-hu19 consists of three single-chain Fv (scFv) antibody fragments connected in a single polypeptide chain. This protein with dual-targeting capacity mediated preferential lysis of antigen double-positive (dp) over single-positive (sp) leukemic cells by recruitment of natural killer (NK) cells as effectors. The two distal scFv modules were specific for the histocompatibility protein HLA-DR and the lymphoid antigen CD19, the central one for the Fc gamma receptor CD16. In antibody-dependent cellular cytotoxicity (ADCC) experiments with a mixture of leukemic target cells comprising both HLA-DR sp HuT-78 or Kasumi-1 cells and (HLA-DR plus CD19) dp SEM cells, the triplebody mediated preferential lysis of the dp cells even when the sp cells were present in <=20-fold numerical excess. The triplebody promoted equal lysis of SEM cells at 2.5-fold and 19.5-fold lower concentrations than the parental antibodies specific for HLA-DR and CD19, respectively. Finally, the triplebody also eliminated primary leukemic cells at lower concentrations than an equimolar mixture of bispecific single-chain Fv fragments (bsscFvs) separately addressing each target antigen (hu19-ds16 and HLA-ds16). The increased selectivity of targeting and the preferential lysis of dp over sp cells achieved by dual-targeting open attractive new perspectives for the use of dual-targeting agents in cancer therapy.
EVALuna2:1718

Advances in cellular therapy: 7th international symposium on the clinical use of cellular products, March 14 and 15, 2013, Erlangen, Germany - Aigner, Michael; Bruns, Heiko; Gary, Regina; Jitschin, Regina; Kremer, Anita; Mougiakakos, Dimitrios; Voelkl, Simon; Mackensen, Andreas; Gerbitz, Armin (Cancer Immunology Immunotherapy, 2014)
EVALuna2:25672

Adverse airway events in parturient compared with non-parturient patients. Is there a difference? Results from a quality management project - Heinrich, Stefan; Irouschek, Andrea; Prottengeier, Johannes; Ackermann, Andreas; Schmidt, Joachim (Journal of Obstetrics and Gynaecology Research, 2015)
The fear of airway problems often leads to prolonged attempts to obtain neuroaxial (spinal anesthesia or epidural anesthesia) anesthesia in obstetric anesthesia. The aim of this institutional quality management study was to revisit existing anesthesia care in the obstetric department, focusing on the frequency of delayed or failed neuroaxial anesthesia as well as the risk of airway problems in parturient and non-obstetric patients.The clinical records from 8 consecutive years (2005-2013) were analyzed retrospectively. Cases of cesarean delivery with general anesthesia were analyzed and compared with an age-matched group of female patients undergoing non-obstetric abdominal or gynecological surgery with rapid sequence induction. Poor laryngeal visualization (Cormack-Lehane grade III or IV) and failed intubation were recorded.The records of 6393 cesarean deliveries including 851 with general anesthesia were analyzed. In 175 cases insufficient or delayed onset of regional anesthesia led to requirement for general anesthesia. The rate of poor laryngoscopic view in parturient women undergoing cesarean delivery was 14/851, and 4/814 in the reference group (P = 0.023). Failed intubation occurred in three patients undergoing cesarean delivery (0.4%) and in one non-obstetric patient (0.1%; P = 0.339).The rate of failed intubations in patients undergoing cesarean delivery may be equivalent to non-obstetric patients. In time-challenging cesarean deliveries, delay of conversion from non-successful neuroaxial anesthesia to general anesthesia in order to avoid adverse airway events does not appear to be justified.
EVALuna2:16690

Age-dependent clinical outcomes in primary versus oral anticoagulation-related intracerebral hemorrhage - Sprügel, Maximilian; Kuramatsu, Joji; Gerner, Stefan T.; Sembill, Jochen; Madzar, Dominik; Reindl, Caroline; Bobinger, Tobias; Müller, Tamara; Hölter, Philip; Lücking, Hannes; Engelhorn, Tobias; Huttner, Hagen (International Journal of Stroke, 2019)
Aims This study determined the influence of age on bleeding characteristics and clinical outcomes in primary spontaneous (non-OAC), vitamin K antagonist-related (VKA-) and non-vitamin K antagonist oral anticoagulant-related (NOAC-) ICH. Methods Pooled individual patient data of multicenter cohort studies were analyzed by logistic regression modelling and propensity-score-matching (PSM) to explore the influence of advanced age on clinical outcomes among non-OAC-, VKA-, and NOAC-ICH. Primary outcome measure was functional outcome at three months assessed by the modified Rankin Scale, dichotomized into favorable (mRS = 0-3) and unfavorable (mRS = 4-6) functional outcome. Secondary outcome measures included mortality, hematoma characteristics, and frequency of invasive interventions. Results In VKA-ICH 33.5% (670/2001), in NOAC-ICH 44.2% (69/156) and in non-OAC-ICH 25.2% (254/1009) of the patients were >= 80 years. After adjustment for treatment interventions and relevant parameters, elderly ICH patients comprised worse functional outcome at three months (adjusted odds ratio (aOR) in VKA-ICH: 1.49 (1.21-1.84); p < 0.001; NOAC-ICH: 2.01 (0.95-4.26); p = 0.069; non-OAC-ICH: 3.54 (2.50-5.03); p < 0.001). Anticoagulation was significantly associated with worse functional outcome below the age of 70 years, (aOR: 2.38 (1.78-3.16); p < 0.001), but not in patients of >= 70 years (aOR: 1.21 (0.89-1.65); p = 0.217). The differences in initial ICH volume and extent of ICH enlargement between OAC-ICH and non-OAC-ICH gradually decreased with increasing patient age. Conclusions As compared to elderly ICH-patients, in patients <70 years OAC-ICH showed worse clinical outcomes compared to non-OAC-ICH because of larger baseline ICH-volumes and extent of hematoma enlargement. Treatment strategies aiming at neutralizing altered coagulation should be aware of these findings.
CRIS-Team WoS Importer:2020-01-28

Aggregated NETs Sequester and Detoxify Extracellular Histones - Knopf, Jasmin; Leppkes, Moritz; Schett, Georg; Herrmann, Martin; Munoz, Luis Enrique (Frontiers in Immunology, 2019)
In response to various infectious and sterile stimuli neutrophils release chromatin decorated with bactericidal proteins, referred to as NETs. Their scaffolds are formed from chromatin fibers which display an apparent diameter of 15-17 nm and mainly consist from DNA (2 nm) and DNA-associated histones (11 nm). The NET-forming strands are thus not naked DNA but higher ordered chromatin structures. The histones may be released from the NET, especially if their tail arginines have been citrullinated. Several studies indicate that extracellular histones are toxic for mammalian epithelia and endothelia and contribute to the microvascular dysfunction observed e.g., in patients suffering from autoimmune diseases or sepsis. NETs formed at sites of very high neutrophil densities tend to clump and form fairly stable enzymatically active aggregates, referred to as aggNETs. The latter are endowed with a bunch of enzymes that cleave, bind, and/or modify autologous as well as foreign macromolecules. The tight binding of the serine proteases to the matrix precludes the spread of these toxic enzymes into the tissue but still allows the access of soluble inflammatory mediators to the enzymatic active internal surfaces of the NETs where they are degraded. Here, we describe that externally added histones are removed from culture supernatants of aggNETs. We will address the fate of the histones and discuss the feature on the background of neutrophil-driven diseases and the resolution of inflammation.
CRIS-Team WoS Importer:2019-09-24

A group of cationic amphiphilic drugs activates MRGPRX2 and induces scratching behavior in mice - Wolf, Katharina; Kühn, Helen; Boehm, Felicitas; Gebhardt, Lisa; Glaudo, Markus; Agelopoulos, Konstantin; Ständer, Sonja; Ectors, Philipp; Zahn, Dirk; Riedel, Yvonne K.; Thimm, Dominik; Müller, Christa E.; et al. (Journal of Allergy and Clinical Immunology, 2021)
Background: Mas gene–related G protein–coupled receptors (MRGPRs) are a G protein–coupled receptor family responsive to various exogenous and endogenous agonists, playing a fundamental role in pain and itch sensation. The primate-specific family member MRGPRX2 and its murine orthologue MRGPRB2 are expressed by mast cells mediating IgE-independent signaling and pseudoallergic drug reactions. Objectives: Our aim was to increase knowledge about the function and regulation of MRGPRX2/MRGPRB2, which is of major importance in prevention of drug hypersensitivity reactions and drug-induced pruritus. Methods: To identify novel MRGPR (ant)agonists, we screened a library of pharmacologically active compounds by utilizing a high-throughput calcium mobilization assay. The identified hit compounds were analyzed for their pseudoallergic and pruritogenic effects in mice and human. Results: We found a class of commonly used drugs activating MRGPRX2 that, to a large extent, consists of antidepressants, antiallergic drugs, and antipsychotics. Three-dimensional pharmacophore modeling revealed structural similarities of the identified agonists, classifying them as cationic amphiphilic drugs. Mast cell activation was investigated by using the 3 representatively selected antidepressants clomipramine, paroxetine, and desipramine. Indeed, we were able to show a concentration-dependent activation and MRGPRX2-dependent degranulation of the human mast cell line LAD2 (Laboratory of Allergic Diseases-2). Furthermore, clomipramine, paroxetine, and desipramine were able to induce degranulation of human skin and murine peritoneal mast cells. These substances elicited dose-dependent scratching behavior following intradermal injection into C57BL/6 mice but less so in MRGPRB2-mutant mice, as well as wheal-and-flare reactions following intradermal injections in humans. Conclusion: Our results contribute to the characterization of structure-activity relationships and functionality of MRGPRX2 ligands and facilitate prediction of adverse reactions such as drug-induced pruritus to prevent severe drug hypersensitivity reactions.
CRIS-Team Scopus Importer:2021-04-19
Keywords: (drug-induced) pruritus; Mas gene–related G protein–coupled receptors; mast cells; pseudoallergic drug reactions

A human CD22 transgenic, myc-driven lymphoma model to test effects of targeted therapies on lymphoma immune microenvironment in immunecompetent mice - Wagner, Franziska; Brandl, Carolin; Petkovic, S.; Emmerich, C.; Nitschke, Lars; Mackensen, Andreas; Müller, Fabian (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

A humanized mouse identifies the bone marrow as a niche with low therapeutic IgG activity - Lux, Anja; Seeling, Michaela; Baerenwaldt, Anne; Lehmann, Birgit; Schwab, Inessa; Repp, Roland; Meidenbauer, Norbert; Mackensen, Andreas; Hartmann, Arndt; Heidkamp, Gordon Frederik; Dudziak, Diana; Nimmerjahn, Falk (Cell Reports, 2014)
Genetic differences between humans and in vivo model systems, including mice and nonhuman primates, make it difficult to predict the efficacy of immunoglobulin G (IgG) activity in humans and understand the molecular and cellular mechanisms underlying that activity. To bridge this gap, we established a small-animal model system that allowed us to study human IgG effector functions in the context of an intact human immune system without the interference of murine Fc? receptors expressed on mouse innate immune effector cells in vivo. Using a model of B cell depletion with different human IgG variants that recognize CD20, we show that this humanized mouse model can provide unique insights into the mechanism of human IgG activity in vivo. Importantly, these studies identify the bone marrow as a niche with low therapeutic IgG activity.
EVALuna2:6588

Allogeneic Hematopoietic Cell Transplantation in Intermediate Risk Acute Myeloid Leukemia negative for FLT3-ITD, NPM1- or biallelic CEBPA Mutations - Heidrich, K.; Thiede, C.; Schaefer-Eckart, K.; Schmitz, N.; Aulitzky, W. E.; Kraemer, A.; Rösler, Wolf; Haenel, M.; Einsele, H.; Baldus, C. D.; Trappe, R. U.; Stoelzel, F.; et al. (Annals of Oncology, 2017)
The value of allogeneic hematopoietic cell transplantation (alloHCT) as post-remission treatment is not well defined for patients with intermediate-risk acute myeloid leukemia (AML) without FLT3 -ITD, biallelic CEBPA -, or NPM1 mutations (here referred to as NPM1 mut-neg / CEBPA dm-neg / FLT3 -ITD neg AML) in first complete remission (CR1).We addressed this question using data from two prospective randomized controlled trials on intensive induction- and risk-stratified post-remission therapy The NPM1 mut-neg / CEBPA dm-neg / FLT3 -ITD neg AML subgroup comprised 497 patients, aged 18-60 years.In donor versus no-donor analyses, patients with a matched related donor had a longer relapse-free survival (RFS) (HR 0.5; 95%-CI, 0.3 - 0.9, p = .02) and a trend towards better overall survival (OS) (HR 0.6, 95%-CI, 0.3 - 1.1, p = .08) compared to patients who received post-remission chemotherapy. Notably, only 58% of patients in the donor group were transplanted in CR1. We therefore complemented the donor versus no-donor analysis with multivariable Cox regression analyses, where alloHCT was tested as a time-dependent covariate: OS (HR 0.58, 95%-CI, 0.37 - 0.9, p = .02) and RFS (HR 0.51; 95%-CI, 0.34 - 0.76; p = .001) for patients who received alloHCT compared to chemotherapy in CR1 were significantly longer.Outside clinical trials, alloHCT should be the preferred post-remission treatment for patients with intermediate risk NPM1 mut-neg /CEBPA dm-neg /FLT3-ITD neg AML in CR1.
EVALuna2:25771

Allogeneic Hematopoietic Cell Transplantation in Patients <= 60 Years with Intermediate-Risk Acute Myeloid Leukemia in First Remission - Results of the Randomized Etal-1 Trial- - Bornhaeuser, Martin; Schliemann, Christoph; Schetelig, Johannes; Rollig, Christoph; Kramer, Michael; Glass, Bertram; Platzbecker, Uwe; Burchert, Andreas; Haenel, Mathias; Mueller, Lutz Peter; Klein, Stefan; Bug, Gesine; et al. (BLOOD, 2021)
CRIS-Team WoS Importer:2022-09-09

Allogeneic Hematopoietic Cell Transplantation vs Standard Consolidation Chemotherapy in Patients With Intermediate-Risk Acute Myeloid Leukemia A Randomized Clinical Trial - Bornhaeuser, Martin; Schliemann, Christoph; Schetelig, Johannes; Roellig, Christoph; Kramer, Michael; Glass, Bertram; Platzbecker, Uwe; Burchert, Andreas; Haenel, Mathias; Mueller, Lutz P.; Klein, Stefan; Bug, Gesine; et al. (JAMA Oncology, 2023)
IMPORTANCE The ideal postremission strategy in intermediate-risk acute myeloid leukemia (AML) in first complete remission (CR) has been a matter of debate. OBJECTIVE To explore the optimal therapy for patients with intermediate-risk AML after first complete remission. DESIGN, SETTINGS, AND PARTICIPANTS This investigator-initiated, open-label, 2-armed, phase 3 randomized clinical trial assessed patients at 16 hospitals in Germany from February 2, 2011, until July 1, 2018. Key eligibility criteria included cytogenetically defined intermediate-risk AML according to Medical Research Council classification, first CR or CR with incomplete blood cell count recovery after conventional induction therapy, age of 18 to 60 years, and availability of a human leukocyte antigen (HLA)-matched sibling or unrelated donor. A detailed statistical analysis plan was written and finalized on July 7, 2020. Data were exported for analysis on April 13, 2021. INTERVENTIONS Patients were randomized 1:1 to receive allogeneic hematopoietic cell transplantation (HCT) or high-dose cytarabine for consolidation and salvage HCT only in case of relapse. Strata for randomization included age (18-40 vs 41-60 years), NPM1 and CEBPA variation status, and donor type (unrelated vs related). MAIN OUTCOMES AND MEASURES End points included overall-survival as the primary outcome and disease-free survival, cumulative incidence of relapse, treatment-related mortality, and quality of life measured according to the Medical Outcomes Study 36-Item Short-Form Health Survey as secondary outcomes. RESULTS A total of 143 patients (mean [SD] age, 48.2 [9.8] years; 81 [57%] male) with AML who fulfilled the eligibility criteria were randomized. In the intention-to-treat analysis, the probability of survival at 2 years was 74% (95% CI, 62%-83%) after primary allogeneic HCT and 84% (95% CI, 73%-92%) after consolidation chemotherapy (P = .22). Disease-free survival after HCT at 2 years was 69% (95% CI, 57%-80%) compared with 40% (95% CI, 28%-53%) after consolidation chemotherapy (P = .001). Allogeneic HCT during the first CR was associated with a cumulative incidence of relapse at 2 years of 20% (95% CI, 13%-31%) compared with 58% (95% CI, 47%-71%; P < .001). Nonrelapse mortality at 2 years after primary allogeneic HCT was 9% (95% CI, 5%-19%) and 2% (95% CI, 0%-11%) after consolidation chemotherapy (P = .005). Similar outcomes were observed when analyses were confined to the 96 patients at intermediate risk according to the European Leukemia Network classification. Most importantly, all 41 patients relapsing after consolidation chemotherapy (36 hematologic, 4 molecular, and 1 extramedullary) proceeded to allogeneic HCT. No significant differences in health-related quality of life measures were observed between groups. CONCLUSIONS AND RELEVANCE Primary allogeneic HCT during first CR was not associated with superior overall survival compared with consolidation chemotherapy in patients 60 years or younger with intermediate-risk AML during the first CR and an available donor.
CRIS-Team WoS Importer:2023-03-31

Allogeneic hematopoietic stem cell transplantation in patients with acute myeloid leukemia with ASXL1-, RUNX1- and TP53 mutations - Egger-Heidrich, K.; Middeke, J. M.; Schaefer-Eckart, K.; Kaufmann, M.; Einsele, H.; Mueller-Tidow, C.; Rösler, Wolf; Haenel, M.; Baldus, C. D.; Fransecky, L.; Stoelzel, F.; Roellig, C.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Allogeneic Stem Cell Transplantation Improves Survival in Patients with Acute Myeloid Leukemia Characterized by a High Allelic Ratio of Mutant FLT3-ITD - Ho, Anthony D.; Schetelig, Johannes; Bochtler, Tilmann; Schaich, Markus; Schaefer-Eckart, Kerstin; Haenel, Mathias; Rösler, Wolf; Einsele, Hermann; Kaufmann, Martin; Serve, Hubert; Berde, Wolfgang E.; Stelljes, Matthias; et al. (Biology of Blood and Marrow Transplantation, 2016)
Allogeneic hematopoietic cell transplantation (alloHCT) as a postremission therapy in patients with FLT3-ITD-positive intermediate-risk acute myeloid leukemia (AML) remains controversial. FLT3-ITD mutations are heterogeneous with respect to allelic ratio, location, and length of the insertion, with a high mutant-to-wild-type ratio consistently associated with inferior prognosis. We retrospectively analyzed the role of alloHCT in first remission in relationship to the allelic ratio and presence or absence of nucleophosmin 1 mutations (NPM1) in the Study Alliance Leukemia AML2003 trial. FLT3-ITD mutations were detected in 209 patients and concomitant NPM1 mutations in 148 patients. Applying a predefined cutoff ratio of .8, AML was grouped into high- and low-ratio FLT3-ITD AML (HR(FLT3-ITD) and LR(FLT3-ITD)). Sixty-one patients (29%) were transplanted in first remission. Overall survival (OS) (HR, .3; 95% CI, .16 to .7; P = .004) and event-free survival (EFS) (HR, .4; 95% CI, .16 to .9; P = .02) were significantly increased in patients with HR(FLT3-ITD) AML who received alloHCT as consolidation treatment compared with patients who received consolidation chemotherapy. Patients with LR(FLT3-ITD) AML and wild-type NPM1 who received alloHCT in first remission had increased OS (HR, .3; 95% CI, .1 to .8; P = .02) and EFS (HR, .2; 95% CI, .1 to .8; P = .02), whereas alloHCT in first remission did not have a significant impact on OS and EFS in patients with LR(FLT3-ITD) AML and concomitant NPM1 mutation. In conclusion, our results provide additional evidence that alloHCT in first remission improves EFS and OS in patients with HR(FLT3-ITD) AML and in patients with LR(FLT3-ITD) AML and wild-type NPM1.
EVALuna2:25727

Allogeneic Stem-Cell Transplantation in Patients With NPM1-Mutated Acute Myeloid Leukemia: Results From a Prospective Donor Versus No-Donor Analysis of Patients After Upfront HLA Typing Within the SAL-AML 2003 Trial - Roellig, Christoph; Bornhaeuser, Martin; Kramer, Michael; Thiede, Christian; Ho, Anthony D.; Kraemer, Alwin; Schaefer-Eckart, Kerstin; Wandt, Hannes; Haenel, Mathias; Einsele, Hermann; Aulitzky, Walter E.; Schmitz, Norbert; et al. (Journal of Clinical Oncology, 2015)
The presence of a mutated nucleophosmin-1 gene (NPM1mut) in acute myeloid leukemia (AML) is associated with a favorable prognosis. To assess the predictive value with regard to allogeneic stem-cell transplantation (SCT), we compared the clinical course of patients with NPM1mut AML eligible for allogeneic SCT in a donor versus no-donor analysis.Of 1,179 patients with AML (age 18 to 60 years) treated in the Study Alliance Leukemia AML 2003 trial, we identified all NPM1mut patients with an intermediate-risk karyotype. According to the trial protocol, patients were intended to receive an allogeneic SCT if an HLA-identical sibling donor was available. Patients with no available donor received consolidation or autologous SCT. We compared relapse-free survival (RFS) and overall survival (OS) depending on the availability of a suitable donor.Of 304 eligible patients, 77 patients had a sibling donor and 227 had no available matched family donor. The 3-year RFS rates in the donor and no-donor groups were 71% and 47%, respectively (P = .005); OS rates were 70% and 60%, respectively (P = .114). In patients with normal karyotype and no FLT3 internal tandem duplication (n = 148), the 3-year RFS rates in the donor and no-donor groups were 83% and 53%, respectively (P = .004); and the 3-year OS rates were 81% and 75%, respectively (P = .300).Allogeneic SCT led to a significantly prolonged RFS in patients with NPM1mut AML. The absence of a statistically significant difference in OS is most likely a result of the fact that NPM1mut patients who experienced relapse responded well to salvage treatment. Allogeneic SCT in first remission has potent antileukemic efficacy and is a valuable treatment option in patients with NPM1mut AML with a sibling donor.
EVALuna2:25704

Allogeneic transplantation in multiple myeloma: long-term follow-up and cytogenetic subgroup analysis - Knop, Stefan; Engelhardt, Monika; Liebisch, Peter; Meisner, Christoph; Holler, Ernst; Metzner, Bernd; Peest, Dietrich; Kaufmann, Martin; Bunjes, Donald; Straka, Christian; Fischer, Thomas; Sezer, Orhan; et al. (Leukemia, 2019)
This phase 3 trial compared tandem autologous stem cell transplantation (autoSCT) versus autoSCT followed by reduced-intensity conditioning allogeneic stem cell transplantation (auto/alloSCT) in patients with newly diagnosed multiple myeloma (MM) with deletion of (del) chromosome 13q (del13q). The availability/absence of a human leukocyte antigen-matched-related or matched-unrelated donor (MUD) determined the nature of the second SCT. The primary endpoint was progression-free survival (PFS) in the intention-to-treat population (n = 199). Auto/alloSCT was performed in 126 patients; 74 received MUD allografts. After 91 months median follow-up, median PFS with auto/allo versus tandem autoSCT was 34.5 versus 21.8 months (P = 0.003; adjusted hazard ratio 0.55, 95% confidence interval 0.36–0.84). Median overall survival (OS) was 70.2 versus 71.8 months (P = 0.856). Two-year non-relapse mortality with auto/allo versus tandem autoSCT was 14.3% versus 4.1% (P = 0.008). In patients harboring both del13q and del17p, median PFS and OS were 37.5 and 61.5 months with auto/allo (n = 19) versus 6.1 and 23.4 months with tandem autoSCT (n = 6) (P = 0.0002 and 0.032). Our findings suggest that auto/alloSCT significantly extends PFS versus tandem autoSCT in del13q MM, and indicate some survival benefit for first-line alloSCT in high-risk MM.
CRIS-Team Scopus Importer:2019-09-17

All-trans retinoic acid (ATRA) regulates CD8+T cell development, activity and functionality - Wendland, Kerstin; Kotarsky, K.; Belling, K.; Niss, K.; Nakawesi, J.; Lahl, K.; Agace, W. W. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Alnuctamab (ALNUC; BMS-986349; CC-93269), a B-Cell Maturation Antigen (BCMA) x CD3 T-Cell Engager (TCE), in Patients (pts) with Relapsed/Refractory Multiple Myeloma (RRMM): Results from a Phase 1 First-in-Human Clinical Study - Wong, Sandy W.; Bar, Noffar; Paris, Laura; Hofmeister, Craig C.; Hansson, Markus; Santoro, Armando; Mateos, Maria-Victoria; Rodriguez-Otero, Paula; Lund, Johan; Encinas, Cristina; Yee, Andrew J.; Oriol, Albert; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Alterations of cohesin complex genes in acute myeloid leukemia: differential co-mutations, clinical presentation and impact on outcome - Eckardt, Jan Niklas; Stasik, Sebastian; Röllig, Christoph; Sauer, Tim; Scholl, Sebastian; Hochhaus, Andreas; Crysandt, Martina; Brümmendorf, Tim H.; Naumann, Ralph; Steffen, Björn; Kunzmann, Volker; Einsele, Hermann; et al. (Blood Cancer Journal, 2023)
Functional perturbations of the cohesin complex with subsequent changes in chromatin structure and replication are reported in a multitude of cancers including acute myeloid leukemia (AML). Mutations of its STAG2 subunit may predict unfavorable risk as recognized by the 2022 European Leukemia Net recommendations, but the underlying evidence is limited by small sample sizes and conflicting observations regarding clinical outcomes, as well as scarce information on other cohesion complex subunits. We retrospectively analyzed data from a multi-center cohort of 1615 intensively treated AML patients and identified distinct co-mutational patters for mutations of STAG2, which were associated with normal karyotypes (NK) and concomitant mutations in IDH2, RUNX1, BCOR, ASXL1, and SRSF2. Mutated RAD21 was associated with NK, mutated EZH2, KRAS, CBL, and NPM1. Patients harboring mutated STAG2 were older and presented with decreased white blood cell, bone marrow and peripheral blood blast counts. Overall, neither mutated STAG2, RAD21, SMC1A nor SMC3 displayed any significant, independent effect on clinical outcomes defined as complete remission, event-free, relapse-free or overall survival. However, we found almost complete mutual exclusivity of genetic alterations of individual cohesin subunits. This mutual exclusivity may be the basis for therapeutic strategies via synthetic lethality in cohesin mutated AML.
CRIS-Team Scopus Importer:2023-02-03

Alterations of Immune Cells By Large B Cell Lymphoma Persist Years after Achieving Complete Remission and Correlate with Impaired Adaptive Immunity - Pelzl, Richard; Kübel, Sabrina; Klein, Paulina; Gsottberger, Franziska; Wendland, Kerstin; Petkovic, Srdjan; Brueckl, Valeska; Baur, Rebecca; Völkl, Simon; Mackensen, Andreas; Nganou-Makamdop, Krystelle; Müller, Fabian (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Alzheimer's disease protease-containing plasma extracellular vesicles transfer to the hippocampus via the choroid plexus - Lee, Jung Hyun; Ostalecki, Christian; Oberstein, Timo; Schierer, Stefan; Zinser, Elisabeth; Eberhardt, Martin; Blume, Katja; Plosnita, Bianca; Stich, Lena; Bruns, Heiko; Coras, Roland; Vera González, Julio; et al. (EBioMedicine, 2022)
Background: Plasma extracellular vesicles (pEV) can harbor a diverse array of factors including active proteases and the amyloid-precursor-protein (APP) cleavage product Aβ, involved in plaque formation in Alzheimer`s diseases (AD). A potential role of such vesicles in AD pathology is unexplored. Methods: In a case-control study of randomly selected patients with AD and other neurological diseases (n = 14), and healthy controls (n = 7), we systematically analyzed the content of pEV, using different assay systems. In addition, we determined their entry path into brain tissue, employing animal (mice) injection experiments with ex vivo generated EV that were similar to AD-pEV, followed by multi antigen analysis (MAA) of brain tissue (n = 4 per condition). The results were compared with an IHC staining of human brain tissue in a small cohort of AD patients (n = 3) and controls with no neurodegenerative diseases (n = 3). Findings: We show that pEV levels are considerably upregulated in AD patients. Besides numerous inflammatory effectors, AD-pEV contained α-, β- and γ-secretases, able to cleave APP in in target cells. In vitro generated EV with similar characteristics as AD-pEV accumulated in the choroid plexus (CP) of injected animals and reached primarily hippocampal neurons. Corroborating findings were made in human brain samples. An inhibitor of hyaluronic-acid-synthetase (HAS) blocked uploading of proteases and Hyaluronan onto EV in vitro and abolished CP targeting in animal injection experiments. Interpretation: We conclude that protease-containing pEV could be part of a communication axis between the periphery and the brain that could be become detrimental depending on pEV concentration and duration of target cell impact.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Alzheimer's disease; APP; Aβ; BACE; Choroid plexus; Hippocampus; Hyaluronan; Hyaluronic acid synthetase; Plasma extracellular vesicles; Secretases

AML-derived exosomes promote induction of myeloid-derived suppressor cells in an mTOR-signaling-dependent fashion - Jitschin, R.; Tohumeken, Sehmus; Saul, D.; Bruns, Heiko; Braun, Martina; Mackensen, Andreas; Mougiakakos, Dimitrios (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

A murine, myc-driven lymphoma model expressing human CD22 enables testing of targeted therapies and their effects on tumor immune microenvironment - Gsottberger, Franziska; Brandl, Carolin; Petkovic, S.; Emmerich, C.; Nitschke, Lars; Mackensen, Andreas; Müller, Fabian (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Analysis of dendritic cell subpopulations in follicular lymphoma with respect to the tumor immune microenvironment - Chevalier, Nina; Mueller, Michael; Mougiakakos, Dimitrios; Ihorst, Gabriele; Marks, Reinhard; Schmitt-Graeff, Annette; Veelken, Hendrik (Leukemia & Lymphoma, 2016)
The immune cell composition of the follicular lymphoma (FL) tumor microenvironment is increasingly recognized as an important determinant for clinical outcome. Here, we explored frequency and distribution of dendritic cell (DC) subtypes in relation to regulatory T cells (Treg) by immunohistochemistry in lymph node biopsies from patients with de novo FL. We found that neoplastic follicles contained lower DC and higher Treg frequencies than hyperplastic follicles in control lymph nodes. Treg numbers particularly correlated with the subset of conventional CD11c(+ )DCs. Additionally, both a high intra- to interfollicular ratio of CD11c(+ )DCs and increased intrafollicular Treg frequencies were associated with decreased overall survival. This suggests that functional interactions between these cells may be relevant for FL progression/recurrence. The presence of CD11c(+ )DCs in the tumor microenvironment may assist tumor infiltration by Tregs, thus contributing to the suppression of an otherwise beneficial T-cell-dominated FL microenvironment.
EVALuna:31719

Analysis of Luminex-based algorithms to define unacceptable HLA antibodies in CDC-crossmatch negative kidney transplant recipients - Zecher, Daniel; Bach, Christian; Preiss, Adrian; Staudner, Christoph; Utpatel, Kirsten; Evert, Matthias; Jung, Bettina; Bergler, Tobias; Boeger, Carsten A.; Spriewald, Bernd M.; Banas, Bernhard (Transplantation, 2018)
BACKGROUND: HLA-specific antibodies detected by solid phase assays are increasingly used to define unacceptable HLA antigen mismatches (UAM) prior to renal transplantation. The accuracy of this approach is unclear. METHODS: Day of transplant sera from 211 CDC-crossmatch-negative patients were retrospectively analyzed for donor-specific anti-HLA antibodies (DSA) using Luminex technology. HLA were defined as UAM if DSA had mean fluorescence intensity above (I) 3000 (patients retransplanted and those with DSA against HLA class I and II) or 5000 (all other patients), (II) 5000 for HLA A, B and DR and 10,000 for HLA DQ or (III) 10,000 (all HLA). We then studied the accuracy of these algorithms to identify patients with antibody-mediated rejection (AMR) and graft loss. UAM were also determined in 256 transplant candidates and virtual panel-reactive antibody (vPRA) levels calculated. RESULTS: At transplantation, 67/211 patients had DSA. Of these, 31 (algorithm I), 24 (II) and 17 (III) had UAM. 9 (I and II) and 8 (III) of 11 early AMR episodes and 7 (I), 6 (II) and 5 (III) of 9 graft losses occurred in UAM-positive patients during 4.9 years of follow-up. Algorithms (I) and (II) identified patients with persistently lower GFR even in the absence of overt AMR. 23-33% of waiting list patients had UAM with median vPRA of 69.2-79.1%. CONCLUSIONS: Algorithms (I) and (II) had comparable efficacy but were superior to (III) in identifying at-risk patients at an acceptable false positive rate. However, Luminex-defined UAM significantly restrict the donor pool of affected patients, which might prolong waiting time.
EVALuna2:34169

An easily expandable multi-drug LC-MS assay for the simultaneous quantification of 57 oral antitumor drugs in human plasma - Kehl, Niklas; Schlichtig, Katja; Dürr, Pauline; Bellut, Laura; Dörje, Frank; Fietkau, Rainer; Pavel, Marianne Ellen; Mackensen, Andreas; Wullich, Bernd; Maas, Renke; Fromm, Martin; Geßner, Arne; et al. (Cancers, 2021)
Oral anticancer drugs have led to significant improvements in the treatment of multiple tumor entities. However, in patients undergoing oral antitumor therapy, plasma concentrations are highly variable, resulting in risks of reduced therapeutic effects or an increase in side effects. One important tool to reduce this variability is therapeutic drug monitoring. In this work we describe a method to simultaneously quantify the plasma concentrations of 57 oral antitumor agents. Quantification of these drugs was achieved using liquid chromatography coupled to an Orbitrap mass spectrometer. The method was fully validated according to the FDA guidelines and constitutes a simple and robust way for exposure monitoring of a wide variety of oral anticancer drugs. Applicability to clinical routine was demonstrated by the analysis of 71 plasma samples taken from 39 patients. In summary, this new multi-drug method allows simultaneous quantification of 57 oral antitumor drugs, which can be applied to exposure monitoring in clinical studies, taking into account the broad variety of oral antitumor drugs prescribed in clinical routine.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Exposure measurement; Kinase inhibitors; Liquid chromatography mass spectrometry; Oral antitumor drug; Orbitrap mass spectrometer

A New Diagnostic Approach to HLA Testing in Kidney Transplant Patients Using Renal Epithelial Cells - Herrmann, Markus; Bach, Christian; Knaup, Karl; Schiffer, Mario; Spriewald, B.; Wiesener, M. S. (AMERICAN JOURNAL OF TRANSPLANTATION, 2020)
CRIS-Team WoS Importer:2020-10-16

A NEW DIAGNOSTIC APPROACH TO HLA TESTING IN KIDNEY TRANSPLANT RECIPIENTS USING CULTURED URINE DERIVED TUBULAR CELLS - Spriewald, Bernd M.; Herrmann, Markus; Bach, Christian; Knaup, Karl; Krumbiegel, Mandy; Reis, André; Schiffer, Mario; Wiesener, Michael (HLA, 2020)
CRIS-Team WoS Importer:2020-03-24

Angioedema in Stroke Patients With Thrombolysis - Fröhlich, Katharina; Macha, Kosmas; Gerner, Stefan; Bobinger, Tobias; Schmidt, Manuel; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Seifert, Frank; Kallmünzer, Bernd; Winder, Klemens (Stroke, 2019)
Background and Purpose- Oral angioedema (OA) is a rare but life-threatening complication in patients with ischemic stroke receiving intravenous thrombolysis with r-tPA (recombinant tissue-type plasminogen activator). This study intended to determine associations between thrombolysis-related OA and ischemic stroke lesion sites using a voxel-wise lesion analysis. Methods- Prospective registry data were used to identify ischemic stroke patients with thrombolysis-related OA between 2002 and 2018. For the study registry, ethics approval was obtained by the Ethics Committee of the Friedrich-Alexander Universität (FAU) Erlangen-Nürnberg (clinical registry registration: 377_17Bc). Ischemic stroke patients with thrombolysis treatment but without OA admitted in the years 2011 and 2012 comprised the control group. Ischemic lesions were manually outlined on magnetic resonance imaging (1.5T or 3T) or computed tomographic scans and transformed into stereotaxic space. We determined the lesion overlap and compared the absence or presence of OA voxel-wise between patients with and without lesions in a given voxel using the Liebermeister test. Stroke severity was rated using the National Institutes of Health Stroke Scale score, and blood pressure, heart rate, blood glucose levels, and body temperature were determined on admission. Results- Fifteen ischemic stroke patients with thrombolysis-related OA were identified. The voxel-wise analysis yielded associations between OA and ischemic lesions in the insulo-opercular region with a right hemispheric dominance. Mean blood pressure was significantly lower in patients with OA than in controls. Age, National Institutes of Health Stroke Scale scores, infarct volumes, heart rate, and blood glucose levels did not differ between patients with and without OA. Conclusions- The voxel-wise analysis linked thrombolysis-related OA to right insulo-opercular lesions. The lower blood pressure in patients with thrombolysis-related OA may reflect bradykinin effects causing vasodilatation and increasing vascular permeability.
CRIS-Team Scopus Importer:2019-07-19
Keywords: angioedema; autonomic nervous system; brain ischemia; neuroimaging; stroke; tissue-type plasminogen activator

An IL-1β-driven neutrophil–stromal cell axis fosters a BAFF-rich protumor microenvironment in individuals with multiple myeloma - de Jong, Madelon M.E.; Fokkema, Cathelijne; Papazian, Natalie; Czeti, Ágnes; Appelman, Marjolein K.; Vermeulen, Michael; van Heusden, Teddie; Hoogenboezem, Remco M.; van Beek, Gregory; Tahri, Sabrin; Sanders, Mathijs A.; van de Woestijne, Pieter C.; et al. (Nature Immunology, 2024)
Human bone marrow permanently harbors high numbers of neutrophils, and a tumor-supportive bias of these cells could significantly impact bone marrow-confined malignancies. In individuals with multiple myeloma, the bone marrow is characterized by inflammatory stromal cells with the potential to influence neutrophils. We investigated myeloma-associated alterations in human marrow neutrophils and the impact of stromal inflammation on neutrophil function. Mature neutrophils in myeloma marrow are activated and tumor supportive and transcribe increased levels of IL1B and myeloma cell survival factor TNFSF13B (BAFF). Interactions with inflammatory stromal cells induce neutrophil activation, including BAFF secretion, in a STAT3-dependent manner, and once activated, neutrophils gain the ability to reciprocally induce stromal activation. After first-line myeloid-depleting antimyeloma treatment, human bone marrow retains residual stromal inflammation, and newly formed neutrophils are reactivated. Combined, we identify a neutrophil–stromal cell feed-forward loop driving tumor-supportive inflammation that persists after treatment and warrants novel strategies to target both stromal and immune microenvironments in multiple myeloma.
CRIS-Team Scopus Importer:2024-04-19

A noninvasive diagnostic approach to retrospective donor HLA typing in kidney transplant patients using urine - Bach, Christian; Knaup, Karl; Herrmann, Markus; Krumbiegel, Mandy; Pfister, Frederick; Büttner-Herold, Maike; Steffen, Martin; Zecher, Daniel; Lopau, Kai; Schneider, Karen; Dieterle, Anne; Amann, Kerstin Ute; et al. (Transplant International, 2021)
Antibody-mediated rejection (AMR) is a major obstacle to long-term kidney transplantation. AMR is mostly caused by donor specific HLA antibodies, which can arise before or any time after transplantation. Incomplete donor HLA typing and unavailability of donor DNA regularly preclude the assessment of donor-specificity of circulating anti-HLA antibodies. In our centre, this problem arises in approximately 20% of all post-transplant HLA-antibody assessments. We demonstrate that this diagnostic challenge can be resolved by establishing donor renal tubular cell cultures from recipient´s urine as a source of high-quality donor DNA. DNA was then verified for genetic origin and purity by fluorescence in situ hybridization and short tandem repeat analysis. Two representative cases highlight the diagnostic value of this approach which is corroborated by analysis of ten additional patients. The latter were randomly sampled from routine clinical care patients with available donor DNA as controls. In all 12 cases, we were able to perform full HLA typing of the respective donors confirmed by cross-comparison to results from the stored 10 donor DNAs. We propose that this noninvasive diagnostic approach for HLA typing in kidney transplant patients is valuable to determine donor specificity of HLA antibodies, which is important in clinical assessment of suspected AMR.
CRIS-Team Scopus Importer:2021-06-25
Keywords: antibody-mediated rejection; HLA typing; HLA-antibody post-transplantation; rejection

A novel immunoregulatory function of beta-2-microglobulin as a promoter of myeloid derived suppressor cell induction - Bruns, Heiko; Jitschin, Simon; Gamali, Sara; Saul, Domenica; Böttcher, Martin; Mackensen, Andreas; Jitschin, Regina; Mougiakakos, Dimitrios (Leukemia, 2019)
EVALuna2:35231

A novel interaction between hydrogen peroxide metabolism and LDL-uptake controls immunergulatory properties in human dendritic cells - Potential implications for tumor immune escape - Menzner, Ann-Katrin; Rottmar, Tanja; Bosch, Jacobus J.; Mougiakakos, Dimitrios; Mackensen, Andreas; Resheq, Yazid; Völkl, Simon (CANCER RESEARCH, 2020)
CRIS-Team WoS Importer:2021-03-05

A Novel Model of Metastatic Conjunctival Melanoma in Immune-Competent Mice - Schlereth, Simona L.; Iden, Sandra; Mescher, Melina; Ksander, Bruce R.; Bosch, Jacobus J.; Cursiefen, Claus; Heindl, Ludwig M. (Investigative Ophthalmology & Visual Science, 2015)
Conjunctival melanoma (CM) is an ocular surface tumor that can lead to fatal metastases. Patients developing, tumor-associated lymphangiogenesis have a significantly increased risk of metastatic disease, because tumor spread primarily occurs via lymphatic vessels to the draining lymph node. Here, we describe a novel immune-competent mouse model of CM that displays tumor-associated lymphangiogenesis with development of metastatic tumors.C57BL/6N mice received C57BL/6N-derived dermal melanoma cells (hepatocyte growth factor [HGF] cyclin dependent kinase-4 [Cdk4]+) or B16F10 via subconjunctival injection. A clinical score quantified primary tumor growth and metastases were identified by macroscopic examination of the draining lymph nodes, lung, and spleen. Confirmation of tumors and metastases was achieved by immunohistochemical staining for markers of pigmented cells (tyrosinase related protein-2 [TRP2]) and S-100, and of cell proliferation (Ki67). The intra- and peritumoral CD31+ blood and lymphatic vessel endothelium hyaluronan receptor-1 (LYVE-1)+ lymphatic vessels were quantified immunohistochemically.All mice rapidly developed aggressive TRP2+, S100+, and Ki67+ CM. Metastatic tumors were found in the lymph node (9%) and lung (6%) of HGF-Cdk4(R24C)-treated mice and in the spleen (8%) and lung (17%) of B16F10-treated mice. The amount of peri- and intratumoral blood vessels was significantly increased compared with lymphatic vessels.This CM model in immune-competent animals offers new possibilities to study the pathobiology of tumor growth, invasion, and mechanisms of metastatic tumor spread, and provides a robust model to explore new immune-based and antilymphangiogenic treatment modalities of this malignancy.
EVALuna2:25719

ANTAGONISM OF PLATELET-DERIVED SEROTONIN (5-HT) MODULATES MACROPHAGE-MEDIATED TRANSPLANT VASCULOPATHY AFTER AORTIC TRANSPLANTATION BUT NOT LARGE AIRWAY REMODELING IN MURINE TRACHEAL ALLOGRAFTS - Bujnoch, Daniel; Gocht, A.; Distler, Jörg; Spriewald, B.; Ramsperger-Gleixner, Martina; Weyand, Michael; Ensminger, S.; Heim, Christian (2018)
EVALuna2:34953

Anti-CD19 CAR T cell therapy for refractory systemic lupus erythematosus - Mackensen, Andreas; Müller, Fabian; Mougiakakos, Dimitrios; Böltz, Sebastian; Wilhelm, Artur; Aigner, Michael; Völkl, Simon; Simon, David; Kleyer, Arnd; Munoz, Luis Enrique; Kretschmann, Sascha; Kharboutli, Soraya; et al. (Nature Medicine, 2022)
Systemic lupus erythematosus (SLE) is a life-threatening autoimmune disease characterized by adaptive immune system activation, formation of double-stranded DNA autoantibodies and organ inflammation. Five patients with SLE (four women and one man) with a median (range) age of 22 (6) years, median (range) disease duration of 4 (8) years and active disease (median (range) SLE disease activity index Systemic Lupus Erythematosus Disease Activity Index: 16 (8)) refractory to several immunosuppressive drug treatments were enrolled in a compassionate-use chimeric antigen receptor (CAR) T cell program. Autologous T cells from patients with SLE were transduced with a lentiviral anti-CD19 CAR vector, expanded and reinfused at a dose of 1 × 106 CAR T cells per kg body weight into the patients after lymphodepletion with fludarabine and cyclophosphamide. CAR T cells expanded in vivo, led to deep depletion of B cells, improvement of clinical symptoms and normalization of laboratory parameters including seroconversion of anti-double-stranded DNA antibodies. Remission of SLE according to DORIS criteria was achieved in all five patients after 3 months and the median (range) Systemic Lupus Erythematosus Disease Activity Index score after 3 months was 0 (2). Drug-free remission was maintained during longer follow-up (median (range) of 8 (12) months after CAR T cell administration) and even after the reappearance of B cells, which was observed after a mean (±s.d.) of 110 ± 32 d after CAR T cell treatment. Reappearing B cells were naïve and showed non-class-switched B cell receptors. CAR T cell treatment was well tolerated with only mild cytokine-release syndrome. These data suggest that CD19 CAR T cell transfer is feasible, tolerable and highly effective in SLE.
CRIS-Team Scopus Importer:2022-09-30

Anti-HLA alloantibodies of the IgA isotype in re-transplant candidates part II: Correlation with graft survival - Bach, Christian; Heinemann, F. M.; Horn, P. A.; Ziemann, M.; Lachmann, N.; Muehlbacher, A.; Dick, A.; Ender, A.; Thammanichanond, D.; Schaub, S.; Honger, G.; Fischer, G. F.; et al. (International Journal of Immunogenetics, 2018)
We reported previously on the widespread occurrence of anti-HLA alloantibodies of the IgA isotype (anti-HLA IgA) in the sera of solid-organ re-transplantation (re-tx) candidates (Arnold et al., ). Specifically focussing on kidney re-tx patients, we now extended our earlier findings by examining the impact of the presence and donor specificity of anti-HLA IgA on graft survival. We observed frequent concurrence of anti-HLA IgA and anti-HLA IgG in 27% of our multicenter collective of 694 kidney re-tx patients. This subgroup displayed significantly reduced graft survival as evidenced by the median time to first dialysis after transplantation (TTD 77 months) compared to patients carrying either anti-HLA IgG or IgA (TTD 102 and 94 months, respectively). In addition, donor specificity of anti-HLA IgA had a significant negative impact on graft survival (TTD 74 months) in our study. Taken together, our data strongly indicate that presence of anti-HLA IgA, in particular in conjunction with anti-HLA-IgG, in sera of kidney re-tx patients is associated with negative transplantation outcome.
EVALuna2:34168

Anti-TNF immunotherapy reduces CD8+ T cell-mediated antimicrobial activity against Mycobacterium tuberculosis in humans. - Bruns, Heiko; Bruns, Heiko; Meinken, Christoph; Schauenberg, Philipp; Haerter, Georg; Kern, Peter; Modlin, Robert L.; Antoni, Christian; Stenger, Steffen (Journal of Clinical Investigation, 2009)
The incidence of tuberculosis is increased during treatment of autoimmune diseases with anti-TNF antibodies. This is a significant clinical complication, but also provides a unique model to study immune mechanisms in human tuberculosis. Given the key role for cell-mediated immunity in host defense against Mycobacterium tuberculosis, we hypothesized that anti-TNF treatment impairs T cell-directed antimicrobial activity. Anti-TNF therapy reduced the expression in lymphocytes of perforin and granulysin, 2 components of the T cell-mediated antimicrobial response to intracellular pathogens. Specifically, M. tuberculosis-reactive CD8+CCR7-CD45RA+ effector memory T cells (TEMRA cells) expressed the highest levels of granulysin, lysed M. tuberculosis, and infected macrophages and mediated an antimicrobial activity against intracellular M. tuberculosis. Furthermore, TEMRA cells expressed cell surface TNF and bound the anti-TNF therapeutic infliximab in vitro, making them susceptible to complement-mediated lysis. Immune therapy with anti-TNF was associated with reduced numbers of CD8+ TEMRA cells and decreased antimicrobial activity against M. tuberculosis, which could be rescued by the addition of CD8+ TEMRA cells. These results suggest that anti-TNF therapy triggers a reduction of CD8+ TEMRA cells with antimicrobial activity against M. tuberculosis, providing insight into the mechanism whereby key effector T cell subsets contribute to host defense against tuberculosis.

A Phase I Open Label Dose Escalation Study of MB-CART19.1 in Relapsed and Refractory CD19+B Cell Malignancies, Interim Preliminary Results in Pediatric ALL, Adult ALL Including CLL Cohorts - Mackensen, Andreas; Hanssens, Linda; Stelljes, Matthias; Bethge, Wolfgang A.; Feuchtinger, Tobias; Kuenkele, Annette; Aigner, Michael; Yakushina, Alisa; Karitzky, Sandra; Holtkamp, Silke; Assenmacher, Mario; Jurk, Marion; et al. (BLOOD, 2021)
CRIS-Team WoS Importer:2022-09-09

A Practical Approach to Systemic Mastocytosis Complications in Cardiac Surgery: A Case Report and Systematic Review of the Literature - Suleiman, Mathieu; Brueckl, Valeska; Fechner, Jörg; Kaemmerer, Ann-Sophie; Wilk, Florian; Weyand, Michael; Harig, Frank (Journal of Clinical Medicine, 2023)
(1) Background: Systemic mastocytosis is a rare, non-curable disease with potential life-threatening complications in patients receiving cardiac surgery. (2) Methods: This systematic review of the literature was prompted by the case of a life-threatening anaphylactic reaction during cardiac surgery related to systemic mastocytosis. The search of all types of studies, using several databases (Pubmed, Scopus and Web of Science), was conducted through September 2022 to identify the relevant studies. (3) Results: Twelve studies were included describing cases of patients undergoing cardiac surgery who were diagnosed with systemic mastocytosis. An adverse effect, namely anaphylaxis, has happened in three cases. Different strategies of premedication, intraoperative and postoperative management were used. In our case, the patient was admitted for elective biological aortic valve replacement due to severe aortic stenosis. Intraoperatively, the patient developed an anaphylactic shock during the administration of protamine after separation from the cardiopulmonary bypass. This anaphylaxis reaction was a complication of the pre-existing systemic mastocytosis and could be successfully managed by the administration of epinephrine, antihistamines and corticosteroids. (4) Conclusions: This systematic literature search and case report highlight the importance of careful preoperative planning, as well as coordination between cardiac surgeons, anesthesiologists and hemato-oncological specialists, in patients with rare but complication-prone diseases such as systemic mastocytosis.
CRIS-Team WoS Importer:2023-03-10

A Protocol for In Vitro High-Throughput Chemical Susceptibility Screening in Differentiating NT2 Stem Cells - Menzner, Ann-Katrin; Gilbert, Daniel (Methods in Molecular Biology, 2017)
The incidence of neurological diseases including learning and developmental disorders has increased in recent years. Concurrently, the number and volume of worldwide registered and traded chemicals have also increased. There is a broad consensus that the developing brain is particularly sensitive to damage by chemicals and that evaluation of chemicals for developmental toxicity or neurotoxicity is critical to human health. Human pluripotent embryonal carcinoma (NTERA-2 or NT2) cells are increasingly considered as a suitable model for in vitro developmental toxicity and neurotoxicity (DT/DNT) studies as they undergo neuronal differentiation upon stimulation with retinoic acid (RA) and allow toxicity assessment at different stages of maturation. Here we describe a protocol for cell fitness screening in differentiating NT2 cells based on the analysis of intracellular ATP levels allowing for the identification of chemicals which are potentially harmful to the developing brain. The described method is suitable to be adapted to low-, medium-, and high-throughput screening and allows multiplexing with other cell fitness indicators. While the presented protocol focuses on cell fitness screening in human pluripotent stem cells it may also be applied to other in vitro models.
Keywords: Cell fitness; Cell viability; Cell-based assays; CellTiter-Glo Luminescent Cell Viability Assay; Chemical susceptibility; DNT; Developmental toxicity and neurotoxicity; Differentiation; Drug discovery; Drug screening; High-throughput screening; In vitro toxicity screening; Neurotoxicity; Target validation

A randomised study of the impact of the SGLT2 inhibitor dapagliflozin on microvascular and macrovascular circulation - Ott, Christian; Jumar, Agnes; Striepe, Kristina; Friedrich, Stefanie; Karg, Margarete; Bramlage, Peter; Schmieder, Roland (Cardiovascular Diabetology, 2017)
The sodium-glucose cotransporter 2 inhibitor, dapagliflozin, has been shown to improve diabetic control and reduce blood pressure in patients with type 2 diabetes mellitus. Its effects on micro- and macrovascular structure and function have not yet been reported.This was a prospective, single-centre, placebo-controlled, double-blind, randomised crossover phase IIIb study conducted between March 2014 and February 2015. After a 4-week run-in/washout phase, patients (N = 59) received 6 weeks of either dapagliflozin 10 mg or placebo once daily. They then underwent a 1-week washout before crossing over to the other treatment. Changes in retinal capillary flow (RCF) and arteriole remodelling were evaluated using scanning laser Doppler flowmetry, while micro- and macrovascular parameters in the systemic circulation were assessed using pulse wave analysis.Six weeks of dapagliflozin treatment resulted in improvements in diabetes control, including blood glucose and insulin resistance, and reduced office and 24-h ambulatory blood pressure values. RCF decreased from 324 AU at baseline to 308 AU after treatment with dapagliflozin (p = 0.028), while there was little difference after the placebo (318 AU; p = 0.334). Furthermore, the arteriole remodelling that was seen after the placebo phase was not evident after the dapagliflozin phase. Central systolic and diastolic blood pressure values were significantly lower after 6 weeks of dapagliflozin, by 3.0 and 2.2 mmHg, respectively (p = 0.035 and 0.020, respectively vs. baseline).Six weeks of dapagliflozin treatment resulted in numerous beneficial effects. In addition to achieving superior diabetes control and blood pressure, parameters associated with the early stages of vascular remodelling were also improved. Trial registration http://www.clinicaltrials.gov (NCT02383238).
EVALuna2:3943

Arming immune cells for battle: A brief journey through the advancements of t and nk cell immunotherapy - Wendel, Philipp; Reindl, Lisa Marie; Bexte, Tobias; Künnemeyer, Leander; Särchen, Vinzenz; Albinger, Nawid; Mackensen, Andreas; Rettinger, Eva; Bopp, Tobias; Ullrich, Evelyn (Cancers, 2021)
The promising development of adoptive immunotherapy over the last four decades has revealed numerous therapeutic approaches in which dedicated immune cells are modified and ad-ministered to eliminate malignant cells. Starting in the early 1980s, lymphokine activated killer (LAK) cells were the first ex vivo generated NK cell‐enriched products utilized for adoptive immu-notherapy. Over the past decades, various immunotherapies have been developed, including cyto-kine‐induced killer (CIK) cells, as a peripheral blood mononuclear cells (PBMCs)‐based therapeutic product, the adoptive transfer of specific T and NK cell products, and the NK cell line NK‐92. In addition to allogeneic NK cells, NK‐92 cell products represent a possible “off‐the‐shelf” therapeutic concept. Recent approaches have successfully enhanced the specificity and cytotoxicity of T, NK, CIK or NK‐92 cells towards tumor‐specific or associated target antigens generated by genetic engineering of the immune cells, e.g., to express a chimeric antigen receptor (CAR). Here, we will look into the history and recent developments of T and NK cell‐based immunotherapy.
CRIS-Team Scopus Importer:2021-04-02
Keywords: CAR‐NK cell; CAR‐T cell; Cell therapy; CIK cell; Immune therapy; NK cell; NK‐92; T cell

A round robin study for Laser Beam Melting in Metal Powder Bed: Comparing mechanical characteristics with system technology variation - Ahuja, B.; Schaub, Adam; Junker, Daniel; Karg, M.; Tenner, F.; Plettke, Raoul; Merklein, Marion; Schmidt, M. (Proc. 15th Annual Conference of RAPDASA 2014, 2014)
LFT Import::2019-08-05 (2095)

Asparaginase activities during intensified treatment with pegylated E. coli asparaginase in adults with newly-diagnosed acute lymphoblastic leukemia - Lanvers-Kaminsky, Claudia; Niemann, Andreas; Eveslage, Maria; Beck, Joachim; Köhnke, Thomas; Martin, Sonja; de Wit, Maike; Spriewald, Bernd; Hauspurg, Holger; Hoelzer, Dieter; Boos, Joachim; Gökbuget, Nicola (Leukemia & Lymphoma, 2019)
The GMALL07/2003 protocol introduced pegylated E. coli asparaginase (PEG-ASNase) frontline for adults with acute lymphoblastic leukemia (ALL). PEG-ASNase (500 U/m2, 1000 U/m2, or 2000 U/m2) was given once in induction and as part of three HD-MTX/PEG-ASNase cycles with two PEG-ASNase doses every other week in consolidation. PEG-ASNase activities were monitored in 1363 serum samples from 304 ALL patients. The overall rate of silent inactivation was low (5%) and did not differ between induction and consolidation. The successful targeting of PEG-ASNase activities ≥100 U/L depended on protocol and dose. Overall PEG-ASNase activities were higher during consolidation compared to induction. To target PEG-ASNase activities ≥100 U/L for 14 day with a single dose in induction, 2000 U/m2 was more preferable than 1000 U/m2 or 500 U/m2. During consolidation with two administrations every other week, 1000 U/m2 and 2000 U/m2 were similarly effective in sustaining PEG-ASNase ≥100 U/L activities over 14 days.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Adult ALL; asparaginase activity; drug monitoring; pegylated E. coli asparaginase

Aspergillus fumigatus Spores Are Not Able to Penetrate Silicone Breast Implant Shells - Horch, Raymund E.; Krappmann, Sven; Duemig, Michaela; Schmitz, Marweh; Kengelbach-Weigand, Annika; Schubert, Dirk W.; Kremser, Thomas; Bogdan, Christian; Ludolph, Ingo (Annals of Plastic Surgery, 2019)
Bacterial contamination is hypothesized to be one reason for the development of capsular contracture after alloplastic breast reconstruction using silicone breast implants. The role of fungal colonization or infection in this context as well as the question if microorganisms can penetrate the shell of silicone breast implants remains an unresolved question to date. Therefore, the aim of this study was to assess whether fungal spores are able to penetrate the shell of silicone implants. In an experimental in vitro setup with different arrangements of growth compartments, silicone chambers were placed in culture dishes filled with Aspergillus minimal medium or liquid culture medium. Inoculation was performed with conidia of Aspergillus fumigatus and incubated for seven days. On a daily basis, plates were inspected for conidial germination and hyphal growth. In none of the different experimental settings nutrients or hyphae of Aspergillus fumigatus were able to penetrate the silicone material.ConclusionsFungal spores and hyphae do not permeate through an intact silicone shell used in breast implants; thus, the silicone material serves as an impenetrable barrie
Keywords: Aspergillus fumigatus; penetration; silicone implants; breast

Aspergillus specific nested PCR from the site of infection is superior to testing concurrent blood samples in immunocompromised patients with suspected invasive aspergillosis - Boch, Tobias; Spiess, Birgit; Heinz, Werner; Cornely, Oliver A.; Schwerdtfeger, Rainer; Hahn, Joachim; Krause, Stefan; Duerken, Matthias; Bertz, Hartmut; Reuter, Stefan; Kiehl, Michael; Claus, Bernd; et al. (Mycoses, 2019)
Invasive aspergillosis (IA) is a severe complication in immunocompromised patients. Early diagnosis is crucial to decrease its high mortality, yet the diagnostic gold standard (histopathology and culture) is time-consuming and cannot offer early confirmation of IA. Detection of IA by polymerase chain reaction (PCR) shows promising potential. Various studies have analysed its diagnostic performance in different clinical settings, especially addressing optimal specimen selection. However, direct comparison of different types of specimens in individual patients though essential, is rarely reported. We systematically assessed the diagnostic performance of an Aspergillus-specific nested PCR by investigating specimens from the site of infection and comparing it with concurrent blood samples in individual patients (pts) with IA. In a retrospective multicenter analysis PCR was performed on clinical specimens (n = 138) of immunocompromised high-risk pts (n = 133) from the site of infection together with concurrent blood samples. 38 pts were classified as proven/probable, 67 as possible and 28 as no IA according to 2008 European Organization for Research and Treatment of Cancer/Mycoses Study Group consensus definitions. A considerably superior performance of PCR from the site of infection was observed particularly in pts during antifungal prophylaxis (AFP)/antifungal therapy (AFT). Besides a specificity of 85%, sensitivity varied markedly in BAL (64%), CSF (100%), tissue samples (67%) as opposed to concurrent blood samples (8%). Our results further emphasise the need for investigating clinical samples from the site of infection in case of suspected IA to further establish or rule out the diagnosis.
CRIS-Team Scopus Importer:2019-10-29
Keywords: antifungal; aspergillosis; Aspergillus; BAL; blood; cerebrospinal fluid; comparison; PCR

Assessment of educational and social status of survivors of childhood cancer: Data of a single center late effects clinic - Hahn, B.; Schuster, Sonja; Metzler, Markus; Mackensen, Andreas; Meidenbauer, Norbert (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Assessment of imatinib as first-line treatment of chronic myeloid leukemia: 10-year survival results of the randomized CML study IV and impact of non-CML determinants - Hehlmann, R.; Lauseker, M.; Saussele, S.; Pfirrmann, M.; Krause, Stefan; Kolb, H. J.; Neubauer, A.; Hossfeld, D. K.; Nerl, C.; Gratwohl, A.; Baerlocher, G. M.; Heim, D.; et al. (Leukemia, 2017)
Chronic myeloid leukemia (CML)-study IV was designed to explore whether treatment with imatinib (IM) at 400 mg/day (n=400) could be optimized by doubling the dose (n=420), adding interferon (IFN) (n=430) or cytarabine (n=158) or using IM after IFN-failure (n=128). From July 2002 to March 2012, 1551 newly diagnosed patients in chronic phase were randomized into a 5-arm study. The study was powered to detect a survival difference of 5% at 5 years. After a median observation time of 9.5 years, 10-year overall survival was 82%, 10-year progression-free survival was 80% and 10-year relative survival was 92%. Survival between IM400 mg and any experimental arm was not different. In a multivariate analysis, risk group, major-route chromosomal aberrations, comorbidities, smoking and treatment center (academic vs other) influenced survival significantly, but not any form of treatment optimization. Patients reaching the molecular response milestones at 3, 6 and 12 months had a significant survival advantage. For responders, monotherapy with IM400 mg provides a close to normal life expectancy independent of the time to response. Survival is more determined by patients' and disease factors than by initial treatment selection. Although improvements are also needed for refractory disease, more life-time can currently be gained by carefully addressing non-CML determinants of survival.
EVALuna2:25772

Assessment of systemic and gastrointestinal tissue damage biomarkers for GVHD risk stratification. - Etra, Aaron; Gergoudis, Stephanie; Morales, George; Spyrou, Nikolaos; Shah, Jay; Kowalyk, Steven; Ayuk, Francis; Baez, Janna; Chanswangphuwana, Chantiya; Chen, Yi Bin; Choe, Hannah; DeFilipp, Zachariah; et al. (Blood Advances, 2022)
We used a rigorous PRoBE (prospective-specimen collection, retrospective-blinded-evaluation) study design to compare the ability of biomarkers of systemic inflammation and biomarkers of gastrointestinal (GI) tissue damage to predict response to corticosteroid treatment, the incidence of clinically severe disease, 6-month nonrelapse mortality (NRM), and overall survival in patients with acute graft-versus-host disease (GVHD). We prospectively collected serum samples of newly diagnosed GVHD patients (n = 730) from 19 centers, divided them into training (n = 352) and validation (n = 378) cohorts, and measured TNFR1, TIM3, IL6, ST2, and REG3α via enzyme-linked immunosorbent assay. Performances of the 4 strongest algorithms from the training cohort (TNFR1 + TIM3, TNFR1 + ST2, TNFR1 + REG3α, and ST2 + REG3α) were evaluated in the validation cohort. The algorithm that included only biomarkers of systemic inflammation (TNFR1 + TIM3) had a significantly smaller area under the curve (AUC; 0.57) than the AUCs of algorithms that contained ≥1 GI damage biomarker (TNFR1 + ST2, 0.70; TNFR1 + REG3α, 0.73; ST2 + REG3α, 0.79; all P < .001). All 4 algorithms were able to predict short-term outcomes such as response to systemic corticosteroids and severe GVHD, but the inclusion of a GI damage biomarker was needed to predict long-term outcomes such as 6-month NRM and survival. The algorithm that included 2 GI damage biomarkers was the most accurate of the 4 algorithms for all endpoints.
EVALuna2:505341

Association of a coding polymorphism in Fc gamma receptor 2A and graft survival in re-transplant candidates - Fuernrohr, Barbara G.; Weiss, Katrin M.; Harre, Ulrike; Wiesener, Michael S.; Spriewald, Bernd M.; Arnold, Martin (Human Immunology, 2015)
The family of Fc gamma receptors (Fc?Rs) is involved in mediating immunological effector functions. Fc?Rs are differentially expressed on immune cells and can act either activating or inhibitory, with Fc?R2A belonging to the first group. The polymorphism H131R (rs1801274) in FCGR2A has been associated with acute rejection and can shift the overall balance between activating and inhibitory Fc?Rs. Anti-HLA allo-antibodies in transplant recipients have been identified as risk factor for organ survival after transplantation. In this study we genotyped FCGR2A H131R in 200 patients who had undergone kidney transplantation and experienced loss of graft function. FCGR2A polymorphism was related to graft survival and anti-HLA antibodies. Graft survival was calculated as the time interval between transplantation and return to chronic dialysis after transplantation. The gene frequency of FCGR2A R/R131 was found significantly more often in patients with earlier (?60months) compared to patients with later (>60months) graft failure. Overall patients homozygous for R/R131 had a significantly shorter graft survival, compared to H/H131 or H/R131 which is even more pronounced, when anti-HLA antibodies were present. These data suggest, that FCGR2A polymorphisms constitute a risk factor for graft loss following kidney transplantation and that this effect is related to anti-HLA antibodie
EVALuna2:3812

Associations of neutrophil-to-lymphocyte ratio with mortality in spontaneous intracerebral hemorrhage - Giede-Jeppe, A.; Bobinger, Tobias; Gerner, Stefan; Sembill, Jochen; Lücking, Hannes; Kuramatsu, J. B.; Huttner, Hagen; Hölter, Philip (2017)
EVALuna2:22568

A surrogate cell-based SARS-CoV-2 spike blocking assay - Schuh, Wolfgang; Baus, Lena; Steinmetz, Tobit; Schulz, Sebastian; Weckwerth, Leonie; Roth, Edith; Hauke, Manuela; Krause, Stefan; Morhart, Patrick; Rauh, Manfred; Hoffmann, Markus; Vesper, Niklas; et al. (European Journal of Immunology, 2021)
To monitor infection by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and successful vaccination against coronavirus disease 2019 (COVID-19), the kinetics of neutralizing or blocking anti-SARS-CoV-2 antibody titers need to be assessed. Here, we report the development of a quick and inexpensive surrogate SARS-CoV-2 blocking assay (SUBA) using immobilized recombinant human angiotensin-converting enzyme 2 (hACE2) and human cells expressing the native form of surface SARS-CoV-2 spike protein. Spike protein-expressing cells bound to hACE2 in the absence or presence of blocking antibodies were quantified by measuring the optical density of cell-associated crystal violet in a spectrophotometer. The advantages are that SUBA is a fast and inexpensive assay, which does not require biosafety level 2- or 3-approved laboratories. Most importantly, SUBA detects blocking antibodies against the native trimeric cell-bound SARS-CoV-2 spike protein and can be rapidly adjusted to quickly pre-screen already approved therapeutic antibodies or sera from vaccinated individuals for their ACE2 blocking activities against any emerging SARS-CoV-2 variants.
CRIS-Team Scopus Importer:2021-10-08
Keywords: COVID-19; hACE2; SARS-CoV-2; Spike protein; Surrogate blocking assay

ASXL1 mutations predict inferior molecular response to nilotinib treatment in chronic myeloid leukemia - Schoenfeld, Lioba; Rinke, Jenny; Hinze, Anna; Nagel, Saskia N.; Schaefer, Vivien; Schenk, Thomas; Fabisch, Christian; Bruemmendorf, Tim H.; Burchert, Andreas; Le Coutre, Philipp; Krause, Stefan; Saussele, Susanne; et al. (Leukemia, 2022)
Gene mutations independent of BCR::ABL1 have been identified in newly diagnosed patients with chronic myeloid leukemia (CML) in chronic phase, whereby mutations in epigenetic modifier genes were most common. These findings prompted the systematic analysis of prevalence, dynamics, and prognostic significance of such mutations, in a clinically well-characterized patient population of 222 CML patients from the TIGER study (CML-V) by targeted next-generation sequencing covering 54 myeloid leukemia-associated genes. In total, 53/222 CML patients (24%) carried 60 mutations at diagnosis with ASXL1 being most commonly affected (n = 20). To study mutation dynamics, longitudinal deep sequencing analysis of serial samples was performed in 100 patients after 12, 24, and 36 months of therapy. Typical patterns of clonal evolution included eradication, persistence, and emergence of mutated clones. Patients carrying an ASXL1 mutation at diagnosis showed a less favorable molecular response to nilotinib treatment, as a major molecular response (MMR) was achieved less frequently at month 12, 18, and 24 compared to all other patients. Patients with ASXL1 mutations were also younger and more frequently found in the high risk category, suggesting a central role of clonal evolution associated with ASXL1 mutations in CML pathogenesis.
CRIS-Team WoS Importer:2022-08-12

ASXL1 Mutations Predict Inferior Molecular Response to Nilotinib Treatment in Newly Diagnosed Patients with Chronic Myeloid Leukemia in Chronic Phase - Ernst, Thomas; Schoenfeld, Lioba; Rinke, Jenny; Hinze, Anna; Nagel, Saskia N.; Schaefer, Vivien; Schenk, Thomas; Fabisch, Christian; Bruemmendorf, Tim H.; Burchert, Andreas; Le Coutre, Philipp; Krause, Stefan; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

ATF4 promotes angiogenesis and neuronal cell death and confers ferroptosis in a xCT-dependent manner - Chen, Daishi; Fan, Zheng; Rauh, Manfred; Buchfelder, Michael; Eyupoglu, I. Y.; Savaskan, Nicolai (Oncogene, 2017)
Activating transcription factor 4 (ATF4) is a critical mediator of metabolic and oxidative homeostasis and cell survival. ATF4 is elevated in response to diverse microenvironmental stresses, including starvation, ER stress damages and exposure to toxic factors. Here we show that ATF4 expression fosters the malignancy of primary brain tumors (WHO grade III and IV gliomas) and increases proliferation and tumor angiogenesis. Hence, ATF4 expression promotes cell migration and anchorage-independent cell growth, whereas siRNA-mediated knockdown of ATF4 attenuates these features of malignancy in human gliomas. Further experiments revealed that ATF4-dependent tumor promoting effects are mediated by transcriptional targeting the glutamate antiporter xCT/SCL7A11 (also known as system Xc-). Thus, xCT is elevated as a consequence of ATF4 activation. We further found evidence that ATF4-induced proliferation can be attenuated by pharmacological or genetic xCT inhibition and ferroptosis inducers such as sorafenib, erastin and GPx4 inhibitor RSL3. Further, fostered xCT expression promotes cell survival and growth in ATF4 knockdown cells. Moreover, increased xCT levels ameliorate sorafenib and erastin-induced ferroptosis. Conversely, ATF4 knockdown renders cells susceptible for erastin, sorafenib and RSL3-induced ferroptosis. We further identified that ATF4 promotes tumor-mediated neuronal cell death which can be alleviated by xCT inhibition. Moreover, elevated ATF4 expression in gliomas promotes tumor angiogenesis. Noteworthy, ATF4-induced angiogenesis could be diminished by ferroptosis inducers erastin and by GPx4 inhibitor RSL3. Our data provide proof-of-principle evidence that ATF4 fosters proliferation and induces a toxic microenvironmental niche. Furthermore, ATF4 increases tumor angiogenesis and shapes the vascular architecture in a xCT-dependent manner. Thus, inhibition of ATF4 is a valid target for diminishing tumor growth and vasculature via sensitizing tumor cells for ferroptosis.
EVALuna2:34242

Author Correction: Anti-CD19 CAR T cell therapy for refractory systemic lupus erythematosus. - Mackensen, Andreas; Müller, Fabian; Mougiakakos, Dimitrios; Böltz, Sebastian; Wilhelm, Artur; Aigner, Michael; Völkl, Simon; Simon, David; Kleyer, Arnd; Munoz, Luis Enrique; Kretschmann, Sascha; Kharboutli, Soraya; et al. (Nature Medicine, 2023)
EVALuna2:512812

Autocrine impact of VEGF-A on uveal melanoma cells - Koch, Konrad R.; Refaian, Nasrin; Hos, Deniz; Schlereth, Simona L.; Bosch, Jacobus J.; Cursiefen, Claus; Heindl, Ludwig M. (Investigative Ophthalmology & Visual Science, 2014)
Tumor-derived VEGF-A, apart from expediting sufficient vascularization, subsequent tumor growth, and metastatic spread, can act on malignant cells themselves provided that VEGF receptors 1 or 2 (VEGF-R1, -R2) are co-expressed. The study goal was to investigate whether such autocrine VEGF-A signaling exists in uveal melanoma (UM).Primary (MEL-270, OM-431) and metastatic (OMM-2.3, OMM-2.5) UM cell lines were analyzed for VEGF-A, VEGF-R1, and VEGF-R2 expression by RT-PCR, ELISA (VEGF-A protein), and immunocytochemistry (VEGF receptors). Proliferation of UM cells incubated with neutralizing anti-VEGF-A antibody bevacizumab (<= 2.5 mg/mL), or VEGF-A (<= 100 ng/mL) was assessed by bromodeoxyuridine (BrdU) ELISA. It was measured by real-time PCR, whether VEGF-A (100 ng/mL) modulated the expression ratio of VEGF-A itself and its antiangiogenic antagonist pigment epithelium-derived factor (PEDF).All UM cells expressed VEGF-A, VEGF-R1, VEGF-R2 mRNA, and protein. In each cell line, the proliferation was stimulated by VEGF-A or inhibited by blocking VEGF-A, or both: bevacizumab significantly decreased the proliferation in MEL-270 (P = 0.005), OMM-2.3 (P = 0.001), and OMM-2.5 (P = 0.011). Increased VEGF-A signaling significantly raised the proliferation in MEL-270, OM-431 (P < 0.001, respectively), and OMM-2.3 (P = 0.043) in a dose-dependent manner but did not significantly change the VEGF-A/PEDF mRNA expression ratio.Autocrine VEGF-A signaling seems to be present in UM, sustaining the proliferation of both primary and metastatic UM cells. Apparently, VEGF-A signaling in UM cells neither acts retroactively on VEGF-A expression, in the sense of a feedback loop, nor contributes to a pro-angiogenic shift of the VEGF-A/PEDF ratio.
EVALuna2:25683

Azacitidine in combination with intensive induction chemotherapy in older patients with acute myeloid leukemia: The AML-AZA trial of the study alliance leukemia - Mueller-Tidow, C.; Tschanter, P.; Roellig, C.; Thiede, Christian; Koschmieder, A.; Stelljes, M.; Koschmieder, S.; Dugas, M.; Gerss, Joachim; Butterfass-Bahloul, T.; Wagner, R.; Eveslage, Maria; et al. (Leukemia, 2016)
DNA methylation changes are a constant feature of acute myeloid leukemia. Hypomethylating drugs such as azacitidine are active in acute myeloid leukemia (AML) as monotherapy. Azacitidine monotherapy is not curative. The AML-AZA trial tested the hypothesis that DNA methyltransferase inhibitors such as azacitidine can improve chemotherapy outcome in AML. This randomized, controlled trial compared the efficacy of azacitidine applied before each cycle of intensive chemotherapy with chemotherapy alone in older patients with untreated AML. Event-free survival (EFS) was the primary end point. In total, 214 patients with a median age of 70 years were randomized to azacitidine/chemotherapy (arm-A) or chemotherapy (arm-B). More arm-A patients (39/105; 37%) than arm-B (25/109; 23%) showed adverse cytogenetics (P=0.057). Adverse events were more frequent in arm-A (15.44) versus 13.52 in arm-B, (P=0.26), but early death rates did not differ significantly (30-day mortality: 6% versus 5%, P=0.76). Median EFS was 6 months in both arms (P=0.96). Median overall survival was 15 months for patients in arm-A compared with 21 months in arm-B (P=0.35). Azacitidine added to standard chemotherapy increases toxicity in older patients with AML, but provides no additional benefit for unselected patients.
EVALuna2:25732

Bacterial nanocellulose stimulates mesenchymal stem cell expansion and formation of stable collagen-I networks as a novel biomaterial in tissue engineering - Vielreicher, Martin; Kralisch, Dana; Sternal, Fabian; Arkudas, Andreas; Friedrich, Oliver; Völkl, Simon (Scientific Reports, 2018)
Biomimetic scaffolds are of great interest to tissue engineering (TE) and tissue repair as they support important cell functions. Scaffold coating with soluble collagen-I has been used to achieve better tissue integration in orthopaedy, however, as collagen persistence was only temporary such efforts were limited. Adequate coverage with cell-derived ECM collagen-I would promise great success, in particular for TE of mechanically challenged tissues. Here, we have used label-free, non-invasive multiphoton microscopy (MPM) to characterise bacterial nanocellulose (BNC) - a promising biomaterial for bone TE - and their potency to stimulate collagen-I formation by mesenchymal stem cells (MSCs). BNC fleeces were investigated by Second Harmonic Generation (SHG) imaging and by their characteristic autofluorescence (AF) pattern, here described for the first time. Seeded MSCs adhered fast, tight and very stable, grew to multilayers and formed characteristic, wide-spread and long-lasting collagen-I. MSCs used micron-sized lacunae and cracks on the BNC surface as cell niches. Detailed analysis using a collagen-I specific binding protein revealed a highly ordered collagen network structure at the cell-material interface. In addition, we have evidence that BNC is able to stimulate MSCs towards osteogenic differentiation. These findings offer new options for the development of engineered tissue constructs based on BNC.
EVALuna2:34280

Bacterial nanocellulose stimulates mesenchymal stem cell expansion, differentiation and formation of stable collagen-I networks - Vielreicher, Martin; Kralisch, Dana; Völkl, Simon; Friedrich, Oliver (International Conference on Biofabrication (Annual Meeting of the International Society for Biofabrication), 2018)

BATF-dependent IL-7RhiGM-CSF+ T cells control intestinal graft-versus-host disease - Ullrich, Evelyn; Abendroth, Benjamin; Rothamer, Johanna; Huber, Carina; Büttner-Herold, Maike; Buchele, Vera; Vogler, Tina; Longerich, Thomas; Zundler, Sebastian; Völkl, Simon; Beilhack, Andreas; Rose-John, Stefan; et al. (Journal of Clinical Investigation, 2018)
Acute graft-versus-host disease (GVHD) represents a severe, T cell-driven inflammatory complication following allogeneic hematopoietic cell transplantation (allo-HCT). GVHD often affects the intestine and is associated with a poor prognosis. Although frequently detectable, proinflammatory mechanisms exerted by intestinal tissue-infiltrating Th cell subsets remain to be fully elucidated. Here, we show that the Th17-defining transcription factor basic leucine zipper transcription factor ATF-like (BATF) was strongly regulated across human and mouse intestinal GVHD tissues. Studies in complete MHC-mismatched and minor histocompatibility-mismatched (miHA-mismatched) GVHD models revealed that BATF-expressing T cells were functionally indispensable for intestinal GVHD manifestation. Mechanistically, BATF controlled the formation of colon-infiltrating, IL-7 receptor-positive (IL-7R+), granulocyte-macrophage colony-stimulating factor-positive (GM-CSF+), donor T effector memory (Tem) cells. This T cell subset was sufficient to promote intestinal GVHD, while its occurrence was largely dependent on T cell-intrinsic BATF expression, required IL-7-IL-7R interaction, and was enhanced by GM-CSF. Thus, this study identifies BATF-dependent pathogenic GM-CSF+ effector T cells as critical promoters of intestinal inflammation in GVHD and hence putatively provides mechanistic insight into inflammatory processes previously assumed to be selectively Th17 drive
EVALuna2:25783

B-cell activating factor BAFF as a novel alert marker for the immunological risk stratification after kidney transplantation - Schuster, Antonia Margarete; Miesgang, N.; Steines, L.; Bach, Christian; Banas, B.; Bergler, T. (Immunologic Research, 2021)
The B cell activating factor BAFF has gained importance in the context of kidney transplantation due to its role in B cell survival. Studies have shown that BAFF correlates with an increased incidence of antibody-mediated rejection and the development of donor-specific antibodies. In this study, we analyzed a defined cohort of kidney transplant recipients who were treated with standardized immunosuppressive regimens according to their immunological risk profile. The aim was to add BAFF as an awareness marker in the course after transplantation to consider patient’s individual immunological risk profile. Included patients were transplanted between 2016 and 2018. Baseline data, graft function, the occurrence of rejection episodes, signs of microvascular infiltration, and DSA kinetics were recorded over 3 years. BAFF levels were determined 14 d, 3 and 12 months post transplantation. Although no difference in graft function could be observed, medium-risk patients showed a clear dynamic in their BAFF levels with low levels shortly after transplantation and an increase in values of 123% over the course of 1 year. Patients with high BAFF values were more susceptible to rejection, especially antibody-mediated rejection and displayed intensified microvascular inflammation; the combination of high BAFF + DSA puts patients at risk. The changing BAFF kinetics of the medium risk group as well as the increased occurrence of rejections at high BAFF values enables BAFF to be seen as an awareness factor. To compensate the changing immunological risk, a switch from a weaker induction therapy to an intensified maintenance therapy is required.
CRIS-Team Scopus Importer:2021-08-20
Keywords: ABMR; BAFF; Immunological risk stratification; Kidney transplantation

B Cell Speed and B-FDC Contacts in Germinal Centers Determine Plasma Cell Output via Swiprosin-1/EFhd2 - Reimer, Dorothea; Meyer-Hermann, Michael; Rakhymzhan, Asylkhan; Steinmetz, Tobit; Tripal, Philipp; Thomas, Jana; Böttcher, Martin; Mougiakakos, Dimitrios; Schulz, Sebastian; Urbanczyk, Sophia; Hauser, Anja E.; Niesner, Raluca A.; et al. (Cell Reports, 2020)
Plasma cells secreting affinity-matured antibodies develop in germinal centers (GCs), where B cells migrate persistently and directionally over defined periods of time. How modes of GC B cell migration influence plasma cell development remained unclear. Through genetic deletion of the F-actin bundling protein Swiprosin-1/EF-hand domain family member 2 (EFhd2) and by two-photon microscopy, we show that EFhd2 restrains B cell speed in GCs and hapten-specific plasma cell output. Modeling the GC reaction reveals that increasing GC B cell speed promotes plasma cell generation. Lack of EFhd2 also reduces contacts of GC B cells with follicular dendritic cells in vivo. Computational modeling uncovers that both GC output and antibody affinity depend quantitatively on contacts of GC B cells with follicular dendritic cells when B cells migrate more persistently. Collectively, our data explain how GC B cells integrate speed and persistence of cell migration with B cell receptor affinity.
CRIS-Team Scopus Importer:2020-08-14
Keywords: actin cytoskeleton; B cell receptor; differentiation; follicular dendritic cell; germinal center; migration; plasma cell; selection; Swiprosin-1/EFhd2; synapse

BCL10 Deficiency Presenting as Severe Combined Immunodeficiency Escaping Newborn Screening - Salou, Sarah; Völkl, Simon; Keller, Baerbel; Ehl, Stephan; Naumann-Bartsch, Nora (Journal of clinical immunology, 2024)
CRIS-Team Scopus Importer:2024-01-12

beta(2)-m - a Trigger for NLRP3 Inflammasome Activation within Macrophages Promoting Multiple Myeloma Cell Proliferation - Hofbauer, Daniel; Mougiakakos, Dimitrios; Büttner-Herold, Maike; Neumann, Frank; Nolting, Jens; Bisht, Savita; Zeiser, Robert; Hamarsheh, Shaima'A; Ricagno, Stefano; Zaiss, Mario; Eberhardt, Martin; Böttcher, Martin; et al. (BLOOD, 2019)
CRIS-Team WoS Importer:2021-10-18

beta(2)-microglobulin - a trigger for NLRP3 inflammasome activation in tumor-associated macrophages promoting multiple myeloma cell progression - Hofbauer, D.; Mougiakakos, D.; Ricagno, S.; Buettner-Herold, M.; Neumann, F.; Bisht, S.; Zeiser, R.; Hamaresh, S.; Zaiss, M.; Eberhardt, M.; Voelkl, S.; Boettcher, M.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Beta-HCG elevation as first sign of a malignant somatic transformation of a non-seminomatous germ cell tumor - Peuser, Moritz; Hartmann, Arndt; Schmidt, Daniela; Mackensen, Andreas; Meidenbauer, Norbert (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Bidirectional transendothelial migration of monocytes across hepatic sinusoidal endothelium shapes monocyte differentiation and regulates the balance between immunity and tolerance in liver - Zimmermann, Henning W.; Bruns, Tony; Weston, Chris J.; Curbishley, Stuart M.; Liaskou, Evaggelia; Li, Ka-Kit; Resheq, Yazid; Badenhorst, Paul W.; Adams, David H. (Hepatology, 2016)
Monocytes are versatile cells that can fulfill proinflammatory and anti-inflammatory functions when recruited to the liver. Recruited monocytes differentiate into tissue macrophages and dendritic cells, which sample antigens and migrate to lymph nodes to elicit T-cell responses. The signals that determine monocyte differentiation and the role of hepatic sinusoidal endothelial cells (HSECs) in this process are poorly understood. HSECs are known to modulate T-cell activation, which led us to investigate whether transendothelial migration of monocytes across HSECs influences their phenotype and function. Subsets of blood-derived monocytes were allowed to transmigrate across human HSECs into a collagen matrix. Most migrated cells remained in the subendothelial matrix, but 10% underwent spontaneous basal to apical transendothelial migration. The maturation, cytokine secretion, and T-cell stimulatory capacity of reverse transmigrating (RT) and subendothelial (SE) monocytes were compared. SE monocytes were mainly CD16(-) , whereas 75%-80% of RT monocytes were CD16(+) . SE monocytes derived from the CD14(++) CD16(-) subset and exhibited high phagocytic activity, whereas RT monocytes originated from CD14(++) CD16(+) and CD14(+) CD16(++) monocytes, displayed an immature dendritic cell-like phenotype (CD11c(pos) HLA-DR(pos) CD80lo CD86lo ), and expressed higher levels of chemokine (C-C motif) receptor 8. Consistent with a dendritic cell phenotype, RT monocytes secreted inflammatory cytokines and induced antigen-specific CD4(+) T-cell activation. In contrast, SE monocytes suppressed T-cell proliferation and activation and exhibited endotoxin tolerance. Transcriptome analysis underscored the functional differences between SE and RT monocytes.Migration across HSECs shapes the subsequent fate of monocytes, giving rise to anergic macrophage-like cells in tissue and the release of immunocompetent pre-dendritic cells into the circulation. (Hepatology 2016;63:233-246).
EVALuna2:25731

Biochemical insight into physiological effects of H 2S: Reaction with peroxynitrite and formation of a new nitric oxide donor, sulfinyl nitrite - Filipovic, Milos; Miljkovic, Jan; Allgäuer, Andrea; Chaurio Gonzalez, Ricardo Alfredo; Shubina, Tatyana; Herrmann, Martin; Ivanovic-Burmazovic, Ivana (Biochemical Journal, 2012)
The reaction of hydrogen sulfide (H S) with peroxynitrite (a key mediator in numerous pathological states) was studied in vitro and in different cellularmodels. The results show that H S can scavenge peroxynitrite with a corresponding second order rate constant of 3.3±0.4×10 M · s at 23°C (8± 2×10 M · s at 37°C). Activation parameters for the reaction (ΔH‡, ΔS‡ and ΔV‡) revealed that the mechanism is rather associative than multi-step free-radical as expected for other thiols. This is in agreement with a primary formation of a new reaction product characterized by spectral and computational studies as HSNO (thionitrate), predominantly present as sulfinyl nitrite, HS(O)NO. This is the first time a thionitrate has been shown to be generated under biologically relevant conditions. The potential of HS(O)NO to serve as a NO donor in a pH-dependent manner and its ability to release NO inside the cells has been demonstrated. Thus sulfide modulates the chemistry and biological effects of peroxynitrite by its scavenging and formation of a new chemical entity (HSNO ) with the potential to release NO, suppressing the pro-apoptotic, oxidative and nitrative properties of peroxynitrite. Physiological concentrations of H S abrogated peroxynitrite-induced cell damage as demonstrated by the: (i) inhibition of apoptosis and necrosis caused by peroxynitrite; (ii) prevention of protein nitration; and (iii) inhibition of PARP-1 [poly(ADP-ribose) polymerase 1] activation in cellular models, implying that a major part of the cytoprotective effects of hydrogen sulfide may be mediated by modulation of peroxynitrite chemistry, in particular under inflammatory conditions. © The Authors Journal compilation © 2012 Biochemical Society.

Biology-driven approaches to prevent and treat relapse of myeloid neoplasia after allogeneic hematopoietic stem cell transplantation - Zeiser, Robert; Beelen, Dietrich W.; Bethge, Wolfgang; Bornhäuser, Martin; Bug, Gesine; Burchert, Andreas; Christopeit, Maximilian; Duyster, Justus; Finke, Jürgen; Gerbitz, Armin; Klusmann, Jan Henning; Kobbe, Guido; et al. (Biology of Blood and Marrow Transplantation, 2019)
The curative potential of allogeneic hematopoietic cell transplantation (allo-HCT) in the treatment of acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) mainly relies on the graft-versus-leukemia (GVL)-effect. Relapse after allo-HCT occurs in a considerable proportion of patients and has a dismal prognosis, with still very limited curative potential. This review provides an overview on the established and evolving approaches to prevent or treat relapse of AML and MDS after allo-HCT, in the context of novels insight into the biology of relapse. Established prophylactic measures to prevent relapse include optimized conditioning and GVHD-prophylaxis as well as donor lymphocyte transfusions for high risk patients while novel immunomodulatory interventions and maintenance approaches are still experimental. Improved diagnostics can detect persistent or recurring disease at a molecular level thus enabling early preemptive interventions. Established options include hypomethylating agents and donor lymphocytes. Standard treatments for haematological relapse comprise chemotherapy, cessation of immunosuppressive treatments and donor lymphocytes. Experimental approaches include molecular targeted therapies, novel immune-modulatory treatments or second allo-HCT. For all interventions, the potential risks including occurrence of GVHD have to be weighed against the benefits individually in each patient. Concurrently, prevention and treatment of relapse post-allo-HCT remains challenging and is an unmet medical need.
EVALuna2:35246

Biomarker-guided preemption of steroid-refractory graft-versus-host disease with alpha-1-antitrypsin - Gergoudis, Stephanie C.; Defilipp, Zachariah; Ozbek, Umut; Sandhu, Karamjeet S.; Etra, Aaron M.; Choe, Hannah K.; Kitko, Carrie L.; Ayuk, Francis; Aziz, Mina; Baez, Janna; Ben-David, Kaitlyn; Bunworasate, Udomsak; et al. (Blood Advances, 2020)
Steroid-refractory (SR) acute graft-versus-host disease (GVHD) remains a major cause of nonrelapse mortality (NRM) after allogeneic hematopoietic cell transplantation (HCT), but its occurrence is not accurately predicted by pre-HCT clinical risk factors. The Mount Sinai Acute GVHD International Consortium (MAGIC) algorithm probability (MAP) identifies patients who are at high risk for developing SR GVHD as early as 7 days after HCT based on the extent of intestinal crypt damage as measured by the concentrations of 2 serum biomarkers, suppressor of tumorigenesis 2 and regenerating islet-derived 3 alpha. We conducted a multicenter proof-of-concept "preemptive" treatment trial of alpha-1-antitrypsin (AAT), a serine protease inhibitor with demonstrated activity against GVHD, in patients at high risk for developing SR GVHD. Patients were eligible if they possessed a high-risk MAP on day 7 after HCT or, if initially low risk, became high risk on repeat testing at day 14. Thirty high-risk patients were treated with twice-weekly infusions of AAT for a total of 16 doses, and their outcomes were compared with 90 high-risk near-contemporaneous MAGIC control patients. AAT treatment was well tolerated with few toxicities, but it did not lower the incidence of SR GVHD compared with controls (20% vs 14%, P = 5.56). We conclude that real-time biomarker-based risk assignment is feasible early after allogeneic HCT but that this dose and schedule of AAT did not change the incidence of SR acute GVHD. This trial was registered at www.clinicaltrials.gov as #NCT03459040.
CRIS-Team WoS Importer:2021-01-15

Biphasic Neutrophil Recovery after CD19 CART in R/R LBCL Is Associated with Superior PFS/OS, Robust CAR T-Cell Expansion in Relation to Baseline Tumor Volume, and a Decrease of Systemic Inflammation over Time - Rejeski, Kai; Perez, Ariel Perez; Iacoboni, Gloria; Buecklein, Veit L.; Blumenberg, Viktoria; Völkl, Simon; Penack, Olaf; Albanyan, Omar; Forsberg, Simon Kg; Petrera, Agnese; Mueller, Niklas; Reid, Kayla M.; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Bispecific T-Cell Engager (BiTE) Antibody Construct Blinatumomab for the Treatment of Patients With Relapsed/Refractory Non-Hodgkin Lymphoma: Final Results From a Phase I Study - Goebeler, Maria-Elisabeth; Knop, Stefan; Viardot, Andreas; Kufer, Peter; Topp, Max S.; Einsele, Hermann; Noppeney, Richard; Hess, Georg; Kallert, Stefan; Mackensen, Andreas; Rupertus, Kathrin; Kanz, Lothar; et al. (Journal of Clinical Oncology, 2016)
Blinatumomab is a CD19/CD3 BiTE (bispecific T-cell engager) antibody construct for the treatment of Philadelphia chromosome-negative acute B-lymphoblastic leukemia. We evaluated blinatumomab in relapsed/refractory B-cell non-Hodgkin lymphoma (NHL).This 3 + 3 design, phase I dose-escalation study determined adverse events and the maximum tolerated dose (MTD) of continuous intravenous infusion blinatumomab in patients with relapsed/refractory NHL. Blinatumomab was administered over 4 or 8 weeks at seven different dose levels (0.5 to 90 ?g/m(2)/day). End points were incidence of adverse events, pharmacokinetics, pharmacodynamics, and overall response rate.Between 2004 and 2011, 76 heavily pretreated patients with relapsed/refractory NHL, who included 14 with diffuse large B-cell lymphoma, were enrolled; 42 received treatment in the formal dose-escalation phase. Neurologic events were dose limiting, and 60 ?g/m(2)/day was established as the MTD. Thirty-four additional patients were recruited to evaluate antilymphoma activity and strategies for mitigating neurologic events at a prespecified MTD. Stepwise dosing (5 to 60 ?g/m(2)/day) plus pentosan polysulfate SP54 (n = 3) resulted in no treatment discontinuations; single-step (n = 5) and double-step (n = 24) dosing entailed two and seven treatment discontinuations due to neurologic events, respectively. Grade 3 neurologic events occurred in 22% of patients (no grade 4/5). Among patients treated at 60 ?g/m(2)/day (target dose; n = 35), the overall response rate was 69% across NHL subtypes and 55% for diffuse large B-cell lymphoma (n = 11); median response duration was 404 days (95% CI, 207 to 1,129 days).In this phase I study of relapsed/refractory NHL, continuous infusion with CD19-targeted immunotherapy blinatumomab at various doses and schedules was feasible, with an MTD of 60 ?g/m(2)/day. Single-agent blinatumomab showed antilymphoma activity.
EVALuna2:25738

BKPYV-SPECIFIC T CELLS REDUCE VIRAL LOAD IN A PRIMARY TUBULAR CELL MODEL - Wasielewski, E.; Lippler, Susanne; Knaup, Karl; Gary, Regina; Aigner, Michael; Kremer, Anna-Lena; Pfister, Felix; Amann, Kerstin Ute; Schiffer, Mario; Mackensen, Andreas; Wiesener, Michael (TRANSPLANT INTERNATIONAL, 2021)
CRIS-Team WoS Importer:2021-10-15

Blocking counter regulation of unfolded protein response by targeted protein synthesis inhibition produces highly synergistic cell death in several cancer entities - Müller, Fabian; Gsottberger, Franziska; Meier, Clara; Petkovic, S.; Krumbholz, Manuela; Metzler, Markus; Mackensen, Andreas (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Blocking the CD47-Sirpa Axis Enhances Tafasitamab-Mediated Phagocytosis - Biedermann, Alexander; Mangelberger-Eberl, Doris; Mougiakakos, Dimitrios; Büttner-Herold, Maike; Flamann, Cindy; Kellner, Christian; Altmeyer, Sarah; Bittenbring, Joerg; Augsberger, Christian; Patra-Kneuer, Maria; Landgraf, Karin; Ilieva-Babinsky, Kristina; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-17

Block of Counter-Regulation By Inhibition of Protein Synthesis Sensitizes Cancer Cells to IRE1a-Mediated Apoptosis Following Unfolded Protein Response - Gsottberger, Franziska; Meier, Christina; Ammon, Anna-Maria; Parker, Scott; Wendland, Kerstin; George, Rebekka; Petkovic, Srdjan; Mellenthin, Lisa; Emmerich, Charlotte; Lutzny-Geier, Gloria; Metzler, Markus; Mackensen, Andreas; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Blood counts in adult and elderly individuals: defining the norms over eight decades of life - Zierk, Jakob; Krebs, Alexander; Rauh, Manfred; Metzler, Markus; Löscher, Astrid; Strasser, Erwin; Krause, Stefan (British Journal of Haematology, 2020)
The blood count is one of the most common tests used for health assessment. In elderly individuals, selection of a ‘healthy’ reference population for laboratory assessment is difficult due to the high prevalence of chronic morbidities, leading to uncertainty regarding appropriate reference intervals. In particular, age-specific lower haemoglobin reference limits to define anaemia are controversial. Here, we applied a data mining approach to a large dataset of 3 029 904 clinical routine samples to establish blood count reference intervals. We excluded samples from units/specialists with a high proportion of abnormal blood counts, samples from patients with an unknown or decreased estimated glomerular filtration rate, and samples with abnormal test results in selected other analytes. After sample exclusion, 566 775–572 060 samples from different individuals aged 20–100 years were available for analysis. We then used an established statistical algorithm to determine the distribution of physiological test results and calculated age- and sex-specific reference intervals. Our results show substantial trends with age in haematology analytes' reference intervals. Most notably, haemoglobin and red cell counts decline in men with advanced age, accompanied by increases in red cell volume in both sexes. These findings were confirmed in an independent dataset, and suggest an at least partly physiologic cause.
CRIS-Team Scopus Importer:2020-02-14
Keywords: anaemia; haematology; laboratory haematology

Blood counts in adults and elderly individuals - Zierk, Jakob; Krebs, A.; Rauh, Manfred; Metzler, Markus; Parsch, H.; Strasser, Erwin; Krause, Stefan (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

BNT211-01: A phase I trial to evaluate safety and efficacy of CLDN6 CAR T cells and CLDN6-encoding mRNA vaccine-mediated in vivo expansion in patients with CLDN6-positive advanced solid tumours - Mackensen, Andreas; Haanen, J. B. A. G.; Koenecke, C.; Alsdorf, W.; Wagner-Drouet, E.; Heudobler, D.; Borchmann, P.; Bokemeyer, C.; Klobuch, S.; Smit, E.; Mueller, F.; Desuki, A.; et al. (ANNALS OF ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-12-23

BNT211: A phase I/II trial to evaluate safety and efficacy of CLDN6 CAR-T cells and CARVac-mediated in vivo expansion in patients with CLDN6+advanced solid tumors - Haanen, J.; Mackensen, Andreas; Koenecke, C.; Alsdorf, W.; Desuki, A.; Wagner-Drouet, E.; Heudobler, D.; Borchmann, P.; Wiegert, E.; Schulz, C.; Rengstl, B.; Preussner, L.; et al. (ANNALS OF ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-12-31

BNT211: A PHASE I/II TRIAL TO EVALUATE SAFETY AND EFFICACY OF CLDN6 CAR-T CELLS AND VACCINE-MEDIATED IN VIVO EXPANSION IN PATIENTS WITH CLDN6-POSITIVE ADVANCED SOLID TUMORS - Mackensen, Andreas; Koenecke, Christian; Haanen, John; Alsdorf, Winfried; Desuki, Alexander; Wagner-Drouet, Eva; Heudobler, Daniel; Borchmann, Peter; Wiegert, Erol; Schulz, Catrine; Rengstl, Benjamin; Preussner, Liane; et al. (JOURNAL FOR IMMUNOTHERAPY OF CANCER, 2021)
CRIS-Team WoS Importer:2022-04-15

Bone marrow stroma cells promote a S100A8/A9high subset of chemoresistant AML blasts with distinct metabolic features in a Jak/STAT-dependent manner - Böttcher, Martin; Panagiotidis, Konstantinos; Mentz, K.; Bruns, Heiko; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Bone marrow stroma cells promote induction of a chemoresistant and prognostic unfavorable S100A8/A9high AML cell subset. - Böttcher, Martin; Panagiotidis, Konstantinos; Bruns, Heiko; Stumpf, Martina; Völkl, Simon; Geyh, Stefanie; Dietel, Barbara; Schroeder, Thomas; Mackensen, Andreas; Mougiakakos, Dimitrios (Blood Advances, 2022)
The bone marrow (BM) stroma represents a protective niche for acute myeloid leukemia (AML) cells. However, the complex underlying mechanisms remain to be fully elucidated. We found 2 small, intracellular, calcium-sensing molecules, S100A8 and S100A9, among the top genes being upregulated in primary AML blasts upon stromal contact. As members of the S100 protein family, they can modulate such cellular processes as proliferation, migration, and differentiation. Dysregulation of S100 proteins is described as a predictor of poor survival in different human cancers, including increased S100A8 expression in de novo AML. Thus, we wanted to decipher the underlying pathways of stroma-mediated S100A8/A9 induction, as well as its functional consequences. Upregulation of S100A8/A9 after stromal cross talk was validated in AML cell lines, was contact independent and reversible and resulted in accumulation of S100A8/A9high cells. Accordingly, frequency of S100A8/A9high AML blasts was higher in the patients' BM than in peripheral blood. The S100A8/A9high AML cell population displayed enhanced utilization of free fatty acids, features of a more mature myeloid phenotype, and increased resilience toward chemotherapeutics and BCL2 inhibition. We identified stromal cell-derived interleukin-6 (IL-6) as the trigger for a Jak/STAT3 signaling-mediated S100A8/A9 induction. Interfering with fatty acid uptake and the IL-6-Jak/STAT3 pathway antagonized formation of S100A8/A9high cells and therapeutic resistance, which could have therapeutic implications as a strategy to interfere with the AML-niche dynamics.
EVALuna2:503901

Bortezomib consolidation following autologous transplant in younger and older patients with newly diagnosed multiple myeloma in two phase III trials - Straka, Christian; Knop, Stefan; Vogel, Martin; Müller, Jürgen; Kropff, Martin; Metzner, Bernd; Langer, Christian; Sayer, Herbert; Jung, Wolfram; Dürk, Heinz A.; Salwender, Hans; Wandt, Hannes; et al. (European Journal of Haematology, 2019)
OBJECTIVE: A post hoc analysis of two phase III trials was carried out to explore the influence of age and treatment factors on the effect of bortezomib consolidation on progression-free survival (PFS) post autologous stem cell transplantation (ASCT). METHODS: Patients with newly diagnosed multiple myeloma were assigned to one of two trials (ClinicalTrials.gov IDs: NCT00416273, NCT00416208), which were conducted in parallel, based on age (18-60 or 61-75 years, respectively). Following induction and ASCT, patients were randomized 1:1 to four 35-day cycles of bortezomib consolidation (1.6 mg/m2 IV on days 1, 8, 15, 22) or observation only. RESULTS: Median PFS with bortezomib consolidation vs observation was 33.6 vs 29.0 months (P = 0.3599) in patients aged 18-60 years (n = 202), and 33.4 vs 26.4 months (P = 0.0073) in patients aged 61-75 years (n = 155), respectively. Bortezomib consolidation post-ASCT appeared to equalize outcomes between older and younger patients who received prior treatment of differing intensity. This suggests that the effect of consolidation may be relative and may depend on the composition and intensity of induction and high-dose therapy. CONCLUSION: Older patients receiving less intensive prior treatment could experience a larger PFS benefit from bortezomib consolidation.
EVALuna2:202558

BRAF inhibitor treatment in classic hairy cell leukemia: a long-term follow-up study of patients treated outside clinical trials - Liebers, Nora; Roider, Tobias; Bohn, Jan Paul; Haberbosch, Isabella; Pircher, Andreas; Ferstl, Barbara; Ebnöther, Monika; Wendtner, Clemens Martin; Dearden, Claire; Follows, George A.; Ho, Anthony D.; Müller-Tidow, Carsten; et al. (Leukemia, 2019)
CRIS-Team Scopus Importer:2019-11-26

BRAF inhibitor treatment in hairy cell leukemia: a long-term follow up study - Liebers, N.; Roider, T.; Bohn, J. -P.; Pircher, A.; Ferstl, B.; Ebnoether, M.; Perker, M.; Mandel, T.; Steurer, M.; Wendtner, C. -M.; Dearden, C.; Mueller-Tidow, C.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Breaking barriers: NEK2 inhibition shines in multiple myeloma treatment - Lischer, Christopher; Bruns, Heiko (Cell Reports Medicine, 2023)
In their article, Cheng et al.1 reveal that NEK2 loss reshapes the tumor microenvironment, reducing tumor-associated macrophages and decreasing T cell exhaustion. They show that this ultimately favors the immune system's anti-cancer response in multiple myeloma.
CRIS-Team Scopus Importer:2023-10-20

Can we starve leukemia? Metabolic needs of MLL - Garcia-Cuellar, Maria-Paz; Lawlor, Jennifer; Böttcher, Martin; Mougiakakos, Dimitrios; Metzler, Markus; Slany, Robert (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

CAR-HEMATOTOX: a model for CAR T-cell–related hematologic toxicity in relapsed/refractory large B-cell lymphoma - Rejeski, Kai; Perez, Ariel; Sesques, Pierre; Hoster, Eva; Berger, Carolina; Jentzsch, Liv; Mougiakakos, Dimitrios; Frölich, Lisa; Ackermann, Josephine; Bücklein, Veit; Blumenberg, Viktoria; Schmidt, Christian; et al. (Blood, 2021)
Hematotoxicity represents a frequent chimeric antigen receptor (CAR) T-cell–related adverse event and remains poorly understood. In this multicenter analysis, we studied patterns of hematopoietic reconstitution and evaluated potential predictive markers in 258 patients receiving axicabtagene ciloleucel (axi-cel) or tisagenlecleucel (tisa-cel) for relapsed/refractory large B-cell lymphoma. We observed profound (absolute neutrophil count [ANC] <100 cells per µL) neutropenia in 72% of patients and prolonged (21 days or longer) neutropenia in 64% of patients. The median duration of severe neutropenia (ANC < 500 cells per µL) was 9 days. We aimed to identify predictive biomarkers of hematotoxicity using the duration of severe neutropenia until day +60 as the primary end point. In the training cohort (n = 58), we observed a significant correlation with baseline thrombocytopenia (r = −0.43; P = .001) and hyperferritinemia (r = 0.54; P < .0001) on univariate and multivariate analysis. Incidence and severity of cytokine-release syndrome, immune effector cell–associated neurotoxicity syndrome, and peak cytokine levels were not associated with the primary end point. We created the CAR-HEMATOTOX model, which included markers associated with hematopoietic reserve (eg, platelet count, hemoglobin, and ANC) and baseline inflammation (eg, C-reactive protein and ferritin). This model was validated in independent cohorts, one from Europe (n = 91) and one from the United States (n = 109) and discriminated patients with severe neutropenia ≥14 days to <14 days (pooled validation: area under the curve, 0.89; sensitivity, 89%; specificity, 68%). A high CAR-HEMATOTOX score resulted in a longer duration of neutropenia (12 vs 5.5 days; P < .001) and a higher incidence of severe thrombocytopenia (87% vs 34%; P < .001) and anemia (96% vs 40%; P < .001). The score implicates bone marrow reserve and inflammation prior to CAR T-cell therapy as key features associated with delayed cytopenia and will be useful for risk-adapted management of hematotoxicity.
CRIS-Team Scopus Importer:2021-12-24

CAR T-cell therapy in autoimmune diseases - Schett, Georg; Mackensen, Andreas; Mougiakakos, Dimitrios (Lancet, 2023)
Despite the tremendous progress in the clinical management of autoimmune diseases, many patients do not respond to the currently used treatments. Autoreactive B cells play a key role in the pathogenesis of autoimmune diseases, such as systemic lupus erythematosus, rheumatoid arthritis, and multiple sclerosis. B-cell-depleting monoclonal antibodies, such as rituximab, have poor therapeutic efficacy in autoimmune diseases, mainly due to the persistence of autoreactive B cells in lymphatic organs and inflamed tissues. The adoptive transfer of T cells engineered to target tumour cells via chimeric antigen receptors (CARs) has emerged as an effective treatment modality in B-cell malignancies. In the last 2 years treatment with autologous CAR T cells directed against the CD19 antigen has been introduced in therapy of autoimmune disease. CD19 CAR T cells induced a rapid and sustained depletion of circulating B cells, as well as in a complete clinical and serological remission of refractory systemic lupus erythematosus and dermatomyositis. In this paper, we discuss the evolving strategies for targeting autoreactive B cells via CAR T cells, which might be used for targeted therapy in autoimmune diseases.
CRIS-Team Scopus Importer:2023-10-13

CAR T Cell Treatment of Refractory Systemic Lupus Erythematosus - Schett, Georg; Böltz, Sebastian; Müller, Fabian; Kleyer, Arnd; Völkl, Simon; Aigner, Michael; Gary, Regina; Kretschmann, Sascha; Simon, David; Kharboutli, Soraya; Mougiakakos, Dimitrios; Krönke, Gerhard; et al. (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

CAR-T CELL TREATMENT OF REFRACTORY SYSTEMIC LUPUS ERYTHEMATOSUS- SAFETY AND PRELIMINARY EFFICACY DATA FROM THE FIRST FOUR PATIENTS - Schett, Georg; Böltz, Sebastian; Müller, Fabian; Kleyer, Arnd; Völkl, Simon; Aigner, Michael; Gary, Regina; Kretschmann, S.; Simon, David; Kharboutli, Soraya; Mougiakakos, D.; Krönke, Gerhard; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Case Report: IBD-like colitis following CAR T cell therapy for diffuse large B cell lymphoma - Zundler, Sebastian; Vitali, Francesco; Kharboutli, Soraya; Völkl, Simon; Polifka, Iris; Mackensen, Andreas; Atreya, Raja; Neurath, Markus; Mougiakakos, Dimitrios (Frontiers in Oncology, 2023)
Chimeric antigen receptor (CAR) T cell therapy has become a new mainstay in the treatment of several hematologic malignancies, but the spectrum of associated complications is still incompletely defined. Here, we report the case of a 70-year-old female patient treated with tisagenlecleucel for diffuse large B cell lymphoma (DLBCL), who developed chronic diarrhea with characteristics of inflammatory bowel disease (IBD)-like colitis. CAR T cells were substantially enriched in the colon lamina propria and other diagnoses were ruled out. Thus, we conclude that IBD-like colitis in this patient was associated to CAR T cell therapy and needs to be considered as a rare potential complication.
CRIS-Team Scopus Importer:2023-06-16
Keywords: CAR T cells; case report; diffuse large B cell lymphoma; inflammatory bowel disease (IBD); tisagenlecleucel

CD137 (4-1BB) stimulation leads to metabolic and functional reprogramming of human monocytes/macrophages enhancing their tumoricidal activity - Stoll, Andrej; Bruns, Heiko; Fuchs, Maximilian; Nimmerjahn, Falk; Kunz, Meik; Peipp, M.; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (Leukemia, 2021)
Immunotherapies have heralded a new era in the cancer treatment. In addition to checkpoint inhibitors, agonistic antibodies against co-stimulatory immune receptors hold the potential to invoke efficient antitumor immunity. Targeting CD137 has gained momentum based on its ability to drive NK- and T-cell-based responses. CD137-engaging mAbs have already entered clinical trials for different types of tumors showing promising results. Despite the efforts to translate CD137-mediated immunotherapy into clinical practice, little remains known regarding the role of CD137 in human monocytes/macrophages. We found CD137 being expressed on monocytes of healthy controls and at even higher levels in patients with multiple myeloma or CLL. CD137HI(GH) monocytes displayed a distinct phenotypic, transcriptomic, and metabolic profile. They possessed an increased phagocytic capacity enabling superior antibody-dependent phagocytosis (ADPC) of multiple myeloma and lymphoma cells that were treated with anti-CD38 or anti-CD20 mAbs. Triggering CD137 promoted both metabolic and tumoricidal activity in an extracellular signal-regulated kinase (ERK)-dependent fashion. In addition, we observed a phenotypic, transcriptomic, and functional skewing towards a M1-like phenotype. Overall, we introduce CD137 as a positive immune checkpoint on human monocytes/macrophages, which can have therapeutic implications especially in view of synergistic effects when combining CD137 agonists with tumor-targeting antibodies.
CRIS-Team Scopus Importer:2021-06-04

CD137 (4-1BB) triggering leads to metabolic and functional reprogramming of human monocytes/macrophages enhancing their tumoricidal activity - Stoll, Andrej; Bruns, Heiko; Gamali, S.; Saul, Domenica; Fuchs, Maximilian; Nimmerjahn, Falk; Kunz, Meik; Peipp, M.; Mackensen, Andreas; Mougiakakos, Dimitrios (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

CD19 CAR T cells are an effective therapy for posttransplant relapse in patients with B-lineage ALL: real-world data from Germany - Bader, Peter; Rossig, Claudia; Hutter, Martin; Ayuk, Francis Ayuketang; Baldus, Claudia D.; Bücklein, Veit L.; Bonig, Halvard; Cario, Gunnar; Einsele, Hermann; Holtick, Udo; Koenecke, Christian; Bakhtiar, Shahrzad; et al. (Blood Advances, 2023)
Patients with precursor B-cell acute lymphoblastic leukemia (pB-ALL) who have relapsed after allogeneic hematopoietic stem cell transplantation (allo-HSCT), have relapsed more than once, or are resistant upfront have a dismal prognosis. CD19-targeted chimeric antigen receptor (CAR) T cells have evolved as potent immune therapies. Tisagenlecleucel (Tisa-cel) is a commercially available autologous CD19-directed CAR T-cell product. We performed a retrospective study inviting all CAR T-cell centers in Germany to participate. Eighty-one patients with pB-ALL were included. Twenty-eight days after CAR T-cell infusion, 71 patients (87.7%) were in complete response, and 8 (9.9%) were in nonremission. At 2 years, the probabilities of event-free survival (pEFS), relapse-free survival (pRFS), and overall survival (pOS) were 45.3%, 51.7%, and 53.2%, respectively. pEFS was not different in patients without (n = 16, 55.0%) vs with prior allo-HSCT (n = 65, 43.4%). In patients treated after allo-HSCT, the time to relapse after allo-HSCT was a strong predictor of outcome. Patients relapsing within 6 months of allo-HSCT had a disappointing pEFS of 18.4% (pOS = 16.0%); the pEFS for those relapsing later was 55.5% (pOS = 74.8%). Our study provides real-world experience in pediatric, adolescent, and young adult patients with ALL treated with Tisa-cel, where most patients were treated after having relapsed after allo-HSCT. A total of 45.3% were rescued with a single dose of Tisa-cel. Our novel finding that patients with ALL after allo-HSCT had by far a better pEFS if relapse occurred beyond 6 months might be helpful in clinical decision-making and motivates studies to uncover the reasons.
CRIS-Team Scopus Importer:2023-08-25

CD19-CAR-T Cells Are Effective and Safe Treatment of Post-Transplant Relapse in Pediatric and Young Adult Patients with B-Lineage ALL: Real-World Data from Germany - Bader, Peter; Rossig, Claudia; Hutter, Martin; Ayuk, Francis A.; Baldus, Claudia D.; Buecklein, Veit L.; Bonig, Halvard; Cario, Gunnar; Einsele, Hermann; Holtick, Udo; Koenecke, Christian; Kuenkele, Annette; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-17

CD19 CAR T-Cell Therapy in Autoimmune Disease - A Case Series with Follow-up. - Müller, Fabian; Taubmann, Jule; Bucci, Laura; Wilhelm, Artur; Bergmann, Christina; Völkl, Simon; Aigner, Michael; Rothe, Tobias; Minopoulou, Ioanna; Tur, Carlo; Knitza, Johannes; Kharboutli, Soraya; et al. (New England Journal of Medicine, 2024)
BACKGROUND: Treatment for autoimmune diseases such as systemic lupus erythematosus (SLE), idiopathic inflammatory myositis, and systemic sclerosis often involves long-term immune suppression. Resetting aberrant autoimmunity in these diseases through deep depletion of B cells is a potential strategy for achieving sustained drug-free remission. METHODS: We evaluated 15 patients with severe SLE (8 patients), idiopathic inflammatory myositis (3 patients), or systemic sclerosis (4 patients) who received a single infusion of CD19 chimeric antigen receptor (CAR) T cells after preconditioning with fludarabine and cyclophosphamide. Efficacy up to 2 years after CAR T-cell infusion was assessed by means of Definition of Remission in SLE (DORIS) remission criteria, American College of Rheumatology-European League against Rheumatism (ACR-EULAR) major clinical response, and the score on the European Scleroderma Trials and Research Group (EUSTAR) activity index (with higher scores indicating greater disease activity), among others. Safety variables, including cytokine release syndrome and infections, were recorded. RESULTS: The median follow-up was 15 months (range, 4 to 29). The mean (±SD) duration of B-cell aplasia was 112±47 days. All the patients with SLE had DORIS remission, all the patients with idiopathic inflammatory myositis had an ACR-EULAR major clinical response, and all the patients with systemic sclerosis had a decrease in the score on the EUSTAR activity index. Immunosuppressive therapy was completely stopped in all the patients. Grade 1 cytokine release syndrome occurred in 10 patients. One patient each had grade 2 cytokine release syndrome, grade 1 immune effector cell-associated neurotoxicity syndrome, and pneumonia that resulted in hospitalization. CONCLUSIONS: In this case series, CD19 CAR T-cell transfer appeared to be feasible, safe, and efficacious in three different autoimmune diseases, providing rationale for further controlled clinical trials. (Funded by Deutsche Forschungsgemeinschaft and others.).
EVALuna2:555903

CD19 CAR-T cell treatment of CNS relapse of Burkitt's lymphoma: A case report - Aigner, Michael; Jacobs, Benedikt; Gary, Regina; Kretschmann, S.; Achenbach, Susanne; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon; Baur, Rebecca (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

CD19 Chimeric Antigen Receptor (CAR) T-Cell Therapy for Adults with B-Cell Acute Lymphoblastic Leukemia (B-ALL): A Large Real-World Series from Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation (EBMT) - Brissot, Eolia; Peczynski, Christophe; Labopin, Myriam; Lussana, Federico; Hough, Rachael; Kuball, Jurgen; Rösler, Wolf; Furst, Sabine; Barba, Pere; Daskalakis, Michael; Gungor, Tayfun; Bierings, Marc; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-17

CD19-targeted CAR T cells in refractory antisynthetase syndrome - Müller, Fabian; Böltz, Sebastian; Knitza, Johannes; Aigner, Michael; Völkl, Simon; Kharboutli, Soraya; Reimann, Hannah; Taubmann, Jule; Kretschmann, Sascha; Rösler, Wolf; Manger, Bernhard; Wacker, Jochen; et al. (Lancet, 2023)
CRIS-Team Scopus Importer:2023-03-24

CD19-targeted CAR T cells in refractory systemic lupus erythematosus - Mougiakakos, Dimitrios; Krönke, Gerhard; Völkl, Simon; Kretschmann, Sascha; Aigner, Michael; Kharboutli, Soraya; Böltz, Sebastian; Manger, Bernhard; Mackensen, Andreas; Schett, Georg (New England Journal of Medicine, 2021)
CRIS-Team Scopus Importer:2021-08-20

CD19-Targeted CAR-T Cells in Refractory Systemic Lupus Erythematosus: Safety, Efficacy, and Mechanistic Insights from the First Five Patients - Müller, Fabian; Völkl, Simon; Mougiakakos, Dimitrios; Böltz, Sebastian; Aigner, Michael; Gary, Regina; Kretschmann, Sascha; Kharboutli, Soraya; Kleyer, Arnd; Simon, David; Rösler, Wolf; Habenicht, Katharina Marie; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

CD33/CD3-bispecific T-cell engaging (BiTE®) antibody construct targets monocytic AML myeloid-derived suppressor cells - Jitschin, Regina; Saul, Domenica; Braun, Martina; Tohumeken, Sehmus; Kischel, Roman; Lutteropp, Michael; Dos Santos, Cedric; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (Journal for ImmunoTherapy of Cancer, 2018)
Acute myeloid leukemia (AML) is the most common acute leukemia amongst adults with a 5-year overall survival lower than 30%. Emerging evidence suggest that immune alterations favor leukemogenesis and/or AML relapse thereby negatively impacting disease outcome. Over the last years myeloid derived suppressor cells (MDSCs) have been gaining momentum in the field of cancer research. MDSCs are a heterogeneous cell population morphologically resembling either monocytes or granulocytes and sharing some key features including myeloid origin, aberrant (immature) phenotype, and immunosuppressive activity. Increasing evidence suggests that accumulating MDSCs are involved in hampering anti-tumor immune responses and immune-based therapies. Here, we demonstrate increased frequencies of CD14+ monocytic MDSCs in newly diagnosed AML that co-express CD33 but lack HLA-DR (HLA-DRlo). AML-blasts induce HLA-DRlo cells from healthy donor-derived monocytes in vitro that suppress T-cells and express indoleamine-2,3-dioxygenase (IDO). We investigated whether a CD33/CD3-bispecific BiTE® antibody construct (AMG 330) with pre-clinical activity against AML-blasts by redirection of T-cells can eradicate CD33+ MDSCs. In fact, T-cells eliminate IDO+CD33+ MDSCs in the presence of AMG 330. Depletion of total CD14+ cells (including MDSCs) in peripheral blood mononuclear cells from AML patients did not enhance AMG 330-triggered T-cell activation and expansion, but boosted AML-blast lysis. This finding was corroborated in experiments showing that adding MDSCs into co-cultures of T- and AML-cells reduced AML-blast killing, while IDO inhibition promotes AMG 330-mediated clearance of AML-blasts. Taken together, our results suggest that AMG 330 may achieve anti-leukemic efficacy not only through T-cell-mediated cytotoxicity against AML-blasts but also against CD33+ MDSCs, suggesting that it is worth exploring the predictive role of MDSCs for responsiveness towards an AMG 330-based therapy.
EVALuna2:35089

CD47 Enhances In Vivo Functionality of Artificial Antigen-Presenting Cells - Bruns, Heiko; Bessell, Catherine; Varela, Juan Carlos; Haupt, Carl; Fang, Jerry; Pasemann, Shirin; Mackensen, Andreas; Oelke, Mathias; Schneck, Jonathan P.; Schuetz, Christian (Clinical Cancer Research, 2015)
Artificial antigen-presenting cells, aAPC, have successfully been used to stimulate antigen-specific T-cell responses in vitro as well as in vivo. Although aAPC compare favorably with autologous dendritic cells in vitro, their effect in vivo might be diminished through rapid clearance by macrophages. Therefore, to prevent uptake and minimize clearance of aAPC by macrophages, thereby increasing in vivo functionality, we investigated the efficiency of "don't eat me" three-signal aAPC compared with classical two-signal aAPC.To generate "don't eat me" aAPC, CD47 was additionally immobilized onto classical aAPC (aAPC(CD47+)). aAPC and aAPC(CD47+) were analyzed in in vitro human primary T-cell and macrophage cocultures. In vivo efficiency was compared in a NOD/SCID T-cell proliferation and a B16-SIY melanoma model.This study demonstrates that aAPC(CD47+) in coculture with human macrophages show a CD47 concentration-dependent inhibition of phagocytosis, whereas their ability to generate and expand antigen-specific T cells was not affected. Furthermore, aAPC(CD47+)-generated T cells displayed equivalent killing abilities and polyfunctionality when compared with aAPC-generated T cells. In addition, in vivo studies demonstrated an enhanced stimulatory capacity and tumor inhibition of aAPC(CD47+) over normal aAPC in conjunction with diverging biodistribution in different organs.Our data for the first time show that aAPC functionalized with CD47 maintain their stimulatory capacity in vitro and demonstrate enhanced in vivo efficiency. Thus, these next-generation aAPC(CD47+) have a unique potential to enhance the application of the aAPC technology for future immunotherapy approaches. Clin Cancer Res; 21(9); 2075-83. ©2015 AAC
EVALuna2:25622

CEBPA mutations in 4708 patients with acute myeloid leukemia: differential impact of bZIP and TAD mutations on outcome - Taube, Franziska; Georgi, Julia Annabell; Kramer, Michael; Stasik, Sebastian; Middeke, Jan Moritz; Röllig, Christoph; Krug, Utz; Krämer, Alwin; Scholl, Sebastian; Hochhaus, Andreas; Brümmendorf, Tim H.; Naumann, Ralph; et al. (Blood, 2022)
Biallelic mutations of the CEBPA gene (CEBPAbi) define a distinct entity associated with favorable prognosis; however, the role of monoallelic mutations (CEBPAsm) is poorly understood. We retrospectively analyzed 4708 adults with acute myeloid leukemia (AML) who had been recruited into the Study Alliance Leukemia trials, to investigate the prognostic impact of CEBPAsm. CEBPA mutations were identified in 240 patients (5.1%): 131 CEBPAbi and 109 CEBPAsm (60 affecting the N-terminal transactivation domains [CEBPAsmTAD] and 49 the C-terminal DNA-binding or basic leucine zipper region [CEBPAsmbZIP]). Interestingly, patients carrying CEBPAbi or CEBPAsmbZIP shared several clinical factors: they were significantly younger (median, 46 and 50 years, respectively) and had higher white blood cell (WBC) counts at diagnosis (median, 23.7 × 109/L and 35.7 × 109/L) than patients with CEBPAsmTAD (median age, 63 years, median WBC 13.1 × 109/L; P < .001). Co-mutations were similar in both groups: GATA2 mutations (35.1% CEBPAbi; 36.7% CEBPAsmbZIP vs 6.7% CEBPAsmTAD; P < .001) or NPM1 mutations (3.1% CEBPAbi; 8.2% CEBPAsmbZIP vs 38.3% CEBPAsmTAD; P < .001). CEBPAbi and CEBPAsmbZIP, but not CEBPAsmTAD were associated with significantly improved overall (OS; median 103 and 63 vs 13 months) and event-free survival (EFS; median, 20.7 and 17.1 months vs 5.7 months), in univariate and multivariable analyses. Additional analyses revealed that the clinical and molecular features as well as the favorable survival were confined to patients with in-frame mutations in bZIP (CEBPAbZIP-inf). When patients were classified according to CEBPAbZIP-inf and CEBPAother (including CEBPAsmTAD and non-CEBPAbZIP-inf), only patients bearing CEBPAbZIP-inf showed superior complete remission rates and the longest median OS and EFS, arguing for a previously undefined prognostic role of this type of mutation.
CRIS-Team Scopus Importer:2022-01-14

Cellular and humoral immune responses to SARS-CoV-2 vaccination in patients after CD19.CAR T-cell therapy - Reimann, Hannah; Kremer, Anita; Blumenberg, Viktoria; Schmidt, Katja; Aigner, Michael; Jacobs, Benedikt; Eisenhauer, Nina; Kämpf, Alina; Rösler, Wolf; Kharboutli, Soraya; Mougiakakos, Dimitrios; Lang, Vanessa; et al. (Blood Advances, 2023)
EVALuna2:512817

Cerebral Ischemia in Patients on Direct Oral Anticoagulants - Macha, Kosmas; Marsch, Armin; Siedler, Gabriela; Breuer, Lorenz; Strasser, Erwin; Engelhorn, Tobias; Schwab, Stefan; Kallmünzer, Bernd (Stroke, 2019)
Background and Purpose- In patients with ischemic stroke on therapy with vitamin K antagonists, stroke severity and clinical course are affected by the quality of anticoagulation at the time of stroke onset, but clinical data for patients using direct oral anticoagulants (DOACs) are limited. Methods- Data from our registry including all patients admitted with acute cerebral ischemia while taking oral anticoagulants for atrial fibrillation between November 2014 and October 2017 were investigated. The activity of vitamin K antagonists was assessed using the international normalized ratio on admission and categorized according to a threshold of 1.7. DOAC plasma levels were measured using the calibrated Xa-activity (apixaban, rivaroxaban, and edoxaban) or the Hemoclot-assay (dabigatran) and categorized into low (<50 ng/mL), intermediate (50-100 ng/mL), or high (>100 ng/mL). Primary objective was the association between anticoagulant activity and clinical and imaging characteristics. Results- Four hundred sixty patients were included (49% on vitamin K antagonists and 51% on DOAC). Patients on vitamin K antagonists with low international normalized ratio values had higher scores on the National Institutes of Health Stroke Scale and a higher risk of large vessel occlusion on admission. For patients on DOAC, plasma levels were available in 75.6% and found to be low in 49 (27.7%), intermediate in 41 (23.2%), and high in 87 patients (49.2%). Low plasma levels were associated with higher National Institutes of Health Stroke Scale scores on admission (low: 8 [interquartile range, 3-15] versus intermediate: 4 [1-11] versus high: 3 [0-8]; P<0.001) and higher risk of persisting neurological deficits or cerebral infarction on imaging (85.7% versus 75.6% versus 54.0%; P<0.001). Low DOAC plasma levels were an independent predictor of large vessel occlusion (odds ratio, 3.84 [95% CI, 1.80-8.20]; P=0.001). Conclusions- The activity of anticoagulation measured by specific DOAC plasma levels on admission is associated with stroke severity and presence of large vessel occlusion.
CRIS-Team Scopus Importer:2019-07-19
Keywords: anticoagulants; atrial fibrillation; direct oral anticoagulants; ischemic stroke; plasma level

Chaperone protein HSC70 regulates intercellular transfer of Y chromosome antigen DBY - Kretschmann, Sascha; Herda, Stefanie; Bruns, Heiko; Russ, Josefine; van der Meijden, Edith D.; Schlötzer-Schrehardt, Ursula; Griffioen, Marieke; Na, Il Kang; Mackensen, Andreas; Kremer, Anita (Journal of Clinical Investigation, 2019)
Recent studies have demonstrated that CD4+ T cells can efficiently reject MHC-II-negative tumors. This requires indirect presentation of tumor-associated antigens on surrounding antigen-presenting cells. We hypothesized that intercellular transfer of proteins is not the sole consequence of cell death-mediated protein release, but depends on heat-shock cognate protein 70 (HSC70) and its KFERQ-like binding motif on substrate proteins. Using human Y chromosome antigen DBY, we showed that mutation of one of its 2 putative binding motifs markedly diminished T cell activation after indirect presentation and reduced protein-protein interaction with HSC70. Intercellular antigen transfer was shown to be independent of cell-cell contact, but relied on engulfment within secreted microvesicles. In vivo, alterations of the homologous KFERQ-like motif in murine DBY hampered tumor rejection, T cell activation, and migration into the tumor and substantially impaired survival. Collectively, we show that intercellular antigen transfer of DBY is tightly regulated via binding to HSC70 and that this mechanism influences recognition and rejection of MHC-II-negative tumors in vivo.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Antigen presentation; Cancer immunotherapy; Immunology; Oncology; T cells

Characteristics and Outcome of Patients with Acute Myeloid Leukemia and Trisomy 4 - Kayser, Sabine; Martinez-Cuadron, David; Hanoun, Maher; Stoelzel, Friedrich; Gil, Cristina; Reinhardt, H. Christian; Aguiar, Eliana; Schaefer-Eckart, Kerstin; Bergua Burgues, Juan Miguel; Steffen, Bjoern; Bernal, Teresa; Krause, Stefan; et al. (BLOOD, 2021)
CRIS-Team WoS Importer:2022-09-09

Characteristics and outcome of patients with acute myeloid leukemia and trisomy 4 - Kayser, Sabine; Martínez-Cuadrón, David; Hanoun, Maher; Stölzel, Friedrich; Gil, Cristina; Reinhardt, H. Christian; Aguiar, Eliana; Schäfer-Eckart, Kerstin; Burgues, Juan Miguel Bergua; Steffen, Björn; Bernal, Teresa; Krause, Stefan; et al. (Haematologica, 2023)
We retrospectively studied 125 patients with acute myeloid leukemia and trisomy 4 (median age at diagnosis, 58 years; range, 16-77 years) treated between 2000 and 2019 within a multicenter study. Trisomy 4 was the sole abnormality in 28 (22%) patients and additional abnormalities were present in 97 (78%) patients. Twenty-two (22%) and 15 (15%) of 101 tested patients harbored NPM1 and FLT3-ITD mutations. Two (3%) of 72 tested patients had double CEBPA mutations. Data on response to intensive anthracycline-based induction therapy were available for 119 patients. Complete remission was achieved in 67% (n=80) and the early death rate was 5% (n=6). Notably, patients with trisomy 4 as sole abnormality had a complete remission rate of 89%. Allogeneic hematopoietic cell transplantation was performed in 40 (34%) patients, of whom 19 were transplanted in first complete remission. The median follow-up of the intensively treated cohort was 5.76 years (95% confidence interval [95% CI]: 2.99-7.61 years). The 5-year overall survival and relapse-free survival rates were 30% (95% CI: 22-41%) and 27% (95% CI: 18-41%), respectively. An Andersen-Gill regression model on overall survival revealed that favorable-risk according to the European LeukemiaNet classification (hazard ratio [HR]=0.34; P=0.006) and trisomy 4 as sole abnormality (HR=0.41; P=0.01) were favorable factors, whereas age with a difference of 10 years (HR=1.15; P=0.11), female gender (HR=0.74; P=0.20) and allogeneic hematopoietic cell transplantation (HR=0.64; P=0.14) did not have an significant impact. In our cohort, patients with trisomy 4 as their sole abnormality had a high complete remission rate and favorable clinical outcome. Allogeneic hematopoietic cell transplantation did not seem to improve overall survival.
CRIS-Team Scopus Importer:2023-01-13

Characteristics and outcome of patients with low-/intermediate-risk acute promyelocytic leukemia treated with arsenic trioxide: an international collaborative - Kayser, Sabine; Schlenk, Richard F.; Lebon, Delphine; Carre, Martin; Goetze, Katharina S.; Stoelzel, Friedrich; Berceanu, Ana; Schaefer-Eckart, Kerstin; Peterlin, Pierre; Hicheri, Yosr; Rahme, Ramy; Raffoux, Emmanuel; et al. (Haematologica, 2021)
The aim of this study was to characterize a large series of 154 patients with acute promyelocytic leukemia (median age, 53 years; range, 18-90 years) and evaluate real-life outcome after up-front treatment with arsenic trioxide and all-trans retinoic acid. All patients were included in the prospective NAPOLEON registry (NCT02192619) between 2013 and 2019. The acute promyelocytic leukemia was de novo in 91% (n=140) and therapy-related in 9% (n=14); 13% (n=20) of the patients were older than 70 years. At diagnosis bleeding/hemorrhage was present in 38% and thrombosis in 3%. Complete remission was achieved in 152 patients (99%), whereas two patients (1%) experienced induction death within 18 days after starting therapy. With a median follow-up of 1.99 years (95% confidence interval: 1.61-2.30 years) 1-year and 2-year overall survival rates were 97% (95% confidence interval: 94-100%) and 95% (95% confidence interval: 91-99%), respectively. Age above 70 years was associated with a significantly shorter overall survival (P<0.001) compared to that of younger patients. So far no relapses have been observed. Six patients (4%) died in complete remission at a median of 0.95 years after diagnosis (range, 0.18-2.38 years). Our data confirm the efficiency and durability of arsenic trioxide and all-trans retinoic acid therapy in the primary management of adults with low-/intermediate-risk acute promyelocytic leukemia in the real-life setting, irrespective of age.
CRIS-Team WoS Importer:2021-12-31

Characteristics of donor-specific anti-HLA antibodies and outcome in renal transplant patients treated with a standardized induction regimen - Zecher, Daniel; Bach, Christian; Staudner, Christoph; Boeger, Carsten A.; Bergler, Tobias; Banas, Bernhard; Spriewald, Bernd M. (Nephrology Dialysis Transplantation, 2017)
Pre-transplant donor-specific anti-human leukocyte antigen (HLA) antibodies (DSA) have been associated with antibody-mediated rejection (AMR) and early kidney allograft loss. Uncertainties remain regarding the general applicability of these findings and the optimal induction therapy in DSA-positive patients.Pre-transplant sera from 174 patients receiving a crossmatch-negative kidney transplant were retrospectively analysed for DSA using Luminex technology. DSA with mean-fluorescence intensity (MFI) values above 500 were considered positive. All recipients received basiliximab induction and tacrolimus-based maintenance immunosuppression. DSA were monitored post-transplantation in patients with pre-transplant DSA. Antibody results were correlated with the incidence of rejection and graft loss.In total, 61/174 patients had pre-transplant DSA. We found a strong correlation between the presence of DSA against class I and II HLA and DSA MFI greater than 10 000. Both DSA patterns independently predicted an increased risk of early AMR (odds ratio 4.24 and 4.75, respectively, P < 0.05). The risk for AMR in patients with intermediate MFI (3000-10 000) gradually increased with increasing MFI but group sizes were too small to allow for final conclusions. The risk for AMR was comparable to nonsensitized patients in patients with only class I or II HLA-DSA or MFI below 3000. 5-year allograft survival was lowest in patients with simultaneous presence of class I and II HLA-DSA and MFI above 10 000 (45%) but was comparable between patients with only HLA class I or II or no DSA (90.0, 90.0 and 88.1%, respectively). AMR was the only independent predictor of graft loss. Undetectable DSA 14 days post-transplant predicted excellent long-term outcome.. The favourable outcome in the majority of DSA-positive patients despite non-depleting antibody induction and the poor outcome in patients with class I and II HLA-DSA and high DSA strength call for a differentiated therapeutic approach in this patient population.
EVALuna2:25766

Characterization and Manipulation of the Crosstalk Between Dendritic and Natural Killer Cells Within the Tumor Microenvironment - Jacobs, Benedikt; Gebel, Veronika; Heger, Lukas; Greze, Victoria; Schild, Hansjorg; Dudziak, Diana; Ullrich, Evelyn (Frontiers in Immunology, 2021)
Cellular therapy has entered the daily clinical life with the approval of CAR T cell therapeutics and dendritic cell (DCs) vaccines in the US and the EU. In addition, numerous other adoptive cellular products, including natural killer (NK) cells, are currently evaluated in early phase I/ II clinical trials for the treatment of cancer patients. Despite these promising accomplishments, various challenges remain to be mastered in order to ensure sustained therapeutic success. These include the identification of strategies by which tumor cells escape the immune system or establish an immunosuppressive tumor microenvironment (TME). As part of the innate immune system, DCs and NK cells are both present within the TME of various tumor entities. While NK cells are well known for their intrinsic anti-tumor activity by their cytotoxicity capacities and the secretion of pro-inflammatory cytokines, the role of DCs within the TME is a double-edged sword as different DC subsets have been described with either tumor-promoting or -inhibiting characteristics. In this review, we will discuss recent findings on the interaction of DCs and NK cells under physiological conditions and within the TME. One focus is the crosstalk of various DC subsets with NK cells and their impact on the progression or inhibition of tumor growth. In addition, we will provide suggestions to overcome the immunosuppressive outcome of the interaction of DCs and NK cells within the TME.
CRIS-Team Scopus Importer:2021-06-11
Keywords: cellular therapies; DC-NK cell interaction; dendritic cells; NK cells; tumor microenvironment

Characterization of CD4+ T cells primed and boosted by MHCII primary uveal melanoma cell-based vaccines. - Kittler, Julia; Sommer, Jonas; Fischer, Anika; Britting, Sabine; Karg, Margarete; Bock, Barbara; Atreya, Imke; Heindl, Ludwig M.; Mackensen, Andreas; Bosch, Jacobus J. (Oncotarget, 2019)
Uveal melanoma is the most common primary malignancy of the eye in adults. Despite significant improvements in treatment of the primary tumor, to date none of these therapies prevent metastatic disease or improve overall survival. We are exploring immunotherapeutic options for metastatic uveal melanoma using MHC II uveal melanoma cell-based vaccines that target the activation of tumor-reactive CD4+ T cells. Previously, we showed that these uveal melanoma cell-based vaccines activate CD4+ T cells within total peripheral blood lymphocytes (PBMC). Since PBMC include professional antigen presenting cells, we now demonstrate that Mel202/DR1/CD80 vaccine cells directly activate a diverse repertoire of purified, naïve CD4+ T cells. The activated CD4+ T cells proliferated, secreted high amounts of interferon gamma (IFNγ) and produced a heterogeneous profile of Th1, Th2 and Th17 cytokines. Analysis of the TCR-Vβ-repertoire showed that a polyclonal T cell response was induced, suggesting the capacity of vaccine-activated CD4+ T cells to target multiple tumor (neo)antigens. In addition, a subset of the responding CD4+ T cells expressed forkhead box protein P3 (FoxP3), indicating that although a regulatory component of the vaccine-activated CD4+ T cell response was induced, the anti-tumor vaccine response was not limited by these regulatory CD4+ T cells. Finally, Mel202/DR1/CD80 uveal melanoma vaccine cells expressed the intercellular adhesion molecule 1 (ICAM-1) that was pivotal for CD4+ T cell activation via lymphocyte function-associated antigen 1(LFA-1). In conclusion, MHC II uveal melanoma vaccines activate purified CD4+ T cells and may serve as a novel immunotherapy for uveal melanoma patients.
EVALuna2:184245
Keywords: uveal melanoma; tumor immunity; T cell activation; CD4+ T cells; ICAM-1

Characterization of CD4+ T cells primed and boosted by MHCII primary uveal melanoma cell-based vaccines - Kittler, Julia; Sommer, Jonas; Fischer, Anika; Britting, Sabine; Karg, Margarete; Bock, Barbara; Atreya, Imke; Heindl, Ludwig M.; Mackensen, Andreas; Bosch, Jacobus J. (Oncotarget, 2019)
Uveal melanoma is the most common primary malignancy of the eye in adults. Despite significant improvements in treatment of the primary tumor, to date none of these therapies prevent metastatic disease or improve overall survival. We are exploring immunotherapeutic options for metastatic uveal melanoma using MHC II uveal melanoma cell-based vaccines that target the activation of tumor-reactive CD4+ T cells. Previously, we showed that these uveal melanoma cell-based vaccines activate CD4+ T cells within total peripheral blood lymphocytes (PBMC). Since PBMC include professional antigen presenting cells, we now demonstrate that Mel202/ DR1/CD80 vaccine cells directly activate a diverse repertoire of purified, naïve CD4+ T cells. The activated CD4+ T cells proliferated, secreted high amounts of interferon gamma (IFNγ) and produced a heterogeneous profile of Th1, Th2 and Th17 cytokines. Analysis of the TCR-Vβ-repertoire showed that a polyclonal T cell response was induced, suggesting the capacity of vaccine-activated CD4+ T cells to target multiple tumor (neo)antigens. In addition, a subset of the responding CD4+ T cells expressed forkhead box protein P3 (FoxP3), indicating that although a regulatory component of the vaccine-activated CD4+ T cell response was induced, the anti-tumor vaccine response was not limited by these regulatory CD4+ T cells. Finally, Mel202/DR1/CD80 uveal melanoma vaccine cells expressed the intercellular adhesion molecule 1 (ICAM-1) that was pivotal for CD4+ T cell activation via lymphocyte function-associated antigen 1(LFA-1). In conclusion, MHC II uveal melanoma vaccines activate purified CD4+ T cells and may serve as a novel immunotherapy for uveal melanoma patients.
CRIS-Team Scopus Importer:2019-06-07
Keywords: CD4+ T cells; ICAM-1; T cell activation; Tumor immunity; Uveal melanoma

Characterizing the Immunogenicity of DM-Sensitive and DM-Resistant Antigens - Bernhardt, Anna Luise; Kretschmann, Sascha; Bausenwein, Judith; Balzer, Heidi; Mackensen, Andreas; Kremer, Anita (BLOOD, 2018)
CRIS-Team WoS Importer:2019-02-27

Chemoimmunotherapy with methotrexate, cytarabine, thiotepa, and rituximab (MATRix regimen) in patients with primary CNS lymphoma: results of the first randomisation of the International Extranodal Lymphoma Study Group-32 (IELSG32) phase 2 trial - Ferreri, Andres J. M.; Cwynarski, Kate; Pulczynski, Elko; Ponzoni, Mourilio; Deckert, Martina; Politi, Letterio S.; Torri, Valter; Fox, Christopher P.; La Rosee, Paul; Schorb, Elisabeth; Ambrosetti, Achille; Roth, Alexander; et al. (Lancet Haematology, 2016)
Standard treatment for patients with primary CNS lymphoma remains to be defined. Active therapies are often associated with increased risk of haematological or neurological toxicity. In this trial, we addressed the tolerability and efficacy of adding rituximab with or without thiotepa to methotrexate-cytarabine combination therapy (the MATRix regimen), followed by a second randomisation comparing consolidation with whole-brain radiotherapy or autologous stem cell transplantation in patients with primary CNS lymphoma. We report the results of the first randomisation in this Article.For the international randomised phase 2 International Extranodal Lymphoma Study Group-32 (IELSG32) trial, HIV-negative patients (aged 18-70 years) with newly diagnosed primary CNS lymphoma and measurable disease were enrolled from 53 cancer centres in five European countries (Denmark, Germany, Italy, Switzerland, and the UK) and randomly assigned (1:1:1) to receive four courses of methotrexate 3·5 g/m(2) on day 1 plus cytarabine 2 g/m(2) twice daily on days 2 and 3 (group A); or the same combination plus two doses of rituximab 375 mg/m(2) on days -5 and 0 (group B); or the same methotrexate-cytarabine-rituximab combination plus thiotepa 30 mg/m(2) on day 4 (group C), with the three groups repeating treatment every 3 weeks. Patients with responsive or stable disease after the first stage were then randomly allocated between whole-brain radiotherapy and autologous stem cell transplantation. A permuted blocks randomised design (block size four) was used for both randomisations, and a computer-generated randomisation list was used within each stratum to preserve allocation concealment. Randomisation was stratified by IELSG risk score (low vs intermediate vs high). No masking after assignment to intervention was used. The primary endpoint of the first randomisation was the complete remission rate, analysed by modified intention to treat. This study is registered with ClinicalTrials.gov, number NCT01011920.Between Feb 19, 2010, and Aug 27, 2014, 227 eligible patients were recruited. 219 of these 227 enrolled patients were assessable. At median follow-up of 30 months (IQR 22-38), patients treated with rituximab and thiotepa had a complete remission rate of 49% (95% CI 38-60), compared with 23% (14-31) of those treated with methotrexate-cytarabine alone (hazard ratio 0·46, 95% CI 0·28-0·74) and 30% (21-42) of those treated with methotrexate-cytarabine plus rituximab (0·61, 0·40-0·94). Grade 4 haematological toxicity was more frequent in patients treated with methotrexate-cytarabine plus rituximab and thiotepa, but infective complications were similar in the three groups. The most common grade 3-4 adverse events in all three groups were neutropenia, thrombocytopenia, anaemia, and febrile neutropenia or infections. 13 (6%) patients died of toxicity.With the limitations of a randomised phase 2 study design, the IELSG32 trial provides a high level of evidence supporting the use of MATRix combination as the new standard chemoimmunotherapy for patients aged up to 70 years with newly diagnosed primary CNS lymphoma and as the control group for future randomised trials.Associazione Italiana del Farmaco, Cancer Research UK, Oncosuisse, and Swiss National Foundation.
EVALuna2:25743

Choosing wisely recommendations in hematology and oncology - Krause, Stefan; Neubauer, A. (Internist, 2017)
Many new diagnostic and therapeutic options have been introduced in the field of hematology and medical oncology during recent years. Rational treatment recommendations are thus of even greater importance. Five presumably underused measures are recommended (positive recommendations), primarily pertaining to supportive therapy, but also concerning the selective use of molecular diagnostics. Recommendations to avoid unnecessary procedures (negative recommendations) involve a possible excessive use of anticancer therapy and imaging, and insufficiently selective use of growth factors, antiemetics, and targeted therapies.
EVALuna2:25763

Circulating Adaptive Immune Cells Expressing the Gut Homing Marker α4β7 Integrin Are Decreased in COVID-19 - Müller, Tanja; Becker, Elisabeth; Wiendl, Maximilian; Schulze, Lisa; Voskens, Caroline; Kremer, Andreas; Neurath, Markus; Zundler, Sebastian; Völkl, Simon (Frontiers in Immunology, 2021)
Background: Infection with the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes a wide range of symptoms including gastrointestinal manifestations, and intestinal epithelial cells are a target of the virus. However, it is unknown how the intestinal immune system contributes to systemic immune responses in coronavirus disease 2019 (COVID-19). Methods: We characterized peripheral blood lymphocytes from patients with active COVID-19 and convalescent patients as well as healthy controls by flow cytometry. Results: The frequency and absolute number of circulating memory T and B cells expressing the gut homing integrin α4β7 integrin was reduced during COVID-19, whether gastrointestinal symptoms were present or not. While total IgA-expressing B cells were increased, gut-imprinted B cells with IgA expression were stable. Conclusion: COVID-19 is associated with a decrease in circulating adaptive immune cells expressing the key gut homing marker α4β7 suggesting that these cells are preferentially recruited to extra-intestinal tissues independently of α4β7 or that the systemic immune response against SARS-CoV-2 is at least numerically dominated by extraintestinal, particularly pulmonary, immune cell priming.
CRIS-Team Scopus Importer:2021-05-21
Keywords: COVID-19; gut homing; integrins; SARS-CoV-2 infection; T cell trafficking

Circulating Tumor DNA in Head and Neck Squamous Cell Carcinoma - Brandt, Anna; Thiele, Benjamin; Schultheiß, Christoph; Daetwyler, Eveline; Binder, Mascha (Cancers, 2023)
Tumors shed cell-free DNA (cfDNA) into the plasma. “Liquid biopsies” are a diagnostic test to analyze cfDNA in order to detect minimal residual cancer, profile the genomic tumor landscape, and monitor cancers non-invasively over time. This technique may be useful in patients with head and neck squamous cell carcinoma (HNSCC) due to genetic tumor heterogeneity and limitations in imaging sensitivity. However, there are technical challenges that need to be overcome for the widespread use of liquid biopsy in the clinical management of these patients. In this review, we discuss our current understanding of HNSCC genetics and the role of cfDNA genomic analyses as an emerging precision diagnostic tool.
CRIS-Team Scopus Importer:2023-04-28
Keywords: cell-free DNA (cfDNA); head and neck squamous cell carcinoma (HNSCC); liquid biopsy; monitoring; prognostication; resistance

Citrullination licenses calpain to decondense nuclei in neutrophil extracellular trap formation - Goesswein, Stefanie; Lindemann, Aylin; Mahajan, Aparna; Maueröder, Christian; Martini, Eva; Patankar, Jay; Schett, Georg; Becker, Christoph; Wirtz, Stefan; Naumann-Bartsch, Nora; Bianchi, Marco E.; Greer, Peter A.; et al. (Frontiers in Immunology, 2019)
Neutrophils respond to various stimuli by decondensing and releasing nuclear chromatin characterized by citrullinated histones as neutrophil extracellular traps (NETs). This achieves pathogen immobilization or initiation of thrombosis, yet the molecular mechanisms of NET formation remain elusive. Peptidyl arginine deiminase-4 (PAD4) achieves protein citrullination and has been intricately linked to NET formation. Here we show that citrullination represents a major regulator of proteolysis in the course of NET formation. Elevated cytosolic calcium levels trigger both peptidylarginine deiminase-4 (PAD4) and calpain activity in neutrophils resulting in nuclear decondensation typical of NETs. Interestingly, PAD4 relies on proteolysis by calpain to achieve efficient nuclear lamina breakdown and chromatin decondensation. Pharmacological or genetic inhibition of PAD4 and calpain strongly inhibit chromatin decondensation of human and murine neutrophils in response to calcium ionophores as well as the proteolysis of nuclear proteins like lamin B1 and high mobility group box protein 1 (HMGB1). Taken together, the concerted action of PAD4 and calpain induces nuclear decondensation in the course of calcium-mediated NET formation.
CRIS-Team Scopus Importer:2019-11-15
Keywords: Calpain; Cell death; Chromatin; Citrullination; Neutrophil; Nucleus; PAD4

CLDN6-specific CAR-T cells plus amplifying RNA vaccine in relapsed or refractory solid tumors: the phase 1 BNT211-01 trial - Mackensen, Andreas; Haanen, John B.A.G.; Koenecke, Christian; Alsdorf, Winfried; Wagner-Drouet, Eva; Borchmann, Peter; Heudobler, Daniel; Ferstl, Barbara; Klobuch, Sebastian; Bokemeyer, Carsten; Desuki, Alexander; Lüke, Florian; et al. (Nature Medicine, 2023)
The oncofetal antigen Claudin 6 (CLDN6) is highly and specifically expressed in many solid tumors, and could be a promising treatment target. We report dose escalation results from the ongoing phase 1/2 BNT211-01 trial evaluating the safety and feasibility of chimeric antigen receptor (CAR) T cells targeting the CLDN6 with or without a CAR-T cell-amplifying RNA vaccine (CARVac) at two dose levels (DLs) in relapsed/refractory CLDN6-positive solid tumors. The primary endpoints were safety and tolerability, maximum tolerated dose and recommended phase 2 dose (RP2D). Secondary endpoints included objective response rate (ORR) and disease control rate. We observed manageable toxicity, with 10 out of 22 patients (46%) experiencing cytokine release syndrome including one grade 3 event and 1 out of 22 (5%) with grade 1 immune effector cell-associated neurotoxicity syndrome. Dose-limiting toxicities occurred in two patients at the higher DL, resolving without sequelae. CAR-T cell engraftment was robust, and the addition of CARVac was well tolerated. The unconfirmed ORR in 21 evaluable patients was 33% (7 of 21), including one complete response. The disease control rate was 67% (14 of 21), with stable disease in seven patients. Patients with germ cell tumors treated at the higher DL exhibited the highest response rate (ORR 57% (4 of 7)). The maximum tolerated dose and RP2D were not established as the trial has been amended to utilize an automated manufacturing process. A repeat of the dose escalation is ongoing and will identify a RP2D for pivotal trials. ClinicalTrials.gov Identifier: NCT04503278 .
CRIS-Team Scopus Importer:2023-12-01

Clinical Characteristics and Outcome in IDH1/2 Mutant AML Patients - Analysis of 3898 Newly Diagnosed Patients with Acute Myeloid Leukemia - Middeke, Jan Moritz; Rollig, Christoph; Kramer, Michael; Kramer, Alwin; Bochtler, Tilman; Scholl, Sebastian; Hochhaus, Andreas; Jost, Edgar; Bruemmendorf, Tim H.; Naumann, Ralph; Steffen, Bjoern; Kunzmann, Volker; et al. (BLOOD, 2018)
CRIS-Team WoS Importer:2019-03-06

Clinical Evaluation of an Innovative Metal-Artifact-Reduction Algorithm in FD-CT Angiography in Cerebral Aneurysms Treated by Endovascular Coiling or Surgical Clipping - Eisenhut, Felix; Schmidt, Manuel; Kalik, Alexander; Struffert, Tobias; Feulner, Julian; Schlaffer, Sven-Martin; Manhart, Michael; Dörfler, Arnd; Lang, Stefan (Diagnostics, 2022)
Treated cerebral aneurysms (IA) require follow-up imaging to ensure occlusion. Metal artifacts complicate radiologic assessment. Our aim was to evaluate an innovative metal-artifact-reduction (iMAR) algorithm for flat-detector computed tomography angiography (FD-CTA) regarding image quality (IQ) and detection of aneurysm residua/reperfusion in comparison to 2D digital subtraction angiography (DSA). Patients with IAs treated by endovascular coiling or clipping underwent both FD-CTA and DSA. FD-CTA datasets were postprocessed with/without iMAR algorithm (MAR+/MAR−). Evaluation of all FD-CTA and DSA datasets regarding qualitative (IQ, MAR) and quantitative (coil package diameter/CPD) parameters was performed. Aneurysm occlusion was assessed for each dataset and compared to DSA findings. In total, 40 IAs were analyzed (ncoiling = 24; nclipping = 16). All iMAR+ datasets demonstrated significantly better IQ (pIQ coiling < 0.0001; pIQ clipping < 0.0001). iMAR significantly reduced the metal-artifact burden but did not affect the CPD. iMAR significantly improved the detection of aneurysm residua/reperfusion with excellent agreement with DSA (naneurysm detection MAR+/MAR−/DSA = 22/1/26). The iMAR algorithm significantly improves IQ by effective reduction of metal artifacts in FD-CTA datasets. The proposed algorithm enables reliable detection of aneurysm residua/reperfusion with good agreement to DSA. Thus, iMAR can help to reduce the need for invasive follow-up in treated IAs.
CRIS-Team Scopus Importer:2022-05-27
Keywords: cerebral aneurysm; endovascular coiling; flat-detector computed tomography angiography; metal-artifact-reduction algorithm; surgical clipping

Clinical-grade generation of peptide-stimulated CMV/EBV-specific T cells from G-CSF mobilized stem cell grafts - Gary, Regina; Aigner, Michael; Moi, Stephanie; Schaffer, Susann; Gottmann, Anja; Maas, Stefanie; Zimmermann, Robert; Zingsem, Jürgen; Strobel, Joachim; Mackensen, Andreas; Mautner, Josef; Moosmann, Andreas; et al. (Journal of Translational Medicine, 2018)
BACKGROUND: A major complication after allogeneic hematopoietic stem cell transplantation (aSCT) is the reactivation of herpesviruses such as cytomegalovirus (CMV) and Epstein-Barr virus (EBV). Both viruses cause significant mortality and compromise quality of life after aSCT. Preventive transfer of virus-specific T cells can suppress reactivation by re-establishing functional antiviral immune responses in immunocompromised hosts. METHODS: We have developed a good manufacturing practice protocol to generate CMV/EBV-peptide-stimulated T cells from leukapheresis products of G-CSF mobilized and non-mobilized donors. Our procedure selectively expands virus-specific CD8+ und CD4+ T cells over 9 days using a generic pool of 34 CMV and EBV peptides that represent well-defined dominant T-cell epitopes with various HLA restrictions. For HLA class I, this set of peptides covers at least 80% of the European population. RESULTS: CMV/EBV-specific T cells were successfully expanded from leukapheresis material of both G-CSF mobilized and non-mobilized donors. The protocol allows administration shortly after stem cell transplantation (d30+), storage over liquid nitrogen for iterated applications, and protection of the stem cell donor by avoiding a second leukapheresis. CONCLUSION: Our protocol allows for rapid and cost-efficient production of T cells for early transfusion after aSCT as a preventive approach. It is currently evaluated in a phase I/IIa clinical trial.
EVALuna2:34166

Clinical phenotypes of CAR-T-cell related hematotoxicity in relapsed/refractory large B-cell lymphoma - Rejeski, K.; Sesques, P.; Berger, C.; Jentzsch, L.; Mougiakakos, Dimitrios; Froelich, L.; Bucklein,; Blumenberg,; Schmidt, C.; Jallades, L.; Fehse, B.; Faul, C.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Clinical significance of panendoscopy in initial staging of oral squamous cell carcinoma and detection of synchronous second malignancies of the upper aerodigestive tract — Insights from a retrospective population-based cohort study - Spoerl, Steffen; Gerken, Michael; Chamilos, Christos; Spörl, Silvia; Fischer, René; Vielsmeier, Veronika; Künzel, Julian; Bohr, Christopher; Meier, Johannes K.; Ettl, Tobias; Reichert, Torsten E.; Spanier, Gerrit (Journal of Cranio-Maxillofacial Surgery, 2022)
The aim of this study was to examine the prevalence of synchronous upper aerodigestive tract (UAT) tumors within oral squamous cell carcinoma (OSCC) patients, and to specify distinct risk groups who benefit from panendoscopy. Definite clinical and pathohistological characteristics, as well as overall and recurrence-free survival (OAS and RFS, respectively) of OSCC patients with and without synchronous second UAT tumors, carcinomas in situ, or higher-grade dysplasia/metaplasia, were evaluated based on a retrospective population-based cohort study, including alignment with cancer registry data. Out of 727 included OSCC patients, 465 cases (64.0%) received panendoscopy. Among these, 18 UAT tumors were detected, all of which were linked to patients with a positive history of nicotine abuse. Every synchronous UAT tumor was revealed by panendoscopy, which, analyzed as an independent staging procedure, was accompanied by a low complication rate (1.7%). When illuminating the impact of a second UAT tumor in OSCC patients, survival analysis revealed reduced 5-year OAS (63.9% vs 43.5%, p = 0.010) and RFS (57.1% vs 32.4%, p = 0.016) for patients with a second oncology diagnosis of the UAT. Within the limitations of the study, it seems that panendoscopy should be performed in the majority of patients suffering from OSCC, because most of them have a history of smoking and drinking, which correlates with an increased risk of developing synchronous UAT tumors.
CRIS-Team Scopus Importer:2022-06-03
Keywords: Oral cancer; Oral squamous cell carcinoma; Panendoscopy; Risk factor; Staging; Synchronous second carcinoma; Upper aerodigestive tract

CLL-cell-mediated MDSC induction by exosomal miR-155 transfer is disrupted by vitamin D - Böttcher, Martin; Bruns, Heiko; Qorraj, M.; Fabri, M.; Jitschin, S.; Dindorf, J.; Busch, L.; Jitschin, R.; Mackensen, Andreas; Mougiakakos, Dimitrios (Leukemia, 2017)
EVALuna2:25753

CLL-cells induce IDOhi CD14+HLA-DRlo myeloid-derived suppressor cells that inhibit T-cell responses and promote TRegs - Jitschin, Regina; Braun, Martina; Büttner, Maike; Dettmer-Wilde, Katja; Bricks, Juliane; Berger, Jana; Eckart, Michael J.; Krause, Stefan; Oefner, Peter J.; Le Blanc, Katarina; Mackensen, Andreas; Mougiakakos, Dimitrios (Blood, 2014)
Myeloid-derived suppressor cells (MDSCs) represent a heterogeneous population that shares certain characteristics including an aberrant myeloid phenotype and the ability to suppress T cells. MDSCs have been predominantly studied in malignant diseases and findings suggest involvement in tumor-associated immune suppression. Chronic lymphocytic leukemia (CLL) is the leukemia with the highest incidence among adults. Immune defects occur already at early disease stages and impact the clinical course. We assessed presence, frequency, association to other immune parameters, and functional properties of circulating CD14(+) cells lacking HLA-DR expression (HLA-DR(lo)) in patients with untreated CLL. These monocytic cells represent one of the best-defined human MDSC subsets. Frequency of CD14(+)HLA-DR(lo) cells was significantly increased in CLL patients. Furthermore, MDSCs suppressed in vitro T-cell activation and induced suppressive regulatory T cells (TRegs). The MDSC-mediated modulation of T cells could be attributed to their increased indoleamine 2,3-dioxygenase (IDO) activity. CLL cells induced IDO(hi) MDSCs from healthy donor monocytes suggesting bidirectional crosstalk between CLL-cells, MDSCs, and TRegs. Overall, we identified a MDSC population that expands in CLL. The exact mechanisms responsible for such accumulation remain to be elucidated and it will be of interest to test whether antagonizing suppressive functions of CLL MDSCs could represent a mean for enhancing immune responses.
EVALuna2:25463

CLL-Derived Extracellular Vesicles Impair T-Cell Activation and Foster T-Cell Exhaustion via Multiple Immunological Checkpoints - Boettcher, Martin; Boettcher-Loschinski, Romy; Kahlfuss, Sascha; Aigner, Michael; Gießl, Andreas; Mackensen, Andreas; Schlötzer-Schrehardt, Ursula; Tueting, Thomas; Bruns, Heiko; Mougiakakos, Dimitrios (Cells, 2022)
Background: Chronic lymphocytic leukemia (CLL) is characterized by the clonal expansion of malignant B-cells and multiple immune defects. This leads, among others, to severe infectious complications and inefficient immune surveillance. T-cell deficiencies in CLL include enhanced immune(-metabolic) exhaustion, impaired activation and cytokine production, and immunological synapse malformation. Several studies have meanwhile reported CLL-cell-T-cell interactions that culminate in T-cell dysfunction. However, the complex entirety of their interplay is incompletely understood. Here, we focused on the impact of CLL cell-derived vesicles (EVs), which are known to exert immunoregulatory effects, on T-cell function. Methods: We characterized EVs secreted by CLL-cells and determined their influence on T-cells in terms of survival, activation, (metabolic) fitness, and function. Results: We found that CLL-EVs hamper T-cell viability, proliferation, activation, and metabolism while fostering their exhaustion and formation of regulatory T-cell subsets. A detailed analysis of the CLL-EV cargo revealed an abundance of immunological checkpoints (ICs) that could explain the detected T-cell dysregulations. Conclusions: The identification of a variety of ICs loaded on CLL-EVs may account for T-cell defects in CLL patients and could represent a barrier for immunotherapies such as IC blockade or adoptive T-cell transfer. Our findings could pave way for improving antitumor immunity by simultaneously targeting EV formation or multiple ICs.
CRIS-Team Scopus Importer:2022-08-12
Keywords: cellular therapy; chronic lymphocytic leukemia; extracellular vesicles; immune checkpoints; immune evasion; T-cells

Clofarabine salvage therapy before allogeneic hematopoietic stem cell transplantation in patients with relapsed or refractory AML: results of the BRIDGE trial - Middeke, J. M.; Herbst, R.; Parmentier, S.; Bug, G.; Haenel, M.; Stuhlers, G.; Schaefer-Eckart, K.; Rösler, Wolf; Klein, S.; Bethge, W.; Bitz, U.; Buettner, B.; et al. (Leukemia, 2016)
In patients with relapsed or refractory (r/r) acute myeloid leukemia (AML), long-term disease control can only be achieved by allogeneic hematopoietic stem cell transplantation (HSCT). We studied the safety and efficacy of clofarabine-based salvage therapy. The study was designed as phase II, multicenter, intent-to-transplant (ITT) study. A total of 84 patients with r/r AML were enrolled. All patients received at least one cycle of CLARA (clofarabine 30 mg/m(2) and cytarabine 1 g/m(2), days 1-5). Chemo-responsive patients with a donor received HSCT in aplasia after first CLARA. Generally, HSCT was performed as soon as possible. The conditioning regimen consisted of clofarabine (4 × 30 mg/m(2)) and melphalan (140 mg/m(2)). The median patient age was 61 years (range 40-75). On day 15 after start of CLARA, 26% of patients were in a morphologically leukemia-free state and 79% exposed a reduction in bone marrow blasts. Overall, 67% of the patients received HSCT within the trial. The primary end point, defined as complete remission after HSCT, was achieved by 60% of the patients. According to the ITT, overall survival at 2 years was 43% (95% confidence interval (CI), 32-54%). The 2-year disease-free survival for transplanted patients was 52% (95% CI, 40-69%). Clofarabine-based salvage therapy combined with allogeneic HSCT in aplasia shows promising results in patients with r/r AML.
EVALuna2:25728

CMV INFECTION WITH SIGHT THREATENING CMV RETINITIS REFRACTORY TO CONVENTIONAL TREATMENT: SALVAGE THERAPY WITH AUTOLOGOUS CMV-SPECIFIC T CELLS - A CASE REPORT - Herrmann, Markus; Gary, Regina; Bosch, J.; Winkler, Julia; Schiffer, Mario; Opgenoorth, M. (TRANSPLANT INTERNATIONAL, 2019)
CRIS-Team WoS Importer:2019-10-29

Coexpressed Catalase Protects Chimeric Antigen Receptor-Redirected T Cells as well as Bystander Cells from Oxidative Stress-Induced Loss of Antitumor Activity - Ligtenberg, Maarten A.; Mougiakakos, Dimitrios; Mukhopadhyay, Madhura; Witt, Kristina; Lladser, Alvaro; Chmielewski, Markus; Riet, Tobias; Abken, Hinrich; Kiessling, Rolf (Journal of Immunology, 2016)
Treatment of cancer patients by adoptive T cell therapy has yielded promising results. In solid tumors, however, T cells encounter a hostile environment, in particular with increased inflammatory activity as a hallmark of the tumor milieu that goes along with abundant reactive oxygen species (ROS) that substantially impair antitumor activity. We present a strategy to render antitumor T cells more resilient toward ROS by coexpressing catalase along with a tumor specific chimeric Ag receptor (CAR) to increase their antioxidative capacity by metabolizing H2O2. In fact, T cells engineered with a bicistronic vector that concurrently expresses catalase, along with the CAR coexpressing catalase (CAR-CAT), performed superior over CAR T cells as they showed increased levels of intracellular catalase and had a reduced oxidative state with less ROS accumulation in both the basal state and upon activation while maintaining their antitumor activity despite high H2O2 levels. Moreover, CAR-CAT T cells exerted a substantial bystander protection of nontransfected immune effector cells as measured by CD3? chain expression in bystander T cells even in the presence of high H2O2 concentrations. Bystander NK cells, otherwise ROS sensitive, efficiently eliminate their K562 target cells under H2O2-induced oxidative stress when admixed with CAR-CAT T cells. This approach represents a novel means for protecting tumor-infiltrating cells from tumor-associated oxidative stress-mediated repression.
EVALuna2:25735

Combination of lenalidomide and vitamin D enhances MOR202-mediated cytotoxicity of macrophages: It takes three to tango - Flamann, Cindy; Busch, Leonhard; Mackensen, Andreas; Bruns, Heiko (Oncotarget, 2019)
EVALuna2:184244

Comorbidities Are Frequent in Older Patients with De Novo Acute Lymphoblastic Leukemia (ALL) and Correlate with Induction Mortality: Analysis of More Than 1200 Patients from GMALL Data Bases - Wermann, Wiba Keke; Viardot, Andreas; Kayser, Sabine; Alakel, Nael; Elmaagacli, Ahmet; Faul, Christoph; Fiedler, Walter; Horst, Heinz A.; Lange, Elisabeth; Martin, Sonja; Mohamed, Omar; Morgner, Anke; et al. (BLOOD, 2018)
CRIS-Team WoS Importer:2019-03-06

Comparing the Hem- and Lymphangiogenic Profile of Conjunctival and Uveal Melanoma Cell Lines - Refaian, Nasrin; Schlereth, Simona L.; Koch, Konrad R.; Notara, Maria; Hos, Deniz; Mescher, Melina; Iden, Sandra; Bosch, Jacobus J.; Jager, Martine J.; Cursiefen, Claus; Heindl, Ludwig M. (Investigative Ophthalmology & Visual Science, 2015)
Malignant melanomas of the ocular surface (conjunctival melanoma [CM]) and within the eye (uveal melanoma [UM]) show different types of metastatic behavior. While CM has a propensity to spread first to regional lymph nodes, UM metastasizes almost exclusively via the hematogenic route to the liver. We investigated whether these different metastatic patterns might be attributable to differential hem- and lymphangiogenic characteristics of CM and UM cells.Human CM (CM2005.1, CRMM1, CRMM2) and UM (Mel270, Mel290, OM431) cell lines were analyzed for VEGF-A, -C, and -D expression by RT-PCR and ELISA. The influence of CM- or UM-conditioned medium on blood (BEC) and lymphatic (LEC) endothelial cell proliferation and migration was measured using 3-[4,5-dimethylthiazol-2yl]-2,5-diphenyl-tetrazolium bromide (MTT) and scratch assays, respectively.Vascular endothelial growth factor-A, -C and -D mRNA, and VEGF-A and -D protein were expressed by all CM and UM cell lines, while VEGF-C protein was only expressed by UM cell lines. The CM- and UM-conditioned medium did neither differentially affect BEC (P = 0.86) and LEC (P = 0.90) proliferation, nor BEC (P = 0.56) and LEC (P = 0.90) migration.Conjunctival melanoma cell lines did not show a higher prolymphangiogenic potential, and UM cell lines did not show a higher prohemangiogenic potential. Accordingly, other mechanisms within the tumor microenvironment might account for the diverging metastatic patterns of conjunctival versus uveal melanomas.
EVALuna2:25718

Comparison of automated differential blood cell counts from abbott sapphire, siemens advia 120, beckman coulter DxH 800, and sysmex XE-2100 in normal and pathologic samples - Meintker, Lisa; Ringwald, Juergen; Rauh, Manfred; Krause, Stefan (American Journal of Clinical Pathology, 2013)
Reliable automated blood cell characterization and quantification remain challenging in pathologic samples, whereas slide reviews due to unnecessary flagging should be avoided. We compared 4 modern hematology analyzers-Abbott Sapphire, Siemens Advia 120, Sysmex XE-2100, and Beckman Coulter DxH 800-regarding complete blood cell count (CBC), leukocyte differential count, and flagging efficacy in a total of 202 samples from hematology patients and normal controls. Manual differential count was used as reference. The analyzers exhibited very good correlation for CBC parameters. Neutrophils and eosinophils also showed very good correlations, whereas lymphocytes and monocytes correlated fairly. The Advia 120 displayed notably lower measurements for both parameters, which is attributable to classification of some events as large unstained cells. Basophil counts were unreliable with all analyzers. Flagging for blasts and immature granulocytes showed moderate sensitivity and specificity. Operators must not rely on blast flagging alone to detect leukemic samples with any analyzer. © American Society for Clinical Pathology.
Created from Fastlane, Scopus look-up
Keywords: Automated blood cell count; Blasts; Flag; Immature granulocytes; Leukocyte differential count

Comparison of clinical outcome variables in patients with and without etomidate-facilitated anesthesia induction ahead of major cardiac surgery: a retrospective analysis - Heinrich, Stefan; Schmidt, Joachim; Ackermann, Andreas; Moritz, Andreas; Harig, Frank; Castellanos, Ixchel (Critical Care, 2014)
It is well known that etomidate may cause adrenal insufficiency. However, the clinical relevance of adrenal suppression after a single dose of etomidate remains vague. The aim of this study was to investigate the association between the administration of a single dose of etomidate or an alternative induction regime ahead of major cardiac surgery and clinical outcome parameters associated with adrenal suppression and onset of sepsis.The anesthesia and intensive care unit (ICU) records from patients undergoing cardiac surgery over five consecutive years (2008 to 2012) were retrospectively analyzed. The focus of the analysis was on clinical parameters like mortality, ventilation hours, renal failure, and sepsis-linked serum parameters. Multivariate analysis and Cox regression were applied to derive the results.In total, 3,054 patient records were analyzed. A group of 1,775 (58%) patients received a single dose of etomidate; 1,279 (42%) patients did not receive etomidate at any time. There was no difference in distribution of age, American Society of Anesthesiologists physical score, duration of surgery, and Acute Physiology and Chronic Health Evaluation II score. Postoperative data showed no significant differences between the two groups in regard to mortality (6.8% versus 6.4%), mean of mechanical ventilation hours (21.2 versus 19.7), days in the ICU (2.6 versus 2.5), hospital days (18.7 versus 17.4), sepsis-associated parameters, Sequential Organ Failure Assessment score, and incidence of renal failure. Administration of etomidate showed no significant influence (P = 0.6) on hospital mortality in the multivariate Cox analysis.This study found no evidence for differences in key clinical outcome parameters based on anesthesia induction with or without administration of a single dose of etomidate. In consequence, etomidate might remain an acceptable option for single-dose anesthesia induction.
EVALuna2:16090

Comparison of Gvhd Biomarker Algorithms for Predicting Lethal Gvhd and Non-Relapse Mortality - Etra, Aaron; Gergoudis, Stephanie; Morales, George; Kowalyk, Steven; Lin, Jung-Yi; Shah, Jay; Kapoor, Urvi; Aziz, Mina; Pawarode, Attaphol; Ayuk, Francis; Holler, Ernst; Choe, Hannah; et al. (BIOLOGY OF BLOOD AND MARROW TRANSPLANTATION, 2019)
CRIS-Team WoS Importer:2021-10-18

Comparison of HLA-mismatched unrelated donor transplantation with post-transplant cyclophosphamide versus HLA-haploidentical transplantation in patients with active acute myeloid leukemia - Baron, Frederic; Labopin, Myriam; Tischer, Johanna; Ciceri, Fabio; Raiola, Anna Maria; Blaise, Didier; Sica, Simona; Vydra, Jan; Fanin, Renato; Diez-Martin, Jose Luis; Bulabois, Claude Eric; Stolzel, Friedrich; et al. (Bone Marrow Transplantation, 2022)
HLA-haploidentical allogeneic hematopoietic stem cell transplantation (Haplo-HCT) is frequently used as treatment for patients with active acute myeloid leukemia (AML). Here, we investigated whether 9/10 HLA-mismatched unrelated donor transplantation (MMUD-HCT) with post-transplant cyclophosphamide (PTCy) is an adequate alternative. Inclusion criteria in this retrospective registry study consisted of adult patients, first HCT with a Haplo donor or MMUD between 2010 and 2020 using PTCy as graft-versus-host disease (GVHD) prophylaxis, and primary refractory or relapsed disease. MMUD patients were pair-matched 1 to 2 with Haplo-recipients. A total of 73 MMUD patients met the inclusion criteria. Their data were compared to those of 146 Haplo patients in a matched-pair analysis. Median follow-up was 27 months in MMUD patients and 36 months in Haplo recipients. Two-year incidences of relapse and non-relapse mortality (NRM) were 40% and 18% in MMUD patients, respectively, versus 50% (P = 0.23) and 24% (P = 0.18) in Haplo recipients. Two-year leukemia-free survival (LFS) and overall survival (OS) was 42% and 46% in MMUD recipients, respectively, versus 26% (P = 0.1) and 28% (P = 0.061) in Haplo-patients. In conclusions, in AML patients with active disease at transplantation, MMUD-HCT results in at least comparable outcomes to Haplo-HCT when PTCy is applied.
CRIS-Team Scopus Importer:2022-09-02

Comparison of leukemia-associated immunophenotype (LAIP)-based and different-from-normal (DfN)-based analysis of measurable residual disease (MRD) in patients with AML - Von Bonin, M.; Buecklein, V.; Krause, S.; Voelkl, S.; Rieger, M.; Berg, T.; Brendel, C.; Hoffmann, J.; Kramer, M.; Roehnert, M.; Oelschlaegel, U.; Subklewe, M. (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Comparison of Metal and Plastic Disposable Laryngoscope Blade with Reusable Macintosh Blade in Difficult and Inhalation Injury Airway Scenario: A Manikin Study - Moritz, Andreas; Heinrich, Stefan; Irouschek, Andrea; Birkholz, Torsten; Prottengeier, Johannes; Schmidt, Joachim (Journal of Emergency Medicine, 2017)
Single-use plastic blades (SUPB) and single-use metal blades (SUMB) for direct laryngoscopy and tracheal intubation have not yet been compared with reusable metal blades (RUMB) in difficult airway scenarios.The purpose of our manikin study was to compare the effectiveness of these different laryngoscope blades in a difficult airway scenario, as well as in a difficult airway scenario with simulated severe inhalation injury.Thirty anesthetists performed tracheal intubation (TI) with each of the three laryngoscope blades in the two scenario manikins.In the inhalation injury scenario, SUPB were associated with prolonged intubation times when compared with the metal blades. In the inhalation injury scenario, both metal laryngoscope blades provided a quicker, easier, and safer TI. In the difficult airway scenario, intubation times were significantly prolonged in the SUPB group in comparison to the RUMB group, but there were no significant differences between the SUPB and the SUMB. In this scenario, the RUMB demonstrated the shortest intubation times and seems to be the most effective device.Generally, results are in line with previous studies showing significant disadvantages of SUPB in both manikin scenarios. Therefore, metal blades might be beneficial, especially in the airway management of patients with inhalation injury.
EVALuna2:16733

Complementary Medicine and Nursing in Oncology Development of evidence-based, symptom-related topic guidelines for interprofessional counseling of tumor patients - Kroeger, B.; Kaschdailewitsch, E.; Behzad, Ali; Schmitt, A.; Lohmueller, L.; Valentini, J.; Noack, B.; Froehlich, D.; Horneber, M.; Mahler, C.; Joos, S.; Stolz, R. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Contact-dependent depletion of hydrogen peroxide by catalase is a novel mechanism of myeloid-derived suppressor cell induction operating in human hepatic stellate cells - Resheq, Yazid J.; Li, Ka-Kit; Ward, Stephen T.; Wilhelm, Annika; Garg, Abhilok; Curbishley, Stuart M.; Blahova, Miroslava; Zimmermann, Henning W.; Jitschin, Regina; Mougiakakos, Dimitrios; Mackensen, Andreas; Weston, Chris J.; et al. (Journal of Immunology, 2015)
Myeloid-derived suppressor cells (MDSC) represent a unique cell population with distinct immunosuppressive properties that have been demonstrated to shape the outcome of malignant diseases. Recently, human hepatic stellate cells (HSC) have been reported to induce monocytic-MDSC from mature CD14(+) monocytes in a contact-dependent manner. We now report a novel and unexpected mechanism by which CD14(+)HLADR(low/-) suppressive cells are induced by catalase-mediated depletion of hydrogen peroxide (H2O2). Incubation of CD14(+) monocytes with catalase led to a significant induction of functional MDSC compared with media alone, and H2O2 levels inversely correlated with MDSC frequency (r = -0.6555, p < 0.05). Catalase was detected in primary HSC and a stromal cell line, and addition of the competitive catalase inhibitor hydroxylamine resulted in a dose-dependent impairment of MDSC induction and concomitant increase of H2O2 levels. The NADPH-oxidase subunit gp91 was significantly increased in catalase-induced MDSC as determined by quantitative PCR outlining the importance of oxidative burst for the induction of MDSC. These findings represent a so far unrecognized link between immunosuppression by MDSC and metabolism. Moreover, this mechanism potentially explains how stromal cells can induce a favorable immunological microenvironment in the context of tissue oxidative stress such as occurs during cancer therapy.
EVALuna2:25703

Control of PD-L1 expression in CLL-cells by stromal triggering of the Notch-c-Myc-EZH2 oncogenic signaling axis - Böttcher, Martin; Bruns, Heiko; Lu, Junyan; Chartomatsidou, E.; Papakonstantinou, N.; Mentz, K.; Büttner-Herold, Maike; Zenz, Thorsten; Herling, M.; Huber, Wolfgang; Ghia, P.; Stamatopoulos, Kostas; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Control of PD-L1 expression in CLL-cells by stromal triggering of the Notch-c-Myc-EZH2 oncogenic signaling axis - Böttcher, Martin; Bruns, Heiko; Völkl, Simon; Lu, Junyan; Chartomatsidou, Elisavet; Papakonstantinou, Nikos; Mentz, Kristin; Büttner-Herold, Maike; Zenz, Thorsten; Herling, Marco; Huber, Wolfgang; Ghia, Paolo; et al. (Journal for ImmunoTherapy of Cancer, 2021)
Chronic lymphocytic leukemia (CLL) is the most common leukemia in adults. Emerging data suggest that CLL-cells efficiently evade immunosurveillance. T-cell deficiencies in CLL include immuno(metabolic) exhaustion that is achieved by inhibitory molecules, with programmed cell death 1/programmed cell death ligand 1 (PD-L1) signaling emerging as a major underlying mechanism. Moreover, CLL-cells are characterized by a close and recurrent interaction with their stromal niches in the bone marrow and lymph nodes. Here, they receive nurturing signals within a well-protected environment. We could previously show that the interaction of CLL-cells with stroma leads to c-Myc activation that is followed by metabolic adaptations. Recent data indicate that c-Myc also controls expression of the immune checkpoint molecule PD-L1. Therefore, we sought out to determine the role of stromal contact for the CLL-cells' PD-L1 expression and thus their immuno-evasive phenotype.
CRIS-Team WoS Importer:2021-05-21

Correlation of mammographic density and serum calcium levels in patients with primary breast cancer - Hack, Carolin; Stoll, Martin; Jud, Sebastian; Heusinger, Katharina; Adler, Werner; Haeberle, Lothar; Ganslandt, Thomas; Heindl, Felix; Schulz-Wendtland, Rüdiger; Uder, Michael; Beckmann, Matthias; Fasching, Peter; et al. (Cancer Medicine, 2017)
Percentage mammographic breast density (PMD) is one of the most important risk factors for breast cancer (BC). Calcium, vitamin D, bisphosphonates, and denosumab have been considered and partly confirmed as factors potentially influencing the risk of BC. This retrospective observational study investigated the association between serum calcium level and PMD. A total of 982 BC patients identified in the research database at the University Breast Center for Franconia with unilateral BC, calcium and albumin values, and mammogram at the time of first diagnosis were included. PMD was assessed, using a semiautomated method by two readers. Linear regression analyses were conducted to investigate the impact on PMD of the parameters of serum calcium level adjusted for albumin level, and well-known clinical predictors such as age, body mass index (BMI), menopausal status and confounder for serum calcium like season in which the BC was diagnosed. Increased calcium levels were associated with reduced PMD (P = 0.024). Furthermore, PMD was inversely associated with BMI (P < 0.001) and age (P < 0.001). There was also an association between PMD and menopausal status (P < 0.001). The goodness-of-fit of the regression model was moderate. This is the first study assessing the association between serum calcium level and PMD. An inverse association with adjusted serum calcium levels was observed. These findings add to previously published data relating to vitamin D, bisphosphonates, denosumab, and the RANK/RANKL signaling pathway in breast cancer risk and prevention.
EVALuna2:175

Corrigendum to "Towards in vitro DT/DNT testing: Assaying chemical susceptibility in early differentiating NT2 cells" [Toxicology 338 (2015) 69-76]. - Menzner, Ann-Katrin; Abolpour Mofrad, Sepideh; Friedrich, Oliver; Gilbert, Daniel (Toxicology, 2017)

CREB1 is affected by the microRNAs miR-22-3p, miR-26a-5p, miR-27a-3p, and miR-221-3p and correlates with adverse clinicopathological features in renal cell carcinoma - Friedrich, Michael; Heimer, Nadine; Stoehr, Christine; Steven, André; Wach, Sven; Taubert, Helge; Hartmann, Arndt; Seliger, Barbara (Scientific Reports, 2020)
The transcription factor cAMP response element-binding protein (CREB1) has been shown to be involved in diverse biological pathways including the regulation of cell proliferation, apoptosis, cell cycle progression, and metastasis. In this context, aberrant expression of CREB1 and the functional consequences are well investigated in a number of hematopoietic and solid tumors. However, CREB1 expression and underlying control mechanisms are only poorly analyzed in renal cell carcinoma (RCC). The present study confirmed a deregulation of CREB1 protein in the clear cell type of RCC (ccRCC) and analysis of in-house ccRCC cell lines suggested a post-transcriptional control. The combination of miRNA enrichment assay, in silico analysis and molecular biological approaches revealed four novel CREB1-regulating miRNAs, namely miR-22-3p, miR-26a-5p, miR-27a-3p, and miR-221-3p. Categorizing RCC samples as CREB1 negative or positive, respectively, the expression of these miRNAs was found to be inversely correlated with CREB1 protein levels. Analyzing 453 consecutive RCC tumors by immunohistochemistry, weakly negative, but significant correlations of CREB1 with tumor stage and grade, vascular invasion (V1) and lymphovascular invasion (L1) were found. In this respect, ccRCC might differ from other solid tumors like esophageal squamous-cell carcinoma or glioma.
CRIS-Team Scopus Importer:2020-05-02

CXCL12 promotes glycolytic reprogramming in acute myeloid leukemia cells via the CXCR4/mTOR axis - Braun, Michael; Qorraj, M.; Büttner, Maike; Klein, F. A.; Saul, D.; Aigner, M.; Huber, W.; Mackensen, Andreas; Jitschin, R.; Mougiakakos, Dimitrios (Leukemia, 2016)
EVALuna2:25512

CXCR2 expression on neutrophil granulocytes in peripheral tumor is associated with shorter survival in oral squamous cell carcinoma - Spörl, Silvia; Erber, Ramona; Gerken, M.; Wittenberg, M.; Fischer, R.; Taxis, J.; Hartmann, Arndt; Geppert, Carol-Immanuel; Mamilos, A.; Mackensen, Andreas; Reichert, T.; Spanier, G.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Cytokine and reactivity profiles in SLE patients following anti-CD19 CART therapy - Nunez, Daniel; Patel, Darshil; Volkov, Jenell; Wong, Steven; Vorndran, Zachary; Müller, Fabian; Aigner, Michael; Völkl, Simon; Mackensen, Andreas; Schett, Georg; Basu, Samik (Molecular Therapy, 2023)
Chimeric antigen receptor (CAR) T cells targeting CD19+ B cells have demonstrated efficacy in refractory systemic lupus erythematosus (SLE). Although initial clinical data suggest that anti-CD19 CAR T cell therapy is well tolerated and highly effective, the immunologic consequences of CAR T cell therapy in SLE patients remain unclear. We profiled serum in six refractory SLE patients prior to and 3 months following CAR T cell infusion. Three months post T cell infusion, the inflammatory cytokines IL-6 and TNFα decreased in patient sera. This was accompanied by elevations in serum IL-7 and BAFF. Furthermore, SLE-associated antibodies dropped profoundly in five of six patients. Last, consistent with other reports of CD19 CAR T therapy in B cell malignancies, we were able to show marginal impact of anti-CD19 CART therapy on pre-existing humoral immune responses in SLE patients. Together, these results provide insights into the mechanisms of efficacy of anti-CD19 CAR T cell therapy in SLE.
CRIS-Team Scopus Importer:2023-09-29
Keywords: antibodies; autoimmune disease; CAR; chimeric antigen receptor T cell; cytokines; SLE; systemic lupus erythematous; vaccines

Cytokines in inflammatory bowel diseases – Update 2020 - Leppkes, Moritz; Neurath, Markus (Pharmacological research, 2020)
Inflammatory Bowel Diseases (IBD), namely Crohn's Disease and Ulcerative Colitis, cause a significant disease burden in modern civilization. Ever since the introduction of anti-TNF-directed therapies 20 years ago, cytokines have attracted a lot of research attention and several cytokine-directed therapies have been implemented in the clinical treatment of these diseases. The research progress in these past years has underlined the importance of both myeloid and lymphoid elements of the immune system in the pathogenesis of IBD and their cytokine-mediated interplay. The conceptual framework of the mucosal cytokine network has shifted during these years from a T helper (Th) dichotomy (Th1/Th2) to the effector/regulatory T cell balance, while nowadays, the importance of myeloid cell instruction of lymphocytes, namely by IL-12 and IL-23, is increasingly recognized. Anti-IL-12p40 agents, like ustekinumab, groundbreakingly changed patient care, and anti-IL23p19-directed approaches are on the verge of grand success. In this review we present a modular approach to understand the cytokine network and put it into the context of the pathogenesis of IBD with a special focus on publications since 2014.
CRIS-Team Scopus Importer:2020-06-09
Keywords: Biologicals; Crohn's disease; Cytokines; Gastroenterology; IBD; Ulcerative colitis

D-2-hydroxyglutarate interferes with HIF-1α stability skewing T-cell metabolism towards oxidative phosphorylation and impairing Th17 polarization - Böttcher, Martin; Renner, Kathrin; Berger, Raffaela; Mentz, Kristin; Thomas, Simone; Cardenas-Conejo, Zugey Elizabeth; Dettmer, Katja; Oefner, Peter J.; Mackensen, Andreas; Kreutz, Marina; Mougiakakos, Dimitrios (OncoImmunology, 2018)
D-2-hydroxyglutarate (D-2HG) is released by various types of malignant cells including acute myeloid leukemia (AML) blasts carrying isocitrate dehydrogenase (IDH) gain-of-function mutations. D-2HG acting as an oncometabolite promotes proliferation, anoikis, and differentiation block of hematopoietic cells in an autocrine fashion. However, prognostic impact of IDH mutations and high D-2HG levels remains controversial and might depend on the overall mutational context. An increasing number of studies focus on the permissive environment created by AML blasts to promote immune evasion. Impact of D-2HG on immune cells remains incompletely understood. Here, we sought out to investigate the effects of D-2HG on T-cells as key mediators of anti-AML immunity. D-2HG was efficiently taken up by T-cells in vitro, which is in line with high 2-HG levels measured in T-cells isolated from AML patients carrying IDH mutations. T-cell activation was slightly impacted by D-2HG. However, D-2HG triggered HIF-1a protein destabilization resulting in metabolic skewing towards oxidative phosphorylation, increased regulatory T-cell (Treg) frequency, and reduced T helper 17 (Th17) polarization. Our data suggest for the first time that D-2HG might contribute to fine tuning of immune responses.
EVALuna2:34274

Daratumomab for the treatment of relapsed multiple myeloma involving the central nervous system: a case report - Brandt, Adrian; Seuß, Hannes; Mackensen, Andreas; Rösler, Wolf (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Deceased Donor Kidney Transplantation in the Eurotransplant Senior Program (ESP): A Single-Center Experience from 2008 to 2013 - Jacobi, Johannes; Beckmann, Sophie; Heller, Katharina; Hilgers, Karl Friedrich; Apel, Hendrik; Spriewald, Bernd; Eckardt, Kai-Uwe; Amann, Kerstin Ute (Annals of Transplantation, 2016)
BACKGROUND The aim of this study was to evaluate the outcome after transplantation of deceased allografts in donor/recipient pairs aged >=65 years enrolled in the Eurotransplant Senior Program (ESP). MATERIAL AND METHODS In this retrospective cohort study we evaluated data from 89 patients transplanted under the ESP protocol from 2008 to 2013. Outcome parameters included graft and patient survival, rate of biopsy-proven acute rejections (BPAR), peri- and post-operative complications, tumor development, development of donor-specific antibodies (DSA), and the prognostic role of preimplantation biopsies. RESULTS One-year patient and allograft survival rates were 92.1% and 84.3%, respectively. During follow-up, 23 (26%) patients died; the major cause of death was sepsis, followed by cardiovascular events and malignancies. BPAR episodes were frequent within the first year ( 33%) and overall were less common in patients treated with tacrolimus. Post-transplant malignancies were seen in 15 (17%) patients. During follow-up, 16 (18%) patients developed DSA; patients with delayed graft function (DGF) were more likely to develop DSA (p=0.029). A higher preimplantation biopsy score was associated with DGF but did not predict later graft outcome. CONCLUSIONS The results highlight increased risks in ESP transplant candidates and the importance of careful surveillance of this patient group.
EVALuna2:3834

Deciphering the role of HLA-DO in immune responses after allogeneic stem cell transplantation - Zeun, Julia; Flamann, Cindy; Neubeck, S.; Bausenwein, J.; Seyler, L.; Vogler, T.; Brey, Stefanie; Büttner-Herold, Maike; Hildner, Kai; Winkler, Thomas; Bruns, Heiko; Kretschmann, S.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Deep Molecular Response Is Reached by the Majority of Patients Treated With Imatinib, Predicts Survival, and Is Achieved More Quickly by Optimized High-Dose Imatinib: Results From the Randomized CML-Study IV - Hehlmann, Rüdiger; Müller, Martin C.; Lauseker, Michael; Hanfstein, Benjamin; Fabarius, Alice; Schreiber, Annette; Proetel, Ulrike; Pletsch, Nadine; Pfirrmann, Markus; Haferlach, Claudia; Schnittger, Susanne; Einsele, Hermann; et al. (Journal of Clinical Oncology, 2014)
Deep molecular response (MR(4.5)) defines a subgroup of patients with chronic myeloid leukemia (CML) who may stay in unmaintained remission after treatment discontinuation. It is unclear how many patients achieve MR(4.5) under different treatment modalities and whether MR(4.5) predicts survival.Patients from the randomized CML-Study IV were analyzed for confirmed MR(4.5) which was defined as >= 4.5 log reduction of BCR-ABL on the international scale (IS) and determined by reverse transcriptase polymerase chain reaction in two consecutive analyses. Landmark analyses were performed to assess the impact of MR(4.5) on survival.Of 1,551 randomly assigned patients, 1,524 were assessable. After a median observation time of 67.5 months, 5-year overall survival (OS) was 90%, 5-year progression-free-survival was 87.5%, and 8-year OS was 86%. The cumulative incidence of MR(4.5) after 9 years was 70% (median, 4.9 years); confirmed MR(4.5) was 54%. MR(4.5) was reached more quickly with optimized high-dose imatinib than with imatinib 400 mg/day (P = .016). Independent of treatment approach, confirmed MR(4.5) at 4 years predicted significantly higher survival probabilities than 0.1% to 1% IS, which corresponds to complete cytogenetic remission (8-year OS, 92% v 83%; P = .047). High-dose imatinib and early major molecular remission predicted MR(4.5). No patient with confirmed MR(4.5) has experienced progression.MR(4.5) is a new molecular predictor of long-term outcome, is reached by a majority of patients treated with imatinib, and is achieved more quickly with optimized high-dose imatinib, which may provide an improved therapeutic basis for treatment discontinuation in CML.
EVALuna2:25682

Deficiency of Fhl2 leads to delayed neuronal cell migration and premature astrocyte differentiation - Kim, Soung Yung; Ludwig, Stephan; Schneider, Holm; Wixler, Viktor; Park, Jung; Völkl, Simon (Journal of Cell Science, 2019)
The four and a half LIM domains protein 2 (Fhl2) is an adaptor protein capable of mediating protein-protein interactions. Here, we report for the first time phenotypic changes in the brain of Fhl2-deficient mice. We showed that Fhl2 is expressed in neural stem cells, precursors and mature cells of neuronal lineage. Moreover, Fhl2 deficiency leads to delayed neuroblast migration in vivo, premature astroglial differentiation of neural stem cells (NSCs) in vitro, and a gliosis-like accumulation of glial fibrillary acidic protein (GFAP)-positive astrocytes in vivo that substantially increases with age. Collectively, Fhl2-deficiency in the brain interrupts the maintenance and the balanced differentiation of adult NSCs, resulting in preferentially glial differentiation and early exhaustion of the NSC pool required for adult neurogenesis.
CRIS-Team WoS Importer:2019-04-12

Defining therapy goals for major molecular remission in chronic myeloid leukemia: results of the randomized CML Study IV - Saussele, Susanne; Hehlmann, Ruediger; Fabarius, Alice; Jeromin, Sabine; Proetel, Ulrike; Rinaldetti, Sebastien; Kohlbrenner, Katharina; Einsele, Hermann; Falge, Christiane; Kanz, Lothar; Neubauer, Andreas; Kneba, Michael; et al. (Leukemia, 2018)
Major molecular remission (MMR) is an important therapy goal in chronic myeloid leukemia (CML). So far, MMR is not a failure criterion according to ELN management recommendation leading to uncertainties when to change therapy in CML patients not reaching MMR after 12 months. At monthly landmarks, for different molecular remission status Hazard ratios (HR) were estimated for patients registered to CML study IV who were divided in a learning and a validation sample. The minimum HR for MMR was found at 2.5 years with 0.28 (compared to patients without remission). In the validation sample, a significant advantage for progression-free survival (PFS) for patients in MMR could be detected (p-value 0.007). The optimal time to predict PFS in patients with MMR could be validated in an independent sample at 2.5 years. With our model we provide a suggestion when to define lack of MMR as therapy failure and thus treatment change should be considered. The optimal response time for 1% BCR-ABL at about 12-15 months was confirmed and for deep molecular remission no specific time point was detected. Nevertheless, it was demonstrated that the earlier the MMR is achieved the higher is the chance to attain deep molecular response later.
EVALuna2:35107

Definition of a New HLA B*52-Restricted Rev CTL Epitope Targeted by an HIV-1-Infected Controller - El Kenz, Boutaina; Schmidt, Katja; Ogungbemi-Alt, Victoria K.; Bergmann, Silke; Steininger, Philipp; Korn, Klaus; Spriewald, Bernd; Harrer, Ellen; Nganou-Makamdop, Krystelle; Harrer, Thomas (Viruses, 2023)
The analysis of T-cell responses in HIV-1-infected controllers may contribute to a better understanding of the protective components of the immune system. Here, we analyzed the HIV-1-specific T-cell response in a 59-year-old HIV-1-infected controller, infected for at least seven years, who presented with low viral loads ranging from <20 copies/mL to 200 copies/mL and normal CD4 counts of >800 cells/µL. In γ-IFN-ELISpot assays using freshly isolated PBMCs, he displayed a very strong polyclonal T-cell response to eight epitopes in Gag, Nef and Rev; with the dominant responses directed against the HLA-B*57-epitope AISPRTLNAW and against a so-far-unknown epitope within Rev. Further analyses using peptide-stimulated T-cell lines in γ-IFN-ELISpot assays delineated the peptide RQRQIRSI (Rev-RI8) as a newly defined HLA-B*52-restricted epitope located within a functionally important region of Rev. Peptide-stimulation assays in 15 HLA-B*52-positive HIV-1-infected subjects, including the controller, demonstrated recognition of the Rev-RI8 epitope in 6/15 subjects. CD4 counts before the start of antiviral therapy were significantly higher in subjects with recognition of the Rev-RI8 epitope. Targeting of the Rev-RI8 epitope in Rev by CTL could contribute to the positive association of HLA-B*52 with a more favorable course of HIV-1-infection.
CRIS-Team Scopus Importer:2023-03-10
Keywords: CTL; elite controller; epitope; HIV-1 infection; HLA B*52; Rev

Delayed therapy with clopidogrel and everolimus prevents progression of transplant arteriosclerosis and impairs humoral alloimmunity in murine aortic allografts - Heim, Christian; Eckl, Sebastian; Preidl, Raimund; Ramsperger-Gleixner, Martina; Koch, Nina; Goldmann, Katja; Spriewald, Bernd M.; Weyand, Michael; Ensminger, Stephan M. (European Journal of Cardio-Thoracic Surgery, 2015)
It was previously shown that the combination of clopidogrel and everolimus reduced the development of transplant arteriosclerosis. The aim of this study was to investigate whether delayed onset of treatment, similar to the clinical situation after heart transplantation, inhibits progression of transplant arteriosclerosis.Fully allogeneic C57BL/6 (H2-b) donor aortas were transplanted into CBA.J (H2-k) recipients treated with clopidogrel and everolimus alone or in combination starting on Days 1, 7 or 14. Grafts were analysed by histology and alloantibodies were detected by fluorescence activated cell sorting after transplantation.Delayed platelet inhibition with clopidogrel reduced the development of transplant arteriosclerosis [neointima formation (Day 14): 50 ± 4 vs 84 ± 9% (control)]. The combination of clopidogrel and everolimus almost abolished formation of transplant arteriosclerosis when therapy was started on Day 1 [neointima formation (Day 1): 14 ± 5 vs 84 ± 9% (control)] and also showed a remarkable reduction in both delayed treatment groups [neointima formation (Day 7): 24 ± 7 vs 84 ± 9% (control); neointima formation (Day 14): 28 ± 11 vs 84 ± 9% (control)]. Platelet inhibition alone and in combination with everolimus resulted in reduced alloantibody production.These results demonstrate that delayed treatment with clopidogrel and everolimus-representative of a clinical setting-prevents the progression of transplant arteriosclerosis and impairs humoral immunity in this experimental model.
EVALuna2:16087

Depletion of donor-specific anti-HLA A2 alloantibodies in a hematopoietic cell transplant recipient using directed mismatched platelet transfusions - Spriewald, Bernd M.; Bach, Christian; Zingsem, Jürgen; Strobel, Joachim; Winkler, Jürgen; Mackensen, Andreas; Rösler, Wolf (Bone Marrow Transplantation, 2018)
EVALuna2:34275

Design and Implementation of a Single Source Multipurpose Hospital-Wide Clinical Trial Registry - Sommer, Marcus; Kirchner, Melanie; Gulden, Christian; Egloffstein, Sainab; Lux, Michael P.; Beckmann, Matthias; Mackensen, Andreas; Prokosch, Hans-Ulrich (ICT FOR HEALTH SCIENCE RESEARCH, 2019)
CRIS-Team WoS Importer:2021-10-18

Design and Implementation of a Single Source Multipurpose Hospital-Wide Clinical Trial Registry - Sommer, Marcus; Kirchner, Melanie; Gulden, Christian; Egloffstein, Sainab; Lux, Michael P.; Beckmann, Matthias; Mackensen, Andreas; Prokosch, Hans-Ulrich (Studies in health technology and informatics, 2019)
IT-supported patient recruitment, serious adverse event reporting as well as making information about clinical trials accessible to the public on websites, are still major challenges in clinical trials. Too often the distribution of information about trials being performed within a hospital across numerous institutions and IT systems is a barrier to provide efficient IT support for such scenarios. Thus, the essential prerequisite to mastering those challenges is to achieve one single point of truth with adequate, complete, accurate and up-to-date information about all clinical trials running at a hospital. We describe the design and implementation of such a single source clinical trial registry serving multiple purposes at a university hospital.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Clinical trials as topic; electronic health record; registries

Design and Implementation of a Single Source Multipurpose Hospital-Wide Clinical Trial Registry. - Sommer, Marcus; Kirchner, Melanie; Gulden, Christian; Egloffstein, Sainab; Lux, Michael P.; Beckmann, Matthias; Mackensen, Andreas; Prokosch, Hans-Ulrich (Studies in health technology and informatics, 2019)
IT-supported patient recruitment, serious adverse event reporting as well as making information about clinical trials accessible to the public on websites, are still major challenges in clinical trials. Too often the distribution of information about trials being performed within a hospital across numerous institutions and IT systems is a barrier to provide efficient IT support for such scenarios. Thus, the essential prerequisite to mastering those challenges is to achieve one single point of truth with adequate, complete, accurate and up-to-date information about all clinical trials running at a hospital. We describe the design and implementation of such a single source clinical trial registry serving multiple purposes at a university hospital.
EVALuna2:184246

Desmoplastic small round cell tumors: Multimodality treatment and new risk factors - Scheer, Monika; Vokuhl, Christian; Blank, Bernd; Hallmen, Erika; Von Kalle, Thekla; Muenter, Marc; Wessalowski, Ruediger; Hartwig, Maite; Sparber-Sauer, Monika; Schlegel, Paul-Gerhardt; Kramm, Christof M.; Kontny, Udo; et al. (Cancer Medicine, 2019)
Background To evaluate optimal therapy and potential risk factors. Methods Data of DSRCT patients Results Median age of 60 patients was 14.5 years. Male:female ratio was 4:1. Tumors were abdominal/retroperitoneal in 56/60 (93%). 6/60 (10%) presented with a localized mass, 16/60 (27%) regionally disseminated nodes, and 38/60 (63%) with extraperitoneal metastases. At diagnosis, 23/60 (38%) patients had effusions, 4/60 (7%) a thrombosis, and 37/54 (69%) elevated CRP. 40/60 (67%) patients underwent tumor resection, 21/60 (35%) macroscopically complete. 37/60 (62%) received chemotherapy according to CEVAIE (ifosfamide, vincristine, actinomycin D, carboplatin, epirubicin, etoposide), 15/60 (25%) VAIA (ifosfamide, vincristine, adriamycin, actinomycin D) and, 5/60 (8%) P6 (cyclophosphamide, doxorubicin, vincristine, ifosfamide, etoposide). Nine received high-dose chemotherapy, 6 received regional hyperthermia, and 20 received radiotherapy. Among 25 patients achieving complete remission, 18 (72%) received metronomic therapies. Three-year event-free (EFS) and overall survival (OS) were 11% (+/- 8 confidence interval [CI] 95%) and 30% (+/- 12 CI 95%), respectively, for all patients and 26.7% (+/- 18.0 CI 95%) and 56.9% (+/- 20.4 CI 95%) for 25 patients achieving remission. Extra-abdominal site, localized disease, no effusion or ascites only, absence of thrombosis, normal CRP, complete tumor resection, and chemotherapy with VAIA correlated with EFS in univariate analysis. In multivariate analysis, significant factors were no thrombosis and chemotherapy with VAIA. In patients achieving complete remission, metronomic therapy with cyclophosphamide/vinblastine correlated with prolonged time to relapse. Conclusion Pleural effusions, venous thrombosis, and CRP elevation were identified as potential risk factors. The VAIA scheme showed best outcome. Maintenance therapy should be investigated further.
CRIS-Team WoS Importer:2019-03-08

Detection by flow cytometry of anti-neutrophil cytoplasmic antibodies in a novel approach based on neutrophil extracellular traps - Roitsch, Stefan; Goesswein, Stefanie; Neurath, Markus; Leppkes, Moritz (Autoimmunity, 2018)
Background:Anti-neutrophil-cytoplasmic antibodies (ANCA) are auto-antibodies directed against components of neutrophil granulocytes and may be found in various inflammatory conditions, like small-vessel vasculitis or ulcerative colitis (UC). Routine ANCA screening is performed on ethanol-fixed neutrophils using indirect immunofluorescence technique. Yet, how neutrophil granule proteins become available to immunologic presentation is a matter of debate. In recent years, various studies have shown that neutrophils are able to extrude their chromatin decorated with granular proteins as neutrophil extracelullar traps (NETs).Aim: We hypothesized that (I) ANCA immunoreactivity may be found on NETs and (II) NETs may serve as a useful tool in a novel approach for ANCA detection.Methods: Sera from patients suffering from either ANCA-associated vasculitis (n=10), UC (n=30) or sera from patients without diagnosed ANCA-associated diseases (n=20), respectively, were subjected to indirect immunofluorescence and a newly developed method to detect ANCA by flow cytometry employing microbead technology.Results: ANCA-related immunofluorescence was readily detectable on ethanol-fixed NETs, establishing NETs as a structure carrying ANCA target antigens. Moreover, we observed that neutrophils form NETs in response to microbeads and stick to the surface of these beads. Using these NET-coated microbeads in flow cytometry, we were capable of reliably detecting p-ANCA, c-ANCA, and a-ANCA in tested patient sera. UC-related complex DNase-1-sensitive ANCA (NET-ANCA) antigens were also detected on NET-coated microbeads.Conclusion: NET-coated microbeads may be commercially developed as a novel tool for automated ANCA screening assays using flow cytometry.
EVALuna2:35193

Detection of Signature Double-Negative T Cells Is a Reliable Marker for ALPS Associated with FAS Mutation - Eisenhauer, Nina; Miano, Maurizio; Naumann-Bartsch, Nora; Leyh, Jörg; Terranova, Paola; Hinze, Claas; Aigner, Michael; Wittkowski, Helmut; Bruns, Heiko; Ehl, Stephan; Metzler, Markus; Arkwright, Peter; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-17

Determinants Affecting the Clinical Implementation of a Molecularly Informed Molecular Tumor Board Recommendation: Experience from a Tertiary Cancer Center. - Tögel, Lars; Schubart, Christoph; Lettmaier, Sebastian; Neufert, Clemens; Hoyer, Juliane; Wolff, Kerstin; Moskalev, Evgeny; Stöhr, Robert; Agaimy, Abbas; Wiesmann da Silva Reis, André; Wullich, Bernd; Mackensen, Andreas; et al. (Cancers, 2023)
Molecular Tumor Boards (MTBs) converge state-of-the-art next-generation sequencing (NGS) methods with the expertise of an interdisciplinary team consisting of clinicians, pathologists, human geneticists, and molecular biologists to provide molecularly informed guidance in clinical decision making to the treating physician. In the present study, we particularly focused on elucidating the factors impacting on the clinical translation of MTB recommendations, utilizing data generated from gene panel mediated comprehensive genomic profiling (CGP) of 554 patients at the MTB of the Comprehensive Cancer Center Erlangen, Germany, during the years 2016 to 2020. A subgroup analysis of cases with available follow-up data (n = 332) revealed 139 cases with a molecularly informed MTB recommendation, which was successfully implemented in the clinic in 44 (31.7%) of these cases. Here, the molecularly matched treatment was applied in 45.4% (n = 20/44) of cases for ≥6 months and in 25% (n = 11/44) of cases for 12 months or longer (median time to treatment failure, TTF: 5 months, min: 1 month, max: 38 months, ongoing at data cut-off). In general, recommendations were preferentially implemented in the clinic when of high (i.e., tier 1) clinical evidence level. In particular, this was the case for MTB recommendations suggesting the application of PARP, PIK3CA, and IDH1/2 inhibitors. The main reason for non-compliance to the MTB recommendation was either the application of non-matched treatment modalities (n = 30)/stable disease (n = 7), or deteriorating patient condition (n = 22)/death of patient (n = 9). In summary, this study provides an insight into the factors affecting the clinical implementation of molecularly informed MTB recommendations, and careful considerations of these factors may guide future processes of clinical decision making.
EVALuna2:545872
Keywords: Molecular Tumor Board; clinical decision making; precision medicine; molecular pathology; real-world data; cancer care

Development of a coordinated allo T cell and auto B cell response against autosomal PTK2B after allogeneic hematopoietic stem cell transplantation - Kremer, Anita; Van Der Griendt, Judith C.; Van Der Meijden, Edith D.; Honders, M. Willy; Ayoglu, Burcu; Schwenk, Jochen M.; Nilsson, Peter; Falkenburg, J. H. Frederik; Griffioen, Marieke (Haematologica, 2014)
It is well known that allo-reactive T cells play a crucial role in graft-versus-leukemia and graft-versus-host disease after allogeneic hematopoietic stem cell transplantation (alloSCT). Allo-reactive CD4(+) T cells can mediate direct cytolysis, but may also stimulate production of IgG antibodies as helper cells. Immune complexes may subsequently be processed and presented by professional antigen presenting cells and stimulate induction of specific CD8(+) T cells. As such, proteins targeted in coordinated T- and B-cell responses may represent a class of immunodominant antigens in clinical responses after alloSCT. We previously identified LB-PTK2B-1T as HLA class II restricted polymorphic antigen in a patient treated with donor lymphocyte infusion for relapsed chronic myeloid leukemia after HLA-matched alloSCT. Since PTK2B has also been described as antibody target, we here investigated whether a coordinated T- and B-cell response against PTK2B was induced. Patient serum before and after alloSCT and donor lymphocyte infusion (DLI) was screened for antibodies, and we indeed observed development of a humoral immune response against PTK2B. Antibodies against PTK2B were only found after DLI and, in contrast to the CD4(+) T cells, recognized a monomorphic region of the protein. To our knowledge, this is the first description of a coordinated allo-reactive CD4(+) T-cell and auto-reactive antibody response against an autosomal antigen.
EVALuna2:25676

Development of pseudomonas exotoxin based Duotoxins for the treatment of hematologic malignancies - Ammon, Anna-Maria; Emmerich, C.; Mellenthin, Lisa; Mackensen, Andreas; Müller, Fabian (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Diagnosis of invasive fungal infections in haematological patients by combined use of galactomannan, 1,3-β-D-glucan, Aspergillus PCR, multifungal DNA-microarray, and Aspergillus azole resistance PCRs in blood and bronchoalveolar lavage samples: results of a prospective multicentre study - Boch, T.; Spiess, B.; Cornely, O. A.; Vehreschild, J. J.; Rath, P. M.; Steinmann, J.; Heinz, W. J.; Hahn, J.; Krause, Stefan; Kiehl, M. G.; Egerer, G.; Liebregts, T.; et al. (Clinical Microbiology and Infection, 2016)
High mortality rates of invasive fungal disease (IFD), especially invasive aspergillosis (IA), in immunocompromised haematological patients and current diagnostic limitations require improvement of detection of fungal pathogens by defining the optimal use of biomarkers and clinical samples. Concurrent bronchoalveolar lavage (BAL) and peripheral blood samples of 99 haematological patients with suspected IFD were investigated within a multicentre prospective study. Diagnostic performance of a galactomannan (GM) enzyme immune assay (EIA), a 1,3-?-D-glucan assay (BDG), an Aspergillus PCR, and a multifungal DNA-microarray (Chip) alone or in combination were calculated. IFD were classified as proven (n=3), probable (n=34), possible (n=33), and no IFD (n=29) according to EORTC/MSG criteria. GM, PCR, and Chip showed superior diagnostic performance in BAL than in blood, whereas specificity of BDG in BAL was poor (48% (14/29)). The combination of GM (BAL) with BDG (blood) showed sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and DOR (diagnostic odds ratio) of 92% (34/37), 93% (27/29), 94%, 90%, and 153.0, respectively. Combining GM (BAL) with PCR (BAL) showed convincing diagnostic potential for diagnosing IA with sensitivity, specificity, PPV, NPV, and DOR of 85% (17/20), 97% (28/29), 94%, 90%, and 158.7. Addition of the DNA-microarray resulted in further detection of two mucormycetes infections. In 1 out of 15 Aspergillus DNA-positive samples a triazole resistance-mediating Cyp51A mutation was found. Combination of biomarkers is superior to their sole use in diagnosing IFD, particularly IA. Integrating blood and BAL samples into a diagnostic algorithm is an advantageous approach.
EVALuna2:25752

Diagnostic Accuracy of Breast Medical Tactile Examiners (MTEs): A Prospective Pilot Study - Lux, Michael P.; Emons, Julius; Bani, Mayada; Wunderle, Marius; Sell, Charlotte; Preuss, Caroline; Rauh, Claudia; Jud, Sebastian; Heindl, Felix; Langemann, Hanna; Geyer, Thomas; Brandl, Anna-Lisa; et al. (Breast Care, 2019)
Background: The usefulness of clinical breast examination (CBE) in general and in breast cancer screening programs has been a matter of debate. This study investigated whether adding vision-impaired medical tactile examiners (MTEs) improves the predictiveness of CBE for suspicious lesions and analyzed the feasibility and acceptability of this approach. Methods: The prospective study included 104 patients. Physicians and MTEs performed CBEs, and mammography and ultrasound results were used as the gold standard. Sensitivity and specificity were calculated and logistic regression models were used to compare the predictive value of CBE by physicians alone, MTEs alone, and physicians and MTEs combined. Results: For CBEs by physicians alone, MTEs alone, and both combined, sensitivity was 71, 82, and 89% and specificity was 55, 45, and 35%, respectively. Using adjusted logistic regression models, the validated areas under the curve were 0.685, 0.692, and 0.710 (median bootstrapped p value (DeLong) = 0.381). Conclusion: The predictive value for a suspicious breast lesion in CBEs performed by MTEs in patients without prior surgery was similar to that of physician-conducted CBEs. Including MTEs in the CBE procedure in breast units thus appears feasible and could be a way of utilizing their skills. (c) 2019 S. Karger AG, Basel
CRIS-Team WoS Importer:2019-03-22

Diagnostic performance of the novel Fungitell STAT assay in comparison to the classical Fungitell assay and the Fujifilm Wako beta-glucan test in patients with invasive fungal disease - Kuepper, C.; Forster, J.; Traeger, J.; Meyer, R.; Cipa, Franziska; Mihai, Sidonia; Meintker, Lisa; Werblow, M.; Kurzai, O.; Held, Jürgen (MYCOSES, 2021)
CRIS-Team WoS Importer:2021-10-08

Different doses of micafungin for prophylaxis of invasive fungal diseases in hemato-oncological high-risk patients: a web-based non-interventional trial in four large university hospitals in Germany - Heimann, S. M.; Vehreschild, M. J. G. T.; Meintker, Lisa; Heinz, W.; Schroeder, T.; Von Bergwelt-Baildon, M.; Cornely, O. A.; Vehreschild, J. J. (Transplant Infectious Disease, 2014)
Treatment indications of new antifungals in clinical practice often deviate from the strict criteria used in controlled clinical trials. Under routine clinical conditions, beneficial and adverse effects, not previously described in clinical trials may be observed. The aim of this study was to describe customary prescription and treatment strategies of micafungin (MCFG).A registry was set up on www.ClinicalSurveys.net and physicians were invited to provide retrospective information on cases they had treated with MCFG. Documentation comprised demographic information, underlying disease, effectiveness, safety, and tolerability of MCFG.A total of 125 episodes of patients hospitalized between September 2009 and February 2012 were documented, of which 7 had to be excluded because of incomplete documentation. The most common risk factors of patients were hematological malignancy (n = 116, 98.3%) and antibiotic treatment >3 days (n = 115, 97.5%). MCFG was administered as prophylaxis in 106 (89.9%) patients. Median duration of MCFG application as prophylaxis was 21 days (range: 3-78); 53 of the patients (50%) received a dose of 50 mg, while the other 53 (50%) received 100 mg/day. For the different doses, prophylactic outcome was rated as success in 42 (79.2%) vs. 52 (98.1%; P = 0.004) patients. Fifty-five patients (51.9%) were treated with posaconazole before initiation of MCFG. Four patients (7.5%) developed a proven invasive fungal disease (IFD) while being treated with 50 mg MCFG, compared to no patient treated with 100 mg (P = 0.118). At the end of MCFG prophylaxis, 24 (22.6%) patients were switched to fluconazole and 64 (60.3%) patients to posaconazole.Our study shows clinical effectiveness of MCFG prophylaxis with low rates of breakthrough fungal infections. In most cases, MCFG was part of a multi-modal antifungal prophylactic strategy. Investigators reported fewer proven IFDs in patients receiving therapeutic doses of MCFG as prophylaxis.
EVALuna2:25712

Differential impact of IDH1/2 mutational subclasses on outcome in adult AML: results from a large multicenter study - Middeke, Jan M.; Metzeler, Klaus H.; Rollig, Christoph; Kramer, Michael; Eckardt, Jan Niklas; Stasik, Sebastian; Greif, Philipp A.; Spiekermann, Karsten; Rothenberg-Thurley, Maja; Krug, Utz; Braess, Jan; Kramer, Alwin; et al. (Blood Advances, 2022)
Mutations of the isocitrate dehydrogenase-1 (IDH1) and IDH2 genes are among the most frequent alterations in acute myeloid leukemia (AML) and can be found in 20% of patients at diagnosis. Among 4930 patients (median age, 56 years; interquartile range, 45-66) with newly diagnosed, intensively treated AML, we identified IDH1 mutations in 423 (8.6%) and IDH2 mutations in 575 (11.7%). Overall, there were no differences in response rates or survival for patients with mutations in IDH1 or IDH2 compared with patients without mutated IDH1/2. However, distinct clinical and comutational phenotypes of the most common subtypes of IDH1/2 mutations could be associated with differences in outcome. IDH1-R132C was associated with increased age, lower white blood cell (WBC) count, less frequent comutation of NPM1 and FLT3 internal tandem mutation (ITD) as well as with lower rate of complete remission and a trend toward reduced overall survival (OS) compared with other IDH1 mutation variants and wild-type (WT) IDH1/2. In our analysis, IDH2-R172K was associated with significantly lower WBC count, more karyotype abnormalities, and less frequent comutations of NPM1 and/or FLT3-ITD. Among patients within the European LeukemiaNet 2017 intermediate- and adverse-risk groups, relapse-free survival and OS were significantly better for those with IDH2-R172K compared with WT IDH, providing evidence that AML with IDH2-R172K could be a distinct entity with a specific comutation pattern and favorable outcome. In summary, the presented data from a large cohort of patients with IDH1/2 mutated AML indicate novel and clinically relevant findings for the most common IDH mutation subtypes.
CRIS-Team Scopus Importer:2022-03-18

Differential prognostic value of MYC immunohistochemistry in subtypes of papillary renal cell carcinoma - Bellut, Julia; Bertz, Simone; Nolte, Elke; Stoehr, Christine; Polifka, Iris; Lieb, Verena; Herrmann, Edwin; Jung, Rudolf; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; Wach, Sven (Scientific Reports, 2017)
The histomorphological subtyping of papillary renal cell carcinomas (pRCCs) has improved the predictions of patients' long-term survival. Based on our previous results, we hypothesized that the MYC proto-oncogene would show differential expression in pRCC subtypes. Using a multi-institutional cohort of 204 pRCC patients we assessed the additional value of the immunohistochemical markers MYC, MINA53, and Ki67 in predicting patient's long-term survival. The clinical endpoints were overall survival (OS) and cancer-specific survival (CSS). Nomograms were constructed to predict each patient's risk of death (OS). The incorporation of the MYC staining patterns allowed the stratification of pRCC type 1 patients into better and worse prognostic groups. None of the patients with pRCC type 1 tumors and favorable MYC staining patterns died from tumor-related causes. This prognostic value was independent of the patient's age at surgery, the pathological tumor stage and presence of lymph node invasion. we could show that the immunohistochemical assessment of MYC and the histomorphological subtyping of pRCC stratifies pRCC type 1 tumors with regard to OS and CSS. The determination of the histomorphologic pRCC subtype in combination with the MYC immunohistochemical staining patterns allows a more accurate prediction of patients' individual risk of death.
EVALuna2:33570

Digitally supported shared decision-making and treat-to-target in rheumatology: a qualitative study embedded in a multicenter randomized controlled trial - Muehlensiepen, Felix; May, Susann; Hadaschik, Katharina; Vuillerme, Nicolas; Heinze, Martin; Grahammer, Manuel; Labinsky, Hannah; Böltz, Sebastian; Detert, Jacqueline; Petersen, Jana; Krönke, Gerhard; Schett, Georg; et al. (Rheumatology International, 2022)
Patient-reported outcomes (PRO) represent a cornerstone in the management of patients with rheumatoid arthritis (RA). However, PRO are currently recorded mainly on paper and only during on-site appointments. Electronic PRO (ePRO) enable continuous remote monitoring and could improve shared decision-making (SDM) and implementation of a treat-to-target (T2T) approach. This study aims to investigate patient and physician experiences, perceived drawbacks and benefits of using an ePRO web-app (ABATON RA) to digitally support SDM and T2T. A qualitative study embedded in a multicenter randomized controlled trial (RCT) consisting of interviews with RA patients and physicians that were subsequently analyzed using deductive-inductive qualitative content analysis. Between August 2021 and May 2022, interviews with ten RA patients and five physicians were completed. Three key themes emerged in the analysis: (i) App user experiences; (ii) perceived drawbacks of app-supported rheumatology care; and (iii) perceived benefits of app-supported rheumatology care. Continuous ePRO collection and a high level of standardization strained some RA patients. Certain ePRO seemed outdated and were hard to understand. Patients and physicians appreciated having an improved overview of disease activity, capturing disease flares and continuous remote monitoring. Paper- and time-saving were associated with using ePRO. Physicians feared to become too focused on ePRO data, stressed the lack of ePRO monitoring reimbursement and app interoperability. For RA patients and physicians, benefits seemed to outweigh observed drawbacks of the digitally supported SDM using ePRO. The software was easy to use and could lead to a better understanding of the individual disease course, resource allocation and treatment of rheumatoid arthritis.
CRIS-Team Scopus Importer:2022-10-28
Keywords: ePRO; Health Services Research; mHealth; Qualitative research; Rheumatology; SDM

Direct aqueous measurement of 25-hydroxyvitamin D levels in a cellular environment by LC-MS/MS using the novel chemical derivatization reagent MDBP - Mueller, Miriam J.; Bruns, Heiko; Volmer, Dietrich A. (Analytical and Bioanalytical Chemistry, 2017)
Vitamin D measurements in biological fluids by mass spectrometry are challenging at very low concentration levels. As a result, chemical derivatization is often employed to enhance the ionization properties of low abundant vitamin D compounds. Cookson-type reagents such as 4-phenyl-1,2,4-triazoline-3,5-dione (PTAD) or similar derivatives work well but require careful, water-free experimental conditions, as traces of water inactivate the reagent and inhibit or stop the derivatization reactions, thus making quantitative measurements in aqueous samples impossible. We describe a novel electrospray liquid chromatography-tandem mass spectrometry (LC-MS/MS) assay for determining 25-hydroxyvitamin D3 (25(OH)D3) directly in aqueous cellular systems using a new derivatization reagent, the ionic liquid 12-(maleimidyl)dodecyl-tri-n-butylphosphonium bromide (MDBP). The proof-of-concept for the MDBP assay was demonstrated by measuring the levels of 25(OH)D3 in four different human cell types, namely T cells, helper T cells, B cells, and macrophages. In addition to the ability to determine the levels of 25(OH)D3 directly in aqueous samples, the cellular integrity was maintained in our application. We show the time-dependent uptake of 25(OH)D3 into the investigated cells to demonstrate the applicability of the new label. Furthermore, the MDBP derivatization technique may be equally useful in imaging mass spectrometry, where it could be used for response enhancements of spatially localized vitamin D metabolites on wet tissue surfaces, without destroying the integrity of the tissue surface. Graphical Abstract MDBP labelling of 25-hydroxyvitamin D in the extracellular spac
EVALuna2:25761

Direct oral anticoagulants versus Vitamin K antagonists after a recent ischemic stroke or TIA- a pooled individual patient data analysis - Seiffge, David; Paciaroni, Maurizio; Wilson, Duncan; Koga, Masatoshi; Macha, Kosmas; Cappellari, Manuel; Schaedelin, Sabine; Shakeshaft, Clare; Takagi, Masahito; Tsivgoulis, Georgios; Bonetti, Bruno; Kallmünzer, Bernd; et al. (NEUROLOGY, 2019)
CRIS-Team WoS Importer:2019-08-02

Direct oral anticoagulants versus vitamin K antagonists after recent ischemic stroke in patients with atrial fibrillation - Seiffge, David J.; Paciaroni, Maurizio; Wilson, Duncan; Koga, Masatoshi; Macha, Kosmas; Cappellari, Manuel; Schaedelin, Sabine; Shakeshaft, Clare; Takagi, Masahito; Tsivgoulis, Georgios; Bonetti, Bruno; Kallmünzer, Bernd; et al. (Annals of Neurology, 2019)
Objective: We compared outcomes after treatment with direct oral anticoagulants (DOACs) and vitamin K antagonists (VKAs) in patients with atrial fibrillation (AF) and a recent cerebral ischemia. Methods: We conducted an individual patient data analysis of seven prospective cohort studies. We included patients with AF and a recent cerebral ischemia (<3 months before starting oral anticoagulation) and a minimum follow-up of 3 months. We analyzed the association between type of anticoagulation (DOAC versus VKA) with the composite primary endpoint (recurrent ischemic stroke [AIS], intracerebral hemorrhage [ICH], or mortality) using mixed-effects Cox proportional hazards regression models; we calculated adjusted hazard ratios (HRs) with 95% confidence intervals (95% CIs). Results: We included 4,912 patients (median age, 78 years [interquartile range IQR, 71–84]; 2,331 [47.5%] women; median National Institute of Health Stroke Severity Scale at onset, 5 [IQR, 2–12]); 2,256 (45.9%) patients received VKAs and 2,656 (54.1%) DOACs. Median time from index event to starting oral anticoagulation was 5 days (IQR, 2–14) for VKAs and 5 days (IQR, 2–11) for DOACs (p = 0.53). There were 262 acute ischemic strokes (AISs; 4.4%/year), 71 intracranial hemorrrhages (ICHs; 1.2%/year), and 439 deaths (7.4%/year) during the total follow-up of 5,970 patient-years. Compared to VKAs, DOAC treatment was associated with reduced risks of the composite endpoint (HR, 0.82; 95% CI, 0.67–1.00; p = 0.05) and ICH (HR, 0.42; 95% CI, 0.24–0.71; p < 0.01); we found no differences for the risk of recurrent AIS (HR, 0.91; 95% CI, 0.70–1.19; p = 0.5) and mortality (HR, 0.83; 95% CI, 0.68–1.03; p = 0.09). Interpretation: DOAC treatment commenced early after recent cerebral ischemia related to AF was associated with reduced risk of poor clinical outcomes compared to VKA, mainly attributed to lower risks of ICH. ANN NEUROL 2019.
CRIS-Team Scopus Importer:2019-05-17

Discovery and Differential Processing of HLA Class II-Restricted Minor Histocompatibility Antigen LB-PIP4K2A-1S and Its Allelic Variant by Asparagine Endopeptidase - Kremer, Anita; Bausenwein, Judith; Lurvink, Ellie; Kremer, Andreas; Rutten, Caroline E.; van Bergen, Cornelis A.M.; Kretschmann, Sascha; van der Meijden, Edith; Honders, Maria W.; Mazzeo, Daniela; Watts, Colin; Mackensen, Andreas; et al. (Frontiers in Immunology, 2020)
Minor histocompatibility antigens are the main targets of donor-derived T-cells after allogeneic stem cell transplantation. Identification of these antigens and understanding their biology are a key requisite for more insight into how graft vs. leukemia effect and graft vs. host disease could be separated. We here identified four new HLA class II-restricted minor histocompatibility antigens using whole genome association scanning. For one of the new antigens, i.e., LB-PIP4K2A-1S, we measured strong T-cell recognition of the donor variant PIP4K2A-1N when pulsed as exogenous peptide, while the endogenously expressed variant in donor EBV-B cells was not recognized. We showed that lack of T-cell recognition was caused by intracellular cleavage by a protease named asparagine endopeptidase (AEP). Furthermore, microarray gene expression analysis showed that PIP4K2A and AEP are both ubiquitously expressed in a wide variety of healthy tissues, but that expression levels of AEP were lower in primary acute myeloid leukemia (AML). In line with that, we confirmed low activity of AEP in AML cells and demonstrated that HLA-DRB1*03:01 positive primary AML expressing LB-PIP4K2A-1S or its donor variant PIP4K2A-1N were both recognized by specific T-cells. In conclusion, LB-PIP4K2A-1S not only represents a novel minor histocompatibility antigen but also provides evidence that donor T-cells after allogeneic stem cell transplantation can target the autologous allelic variant as leukemia-associated antigen. Furthermore, it demonstrates that endopeptidases can play a role in cell type-specific intracellular processing and presentation of HLA class II-restricted antigens, which may be explored in future immunotherapy of AML.
CRIS-Team Scopus Importer:2020-04-07
Keywords: allogeneic stem cell transplantation; CD4 T-cells; graft vs. leukemia effect; HLA class II; minor histocompatibility antigens

Disease risk and GVHD biomarkers can stratify patients for risk of relapse and nonrelapse mortality post hematopoietic cell transplant - Aziz, Mina D.; Shah, Jay; Kapoor, Urvi; Dimopoulos, Christina; Anand, Sarah; Augustine, Allan; Ayuk, Francis; Chaudhry, Mohammed; Chen, Yi-Bin; Choe, Hannah K.; Etra, Aaron; Gergoudis, Stephanie; et al. (Leukemia, 2020)
The graft-versus-leukemia (GVL) effect after allogeneic hematopoietic cell transplant (HCT) can prevent relapse but the risk of severe graft-versus-host disease (GVHD) leads to prolonged intensive immunosuppression and possible blunting of the GVL effect. Strategies to reduce immunosuppression in order to prevent relapse have been offset by increases in severe GVHD and nonrelapse mortality (NRM). We recently validated the MAGIC algorithm probability (MAP) that predicts the risk for severe GVHD and NRM in asymptomatic patients using serum biomarkers. In this study we tested whether the MAP could identify patients whose risk for relapse is higher than their risk for severe GVHD and NRM. The multicenter study population (n = 1604) was divided into two cohorts: historical (2006–2015, n = 702) and current (2015–2017, n = 902) with similar NRM, relapse, and survival. On day 28 post-HCT, patients who had not developed GVHD (75% of the population) and who possessed a low MAP were at much higher risk for relapse (24%) than severe GVHD and NRM (16 and 9%); this difference was even more pronounced in patients with a high disease risk index (relapse 33%, NRM 9%). Such patients are good candidates to test relapse prevention strategies that might enhance GVL.
CRIS-Team Scopus Importer:2020-02-18

Disrupted osteoclast differentiation results in myelodysplasia - Kazianka, L.; Kornauth, C.; Van Der Kouwe, E.; Schmetterer, K.; Heller, G.; Marculescu, R.; Bach, Christian; Valent, P.; Tenen, D. G.; Staber, P. B. (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Distinct characteristics of e13a2 versus e14a2 BCR-ABL1 driven chronic myeloid leukemia under first-line therapy with imatinib - Hanfstein, Benjamin; Lauseker, Michael; Hehlmann, Ruediger; Saussele, Susanne; Erben, Philipp; Dietz, Christian; Fabarius, Alice; Proetel, Ulrike; Schnittger, Susanne; Haferlach, Claudia; Krause, Stefan; Schubert, Joerg; et al. (Haematologica, 2014)
The vast majority of chronic myeloid leukemia patients express a BCR-ABL1 fusion gene mRNA encoding a 210 kDa tyrosine kinase which promotes leukemic transformation. A possible differential impact of the corresponding BCR-ABL1 transcript variants e13a2 ("b2a2") and e14a2 ("b3a2") on disease phenotype and outcome is still a subject of debate. A total of 1105 newly diagnosed imatinib-treated patients were analyzed according to transcript type at diagnosis (e13a2, n=451; e14a2, n=496; e13a2+e14a2, n=158). No differences regarding age, sex, or Euro risk score were observed. A significant difference was found between e13a2 and e14a2 when comparing white blood cells (88 vs. 65 × 10(9)/L, respectively; P<0.001) and platelets (296 vs. 430 × 10(9)/L, respectively; P<0.001) at diagnosis, indicating a distinct disease phenotype. No significant difference was observed regarding other hematologic features, including spleen size and hematologic adverse events, during imatinib-based therapies. Cumulative molecular response was inferior in e13a2 patients (P=0.002 for major molecular response; P<0.001 for MR4). No difference was observed with regard to cytogenetic response and overall survival. In conclusion, e13a2 and e14a2 chronic myeloid leukemia seem to represent distinct biological entities. However, clinical outcome under imatinib treatment was comparable and no risk prediction can be made according to e13a2 versus e14a2 BCR-ABL1 transcript type at diagnosis. (clinicaltrials.gov identifier:00055874).
EVALuna2:25689

Distinct von Hippel-Lindau gene and hypoxia-regulated alterations in gene and protein expression patterns of renal cell carcinoma and their effects on metabolism - Leisz, Sandra; Schulz, Kristin; Erb, Susanne; Oefner, Peter; Dettmer, Katja; Mougiakakos, Dimitrios; Wang, Ena; Marincola, Francesco M.; Stehle, Franziska; Seliger, Barbara (Oncotarget, 2015)
During the last decade the knowledge about the molecular mechanisms of the cellular adaption to hypoxia and the function of the "von Hippel Lindau" (VHL) protein in renal cell carcinoma (RCC) has increased, but there exists little information about the overlap and differences in gene/protein expression of both processes. Therefore the aim of this study was to dissect VHL- and hypoxia-regulated alterations in the metabolism of human RCC using ome-based strategies. The effect of the VHL- and hypoxia-regulated altered gene/protein expression pattern on the cellular metabolism was analyzed by determination of glucose uptake, lactate secretion, extracellular pH, lactate dehydrogenase activity, amino acid content and ATP levels. By employing VHL-/VHL+ RCC cells cultured under normoxic and hypoxic conditions, VHL-dependent, HIF-dependent as well as VHL-/HIF-independent alterations in the gene and protein expression patterns were identified and further validated in other RCC cell lines. The genes/proteins differentially expressed under these distinct conditions were mainly involved in the cellular metabolism, which was accompanied by an altered metabolism as well as changes in the abundance of amino acids in VHL-deficient cells. In conclusion, the study reveals similarities, but also differences in the genes and proteins controlled by VHL functionality and hypoxia thereby demonstrating differences in the metabolic switch of RCC under these conditions.
EVALuna2:25711

DNA Damage-Response Pathway in Lymphoma Determines Interactions with Macrophages By Altered PD-Li Expression and Fxosome Formation - Vorholt, Daniela; Izquierdo-Alvarez, Elena; Sackey, Benedict; Schmitz, Jan; Nickel, Nadine; Blakemore, Stuart; Knittel, Gero; Reinhardt, Christian; Wendtner, Clemens-Martin; Bruns, Heiko; Hallek, Michael; Pallasch, Christian (BLOOD, 2018)
CRIS-Team WoS Importer:2019-03-06

DNA methylation in PRDM8 is indicative for dyskeratosis congenita - Weidner, Carola I.; Lin, Qiong; Birkhofer, Carina; Gerstenmaier, Uwe; Kaifie, Andrea; Kirschner, Martin; Bruns, Heiko; Balabanov, Stefan; Trummer, Arne; Stockklausner, Clemens; Hoechsmann, Britta; Schrezenmeier, Hubert; et al. (Oncotarget, 2016)
Dyskeratosis congenita (DKC) is associated with impaired telomere maintenance and with clinical features of premature aging. In this study, we analysed global DNA methylation (DNAm) profiles of DKC patients. Age-associated DNAm changes were not generally accelerated in DKC, but there were significant differences to DNAm patterns of healthy controls, particularly in CpG sites related to an internal promoter region of PR domain containing 8 (PRDM8). Notably, the same genomic region was also hypermethylated in aplastic anemia (AA) - another bone marrow failure syndrome. Site-specific analysis of DNAm level in PRDM8 with pyrosequencing and MassARRAY validated aberrant hypermethylation in 11 DKC patients and 27 AA patients. Telomere length, measured by flow-FISH, did not directly correlate with DNAm in PRDM8. Therefore the two methods may be complementary to also identify patients with still normal telomere length. In conclusion, blood of DKC patients reveals aberrant DNAm patterns, albeit age-associated DNAm patterns are not generally accelerated. Aberrant hypermethylation is particularly observed in PRDM8 and this may support identification and classification of bone marrow failure syndrome
EVALuna2:25740

Documentation Time and Effort and Associated Resources for Patients with Primary Breast Cancer from Diagnosis to End of Follow-Up - Results of a Multicentre Validation - Beckmann, Matthias; Sell, C.; Aydogdu, M.; Brucker, S. Y.; Fehm, T.; Janni, W.; Kreienberg, R.; Kuemmel, S.; Neumann, M.; Scharl, A.; Schleicher, B.; Wallwiener, D.; et al. (Gesundheitswesen, 2016)
INTRODUCTION: Tumour documentation is essential for quality assurance of oncological therapies and as a source of reliable information about the in- and outpatient care. The documentation effort and the associated resource consumption were analysed for the example of breast cancer. MATERIAL AND METHODS: The different steps in the care of patients with primary breast cancer in a standardised disease situation were defined from initial diagnosis to the end of the follow-up. After the pilot phase, a multicentre validation (n=7 centres) was performed with the support of the Federal Ministry of Health. The documentation time points were horizontally collected and analysed with regard to amount, duration and personnel expenses. RESULTS: 57% of the documentation costs are caused by the physicians. Regarding the different centres, documentation costs were calculated between € 352.82 and € 1 084.08 per patient from diagnosis to completion of aftercare. Non-certified centres had a reduced documentation effort and thus lower costs. CONCLUSIONS: The results demonstrate the need for a reduction of the documentation effort - particularly for physicians - the most expensive profession in the health system. A quality improvement is expected from the certification with its special requirements. In this context, there is a justified demand for an adequate remuneration of the documentation effort for certified centres. Furthermore, it is necessary to reduce the number of variables for quality assurance and to define them centrally. A comprehensive multi-disciplinary documentation should be achieved. Investments in a single data set and interface enhancements of existing documentation systems should be realised.
EVALuna2:33544

Does time from diagnosis to treatment affect the prognosis of patients with newly diagnosed acute myeloid leukemia? - Röllig, Christoph; Kramer, Michael; Schliemann, Christoph; Mikesch, Jan Henrik; Steffen, Björn; Krämer, Alwin; Noppeney, Richard; Schäfer-Eckart, Kerstin; Krause, Stefan; Hänel, Mathias; Herbst, Regina; Kunzmann, Volker; et al. (Blood, 2020)
In fit patients with newly diagnosed acute myeloid leukemia (AML), immediate treatment start is recommended due to the poor prognosis of untreated acute leukemia. We explored the relationship between time from diagnosis to treatment start (TDT) and prognosis in a large real-world data set from the German Study Alliance Leukemia-Acute Myeloid Leukemia (SAL-AML) registry. All registered non-acute promyelocytic leukemia patients with intensive induction treatment and a minimum 12 months of follow-up were selected (n = 2263). We analyzed influence of TDT on remission, early death, and overall survival (OS) in univariable analyses for each day of treatment delay, in groups of 0 to 5, 6 to 10, 11 to 15, and >15 days of TDT, adjusted for influence of established prognostic variables on outcomes. Median TDT was 3 days (interquartile range, 2-7). Unadjusted 2-year OS rates, stratified by TDT of 0 to 5, 6 to 10, 11 to 15, and >15 days, were 51%, 48%, 44%, and 50% (P = .211). In multivariable Cox regression analysis accounting for established prognostic variables, the TDT hazard ratio as a continuous variable was 1.00 (P = .617). In OS analyses, separately stratified for age ≤60 and >60 years and for high vs lower initial white blood cell count, no significant differences between TDT groups were observed. Our study suggests that TDT is not related to survival. As stratification in intensive first-line AML treatment evolves, TDT data suggest that it may be a feasible approach to wait for genetic and other laboratory test results so that clinically stable patients are assigned the best available treatment option. This trial was registered at www.clinicaltrials.gov as #NCT03188874.
CRIS-Team Scopus Importer:2020-08-28

Domain II of Pseudomonas Exotoxin Is Critical for Efficacy of Bolus Doses in a Xenograft Model of Acute Lymphoblastic Leukemia - Müller, Fabian; Cunningham, Tyler; Beers, Richard; Bera, Tapan K.; Wayne, Alan S.; Pastan, Ira (Toxins, 2018)
Moxetumomab pasudotox is a fusion protein of a CD22-targeting antibody and Pseudomonas exotoxin. Minutes of exposure to Moxetumomab achieves similar cell killing than hours of exposure to a novel deimmunized variant against some acute lymphoblastic leukemia (ALL). Because blood levels fall quickly, Moxetumomab is more than 1000-fold more active than the deimmunized variant in vivo. We aimed to identify which part of Moxetumomab increases in vivo efficacy and generated five immunotoxins, tested time-dependent activity, and determined the efficacy in a KOPN-8 xenograft model. Full domain II shortened the time cells had to be exposed to die to only a few minutes for some ALL; deimmunized domain III consistently extended the time. Against KOPN-8, full domain II accelerated time to arrest protein synthesis by three-fold and tripled PARP-cleavage. In vivo efficacy was increased by more than 10-fold by domain II and increasing size, and therefore half-life enhanced efficacy two- to four-fold. In summary, in vivo efficacy is determined by the time cells have to be exposed to immunotoxin to die and serum half-life. Thus, domain II is most critical for activity against some ALL treated with bolus doses; however, immunotoxins lacking all but the furin-cleavage site of domain II may be advantageous when treating continuously.
EVALuna2:34276

Donor CD4 T Cell Diversity Determines Virus Reactivation in Patients After HLA-Matched Allogeneic Stem Cell Transplantation - Ritter, J.; Seitz, V.; Balzer, H.; Gary, R.; Lenze, D.; Moi, S.; Pasemann, S.; Seegebarth, A.; Wurdack, M.; Hennig, S.; Gerbitz, A.; Hummel, M. (American Journal of Transplantation, 2015)
Delayed reconstitution of the T cell compartment in recipients of allogeneic stem cell grafts is associated with an increase of reactivation of latent viruses. Thereby, the transplanted T cell repertoire appears to be one of the factors that affect T cell reconstitution. Therefore, we studied the T cell receptor beta (TCR?) gene rearrangements of flow cytometry-sorted CD4(+) and CD8(+) T cells from the peripheral blood of 23 allogeneic donors before G-CSF administration and on the day of apheresis. For this purpose, TCR? rearrangements were amplified by multiplex PCR followed by high-throughput amplicon sequencing. Overall, CD4(+) T cells displayed a significantly higher TCR? diversity compared to CD8(+) T cells irrespective of G-CSF administration. In line, no significant impact of G-CSF treatment on the TCR V? repertoire usage was found. However, correlation of the donor T cell repertoire with clinical outcomes of the recipient revealed that a higher CD4(+) TCR? diversity after G-CSF treatment is associated with lower reactivation of cytomegalovirus and Epstein-Barr virus. By contrast, no protecting correlation was observed for CD8(+) T cells. In essence, our deep TCR? analysis identifies the importance of the CD4(+) T cell compartment for the control of latent viruses after allogeneic stem cell transplantation.
EVALuna2:25710

Donor-specific Anti-HLA Antibodies Present in Pooled Human Serum Do Not Prevent Development of Human Mreg_UKR From Monocytes in Culture - Hutchinson, James A.; Riquelme, Paloma; Bach, Christian; Kekarainen, Tuija; Faendrich, Fred; Geissler, Edward K.; Ahrens, Norbert (Transplantation, 2017)
EVALuna2:25769

DONOR SPECIFIC ANTI-HLA IGA ANTIBODIES AND GRAFT SURVIVAL AFTER KIDNEY TRANSPLANTATION - Bach, Christian; Heinemann, Falko M.; Dick, Andrea; Spriewald, Bernd M.; Arnold, Martin (2018)
EVALuna2:34162

Dose adjustment of cisplatin, etoposide, and ifosfamide according to kidney function: a retrospective analysis and implications for medication safety - Grafe, Carolin; Semrau, Sabine; Hein, Alexander; Beckmann, Matthias; Mackensen, Andreas; Dörje, Frank; Fromm, Martin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)
Clearance of cisplatin, etoposide, and ifosfamide depends on kidney function and dosages should be adjusted in patients with renal impairment. However, there is still limited data on the adherence of physicians to dosing recommendations for these drugs in cancer patients with renal impairment. Three thousand four hundred forty-eight prescriptions to 369 patients, treated in the Comprehensive Cancer Center of a German university hospital, were retrospectively evaluated. The administered relative doses of cisplatin, etoposide, and ifosfamide were compared with relative doses recommended at the time of prescription according to the patients' creatinine clearance. Cisplatin is contraindicated according to two German summary of product characteristics (SmPC) in patients with a creatinine clearance < 60 mL/min. Nevertheless, 37 cisplatin prescriptions were made for this group of patients (i.e., 2.0% of all cisplatin prescriptions). According to one German SmPC (valid in the year of data analysis), etoposide dosage should be reduced in patients with a creatinine clearance from 15 to 50 mL/min, while it is contraindicated below 15 mL/min. Thirteen etoposide prescriptions were without dose reduction in patients with creatinine clearance from 15 to 50 mL/min (1.5% of all etoposide prescriptions); one patient received etoposide with creatinine clearance below 15 mL/min. In 8.9% of ifosfamide prescriptions, patients did not receive a reduced dose in spite of respective recommendations. Dosages of cisplatin, etoposide, and ifosfamide are not always adjusted as recommended in patients with renal impairment. Consistent international dosing recommendations (e.g., in SmPCs), preferentially included in clinical decision support systems, should be developed to tackle this problem.
EVALuna2:25784

DOTting the path to doom: how acceleration of histone methylation leads to leukemia - Bach, Christian; Slany, Robert (Cancer Cell, 2014)
Epigenetic control mechanisms are central to normal and malignant hematopoiesis. In this issue of Cancer Cell, Deshpande and colleagues demonstrate that AF10, an interaction partner of the histone methyltransferase DOT1L, is essential for efficient H3K79 methylation, thus regulating HOX-gene transcription and transformation in myeloid leukemia.
EVALuna2:25714

Drug Therapy Safety with new oral Antitumor Agents for the Therapy of Prostate and Renal Cell Carcinoma: Findings from the AMBORA Study - Cuba, Lisa; Schlichtig, Katja; Dürr, Pauline; Bellut, Laura; Meidenbauer, Norbert; Kunath, Frank; Goebell, Peter; Mackensen, Andreas; Dörje, Frank; Fromm, Martin; Wullich, Bernd (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Dual checkpoint blockade of CD47 and LILRB1 enhances CD20 antibody-dependent phagocytosis of lymphoma cells by macrophages - Zeller, Tobias; Lutz, Sebastian; Münnich, Ira A.; Windisch, Roland; Hilger, Patricia; Herold, Tobias; Tahiri, Natyra; Banck, Jan C.; Weigert, Oliver; Moosmann, Andreas; von Bergwelt-Baildon, Michael; Flamann, Cindy; et al. (Frontiers in Immunology, 2022)
Antibody-dependent cellular phagocytosis (ADCP) by macrophages, an important effector function of tumor targeting antibodies, is hampered by ‘Don´t Eat Me!’ signals such as CD47 expressed by cancer cells. Yet, human leukocyte antigen (HLA) class I expression may also impair ADCP by engaging leukocyte immunoglobulin-like receptor subfamily B (LILRB) member 1 (LILRB1) or LILRB2. Analysis of different lymphoma cell lines revealed that the ratio of CD20 to HLA class I cell surface molecules determined the sensitivity to ADCP by the combination of rituximab and an Fc-silent variant of the CD47 antibody magrolimab (CD47-IgGσ). To boost ADCP, Fc-silent antibodies against LILRB1 and LILRB2 were generated (LILRB1-IgGσ and LILRB2-IgGσ, respectively). While LILRB2-IgGσ was not effective, LILRB1-IgGσ significantly enhanced ADCP of lymphoma cell lines when combined with both rituximab and CD47-IgGσ. LILRB1-IgGσ promoted serial engulfment of lymphoma cells and potentiated ADCP by non-polarized M0 as well as polarized M1 and M2 macrophages, but required CD47 co-blockade and the presence of the CD20 antibody. Importantly, complementing rituximab and CD47-IgGσ, LILRB1-IgGσ increased ADCP of chronic lymphocytic leukemia (CLL) or lymphoma cells isolated from patients. Thus, dual checkpoint blockade of CD47 and LILRB1 may be promising to improve antibody therapy of CLL and lymphomas through enhancing ADCP by macrophages.
CRIS-Team Scopus Importer:2022-11-25
Keywords: antibody therapy; CD20; CD47; innate immune checkpoint blockade; LILRB1 (ILT2); lymphoma; macrophages; phagocytosis

Dual immune checkpoint blockade of LILRB1 and CD47 enhances antibody-dependent cellular phagocytosis of lymphoma cells by CD20 antibodies - Zeller, T.; Lutz, S.; Muennich, I. A.; Windisch, R.; Hilger, P.; Herold, T.; Tahiri, N.; Banck, J. C.; Weigert, O.; Moosmann, A.; Von Bergwelt-Baildon, M.; Bruns, Heiko; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Dual-targeting triplebody 33-16-123 (SPM-2) mediates effective redirected lysis of primary blasts from patients with a broad range of AML subtypes in combination with natural killer cells - Braciak, Todd A.; Roskopf, Claudia C.; Wildenhain, Sarah; Fenn, Nadja C.; Schiller, Christian B.; Schubert, Ingo A.; Jacob, Uwe; Honegger, Annemarie; Krupka, Christina; Subklewe, Marion; Spiekermann, Karsten; Hopfner, Karl-Peter; et al. (OncoImmunology, 2018)
A number of agents designed for immunotherapy of Acute Myeloid Leukemia (AML) are in preclinical and early clinical development. Most of them target a single antigen on the surface of AML cells. Here we describe the development and key biological properties of a tri-specific agent, the dual-targeting triplebody SPM-2, with binding sites for target antigens CD33 and CD123, and for CD16 to engage NK cells as cytolytic effectors. Primary blasts of nearly all AML patients carry at least one of these target antigens and the pair is particularly promising for the elimination of blasts and leukemia stem cells (LSCs) from a majority of AML patients by dual-targeting agents. The cytolytic activity of NK cells mediated by SPM-2 was analyzed in vitro for primary leukemic cells from 29 patients with a broad range of AML-subtypes. Blasts from all 29 patients, including patients with genomic alterations associated with an unfavorable genetic subtype, were lysed at nanomolar concentrations of SPM-2. Maximum susceptibility was observed for cells with a combined density of CD33 and CD123 above 10,000 copies/cell. Cell populations enriched for AML-LSCs (CD34pos and CD34pos CD38neg cells) from 2 AML patients carried an increased combined antigen density and were lysed at correspondingly lower concentrations of SPM-2 than unsorted blasts. These initial findings raise the expectation that SPM-2 may also be capable of eliminating AML-LSCs and thus of prolonging survival. In the future, patients with a broad range of AML subtypes may benefit from treatment with SPM-2.
EVALuna2:34647

Dysregulation of the B lymphocyte compartment in patients with chronic graft-versus-host disease - Habenicht, Katharina Marie; Bootz, Anna; Schneider, Alexandra; Schäfer, Simon; Hoffmann, P.; Winkler, Julia; Wolff, D.; Winkler, Thomas (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Early clinical trial unit tumor board: a real-world experience in a national cancer network - Weiss, L.; Dorman, K.; Boukovala, M.; Schwinghammer, F.; Jordan, P.; Fey, T.; Hasselmann, K.; Subklewe, M.; Bücklein, V.; Bargou, R.; Goebeler, M.; Sayehli, C.; et al. (Journal of Cancer Research and Clinical Oncology, 2023)
Purpose: Early clinical trials are the first step into clinical therapies for new drugs. Within the six Bavarian university-based hospitals (Augsburg, Erlangen, Regensburg, Munich (LMU and TU), Würzburg) we have enrolled a virtual network platform for patient discussion. Methods: The virtual Early Clinical Trial Unit Tumor Board (ECTU Tumor Board) is a secured web-based meeting to evaluate early clinical trial options for patients, where representatives from local ECTUs participate. We retrospectively analyzed patient cases discussed between November 2021 and November 2022. Results: From November 2021 to November 2022, a total of 43 patients were discussed in the ECTU Tumor Board. Median age at diagnosis was 44.6 years (range 10–76 years). The median number of previous lines of therapies was 3.7 (range 1–9 therapies) including systemic treatment, surgery, and radiation therapy. A total of 27 different tumor entities were presented and 83.7% (36/43) patients received at least one trial recommendation. In total, 21 different active or shortly recruiting clinical trials were recommended: ten antibody trials, four BiTE (bispecific T cell engager) trials, six CAR (chimeric antigen receptor) T-cell trials, and one chemotherapy trial. Only six trials (28.6%) were recommended on the basis of the previously performed comprehensive genetic profiling (CGP). Conclusion: The ECTU Tumor Board is a feasible and successful network, highlighting the force of virtual patient discussions for improving patient care as well as trial recruitment in advanced diseases. It can provide further treatment options after local MTB presentation, aiming to close the gap to access clinical trials.
CRIS-Team Scopus Importer:2023-08-04
Keywords: Clinical trials; Early clinical trial; ECTU; Interdisciplinary; Precision oncology; Tumor board

Early Expansion of CD19.CAR-T Cells in vivo identify the Patients at Risk for the Treatment Failure in diffuse large B-Cell Lymphoma - Blumenberg, V.; Busch, G.; Baumann, S.; Jitschin, R.; Winkelmann, M.; Hellwig, Konstantin; Schmidt, C.; Froehlich, L.; Tast, B.; Hildebrand, F.; Rejeski, K.; Dekorsy, F.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Early Initiation of Anticoagulation with Direct Oral Anticoagulants in Patients after Transient Ischemic Attack or Ischemic Stroke - Macha, Kosmas; Volbers, Bastian; Bobinger, Tobias; Kurka, Natalia; Breuer, Lorenz; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin (Journal of Stroke and Cerebrovascular Diseases, 2016)
Direct oral anticoagulants (DOACs) are increasingly used for secondary prevention of cardioembolic stroke. While DOACs are associated with a long-term reduced risk of intracranial hemorrhage compared to vitamin K antagonists, pivotal trials avoided the very early period after stroke and few data exist on early initiation of DOAC therapy post stroke.We retrospectively analyzed data from our prospective database of all consecutive transient ischemic attack (TIA) or ischemic stroke patients with atrial fibrillation treated with DOACs during hospital stay. As per our institutional treatment algorithm for patients with cardioembolic ischemia DOACs are started immediately in TIA and minor stroke (group 1), within days 3-5 in patients with infarcts affecting one third or less of the middle cerebral artery, the anterior cerebral artery, or the posterior cerebral artery territories (group 2) as well as in infratentorial stroke (group 3) and after 1-2 weeks in patients with large infarcts (> 1/3 MCA territory, group 4). We investigated baseline characteristics, time to initiation of DOAC therapy after symptom onset, and hemorrhagic complications.In 243 included patients, administration of DOAC was initiated 40.5 hours (interquartile range [IQR] 23.0-65.5) after stroke onset in group 1 (n = 41) and after 76.7 hours (IQR 48.0-134.0), 108.4 hours (IQR 67.3-176.4), and 161.8 hours (IQR 153.9-593.8) in groups 2-4 (n = 170, 28, and 4), respectively. Two cases of asymptomatic intracranial hemorrhage (.8%) and 1 case of symptomatic intracranial hemorrhage (.4%) were observed, both in group 2.No severe safety issues were observed in early initiation of DOACs for secondary prevention after acute stroke in our in-patient cohort.
EVALuna2:22461

Early quantification of anti-CD19 CAR T cells by flow cytometry predicts response in R/R DLBCL - Blumenberg, Viktoria; Busch, Galina; Baumann, Stephan; Jitschin, Regina; Iacoboni, Gloria; Gallur, Laura; Iraola-Truchuelo, Josu; Hoster, Eva; Winkelmann, Michael; Hellwig, Konstantin; Schmidt, Christian; Frölich, Lisa; et al. (Blood Advances, 2023)
CRIS-Team Scopus Importer:2023-12-15

Early Real Time Quantification of CD19. CAR T Cells By Flow Cytometry As a Predictive Biomarker for Response in Patients with R/R LBCL - Blumenberg, Viktoria; Busch, Galina; Baumann, Stephan; Jitschin, Regina; Winkelmann, Michael; Hellwig, Konstantin; Rejeski, Kai; Froelich, Lisa; Tast, Benjamin; Schmidt, Christian; Hildebrandt, Friederike; Dekorsy, Franziska; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-17

Editorial: NK-Myeloid Cell Interactions in the Tumor Microenvironment: Implications for Cancer Immunotherapy - Wennerberg, Erik; Lundqvist, Andreas; Mao, Yumeng; Mougiakakos, Dimitrios (Frontiers in Immunology, 2021)
CRIS-Team Scopus Importer:2021-07-30
Keywords: cancer immunotherapy; cytokines; dendritic cells; MDSCs (myeloid-derived suppressor cells); myeloid cells; NK cells; platelets

Effective elimination of acute myeloid leukemic cells by recombinant bispecific antibody derivatives directed against CD33 and CD16. - Singer, Heiko; Kellner, Christian; Lanig, Harald; Aigner, Michael; Stockmeyer, Bernhard; Oduncu, Fuat S.; Schwemmlein, Michael; Stein, Christoph; Mentz, Kristin; Mackensen, Andreas; Fey, Georg (Journal of immunotherapy (Hagerstown, Md. : 1997), 2010)
Single-chain Fv triplebodies (sctb), consisting of a single polypeptide chain with 3 single-chain antibody variable fragments connected in tandem, were generated as antileukemic agents. A CD19-specific sctb of this format has previously been shown to be superior to a bispecific single-chain Fv antibody fragment (bsscFv) for the elimination of leukemic B-lineage cells, but corresponding targeted agents for the treatment of acute myeloid leukemia are still lacking. For this purpose, both a bsscFv and a sctb specific for CD33 and the trigger molecule CD16 (FcgammaRIII) were produced. The sctb displayed 3.5-fold greater avidity for CD33 than the bsscFv 33xds16, whereas both had close to equal affinity for CD16. In antibody-dependent cellular cytotoxicity (ADCC) reactions with human mononuclear cells as effectors, both the bsscFv 33xds16 and the sctb induced lysis of tumor cells with half maximum effective concentrations (EC50) in the low picomolar range. It is interesting to note that the sctb promoted equal lysis of human leukemia-derived cell lines at 10 to 200-fold lower concentrations than the bsscFv. Both molecules mediated ADCC of primary patient cells. In conclusion, both the bsscFv 33xds16 and the sctb 33xds16x33 eliminated acute myeloid leukemia cells in ADCC reactions, but the novel sctb format showed significantly greater specific activity.

Effective Treatment of Low Risk Acute Gvhd with Itacitinib Monotherapy - Capellini, Alexandra; Etra, Aaron; Alousi, Amin M.; Al Malki, Monzr M.; Choe, Hannah; Defilipp, Zachariah; Hogan, William J.; Kitko, Carrie Lynn; Ayuk, Francis A.; Baez, Janna; Gandhi, Isha; Kasikis, Stelios; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Effective treatment of low-risk acute GVHD with itacitinib monotherapy - Etra, Aaron; Capellini, Alexandra; Alousi, Amin; Al Malki, Monzr M.; Choe, Hannah; DeFilipp, Zachariah; Hogan, William J.; Kitko, Carrie L.; Ayuk, Francis; Baez, Janna; Gandhi, Isha; Kasikis, Stelios; et al. (Blood, 2023)
The standard primary treatment for acute graft-versus-host disease (GVHD) requires prolonged, high-dose systemic corticosteroids (SCSs) that delay reconstitution of the immune system. We used validated clinical and biomarker staging criteria to identify a group of patients with low-risk (LR) GVHD that is very likely to respond to SCS. We hypothesized that itacitinib, a selective JAK1 inhibitor, would effectively treat LR GVHD without SCS. We treated 70 patients with LR GVHD in a multicenter, phase 2 trial (NCT03846479) with 28 days of itacitinib 200 mg/d (responders could receive a second 28-day cycle), and we compared their outcomes to those of 140 contemporaneous, matched control patients treated with SCSs. More patients responded to itacitinib within 7 days (81% vs 66%, P = .02), and response rates at day 28 were very high for both groups (89% vs 86%, P = .67), with few symptomatic flares (11% vs 12%, P = .88). Fewer itacitinib-treated patients developed a serious infection within 90 days (27% vs 42%, P = .04) due to fewer viral and fungal infections. Grade ≥3 cytopenias were similar between groups except for less severe leukopenia with itacitinib (16% vs 31%, P = .02). No other grade ≥3 adverse events occurred in >10% of itacitinib-treated patients. There were no significant differences between groups at 1 year for nonrelapse mortality (4% vs 11%, P = .21), relapse (18% vs 21%, P = .64), chronic GVHD (28% vs 33%, P = .33), or survival (88% vs 80%, P = .11). Itacitinib monotherapy seems to be a safe and effective alternative to SCS treatment for LR GVHD and deserves further investigation.
CRIS-Team Scopus Importer:2023-02-03

Effect of Idelalisib on PKC beta/NF-kappa B regulation in stromal cells of chronic lymphocytic leukemia - Lutzny-Geier, Gloria; Handl, Sarah Annika; Von Heydebrand, F.; Wilke, J.; Kremer, Anna-Lena; Mackensen, Andreas; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Effect of Proinflammatory and Homeostatic Cytokines on the Functionality of Human Double-Negative Regulatory T Cells - Peuser, Moritz; Haug, Tabea; Aigner, Michael; Mackensen, Andreas; Völkl, Simon (BLOOD, 2018)
CRIS-Team WoS Importer:2019-02-27

Effects of Anti-Integrin Treatment With Vedolizumab on Immune Pathways and Cytokines in Inflammatory Bowel Diseases - Rath, Timo; Billmeier, Ulrike; Ferrazzi, Fulvia; Ekici, Arif Bülent; Neurath, Markus; Atreya, Raja; Vieth, Michael (Frontiers in Immunology, 2018)
Background and aims: Despite proven clinical efficacy of vedolizumab (VDZ) for inducing and maintaining remission in patients with Crohn's disease (CD) and ulcerative colitis (UC), subgroups of patients have no therapeutic benefit from anti-α4β7 integrin therapy with VDZ. Within this study, we aimed to identify genetic, cellular, and immunological mechanisms that define response and failure to VDZ treatment. Methods: Intestinal RNA sequencing was performed in UC and CD patients before and at week 14 of VDZ therapy. α4β7 expression on peripheral and mucosal immune cells was assessed by flow cytometry and immunohistochemistry. Cellular modes of VDZ-mediated action were analyzed ex vivo and in VDZ-treated inflammatory bowel disease patients. Results: Transcriptome analysis showed an impairment of signaling cascades associated with adhesion, diapedesis, and migration of granulocytes and agranulocytes upon VDZ therapy. In non-remitters to VDZ therapy, a tissue destructive and leukocyte-mediated inflammatory activity with activation of TNF-dependent pathways was present, all of which were inhibited in remitters to VDZ. Clinical remission was associated with a significant reduction of α4β7 expression on Th2 and Th17 polarized mucosal CD4+ T cells at week 14 of VDZ therapy and with significantly higher numbers of α4β7-expressing mucosal cells prior to the initiation of VDZ therapy compared with non-remitters. Conclusion: Intestinal α4β7 expression prior to VDZ therapy might represent a biomarker that predicts therapeutic response to subsequent VDZ treatment. Due to high activation of TNF signaling in VDZ non-remitters, anti-TNF treatment might represent a promising therapeutic strategy in VDZ refractory patients.
EVALuna2:34622

Effects of the Selective Sodium-Glucose Cotransporter 2 Inhibitor Empagliflozin on Vascular Function and Central Hemodynamics in Patients With Type 2 Diabetes Mellitus - Striepe, Kristina; Jumar, Agnes; Ott, Christian; Karg, Margarete; Schneider, Markus; Kannenkeril, Dennis; Schmieder, Roland (Circulation, 2017)
EVALuna2:4021

Effects of the STAMP-inhibitor asciminib on T cell activation and metabolic fitness compared to tyrosine kinase inhibition by imatinib, dasatinib, and nilotinib - Häselbarth, Lukas; Karow, Axel; Mentz, Kristin; Böttcher, Martin; Roche-Lancaster, Oisin; Krumbholz, Manuela; Jitschin, Regina; Mougiakakos, Dimitrios; Metzler, Markus (Cancer Immunology, Immunotherapy, 2023)
T cell function is central to immune reconstitution and control of residual chronic myeloid leukemia (CML) cells after treatment initiation and is associated with achieving deep molecular response as a prerequisite for treatment-free remission, the ultimate therapeutic goal in CML. ATP-pocket-binding tyrosine kinase inhibitors (TKIs) like imatinib, dasatinib, and nilotinib are widely used for treating CML, but they have shown to inhibit T cell function as an “off-target” effect. Therefore, we tested asciminib, the first-in-class BCR::ABL1 fusion protein inhibitor specifically targeting the ABL myristoyl pocket (STAMP) and compared its effects on T cell function with imatinib, dasatinib, and nilotinib. Whereas all four TKIs inhibited the expression of the co-stimulatory protein CD28, the amino acid transporter CD98, proliferation, and secretion of pro-inflammatory cytokines IFNγ, IL-6, and IL-17A upon T cell stimulation, asciminib had less impact on PD-1, activation markers, and IL-2 secretion. T cells treated with asciminib and the other TKIs maintained their ability to mobilize their respiratory capacity and glycolytic reserve, which is an important surrogate for metabolic fitness and flexibility. Overall, we found milder inhibitory effects of asciminib on T cell activation, which might be beneficial for the immunological control of residual CML cells.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Activity; Asciminib; CML; Metabolism; T cell; TKI

Effects of weak/non-complement-binding HLA antibodies on C1q-binding - Hönger, G.; Amico, P.; Spriewald, B. M.; Schaub, S.; Arnold, Martin (HLA, 2017)
It is unknown under what conditions and to what extent weak/non-complement (C)-binding IgG subclasses (IgG2/IgG4) can block C1q-binding triggered by C-binding IgG subclasses (IgG1/IgG3). Therefore, we investigated in vitro C1q-binding induced by IgG subclass mixtures targeting the same HLA epitope. Various mixtures of HLA class II specific monoclonal antibodies of different IgG subclasses but identical V-region were incubated with HLA DRB1*07:01 beads and monitored for C1q-binding. The lowest concentration to achieve maximum C1q-binding was measured for IgG3, followed by IgG1, while IgG2 and IgG4 did not show appreciable C1q-binding. C1q-binding occurred only after a critical amount of IgG1/3 has bound and sharply increased thereafter. When both, C-binding and weak/non-C-binding IgG subclasses were mixed, C1q-binding was diminished proportionally to the fraction of IgG2/4. A 2- to 4-fold excess of IgG2/4 inhibited C1q-binding by 50%. Very high levels (10-fold excess) almost completely abrogated C1q-binding even in the presence of significant IgG1/3 levels that would usually lead to strong C1q-binding. In sensitized renal allograft recipients, IgG subclass constellations with >= 2-fold excess of IgG2/4 over IgG1/3 were present in 23/66 patients (34.8%) and overall revealed slightly decreased C1q signals. However, spiking of patient sera with IgG2 targeting a different epitope than the patient's IgG1/3 synergistically increased C1q-binding. In conclusion, if targeting the same epitope, an excess of IgG2/4 is repressing the extent of IgG1/3 triggered C1q-binding in vitro. Such IgG subclass constellations are present in about a third of sensitized patients and their net effect on C1q-binding is slightly inhibitory.
EVALuna2:13437

Efficacy of Ropeginterferon Alpha 2b in Inducing Treatment Free Remission in Chronic Myeloid Leukemia - an International, Randomized Phase III Trial (ENDURE, CML-IX) of the German CML-Study Group - Burchert, Andreas; Saussele, Susanne; Michel, Christian; Metzelder, Stephan K.; Hochhaus, Andreas; Gattermann, Norbert; Crysandt, Martina; Schafhausen, Philippe; Bormann, Matthias; Radsak, Markus P.; Guerci-Bresler, Agnes; Illmer, Thomas; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

EFFICACY OF WNT PATHWAY INHIBITORS FOR THE PREVENTION OF CARDIAC ALLOGRAFT VASCULOPATHY IN A MOUSE MODEL - Kuckhahn, A.; Ramsperger-Gleixner, Martina; Distler, Jörg; Spriewald, B.; Ensminger, S.; Weyand, Michael; Heim, Christian (TRANSPLANT INTERNATIONAL, 2019)
CRIS-Team WoS Importer:2019-10-29

Efficient Elimination of Cells from Patients with Different AML Subtypes by Dual-Targeting Triplebody 33-16-123 - Braciak, T.; Fenn, N.; Wildenhain, S.; Schiller, C.; Roskopf, C.; Schubert, Ingo; Jacob, U.; Hopfner, K. P.; Honegger, A.; Aigner, M.; Krause, Stefan; Mackensen, Andreas; et al. (ANNALS OF HEMATOLOGY, 2019)
CRIS-Team WoS Importer:2019-03-06

Eine übermäßige Phagozytose von Myelomzellen induziert Pyroptose in Myelom-assoziierten Makrophagen und beeinträchtigt die Wirksamkeit therapeutischer Antikörper - Flamann, Cindy; Biedermann, Alexander; Mougiakakos, D.; Bitterer, Katrin; Karg, K.; Bittenbring, J.; Büttner-Herold, Maike; Liebisch, G.; Leffler, M.; Lischer, Christopher; Eberhardt, Martin; Vera-Gonzales, J.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Emerging Histopathological and Genetic Parameters of Pituitary Adenomas: Clinical Impact and Recommendation for Future WHO Classification - Saeger, W.; Petersenn, S.; Schöfl, Christof; Knappe, U. J.; Theodoropoulou, M.; Buslei, R.; Honegger, J. (Endocrine Pathology, 2016)
The review assesses immunohistochemical findings of somatostatin receptors and of metalloproteinases in different pituitary adenoma types and the significance of molecular genetic data. Current evidence does not support routine immunohistochemical assessment of somatostatin or dopamine receptor subtype expression on hormone-secreting or nonfunctioning pituitary adenomas. Further prospective studies are needed to define its role for clinical decision making. Until then we suggest to restrict membrane receptor profiling to individual cases or for study purposes. The problems of adenoma expansion and invasion are discussed. Despite partially contradictory publications, proteases clearly play a major role in permission of infiltrative growth of pituitary adenomas. Therefore, detection of at least MMP-2, MMP-9, TIMP-2, and uPA seems to be justified. Molecular characterization is important for familial adenomas, adenomas in MEN, Carney complex, and McCune-Albright syndrome and can gain insight into pathogenesis of sporadic adenomas.
EVALuna2:7324

Enasidenib in IDH-2 mutant AML patients with relapse after allogeneic stem cell transplantation - Vasova, Ingrid; Spörl, Silvia; Guggenberger, Valentin; Berisha, M.; Rech, D.; Behzad, Ali; Brandt, Amelie; Kremer, A.; Mackensen, Andreas; Rösler, Wolf; Winkler, J. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Energy metabolism is co-determined by genetic variants in chronic lymphocytic leukemia and influences drug sensitivity - Lu, Junyan; Böttcher, Martin; Walther, Tatjana; Mougiakakos, Dimitrios; Zenz, Thorsten; Huber, Wolfgang (Haematologica, 2019)
Chronic lymphocytic leukemia cells have an altered energy metabolism compared to normal B cells. While there is growing understanding of the molecular heterogeneity of the disease, the extent of metabolic heterogeneity and its relation to molecular heterogeneity has not been systematically studied. Here, we assessed 11 bioenergetic features, primarily reflecting cell's oxidative phosphorylation and glycolytic activity, in leukemic cells from 140 chronic lymphocytic leukemia patients using metabolic flux analysis. We surveyed these bioenergetic features for relationships with molecular profiles (including genetic aberrations, transcriptome and methylome profiles) of the tumors, their ex vivo responses to a panel of 63 compounds, and with clinical data. We observed that leukemic cells with mutated immunoglobulin variable heavy-chain show significantly lower glycolytic activity than cells with unmutated immunoglobulin variable heavy-chain. Accordingly, several key glycolytic genes (PFKP, PGAM1 and PGK1) were found to be downregulated in samples harboring mutated immunoglobulin variable heavy-chain. In addition, 8q24 copy number gains, 8p12 deletions, 13q14 deletions and ATM mutations were identified as determinants of cellular respiration. The metabolic state of leukemic cells was associated with drug sensitivity, in particular, higher glycolytic activity was linked to increased resistance towards several drugs including rotenone, navitoclax, and orlistat. In addition, we found glycolytic capacity and glycolytic reserve to be predictors of overall survival (P < 0.05) independent of established genetic predictors. Taken together, our study shows that heterogeneity in the energy metabolism of chronic lymphocytic leukemia cells is influenced by genetic variants and may be exploitable for the choice of therapeutic strategies.
EVALuna2:184247

Enhanced potency of immunotherapy against B-cell precursor acute lymphoblastic leukemia by combination of an Fc-engineered CD19 antibody and CD47 blockade - Schewe, Denis M.; Vogiatzi, Fotini; Münnich, Ira A.; Zeller, Tobias; Windisch, Roland; Wichmann, Christian; Müller, Kristina; Bhat, Hilal; Felix, Elisa; Mougiakakos, Dimitrios; Bruns, Heiko; Lenk, Lennart; et al. (HemaSphere, 2024)
CD19-directed immunotherapy has become a cornerstone in the therapy of B-cell precursor acute lymphoblastic leukemia (BCP-ALL). CD19-directed cellular and antibody-based therapeutics have entered therapy of primary and relapsed disease and contributed to improved outcomes in relapsed disease and lower therapy toxicity. However, efficacy remains limited in many cases due to a lack of therapy response, short remission phases, or antigen escape. Here, BCP-ALL cell lines, patient-derived xenograft (PDX) samples, human macrophages, and an in vivo transplantation model in NOD.Cg-PrkdcscidIl2rgtm1Wjl/SzJ (NSG) mice were used to examine the therapeutic potency of a CD19 antibody Fc-engineered for improved effector cell recruitment (CD19-DE) and antibody-dependent cellular phagocytosis (ADCP), in combination with a novel modified CD47 antibody (Hu5F9-IgG2σ). For the in vivo model, only samples refractory to CD19-DE monotherapy were chosen. Hu5F9-IgG2σ enhanced ADCP by CD19-DE in various BCP-ALL cell line models with varying CD19 surface expression and cytogenetic backgrounds, two of which contained the KMT2A-AFF1 fusion. Also, the antibody combination was efficient in inducing ADCP by human macrophages in pediatric PDX samples with and adult samples with and without KMT2A-rearrangement in vitro. In a randomized phase 2-like PDX trial using seven KMT2A-rearranged BCP-ALL samples in NSG mice, the CD19/CD47 antibody combination proved highly efficient. Our findings support that the efficacy of Fc-engineered CD19 antibodies may be substantially enhanced by a combination with CD47 blockade. This suggests that the combination may be a promising therapy option for BCP-ALL, especially in relapsed patients and/or patients refractory to CD19-directed therapy.
CRIS-Team Scopus Importer:2024-03-22

Enhancing the Activation and Releasing the Brakes: A Double Hit Strategy to Improve NK Cell Cytotoxicity Against Multiple Myeloma - Tognarelli, Sara; Wirsching, Sebastian; Von Metzler, Ivana; Rais, Bushra; Jacobs, Benedikt; Serve, Hubert; Bader, Peter; Ullrich, Evelyn (Frontiers in Immunology, 2018)
Natural killer (NK) cells are innate lymphocytes with a strong antitumor ability. In tumor patients, such as multiple myeloma (MM) patients, an elevated number of NK cells after stem cell transplantation (SCT) has been reported to be correlated with a higher overall survival rate. With the aim of improving NK cell use for adoptive cell therapy, we also addressed the cytotoxicity of patient-derived, cytokine-stimulated NK cells against MM cells at specific time points: at diagnosis and before and after autologous stem cell transplantation. Remarkably, after cytokine stimulation, the patients' NK cells did not significantly differ from those of healthy donors. In a small cohort of MM patients, we were able to isolate autologous tumor cells, and we could demonstrate that IL-2/15 stimulated autologous NK cells were able to significantly improve their killing capacity of autologous tumor cells. With the aim to further improve the NK cell killing capacity against MM cells, we investigated the potential use of NK specific check point inhibitors with focus on NKG2A because this inhibitory NK cell receptor was upregulated following ex vivo cytokine stimulation and MM cells showed HLA-E expression that could even be increased by exposure to IFN-γ. Importantly, blocking of NKG2A resulted in a significant increase in the NK cell-mediated lysis of different MM target cells. Finally, these results let suggest that combining cytokine induced NK cell activation and the specific check point inhibition of the NKG2A-mediated pathways can be an effective strategy to optimize NK cell therapeutic approaches for treatment of multiple myeloma.
EVALuna2:35088

Epidemiology of invasive aspergillosis and azole resistance in patients with acute leukaemia: the SEPIA Study - Koehler, Philipp; Hamprecht, Axel; Bader, Oliver; Bekeredjian-Ding, Isabelle; Buchheidt, Dieter; Doelken, Gottfried; Elias, Johannes; Haase, Gerhard; Hahn-Ast, Corinna; Karthaus, Meinolf; Kekule, Alexander; Keller, Peter; et al. (International Journal of Antimicrobial Agents, 2016)
Invasive aspergillosis (IA) is a serious hazard to high-risk haematological patients. There are increasing reports of azole-resistant Aspergillus spp. This study assessed the epidemiology of IA and azole-resistant Aspergillus spp. in patients with acute leukaemia in Germany. A prospective multicentre cohort study was performed in German haematology/oncology centres. The incidence of probable and proven aspergillosis according to the revised EORTC/MSG criteria was assessed for all patients with acute leukaemia [acute myeloid leukaemia (AML) and acute lymphoblastic leukaemia (ALL)]. Cases were documented into a web-based case report form, and centres provided data on standards regarding prophylactic and diagnostic measures. Clinical isolates were screened centrally for azole resistance and, if applicable, underlying resistance mechanisms were analysed. Between September 2011 and December 2013, 179 cases of IA [6 proven (3.4%) and 173 probable (96.6%)] were diagnosed in 3067 patients with acute leukaemia. The incidence of IA was 6.4% among 2440 AML patients and 3.8% among 627 ALL patients. Mortality at Day 84 was 33.8% (49/145) and attributable mortality was 26.9% (39/145). At Day 84, 53 patients (29.6%) showed a complete response, 25 (14.0%) a partial response and 17 (9.5%) a deterioration or failure. A total of 77 clinical Aspergillus fumigatus isolates were collected during the study period. Two episodes of azole-resistant IA (1.1%) were caused by a TR/L98H mutation in the cyp51A gene. With only two cases of IA due to azole-resistant A. fumigatus, a change of antifungal treatment practices in Germany does not appear warranted currently.
EVALuna2:25757

Essential respiratory chain subunits encoded by mitochondrial DNA control plasma cell development - Urbanczyk, Sophia; Baris, Olivier; Mougiakakos, Dimitrios; Wiesner, Rudolf; Jäck, Hans-Martin; Mielenz, Dirk (JOURNAL OF IMMUNOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-08

Evaluating the RIST Molecular-Targeted Regimen in a Three-Dimensional Neuroblastoma Spheroid Cell Culture Model - Kaess, Carina; Matthes, Marie; Gross, Jonas; Waetzig, Rebecca; Heise, Tilman; Corbacioglu, Selim; Sommer, Gunhild (Cancers, 2023)
Background: The outcome for patients with high-risk neuroblastoma remains poor and novel treatment strategies are urgently needed. The RIST protocol represents a novel metronomic and multimodal treatment strategy for high-risk neuroblastoma combining molecular-targeted drugs as ‘pre-treatment’ with a conventional chemotherapy backbone, currently evaluated in a phase II clinical trial. For preclinical drug testing, cancer cell growth as spheroid compared to mo-nolayer cultures is of advantage since it reproduces a wide range of tumor characteristics, including the three-dimensional architecture and cancer stem cell (CSC) properties. The objective of this study was to establish a neuroblastoma spheroid model for the rigorous assessment of the RIST treatment protocol. Methods: Evaluation of CSC marker expression was performed by mRNA and protein analysis and spheroid viability by luminescence-based assays. Aberrant expression of RNA-binding protein La in neuroblastoma was assessed by tissue microarray analysis and patients’ data mining. Results: Spheroid cultures showed increased expression of a subgroup of CSC-like markers (CXCR4, NANOG and BMI) and higher Thr389 phosphorylation of the neuroblastoma-associated RNA-binding protein La when compared to monolayer cultures. Molecular-targeted ‘pre-treatment’ of spheroids decreased neoplastic signaling and CSC marker expression. Conclusions: The RIST treatment protocol efficiently reduced the viability of neuroblastoma spheroids characterized by advanced CSC properties.
CRIS-Team Scopus Importer:2023-04-14
Keywords: 3D model; cancer stem cells; CSC; La (LARP3; La autoantigen); La/SSB; neuroblastoma; RIST; RNA-binding protein; spheroids; three-dimensional

Evaluation of Elafin as a Prognostic Biomarker in Acute Graft-versus-Host Disease: M. G. Zewde et al - Zewde, Makda Getachew; Morales, George; Gandhi, Isha; Özbek, Umut; Aguayo-Hiraldo, Paibel; Ayuk, Francis; Baez, Janna; Chanswangphuwana, Chantiya; Choe, Hannah; DeFilipp, Zachariah; Etra, Aaron; Grupp, Stephan; et al. (Transplantation and Cellular Therapy, 2021)
Acute graft-versus-host disease (GVHD) is a major cause of mortality in patients undergoing hematopoietic cell transplantation (HCT) for hematologic malignancies. The skin is the most commonly involved organ in GVHD. Elafin, a protease inhibitor overexpressed in inflamed epidermis, was previously identified as a diagnostic biomarker of skin GVHD; however, this finding was restricted to a subset of patients with isolated skin GVHD. The main driver of nonrelapse mortality (NRM) in HCT recipients is gastrointestinal (GI) GVHD. Two biomarkers, Regenerating islet-derived 3a (REG3α) and Suppressor of tumorigenesis 2 (ST2), have been validated as biomarkers of GI GVHD that predict long-term outcomes in patients treated for GVHD. We undertook this study to determine the utility of elafin as a prognostic biomarker in the general population of acute GVHD patients in whom GVHD may develop in multiple organs. We analyzed serum elafin concentrations as a predictive biomarker of acute GVHD outcomes and compared it with ST2 and REG3α in a large group of patients treated at multiple centers. A total of 526 patients from the Mount Sinai Acute GVHD International Consortium (MAGIC) who had received corticosteroid treatment for skin GVHD and who had not been previously studied were analyzed. Serum concentrations of elafin, ST2, and REG3α were measured by ELISA in all patients. The patients were divided at random into equal training and validation sets, and a competing-risk regression model was developed to model 6-month NRM using elafin concentration in the training set. Additional models were developed using concentrations of ST2 and REG3α or the combination of all 3 biomarkers as predictors. Receiver operating characteristic (ROC) curves were constructed using the validation set to evaluate the predictive accuracy of each model and to stratify patients into high- and low-risk biomarker groups. The cumulative incidence of 6-month NRM, overall survival (OS), and 4-week treatment response were compared between the risk groups. Unexpectedly, patients in the low-risk elafin group demonstrated a higher incidence of 6-month NRM, although the difference was not statistically significant (17% versus 11%; P = .19). OS at 6 months (68% versus 68%; P > .99) and 4-week response (78% versus 78%; P = .98) were similar in the low-risk and high-risk elafin groups. The area under the ROC curve (AUC) was 0.55 for elafin and 0.75 for the combination of ST2 and REG3α. The addition of elafin to the other 2 biomarkers did not improve the AUC. Our data indicate that serum elafin concentrations measured at the initiation of systemic treatment for acute GVHD did not predict 6-month NRM, OS, or treatment response in a multicenter population of patients treated systemically for acute GVHD. As seen in previous studies, serum concentrations of the GI GVHD biomarkers ST2 and REG3α were significant predictors of NRM, and the addition of elafin levels did not improve their accuracy. These results underscore the importance of GI disease in driving NRM in patients who develop acute GVHD.
CRIS-Team Scopus Importer:2021-12-17
Keywords: biomarkers; Graft-versus-host disease; hematopoietic cell transplantation

Evaluation of pregnancies after allogeneic stem cell transplantation during the last 15years in Germany - Sockel, K.; Frank, S.; Neu, A.; Ditschkowski, M.; Hilgendorf, I.; Goeckenjan, M.; Stoelzel, F.; Middeke, J. M.; Kroeger, N.; Ayuketang, Ayuk F.; Eder, M.; Bethge, W.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Expansion of IL-23 receptor bearing TNFR2+ T cells is associated with molecular resistance to anti-TNF therapy in Crohn's disease - Schmitt, Heike; Billmeier, Ulrike; Dieterich, Walburga; Rath, Timo; Sonnewald, Sophia; Reid, Stephen; Hirschmann, Simon; Hildner, Kai; Waldner, Maximilian; Mudter, Jonas; Hartmann, Arndt; Grützmann, Robert; et al. (Gut, 2018)
OBJECTIVE: Anti-tumour necrosis factor (TNF) antibodies are successfully used for treatment of Crohn's disease. Nevertheless, approximately 40% of patients display failure to anti-TNF therapy. Here, we characterised molecular mechanisms that are associated with endoscopic resistance to anti-TNF therapy. DESIGN: Mucosal and blood cells were isolated from patients with Crohn's disease prior and during anti-TNF therapy. Cytokine profiles, cell surface markers, signalling proteins and cell apoptosis were assessed by microarray, immunohistochemistry, qPCR, ELISA, whole organ cultures and FACS. RESULTS: Responders to anti-TNF therapy displayed a significantly higher expression of TNF receptor 2 (TNFR2) but not IL23R on T cells than non-responders prior to anti-TNF therapy. During anti-TNF therapy, there was a significant upregulation of mucosal IL-23p19, IL23R and IL-17A in anti-TNF non-responders but not in responders. Apoptosis-resistant TNFR2+IL23R+ T cells were significantly expanded in anti-TNF non-responders compared with responders, expressed the gut tropic integrins α4β7, and exhibited increased expression of IFN-γ, T-bet, IL-17A and RORγt compared with TNFR2+IL23R- cells, indicating a mixed Th1/Th17-like phenotype. Intestinal TNFR2+IL23R+ T cells were activated by IL-23 derived from CD14+ macrophages, which were significantly more present in non-responders prior to anti-TNF treatment. Administration of IL-23 to anti-TNF-treated mucosal organ cultures led to the expansion of CD4+IL23R+TNFR2+ lymphocytes. Functional studies demonstrated that anti-TNF-induced apoptosis in mucosal T cells is abrogated by IL-23. CONCLUSIONS: Expansion of apoptosis-resistant intestinal TNFR2+IL23R+ T cells is associated with resistance to anti-TNF therapy in Crohn's disease. These findings identify IL-23 as a suitable molecular target in patients with Crohn's disease refractory to anti-TNF therapy.
EVALuna2:34305

Expansion of Plasmablasts at Day 90 after Allogeneic Stem Cell Transplantation Predict Chronic Gvhd - Habenicht, Katharina Marie; Bootz, Anna; Schäfer, Simon; Vasova, Ingrid; Fante, Matthias; Schneider, Andrea; Rehli, Michael; Hoffmann, Petra; Rösler, Wolf; Edinger, Matthias; Herr, Wolfgang; Mackensen, Andreas; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Exploitable metabolic dependencies in MLL-ENL-induced leukemia - Garcia-Cuellar, Maria-Paz; Lawlor, Jennifer; Böttcher, Martin; Mougiakakos, Dimitrios; Metzler, Markus; Slany, Robert (Blood Advances, 2020)
Mixed-lineage leukemia (MLL) fusions are transcriptional activators that induce leukemia, with a dismal prognosis that mandates further elucidation of their transformation mechanism. In this study, knockdown of the direct MLL-ENL target gene polypyrimidine tract binding protein-1 (PTBP1) was rate limiting for cell proliferation and caused a metabolic phenotype associated with reduced glucose consumption and lactate production. This effect was accompanied by a reduction of splice isoform-2 of pyruvate kinase M (PKM2). Because PKM2 restricts glycolytic outflow to provide anabolic intermediates, we tested the consequences of glucose, energy, and Ser/Gly starvation for cell physiology. Administration of deoxyglucose, energetic decoupling with rotenone, and inhibition of Ser biosynthesis by CBR5884 had a significantly stronger influence on self-renewal and survival of transformed cells than on normal controls. In particular, inhibition of Ser synthesis, which branches off glycolysis caused accumulation of reactive oxygen species, DNA damage, and apoptosis, predominantly in leukemic cells. Depletion of exogenous Ser/Gly affected proliferation and self-renewal of murine and human leukemia samples, even though they are classified as nonessential amino acids. Response to Ser/Gly starvation correlated with glucose transport, but did not involve activation of the AMPK energy homeostasis system. Finally, survival times in transplantation experiments were significantly extended by feeding recipients a Ser/Gly-free diet. These results suggest selective starvation as an option for supportive leukemia treatment.
CRIS-Team WoS Importer:2020-09-04

Exploration of Sulfur Assimilation of Aspergillus fumigatus Reveals Biosynthesis of Sulfur-Containing Amino Acids as a Virulence Determinant - Amich, Jorge; Duemig, Michaela; O'Keeffe, Grainne; Binder, Jasmin; Doyle, Sean; Beilhack, Andreas; Krappmann, Sven (Infection and Immunity, 2016)
Fungal infections are of major relevance due to the increased numbers of immunocompromised patients, frequently delayed diagnosis, and limited therapeutics. To date, the growth and nutritional requirements of fungi during infection, which are relevant for invasion of the host, are poorly understood. This is particularly true for invasive pulmonary aspergillosis, as so far, sources of (macro)elements that are exploited during infection have been identified to only a limited extent. Here, we have investigated sulfur (S) utilization by the human-pathogenic mold Aspergillus fumigatus during invasive growth. Our data reveal that inorganic S compounds or taurine is unlikely to serve as an S source during invasive pulmonary aspergillosis since a sulfate transporter mutant strain and a sulfite reductase mutant strain are fully virulent. In contrast, the S-containing amino acid cysteine is limiting for fungal growth, as proven by the reduced virulence of a cysteine auxotroph. Moreover, phenotypic characterization of this strain further revealed the robustness of the subordinate glutathione redox system. Interestingly, we demonstrate that methionine synthase is essential for A. fumigatus virulence, defining the biosynthetic route of this proteinogenic amino acid as a potential antifungal target. In conclusion, we provide novel insights into the nutritional requirements ofA. fumigatus during pathogenesis, a prerequisite to understanding and fighting infection.
EVALuna2:7707

Expression of disialoganglioside GD2 in breast cancer subtypes - Gaß, Paul; Kailayangiri, Sareetha; Hübner, Hanna; Rübner, Matthias; Hartmann, Arndt; Häberle, Lothar; Völkl, Simon; Mackensen, Andreas; Landgraf, Laura; Schulz-Wendtland, Rüdiger; Farwick, Nicole; Roessig, Claudia; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Expression of PD-1 and CTLA-4 Are Negative Prognostic Markers in Renal Cell Carcinoma - Kahlmeyer, Andreas; Stoehr, Christine; Hartmann, Arndt; Goebell, Peter; Wullich, Bernd; Wach, Sven; Taubert, Helge; Erlmeier, Franziska (Journal of Clinical Medicine, 2019)
Immuno-oncological therapy with checkpoint inhibition (CI) has become a new standard treatment in metastatic renal cell carcinoma (RCC), but the prognostic value of the expression of CI therapy target molecules is still controversial. 342 unselected consecutive RCC tumor samples were analyzed regarding their PD-1, PD-L1, and CTLA-4 expression by immunohistochemistry (IHC). The prognostic values for cancer-specific survival (CSS) and overall survival (OS) were analyzed for those not exposed to CI therapy. The expression of PD-1 in tumor-infiltrating mononuclear cells (TIMC) and PD-L1 in tumor cells was detected in 9.4% and 12.3%, respectively (Immune reactive score (IRS) > 0). Furthermore, PD-L1 expression in TIMC (IRS > 0) and CTLA-4 expression in TIMC (>1% positive cells) was detected in 4.8% and 6.3%. PD-1 expression and CTLA-4 expression were significantly associated with a worse OS and CSS in log rank survival analysis and univariate Cox regression analysis. CTLA-4 expression is a prognostic marker that is independently associated with a worse outcome in multivariate Cox regression analysis in the whole cohort (OS: p = 0.013; CSS: p = 0.048) as well as in a non-metastatic subgroup analysis (OS: p = 0.028; CSS: p = 0.022). Patients with combined CTLA-4 expression and PD-1-expression are at highest risk in OS and CSS. In RCC patients, PD-1 expression in TIMC and CTLA-4 expression in TIMC are associated with a worse OS and CSS. The combination of PD-1 expression in TIMC and CTLA-4 expression in TIMC might identify high risk patients. This is, to our knowledge, the first description of CTLA-4 expression to be a prognostic marker in RCC.
CRIS-Team WoS Importer:2019-06-25

Externalized decondensed neutrophil chromatin occludes pancreatic ducts and drives pancreatitis - Leppkes, Moritz; Maueröder, Christian; Hirth, Sebastian; Nowecki, Stefanie; Günther, Claudia; Billmeier, Ulrike; Paulus, Susanne; Biermann, Mona; Munoz, Luis Enrique; Hoffmann, Markus; Wildner, Dane; Croxford, Andrew L.; et al. (Nature Communications, 2016)
Ductal occlusion has been postulated to precipitate focal pancreatic inflammation, while the nature of the primary occluding agents has remained elusive. Neutrophils make use of histone citrullination by peptidyl arginine deiminase-4 (PADI4) in contact to particulate agents to extrude decondensed chromatin as neutrophil extracellular traps (NETs). In high cellular density, NETs form macroscopically visible aggregates. Here we show that such aggregates form inside pancreatic ducts in humans and mice occluding pancreatic ducts and thereby driving pancreatic inflammation. Experimental models indicate that PADI4 is critical for intraductal aggregate formation and that PADI4-deficiency abrogates disease progression. Mechanistically, we identify the pancreatic juice as a strong instigator of neutrophil chromatin extrusion. Characteristic single components of pancreatic juice, such as bicarbonate ions and calcium carbonate crystals, induce aggregated NET formation. Ductal occlusion by aggregated NETs emerges as a pathomechanism with relevance in a plethora of inflammatory conditions involving secretory ducts.
EVALuna2:2052

Extracellular DNA traps in inflammation, injury and healing - Daniel, Christoph; Leppkes, Moritz; Munoz, Luis Enrique; Muñoz, Luis E.; Schley, Gunnar; Schett, Georg; Herrmann, Martin (Nature Reviews Nephrology, 2019)
Following strong activation signals, several types of immune cells reportedly release chromatin and granular proteins into the extracellular space, forming DNA traps. This process is especially prominent in neutrophils but also occurs in other innate immune cells such as macrophages, eosinophils, basophils and mast cells. Initial reports demonstrated that extracellular traps belong to the bactericidal and anti-fungal armamentarium of leukocytes, but subsequent studies also linked trap formation to a variety of human diseases. These pathological roles of extracellular DNA traps are now the focus of intensive biomedical research. The type of pathology associated with the release of extracellular DNA traps is mainly determined by the site of trap formation and the way in which these traps are further processed. Targeting the formation of aberrant extracellular DNA traps or promoting their efficient clearance are attractive goals for future therapeutic interventions, but the manifold actions of extracellular DNA traps complicate these approaches.
CRIS-Team Scopus Importer:2019-07-09

Extracellular vesicles and PD-L1 suppress macrophages, inducing therapy resistance in TP53-deficient B-cell malignancies - Izquierdo, Elena; Vorholt, Daniela; Blakemore, Stuart; Sackey, Benedict; Nolte, Janica L.; Barbarino, Verena; Schmitz, Jan; Nickel, Nadine; Bachurski, Daniel; Lobastova, Liudmila; Nikolic, Milos; Michalik, Michael; et al. (Blood, 2022)
Genetic alterations in the DNA damage response (DDR) pathway are a frequent mechanism of resistance to chemoimmunotherapy (CIT) in B-cell malignancies. We have previously shown that the synergy of CIT relies on secretory crosstalk elicited by chemotherapy between the tumor cells and macrophages. Here, we show that loss of multiple different members of the DDR pathway inhibits macrophage phagocytic capacity in vitro and in vivo. Particularly, loss of TP53 led to decreased phagocytic capacity ex vivo across multiple B-cell malignancies. We demonstrate via in vivo cyclophosphamide treatment using the Eμ-TCL1 mouse model that loss of macrophage phagocytic capacity in Tp53-deleted leukemia is driven by a significant downregulation of a phagocytic transcriptomic signature using small conditional RNA sequencing. By analyzing the tumor B-cell proteome, we identified a TP53-specific upregulation of proteins associated with extracellular vesicles (EVs). We abrogated EV biogenesis in tumor B-cells via clustered regularly interspaced short palindromic repeats (CRISPR)-knockout (KO) of RAB27A and confirmed that the EVs from TP53-deleted lymphoma cells were responsible for the reduced phagocytic capacity and the in vivo CIT resistance. Furthermore, we observed that TP53 loss led to an upregulation of both PD-L1 cell surface expression and secretion of EVs by lymphoma cells. Disruption of EV bound PD-L1 by anti-PD-L1 antibodies or PD-L1 CRISPR-KO improved macrophage phagocytic capacity and in vivo therapy response. Thus, we demonstrate enhanced EV release and increased PD-L1 expression in TP53-deficient B-cell lymphomas as novel mechanisms of macrophage function alteration in CIT resistance. This study indicates the use of checkpoint inhibition in the combination treatment of B-cell malignancies with TP53 loss.
CRIS-Team Scopus Importer:2022-07-08

Extracellular Vesicles of CLL Cells affect T-Cell Activation and promote their Depletion via diverse immunological Checkpoints - Boettcher, M.; Boettcher-Loschinski, R.; Gießl, Andreas; Schlötzer-Schrehardt, Ursula; Bruns, Heiko; Mougiakakos, D. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Ex vivo expanded NK Cells from Melanoma Patients receive their Migration in a 3D Model and lyse autologous Melanoma Cells - Rossner, S.; Czerwinski, Tina; Mark, Christoph; Gross, S.; Karg, Margarete; Bosch, J.; Schuler-Thurner, Beatrice; Fabry, Ben; Schuler, Gerold; Bosch-Voskens, C. (2018)
EVALuna2:34775

Ex vivo expanded NK cells up-regulate natural cytotoxicity receptors able to mediate autologous melanoma cell killing - Roessner, S.; Gross, S.; Karg, M.; Hamann, A.; Campana, D.; Schuler-Thurner, Beatrice; Bosch, J.; Schuler, Gerold; Voskens, C. J. (2017)
EVALuna2:34314

EZH2 Mutations and Impact on Clinical Outcome Analyzed in 1604 Patients with Acute Myeloid Leukemia - Stasik, Sebastian; Middeke, Jan Moritz; Kraemer, Michael; Rollig, Christoph; Kramer, Alwin; Scholl, Sebastian; Hochhaus, Andreas; Crysandt, Martina; Bruemmendorf, Tim H.; Naumann, Ralph; Steffen, Bjoern; Kunzmann, Volker; et al. (BLOOD, 2018)
CRIS-Team WoS Importer:2019-03-06

EZH2 mutations and impact on clinical outcome: an analysis in 1,604 patients with newly diagnosed acute myeloid leukemia - Stasik, Sebastian; Middeke, Jan M.; Kramer, Michael; Roellig, Christoph; Kraemer, Alwin; Scholl, Sebastian; Hochhaus, Andreas; Crysandt, Martina; Bruemmendorf, Tim H.; Naumann, Ralph; Steffen, Bjorn; Kunzmann, Volker; et al. (Haematologica, 2020)
EVALuna2:216180

Fatal Encephalitis Associated with Borna Disease Virus 1 - Korn, Klaus; Coras, Roland; Bobinger, Tobias; Herzog, Sibylle M.; Lücking, Hannes; Stoehr, Roland; Huttner, Hagen; Hartmann, Arndt; Enßer, Armin (New England Journal of Medicine, 2018)
EVALuna2:34851

Fcγ receptor IIB (FcγRIIB) maintains humoral tolerance in the human immune system in vivo. - Bärenwaldt, Anne; Lux, Anja; Danzer, Heike; Spriewald, Bernd M.; Ullrich, Evelyn; Heidkamp, Gordon Frederik; Dudziak, Diana; Nimmerjahn, Falk (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Maintenance of immunological tolerance is crucial to prevent development of autoimmune disease. The production of autoantibodies is a hallmark of many autoimmune diseases and studies in mouse model systems suggest that inhibitory signaling molecules may be important checkpoints of humoral tolerance. By generating humanized mice with normal and functionally impaired Fcγ receptor IIB (FcγRIIB) variants, we show that the inhibitory Fcγ-receptor is a checkpoint of humoral tolerance in the human immune system in vivo. Impaired human FcγRIIB function resulted in the generation of higher levels of serum immunoglobulins, the production of different autoantibody specificities, and a higher proportion of human plasmablasts and plasma cells in vivo. Our results suggest that the inhibitory FcγRIIB may be an important checkpoint of humoral tolerance in the human immune system.

Feasibility, Safety, and Preliminary Efficacy of Very Low-Volume Interval Training in Advanced Cancer Patients - Reljic, Dejan; Herrmann, Hans J.; Jakobs, Benedikt; Dieterich, Walburga; Mougiakakos, Dimitrios; Neurath, Markus; Zopf, Yurdagül (Medicine and science in sports and exercise, 2022)
Purpose High-intensity interval training (HIIT) has been shown to improve cardiorespiratory fitness (CRF) and health-related outcomes in various chronic diseases, including cancer. However, data on feasibility and efficacy of HIIT in advanced cancer patients are still sparse, presumably because of safety concerns, like suspected immunosuppression after vigorous exercise. This randomized, sham-intervention controlled study aimed to investigate feasibility, safety, and preliminary efficacy of very low-volume HIIT (LOW-HIIT) in advanced cancer patients. Methods Twenty-seven patients (55.4 ± 13.2 yr) with different advanced cancers (Union for International Cancer Control [UICC] III/IV) were randomly allocated to LOW-HIIT (n = 13), consisting of 5 × 1 min cycle ergometer intervals (14 min per session total duration) at 80% to 95% HRpeak (two sessions per week for 12 wk), or a sham intervention (n = 14) performing light physical mobilization exercises (SHAM). Primary outcomes were attrition and attendance rates, with values of ≤25% and ≥80%, respectively, considered acceptable. Secondary outcomes were safety, protocol fidelity, physiological (including CRF measures) and patient-reported outcomes (including fatigue and quality of life). Results One of 13 patients (8%) receiving LOW-HIIT dropped out. Mean attendance rate was 93%. The prescribed minimum exercise intensity was consistently reached by all patients. Low-volume HIIT was well tolerated and not associated with any serious adverse event nor with increased infection susceptibility. There were no biochemical signs of acute immunosuppression after LOW-HIIT. Contrarily, differentiation and degranulation of natural killer cells was acutely increased postexercise. Low-volume HIIT improved CRF measures including peak oxygen uptake, self-reported fatigue, physical, and social functioning. No significant changes occurred in the SHAM group. Conclusions Low-volume HIIT can be regarded as feasible and safe in advanced cancer patients. Our preliminary data indicate favorable acute effects on NK-cells and beneficial chronic adaptations in CRF, fatigue, and aspects of quality of life.
CRIS-Team Scopus Importer:2022-10-28
Keywords: AEROBIC EXERCISE; CARDIOPULMONARY FITNESS; HIIT; NK CELLS; ONCOLOGY; SUPPORTIVE CARE

Fever of unknown origin following allogeneic stem cell transplantation - an unusual case - Meintker, Lisa; Kremer, Andreas; Brandt, Adrian; Spoerl, S.; Slanikova, A.; Mackensen, Andreas; Winkler, Julia; Rösler, Wolf (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Flat Panel Detector Computed Tomography-Guided Placement of External Ventricular Drains Using the BrainLAB Headband and Precalibrated Disposable Stylet Instrument: A Cadaveric Feasibility Study - Feulner, Julian; Lang, Stefan; Buder, Thomas; Struffert, Tobias; Buchfelder, Michael; Brandner, Sebastian (World Neurosurgery, 2018)
BACKGROUND: The standard freehand method for the insertion of external ventricular drains (EVDs) is associated with high rates of incorrect placement. Use of neuronavigation has been shown to reduce the rates of inaccurately positioned EVDs. We present a novel neuronavigation-based approach for EVD placement using flat panel detector computed tomography (FDCT) imaging. METHODS: Four cadaveric heads were used for neuronavigated placement of EVDs using the BrainLAB reference headband in combination with laser surface registration and the precalibrated disposable stylet. In 2 cases, conventional multislice CT imaging was performed to reference neuronavigation. In the other 2 cases, preprocedural imaging was performed with FDCT. After inserting the EVDs, all heads were examined again with the identical imaging method as used before the procedure, followed by evaluation of catheter position. RESULTS: Our data demonstrate that FDCT imaging provides adequate image quality for referencing neuronavigation and performing navigated neurosurgery. All EVDs showed an optimal position in the ipsilateral frontal horn. Use of a BrainLAB reference headband combined with laser surface registration and the precalibrated disposable stylet affords the advantage of not requiring rigid fixation in a clamp. CONCLUSIONS: Our presented method is fast, accurate, and easy to use. Furthermore, this study is the first to demonstrate that navigated neurosurgery can be performed on the basis of FDCT imaging.
EVALuna2:212791

Fluorescence-free imaging and tracking of individual secretory proteins and bioparticles - Gemeinhardt, Andre; McDonald, Matthew P.; König, Katharina; Piliarik, Marek; Schaffer, Stefanie; Aigner, Michael; Mackensen, Andreas; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2017)
We apply interferometric scattering microscopy (iSCAT) to detect single label-free proteins down to a molecular size of 60 kDa. This technique allows us to investigate real-time insitusecretion of living cells.
CRIS-Team Scopus Importer:2023-03-27

Follow-up of the GHSG HD16 trial of PET-guided treatment in early-stage favorable Hodgkin lymphoma. - Fuchs, Michael; Jacob, Anne Sophie; Kaul, Helen; Kobe, Carsten; Kuhnert, Georg; Pabst, Thomas; Greil, Richard; Bröckelmann, Paul J.; Topp, Max S.; Just, Marianne; Hertenstein, Bernd; Soekler, Martin; et al. (Leukemia, 2024)
The primary analysis of the GHSG HD16 trial indicated a significant loss of tumor control with PET-guided omission of radiotherapy (RT) in patients with early-stage favorable Hodgkin lymphoma (HL). This analysis reports long-term outcomes. Overall, 1150 patients aged 18-75 years with newly diagnosed early-stage favorable HL were randomized between standard combined-modality treatment (CMT) (2x ABVD followed by PET/CT [PET-2] and 20 Gy involved-field RT) and PET-2-guided treatment omitting RT in case of PET-2 negativity (Deauville score [DS] < 3). The study aimed at excluding inferiority of PET-2-guided treatment and assessing the prognostic impact of PET-2 in patients receiving CMT. At a median follow-up of 64 months, PET-2-negative patients had a 5-year progression-free survival (PFS) of 94.2% after CMT (n = 328) and 86.7% after ABVD alone (n = 300; HR = 2.05 [1.20-3.51]; p = 0.0072). 5-year OS was 98.3% and 98.8%, respectively (p = 0.14); 4/12 documented deaths were caused by second primary malignancies and only one by HL. Among patients assigned to CMT, 5-year PFS was better in PET-2-negative (n = 353; 94.0%) than in PET-2-positive patients (n = 340; 90.3%; p = 0.012). The difference was more pronounced when using DS4 as cut-off (DS 1-3: n = 571; 94.0% vs. DS ≥ 4: n = 122; 83.6%; p < 0.0001). Taken together, CMT should be considered standard treatment for early-stage favorable HL irrespective of the PET-2-result.
EVALuna2:540960

Full or intensity-reduced high-dose melphalan and single or double autologous stem cell transplant with or without bortezomib consolidation in patients with newly diagnosed multiple myeloma - Straka, Christian; Salwender, Hans; Knop, Stefan; Vogel, Martin; Muller, Juergen; Metzner, Bernd; Langer, Christian; Sayer, Herbert; Jung, Wolfram; Durk, Heinz A.; Bassermann, Florian; Gramatzki, Martin; et al. (European Journal of Haematology, 2021)
Objective A post hoc subgroup analysis of two phase III trials (NCT00416273, NCT00416208) was carried out to investigate the influence of 100/140 and 200 mg/m(2) melphalan as well as single/double autologous stem cell transplantation (ASCT) on progression-free survival (PFS). Additionally, the effect of bortezomib consolidation on PFS was analyzed. Methods Following induction therapy and high-dose melphalan with subsequent ASCT, patients with newly diagnosed multiple myeloma (NDMM) were randomized 1:1 to either four 35-day cycles of bortezomib consolidation (1.6 mg/m(2) IV on days 1, 8, 15, 22) or observation. Results Of the 340 patients included in this analysis, 13.5% received 1 x MEL100/140, 22.9% 2 x MEL100/140, 31.2% 1 x MEL200, and 32.4% 2 x MEL200. With higher cumulative melphalan dose, PFS improved (P = .0085). PFS curves of patients treated with 2 x MEL100/140 and 1 x MEL200 were very similar. The superior dose effect of MEL200 over MEL100/140 was non-existent in the bortezomib consolidation arm but pronounced in the observation arm (P = .0015). Similarly, double ASCT was only beneficial in patients without bortezomib consolidation (P = .0569). Conclusions Full dose melphalan and double transplantation seem advantageous only as long as patients are not receiving bortezomib consolidation afterwards.
CRIS-Team WoS Importer:2021-09-10

Functional characterization of CD34(+) cells from cryopreserved apheresis of patients with bone marrow-infiltrating malignancies - Wendland, Kerstin; Petkovic, S.; Aigner, Michael; Strobel, Joachim; Müller, Fabian (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Functional Fc gamma receptor gene polymorphisms and donor-specific antibody-triggered microcirculation inflammation - Kainz, A.; Hidalgo, L. G.; Eskandary, F.; Kozakowski, N.; Wahrmann, Markus; Haslacher, H.; Oberbauer, R.; Heilos, A.; Spriewald, B. M.; Halloran, P. F.; Boehmig, G. A.; Arnold, Martin (American Journal of Transplantation, 2018)
Fc-dependent effector mechanisms may contribute to antibody-mediated rejection (ABMR), and distinct gene polymorphisms modifying the function of Fc gamma receptors (FcγRs) may influence the capability of donor-specific antibodies (DSAs) to trigger inflammation. To evaluate the relevance of functional FcγR variants in late ABMR, 85 DSA-positive kidney allograft recipients, who were recruited upon antibody screening of 741 prevalent patients, were genotyped for polymorphisms in FcγRIIA (FCGR2A-H/R131 ; rs1801274), FcγRIIIA (FCGR3A-V/F158 ; rs396991), and FcγRIIIB (FCGR3B-neutrophil antigen 1 ([NA1]/NA2; rs35139848). Individuals with high-affinity FCGR3A-V158 alleles (V/V158 or V/F158 ) showed a higher rate (and extent) of peritubular capillaritis (ptc) in protocol biopsies than homozygous carriers of the lower-affinity allele (ptc score ≥1: 53.6% vs 25.9%; P = .018). Associations were independent of C1q-binding to DSA or capillary C4d. In parallel, there was a trend toward increased macrophage- and injury-repair response-associated transcript subsets. Kidney function over 24 months, however, was not different. In support of a functional role of FcγRIIIA polymorphism, NK92 cells expressing FCGR3A-V158 produced >2 times as much interferon gamma upon incubation with HLA antibody-coated cells as those expressing FCGR3A-F158 . FcγRIIA and FcγRIIIB polymorphisms were not associated with allograft morphology. Our data suggest that the presence of high-affinity FcγRIIIA variants may favor DSA-triggered microcirculation inflammation.
EVALuna2:34170

Functional Outcome of Intravenous Thrombolysis in Patients With Lacunar Infarcts in the WAKE-UP Trial - Barow, Ewgenia; Boutitie, Florent; Cheng, Bastian; Cho, Tae-Hee; Ebinger, Martin; Endres, Matthias; Fiebach, Jochen B.; Fiehler, Jens; Ford, Ian; Galinovic, Ivana; Nickel, Alina; Puig, Josep; et al. (JAMA Neurology, 2019)
IMPORTANCE The rationale for intravenous thrombolysis in patients with lacunar infarcts is debated, since it is hypothesized that the microvascular occlusion underlying lacunar infarcts might not be susceptible to pharmacological reperfusion treatment.
CRIS-Team WoS Importer:2019-07-26

Gene Expression in Solitary Fibrous Tumors (SFTs) Correlates with Anatomic Localization and NAB2-STAT6 Gene Fusion Variants - Bieg, Matthias; Moskalev, Evgeny; Will, Rainer; Hebele, Simone; Schwarzbach, Matthias; Schmeck, Sanja; Hohenberger, Peter; Jakob, Jens; Kasper, Bernd; Gaiser, Timo; Ströbel, Philip; Wardelmann, Eva; et al. (American Journal of Pathology, 2021)
Solitary fibrous tumors (SFTs) harbor recurrent NAB2-STAT6 gene fusions, promoting constitutional up-regulation of oncogenic early growth response 1 (EGR1)-dependent gene expression. SFTs with the most common canonical NAB2 exon 4–STAT6 exon 2 fusion variant are often located in the thorax (pleuropulmonary) and are less cellular with abundant collagen. In contrast, SFTs with NAB2 exon 6–STAT6 exon 16/17 fusion variants typically display a cellular round to ovoid cell morphology and are often located in the deep soft tissue of the retroperitoneum and intra-abdominal pelvic region or in the meninges. Here, we employed next-generation sequencing–based gene expression profiling to identify significant differences in gene expression associated with anatomic localization and NAB2-STAT6 gene fusion variants. SFTs with the NAB2 exon 4–STAT6 exon 2 fusion variant showed a transcriptional signature enriched for genes involved in DNA binding, gene transcription, and nuclear localization, whereas SFTs with the NAB2 exon 6–STAT6 exon 16/17 fusion variants were enriched for genes involved in tyrosine kinase signaling, cell proliferation, and cytoplasmic localization. Specific transcription factor binding motifs were enriched among differentially expressed genes in SFTs with different fusion variants, implicating co–transcription factors in the modification of chimeric NGFI-A binding protein 2 (NAB2)-STAT6–dependent deregulation of EGR1-dependent gene expression. In summary, this study establishes a potential molecular biologic basis for clinicopathologic differences in SFTs with distinct NAB2-STAT6 gene fusion variants.
CRIS-Team Scopus Importer:2021-04-02

Generation of an oncolytic herpes simplex virus 1 expressing human MelanA - Boscheinen, Jan; Thomann, Sabrina; Knipe, David M.; Deluca, Neal; Schuler-Thurner, Beatrice; Gross, Stefanie; Dörrie, Jan; Schaft, Niels; Bach, Christian; Rohrhofer, Anette; Werner-Klein, Melanie; Schmidt, Barbara; et al. (Frontiers in Immunology, 2019)
Robust anti-tumor immunity requires innate as well as adaptive immune responses. We have shown that plasmacytoid dendritic cells develop killer cell-like activity in melanoma cell cocultures after exposure to the infectious but replication-deficient herpes simplex virus 1 (HSV-1) d106S. To combine this innate effect with an enhanced adaptive immune response, the gene encoding human MelanA/MART-1 was inserted into HSV-1 d106S via homologous recombination to increase direct expression of this tumor antigen. Infection of Vero cells using this recombinant virus confirmed MelanA expression by Western blotting, flow cytometry, and immunofluorescence. HSV-1 d106S-MelanA induced expression of the transgene in fibroblast and melanoma cell lines not naturally expressing MelanA. Infection of a melanoma cell line with CRISPR-Cas9-mediated knockout of MelanA confirmed de novo expression of the transgene in the viral context. Dependent on MelanA expression, infected fibroblast and melanoma cell lines induced degranulation of HLA-matched MelanA-specific CD8+ T cells, followed by killing of infected cells. To study infection of immune cells, we exposed peripheral blood mononuclear cells and in vitro-differentiated macrophages to the parental HSV-1 d106S, resulting in expression of the transgene GFP in CD11c+ cells and macrophages. These data provide evidence that the application of MelanA-encoding HSV-1 d106S could enhance adaptive immune responses and re-direct MelanA-specific CD8+ T cells to tumor lesions, which have escaped adaptive immune responses via downregulation of their tumor antigen. Hence, HSV-1 d106S-MelanA harbors the potential to induce innate immune responses in conjunction with adaptive antitumor responses by CD8+ T cells, which should be evaluated in further studies.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Cytotoxic T cell response; Herpes virus; Malignant melanoma; Oncolytic viruses; Vaccine

Genetic Breast Cancer Susceptibility Variants and Prognosis in the Prospectively Randomized SUCCESS A Study - Hein, Alexander; Rack, B.; Li, L.; Ekici, Arif Bülent; Reis, André; Lux, Michael P.; Cunningham, J. M.; Rübner, Matthias; Fridley, B. L.; Schneeweiss, A.; Tesch, H.; Lichtenegger, W.; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Large-scale genotyping studies have identified over 70 single nucleotide polymorphisms (SNPs) associated with breast cancer (BC) risk. However, knowledge regarding genetic risk factors associated with the prognosis is limited. The aim of this study was therefore to investigate the prognostic effect of nine known breast cancer risk SNPs. BC patients (n = 1687) randomly sampled in an adjuvant, randomized phase III trial (SUCCESS A study) were genotyped for nine BC risk SNPs: rs17468277 (CASP8) , rs2981582 (FGFR2) , rs13281615(8q24), rs3817198 (LSP1) , rs889312 (MAP3K1) , rs3803662 (TOX3) , rs13387042(2q35), rs4973768 (SLC4A7) , rs6504950 (COX11) . Cox proportional hazards models were used to test the SNPs' association with overall survival (OS) and progression-free survival (PFS). Additional analyses were carried out for molecular subgroups. rs3817198 in LSP1 (lymphocyte-specific protein 1) was the only SNP that significantly influenced OS (p = 0.01) and PFS (p < 0.01) in the likelihood ratio test comparing the genetic survival model with the clinical survival model. In the molecular subgroups, triple-negative patients with two minor alleles in rs3817198 had a much better prognosis relative to OS (adjusted HR 0.03; 95% CI 0.002 - 0.279) and PFS (HR 0.09; 95% CI 0.02 - 0.36) than patients with the common alleles. The same effect on PFS was shown for patients with luminal A tumors (HR 0.19; 95% CI 0.05 - 0.84), whereas patients with luminal B tumors had a poorer PFS with two minor alleles (HR 2.13; 95% CI 1.02 - 4.40). The variant in rs3817198 has a prognostic effect particularly in the subgroup of patients with triple-negative BC, suggesting a possible link with immunomodulation and BC.
EVALuna2:9355

Genital ulcers as diagnostic clue for acute myeloid leukaemia - Schröder, Sina; Krause, Stefan; Erfurt-Berge, Cornelia (International Wound Journal, 2018)
Acute myeloid leukaemia is a myeloid neoplasm with an extremely varying clinical appearance. Skin lesions are common for specific subtypes of acute myeloid leukaemia but are often misinterpreted. Here, we present a case of acute myeloid leukaemia in a young woman exhibiting genital ulcerations and gingival erosions.
EVALuna2:34278

„Gesundheit für alle im Stadtteil“ – ein kommunaler Ansatz zur Gesundheitsförderung in sozial benachteiligten Stadtteilen Nürnbergs. - Barth, Janina; Mengel, Michael; Seebaß, Katharina; Retzlaff, KN; Herbert-Maul, Annika; Barthel-Kraus, E; Wiemer-Urtube, Silvina (Praxishandbuch Qualitätsentwicklung und Evaluation in der Gesundheitsförderung, 2019)
Keywords: Chancengleichheit

GMP-production of purified human B lymphocytes for the adoptive transfer in patients after allogeneic hematopoietic stem cell transplantation - Tittlbach, Hannes; Schneider, Andrea; Strobel, Joachim; Zimmermann, Robert; Maas, Stefanie; Gebhardt, Bernd; Rauser, Georg; Mach, Michael; Mackensen, Andreas; Winkler, Thomas; Winkler, Jürgen (Journal of Translational Medicine, 2017)
We have recently shown that memory B cells from murine CMV immune donor animals adoptively transferred into immunodeficient mice were highly effective in protecting from a viral infection indicating a therapeutic potential of virus specific memory B cells. These preclinical data provided evidence that a cell-based strategy supporting the humoral immune response might be effective in a clinical setting of immunodeficiency after allogeneic hematopoietic stem cell transplantation. As adoptive transfer of B cells has not been used before in a clinical setting it was necessary to establish a technology for the generation of good manufacturing practice (GMP)-grade B cell products.Starting from the leukapheresis product of healthy blood donors, B cells were purified by two different separation strategies using GMP-grade microbeads and the CliniMACS system. A one-step protocol was used for positive enrichment of B lymphocytes with anti-CD19 microbeads. In a two-step enrichment protocol, first T lymphocytes were depleted by anti-CD3 microbeads and the remaining fraction was positively selected by anti-CD19 microbeads.The purity and recovery after enrichment of B lymphocytes from the leukapheresis material in both separations strategies was not statistically different. However, contamination of the B-cell product with T cells was significantly lower after the two-step protocol (0.16%, range 0.01-0.43% after two-step separation and 0.55%, range 0.28-0.85% after one-step separation, p < 0.05). Therefore, a combined CD3 depletion and CD19 enrichment was used for the production of GMP-conform B-cell products from the leukapheresis material of 17 healthy stem cell donors. The absolute B-cell numbers obtained in the final product was 4.70 ± 3.64 × 108 with a purity of 95.98 ± 3.31% B lymphocytes and a recovery of 18.9 ± 10.6%. Importantly, the contamination with CD3+ T cells was extremely low in the final B- cell products (0.10 ± 0.20%). Purified B cells exhibited normal antibody production after in vitro stimulation and showed excellent viability after cryopreservation.A GMP-grade B-cell product can be obtained with high purity and very low T-cell contamination using the two-step enrichment protocol based on CliniMACS® technology.
EVALuna2:25773

Grb2 regulates B-cell maturation, B-cell memory responses and inhibits B-cell Ca2+ signalling - Ackermann, Jochen; Radtke, Daniel; Maurberger, Anna; Winkler, Thomas; Nitschke, Lars (EMBO Journal, 2011)
Grb2 is a ubiquitously expressed adaptor protein, which activates Ras and MAP kinases in growth factor receptor signalling, while in B-cell receptor (BCR) signalling this role is controversial. In B cell lines it was shown that Grb2 can inhibit BCR-induced Ca2+ signalling. Nonetheless, the physiological role of Grb2 in primary B cells is still unknown. We generated a B-cell-specific Grb2-deficient mouse line, which had a severe reduction of mature follicular B cells in the periphery due to a differentiation block and decreased B-cell survival. Moreover, we found several changes in important signalling pathways: enhanced BCR-induced Ca2+ signalling, alterations in mitogen-activated protein kinase activation patterns and strongly impaired Akt activation, the latter pointing towards a defect in PI3K signalling. Interestingly, B-cell-specific Grb2-deficient mice showed impaired IgG and B-cell memory responses, and impaired germinal centre formation. Thus, Grb2-dependent signalling pathways are crucial for lymphocyte differentiation processes, as well as for control of secondary humoral immune responses. The EMBO Journal (2011) 30, 1621-1633. doi:10.1038/emboj.2011.74; Published online 22 March 2011 Subject Categories: signal transduction; immunology
Keywords: adaptor proteins; B cells; B-cell development; calcium signalling; humoral immune response

Haploidentical transplant with post-transplant cyclophosphamide for T-cell acute lymphoblastic leukemia: a report from the EBMT acute leukemia working party - Bazarbachi, Ali; Labopin, Myriam; Angelucci, Emanuele; Gülbas, Zafer; Ozdogu, Hakan; Arat, Mutlu; De Rosa, Luca; Pastano, Rocco; Pioltelli, Pietro; Montserrat, Rovira; Martino, Massimo; Ciceri, Fabio; et al. (Biology of Blood and Marrow Transplantation, 2020)
Allogeneic hematopoietic cell transplantation (HCT) is recommended in high-risk patients with T cell acute lymphoblastic leukemia (T-ALL). For patients with no HLA identical donor, haploidentical transplantation (haplo-HCT) is becoming the leading source of stem cell donation. However, data is scarce on predictive factors for outcome in that setting. We identified 122 adults (20% female; median age 31 years; range 18-68) with T-ALL who received a haplo-HCT with post-transplant cyclophosphamide (ptCy) between 2010 and 2017. Median follow-up of living patients was 23 months. The 2-year relapse incidence and non-relapse mortality were 45% and 21%, respectively. The 2-year leukemia-free survival (LFS), overall survival (OS) and GVHD-free, relapse-free survival (GRFS) were 34%, 42% and 27%, respectively. The 2-year LFS and OS were highly influenced by disease status at transplant, being 49% and 55% respectively for first complete remission (CR1), 34% and 50% respectively for CR2, 8% and 12% respectively for patients with active disease. On multivariate analysis, only disease status affected LFS and OS. Transplantation in CR2 negatively affected LFS, whereas active disease at haplo-HCT negatively affected LFS and OS. In conclusion, haplo-HCT with ptCy produced encouraging results in this challenging disease, particularly when performed in CR. Despite the limitation of the small sample size, results were not affected by the type of conditioning, questioning the need for total body irradiation based-myeloablative conditioning (TBI-MAC) in that setting.
EVALuna2:209543

Haploidentical transplant with post-transplant cyclophosphamide for T-cell acute lymphoblastic leukemia: Outcome strongly correlates with disease status; a report from the EBMT acute leukemia working party - Bazarbachi, Ali; Labopin, Myriam; Angelucci, Emanuele; Gulbas, Zafer; Ozdogu, Hakan; Arat, Mutlu; De Rosa, Luca; Tarella, Corrado; Pioltelli, Pietro; Montserrat, Rovira; Martino, Massimo; Ciceri, Fabio; et al. (BONE MARROW TRANSPLANTATION, 2019)
CRIS-Team WoS Importer:2019-10-11

Head and neck melanoma: outcome and predictors in a population-based cohort study - Spoerl, Steffen; Spanier, Gerrit; Reiter, Elena; Gerken, Michael; Haferkamp, Sebastian; Grosse, Jirka; Drexler, Konstantin; Ettl, Tobias; Klinkhammer-Schalke, Monika; Fischer, Rene; Spörl, Silvia; Reichert, Torsten E.; et al. (Head & Face Medicine, 2021)
Background To evaluate predictive clinico-pathological characteristics on outcome in head and neck melanoma (HNM) in a population-based study with particular emphasis on the prognostic effect of sentinel lymph node biopsy (SLNB), Charlson comorbidity index (CCI) and distinct tumor localisations. Methods Here we primarily describe a retrospective multicenter population-based cohort study with 402 patients having undergone resection with curative intent of HNM between 2010 and 2017. SLNB was used in the diagnosis of 79 HNM patients. Outcome was analyzed, focusing on SLNB, CCI as well as tumor localisation. Overall survival (OAS) und recurrence free survival (RFS) was examined by uni- and multivariate analysis. Results Histopathologically verified lymph node metastasis according to SLNB was associated with impaired RFS in HNM patients (p = 0.004). Especially in higher tumor stages, the sole implementation of SLNB improved survival significantly in the present cohort (p = 0.042). With most of the HNM being located in the face, melanoma of the scalp and neck could be linked to deteriorated patient's outcome in uni- as well as multivariate analysis (p = 0.021, p = 0.004). Conclusions SLNB is a useful tool in predicting development of distant metastasis after HNM resection with curative intent. Especially in higher tumor stages, performing a SLNB ameliorated survival of HNM patients. Additionally, CCI as well as a distinct tumor localisations in HNM were identified as important risk factors in our population-based cohort study.
CRIS-Team WoS Importer:2021-11-05

Health-related quality of life (HRQoL) in CML-patients at diagnosis compared to general population - Lorch, M.; Pfirrmann, M.; Fabisch, C.; Oberle, L.; Kohn, D.; Kohlbrenner, K.; Bruemmendorf, T. H.; Burchert, A.; Krause, Stefan; Le Coutre, P.; Haenel, M.; Franke, G-N; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Helicobacter pylori avoids the critical activation of NLRP3 inflammasome-mediated production of oncogenic mature il-1β in human immune cells - Suneesh Kumar, Pachathundikandi; Blaser, Nicole; Bruns, Heiko; Backert, Steffen (Cancers, 2020)
Helicobacter pylori persistently colonizes the human stomach, and is associated with inflammation-induced gastric cancer. Bacterial crosstalk with the host immune system produces various inflammatory mediators and subsequent reactions in the host, but not bacterial clearance. Interleukin-1β (IL-1β) is implicated in gastric cancer development and certain gene polymorphisms play a role in this scenario. Mature IL-1β production depends on inflammasome activation, and the NLRP3 inflammasome is a major driver in H. pylori-infected mice, while recent studies demonstrated the down-regulation of NLRP3 expression in human immune cells, indicating a differential NLRP3 regulation in human vs. mice. In addition to the formation of mature IL-1β or IL-18, inflammasome activation induces pyroptotic death in cells. We demonstrate that H. pylori infection indeed upregulated the expression of pro-IL-1β in human immune cells, but secreted only very low amounts of mature IL-1β. However, application of exogenous control activators such as Nigericin or ATP to infected cells readily induced NLRP3 inflammasome formation and secretion of high amounts of mature IL-1β. This suggests that chronic H. pylori infection in humans manipulates inflammasome activation and pyroptosis for bacterial persistence. This inflammasome deregulation during H. pylori infection, however, is prone to external stimulation by microbial, environmental or host molecules of inflammasome activators for the production of high amounts of mature IL-1β and signaling-mediated gastric tumorigenesis in humans.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Helicobacter pylori; Inflammasome; Interleukin-1β; NLRP3

Hematopoietic cell transplantation in patients with intermediate and high-risk AML: results from the randomized Study Alliance Leukemia (SAL) AML 2003 trial - Schetelig, J.; Schaich, M.; Schaefer-Eckart, K.; Haenel, M.; Aulitzky, W. E.; Einsele, H.; Schmitz, N.; Rösler, Wolf; Stelljes, M.; Baldus, C. D.; Ho, A. D.; Neubauer, A.; et al. (Leukemia, 2015)
The optimal timing of allogeneic hematopoietic stem cell transplantation (HCT) in acute myeloid leukemia (AML) is controversial. We report on 1179 patients with a median age of 48 years who were randomized upfront. In the control arm, sibling HCT was scheduled in the first complete remission for intermediate-risk or high-risk AML and matched unrelated HCT in complex karyotype AML. In the experimental arm, matched unrelated HCT in first remission was offered also to patients with an FLT3-ITD (FMS-like tyrosine kinase 3-internal tandem duplication) allelic ratio >0.8, poor day +15 marrow blast clearance and adverse karyotypes. Further, allogeneic HCT was recommended in high-risk AML to be performed in aplasia after induction chemotherapy. In the intent-to-treat (ITT) analysis, superiority of the experimental transplant strategy could not be shown with respect to overall survival (OS) or event-free survival. As-treated analyses suggest a profound effect of allogeneic HCT on OS (HR 0.73; P=0.002) and event-free survival (HR 0.67; P<0.001). In high-risk patients, OS was significantly improved after allogeneic HCT in aplasia (HR 0.64; P=0.046) and after HCT in remission (HR 0.74; P=0.03). Although superiority of one study arm could not be demonstrated in the ITT analysis, secondary analyses suggest that early allogeneic HCT is a promising strategy for patients with high-risk AML.
EVALuna2:25686

Hematopoietic Differentiation Is Required for Initiation of Acute Myeloid Leukemia - Ye, Min; Zhang, Hong; Yang, Henry; Koche, Richard; Staber, Philipp B.; Cusan, Monica; Levantini, Elena; Welner, Robert S.; Bach, Christian; Zhang, Junyan; Krivtsov, Andrei V.; Armstrong, Scott A.; et al. (Cell Stem Cell, 2015)
Mutations in acute myeloid leukemia (AML)-associated oncogenes often arise in hematopoietic stem cells (HSCs) and promote acquisition of leukemia stem cell (LSC) phenotypes. However, as LSCs often share features of lineage-restricted progenitors, the relative contribution of differentiation status to LSC transformation is unclear. Using murine MLL-AF9 and MOZ-TIF2 AML models, we show that myeloid differentiation to granulocyte macrophage progenitors (GMPs) is critical for LSC generation. Disrupting GMP formation by deleting the lineage-restricted transcription factor C/EBPa blocked normal granulocyte formation and prevented initiation of AML. However, restoring myeloid differentiation in C/EBPa mutants with inflammatory cytokines reestablished AML transformation capacity. Genomic analyses of GMPs, including gene expression and H3K79me2 profiling in conjunction with ATAC-seq, revealed a permissive genomic environment for activation of a minimal transcription program shared by GMPs and LSCs. Together, these findings show that myeloid differentiation is a prerequisite for LSC formation and AML development, providing insights for therapeutic development.
EVALuna2:25717

High-dose methotrexate-based immuno-chemotherapy for elderly primary CNS lymphoma patients (PRIMAIN study) - Fritsch, K.; Kasenda, B.; Schorb, E.; Hau, P.; Bloehdorn, J.; Moehle, R.; Loew, S.; Binder, M.; Atta, J.; Keller, U.; Wolf, H-H; Krause, Stefan; et al. (Leukemia, 2016)
To investigate immuno-chemotherapy for elderly immuno-competent patients (?65 years) with newly diagnosed primary central nervous system lymphoma, we conducted a multicentre single-arm trial. One cycle consisted of rituximab (375 mg/m(2), days 1, 15, 29), high-dose methotrexate (3 g/m(2) days 2, 16, 30), procarbazine (60 mg/m(2) days 2-11) and lomustine (110 mg/m(2), day 2)-R-MPL protocol. Owing to infectious complications, we omitted lomustine during the study and consecutive patients were treated with the R-MP protocol. Three cycles were scheduled and repeated on day 43. Subsequently, patients commenced 4 weekly maintenance treatment with procarbazine (100 mg for 5 days). Primary end point was complete remission (CR) after 3 cycles. We included 107 patients (69 treated with R-MPL and 38 with R-MP). In all, 38/107 patients achieved CR (35.5%) and 15 (14.0%) achieved partial remission. R-MP was associated with a lower CR rate (31.6%) compared with R-MPL (37.7%), but respective 2-year progression-free survival (All 37.3%; R-MP 34.9%; R-MPL 38.8%) and overall survival (All 47.0%; R-MP 47.7%; R-MPL 46.0%) rates were similar. R-MP was associated with less ?grade 3 toxicities compared with R-MPL (71.1% vs 87.0%). R-MP is more feasible while still associated with similar efficacy compared with R-MPL and warrants further improvement in future studies.Leukemia advance online publication, 9 December 2016; doi:10.1038/leu.2016.334.
EVALuna2:25755

High fat diet increases melanoma cell growth in the bone marrow by inducing osteopontin and interleukin 6 - Chen, Guangliang; Luo, Yubin; Eriksson, Daniel; Meng, Xianyi; Qian, Cheng; Bäuerle, Tobias; Chen, Xiao-Xiang; Schett, Georg; Bozec, Aline (Oncotarget, 2016)
The impact of metabolic stress induced by obesity on the bone marrow melanoma niche is largely unknown. Here we employed diet induced obese mice model, where mice received high-fat (HFD) or normal diet (ND) for 6 weeks before challenge with B16F10 melanoma cells. Tumor size, bone loss and osteoclasts numbers were assessed histologically in the tibial bones. For defining the molecular pathway, osteopontin knock-out mice, interleukin 6 neutralizing antibody or Janus kinase 2 inhibition were carried out in the same model. Mechanistic studies such as adipocyte-melanoma co-cultures for defining adipocyte induced changes of tumor cell proliferation and expression profiles were also performed. As results, HFD enhanced melanoma burden in bone by increasing tumor area and osteoclast numbers. This process was associated with higher numbers of bone marrow adipocytes expressing IL-6 in direct vicinity to tumor cells. Inhibition of IL-6 or of downstream JAK2 blocked HFD-induced tumor progression. Furthermore, the phenotypic changes of melanoma cells triggered macrophage and osteoclast accumulation accompanied by increased osteopontin expression. Osteopontin triggered osteoclastogenesis and also exerted a positive feedback loop to tumor cells, which was abrogated in its absence. Metabolic stress by HFD promotes melanoma growth in the bone marrow by an increase in bone marrow adipocytes and IL-6-JAK2-osteopontin mediated activation of tumor cells and osteoclast differentiation.
EVALuna2:13267

High PD-1 levels in T cells are associated with an early relapse in lymphoma patients upon autologous stem cell transplantation - Richter, Steffi; Jacobs, Benedikt; Böttcher, Martin; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

High proliferation rate and TNM stage but not histomorphological subtype are independent prognostic markers for overall survival in papillary renal cell carcinoma - Polifka, Iris; Agaimy, Abbas; Herrmann, Edwin; Spath, Verena; Trojan, Lutz; Stoeckle, Michael; Becker, Frank; Stroebel, Philipp; Muelfing, Christian; Schrader, Andres J.; Barth, Peter; Staehler, Michael; et al. (Human Pathology, 2019)
Papillary renal cell carcinoma (PRCC) is currently divided in 2 subtypes. We reviewed a large cohort of PRCC and correlated subtype, morphological features and diagnostic marker expression with overall survival (OS) to uncover differences between the 2 subtypes. Three hundred seventy-six renal tumors initially diagnosed as PRCC with clinical and survival data were collected from the participating centers. Two hundred forty-six tumors were classified as PRCC1 (65.4%) and 130 as PRCC2 (34.6%) and graded according to the 2016 World Health Organization/Intemational Society of Urological Pathology grading system. Morphological features (abundant cytoplasm, necrosis, fibrous stroma, foamy macrophages and psammoma bodies) were noted. Immunohistochemical stains (MIB1, p53, Racemase, EMA, CK7, CK20, E-Cadherin) were performed using tissue microarrays. chi(2)-Tests, log-rank tests and uni- and multivariate Cox regression analysis were performed. Both subtypes displayed different morphological features and immunohistochemical profiles: abundant cytoplasm was more frequent in PRCC2, while foamy macrophages were more common in PRCC1. Abundant cytoplasm and presence of psammoma bodies were associated with poorer OS. PRCC1 showed more frequent CK7 expression, PRCC2 more frequent E-Cadherin, p53 and higher MIB1 expression (>15%). Expression of Racemase and CK7 was associated with better OS, while high MIB1 (>15%) was associated with poorer OS. In multivariate analysis, the only independent predictors of OS were proliferation (MIB1), tumor stage, metastasis and age at surgery. Subtype was not an independent prognostic factor. Therefore, PRCC subtype on its own is not suitable for estimating survival. More data focusing on PRCC tumor biology is needed to define prognostic subgroups, especially in PRCC2. (C) 2018 Elsevier Inc. All rights reserved.
CRIS-Team WoS Importer:2019-03-06

High-risk additional chromosomal abnormalities at low blast counts herald death by CML - Hehlmann, Ruediger; Voskanyan, Astghik; Lauseker, Michael; Pfirrmann, Markus; Kalmanti, Lida; Rinaldetti, Sebastien; Kohlbrenner, Katharina; Haferlach, Claudia; Schlegelberger, Brigitte; Fabarius, Alice; Seifarth, Wolfgang; Spiess, Birgit; et al. (Leukemia, 2020)
Blast crisis is one of the remaining challenges in chronic myeloid leukemia (CML). Whether additional chromosomal abnormalities (ACAs) enable an earlier recognition of imminent blastic proliferation and a timelier change of treatment is unknown. One thousand five hundred and ten imatinib-treated patients with Philadelphia-chromosome-positive (Ph+) CML randomized in CML-study IV were analyzed for ACA/Ph+ and blast increase. By impact on survival, ACAs were grouped into high risk (+8, +Ph, i(17q), +17, +19, +21, 3q26.2, 11q23, -7/7q abnormalities; complex) and low risk (all other). The presence of high- and low-risk ACAs was linked to six cohorts with different blast levels (1%, 5%, 10%, 15%, 20%, and 30%) in a Cox model. One hundred and twenty-three patients displayed ACA/Ph+ (8.1%), 91 were high risk. At low blast levels (1-15%), high-risk ACA showed an increased hazard to die compared to no ACA (ratios: 3.65 in blood; 6.12 in marrow) in contrast to low-risk ACA. No effect was observed at blast levels of 20-30%. Sixty-three patients with high-risk ACA (69%) died (n = 37) or were alive after progression or progression-related transplantation (n = 26). High-risk ACA at low blast counts identify end-phase CML earlier than current diagnostic systems. Mortality was lower with earlier treatment. Cytogenetic monitoring is indicated when signs of progression surface or response to therapy is unsatisfactory.
EVALuna2:216177

High-Risk Additional Chromosomal Abnormalities in CML Herald Death By Blast Crisis Already at Low Blast Levels - Hehlmann, Rudiger; Voskanyan, Astghik; Lauseker, Michael; Pfirrmann, Markus; Kalmanti, Lida; Rinaldetti, Sebastien; Kohlbrenner, Katharina; Haferlach, Claudia; Schlegelberger, Brigitte; Fabarius, Alice; Krause, Stefan; Kolb, Hans-Jochem; et al. (BLOOD, 2019)
CRIS-Team WoS Importer:2021-10-18

HIV Activates the Tyrosine Kinase Hck to Secrete ADAM Protease-Containing Extracellular Vesicles - Lee, J. H.; Zhao, Z.; Ostalecki, Christian; Kesti, T.; Bruns, Heiko; Simon, B.; Harrer, Thomas; Saksela, K.; Baur, A. S. (EBioMedicine, 2018)
EVALuna2:13527

HLA-DO: a possible switch between GvHD and GvL effect - Zeun, J.; Neubeck, S.; Lang, Vanessa; Flamann, Cindy; Nagel, L.; Kunert, Timo; Vogler, T.; Brey, Stefanie; Hildner, Kai; Bäuerle, Tobias; Büttner-Herold, Maike; Winkler, Thomas; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

HLA-E expression and its clinical relevance in human renal cell carcinoma - Seliger, Barbara; Jasinski-Bergner, Simon; Quandt, Dagmar; Stoehr, Christine; Bukur, Juergen; Wach, Sven; Legal, Wolfgang; Taubert, Helge; Wullich, Bernd; Hartmann, Arndt (Oncotarget, 2016)
The non-classical human leukocyte antigen E (HLA-E) expression is frequently overexpressed in tumor diseases, transplants and virus-infected cells and represents an immunomodulatory molecule by binding to the receptors CD94/NKG2A, -B and -C on NK and T cells. Due to its immune suppressive features HLA-E expression might represent an important mechanism of tumors to escape immune surveillance. While an aberrant expression of the non-classical HLA-G antigen in human renal cell carcinoma (RCC) has been demonstrated to be associated with a worse outcome of patients and reduced sensitivity to immune effector cell-mediated cytotoxicity, the expression and function of HLA-E has not yet been analyzed in this tumor entity. Higher levels of HLA-E transcripts were detected in all RCC cell lines and tumor lesions, which were tested in comparison to normal kidney epithelium. Immunohistochemical staining of a tissue microarray (TMA) using the HLA-E-specific monoclonal antibody TFL-033 recognizing the cytoplasmic HLA-E ?-chain as monomer revealed a heterogeneous HLA-E expression in RCC lesions with the highest frequency in chromophobe RCC when compared to other RCC subtypes. HLA-E expression did not correlate with the frequency of CD3+, CD4+, CD8+ and FoxP3+ immune cell infiltrations, but showed an inverse correlation with infiltrating CD56+ cells. In contrast to HLA-G, HLA-E expression in RCCs was not statistically significant associated with a decreased disease specific survival. These data suggest that HLA-E overexpression frequently occurs in RCC and correlates with reduced immunogenicity.
EVALuna2:6816

HLA HAPLOTYPES IN 250 FAMILIES: A CORE NGS TESTING MODEL FOR THE 17TH INTERNATIONAL HLA AND IMMUNOGENETICS WORKSHOP - Askar, Medhat; Madbouly, Abeer; Zhrebker, Leah; Willis, Amanda; Kennedy, Shawna; Padros, Karin; Rodriguez, Maria Beatriz; Bach, Christian; Spriewald, Bernd M.; Ameen, Reem; Al Shemmari, Salem; Terassi, Katerina; et al. (HLA, 2019)
CRIS-Team WoS Importer:2019-04-30

HLA HHaplotypes In 250 Families: The Baylor Laboratory Results And A Aerspective On A Core NGS Testing Model For The 17th International HLA And Immunogenetics Workshop - Askar, Medhat; Madbouly, Abeer; Zhrebker, Leah; Willis, Amanda; Kennedy, Shawna; Padros, Karin; Rodriguez, Maria Beatriz; Bach, Christian; Spriewald, Bernd; Ameen, Reem; Shemmari, Salem Al; Tarassi, Katerina; et al. (Human Immunology, 2019)
Since their inception, the International HLA & Immunogenetics Workshops (IHIW) served as a collaborative platform for exchange of specimens, reference materials, experiences and best practices. In this report we present a subset of the results of human leukocyte antigen (HLA) haplotypes in families tested by next generation sequencing (NGS) under the 17th IHIW. We characterized 961 haplotypes in 921 subjects belonging to 250 families from 8 countries (Argentina, Austria, Egypt, Jamaica, Germany, Greece, Kuwait, and Switzerland). These samples were tested in a single core laboratory in a high throughput fashion using 6 different reagents/software platforms. Families tested included patients evaluated clinically as transplant recipients (kidney and hematopoietic cell transplant) and their respective family members. We identified 486 HLA alleles at the following loci HLA-A, -B, -C, -DRB1, -DRB3, -DRB4, -DRB5, -DQA1, -DQB1, -DPA1, -DPB1 (77, 115, 68, 69, 10, 6, 4, 44, 31, 20 and 42 alleles, respectively). We also identified nine novel alleles with polymorphisms in coding regions. This approach of testing samples from multiple laboratories across the world in different stages of technology implementation in a single core laboratory may be useful for future international workshops. Although data presented may not be reflective of allele and haplotype frequencies in the countries to which the families belong, they represent an extensive collection of 3rd and 4th field resolution level 11-locus haplotype associations of 486 alleles identified in families from 8 countries.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Family; HLA haplotype; Linkage disequilibrium

Hobit- and Blimp-1-driven CD4(+) tissue-resident memory T cells control chronic intestinal inflammation - Zundler, Sebastian; Becker, Emily; Spocinska, Marta; Slawik, Monique; Parga-Vidal, Loreto; Stark, Regina; Wiendl, Maximilian; Atreya, Raja; Rath, Timo; Leppkes, Moritz; Hildner, Kai; Lopez Posadas, Rocío; et al. (Nature Immunology, 2019)
Although tissue-resident memory T cells (T-RM cells) have been shown to regulate host protection in infectious disorders, their function in inflammatory bowel disease (IBD) remains to be investigated. Here we characterized T-RM cells in human IBD and in experimental models of intestinal inflammation. Pro-inflammatory T-RM cells accumulated in the mucosa of patients with IBD, and the presence of CD4(+)CD69(+)CD103(+) T-RM cells was predictive of the development of flares. In vivo, functional impairment of T-RM cells in mice with double knockout of the T-RM-cell-associated transcription factors Hobit and Blimp-1 attenuated disease in several models of colitis, due to impaired cross-talk between the adaptive and innate immune system. Finally, depletion of T-RM cells led to a suppression of colitis activity. Together, our data demonstrate a central role for T-RM cells in the pathogenesis of chronic intestinal inflammation and suggest that these cells could be targets for future therapeutic approaches in IBD.
CRIS-Team WoS Importer:2019-03-06

Hobit- and Blimp1-driven tissue resident memory T cells critically control chronic intestinal inflammation - Zundler, Sebastian; Becker, E.; Spocinska, M.; Parga-Vidal, L.; Stark, R.; Atreya, Raja; Rath, T.; Leppkes, Moritz; Neufert, Clemens; Atreya, I.; Van Gisbergen, K.; Neurath, Markus (2018)
EVALuna2:34078

Homozygous G/G variant of SNP309 in the human MDM2 gene is associated with earlier tumor onset in Caucasian female renal cell carcinoma patients - Stoehr, Christine; Stoehr, R.; Wenners, A.; Hartmann, Arndt; Bertz, Simone; Spath, V.; Walter, B.; Junker, K.; Moch, H.; Hinze, R.; Denzinger, S.; Bond, E. E.; et al. (Oncogenesis, 2016)
Human mouse double minute 2 (Mdm2) plays an essential role in the regulation of the tumor suppressor p53. The G/G variant of SNP309 was shown to increase Mdm2 mRNA/protein expression and to be associated with an increased risk and earlier onset of different cancers in Asian populations. However, the frequency and impact of these G/G variants have not been studied in Caucasian renal cell carcinoma (RCC) patients. Therefore, we analyzed an unselected German cohort of 197 consecutive RCC patients and detected the G/G variant in 18 (9.1%) patients, the G/T variant in 116 (58.9%) patients and the T/T variant in 63 (32.0%) patients. Studying the association between age at tumor onset and SNP309 genotypes, no correlation was detected in the entire RCC cohort or among the male RCC patients. However, the female G/G patients (median age 59.5 years) were diagnosed 13.5 years earlier than the T/T females (median age 73 years). When separating all females into two groups at their median age (68 years), 7 and 1 patients with the G/G variant and 9 and 13 patients with the T/T variant were noted in these age groups (P=0.024). To study the age dependency of tumor onset further, a second, age-selected cohort of 205 RCC patients was investigated, which comprised especially young and old patients. Interestingly, the G/G type occurred more often at lower tumor stages and tumor grades compared with higher stages (P=0.039 and 0.004, respectively). In females, the percentage of the G/G variant was only slightly higher in the younger age group, whereas in males, the percentage of the G/G variant was remarkably higher in the younger age group (19.4% vs 8.0%). In summary, female Caucasian RCC patients with the MDM2 SNP309 G/G genotype showed significantly earlier tumor onset than patients with the wild-type T/T genotype.
EVALuna2:6760

How does phagocytosis affect macrophages? - Biedermann, Alexander; Flamann, Cindy; Mougiakakos, Dimitrios; Bitterer, Katrin; Leffler, M.; Kellner, C.; Peipp, M.; Büttner-Herold, Maike; Mackensen, Andreas; Bruns, Heiko (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Human CD22-transgenic, primary murine lymphoma challenges immunotherapies in organ-specific tumor microenvironments - Gsottberger, Franziska; Brandl, Carolin; Wendland, Kerstin; Petkovic, Srdjan; Emmerich, Charlotte; Erber, Ramona; Geppert, Carol-Immanuel; Hartmann, Arndt; Mackensen, Andreas; Nitschke, Lars; Müller, Fabian (International Journal of Molecular Sciences, 2021)
Targeted immunotherapies have greatly changed treatment of patients with B cell malignancies. To further enhance immunotherapies, research increasingly focuses on the tumor microenvironment (TME), which differs considerably by organ site. However, immunocompetent mouse models of disease to study immunotherapies targeting human molecules within organ-specific TME are surprisingly rare. We developed a myc-driven, primary murine lymphoma model expressing a human-mouse chimeric CD22 (h/mCD22). Stable engraftment of three distinct h/mCD22+ lymphoma was established after subcutaneous and systemic injection. However, only systemic lymphoma showed immune infiltration that reflected human disease. In this model, myeloid cells supported lymphoma growth and showed a phenotype of myeloid-derived suppressor cells. The human CD22-targeted immunotoxin Moxetumomab was highly active against h/mCD22+ lymphoma and similarly reduced infiltration of bone marrow and spleen of all three models up to 90-fold while efficacy against lymphoma in lymph nodes varied substantially, highlighting relevance of organ-specific TME. As in human aggressive lymphoma, anti-PD-L1 as monotherapy was not efficient. However, anti-PD-L1 enhanced efficacy of Moxetumomab suggesting potential for future clinical application. The novel model system of h/mCD22+ lymphoma provides a unique platform to test targeted immunotherapies and may be amenable for other human B cell targets such as CD19 and CD20.
CRIS-Team Scopus Importer:2021-10-08
Keywords: CD22; Checkpoint molecule; Immunotoxin; Lymphoma microenvironment; MDSCs; Mouse model; Myc-driven lymphoma; Myeloid derived suppressor cells; PD-L1; Tumor microenvironment

Human CD4+ T cells specific for dominant epitopes of SARS-CoV-2 Spike and Nucleocapsid proteins with therapeutic potential - Verhagen, Johan; van der Meijden, Edith; Lang, Vanessa; Kremer, Andreas; Völkl, Simon; Mackensen, Andreas; Aigner, Michael; Kremer, Anita (Clinical and Experimental Immunology, 2021)
Since December 2019, Coronavirus disease-19 (COVID-19) has spread rapidly throughout the world, leading to a global effort to develop vaccines and treatments. Despite extensive progress, there remains a need for treatments to bolster the immune responses in infected immunocompromised individuals, such as cancer patients who recently underwent a haematopoietic stem cell transplantation. Immunological protection against COVID-19 is mediated by both short-lived neutralizing antibodies and long-lasting virus-reactive T cells. Therefore, we propose that T cell therapy may augment efficacy of current treatments. For the greatest efficacy with minimal adverse effects, it is important that any cellular therapy is designed to be as specific and directed as possible. Here, we identify T cells from COVID-19 patients with a potentially protective response to two major antigens of the SARS-CoV-2 virus, Spike and Nucleocapsid protein. By generating clones of highly virus-reactive CD4+ T cells, we were able to confirm a set of nine immunodominant epitopes and characterize T cell responses against these. Accordingly, the sensitivity of T cell clones for their specific epitope, as well as the extent and focus of their cytokine response was examined. Moreover, using an advanced T cell receptor (TCR) sequencing approach, we determined the paired TCR-αβ sequences of clones of interest. While these data on a limited population require further expansion for universal application, the results presented here form a crucial first step towards TCR-transgenic CD4+ T cell therapy of COVID-19.
CRIS-Team Scopus Importer:2021-07-09
Keywords: COVID-19; epitope; SARS-CoV-2; T cell; T cell receptor

Human Double-Negative Regulatory T-Cells Induce a Metabolic and Functional Switch in Effector T-Cells by Suppressing mTOR Activity - Haug, Tabea; Aigner, Michael; Peuser, Moritz M.; Strobl, Carolin; Hildner, Kai; Mougiakakos, Dimitrios; Bruns, Heiko; Mackensen, Andreas; Völkl, Simon (Frontiers in Immunology, 2019)
The recently discovered population of TCR alpha b + CD4-/CD8-(double-negative, DN) T-cells are highly potent suppressor cells in mice and humans. In preclinical transplantation models, adoptive transfer of DN T-cells specifically inhibits alloreactive T-cells and prevents transplant rejection or graft-vs.-host disease (GvHD). Interestingly, clinical studies in patients who underwent allogeneic stem cell transplantation reveal an inverse correlation between the frequency of circulating DN T-cells and the severity of GvHD, suggesting a therapeutic potential of human DN T-cells. However, their exact mode of action has not been elucidated yet. Investigating the impact of DN T-cells on conventional T-cells, we found that human DN T-cells selectively inhibit mTOR signaling in CD4 T-cells. Given that mTOR is a critical regulator of cellular metabolism, we further determined the impact of DN T-cells on the metabolic framework of T-cells. Intriguingly, DN T-cells diminished expression of glucose transporters and glucose uptake, whereas fatty acid uptake was not modified, indicating that DN T-cells prevent metabolic adaptation of CD4 T-cells upon activation (i.e., glycolytic switch) thereby contributing to their suppression. Further analyses demonstrated that CD4 T-cells also do not upregulate homing receptors associated with inflammatory processes. In contrast, expression of central memory-cell associated cell surface markers and transcription factors were increased by DN T-cells. Moreover, CD4 T-cells failed to produce inflammatory cytokines after co-culture with DN T-cells, whereas IL-2 secretion was enhanced. Taken together DN T-cells impair metabolic reprogramming of conventional CD4 T-cells by abrogating mTOR signaling, thereby modulating CD4 T-cell functionality. These results uncover a new mechanism of DN T-cell-mediated suppression, pointing out that DN T-cells could serve as cell-based therapy to limit alloreactive immune response.
CRIS-Team WoS Importer:2019-05-03

Human leukocyte antigen-DO regulates surface presentation of human leukocyte antigen class II-restricted antigens on B cell malignancies - Kremer, Anita; Van Der Meijden, Edith D.; Honders, M. Willy; Pont, Margot J.; Goeman, Jelle J.; Falkenburg, J. H. Frederik; Griffioen, Marieke (Biology of Blood and Marrow Transplantation, 2014)
Hematological malignancies often express surface HLA class II, making them attractive targets for CD4+ T cell therapy. We previously demonstrated that HLA class II ligands can be divided into DM-resistant and DM-sensitive antigens. In contrast to presentation of DM-resistant antigens, presentation of DM-sensitive antigens is suppressed by HLA-DM but can be rescued by HLA-DO. We also showed that HLA-DO expression remains low in nonhematopoietic cells under inflammatory conditions, suggesting that DM-sensitive antigens may be ideal T cell targets with a low risk for graft-versus-host disease. Here, we demonstrated that B cell malignancies often express HLA-DO and that levels are in particular high in chronic lymphocytic leukemia. Moreover, we showed that surface presentation of DM-sensitive antigens is regulated by HLA-DO, and that DM-sensitive antigens are relevant T cell targets for B cell malignancies and, especially, chronic lymphocytic leukemia. These data open the perspective to target HLA class II ligands with specific processing and presentation behavior for CD4+ T cell therapy of hematological malignancies.
EVALuna2:25693

Human lymphoid organ dendritic cell identity is predominantly dictated by ontogeny, not tissue microenvironment - Heidkamp, Gordon Frederik; Sander, Jil; Lehmann, Christian; Heger, Lukas; Eissing, Nathalie; Baranska, Anna; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Lux, Anja; Söder, Stephan; Hartmann, Arndt; et al. (Science immunology, 2016)
In mice, conventional and plasmacytoid dendritic cells (DCs) derive from separate hematopoietic precursors before they migrate to peripheral tissues. Moreover, two classes of conventional DCs (cDC1 and cDC2 DCs) and one class of plasmacytoid DCs (pDCs) have been shown to be transcriptionally and functionally distinct entities. In humans, these three DC subtypes can be identified using the cell surface markers CD1c (cDC2), CD141 (cDC1), and CD303 (pDCs), albeit it remains elusive whether DC functionality is mainly determined by ontogeny or the tissue microenvironment. By phenotypic and transcriptional profiling of these three DC subtypes in different human tissues derived from a large number of human individuals, we demonstrate that DC subpopulations in organs of the lymphohematopoietic system (spleen, thymus, and blood) are strongly defined by ontogeny rather than by signals from the microenvironment. In contrast, DC subsets derived from human lung or skin differed substantially, strongly arguing that DCs react toward modulatory signals from tissue microenvironments. Collectively, the data obtained in this study may serve as a major resource to guide further studies into human DC biology during homeostasis and inflammatio
EVALuna2:6852

Human lymphoid organ dendritic cell identity is predominantly dictated by ontogeny, not tissue microenvironment - Heidkamp, Gordon Frederik; Sander, J.; Lehmann, C. H. K.; Heger, Lukas; Eissing, N.; Baranska, A.; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Lux, Anja; Söder, Stephan; Hartmann, Arndt; et al. (2017)
EVALuna2:33137

Human monocytes display different levels of CD137/4-1BB expression linked to certain immunometabolic features - Stoll, Andrej; Bruns, Heiko; Saul, Domenica; Mackensen, Andreas; Mougiakakos, Dimitrios (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Hydrogen-peroxide synthesis and LDL-uptake controls immunosuppressive properties in monocyte-derived dendritic cells - Menzner, Ann-Katrin; Rottmar, Tanja; Bosch, Jacobus J.; Mougiakakos, Dimitrios; Mackensen, Andreas; Resheq, Yazid; Völkl, Simon (Cancers, 2021)
Given the encouraging success of immunotherapy in cancer, the role of metabolism in tumor immune-evasion is an emerging research field with a unique potential to overcome current limitations in immunotherapy. Herein, hepatic stromal cells, which may act as immunological bystanders in cancer, are capable of inducing immunosuppressive phenotypes in monocytic cells by controlling hydrogen peroxide (H2O2-) metabolism. As monocytic cells play an important role in tumor-immunology, we sought to identify the underlying mechanisms. Herein, we unraveled a complex interaction between cholesterol/LDL- and H2O2-metabolism: Extracellular depletion of H2O2 leads to enhanced H2O2-production with a consecutive increase in LDL-uptake throughout differentiation of monocytes to monocyte-derived dendritic cells and, as a result, to the induction of distinct immunosuppressive properties. These findings shed new light on the role of LDL-metabolism in tumor-immunology and might help to further improve immunotherapeutic approaches against cancer. Background and Aims: Induction of myeloid-derived suppressor cells (MDSC) is a critical step in immune cell evasion by different cancer types, including liver cancer. In the liver, hepatic stromal cells orchestrate induction of MDSCs, employing a mechanism dependent on hydrogen peroxide (H2O2) depletion. However, the effects on monocyte-derived dendritic cells (moDCs) are unknown. Methods: Monocytes from healthy donors were differentiated to moDCs in the presence of extracellular enzymatic H2O2-depletion (hereinafter CAT-DCs), and studied phenotypically and functionally. To elucidate the underlying molecular mechanisms, we analyzed H2O2- and LDL-metabolism as they are interconnected in monocyte-driven phagocytosis. Results: CAT-DCs were of an immature DC phenotype, particularly characterized by impaired expression of the costimulatory molecules CD80/86. Moreover, CAT-DCs were able to suppress T-cells using indoleamine 2,3-dioxygenase (IDO), and induced IL10/IL17-secreting T-cells-a subtype reported to exert immunosuppression in acute myeloid leukemia. CAT-DCs also displayed significantly increased NADPH-oxidase-driven H2O2-production, enhancing low-density lipoprotein (LDL)-uptake. Blocking LDL-uptake restored maturation, and attenuated the immunosuppressive properties of CAT-DCs. Discussion: Here, we report a novel axis between H2O2- and LDL-metabolism controlling tolerogenic properties in moDCs. Given that moDCs are pivotal in tumor-rejection, and lipid-accumulation is associated with tumor-immune-escape, LDL-metabolism appears to play an important role in tumor-immunology.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Catalase; Hydrogen peroxide; IDO; LDL-uptake; Reactive oxygen species; Tolerogenic dendritic cells; Tumor immune escape

Hyperactive mTOR pathway promotes lymphoproliferation and abnormal differentiation in autoimmune lymphoproliferative syndrome - Voelkl, Simon; Rensing-Ehl, Anne; Allgäuer, Andrea; Schreiner, Elisabeth; Lorenz, Myriam Ricarda; Rohr, Jan; Klemann, Christian; Fuchs, Ilka; Schuster, Volker; Von Bueren, Andre O.; Naumann-Bartsch, Nora; Gambineri, Eleonora; et al. (Blood, 2016)
Autoimmune lymphoproliferative syndrome (ALPS) is a human disorder characterized by defective Fas signaling, resulting in chronic benign lymphoproliferation and accumulation of TCR??(+) CD4(-) CD8(-) double-negative T (DNT) cells. Although their phenotype resembles that of terminally differentiated or exhausted T cells, lack of KLRG1, high eomesodermin, and marginal T-bet expression point instead to a long-lived memory state with potent proliferative capacity. Here we show that despite their terminally differentiated phenotype, human ALPS DNT cells exhibit substantial mitotic activity in vivo. Notably, hyperproliferation of ALPS DNT cells is associated with increased basal and activation-induced phosphorylation of serine-threonine kinases Akt and mechanistic target of rapamycin (mTOR). The mTOR inhibitor rapamycin abrogated survival and proliferation of ALPS DNT cells, but not of CD4(+) or CD8(+) T cells in vitro. In vivo, mTOR inhibition reduced proliferation and abnormal differentiation by DNT cells. Importantly, increased mitotic activity and hyperactive mTOR signaling was also observed in recently defined CD4(+) or CD8(+) precursor DNT cells, and mTOR inhibition specifically reduced these cells in vivo, indicating abnormal programming of Fas-deficient T cells before the DNT stage. Thus, our results identify the mTOR pathway as a major regulator of lymphoproliferation and aberrant differentiation in ALPS.
EVALuna2:25746

Hyper-N-glycosylated SAMD14 and neurabin-I as driver autoantigens of primary central nervous system lymphoma - Thurner, Lorenz; Preuss, Klaus Dieter; Bewarder, Moritz; Kemele, Maria; Fadle, Natalie; Regitz, Evi; Altmeyer, Sarah; Schormann, Claudia; Poeschel, Viola; Ziepert, Marita; Walter, Silke; Roth, Patrick; et al. (Blood, 2018)
To address the role of chronic antigenic stimulation in primary central nervous system lymphoma (PCNSL), we searched for autoantigens and identified sterile α-motif domain containing protein 14 (SAMD14) and neural tissue-specific F-actin binding protein I (neurabin-I) as autoantigenic targets of the B-cell receptors (BCRs) from 8/12 PCNSLs. In the respective cases, SAMD14 and neurabin-I were atypically hyper-N-glycosylated (SAMD14 at ASN339 and neurabin-I at ASN1277), explaining their autoimmunogenicity. SAMD14 and neurabin-I induced BCR pathway activation and proliferation of aggressive lymphoma cell lines transfected with SAMD14- and neurabin-I-reactive BCRs. Moreover, the BCR binding epitope of neurabin-I conjugated to truncated Pseudomonas exotoxin-killed lymphoma cells expressing the respective BCRs. These results support the role of chronic antigenic stimulation by posttranslationally modified central nervous system (CNS) driver autoantigens in the pathogenesis of PCNSL, serve as an explanation for their CNS tropism, and provide the basis for a novel specific treatment approach.
EVALuna2:35098

Hypoxia-mediated alterations and their role in the HER-2/neuregulated CREB status and localization - Steven, Andre; Leisz, Sandra; Sychra, Katharina; Hiebl, Bernhard; Wickenhauser, Claudia; Mougiakakos, Dimitrios; Kiessling, Rolf; Denkert, Carsten; Seliger, Barbara (Oncotarget, 2016)
The cAMP-responsive element-binding protein (CREB) is involved in the tumorigenicity of HER-2/neu-overexpressing murine and human tumor cells, but a link between the HER-2/neu-mediated CREB activation, its posttranslational modification and localization and changes in the cellular metabolism, due to an altered (tumor) microenvironment remains to be established. The present study demonstrated that shRNA-mediated silencing of CREB in HER-2/neu-transformed cells resulted in decreased tumor formation, which was associated with reduced angiogenesis, but increased necrotic and hypoxic areas in the tumor. Hypoxia induced pCREBSer133, but not pCREBSer121 expression in HER-2/neu-transformed cells. This was accompanied by upregulation of the hypoxia-inducible genes GLUT1 and VEGF, increased cell migration and matrix metalloproteinase-mediated invasion. Treatment of HER-2/neu+ cells with signal transduction inhibitors targeting in particular HER-2/neu was able to revert hypoxia-controlled CREB activation. In addition to changes in the phosphorylation, hypoxic response of HER-2/neu+ cells caused a transient ubiquitination and SUMOylation as well as a co-localization of nuclear CREB to the mitochondrial matrix. A mitochondrial localization of CREB was also demonstrated in hypoxic areas of HER-2/neu+ mammary carcinoma lesions. This was accompanied by an altered gene expression pattern, activity and metabolism of mitochondria leading to an increased respiratory rate, oxidative phosphorylation and mitochondrial membrane potential and consequently to an enhanced apoptosis and reduced cell viability. These data suggest that the HER-2/neu-mediated CREB activation caused by a hypoxic tumor microenvironment contributes to the neoplastic phenotype of HER-2/neu+ cells at various levels.
EVALuna:32280

Identification and characterization of T-cell receptors with therapeutic potential showing conserved specificity against all SARS-CoV 2 strains - Reimann, Hannah; Moosmann, Carolin; Schober, Kilian; Lang, Vanessa; Verhagen, Johan; Zeun, Julia; Mackensen, Andreas; Kremer, Anita; Völkl, Simon; Aigner, Michael (Immunobiology, 2023)
Introduction: Treatment of severe COVID-19 disease can be challenging in immunocompromized patients due to newly emerging virus variants of concern (VOC) escaping the humoral response. Thus, T cells recognizing to date unmutated epitopes are not only relevant for patients’ immune responses against VOC, but might also serve as a therapeutic option for patients with severe COVID-19 disease in the future, e.g. following allogenic stem cell transplantation. Methods: To this purpose, the activation, cytokine profile and specificity of T-cell clones against unmutated and omicron Spike (S)-protein was analyzed, HLA restriction was determined and most promising T-cell receptor (TCR) was introduced into allogeneic T cells via CRISPR/Cas9-mediated orthotopic TCR replacement. Finally, T-cell responses of engineered T cells was determined and durability of the TCR replacement measured. Perspective: SARS-CoV-2 specific engineered T cells recognizing a genomically stable region of the S-protein of all SARS-CoV 2 variants were successfully generated. Such transgenic T cells exhibit favorable effector functions and provide a treatment option of immunocompromised COVID-19 patients.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Orthotopic TCR replacement; SARS-CoV-2; T-cell engineering; T-cell therapy

Identification and characterization of the specific murine NK cell subset supporting graft-versus-leukemia- and reducing graft-versus-host-effects - Meinhardt, Kathrin; Kroeger, Irena; Bauer, Ruth; Ganss, Franziska; Ovsiy, Ilja; Rothamer, Johanna; Büttner, Maike; Atreya, Imke; Waldner, Maximilian; Bittrich, Max; Lehmann, Christian; Rieger, Michael A.; et al. (OncoImmunology, 2015)
Clinical studies investigating the impact of natural killer (NK) cells in allogeneic hematopoietic stem cell transplantation settings have yielded promising results. However, NK cells are a functionally and phenotypically heterogeneous population. Therefore, we addressed the functional relevance of specific NK cell subsets distinguished by expression of CD117, CD27 and CD11b surface markers in graft-versus-leukemia (GVL)-reaction and graft-versus-host-disease (GVHD). Our results clearly demonstrate that the subset of c-Kit(-)CD27(-)CD11b(+) NK cells expressed multiple cytotoxic pathway genes and provided optimal graft-versus-leukemia-effects, while significantly reducing T cell proliferation induced by allogeneic dendritic cells. Furthermore, these NK cells migrated to inflamed intestinal tissues where graft-versus-host-colitis was efficiently mitigated. For the first time, we identified the c-Kit(-)CD27(-)CD11b(+) NK cell population as the specific effector NK cell subset capable of significantly diminishing GVHD in fully mismatched bone marrow transplantation settings. In conclusion, the subset of c-Kit(-)CD27(-)CD11b(+) NK cells not only supports GVL, but also plays a unique role in the protection against GVHD by migrating to the peripheral GVHD target organs where they exert efficient immunoregulatory activities. These new insights demonstrate the importance of selecting the optimal NK cell subset for cellular immunotherapy following allogeneic hematopoietic stem cell transplantation.
EVALuna2:1965

Identification and validation of expressed HLA-binding breast cancer neoepitopes for potential use in individualized cancer therapy - Reimann, Hannah; Nguyen, Andrew; Sanborn, J. Zachary; Vaske, Charles J.; Benz, Stephen C.; Niazi, Kayvan; Rabizadeh, Shahrooz; Spilman, Patricia; Mackensen, Andreas; Rübner, Matthias; Hein, Alexander; Beckmann, Matthias; et al. (Journal for ImmunoTherapy of Cancer, 2021)
Background Therapeutic regimens designed to augment the immunological response of a patient with breast cancer (BC) to tumor tissue are critically informed by tumor mutational burden and the antigenicity of expressed neoepitopes. Herein we describe a neoepitope and cognate neoepitope-reactive T-cell identification and validation program that supports the development of next-generation immunotherapies. Methods Using GPS Cancer, NantOmics research, and The Cancer Genome Atlas databases, we developed a novel bioinformatic-based approach which assesses mutational load, neoepitope expression, human leukocyte antigen (HLA)-binding prediction, and in vitro confirmation of T-cell recognition to preferentially identify targetable neoepitopes. This program was validated by application to a BC cell line and confirmed using tumor biopsies from two patients with BC enrolled in the Tumor-Infiltrating Lymphocytes and Genomics (TILGen) study. Results The antigenicity and HLA-A2 restriction of the BC cell line predicted neoepitopes were determined by reactivity of T cells from HLA-A2-expressing healthy donors. For the TILGen subjects, tumor-infiltrating lymphocytes (TILs) recognized the predicted neoepitopes both as peptides and on retroviral expression in HLA-matched Epstein-Barr virus-lymphoblastoid cell line and BC cell line MCF-7 cells; PCR clonotyping revealed the presence of T cells in the periphery with T-cell receptors for the predicted neoepitopes. These high-avidity immune responses were polyclonal, mutation-specific and restricted to either HLA class I or II. Interestingly, we observed the persistence and expansion of polyclonal T-cell responses following neoadjuvant chemotherapy. Conclusions We demonstrate our neoepitope prediction program allows for the successful identification of neoepitopes targeted by TILs in patients with BC, providing a means to identify tumor-specific immunogenic targets for individualized treatment, including vaccines or adoptively transferred cellular therapies.
CRIS-Team Scopus Importer:2021-07-09
Keywords: Antigens; Breast neoplasms; Neoplasm

Identification of Bronchoalveolar Lavage Components Applying Confocal Laser Endomicroscopy - Zirlik, Sabine; Neurath, Markus; Meidenbauer, Norbert; Fuchs, Florian; Vieth, Michael (Medical Science Monitor, 2018)
BACKGROUND In many studies, confocal laser endomicroscopy (CLE) has proven to be a useful tool in pulmonology; nevertheless, the application in this field is still experimental. By contrast, CLE is almost a standard technique in gastroenterology. The aim of the present study was to demonstrate the identification of bronchoalveolar lavage (BAL) components applying CLE, using a dye. MATERIAL AND METHODS In 21 patients with various underlying diseases a bronchoscopy with BAL was performed. As in routine clinical practice common, BAL fluid (BALF) was analyzed in terms of cytologic, virologic, and microbiologic aspects. To one fraction of BALF, we added acriflavine. After centrifugation CLE was applied and the video sequences were analyzed by an experienced investigator. RESULTS Using CLE, BALF components (such as alveolar macrophages or leucocytes) could be easily identified. A further subdivision of leucocytes (neutrophilic, eosinophilic granulocytes, and lymphocytes) was not possible. Analogous to conventional cytology, a precise distinction of lymphocyte subpopulation (cd 4/cd 8 ratio) was not feasible. In terms of quantification, this is still the application field of flow cytometry and immunohistochemistry. CONCLUSIONS Using CLE, alveolar macrophages and leucocytes in stained BALF can be differentiated independent of smoking status. Further studies should be initiated in order to subclassify leucocytes in eosinophilic, neutrophilic granulocytes, and lymphocytes, which is important for routine clinical practice.
EVALuna2:34445

Identification of Disparities in Personalized Cancer Care—A Joint Approach of the German WERA Consortium - Lüke, Florian; Haller, Florian; Utpatel, Kirsten; Krebs, Markus; Meidenbauer, Norbert; Scheiter, Alexander; Spörl, Silvia; Heudobler, Daniel; Sparrer, Daniela; Kaiser, Ulrich; Keil, Felix; Schubart, Christoph; et al. (Cancers, 2022)
(1) Background: molecular tumor boards (MTBs) are crucial instruments for discussing and allocating targeted therapies to suitable cancer patients based on genetic findings. Currently, limited evidence is available regarding the regional impact and the outreach component of MTBs; (2) Methods: we analyzed MTB patient data from four neighboring Bavarian tertiary care oncology centers in Würzburg, Erlangen, Regensburg, and Augsburg, together constituting the WERA Alliance. Absolute patient numbers and regional distribution across the WERA-wide catchment area were weighted with local population densities; (3) Results: the highest MTB patient numbers were found close to the four cancer centers. However, peaks in absolute patient numbers were also detected in more distant and rural areas. Moreover, weighting absolute numbers with local population density allowed for identifying so-called white spots—regions within our catchment that were relatively underrepresented in WERA MTBs; (4) Conclusions: investigating patient data from four neighboring cancer centers, we comprehensively assessed the regional impact of our MTBs. The results confirmed the success of existing collaborative structures with our regional partners. Additionally, our results help identifying potential white spots in providing precision oncology and help establishing a joint WERA-wide outreach strategy.
CRIS-Team Scopus Importer:2022-11-04
Keywords: cancer care; MTB; outcomes research; outreach; patient access; precision oncology; real world data

Identification of EBV epitope-specific T cell receptors for adoptive T cell transfer against EBV infection and associated malignancies - Cobo, Lammoglia M. F.; Welters, C.; Pircher, C.; Gary, Regina; Dietze, K.; Takvorian, A.; Penter, L.; Bullinger, L.; Dornmair, K.; Moosmann, A.; Mautner, J.; Blankenstein, T.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Identification of HLA-C restricted, HIV-1-specific CTL epitopes by peptide induced upregulation of HLA-C expression - Stoll, Andrej; Bergmann, Silke; Mummert, Christiane; Mueller-Schmucker, Sandra M.; Spriewald, Bernd M.; Harrer, Ellen G.; Harrer, Thomas (Journal of Immunological Methods, 2015)
HIV-1 negative regulatory factor (Nef) can inhibit CTL recognition by downregulation of HLA-A and HLA-B on the cell surface. In contrast, HLA-C is not affected by Nef and a growing number of studies demonstrate an important role of HLA-C for the control of HIV-1. So far, only a limited number of HLA-C restricted CTL epitopes are known. As the mapping of new CTL epitopes is time and labor intensive, we investigated a novel method for the identification of HLA-C restricted CTL epitopes. B-lymphoblastoid cell lines (B-LCLs) and T2-cells were incubated with HIV-1 specific peptides and subsequently stained for HLA-C surface expression using the HLA-C specific antibody DT9. Peptides that led to increased HLA-C surface expression were used for stimulation of PBMC from HIV-1-infected patients. Subsequently, outgrowing cells were tested for peptide recognition in IFN-? ELISPOT assays and HLA restriction of the recognized peptides was analyzed in ELISPOT assays using HLA-matched B-LCL. We observed that known HLA-C binding peptides increase HLA-C surface expression on T2-cells and on HLA-C*0102 and HLA-C*0702 homozygous B-LCL. Moreover, screening of HIV-1 Nef with overlapping peptides for potential C*0702 restricted epitopes using this method revealed a total of 8 peptides which considerably increased cell surface expression of HLA-C. By epitope mapping and functional analysis of peptide-stimulated T-cell lines we were able to define the peptide YPLTFGWCY as a new C*0702-restricted CTL epitope. These results show that the analysis of peptide induced HLA-C upregulation on B-LCL and T2-cells enables the efficient identification of new HLA-C restricted CTL epitopes.
EVALuna2:13104

Identification of human CD4(+) T cells specific for dominant epitopes of SARS-CoV-2 Spike and Nucleocapsid proteins with therapeutic potential - Verhagen, Johan; van der Meijden, Edith; Lang, Vanessa; Kremer, Andreas; Völkl, Simon; Mackensen, Andreas; Aigner, Michael; Kremer, Anita (ONCOLOGY RESEARCH AND TREATMENT, 2021)
Since December 2019, Coronavirus disease-19 (COVID-19) has spread rapidly throughout the world, leading to a global effort to develop vaccines and treatments. Despite extensive progress, there remains a need for treatments to bolster the immune responses in infected immunocompromised individuals, such as cancer patients who recently underwent a haematopoietic stem cell transplantation. Immunological protection against COVID-19 is mediated by both short-lived neutralizing antibodies and long-lasting virus-reactive T cells. Therefore, we propose that T cell therapy may augment efficacy of current treatments. For the greatest efficacy with minimal adverse effects, it is important that any cellular therapy is designed to be as specific and directed as possible. Here, we identify T cells from COVID-19 patients with a potentially protective response to two major antigens of the SARS-CoV-2 virus, Spike and Nucleocapsid protein. By generating clones of highly virus-reactive CD4+ T cells, we were able to confirm a set of nine immunodominant epitopes and characterize T cell responses against these. Accordingly, the sensitivity of T cell clones for their specific epitope, as well as the extent and focus of their cytokine response was examined. Moreover, using an advanced T cell receptor (TCR) sequencing approach, we determined the paired TCR-αβ sequences of clones of interest. While these data on a limited population require further expansion for universal application, the results presented here form a crucial first step towards TCR-transgenic CD4+ T cell therapy of COVID-19.<br
CRIS-Team WoS Importer:2022-03-25
Keywords: COVID-19; SARS-CoV-2; T cell; T cell receptor; epitope

IFN-γ-driven intratumoral microenvironment exhibits superior prognostic effect compared with an IFN-α-driven microenvironment in patients with colon carcinoma - Grenz, Sandra; Naschberger, Elisabeth; Merkel, Susanne; Britzen-Laurent, Nathalie; Schaal, Ute; Konrad, Andreas; Aigner, Michael; Rau, Tilman; Hartmann, Arndt; Croner, Roland S.; Hohenberger, Werner; Stürzl, Michael (American Journal of Pathology, 2013)
Interferon (IFN)-α and IFN-γ are cytokines with potent immunomodulating and anti-tumor activities. It is unknown which of the two IFNs may be more potent in the regulation of an anti-tumorigenic response in colorectal carcinoma or whether both cytokines cooperate. We, therefore, established human myxovirus resistance protein A and human guanylate-binding protein-1 as markers for the differential detection of IFN-α- and IFN-γ-driven tumor micromilieus, respectively. In vitro studies with different cultures of tumor cells from colorectal carcinoma and stroma cells showed that the expression of myxovirus resistance protein A was exclusively induced by IFN-α, whereas guanylate-binding protein-1 was strongly induced by IFN-γ and only weakly by IFN-α. This expression pattern was used to distinguish cell activation caused by the two cytokines in a clinical cohort of patients with colon carcinoma (n = 378). Patients with primary tumors expressing only guanylate-binding protein-1 exhibited the highest cancer-specific 5-year survival (94.0%, P = 0.006) compared with those expressing both factors (90.3%, P = 0.006), myxovirus resistance protein A alone (83.5%, P = 0.096), or none (72.8%). Our study describes a successful proof-of-principle approach that complex cytokine interaction networks can be dissected in human tissues and demonstrates that an IFN-γ-driven tumor microenvironment exhibits a superior prognostic effect compared with an IFN-α-driven tumor microenvironment in colon carcinoma. © 2013 American Society for Investigative Pathology.
Created from Fastlane, Scopus look-up

IGA ISOTYPE ANTI-HLA ANTIBODIES AND ORGAN GRAFT SURVIVAL IN KIDNEY TRANSPLANTATION - Bach, Christian; Spriewald, B. M.; Arnold, Martin (2018)
EVALuna2:35091

IL-21 modulates memory and exhaustion phenotype of T-cells in a fatty acid oxidation-dependent manner - Loschinski, Romy; Böttcher, Martin; Stoll, Andrej; Bruns, Heiko; Mackensen, Andreas; Mougiakakos, Dimitrios (Oncotarget, 2018)
T-cell-based therapies represent a promising strategy for cancer treatment. In this context, cytokines are discussed as a bona fide instrument for fine-tuning T- cell biology. One promising candidate is the pleiotropic interleukin-21 (IL-21) with only little being known regarding its direct effects on human T-cells. Thus, we sought out to characterize the impact of IL-21 on T-cell metabolism, fitness, and differentiation. Culturing T-cells in presence of IL-21 elicited a metabolic skewing away from aerobic glycolysis towards fatty acid oxidation (FAO). These changes of the metabolic framework were paralleled by increased mitochondrial fitness and biogenesis. However, oxidative stress levels were not increased but rather decreased. Furthermore, elevated FAO and mitochondrial biomass together with enhanced antioxidative properties are linked to formation of longer lasting memory responses and less PD-1 expression. We similarly observed an IL-21-triggered induction of central memory-like T-cells and reduced levels of PD-1 on the cell surface. Taken together, IL-21 shifts T-cells towards an immunometabolic phenotype that has been associated with increased survivability and enhanced anti-tumor efficacy. In addition, our data reveals a novel interconnection between fatty acid metabolism and immune function regulated by IL 21.
EVALuna2:34164

IL-23 is centrally involved in mediating molecular resistance to anti-TNF therapy in Crohn's disease patients - Schmitt, H.; Billmeier, Ulrike; Dieterich, Walburga; Rath, T.; Sonnewald, Sophia; Reid, Stephen; Hirschmann, S.; Hildner, Kai; Waldner, Maximilian; Mudter, J.; Hartmann, Arndt; Grützmann, Robert; et al. (2018)
EVALuna2:34077

IL-33-induced metabolic reprogramming controls the differentiation of alternatively activated macrophages and the resolution of inflammation - Faas, Maria; Ipseiz, Natacha; Ackermann, Jochen; Culemann, Stephan; Grüneboom, Anika; Schröder, Fenja; Rothe, Tobias; Scholtysek, Carina; Eberhardt, Martin; Böttcher, Martin; Kirchner, Philipp; Stoll, Cornelia; et al. (Immunity, 2021)
Alternatively activated macrophages (AAMs) contribute to the resolution of inflammation and tissue repair. However, molecular pathways that govern their differentiation have remained incompletely understood. Here, we show that uncoupling protein-2-mediated mitochondrial reprogramming and the transcription factor GATA3 specifically controlled the differentiation of pro-resolving AAMs in response to the alarmin IL-33. In macrophages, IL-33 sequentially triggered early expression of pro-inflammatory genes and subsequent differentiation into AAMs. Global analysis of underlying signaling events revealed that IL-33 induced a rapid metabolic rewiring of macrophages that involved uncoupling of the respiratory chain and increased production of the metabolite itaconate, which subsequently triggered a GATA3-mediated AAM polarization. Conditional deletion of GATA3 in mononuclear phagocytes accordingly abrogated IL-33-induced differentiation of AAMs and tissue repair upon muscle injury. Our data thus identify an IL-4-independent and GATA3-dependent pathway in mononuclear phagocytes that results from mitochondrial rewiring and controls macrophage plasticity and the resolution of inflammation.
CRIS-Team Scopus Importer:2021-11-19
Keywords: alternatively activated macrophage; GATA3; interleukin-33; itaconate; mitochondrial rewiring; resolution of inlammation; UCP2; uncoupling

IL-3 is essential for ICOS-L stabilization on mast cells, and sustains the IL-33-induced RORγt+ Treg generation via enhanced IL-6 induction - Drube, Sebastian; Müller, Sylvia; Weber, Franziska; Wegner, Philine; Böttcher-Loschinski, Romy; Gaestel, Matthias; Hutloff, Andreas; Kamradt, Thomas; Andreas, Nico (Immunology, 2021)
IL-33 is a member of the IL-1 family. By binding to its receptor ST2 (IL-33R) on mast cells, IL-33 induces the MyD88-dependent activation of the TAK1-IKK2 signalling module resulting in activation of the MAP kinases p38, JNK1/2 and ERK1/2, and of NFκB. Depending on the kinases activated in these pathways, the IL-33-induced signalling is essential for production of IL-6 or IL-2. This was shown to control the dichotomy between RORγt+ and Helios+ Tregs, respectively. SCF, the ligand of c-Kit (CD117), can enhance these effects. Here, we show that IL-3, another growth factor for mast cells, is essential for the expression of ICOS-L on BMMCs, and costimulation with IL-3 potentiated the IL-33-induced IL-6 production similar to SCF. In contrast to the enhanced IL-2 production by SCF-induced modulation of the IL-33 signalling, IL-3 blocked the production of IL-2. Consequently, IL-3 shifted the IL-33-induced Treg dichotomy towards RORγt+ Tregs at the expense of RORγt− Helios+ Tregs. However, ICOS-L expression was downregulated by IL-33. In line with that, ICOS-L did not play any important role in the Treg modulation by IL-3/IL-33-activated mast cells. These findings demonstrate that different from the mast cell growth factor SCF, IL-3 can alter the IL-33-induced and mast cell-dependent regulation of Treg subpopulations by modulating mast cell-derived cytokine profiles.
CRIS-Team Scopus Importer:2021-02-05
Keywords: IL-3; IL-33; immune homeostasis; mast cells; T

IL-7 Abrogates the Immunosuppressive Function of Human Double-Negative T Cells by Activating Akt/mTOR Signaling - Allgäuer, Andrea; Schreiner, Elisabeth; Ferrazzi, Fulvia; Ekici, Arif Bülent; Gerbitz, Armin; Mackensen, Andreas; Voelkl, Simon (Journal of Immunology, 2015)
Recently, a novel subset of TCR??(+) CD4(-) CD8(-) double-negative (DN) T cells was described to suppress immune responses in both mice and humans. Moreover, in murine models, infusion and/or activation of DN T cells specifically suppressed alloreactive T cells and prevented the development of graft-versus-host disease after allogeneic hematopoietic stem cell transplantation. We demonstrated that human DN T cells, like their murine counterparts, are highly potent suppressor cells of both CD4(+) and CD8(+) T cell responses. After hematopoietic stem cell transplantation and other lymphopenic conditions, IL-7 plays an important role in the reconstitution, survival, and homeostasis of the T cell compartment. Because IL-7 was shown to interfere with T cell functionality, we asked whether IL-7 affects the functionality of human DN T cells. Intriguingly, IL-7 diminished the suppressive activity of DN T cells toward allogeneic CD4(+) effector T cells. Of interest, our studies revealed that IL-7 activates the Akt/mechanistic target of rapamycin (mTOR) pathway in human DN T cells. Importantly, selective inhibition of the protein kinases Akt or mTOR reversed the IL-7 effect, thereby restoring the functionality of DN T cells, whereas inhibition of other central T cell signaling pathways did not. Further analyses suggest that the IL-7/Akt/mTOR signaling cascade downregulates anergy-associated genes and upregulates activation- and proliferation-associated factors that may be crucial for DN T cell functionality. These findings indicate that IL-7 and Akt/mTOR signaling are critical factors for the suppressive capacity of DN T cells. Targeting of these pathways by pharmacological agents may restore and/or enhance DN T cell functionality in graft-versus-host disease.
EVALuna2:9259

Imatinib Triggers Phagolysosome Acidification and Antimicrobial Activity against Mycobacterium bovis Bacille Calmette-Guérin in Glucocorticoid-Treated Human Macrophages - Steiger, Julia; Stephan, Alexander; Inkeles, Megan S.; Realegeno, Susan; Bruns, Heiko; Kroell, Philipp; Kroner, Juliana De Castro; Sommer, Andrea; Batinica, Marina; Pitzler, Lena; Kalscheuer, Rainer; Hartmann, Pia; et al. (Journal of Immunology, 2016)
Glucocorticoids are extensively used to treat inflammatory diseases; however, their chronic intake increases the risk for mycobacterial infections. Meanwhile, the effects of glucocorticoids on innate host responses are incompletely understood. In this study, we investigated the direct effects of glucocorticoids on antimycobacterial host defense in primary human macrophages. We found that glucocorticoids triggered the expression of cathelicidin, an antimicrobial critical for antimycobacterial responses, independent of the intracellular vitamin D metabolism. Despite upregulating cathelicidin, glucocorticoids failed to promote macrophage antimycobacterial activity. Gene expression profiles of human macrophages treated with glucocorticoids and/or IFN-?, which promotes induction of cathelicidin, as well as antimycobacterial activity, were investigated. Using weighted gene coexpression network analysis, we identified a module of highly connected genes that was strongly inversely correlated with glucocorticoid treatment and associated with IFN-? stimulation. This module was linked to the biological functions autophagy, phagosome maturation, and lytic vacuole/lysosome, and contained the vacuolar H(+)-ATPase subunit a3, alias TCIRG1, a known antimycobacterial host defense gene, as a top hub gene. We next found that glucocorticoids, in contrast with IFN-?, failed to trigger expression and phagolysosome recruitment of TCIRG1, as well as to promote lysosome acidification. Finally, we demonstrated that the tyrosine kinase inhibitor imatinib induces lysosome acidification and antimicrobial activity in glucocorticoid-treated macrophages without reversing the anti-inflammatory effects of glucocorticoids. Taken together, we provide evidence that the induction of cathelicidin by glucocorticoids is not sufficient for macrophage antimicrobial activity, and identify the vacuolar H(+)-ATPase as a potential target for host-directed therapy in the context of glucocorticoid therap
EVALuna2:25741

Immature platelets do not reliably predict platelet recovery in patients with intensive chemotherapy or stem cell transplantation - Meintker, Lisa; Fritsch, Juliana; Ringwald, J.; Krause, Stefan (Vox Sanguinis, 2017)
It has been reported that immature platelets may indicate imminent platelet (PLT) recovery following intensive chemotherapy and/or haematopoietic stem cell transplantation with the perspective to withhold unnecessary transfusions. The objective of our prospective study was to test immature PLTs as measured by two haematology analysers to predict PLT recovery.This study monitored 51 courses of severe thrombocytopenia after chemotherapy in 35 adult haematology/oncology patients starting at a PLT count <70 × 10(9) /l until PLT recovery (>20 × 10(9) /l) or discharge from hospital. Immature platelets as measured by immature platelet fraction (IPF) (Sysmex XE-5000) and retPLT (Abbott CD-Sapphire) as well as reticulocyte and leucocyte count were evaluated regarding their usefulness to predict PLT recovery. Furthermore, the influence of platelet concentrate (PC) transfusions upon IPF and retPLT was assessed.With beginning of thrombocytopenia, most patients demonstrated elevated IPF% (median 8·6%) and retPLT% (median 6·8%). These elevated values significantly dropped after transfusions of PCs. IPF and retPLT values during nadir and at imminent PLT recovery were largely overlapping and receiver operating characteristics analysis demonstrated poor separation between both clinical situations. A reasonable cut-off could not be established to prospectively predict imminent PLT recovery for either of the parameters investigated.Measurements of IPF and retPLT lack predictive power regarding imminent PLT recovery in patients with severe thrombocytopenia following intensive chemotherapy. Decisions regarding prophylactic PC transfusions should not be based on these parameters.
EVALuna2:25760

Immune cell regulation by vitamin D-3 during allogeneic hematopoietic stem cell transplantation (HSCT) - Flamann, Cindy; Zeun, J.; Kremer, Andreas; Peter, K.; Kreutz, M.; Büttner-Herold, Maike; Kellner, C.; Saul, Domenica; Mougiakakos, Dimitrios; Mackensen, Andreas; Bruns, Heiko; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Immune Checkpoint Co-blockade of CD47 and HLA Class I Receptors to increase CD20 Antibody-mediated Phagocytosis of Lymphoma Cells - Zeller, T.; Lutz, S.; Munnich, I. A.; Windisch, R.; Hilger, P.; Herold, T.; Tahiri, N.; Banck, J. C.; Weigert, O.; Moosmann, A.; Von Bergwelt-Baildon, M.; Bruns, Heiko; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Immune-Epithelial Crosstalk in Inflammatory Bowel Diseases and Mucosal Wound Healing - Leppkes, Moritz; Siegmund, Britta; Becker, Christoph (Frontiers in Immunology, 2018)
EVALuna2:35168

Immune modulatory effects of Idelalisib in stromal cells of chronic lymphocytic leukemia - Handl, Sarah Annika; Von Heydebrand, Franziska; Völkl, Simon; Oostendorp, Robert A. J.; Wilke, Jochen; Kremer, Anita; Mackensen, Andreas; Lutzny-Geier, Gloria (Leukemia & Lymphoma, 2021)
Molecular targets of tyrosine kinase inhibitors are not restricted to the B-cell compartment but also regulate functions in the tumor microenvironment. Increasing evidence suggests that B-cell receptor-associated kinases like protein kinase C (PKC)-beta is essential for the formation of a microenvironment supporting leukemic growth. Here we describe the effect of Idelalisib on the PKC beta/NF-kappa B and Notch pathway in stromal cells upon contact to primary chronic lymphocytic leukemia cells (CLL). There is no Idelalisib-dependent regulation of the Notch expression in stromal cells, whereas Idelalisib induces PKC beta expression and activates the canonical NF-kappa B pathway. Idelalisib deregulates important immune-modulatory proteins in activated stromal cells, which might provoke the patient's side effects. Additionally, we established a 3D-stroma/leukemia model, that can give us a more defined look into the communication between tumor and stromal cells than standard cell cultures. This opens up the possibility to improve therapies, especially in the context of minimal-residual disease.
CRIS-Team WoS Importer:2021-05-28

Immunohistochemical panel for the diagnosis of Hirschsprung's disease using antibodies to MAP2, calretinin, GLUT1 and S100 - Bachmann, Leonhard; Besendörfer, Manuel; Carbon, Roman; Lux, Philipp; Agaimy, Abbas; Hartmann, Arndt; Rau, Tilman (Histopathology, 2015)
The diagnosis of Hirschsprung's disease is currently based on the identification of aganglionosis and the presence of an increase in acetylcholinesterase-positive hypertrophic nerve fibres in the large bowel submucosa. However, acetylcholinesterase staining is laborious and requires a skilled technician. The aim of this study was to identify a method for diagnosing Hirschsprung's disease reliably using an immunohistochemical panel of recently proposed markers.Sixty-nine specimens from 37 patients were evaluated. MAP2 and calretinin antibodies were shown to stain ganglia reliably in the submucosal and myenteric plexuses of normal tissue. By contrast, reduced staining of ganglia was observed in patients with Hirschsprung's disease. Staining for GLUT1 and S100 was used to evaluate the number and thickness of nerve fibres. Gain of GLUT1 and S100 expression was in contrast to the loss of calretinin and MAP2. Hypertrophic submucosal nerve fibres in Hirschsprung's disease develop a perineurium with a ring-like GLUT1 staining pattern similar in size and intensity to that observed in deeper subserosal tissue.The diagnosis of Hirschsprung's disease using immunohistochemical panels could be as accurate as with conventional frozen section techniques. In particular, the use of a combination of markers for ganglia and hypertrophic nerve fibres highlighting a prominent perineurium in Hirschsprung's disease could be an alternative method.
EVALuna2:6718

Immunometabolic alteration in NK cells from multiple myeloma patients - Jacobs, Benedikt; Richter, S.; Stoll, Andrej; Völkl, Simon; Mackensen, Andreas; Mougiakakos, D. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Immunometabolic alterations in lymphoma patients with early relapse upon autologous stem cell transplantation - Richter, Swetlana; Jacobs, Benedikt; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

IMMUNOMONITORING OF CD19. CAR T-CELLS IN LARGE B-CELL LYMPHOMA- A TWO-CENTER EXPERIENCE - Blumenberg, V.; Völkl, Simon; Busch, G.; Baumann, S.; Winkelmann, M.; Tast, B.; Nixdorf, D.; Haenel, G.; Froelich, L.; Schmidt, C.; Jitschin, R.; Vettermann, F.; et al. (JOURNAL FOR IMMUNOTHERAPY OF CANCER, 2021)
Background: CD19. CAR T-cells for the treatment of relapsed and refractory (r/r) Diffuse Large B-Cell Lymphoma (DLBCL) demonstrated complete responses in 40%-58% of the patients. Recently, others could associate high tumor volume and low CAR T-cell expansion in vivo with poor outcome. We hypothesize, that the expansion and immunphenotype of (CAR) T cells in vivo determine treatment response and depend on patient- and disease associated factors. Materials and Methods Patients with r/r DLBCL (n=34) were treated with either Axi-cel or Tisa-cel at the University Hospitals of Erlangen and Munich (LMU). The CAR T-cell product and peripheral blood were collected on day 0, 4, 7, 14, 30, 60 and 90 post transfusion. CAR T-cells were detected through flow cytometry utilizing a two step-staining with a biotinylated CD19 protein. Effector:Target (E:T) Ratios were estimated as absolute peak expansion of CAR T-cells (/ul) per tumorvolume (cm3). Responder (R, complete or partial remission) were compared to Non-Responder (NR, table or progressive disease) according to response assessment with PET-CT three months after transfusion. Results: CAR T-cell expansion peaked between day 7 and day 14 after transfusion with a greater expansion of CD8+compared to CD8- CAR T-cells on day 14 (59.27% vs 37.42%, p=0.021). The ratio of CD8+ and CD8- CAR T-cells did not differ between R and NR, however R exhibited higher E:T ratios of CD3+ CAR T-cells compared to NR (20.94 vs 12.81, p=0.015) and an increased E:T ratio of CD8+ CAR T-cells correlated with better progression-free survival (p=0.033). Interestingly, high CRP and ferritin levels at baseline were inversely associated with the E:T ratio (p=0.048 and p=0.017). CD3+ CAR T-cells of R showed earlier peak expression of PD-1 than NR (day 7 vs day 21). Further, peak expansion of CD3+ CAR T-cells correlated with higher PD-1 expression in R but not in NR (p=0.003 vs p=0.12). In addition, R revealed an increased relative frequency of effector memory differentiated CD3+ CAR T-cells (CCR7-CD45RA-, p=0.02), whereas CAR T-cells in NR showed an increased relative frequency of a naïve phenotype (CCR7+CD45RA+, p=0.001) on day 7 post infusion. Conclusions: Flow-based immunomonitoring with longitudinal characterization of CAR T-cells demonstrated a correlation of the E:T ratio with treatment response and survival. Increased inflammatory conditions at baseline correlated with diminished E:T ratios. Notably, in R CAR peak expansion was positively associated with higher PD-1 expression suggestive for superior CAR T-cell activation. In addition, greater memory differentiation was associated with efficacy during the time of peak expansion. Multiparameter analysis with other clinical covariates will show, whether CAR T-cell expansion and immunphenotypes can predict patient outcom
CRIS-Team WoS Importer:2021-12-03

Impact of age on outcome of CAR-T cell therapies for large B-cell lymphoma: the GLA/DRST experience - Dreger, Peter; Holtick, Udo; Subklewe, Marion; von Tresckow, Bastian; Ayuk, Francis; Wagner, Eva; Wulf, Gerald; Marks, Reinhardt; Penack, Olaf; Schnetzke, Ulf; Koenecke, Christian; von Bonin, Malte; et al. (Bone Marrow Transplantation, 2022)
CRIS-Team Scopus Importer:2022-12-09

Impact of BMI on patient outcome in acute myeloid leukaemia patients receiving intensive induction therapy: a real-world registry experience - Enßle, Julius C.; Wolf, Sebastian; Scheich, Sebastian; Weber, Sarah; Kramer, Michael; Ruhnke, Leo; Schliemann, Christoph; Mikesch, Jan Henrik; Krause, Stefan; Sauer, Tim; Hanoun, Maher; Reinhardt, Hans Christian; et al. (British Journal of Cancer, 2023)
Background: Acute myeloid leukaemia (AML) is treated with intensive induction chemotherapy (IT) in medically fit patients. In general, obesity was identified as a risk factor for all-cause mortality, and there is an ongoing debate on its impact on outcome and optimal dosing strategy in obese AML patients. Methods: We conducted a registry study screening 7632 patients and assessed the impact of obesity in 1677 equally IT treated, newly diagnosed AML patients on the outcome (OS, EFS, CR1), comorbidities, toxicities and used dosing strategies. Results: Obese patients (BMI ≥ 30) displayed a significant inferior median OS (29.44 vs. 47.94 months, P = 0.015) and CR1 rate (78.7% vs. 84.3%, P = 0.015) without differences in median EFS (7.8 vs. 9.89 months, P = 0.3) compared to non-obese patients (BMI < 30). The effect was predominantly observed in older (≥60 years) patients. Obesity was identified as an independent risk factor for death, and obese patients demonstrated higher rates of cardiovascular or metabolic comorbidities. No differences for OS, EFS, CR1 or treatment-related toxicities were observed by stratification according to used dosing strategy or dose reduction. Conclusions: In conclusion, this study identifies obesity as an independent risk factor for worse OS in older AML patients undergoing curative IT most likely due to obesity-related comorbidities and not to dosing strategy.
CRIS-Team Scopus Importer:2023-08-18

Impact of Body Mass Index on Patient Outcome in Acute Myeloid Leukemia Patients Receiving Intensive Induction Therapy: A Real-World Registry Experience - Enssle, Julius Christoph; Wolf, Sebastian; Scheich, Sebastian; Weber, Sarah; Kramer, Michael; Ruhnke, Leo; Schliemann, Christoph; Mikesch, Jan-Henrik; Krause, Stefan; Sauer, Tim; Hanoun, Maher; Reinhardt, Hans Christian; et al. (BLOOD, 2021)
CRIS-Team WoS Importer:2022-09-09

Impact of collection programs for the generation of monocyte apheresis products on product quality and composition as starting material for the generation of cellular therapeutics - Pfeiffer, Hella; Gary, Regina; Mackensen, Andreas; Achenbach, Susanne; Strasser, Erwin; Aigner, Michael; Völkl, Simon (Transfusion, 2018)
BACKGROUND: With the discontinuation of the last generation of apheresis machines, new options for monocyte apheresis became available. As apheresis products play a crucial role in the generation of new cellular therapeutics (e.g., generation of dendritic cells [DCs] or precursor for T-cell experiments) we sought to compare two different collection programs for potential benefits or disadvantages due to different composition of the cellular products. STUDY DESIGN AND METHODS: Composition of discontinuously and continuously collected monocyte products from the same 13 donors was analyzed. For further evaluation as starting material for manufacturing of cellular therapeutics typically used steps such as Ficoll Isopaque, cryoconservation and monocyte isolation, with subsequent generation of mature DCs (mDCs) and assessment of T-cell function, were performed on seven of these apheresis pairs. RESULTS: Yield of total cells, monocytes, and mDCs was equal with both methods. T-cell composition did not differ significantly in content of CD3+, CD4+, and CD8+ cells. Differentiation status and cytokine production of CD8+ T cells upon stimulation with cytomegalovirus pp65 antigen was not significantly different. CONCLUSION: Both methods seem comparably suited for the generation of cellular products. If the intended use is "fresh" (without cryoconservation), continuously harvested cells show better cell numbers, while discontinuously harvested cells show better recovery after cryoconservation.
EVALuna2:34646

Impact of comorbidities on outcome with second and further line TKI treatment in patients with chronic myeloid leukemia - Yildirim-Zuemruet, G.; Kohlbrenner, K.; Hehlmann, R.; Fabarius, A.; Baerlocher, G. M.; Krause, Stefan; Burchert, A.; Hofmann, W. -K.; Hochhaus, A.; Pfirrmann, M.; Lauseker, M.; Saussele, S. (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Impact of comorbidities on overall survival in patients with chronic myeloid leukemia: results of the randomized CML study IV - Saussele, Susanne; Krauss, Marie-Paloma; Hehlmann, Ruediger; Lauseker, Michael; Proetel, Ulrike; Kalmanti, Lida; Hanfstein, Benjamin; Fabarius, Alice; Kraemer, Doris; Berdel, Wolfgang E.; Bentz, Martin; Staib, Peter; et al. (Blood, 2015)
We studied the influence of comorbidities on remission rate and overall survival (OS) in patients with chronic myeloid leukemia (CML). Participants of the CML Study IV, a randomized 5-arm trial designed to optimize imatinib therapy, were analyzed for comorbidities at diagnosis using the Charlson Comorbidity Index (CCI); 511 indexed comorbidities were reported in 1519 CML patients. Age was an additional risk factor in 863 patients. Resulting CCI scores were as follows: CCI 2, n = 589; CCI 3 or 4, n = 599; CCI 5 or 6, n = 229; and CCI >= 7, n = 102. No differences in cumulative incidences of accelerated phase, blast crisis, or remission rates were observed between patients in the different CCI groups. Higher CCI was significantly associated with lower OS probabilities. The 8-year OS probabilities were 93.6%, 89.4%, 77.6%, and 46.4% for patients with CCI 2, 3 to 4, 5 to 6, and >=7, respectively. In multivariate analysis, CCI was the most powerful predictor of OS, which was still valid after removal of its age-related components. Comorbidities have no impact on treatment success but do have a negative effect on OS, indicating that survival of patients with CML is determined more by comorbidities than by CML itself. OS may therefore be inappropriate as an outcome measure for specific CML treatments. The trial was registered at www.clinicaltrials.gov as #NCT00055874.
EVALuna2:25724

Impact of IDH1 and IDH2 mutational subgroups in acute myeloid leukemia patients after allogeneic hematopoietic cell transplantation - Kunadt, D.; Stasik, S.; Metzeler, K.; Roellig, C.; Kramer, M.; Greif, P.; Spiekermann, K.; Rothenberg-Thurley, M.; Krug, U.; Braess, J.; Kraemer, A.; Hochhaus, A.; et al. (BONE MARROW TRANSPLANTATION, 2022)
CRIS-Team WoS Importer:2022-11-25

Impact of IDH1 and IDH2 mutational subgroups in AML patients after allogeneic stem cell transplantation - Kunadt, Desiree; Stasik, Sebastian; Metzeler, Klaus H.; Roellig, Christoph; Schliemann, Christoph; Greif, Philipp A.; Spiekermann, Karsten; Rothenberg-Thurley, Maja; Krug, Utz; Braess, Jan; Kraemer, Alwin; Hochhaus, Andreas; et al. (Journal of Hematology & Oncology, 2022)
BACKGROUND: The role of allogeneic hematopoietic cell transplantation (alloHCT) in acute myeloid leukemia (AML) with mutated IDH1/2 has not been defined. Therefore, we analyzed a large cohort of 3234 AML patients in first complete remission (CR1) undergoing alloHCT or conventional chemo-consolidation and investigated outcome in respect to IDH1/2 mutational subgroups (IDH1 R132C, R132H and IDH2 R140Q, R172K). METHODS: Genomic DNA was extracted from bone marrow or peripheral blood samples at diagnosis and analyzed for IDH mutations with denaturing high-performance liquid chromatography, Sanger sequencing and targeted myeloid panel next-generation sequencing, respectively. Statistical as-treated analyses were performed using R and standard statistical methods (Kruskal-Wallis test for continuous variables, Chi-square test for categorical variables, Cox regression for univariate and multivariable models), incorporating alloHCT as a time-dependent covariate. RESULTS: Among 3234 patients achieving CR1, 7.8% harbored IDH1 mutations (36% R132C and 47% R132H) and 10.9% carried IDH2 mutations (77% R140Q and 19% R172K). 852 patients underwent alloHCT in CR1. Within the alloHCT group, 6.2% had an IDH1 mutation (43.4% R132C and 41.4% R132H) and 10% were characterized by an IDH2 mutation (71.8% R140Q and 24.7% R172K). Variants IDH1 R132C and IDH2 R172K showed a significant benefit from alloHCT for OS (p = .017 and p = .049) and RFS (HR = 0.42, p = .048 and p = .009) compared with chemotherapy only. AlloHCT in IDH2 R140Q mutated AML resulted in longer RFS (HR = 0.4, p = .002). CONCLUSION: In this large as-treated analysis, we showed that alloHCT is able to overcome the negative prognostic impact of certain IDH mutational subclasses in first-line consolidation treatment and could pending prognostic validation, provide prognostic value for AML risk stratification and therapeutic decision making.
CRIS-Team Scopus Importer:2022-09-16
Keywords: Acute myeloid leukemia; Allogeneic hematopoietic cell transplantation; IDH mutations

Impact of immunosuppressive treatment on the bioenergetics of T-cells - Karl, Franziska; Gamali, S.; Mackensen, Andreas; Mougiakakos, Dimitrios (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Impact of Nrf2 expression in reconstituting T-cells of allogeneic hematopoietic stem cell transplanted patients - Karl, Franziska; Stoll, Andrej; Böttcher-Loschinski, Romy; Böttcher, Martin; Jacobs, Benedikt; Jitschin, Regina; Rösler, Wolf; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon; Baur, Rebecca (Leukemia, 2020)
CRIS-Team Scopus Importer:2020-07-31

Impact of Nrf2 expression in reconstituting T-cells of allogeneic hematopoietic stem cell transplanted patients - Karl, Franziska; Stoll, Andrej; Gamali, S.; Böttcher-Loschinski, Romy; Böttcher, Martin; Baur, Rebecca; Jacobs, Benedikt; Rösler, Wolf; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Impact of PTPN11 mutations on clinical outcome analyzed in 1529 patients with acute myeloid leukemia - Stasik, Sebastian; Eckardt, Jan-Niklas; Kramer, Michael; Roellig, Christoph; Kraemer, Alwin; Scholl, Sebastian; Hochhaus, Andreas; Crysandt, Martina; Bruemmendorf, Tim H.; Naumann, Ralph; Steffen, Bjorn; Kunzmann, Volker; et al. (Blood Advances, 2021)
The tyrosine-protein phosphatase nonreceptor type 11 (PTPN11) is an important regulator of RAS signaling and frequently affected by mutations in patients with acute myeloid leukemia (AML). Despite the relevance for leukemogenesis and as a potential therapeutic target, the prognostic role is controversial. To investigate the prognostic impact of PTPN11 mutations, we analyzed 1529 adult AML patients using next-generation sequencing. PTPN11 mutations were detected in 106 of 1529 (6.93%) patients (median VAF: 24%) in dominant (36%) and subclonal (64%) configuration. Patients with PTPN11 mutations were associated with concomitant mutations in NPM1 (63%), DNMT3A (37%), and NRAS (21%) and had a higher rate of European LeukemiaNet (ELN) favorable cytogenetics (57.8% vs 39.1%; P < .001) and higher white blood cell counts (P = .007) compared with PTPN11 wild-type patients. In a multivariable analysis, PTPN11 mutations were independently associated with poor overall survival (hazard ratio [HR]: 1.75; P < .001), relapse-free survival (HR: 1.52; P = .013), and a lower rate of complete remission (odds ratio: 0.46; P = .008). Importantly, the deleterious effect of PTPN11 mutations was confined predominantly to the ELN favorable-risk group and patients with subclonal PTPN11 mutations (HR: 2.28; P < .001) but not found with dominant PTPN11 mutations (HR: 1.07; P = .775), presumably because of significant differences within the rate and spectrum of associated comutations. In conclusion, our data suggest an overall poor prognostic impact of PTPN11 mutations in AML, which is significantly modified by the underlying cytogenetics and the clonal context in which they occur.
CRIS-Team WoS Importer:2021-10-15

Impact of spatially heterogeneous trop‐2 expression on prognosis in oral squamous cell carcinoma - Erber, Ramona; Spoerl, Steffen; Mamilos, Andreas; Krupar, Rosemarie; Hartmann, Arndt; Rübner, Matthias; Taxis, Juergen; Wittenberg, Mareike; Reichert, Torsten E.; Spanier, Gerrit; Spörl, Silvia (International Journal of Molecular Sciences, 2022)
Oral cancer often presents with aggressive behavior and a high risk of recurrence and metastasis. For oral squamous cell carcinoma (OSCC), which is the most frequent histological subtype, therapy strategies include surgery, radiation therapy, chemotherapy, immune checkpoint inhibitors, and EGFR inhibitors. Recently, a Trop‐2 antibody‐drug conjugate (ADC) has been approved in the United States of America for the treatment of advanced triple‐negative breast cancer. However, this ADC has also been tested in other solid tumors including head & neck squamous cell carcinoma. The prognostic impact of Trop‐2 has already been reported for several cancers. We studied the prognostic influence of Trop‐2 protein expression on OSCC patients’ survival. The cohort comprised n = 229 OSCC patients with available archived tumor tissue and corresponding non‐neoplastic oral mucosa tissue. Using immunohistochemistry, we investigated Trop‐2 expression in both the central and peripheral regions of each tumor and in corresponding non‐neoplastic oral mucosa. In patients suffering from OSCC with combined high central and low peripheral Trop‐2 expression, five‐year overall survival (OS) was 41.2%, whereas 55.6% of OSCC patients who presented lower central and/or higher peripheral tumoral Trop‐2 expression were alive after five years (p = 0.075). In multivariate Cox regression, the expression pattern of high central tumoral and lower peripheral Trop‐2 expression was significantly correlated with impaired OS (HR = 1.802, 95%‐CI: 1.134–2.864; p = 0.013) and recurrence‐free survival (RFS) (HR = 1.633, 95%‐CI: 1.042–2.560; p = 0.033), respectively, when adjusting for co‐variables. Hence, Trop‐2 may serve as an independent prognostic biomarker in OSCC. In subsequent studies, the pathophysiological meaning of downregulated Trop‐2 expression in the OSCC periphery has to be analyzed.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Antibody‐drug conjugates; Biomarker; Head and neck cancer; Immunohistochemistry; Oral squamous cell carcinoma; Prognosis; TACSTD2; Trop‐2; Tumor associated calcium signal transducer 2

Impact of timing of continuous intravenous anesthetic drug treatment on outcome in refractory status epilepticus - Madzar, Dominik; Reindl, Caroline; Giede-Jeppe, Antje; Bobinger, Tobias; Sprügel, Maximilian; Knappe, Ruben U.; Hamer, Hajo; Huttner, Hagen (Critical Care, 2018)
BACKGROUND: Patients in refractory status epilepticus (RSE) may require treatment with continuous intravenous anesthetic drugs (cIVADs) for seizure control. The use of cIVADs, however, was recently associated with poor outcome in status epilepticus (SE), raising the question of whether cIVAD therapy should be delayed for attempts to halt seizures with repeated non-anesthetic antiepileptic drugs. In this study, we aimed to determine the impact of differences in therapeutic approaches on RSE outcome using timing of cIVAD therapy as a surrogate for treatment aggressiveness. METHODS: This was a retrospective cohort study over 14 years (n = 77) comparing patients with RSE treated with cIVADs within and after 48 h after RSE onset, and functional status at last follow-up was the primary outcome (good = return to premorbid baseline or modified Rankin Scale score of less than 3). Secondary outcomes included discharge functional status, in-hospital mortality, RSE termination, induction of burst suppression, use of thiopental, duration of RSE after initiation of cIVADs, duration of mechanical ventilation, and occurrence of super-refractory SE. Analysis was performed on the total cohort and on subgroups defined by RSE severity according to the Status Epilepticus Severity Score (STESS) and by the variables contained therein. RESULTS: Fifty-three (68.8%) patients received cIVADs within the first 48 h. Early cIVAD treatment was independently associated with good outcome (adjusted risk ratio [aRR] 3.175, 95% confidence interval [CI] 1.273-7.918; P = 0.013) as well as lower chance of both induction of burst suppression (aRR 0.661, 95% CI 0.507-0.861; P = 0.002) and use of thiopental (aRR 0.446, 95% CI 0.205-0.874; P = 0.043). RSE duration after cIVAD initiation was shorter in the early cIVAD cohort (hazard ratio 1.796, 95% CI 1.047-3.081; P = 0.033). Timing of cIVAD use did not impact the remaining secondary outcomes. Subgroup analysis revealed early cIVAD impact on the primary outcome to be driven by patients with STESS of less than 3. CONCLUSIONS: Patients with RSE treated with cIVADs may benefit from early initiation of such therapy.
EVALuna2:201933

Impact of trisomy 19 on outcome according to genetic makeup in patients with acute myeloid leukemia - Kayser, Sabine; Martínez-Cuadrón, David; Rodriguez-Veiga, Rebeca; Hänel, Mathias; Tormo, Mar; Schäfer-Eckart, Kerstin; Botella, Carmen; Stölzel, Friedrich; Del Castillo, Teresa Bernal; Keller, Ulrich; Rodriguez-Medina, Carlos; Held, Gerhard; et al. (Haematologica, 2023)
We retrospectively studied 97 acute myeloid leukemia patients with trisomy 19 (median age at diagnosis 57 years; range, 17- 83 years) treated between 2001 and 2019 within two multicenter study groups. Trisomy 19 occurred alone in ten (10.5%) patients, with additional abnormalities being present in non-complex karyotypes in eight (8%) patients and in complex karyotypes in 79 (82%) patients. Altogether, karyotypes characterized by trisomies only were present in 27 (28%) patients. Data on response and outcome of intensively treated patients were available for 92 cases. The median follow-up was 6.4 years (95% confidence interval [95% CI]: 2.9-9.0 years). The complete remission (CR) rate after induction therapy was 52% (48 patients); the early death rate was 10% (n=9). Notably, patients with trisomy 19 as the sole abnormality had a CR rate of 89%. Allogeneic hematopoietic stem cell transplantation (allo-HCT) was performed in 34 (35%) patients (CR, n=19; active disease, n=15). Five-year relapse-free and overall survival rates were 26% (95% CI: 16-43%) and 20% (95% CI: 13-31%), respectively. Overall survival rates were significantly higher in patients with trisomy 19 as the sole abnormality or within karyotypes characterized by trisomies only (P=0.05). An Andersen-Gill model including allo-HCT as a time-dependent covariable on overall survival revealed that trisomy 19 as the sole abnormality or within karyotypes characterized by trisomies only was a favorable factor (hazard ratio [HR]=0.47; P=0.021); higher age at diagnosis had an adverse impact (10 years difference; HR=1.29; P=0.002), whereas allo-HCT did not have a beneficial impact (odds ratio=1.45; P=0.21). In our cohort, patients with trisomy 19 as the sole abnormality or within karyotypes characterized by trisomies only had a high CR rate and better clinical outcome.
CRIS-Team Scopus Importer:2023-08-11

Impact of unbalanced minor route versus major route karyotypes at diagnosis on prognosis of CML - Fabarius, Alice; Kalmanti, Lida; Dietz, Christian T.; Lauseker, Michael; Rinaldetti, Sebastien; Haferlach, Claudia; Goehring, Gudrun; Schlegelberger, Brigitte; Jotterand, Martine; Hanfstein, Benjamin; Seifarth, Wolfgang; Haenel, Mathias; et al. (Annals of Hematology, 2015)
Major route additional cytogenetic aberrations (ACA) at diagnosis of chronic myeloid leukaemia (CML) indicate an increased risk of progression and shorter survival. Since major route ACA are almost always unbalanced, it is unclear whether other unbalanced ACA at diagnosis also confer an unfavourable prognosis. On the basis of 1348 Philadelphia chromosome-positive chronic phase patients of the randomized CML study IV, we examined the impact of unbalanced minor route ACA at diagnosis versus major route ACA on prognosis. At diagnosis, 1175 patients (87.2 %) had a translocation t(9;22)(q34;q11) and 74 (5.5 %) a variant translocation t(v;22) only, while a loss of the Y chromosome (-Y) was present in addition in 44 (3.3 %), balanced or unbalanced minor route ACA each in 17 (1.3 %) and major route ACA in 21 (1.6 %) cases. Patients with unbalanced minor route ACA had no significantly different cumulative incidences of complete cytogenetic remission or major molecular remission and no significantly different progression-free survival (PFS) or overall survival (OS) than patients with t(9;22), t(v;22), -Y and balanced minor route karyotypes. In contrast, patients with major route ACA had a shorter OS and PFS than all other groups (all pairwise comparisons to each of the other groups: p <= 0.015). Five-year survival probabilities were for t(9;22) 91.4 % (95 % CI 89.5-93.1), t(v; 22) 87 % (77.2-94.3), -Y 89.0 % (76.7-97.0), balanced 100 %, unbalanced minor route 92.3 % (72.4-100) and major route 52.2 % (28.2-75.5). We conclude that only major route, but not balanced or unbalanced minor route ACA at diagnosis, has a negative impact on prognosis of CML.
EVALuna2:25723

Impaired Transmigration of Myeloid-Derived Suppressor Cells across Human Sinusoidal Endothelium Is Associated with Decreased Expression of CD13 - Resheq, Yazid J.; Menzner, Ann-Katrin; Bosch, Jacobus; Tickle, Joseph; Li, Ka-Kit; Wilhelm, Annika; Hepburn, Elizabeth; Murihead, Gillian; Ward, Stephen T.; Curbishley, Stuart M.; Zimmermann, Henning W.; Bruns, Tony; et al. (Journal of Immunology, 2017)
Human monocytic myeloid-derived suppressor cells (MO-MDSCs) within the hepatic compartment suppress inflammation and impair immune surveillance in liver cancer. It is currently not known whether recruitment of MO-MDSCs from blood via hepatic sinusoidal endothelium (HSEC) contributes to their enrichment within the hepatic compartment. We compared the transmigratory potential of MO-MDSCs and monocytes after adhesion to hepatic endothelial monolayers in flow-based assays that mimic in vivo shear stress in the sinusoids. Despite comparable binding to HSEC monolayers, proportionally fewer MO-MDSCs underwent transendothelial migration, indicating that the final steps of extravasation, where actin polymerization plays an important role, are impaired in MO-MDSCs. In this article, we found reduced levels of CD13 on MO-MDSCs, which has recently been reported to control cell motility in monocytes, alongside reduced VLA-4 expression, an integrin predominantly involved in adherence to the apical side of the endothelium. CD13 and VLA-4 blocking and activating Abs were used in flow-based adhesion assays, live-cell imaging of motility, and actin polymerization studies to confirm a role for CD13 in impaired MO-MDSC transmigration. These findings indicate that CD13 significantly contributes to tissue infiltration by MO-MDSCs and monocytes, thereby contributing to the pathogenesis of hepatic inflammation.
EVALuna2:25713

Implementation and Feasibility of Electronic Patient-Reported Outcome (ePRO) Data Entry in the PRAEGNANT Real-Time Advanced and Metastatic Breast Cancer Registry - Wallwiener, Markus; Heindl, Felix; Brucker, Sara Y.; Taran, Florin-Andrei; Hartkopf, Andreas; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; Lux, Michael P.; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Patient-reported outcomes (PROs) have been incorporated into clinical trials for many symptoms and medical conditions. A transition from paper-based capture of PROs to electronic PROs (ePROs) has recently started. This study reports on the feasibility of ePRO assessment in a prospective registry including molecular data for patients with advanced breast cancer.As part of the PRAEGNANT network, patients were invited by clinical trial staff, physicians, and nurses to complete three standardized Internet-based questionnaires (EQ 5D 5 L, CES-D and IPAQ). Feasibility was assessed by the staff members who assigned the user accounts by the patients. The completeness of the questionnaires was also assessed.Fifteen of 17 patients who were asked agreed to participate to complete the PRO questionnaires (EQ-5D-5L and CES-D). However, the IPAQ (physical activity) questionnaire was only validly completed by 9 patients. Feasibility was ranked better by the physicians and dedicated clinical trial staff than by the nursing staff.Incorporating ePRO questionnaires into an advanced breast cancer registry is feasible, and no major hurdles were reported. Involving stakeholders from the start, the application is tailored to the capacities and abilities of both patients and clinical staff. The patients' compliance was better with some questionnaires, but others may present difficulties.
EVALuna2:176

Improved Pseudomonas exotoxin and Mertansine-based Duotoxins for the treatment of hematologic malignancies - Ammon, Anna-Maria; George, Rebekka; Mellenthin, Lisa; Mackensen, Andreas; Mueller, F. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Incidence and predictors of difficult laryngoscopy in 11,219 pediatric anesthesia procedures - Heinrich, Stefan; Birkholz, Torsten; Ihmsen, Harald; Irouschek, Andrea; Ackermann, Andreas; Schmidt, Joachim (Pediatric Anesthesia, 2012)
Difficult laryngoscopy in pediatric patients undergoing anesthesia.This retrospective analysis was conducted to investigate incidence and predictors of difficult laryngoscopy in a large cohort of pediatric patients receiving general anesthesia with endotracheal intubation.Young age and craniofacial dysmorphy are predictors for the difficult pediatric airway and difficult laryngoscopy. For difficult laryngoscopy, other general predictors are not yet described.Retrospectively, from a 5-year period, data from 11.219 general anesthesia procedures in pediatric patients with endotracheal intubation using age-adapted Macintosh blades in a single center (university hospital) were analyzed statistically.The overall incidence of difficult laryngoscopy [Cormack and Lehane (CML) grade III and IV] was 1.35%. In patients younger than 1 year, the incidence of CML III or IV was significantly higher than in the older patients (4.7% vs 0.7%). ASA Physical Status III and IV, a higher Mallampati Score (III and IV) and a low BMI were all associated (P < 0.05) with difficult laryngoscopy. Patients undergoing oromaxillofacial surgery and cardiac surgery showed a significantly higher rate of CML III/IV findings.The general incidence of difficult laryngoscopy in pediatric anesthesia is lower than in adults. Our results show that the risk of difficult laryngoscopy is much higher in patients below 1 year of age, in underweight patients and in ASA III and IV patients. The underlying disease might also contribute to the risk. If the Mallampati score could be obtained, prediction of difficult laryngoscopy seems to be reliable. Our data support the existing recommendations for a specialized anesthesiological team to provide safe anesthesia for infants and neonates.
EVALuna2:16625

Incidence, clinical presentation, risk factors, outcomes, and biomarkers in de novo late acute GVHD - Akahoshi, Yu; Spyrou, Nikolaos; Hogan, William J.; Ayuk, Francis; DeFilipp, Zachariah; Weber, Daniela; Choe, Hannah K.; Hexner, Elizabeth O.; Rösler, Wolf; Etra, Aaron M.; Sandhu, Karamjeet; Yanik, Gregory A.; et al. (Blood Advances, 2023)
Late acute graft-versus-host disease (GVHD) is defined as de novo acute GVHD presenting beyond 100 days after allogeneic hematopoietic cell transplantation (HCT) without manifestations of chronic GVHD. Data are limited regarding its characteristics, clinical course, and risk factors because of underrecognition and changes in classification. We evaluated 3542 consecutive adult recipients of first HCTs at 24 Mount Sinai Acute GVHD International Consortium (MAGIC) centers between January 2014 and August 2021 to better describe the clinical evolution and outcomes of late acute GVHD. The cumulative incidence of classic acute GVHD that required systemic treatment was 35.2%, and an additional 5.7% of patients required treatment for late acute GVHD. At the onset of symptoms, late acute GVHD was more severe than classic acute GVHD based on both clinical and MAGIC algorithm probability biomarker parameters and showed a lower overall response rate on day 28. Both clinical and biomarker grading at the time of treatment stratified the risk of nonrelapse mortality (NRM) in patients with classic and late acute GVHD, respectively, but long-term NRM and overall survival did not differ between patients with classic and late acute GVHD. Advanced age, female-to-male sex mismatch, and the use of reduced intensity conditioning were associated with the development of late acute GVHD, whereas the use of posttransplant cyclophosphamide–based GVHD prevention was protective mainly because of shifts in GVHD timing. Because overall outcomes were comparable, our findings, although not definitive, suggest that similar treatment strategies, including eligibility for clinical trials, based solely on clinical presentation at onset are appropriate.
CRIS-Team Scopus Importer:2023-09-15

Increased CD47 expression inhibits phagocytosis of alloreactive donor T cells after allo-HSCT - Flamann, Cindy; Matos, C.; Kreutz, M.; Shaikh, H.; Beilhack, A.; Büttner-Herold, Maike; Lischer, Christopher; Völkl, Simon; Kellner, C.; Zeun, J.; Kremer, Andreas; Bitterer, Katrin; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Increased incidence of chronic GvHD and CMV disease in patients with vitamin D deficiency before allogeneic stem cell transplantation - Von Bahr, L.; Blennow, O.; Alm, J.; Bjorklund, A.; Malmberg, K-J; Mougiakakos, Dimitrios; Le Blanc, A.; Oefner, P. J.; Labopin, M.; Ljungman, Per; Le Blanc, K. (Bone Marrow Transplantation, 2015)
Vitamin D has emerged as a central player in the immune system, with its deficiency being implicated in the pathogenesis of several autoimmune diseases, including chronic GvHD. This is a retrospective cohort analysis of 166 patients, who underwent allogeneic hematopoietic stem cell transplantation (HSCT) at the Karolinska University Hospital, evaluating GvHD, graft failure, infectious complications and survival after HSCT in relation to pre-transplantation vitamin D levels. Most of the patients were deficient in vitamin D before HSCT (median 42 nmol/L). In multivariate analysis, vitamin D level before HSCT was identified as a significant independent risk factor for development of cGvHD. The increased incidence of cGvHD was not coupled to better disease-free survival; instead there was a trend towards lower overall survival in the vitamin D-deficient patients. In addition, we found a significant correlation between vitamin D deficiency and incidence of CMV disease, with no case of CMV disease occurring in patients with sufficient levels of vitamin D before HSCT. Our results support a role of vitamin D in immune tolerance following HSCT. These findings could be highly relevant for the care of HSCT patients, and prospective, randomized studies on the effect of vitamin D supplementation are therefore needed.
EVALuna2:25716

Increased Levels of sCD30 Have No Impact on the Incidence of Early ABMR and Long-Term Outcome in Intermediate-Risk Renal Transplant Patients With Preformed DSA - Drasch, Thomas; Bach, Christian; Luber, Markus; Spriewald, Bernd; Utpatel, Kirsten; Büttner-Herold, Maike; Banas, Bernhard; Zecher, Daniel (Frontiers in Medicine, 2021)
Background: It is still incompletely understood why some patients with preformed donor-specific anti-HLA antibodies (DSA) have reduced kidney allograft survival secondary to antibody-mediated rejection (ABMR), whereas many DSA-positive patients have favorable long-term outcomes. Elevated levels of soluble CD30 (sCD30) have emerged as a promising biomarker indicating deleterious T-cell help in conjunction with DSA in immunologically high-risk patients. We hypothesized that this would also be true in intermediate-risk patients. Methods: We retrospectively analyzed pre-transplant sera from 287 CDC-crossmatch negative patients treated with basiliximab induction and tacrolimus-based maintenance therapy for the presence of DSA and sCD30. The incidence of ABMR according to the Banff 2019 classification and death-censored allograft survival were determined. Results: During a median follow-up of 7.4 years, allograft survival was significantly lower in DSA-positive as compared to DSA-negative patients (p < 0.001). In DSA-positive patients, most pronounced in those with strong DSA (MFI > 5,000), increased levels of sCD30 were associated with accelerated graft loss compared to patients with low sCD30 (3-year allograft survival 75 vs. 95%). Long-term survival, however, was comparable in DSA-positive patients irrespective of sCD30 status. Likewise, the incidence of early ABMR and lesion score characteristics were comparable between sCD30-positive and sCD30-negative patients with DSA. Finally, increased sCD30 levels were not predictive for early persistence of DSA. Conclusion: Preformed DSA are associated with an increased risk for ABMR and long-term graft loss independent of sCD30 levels in intermediate-risk kidney transplant patients.
CRIS-Team Scopus Importer:2021-12-03
Keywords: ABMR; antibody-mediated rejection; donor-specific anti HLA antibodies; kidney transplantation; risk stratification; sCD30

Increased Neutrophil-to-Lymphocyte Ratio is Associated with Unfavorable Functional Outcome in Acute Ischemic Stroke - Giede-Jeppe, Antje; Madzar, Dominik; Sembill, Jochen; Sprügel, Maximilian; Atay, Selim; Lücking, Hannes; Huttner, Hagen; Bobinger, Tobias; Hölter, Philip (Neurocritical Care, 2019)
Background Inflammatory response is the hallmark of secondary brain injury in stroke patients. Neutrophil-to-lymphocyte ratio (NLR) emerged as a marker for functional outcome in several diseases. Objectives To investigate the association between NLR on admission and during hospital stay and functional outcome in acute ischemic stroke (AIS). Methods This observational study included all consecutive AIS patients admitted at a German stroke center covering 2011-2013. Patient characteristics and clinical data were retrieved from institutional databases. Multivariate analysis was conducted to investigate parameters associated with functional outcome. Receiver operating characteristic (ROC) analysis was performed to identify the best cutoff for NLR to discriminate between favorable and unfavorable functional outcome. To account for imbalances in baseline characteristics, propensity score matching was carried out to assess the influence of NLR on functional outcome. Results A total of 807 patients with AIS were included for analysis. Patients with worse functional outcome at 3 months were older and had worse clinical status on admission, higher rates of infectious complications, and an increased NLR. ROC analysis identified a NLR of 3.3 as best cutoff value to discriminate between favorable and unfavorable functional outcomes (area under the curve 0.693, p < 0.001, Youden's index = 0.318; p < 0.001; sensitivity 68.5%, specificity 63.9%). Propensity-matched analysis still demonstrated a higher rate of unfavorable functional outcome at 3 months in patients with NLR >= 3.3 [modified Rankin scale 3-6 at 3 months: NLR >= 3.3 51.5% vs. NLR < 3.3 36.4%; p = 0.002]. Conclusions In AIS patients we identified NLR as an important predictor for unfavorable functional outcome.
CRIS-Team WoS Importer:2019-10-25

Increased PD-1 Expression on Circulating T Cells Correlates with Inferior Outcome after Autologous Stem Cell Transplantation - Richter, Silja; Böttcher, Martin; Stoll, Andrej; Zeremski, Vanja; Völkl, Simon; Mackensen, Andreas; Ekici, Arif Bülent; Jacobs, Benedikt; Mougiakakos, Dimitrios (Transplantation and Cellular Therapy, 2024)
High-dose chemotherapy followed by autologous stem cell transplantation (auto-SCT) is a well-established treatment option for multiple myeloma and malignant lymphoma patients. It is able to induce long-term progression-free survival (PFS) in both patient groups and even provide a cure in patients with aggressive lymphoma. However, relapse is common and has been associated with the pace and quality of immunologic reconstitution after transplantation, as well as with immune cell exhaustion and immunometabolic defects. We aimed to analyze the dynamics of the prototypical exhaustion marker PD-1 on immune cells during reconstitution on high-dose chemotherapy followed by auto-SCT and its impact on PFS. We performed a comprehensive analysis of exhaustion and metabolic markers on immune cells from myeloma and lymphoma patients undergoing auto-SCT using flow cytometry and NanoString technologies. The expression levels of PD-1 were increased during early reconstitution after transplantation on T cells and natural killer (NK) cells, as well as on monocytes. However, while PD-1 expression in NK cells and monocytes normalized over time, PD-1 expression on T cells demonstrated a variable course. Of note, lymphoma patients with continuously increasing PD-1 expression on T cells after auto-SCT had an inferior median PFS of only 146 days, whereas the median PFS was not reached in the lymphoma patients without such a PD-1 expression pattern. T cells from patients with increased PD-1 expression after auto-SCT exhibited an immunometabolic (over)activation and exhausted phenotype compared to T cells from patients with a low PD-1 expression after transplantation, including higher levels of the glycolytic pacemaker enzyme hexokinase 2 and the inhibitory receptor CTLA-4. In addition, proliferating Ki-67+ T cells were more abundant in patients with high PD-1 expression on T cells compared to those with low expression after auto-SCT (11.9% versus 4.2%). PD-1 expression on T cells might serve as an adverse biomarker for lymphoma patients undergoing auto-SCT; however, further validation by larger prospective studies is required.
CRIS-Team Scopus Importer:2024-04-12
Keywords: auto-SCT; exhaustion; PD-1; T cells

Increased Rate of Poor Laryngoscopic Views in Patients Scheduled for Cardiac Surgery Versus Patients Scheduled for General Surgery: A Propensity Score-Based Analysis of 21,561 Cases - Heinrich, Stefan; Ackermann, Andreas; Prottengeier, Johannes; Castellanos, Ixchel; Schmidt, Joachim; Schüttler, Jürgen (Journal of Cardiothoracic and Vascular Anesthesia, 2015)
Former analyses reported an increased rate of poor direct laryngoscopy view in cardiac surgery patients; however, these findings frequently could be attributed to confounding patient characteristics. In most of the reported cardiac surgery cohorts, the rate of well-known risk factors for poor direct laryngoscopy view such as male sex, obesity, or older age, were increased compared with the control groups. Especially in the ongoing debate on anesthesia staff qualification for cardiac interventions outside the operating room a detailed and stratified risk analysis seems necessary.Retrospective, anonymous, propensity score-based, matched-pair analysis.Single-center study in a university hospital.No active participants. Retrospective, anonymous chart analysis.The anesthesia records of patients undergoing cardiac surgery in a period of 6 consecutive years were analyzed retrospectively. The results were compared with those of a control group of patients who underwent general surgery. Poor laryngoscopic view was defined as Cormack and Lehane classification grade 3 or 4.The records of 21,561 general anesthesia procedures were reviewed for the study. The incidence of poor direct laryngoscopic views in patients scheduled for cardiac surgery was significantly increased compared with those of the general surgery cohort (7% v 4.2%). Using propensity score-based matched-pair analysis, equal subgroups were generated of each surgical department, with 2,946 patients showing identical demographic characteristics. After stratifying for demographic characteristics, the rate of poor direct laryngoscopy view remained statistically significantly higher in the cardiac surgery group (7.5% v 5.7%).Even with stratification for demographic risk factors, cardiac surgery patients showed a significantly higher rate of poor direct laryngoscopic view compared with general surgery patients. These results should be taken into account for human resource management and distribution of difficult airway equipment, especially when cardiac interventional programs are implemented in remote hospital locations.
EVALuna2:16681

Indirect determination of hematology reference intervals in adult patients on Beckman Coulter UniCell DxH 800 and Abbott CELL-DYN Sapphire devices - Zierk, Jakob; Arzideh, Farhad; Haeckel, Rainer; Rauh, Manfred; Metzler, Markus; Ganslandt, Thomas; Krause, Stefan (Clinical Chemistry and Laboratory Medicine, 2018)
Background Conventional establishment of reference intervals for hematological analytes is challenging due to the need to recruit healthy persons. Indirect methods address this by deriving reference intervals from clinical laboratory databases which contain large datasets of both physiological and pathological test results. Methods We used the "Reference Limit Estimator" (RLE) to establish reference intervals for common hematology analytes in adults aged 18-60 years. One hundred and ninety-five samples from 44,519 patients, measured on two different devices in a tertiary care center were analyzed. We examined the influence of patient cohorts with an increasing proportion of abnormal test results, compared sample selection strategies, explored inter-device differences, and analyzed the stability of reference intervals in simulated datasets with varying overlap of pathological and physiological test results. Results Reference intervals for hemoglobin, hematocrit, red cell count and platelet count remained stable, even if large numbers of pathological samples were included. Reference intervals for red cell indices, red cell distribution width and leukocyte count were sufficiently stable, if patient cohorts with the highest fraction of pathological samples were excluded. In simulated datasets, estimated reference limits shifted, if the pathological dataset contributed more than 15%-20% of total samples and approximated the physiological distribution. Advanced sample selection techniques did not improve the algorithm's performance. Inter-device differences were small except for red cell distribution width. Conclusions The RLE is well-suited to create reference intervals from clinical laboratory databases even in the challenging setting of a adult tertiary care center. The procedure can be used as a complement for reference interval determination where conventional approaches are limited.
EVALuna2:34837

Inferior Outcomes of EU Versus US Patients Treated with CD19 CAR-T for Relapsed/Refractory Large B-cell Lymphoma: Association with Differences in Tumor Burden, Systemic Inflammation, Bridging Therapy Utilization, and CAR-T Product Use - Bücklein, Veit; Perez, Ariel; Rejeski, Kai; Iacoboni, Gloria; Jurinovic, Vindi; Holtick, Udo; Penack, Olaf; Kharboutli, Soraya; Blumenberg, Viktoria; Ackermann, Josephine; Frölich, Lisa; Johnson, Grace; et al. (HemaSphere, 2023)
Real-world evidence suggests a trend toward inferior survival of patients receiving CD19 chimeric antigen receptor (CAR) T-cell therapy in Europe (EU) and with tisagenlecleucel. The underlying logistic, patient-and disease-related reasons for these discrepancies remain poorly understood. In this multicenter retrospective observational study, we studied the patient-individual journey from CAR-T indication to infusion, baseline features, and survival outcomes in 374 patients treated with tisagenlecleucel (tisa-cel) or axicabtagene-ciloleucel (axi-cel) in EU and the United States (US). Compared with US patients, EU patients had prolonged indication-To-infusion intervals (66 versus 50 d; P < 0.001) and more commonly received intermediary therapies (holding and/or bridging therapy, 94% in EU versus 74% in US; P < 0.001). Baseline lactate dehydrogenase (LDH) (median 321 versus 271 U/L; P = 0.02) and ferritin levels (675 versus 425 ng/mL; P = 0.004) were significantly elevated in the EU cohort. Overall, we observed inferior survival in EU patients (median progression-free survival [PFS] 3.1 versus 9.2 months in US; P < 0.001) and with tisa-cel (3.2 versus 9.2 months with axi-cel; P < 0.001). On multivariate Lasso modeling, nonresponse to bridging, elevated ferritin, and increased C-reactive protein represented independent risks for treatment failure. Weighing these variables into a patient-individual risk balancer (high risk [HR] balancer), we found higher levels in EU versus US and tisa-cel versus axi-cel cohorts. Notably, superior PFS with axi-cel was exclusively evident in patients at low risk for progression (according to the HR balancer), but not in high-risk patients. These data demonstrate that inferior survival outcomes in EU patients are associated with longer time-To-infusion intervals, higher tumor burden/LDH levels, increased systemic inflammatory markers, and CAR-T product use.
CRIS-Team Scopus Importer:2023-07-28

Inferior Outcomes of EU Vs. US Patients with Relapsed/Refractory Large B-Cell Lymphoma after CD19 CAR T-Cell Therapy Are Associated with Differences in Tumor Burden, Systemic Inflammation, Bridging Therapy Utilization and CAR-T Product Selection - Buecklein, Veit L.; Perez-Perez, Ariel; Rejeski, Kai; Iacoboni, Gloria; Jurinovic, Vindi; Holtick, Udo; Penack, Olaf; Kharboutli, Soraya; Blumenberg, Viktoria; Ackermann, Josephine; Froelich, Lisa; Johnson, Grace; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Inflammation-induced glycolytic switch controls suppressivity of mesenchymal stem cells via STAT1 glycosylation - Jitschin, R.; Böttcher, Martin; Saul, D.; Lukassen, Sören; Bruns, Heiko; Loschinski, Romy; Ekici, Arif Bülent; Reis, André; Mackensen, Andreas; Mougiakakos, Dimitrios (Leukemia, 2019)
Mesenchymal stem cells (MSCs) represent key contributors to tissue homeostasis and promising therapeutics for hyperinflammatory conditions including graft-versus-host disease. Their immunomodulatory effects are controlled by microenvironmental signals. The MSCs' functional response towards inflammatory cues is known as MSC-"licensing" and includes indoleamine 2,3-dioxygenase (IDO) upregulation. MSCs use tryptophan-depleting IDO to suppress T-cells. Increasing evidence suggests that several functions are (co-)determined by the cells' metabolic commitment. MSCs are capable of both, high levels of glycolysis and of oxidative phosphorylation. Although several studies have addressed alterations of the immune regulatory phenotype elicited by inflammatory priming metabolic mechanisms controlling this process remain unknown. We demonstrate that inflammatory MSC-licensing causes metabolic shifts including enhanced glycolysis and increased fatty acid oxidation. Yet, only interfering with glycolysis impacts IDO upregulation and impedes T-cell-suppressivity. We identified the Janus kinase (JAK)/signal transducer and activator of transcription (STAT)1 pathway as a regulator of both glycolysis and IDO, and show that enhanced glucose turnover is linked to abundant STAT1 glycosylation. Inhibiting the responsible O-acetylglucosamine (O-GlcNAc) transferase abolishes STAT1 activity together with IDO upregulation. Our data suggest that STAT1-O-GlcNAcylation increases its stability towards degradation thus sustaining downstream effects. This pathway could represent a target for interventions aiming to enhance the MSCs' immunoregulatory potency.
EVALuna2:35805

Influence of DM-sensitivity on immunogenicity of MHC class II restricted antigens - Bernhardt, Anna Luise; Zeun, Julia; Marecek, Miriam; Reimann, Hannah; Kretschmann, Sascha; Bausenwein, Judith; van der Meijden, Edith; Karg, Margarete; Haug, Tabea; Meintker, Lisa; Lutzny-Geier, Gloria; Mackensen, Andreas; et al. (Journal for ImmunoTherapy of Cancer, 2021)
Background Graft-versus-host-disease (GvHD) is a major problem in allogeneic stem cell transplantation. We previously described two types of endogenous human leukocyte antigen (HLA)-II restricted antigens depending on their behavior towards HLA-DM. While DM-resistant antigens are presented in the presence of HLA-DM, DM-sensitive antigens rely on the expression of HLA-DO-the natural inhibitor of HLA-DM. Since expression of HLA-DO is not upregulated by inflammatory cytokines, DM-sensitive antigens cannot be presented on non-hematopoietic tissues even under inflammatory conditions. Therefore, usage of CD4+ T cells directed against DM-sensitive antigens might allow induction of graft-versus-leukemia effect without GvHD. As DM-sensitivity is likely linked to low affinity peptides, it remains elusive whether DM-sensitive antigens are inferior in their immunogenicity. Methods We created an in vivo system using a DM-sensitive and a DM-resistant variant of the same antigen. First, we generated murine cell lines overexpressing either H2-M or H2-O (murine HLA-DM and HLA-DO) to assign the two model antigens ovalbumin (OVA) and DBY to their category. Further, we introduced mutations within the two T-cell epitopes and tested the effect on DM-sensitivity or DM-resistance. Furthermore, we vaccinated C57BL/6 mice with either variant of the epitope and measured expansion and reactivity of OVA-specific and DBY-specific CD4+ T cells. Results By testing T-cell recognition of OVA and DBY on a murine B-cell line overexpressing H2-M and H2-O, respectively, we showed that OVA leads to a stronger T-cell activation in the presence of H2-O demonstrating its DM-sensitivity. In contrast, the DBY epitope does not rely on H2-O for T-cell activation indicating DM-resistance. By introducing mutations within the T-cell epitopes we could generate one further DM-sensitive variant of OVA and two DM-resistant counterparts. Likewise, we designed DM-resistant and DM-sensitive variants of DBY. On vaccination of C57BL/6 mice with either epitope variant we measured comparable expansion and reactivity of OVA-specific and DBY-specific T-cells both in vivo and ex vivo. By generating T-cell lines and clones of healthy human donors we showed that DM-sensitive antigens are targeted by the natural T-cell repertoire. Conclusion We successfully generated DM-sensitive and DM-resistant variants for two model antigens. Thereby, we demonstrated that DM-sensitive antigens are not inferior to their DM-resistant counterpart and are therefore interesting tools for immunotherapy after allogeneic stem cell transplantation.
CRIS-Team Scopus Importer:2021-07-30
Keywords: adoptive; antigen presentation; antigens; CD4-positive T-lymphocytes; immunotherapy

Influence of Swiprosin2/EFhd1 on the metabolic control of B cell differentiation and humoral immunity - Urbanczyk, Sophia; Stein, Marcello F.; Duetting, S.; Mougiakakos, Dimitrios; Boesl, M.; Reimer, Dorothea; Steinmetz, Tobit; Schuh, Wolfgang; Bozec, Aline; Winkler, Thomas; Jäck, Hans-Martin; Mielenz, Dirk (2017)
EVALuna2:13653

Inhibition of TNF-alpha reduces transplant arteriosclerosis in a murine aortic transplant model. - Wollin, Martina; Abele, Silke; Bruns, Heiko; Weyand, Michael; Kalden, Joachim; Ensminger, Stephan M.; Spriewald, Bernd M. (Transplant International, 2009)
Experimental and clinical data provide evidence that TNF-alpha contributes to acute and chronic allograft rejection. In this study, we explored the effect of TNF-alpha blockade using the chimeric monoclonal antibody infliximab on the development of transplant arterisoclerosis in a fully mismatched aortic allograft model. Post-transplant treatment of CBA (H2(k)) recipients with 250 mug infliximab (cumulative dose 1.25 mg) reduced luminal occlusion of C57Bl/6 (H2(b)) aortic grafts on day 30 from 77 +/- 5% in untreated controls to 52 +/- 6%. Increasing the dose of anti-TNF-alpha antibody had no further beneficial effect. Treatment with human control immunoglobulin had no effect on intima proliferation. Under TNF-alpha blockade, ICAM-1 and PDGF mRNA expression within the grafts was strongly reduced, whereas iNOS expression was enhanced. The data show that TNF-alpha blockade using infliximab can reduce the development of transplant arteriosclerosis in fully mismatched murine aortic grafts.

In mammalian skeletal muscle, phosphorylation of TOMM22 by protein kinase CSNK2/CK2 controls mitophagy - Kravic, Bojana; Harbauer, Angelika B.; Romanello, Vanina; Simeone, Luca; Vögtle, F. Nora; Kaiser, Tobias; Straubinger, Marion; Huraskin, Danyil; Böttcher, Martin; Cerqua, Cristina; Martin, Eva Denise; Poveda-Huertes, Daniel; et al. (Autophagy, 2017)
In yeast, Tom22 the central component of the TOMM (translocase of outer mitochondrial membrane) receptor complex is responsible for the recognition and translocation of synthesized mitochondrial precursor proteins, and its protein kinase CK2-dependent phosphorylation is mandatory for TOMM complex biogenesis and proper mitochondrial protein import. In mammals, the biological function of protein kinase CSNK2/CK2 remains vastly elusive and it is unknown whether CSNK2-dependent phosphorylation of TOMM protein subunits has a similar role as that in yeast. To address this issue, we used a skeletal muscle-specific Csnk2b/Ck2?-conditional knockout (cKO) mouse model. Phenotypically, these skeletal muscle Csnk2b cKO mice showed reduced muscle strength and abnormal metabolic activity of mainly oxidative muscle fibers, which point towards mitochondrial dysfunction. Enzymatically, active muscle lysates from skeletal muscle Csnk2b cKO mice phosphorylate murine TOMM22, the mammalian ortholog of yeast Tom22, to a lower extent than lysates prepared from controls. Mechanistically, CSNK2-mediated phosphorylation of TOMM22 changes its binding affinity for mitochondrial precursor proteins. However, in contrast to yeast, mitochondrial protein import seems not to be affected in vitro using mitochondria isolated from muscles of skeletal muscle Csnk2b cKO mice. PINK1, a mitochondrial health sensor that undergoes constitutive import under physiological conditions, accumulates within skeletal muscle Csnk2b cKO fibers and labels abnormal mitochondria for removal by mitophagy as demonstrated by the appearance of mitochondria-containing autophagosomes through electron microscopy. Mitophagy can be normalized by either introduction of a phosphomimetic TOMM22 mutant in cultured myotubes, or by in vivo electroporation of phosphomimetic Tomm22 into muscles of mice. Importantly, transfection of the phosphomimetic Tomm22 mutant in muscle cells with ablated Csnk2b restored their oxygen consumption rate comparable to wild-type levels. In sum, our data show that mammalian CSNK2-dependent phosphorylation of TOMM22 is a critical switch for mitophagy and reveal CSNK2-dependent physiological implications on metabolism, muscle integrity and behavior.
EVALuna2:25775

Innate extracellular vesicles from melanoma patients suppress beta-catenin in tumor cells by miRNA-34a - Lee, Jung-Hyun; Dindorf, Jochen; Eberhardt, Martin; Lai, Xin; Ostalecki, Christian; Koliha, Nina; Gross, Stefani; Blume, Katja; Bruns, Heiko; Wild, Stefan; Schuler, Gerold; Vera, Julio; et al. (Life Science Alliance, 2019)
Upon tumor development, new extracellular vesicles appear in circulation. Our knowledge of their relative abundance, function, and overall impact on cancer development is still preliminary. Here, we demonstrate that plasma extracellular vesicles (pEVs) of non-tumor origin are persistently increased in untreated and post-excision melanoma patients, exhibiting strong suppressive effects on the proliferation of tumor cells. Plasma vesicle numbers, miRNAs, and protein levels were elevated two-to tenfold and detected many years after tumor resection. The vesicles revealed individual and clinical stage-specific miRNA profiles as well as active ADAM10. However, whereas pEV from patients preventing tumor relapse down-regulated beta-catenin and blocked tumor cell proliferation in an miR-34a-dependent manner, pEV from metastatic patients lost this ability and stimulated beta-catenin-mediated transcription. Cancer-induced pEV may constitute an innate immune mechanismsuppressing tumor cell activity including that of residual cancer cells present after primary surgery.
CRIS-Team WoS Importer:2019-05-17

Innovative cellular therapies for autoimmune diseases: expert-based position statement and clinical practice recommendations from the EBMT practice harmonization and guidelines committee. - Greco, Raffaella; Alexander, Tobias; Del Papa, Nicoletta; Müller, Fabian; Saccardi, Riccardo; Sanchez-Guijo, Fermin; Schett, Georg; Sharrack, Basil; Snowden, John A.; Tarte, Karin; Onida, Francesco; Sánchez-Ortega, Isabel; et al. (EClinicalMedicine, 2024)
Autoimmune diseases (ADs) are characterized by loss of immune tolerance, high chronicity, with substantial morbidity and mortality, despite conventional immunosuppression (IS) or targeted disease modifying therapies (DMTs), which usually require repeated administration. Recently, novel cellular therapies (CT), including mesenchymal stromal cells (MSC), Chimeric Antigen Receptors T cells (CART) and regulatory T cells (Tregs), have been successfully adopted in ADs. An international expert panel of the European Society for Blood and Marrow Transplantation and the International Society for the Cell and Gene Therapy, reviewed all available evidence, based on the current literature and expert practices, on use of MSC, CART and Tregs, in AD patients with rheumatological, neurological, and gastroenterological indications. Expert-based consensus and recommendations for best practice and quality of patient care were developed to support clinicians, scientists, and their multidisciplinary teams, as well as patients and care providers and will be regularly updated.
EVALuna2:554515

Inotuzumab Ozogamicin as Induction Therapy for Patients Older Than 55 Years With Philadelphia Chromosome-Negative B-Precursor ALL - Stelljes, Matthias; Raffel, Simon; Alakel, Nael; Wäsch, Ralph; Kondakci, Mustafa; Scholl, Sebastian; Rank, Andreas; Hänel, Mathias; Spriewald, Bernd; Hanoun, Maher; Martin, Sonja; Schwab, Katjana; et al. (Journal of Clinical Oncology, 2024)
PURPOSE: Despite recent advances in adapting the intensity of treatment for older patients with ALL, current protocols are associated with high rates of early deaths, treatment-related toxicity, and dismal prognosis. We evaluated inotuzumab ozogamicin and dexamethasone (Dex) as induction therapy in older patients with ALL within the German Multicenter Study Group for Adult ALL (GMALL). PATIENTS AND METHODS: The open-label, multicenter, phase II, INITIAL-1 trial enrolled 45 patients older than 55 years with newly diagnosed, CD22-positive, BCR::ABL-negative B-precursor ALL (B-ALL). Patients received up to three cycles of inotuzumab ozogamicin/Dex and up to six cycles of age-adapted GMALL consolidation and maintenance therapy. RESULTS: Forty-three evaluable patients with common/pre-B (n = 38) and pro-B ALL (n = 5), with a median age of 64 years (range, 56-80), received at least two cycles of inotuzumab ozogamicin induction therapy. All patients achieved complete remission (CR/CR with incomplete hematologic recovery). Twenty-three (53%) and 30 (71%) patients had no evidence of molecularly assessed measurable residual disease (minimum 10e-4 threshold) after the second and third inductions, respectively. After a median follow-up of 2.7 years, event-free survival at one (primary end point) and 3 years was 88% (95% CI, 79 to 98) and 55% (95% CI, 40 to 71), while overall survival (OS) was 91% (95% CI, 82 to 99) and 73% (95% CI, 59 to 87), respectively. None of the patients died during 6 months after the start of induction. Most common adverse events having common toxicity criteria grade ≥3 during induction were leukocytopenia, neutropenia, thrombocytopenia, anemia, and elevated liver enzymes. One patient developed nonfatal veno-occlusive disease after induction II. CONCLUSION: Inotuzumab ozogamicin-based induction followed by age-adapted chemotherapy was well tolerated and resulted in high rates of remission and OS. These data provide a rationale for integrating inotuzumab ozogamicin into first-line regimens for older patients with B-ALL.
CRIS-Team Scopus Importer:2024-02-02

In Patients with Relapsed/Refractory AML Sequential Conditioning and Immediate Allogeneic Stem Cell Transplantation (allo-HCT) Results in Similar Overall and Leukemia-Free Survival Compared to Intensive Remission Induction Chemotherapy Followed By Allo-HCT: Results from the Randomized Phase III ASAP Trial - Stelljes, Matthias; Middeke, Jan Moritz; Bug, Gesine; Wagner, Eva-Maria; Mueller, Lutz Peter; Christoph, Schmid; Krause, Stefan; Bethge, Wolfgang; Jost, Edgar; Platzbecker, Uwe; Klein, Stefan; Schubert, Jorg; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Intensified cytarabine dose during consolidation in adult AML patients under 65 years is not associated with survival benefit: real-world data from the German SAL-AML registry - Hanoun, Maher; Ruhnke, Leo; Kramer, Michael; Hanoun, Christine; Schaefer-Eckart, Kerstin; Steffen, Bjoern; Sauer, Tim; Krause, Stefan; Schliemann, Christoph; Mikesch, Jan-Henrik; Kaufmann, Martin; Haenel, Mathias; et al. (Journal of Cancer Research and Clinical Oncology, 2022)
Purpose: Higher doses of cytarabine appear to improve long-term outcome in acute myeloid leukemia (AML), in particular for younger patients. To this end, the optimal dosage of single-agent cytarabine in consolidation therapy remains elusive. Here, we assessed the impact of different dosages of cytarabine consolidation after 7 + 3 induction on outcome in a large real-world data set from the German Study Alliance Leukemia-Acute Myeloid Leukemia (SAL-AML) registry. Methods: Patients between 18 and 64 years of age, registered between April 2005 and September 2020, who attained complete remission after intensive induction and received at least one consolidation cycle with intermediate (IDAC) or high-dose cytarabine (HiDAC) were selected. To account for differences in patient and disease characteristics between both groups, the average treatment effect was estimated by propensity score weighting. Results: Six-hundred-forty-two patients received HiDAC consolidation with median dosage of 17.6 (IQR (interquartile range), 16.5–18.0) g/m2 for a median number of 3 cycles (IQR, 2–3), whereas 178 patients received IDAC consolidation with 5.9 (IQR, 5.7–8.6) g/m2 for a median of 2 cycles (IQR, 1–3). Both groups differed significantly in some important characteristics (age, sex, cytogenetic risk group, ECOG performance status, disease status, HCT-CI, number of induction cycles). After propensity score weighting for differences in patient and disease characteristics, relapse-free survival after 2 years was comparable between HiDAC-treated (55.3%) and IDAC-treated (55.6%) patients (HR = 0.935, p = 0.69). Moreover, no significant differences in overall survival were observed after 2 years (84.7 vs. 80.6%, HR = 1.101, p = 0.65). Notably, more patients treated with IDAC received allogeneic hematopoietic cell transplantation in first remission (37.6 vs. 19.8%, p < 0.001). Censoring for allogeneic hematopoietic cell transplantation in first remission revealed no significant survival difference with regard to cytarabine dosage. Considering only of European LeukemiaNet (ELN) favorable-risk AML patients, there was no significant difference in outcome. Of note, significantly more patients treated with HiDAC suffered from ≥ 3 CTCAE infectious complications (56.7 [95%-CI 52.8–60.6%] vs. 44.1% [95%-CI 36.6–51.7%]; p = 0,004). The rate of other ≥ 3 CTCAE non-hematological toxicities and secondary malignancies was comparable in both treatment groups. Conclusions: This retrospective analysis suggests no significant benefit of high-dose cytarabine compared to intermediate dosages in consolidation for AML patients under 65 years of age, independent of ELN risk group. Trial registration: NCT03188874.
CRIS-Team Scopus Importer:2022-10-14
Keywords: Acute myeloid leukemia; Consolidation therapy; Cytarabine dosage; Real-world data

Interaction of TWEAK with Fn14 leads to the progression of fibrotic liver disease by directly modulating hepatic stellate cell proliferation - Wilhelm, Annika; Shepherd, Emma L.; Amatucci, Aldo; Munir, Mamoona; Reynolds, Gary; Humphreys, Elizabeth; Resheq, Yazid; Adams, David H.; Huebscher, Stefan; Burkly, Linda C.; Weston, Christopher J.; Afford, Simon C. (Journal of Pathology, 2016)
Tumour necrosis factor-like weak inducer of apoptosis (TWEAK) and its receptor fibroblast growth factor-inducible 14 (Fn14) have been associated with liver regeneration in vivo. To further investigate the role of this pathway we examined their expression in human fibrotic liver disease and the effect of pathway deficiency in a murine model of liver fibrosis. The expression of Fn14 and TWEAK in normal and diseased human and mouse liver tissue and primary human hepatic stellate cells (HSCs) were investigated by qPCR, western blotting and immunohistochemistry. In addition, the levels of Fn14 in HSCs following pro-fibrogenic and pro-inflammatory stimuli were assessed and the effects of exogenous TWEAK on HSCs proliferation and activation were studied in vitro. Carbon tetrachloride (CCl4 ) was used to induce acute and chronic liver injury in TWEAK KO mice. Elevated expression of both Fn14 and TWEAK were detected in acute and chronic human liver injury, and co-localized with markers of activated HSCs. Fn14 levels were low in quiescent HSCs but were significantly induced in activated HSCs, which could be further enhanced with the profibrogenic cytokine TGF? in vitro. Stimulation with recombinant TWEAK induced proliferation but not further HSCs activation. Fn14 gene expression was also significantly up-regulated in CCl4 models of hepatic injury whereas TWEAK KO mice showed reduced levels of liver fibrosis following chronic CCl4 injury. In conclusion, TWEAK/Fn14 interaction leads to the progression of fibrotic liver disease via direct modulation of HSCs proliferation, making it a potential therapeutic target for liver fibrosis. © 2016 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.
EVALuna2:25751

Interprofessional Communication about Complementary and Integrative Health (CIH): Development and Implementation of a Training Program - Behzad, Ali; Stein, Barbara; Kaltenbach, Anna; Lohmueller, Lioba; Kroeger, Birgit; Boltenhagen, Ursula; Joos, Stefanie; Klafke, Nadja; Mahler, Cornelia; Stolz, Regina; Valentini, Jan; Horneber, Markus (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Interprofessionelle Kommunikation uber,Complementary and Integrative Health" (CIH): Entwicklung und Implementierung eines Training-Programms - Behzad, Ali; Stein, B.; Schmitt, A.; Lohmuller, L.; Kroger, B.; Boltenhagen, U.; Joos, S.; Klafke, N.; Mahler, C.; Stolz, R.; Valentini, J.; Horneber, M. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Intestinal graft-versus-host disease is driven by BATF-dependent IL-7R(hi)GM-CSF+ T cells - Ullrich, Evelyn; Abendroth, Benjamin; Rothamer, Johanna; Huber, Carina; Buettner-Herold, Maike; Kitowski, Vera; Vogler, Tina; Longerich, Thomas; Zundler, Sebastian; Völkl, Simon; Beilhack, Andreas; Rose-John, Stefan; et al. (2018)
EVALuna2:207769

Intravascular Large B-Cell Lymphoma: A Review with a Focus on the Prognostic Value of Skin Involvement - Breakell, Thomas; Waibel, Heidi; Schliep, Stefan; Ferstl, Barbara; Erdmann, Michael; Berking, Carola; Heppt, Markus (Current Oncology, 2022)
Intravascular large B-cell lymphoma (IVLBCL) is an aggressive Non-Hodgkin lymphoma (NHL) characterised by the presence of neoplastic lymphoid cells within small-and medium-sized blood vessels. According to the clinical presentation, the current WHO classification distinguishes the ‘classic’ (formerly ‘Western’) from a hemophagocytic syndrome-associated (formerly ‘Asian’) variant. A third ‘cutaneous’ variant has been proposed, characterised by a good prognosis and unique clinical features. While laboratory findings can hint at diagnosis, symptoms are rather nonspecific, and deep skin biopsy supported by further measures such as bone marrow aspiration and positron emission tomography-computed tomography scanning is needed to make a definite diagnosis. Treatment is comprised of anthracycline-based chemotherapy supplemented with rituximab and central nervous system prophylaxis. While there are various prognostic models for NHL, only one is specific to IVLBCL, which does not sufficiently represent some patient groups, especially regarding the lack of differentiation within the patient collective with skin involvement. This underlines the necessity for the establishment of further prognostic models in particular for IVLBCL patients with cutaneous manifestations.
CRIS-Team Scopus Importer:2022-05-13
Keywords: dermato-oncology; intravascular large B-cell lymphoma; IVLBCL; prognostic model; R-CHOP; skin cancer

Introducing a novel highly prognostic grading scheme based on tumour budding and cell nest size for squamous cell carcinoma of the uterine cervix - Jesinghaus, Moritz; Strehl, Johanna; Boxberg, Melanie; Bruehl, Frido; Wenzel, Adrian; Konukiewitz, Bjoern; Schlitter, Anna M.; Steiger, Katja; Warth, Arne; Schnelzer, Andreas; Kiechle, Marion; Beckmann, Matthias; et al. (Journal of Pathology: Clinical Research, 2018)
A novel histopathological grading system based on tumour budding and cell nest size has recently been shown to outperform conventional (WHO-based) grading algorithms in several tumour entities such as lung, oral, and oesophageal squamous cell carcinoma (SCC) in terms of prognostic patient stratification. Here, we tested the prognostic value of this innovative grading approach in two completely independent cohorts of SCC of the uterine cervix. To improve morphology-based grading, we investigated tumour budding activity and cell nest size as well as several other histomorphological factors (e.g., keratinization, nuclear size, mitotic activity) in a test cohort (n = 125) and an independent validation cohort (n = 122) of cervical SCC. All parameters were correlated with clinicopathological factors and patient outcome. Small cell nest size and high tumour budding activity were strongly associated with a dismal patient prognosis (p < 0.001 for overall survival [OS], disease-specific survival, and disease-free survival; test cohort) in both cohorts of cervical SCC. A novel grading algorithm combining these two parameters proved to be a highly effective, stage-independent prognosticator in both cohorts (OS: p < 0.001, test cohort; p = 0.001, validation cohort). In the test cohort, multivariate statistical analysis of the novel grade revealed that the hazard ratio (HR) for OS was 2.3 for G2 and 5.1 for G3 tumours compared to G1 neoplasms (p = 0.010). In the validation cohort, HR for OS was 3.0 for G2 and 7.2 for G3 tumours (p = 0.012). In conclusion, our novel grading algorithm incorporating cell nest size and tumour budding allows strongly prognostic histopathological grading of cervical SCC superior to WHO-based grading. Therefore, our data can be regarded as a cross-organ validation of previous results demonstrated for oesophageal, lung, and oral SCC. We suggest this grading algorithm as an additional morphology-based parameter for the routine diagnostic assessment of this tumour entity.
EVALuna2:35627

Invariant Natural Killer T Cells from Donor Lymphocyte Infusions (DLI-iNKTs) Contribute to Anti-Tumor Immunity after Allogeneic Hematopoietic Cell Transplantation - Jahnke, Simona; Schmid, Hannes; Secker, Kathy-Ann; Duerr-Stoerzer, Silke; Keppeler, Hildegard; Schumm, Michael; Handgretinger, Rupert; Bethge, Wolfgang; Kanz, Lothar; Schneidawind, Corina; Schneidawind, Dominik; Baur, Rebecca (BLOOD, 2018)
CRIS-Team WoS Importer:2019-02-27

Invariant NKT Cells From Donor Lymphocyte Infusions (DLI-iNKTs) Promote ex vivo Lysis of Leukemic Blasts in a CD1d-Dependent Manner - Jahnke, Simona; Schmid, Hannes; Secker, Kathy-Ann; Einhaus, Jakob; Duerr-Stoerzer, Silke; Keppeler, Hildegard; Schober-Melms, Irmtraud; Schumm, Michael; Handgretinger, Rupert; Bethge, Wolfgang; Kanz, Lothar; Schneidawind, Corina; et al. (Frontiers in Immunology, 2019)
Allogeneic hematopoietic cell transplantation (allo-HCT) is a curative treatment option for hematologic malignancies but relapse remains the most common cause of death. Infusion of donor lymphocytes (DLIs) can induce remission and prolong survival by exerting graft-vs.-leukemia (GVL) effects. However, sufficient tumor control cannot be established in all patients and occurrence of graft-vs.-host disease (GVHD) prevents further dose escalation. Previous data indicate that invariant natural killer T (iNKT) cells promote anti-tumor immunity without exacerbating GVHD. In the present study we investigated lysis of leukemic blasts through iNKT cells from donor-derived lymphocytes for leukemia control and found that iNKT cells constitute about 0.12% of cryopreserved donor T cells. Therefore, we established a 2-week cell culture protocol allowing for a robust expansion of iNKT cells from cryopreserved DLIs (DLI-iNKTs) that can be used for further preclinical and clinical applications. Such DLI-iNKTs efficiently lysed leukemia cell lines and primary patient AML blasts ex vivo in a dose- and CD1d-dependent manner. Furthermore, expression of CD1d on target cells was required to release proinflammatory cytokines and proapoptotic effector molecules. Our results suggest that iNKT cells from donor-derived lymphocytes are involved in anti-tumor immunity after allo-HCT and therefore may reduce the risk of relapse and improve progression-free and overall survival.
CRIS-Team WoS Importer:2019-07-23

In Vivo Effects of Mesenchymal Stromal Cells in Two Patients With Severe Acute Respiratory Distress Syndrome - Simonson, Oscar E.; Mougiakakos, Dimitrios; Heldring, Nina; Bassi, Giulio; Johansson, Henrik J.; Dalen, Magnus; Jitschin, Regina; Rodin, Sergey; Corbascio, Matthias; El Andaloussi, Samir; Wiklander, Oscar P. B.; Nordin, Joel Z.; et al. (Stem Cells Translational Medicine, 2015)
Mesenchymal stromal cells (MSCs) have been investigated as a treatment for various inflammatory diseases because of their immunomodulatory and reparative properties. However, many basic questions concerning their mechanisms of action after systemic infusion remain unanswered. We performed a detailed analysis of the immunomodulatory properties and proteomic profile of MSCs systemically administered to two patients with severe refractory acute respiratory distress syndrome (ARDS) on a compassionate use basis and attempted to correlate these with in vivo anti-inflammatory actions. Both patients received 2×10(6) cells per kilogram, and each subsequently improved with resolution of respiratory, hemodynamic, and multiorgan failure. In parallel, a decrease was seen in multiple pulmonary and systemic markers of inflammation, including epithelial apoptosis, alveolar-capillary fluid leakage, and proinflammatory cytokines, microRNAs, and chemokines. In vitro studies of the MSCs demonstrated a broad anti-inflammatory capacity, including suppression of T-cell responses and induction of regulatory phenotypes in T cells, monocytes, and neutrophils. Some of these in vitro potency assessments correlated with, and were relevant to, the observed in vivo actions. These experiences highlight both the mechanistic information that can be gained from clinical experience and the value of correlating in vitro potency assessments with clinical effects. The findings also suggest, but do not prove, a beneficial effect of lung protective strategies using adoptively transferred MSCs in ARDS. Appropriate randomized clinical trials are required to further assess any potential clinical efficacy and investigate the effects on in vivo inflammation.This article describes the cases of two patients with severe refractory adult respiratory syndrome (ARDS) who failed to improve after both standard life support measures, including mechanical ventilation, and additional measures, including extracorporeal ventilation (i.e., in a heart-lung machine). Unlike acute forms of ARDS (such in the current NIH-sponsored study of mesenchymal stromal cells in ARDS), recovery does not generally occur in such patients.
EVALuna2:25722

Karyotype complexity and prognosis in acute myeloid leukemia - Stoelzel, F.; Mohr, B.; Kramer, M.; Oelschlaegel, U.; Bochtler, T.; Berdel, W. E.; Kaufmann, M.; Baldus, C. D.; Schaefer-Eckart, K.; Stuhlmann, R.; Einsele, H.; Krause, Stefan; et al. (Blood Cancer Journal, 2016)
A complex aberrant karyotype consisting of multiple unrelated cytogenetic abnormalities is associated with poor prognosis in patients with acute myeloid leukemia (AML). The European Leukemia Net classification and the UK Medical Research Council recommendation provide prognostic categories that differ in the definition of unbalanced aberrations as well as the number of single aberrations. The aim of this study on 3526 AML patients was to redefine and validate a cutoff for karyotype complexity in AML with regard to adverse prognosis. Our study demonstrated that (1) patients with a pure hyperdiploid karyotype have an adverse risk irrespective of the number of chromosomal gains, (2) patients with translocation t(9;11)(p21 22;q23) have an intermediate risk independent of the number of additional aberrations, (3) patients with ?4 abnormalities have an adverse risk per se and (4) patients with three aberrations in the absence of abnormalities of strong influence (hyperdiploid karyotype, t(9;11)(p21 22;q23), CBF-AML, unique adverse-risk aberrations) have borderline intermediate/adverse risk with a reduced overall survival compared with patients with a normal karyotype.
EVALuna2:25734

Knowledge transfer to enhance the performance of deep learning models for automated classification of B-cell neoplasms - Mallesh, N.; Zhao, M.; Meintker, Lisa; Hoellein, A.; Elsner, F.; Lueling, H.; Haferlach, T.; Kern, W.; Westermann, J.; Brossart, P.; Krause, Stefan; Krawitz, P. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25
Keywords: deep learning; flow cytometry; lymphoma; neoplasm; classification; decision-support; open source; transfer learning; FCS data merge

Knowledge transfer to enhance the performance of deep learning models for automated classification of B cell neoplasms - Mallesh, Nanditha; Zhao, Max; Meintker, Lisa; Hoellein, Alexander; Elsner, Franz; Lueling, Hannes; Haferlach, Torsten; Kern, Wolfgang; Westermann, Jorg; Brossart, Peter; Krause, Stefan; Krawitz, Peter M. (Patterns, 2021)
Multi-parameter flow cytometry (MFC) is a cornerstone in clinical decision making for leukemia and lymphoma. MFC data analysis requires manual gating of cell populations, which is time-consuming, subjective, and often limited to a two-dimensional space. In recent years, deep learning models have been successfully used to analyze data in high-dimensional space and are highly accurate. However, AI models used for disease classification with MFC data are limited to the panel they were trained on. Thus, a key challenge in deploying AI into routine diagnostics is the robustness and adaptability of such models. This study demonstrates how transfer learning can be applied to boost the performance of models with smaller datasets acquired with different MFC panels. We trained models for four additional datasets by transferring the features learned from our base model. Our workflow increased the model's overall performance and, more prominently, improved the learning rate for small training sizes.
CRIS-Team WoS Importer:2021-10-29

Krüppel-like factor 2 controls IgA plasma cell compartmentalization and IgA responses - Wittner, Jens; Schulz, Sebastian; Steinmetz, Tobit; Berges, Johannes; Hauke, Manuela; Channell, William M.; Cunningham, Adam F.; Hauser, Anja E.; Hutloff, Andreas; Mielenz, Dirk; Jäck, Hans-Martin; Schuh, Wolfgang (Mucosal Immunology, 2022)
Krüppel-like factor 2 (KLF2) is a potent regulator of lymphocyte differentiation, activation and migration. However, its functional role in adaptive and humoral immunity remains elusive. Therefore, by using mice with a B cell-specific deletion of KLF2, we investigated plasma cell differentiation and antibody responses. We revealed that the deletion of KLF2 resulted in perturbed IgA plasma cell compartmentalization, characterized by the absence of IgA plasma cells in the bone marrow, their reductions in the spleen, the blood and the lamina propria of the colon and the small intestine, concomitant with their accumulation and retention in mesenteric lymph nodes and Peyer’s patches. Most intriguingly, secretory IgA in the intestinal lumen was almost absent, dimeric serum IgA was drastically reduced and antigen-specific IgA responses to soluble Salmonella flagellin were blunted in KLF2-deficient mice. Perturbance of IgA plasma cell localization was caused by deregulation of CCR9, Integrin chains αM, α4, β7, and sphingosine-1-phosphate receptors. Hence, KLF2 not only orchestrates the localization of IgA plasma cells by fine-tuning chemokine receptors and adhesion molecules but also controls IgA responses to Salmonella flagellin.
CRIS-Team Scopus Importer:2022-04-15

Label-Free High-Throughput Leukemia Detection by Holographic Microscopy - Ugele, Matthias; Weniger, Markus; Stanzel, Manfred; Bassler, Michael; Krause, Stefan; Friedrich, Oliver; Hayden, Oliver; Richter, Lukas (Advanced Science, 2018)
Complete blood count and differentiation of leukocytes (DIFF) belong to the most frequently performed laboratory diagnostic tests. Here, a flow cytometry-based method for label-free DIFF of untouched leukocytes by digital holographic microscopy on the rich phase contrast of peripheral leukocyte images, using highly controlled 2D hydrodynamic focusing conditions is reported. Principal component analysis of morphological characteristics of the reconstructed images allows classification of nine leukocyte types, in addition to different types of leukemia and demonstrates disappearance of acute myeloid leukemia cells in remission. To exclude confounding effects, the classification strategy is tested by the analysis of 20 blinded clinical samples. Here, 70% of the specimens are correctly classified with further 20% classifications close to a correct diagnosis. Taken together, the findings indicate a broad clinical applicability of the cytometry method for automated and reagent-free diagnosis of hematological disorders.
EVALuna2:35096

Label-Free Imaging of Single Proteins Secreted from Living Cells via iSCAT Microscopy - Gemeinhardt, André; McDonald, Matthew P.; König, Katharina; Aigner, Michael; Mackensen, Andreas; Sandoghdar, Vahid (Journal of Visualized Experiments, 2018)
We demonstrate interferometric scattering (iSCAT) microscopy, a method capable of detecting single unlabeled proteins secreted from individual living cells in real time. In this protocol, we cover the fundamental steps to realize an iSCAT microscope and complement it with additional imaging channels to monitor the viability of a cell under study. Following this, we use the method for real-time detection of single proteins as they are secreted from a living cell which we demonstrate with an immortalized B-cell line (Laz388). Necessary steps concerning the preparation of microscope and sample as well as the analysis of the recorded data are discussed. The video protocol demonstrates that iSCAT microscopy offers a straightforward method to study secretion at the single-molecule level.
EVALuna2:35094

Labeling of cancer cells with magnetic nanoparticles for magnetic resonance imaging - Weis, Christian; West, Adrian; Blank, Fabian; Black, Gregory; Woodward, Robert C.; Carroll, Matthew R. J.; Mainka, Astrid; Kartmann, René; Brandl, Anna; Bruns, Heiko; Hallam, Elizabeth; Shaw, Jeremy; et al. (Magnetic Resonance in Medicine, 2014)
The process of invasion and metastasis formation of tumor cells can be studied by following the migration of labeled cells over prolonged time periods. This report investigates the applicability of iron oxide nanoparticles as a magnetic resonance imaging (MRI) contrast agent for cell labeling.?Fe2 O3 nanoparticles prepared with direct flame spray pyrolysis are biofunctionalized with poly-l-lysine (PLL). The nanoparticles within the cells were observed with transmission electron microscopy, bright-field microscopy, and magnetorelaxometry. MRI of labeled cells suspended in agarose was used to estimate the detection limit.PLL-coated particles are readily taken up, stored in intracellular clusters, and gradually degraded by the cells. During cell division, the nanoparticle clusters are divided and split between daughter cells. The MRI detection limit was found to be 25 cells/mm(3) for R2*, and 70 cells/mm(3) for R2. The iron specificity, however, was higher for R2 images. Due to the degradation of intracellular ?Fe2 O3 to paramagnetic iron ions within 13 days, the R1, R2, and R2* contrast gradually decreased over this time period to approximately 50% of its initial value.These results suggest that PLL-coated ?Fe2 O3 nanoparticles can be used as an MRI contrast agent for long-term studies of cell migration. Magn Reson Med 71:1896-1905, 2014. © 2013 Wiley Periodicals, In
EVALuna2:25706

Large case-control study indicates no association of KIR genotype and risk of developing acute myeloid leukemia - Heidenreich, Falk; Falk, Bose; Baldauf, Henning; Massalski, Carolin; Schäfer, Gesine; Rücker-Braun, Elke; Altmann, Heidi; Sauter, Jürgen; Solloch, Ute V.; Lange, Vinzenz; Stölzel, Friedrich; Röllig, Christoph; et al. (Blood Advances, 2023)
Immunogenetic association studies may give rise to new hypotheses on the immune surveillance of cancer. We hypothesized that certain combinations of killer immunoglobulin-like receptor (KIR) and HLA genotypes may enhance natural killer (NK) cell immunity against nascent acute myeloid leukemia (AML) and, thereby, lead to a skewed genotype distribution among patients. For this purpose, we analyzed KIR and HLA genotypes of 1767 German patients with AML and compared the results with that of the data of 51 890 German volunteers who had registered with German bone marrow donor file (DKMS). Patient samples were retrieved from the Collaborative Biobank and the biorepository of the Study Alliance Leukemia. All samples were genotyped with high-resolution amplicon-based next-generation sequencing. Because of the large number of controls, this study was very sensitive to detect the impact of KIR genotype. Knowledge on KIRs and their cognate HLA ligands allowed for testing of several hypotheses of NK cell–mediated endogenous leukemia surveillance. We did not find significant differences between the 2 cohorts in regard to the presence or absence of single KIR genes. When grouped based on telomeric or centromeric gene content, the major haplotypes A/A, A/B, and B/B were equally distributed among patients and control subjects. Using information on KIRs and their HLA ligands, we further tested receptor-ligand models and summation models without revealing markedly significant differences between patients and controls, albeit we observed a trend pointing at a minor protective effect of a low number of inhibitory KIR/KIR-ligand pairs. The results suggest that the KIR/KIR-ligand genotype has no effect on the susceptibility for the development of de novo AML.
CRIS-Team Scopus Importer:2023-08-11

Late Non-Relapse Mortality (NRM) after Standard-of-Care (SOC) CAR-T Cell Therapy for Large B-Cell Lymphoma (LBCL): Frequency, Causes, and Risk Factors.a GLA/DRST Real World Analysis - Dreger, Peter; Schubert, Maria-Luisa; Holtick, Udo; Subklewe, Marion; Von Bastian, Tresckow; Ayuk, Francis A.; Wagner, Eva Maria; Wulf, Gerald; Marks, Reinhard; Penack, Olaf; Schnetzke, Ulf; Koenecke, Christian; et al. (BLOOD, 2021)
CRIS-Team WoS Importer:2022-09-09

LDHA-Associated Lactic Acid Production Blunts Tumor Immunosurveillance by T and NK Cells - Brand, Almut; Singer, Katrin; Koehl, Gudrun E.; Kolitzus, Marlene; Schoenhammer, Gabriele; Thiel, Annette; Matos, Carina; Bruss, Christina; Klobuch, Sebastian; Peter, Katrin; Kastenberger, Michael; Bogdan, Christian; et al. (Cell Metabolism, 2016)
Elevated lactate dehydrogenase A (LDHA) expression is associated with poor outcome in tumor patients. Here we show that LDHA-associated lactic acid accumulation in melanomas inhibits tumor surveillance by T and NK cells. In immunocompetent C57BL/6 mice, tumors with reduced lactic acid production (Ldha(low)) developed significantly slower than control tumors and showed increased infiltration with IFN-?-producing T and NK cells. However, in Rag2(-/-)?c(-/-) mice, lacking lymphocytes and NK cells, and in Ifng(-/-) mice, Ldha(low) and control cells formed tumors at similar rates. Pathophysiological concentrations of lactic acid prevented upregulation of nuclear factor of activated T cells (NFAT) in T and NK cells, resulting in diminished IFN-? production. Database analyses revealed negative correlations between LDHA expression and T cell activation markers in human melanoma patients. Our results demonstrate that lactic acid is a potent inhibitor of function and survival of T and NK cells leading to tumor immune escape.
EVALuna2:7715

Lenalidomide, adriamycin, dexamethasone (RAD) for induction followed by stem-cell transplant in newly diagnosed myeloma - Knop, S.; Langer, C.; Engelhardt, M.; Muegge, L-O; Reichle, A.; Rösler, Wolf; Bassermann, F.; Hertenstein, B.; Kunitz, A.; Roellig, C.; Ostermann, H.; Schaefer-Eckart, K.; et al. (Leukemia, 2017)
Leukemia accepted article preview online, 25 April 2017. doi:10.1038/leu.2017.124.
EVALuna2:25764

Lenalidomide enhances MOR202-dependent macrophage-mediated effector functions via the vitamin D pathway - Busch, Leonhard; Mougiakakos, Dimitrios; Büttner-Herold, Maike; Müller, Miriam J.; Volmer, Dietrich A.; Bach, Christian; Fabri, Mario; Bittenbring, Jörg T.; Neumann, Frank; Boxhammer, Rainer; Nolting, Jens; Bisht, Savita; et al. (Leukemia, 2018)
Macrophages are key mediators of the therapeutic effects exerted by monoclonal antibodies, such as the anti-CD38 antibody MOR202, currently introduced in multiple myeloma (MM) therapy. Therefore, it is important to understand how antibody-mediated effector functions of myeloma-associated macrophages (MAMs) are regulated. Here, we focused on the effects of vitamin D, a known regulator of macrophage effector functions. Consequently, it was the aim of this study to assess whether modulation of the vitamin D pathway alters the tumoricidal activity of MAMs. Here, we demonstrate that MAMs display a defective vitamin D pathway with reduced expression level of CYP27B1 and limited tumoricidal activity which can be restored by the IMiD lenalidomide in vitro. Furthermore, our data indicate that the vitamin D pathway of MAMs from MM patients does recover during an IMiD-containing therapy shown by an improved MOR202-mediated cytotoxic activity of these MAMs against primary MM cells ex vivo. Here, the ex vivo cytotoxic activity could be further enhanced by vitamin D supplementation. These data suggest that vitamin D holds a key role for the effector functions of MAMs and that vitamin D supplementation in IMiD combination trials could further increase the therapeutic efficacy of anti-CD38 antibodies such as MOR202, which remains to be investigated in clinical studies.
EVALuna2:34165

Leukemia control after allogeneic hematopoietic cell transplantation through ex vivo expanded invariant natural killer T cells from donor lymphocyte infusions (DLI-INKTS) - Jahnke, Simona; Schmid, Hannes; Secker, Kathy-Ann; Duerr-Stoerzer, Silke; Keppeler, Hildegard; Schumm, Michael; Handgretinger, Rupert; Bethge, Wolfgang; Kanz, Lothar; Schneidawind, Corina; Schneidawind, Dominik; Baur, Rebecca (BONE MARROW TRANSPLANTATION, 2019)
CRIS-Team WoS Importer:2019-10-11

Linking CREB function with altered metabolism in murine fibroblast-based model cell lines - Steven, André; Leisz, Sandra; Wickenhauser, Claudia; Schulz, Kristin; Mougiakakos, Dimitrios; Kiessling, Rolf; Denkert, Carsten; Seliger, Barbara (Oncotarget, 2017)
The cAMP-responsive element binding protein CREB is frequently overexpressed and activated in tumors of distinct histology, leading to enhanced proliferation, migration, invasion and angiogenesis as well as reduced apoptosis. The de-regulated expression of CREB might be linked with transcriptional as well as post-transcriptional regulation mechanisms. We show here that altered CREB expression levels and function are associated with changes in the cellular metabolism. Using comparative proteome-based analysis an altered expression pattern of proteins involved in the cellular metabolism in particular in glycolysis was found upon CREB down-regulation in HER-2/neu-transfected cell lines. This was associated with diminished expression levels of the glucose transporter 1, reduced glucose uptake and reduced glycolytic activity in HER-2/neu-transfected cells with down-regulated CREB when compared to HER-2/neu+ cells. Furthermore, hypoxia-induced CREB activity resulted in changes of the metabolism in HER-2/neu transfected cells. Low pH values in the supernatant of HER-2/neu transformants were restored by CREB down-regulation, but further decreased by hypoxia. The altered intracellular pH values were associated with a distinct expression of lactate dehydrogenase, and its substrate lactate. Moreover, enhanced phosphorylation of CREB on residue Ser133 was accompanied by a down-regulation of pERK and an up-regulation of pAKT. CREB promotes the detoxification of ROS by catalase, therefore protecting the mitochondrial activity under oxidative stress. These data suggest that there might exists a link between CREB function and the altered metabolism in HER-2/neu-transformed cells. Thus, targeting these altered metabolic pathways might represent an attractive therapeutic approach at least for the treatment of patients with HER-2/neu overexpressing tumors.
EVALuna2:25770

Linking Immunoevasion and Metabolic Reprogramming in B-Cell–Derived Lymphomas - Böttcher, Martin; Stoll, Andrej; Mackensen, Andreas; Mougiakakos, Dimitrios; Baur, Rebecca (Frontiers in Oncology, 2020)
Lymphomas represent a diverse group of malignancies that emerge from lymphocytes. Despite improvements in diagnosis and treatment of lymphomas of B-cell origin, relapsed and refractory disease represents an unmet clinical need. Therefore, it is of utmost importance to better understand the lymphomas’ intrinsic features as well as the interactions with their cellular microenvironment for developing novel therapeutic strategies. In fact, the role of immune-based approaches is steadily increasing and involves amongst others the use of monoclonal antibodies against tumor antigens, inhibitors of immunological checkpoints, and even genetically modified T-cells. Metabolic reprogramming and immune escape both represent well established cancer hallmarks. Tumor metabolism as introduced by Otto Warburg in the early 20th century promotes survival, proliferation, and therapeutic resistance. Simultaneously, malignant cells employ a plethora of mechanisms to evade immune surveillance. Increasing evidence suggests that metabolic reprogramming does not only confer cell intrinsic growth and survival advantages to tumor cells but also impacts local as well as systemic anti-tumor immunity. Tumor and immune cells compete over nutrients such as carbohydrates or amino acids that are critical for the immune cell function. Moreover, skewed metabolic pathways in malignant cells can result in abundant production and release of bioactive metabolites such as lactic acid, kynurenine or reactive oxygen species (ROS) that affect immune cell fitness and function. This “metabolic re-modeling” of the tumor microenvironment shifts anti-tumor immune reactivity toward tolerance. Here, we will review molecular events leading to metabolic alterations in B-cell lymphomas and their impact on anti-tumor immunity.
CRIS-Team Scopus Importer:2020-11-27
Keywords: B-cell-derived Non-Hodgkin lymphoma; chronic lymphocytic leukemia; immune escape; immune therapeutics; metabolism

Lipomatous Solitary Fibrous Tumors Harbor Rare NAB2-STAT6 Fusion Variants and Show Up-Regulation of the Gene PPARG, Encoding for a Regulator of Adipocyte Differentiation - Haller, Florian; Schlieben, Lea D.; Ferrazzi, Fulvia; Michal, Michael; Stöhr, Robert; Moskalev, Evgeny; Bieg, Matthias; Bovée, Judith V.M.G.; Ströbel, Philip; Ishaque, Naveed; Grützmann, Robert; Meidenbauer, Norbert; et al. (American Journal of Pathology, 2021)
Solitary fibrous tumors (SFTs) harbor activating NAB2-STAT6 gene fusions. Different variants of the NAB2-STAT6 gene fusion have been associated with distinct clinicopathologic features. Lipomatous SFTs are a morphologic variant of SFTs, characterized by a fat-forming tumor component. Our aim was to evaluate NAB2-STAT6 fusion variants and to further study the molecular genetic features in a cohort of lipomatous SFTs. A hybrid-capture–based next-generation sequencing panel was employed to detect NAB2-STAT6 gene fusions at the RNA level. In addition, the RNA expression levels of 507 genes were evaluated using this panel, and were compared with a control cohort of nonlipomatous SFTs. Notably, 5 of 11 (45%) of lipomatous SFTs in the current series harbored the uncommon NAB2 exon 4–STAT6 exon 4 gene fusion variant, which is observed in only 0.9% to 1.4% of nonlipomatous SFTs. Furthermore, lipomatous SFTs displayed significant differences in gene expression compared with their nonlipomatous counterparts, including up-regulation of the gene peroxisome proliferator activated receptor-γ (PPARG). Peroxisome proliferator activated receptor-γ is a nuclear receptor regulating adipocyte differentiation, providing a possible explanation for the fat-forming component in lipomatous SFTs. In summary, the current study provides a possible molecular genetic basis for the distinct morphologic features of lipomatous SFTs.
CRIS-Team Scopus Importer:2021-06-04

Lipotoxicity as a Barrier for T Cell-Based Therapies - Boettcher-Loschinski, Romy; Rial Saborido, Judit; Boettcher, Martin; Kahlfuss, Sascha; Mougiakakos, Dimitrios (Biomolecules, 2022)
Nowadays, T-cell-based approaches play an increasing role in cancer treatment. In particular, the use of (genetically engineered) T-cells has heralded a novel era for various diseases with previously poor outcomes. Concurrently, the relationship between the functional behavior of immune cells and their metabolic state, known as immunometabolism, has been found to be an important determinant for the success of immunotherapy. In this context, immune cell metabolism is not only controlled by the expression of transcription factors, enzymes and transport proteins but also by nutrient availability and the presence of intermediate metabolites. The lack of as well as an oversupply of nutrients can be detrimental and lead to cellular dysfunction and damage, potentially resulting in reduced metabolic fitness and/or cell death. This review focusses on the detrimental effects of excessive exposure of T cells to fatty acids, known as lipotoxicity, in the context of an altered lipid tumor microenvironment. Furthermore, implications of T cell-related lipotoxicity for immunotherapy will be discussed, as well as potential therapeutic approaches.
CRIS-Team WoS Importer:2022-09-30

Long-Term Clinical and Radiologic Outcome Following Surgical Treatment of Lumbar Spondylodiscitis: A Retrospective Bicenter Study - Sommer, Björn; Babbe-Pekol, Timo; Feulner, Julian; Richter, Richard Heinrich; Buchfelder, Michael; Shiban, Ehab; Sesselmann, Stefan; Forst, Raimund; Wiendieck, Kurt (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background and Study Aims Spinal instrumentation for spondylodiskitis (SD) remains highly controversial. To date, surgical data are limited to relatively small case series with short-term follow-up data. In this study, we wanted to elucidate the biomechanical, surgical, and neurologic long-term outcomes in these patients. Material and Methods A retrospective analysis from two German primary care hospitals over a 9-year period (2005-2014) was performed. The inclusion criteria were (1) pyogenic lumbar SD, (2) minimum follow-up of 1 year, and (3) surgical instrumentation. The clinical and radiologic outcome was assessed before surgery, at discharge, and at a minimum of 12 months of follow-up. Follow-up included physical examination, laboratory results, CT and MRI scans, as well as assessment of quality of life (QoL) using short-form health survey (SF-36) inventory, Oswestry Disability Questionnaire, and visual analog scale (VAS) spine score. Results Complete data were available in 70 patients (49 males and 21 females, with an age range of 67±12.3 years) with a median follow-up of 6.6 ± 4.2 years. Follow-up data were available in 70 patients after 1 year, in 58 patients after 2 years, and in 44 patients after 6 years. Thirty-five patients underwent posterior stabilization and decompression alone and 35 patients were operated on in a two-stage 360-degree interbody fusion with decompression. Pre- and postoperative angles of the affected motion segment were 17.6 ± 10.2 and 16.1 ± 10.7 degrees in patients with posterior instrumentation only and 21.0 ± 10.2 and 18.3 ± 10.5 degrees in patients with combined anterior/posterior fusion. Vertebral body subsidence was seen in 12 and 6 cases following posterior instrumentation and 360-degree instrumentation, respectively. Nonfusion was encountered in 22 and 11 cases following posterior instrumentation and 360-degree instrumentation, respectively. The length of hospital stay was 35.0 ± 24.5 days. Surgery-associated complication rate was 18% (12/70). New neurologic symptoms occurred in 7% (5/70). Revision surgery was performed in 3% (2/70) due to screw misplacement/hardware failure and in 3% (2/70) due to intraspinal hematoma. Although patients reported a highly impaired pain deception and vitality, physical mobility was unaffected and pain disability during daily activities was moderate. Conclusion Surgical treatment of SD with a staged surgical approach (if needed) is safe and provides very good long-term clinical and radiologic outcome.
CRIS-Team Scopus Importer:2022-07-22
Keywords: biomechanics; diagnostics; functional outcome; quality of life; risk factor; spinal infection; surgical approach; vertebral pyogenic osteomyelitis

Long-term efficacy, safety and neurotolerability of MATRix regimen followed by autologous transplant in primary CNS lymphoma: 7-year results of the IELSG32 randomized trial - Ferreri, Andres J. M.; Cwynarski, Kate; Pulczynski, Elisa; Fox, Christopher P.; Schorb, Elisabeth; Celico, Claudia; Falautano, Monica; Nonis, Alessandro; La Rosee, Paul; Binder, Mascia; Fabbri, Alberto; Ilariucci, Fiorella; et al. (Leukemia, 2022)
219 HIV-negative adults <= 70 years with primary CNS lymphoma (PCNSL) were enrolled in the randomized IELSG32 trial. Enrolled patients were randomly assigned to receive methotrexate-cytarabine (arm A), or methotrexate-cytarabine-rituximab (B), or methotrexate-cytarabine-thiotepa-rituximab (MATRix; arm C). A second randomization allocated patients with responsive/stable disease to whole-brain irradiation (WBRT) or carmustine-thiotepa-conditioned autologous transplantation (ASCT). First results, after a median follow-up of 30 months, showed that MATRix significantly improves outcome, with both WBRT and ASCT being similarly effective. However, sound assessment of overall survival (OS), efficacy of salvage therapy, late complications, secondary tumors, and cognitive impairment requires longer follow-up. Herein, we report the results of this trial at a median follow-up of 88 months. As main findings, MATRix was associated with excellent long-lasting outcome, with a 7-year OS of 21%, 37%, and 56% respectively for arms A, B, and C. Notably, patients treated with MATRix and consolidation had a 7-year OS of 70%. The superiority of arm B on arm A suggests a benefit from the addition of rituximab. Comparable efficacy of WBRT and ASCT was confirmed. Salvage therapy was ineffective; benefit was recorded only in patients with late relapse re-treated with methotrexate. Eight (4%) patients developed a second cancer. Importantly, MATRix and ASCT did not result in higher non-relapse mortality or second tumors incidence. Patients who received WBRT experienced impairment in attentiveness and executive functions, whereas patients undergoing ASCT experienced improvement in these functions as well as in memory and quality of life.
CRIS-Team WoS Importer:2022-06-03

Long-Term Follow-Up and Impact of Comorbidity before Allogeneic Hematopoietic Stem Cell Transplantation in Patients with Relapsed or Refractory Acute Myeloid Leukemia-Lessons Learned from the Prospective BRIDGE Trial - Middeke, Jan Moritz; Herbst, Regina; Parmentier, Stefani; Bug, Gesine; Hänel, Mathias; Stuhler, Gernot; Schäfer-Eckart, Kerstin; Rösler, Wolf; Klein, Stefan; Bethge, Wolfgang; Bitz, Ulrich; Büttner, Bozena; et al. (Biology of Blood and Marrow Transplantation, 2017)
In patients with relapsed or refractory (r/r) acute myeloid leukemia (AML), allogeneic hematopoietic stem cell transplantation (HSCT) is considered to be the only treatment providing long-term disease control. The BRIDGE trial studied the safety and efficacy of a clofarabine-based salvage therapy before HSCT in patients with r/r AML. Here, we report the long-term follow-up of this phase II multicenter trial and exploratory analyses on the impact of comorbidity on outcome. Eighty-four patients with a median age of 61 years (range, 40 to 75) were enrolled. Patients were scheduled for at least 1 cycle of salvage therapy with CLARA (clofarabine 30 mg/m(2); cytarabine 1 g/m(2), days 1 to 5). Chemo-responsive patients with a donor received HSCT after first CLARA. The conditioning regimen consisted of clofarabine 30 mg/m(2), day -6 to -3, and melphalan 140 mg/m(2) day -2. The Eastern Cooperative Oncology Group (ECOG) score, the hematopoietic cell transplantation-specific comorbidity index (HCT-CI), and the Cumulative Illness Rating Scale were obtained at study enrollment as well as before HSCT. Sixty-seven percent of the patients received HSCT within the trial. After a median follow up of 40 months, the estimated 3-year overall survival (OS) for all enrolled patients and those with HSCT within the trial was 40% and 55%, respectively. Relapse-free survival for patients who underwent transplantation with a complete remission afterwards (n = 50) was 48%, calculated from the day of transplantation. In multivariate analysis, both the HCT-CI and ECOG score had a statistically significant impact on OS with a hazard ratio of 1.22 (P = .025)and 1.72 (P = .001), respectively. Using a clofarabine-based salvage therapy combined with early allogeneic HSCT, we were able to achieve good long-term results for patients with r/r AML. In this cohort, both the HCT-CI and the ECOG scores gave prognostic information on OS, showing the feasibility and clinical relevance of comorbidity evaluation at the time of diagnosis of r/r AML patients.
EVALuna2:25768

Long-Term Outcome of a Prospective Randomized Trial Comparing Continuous Lenalidomide/Dexamethasone with Lenalidomide/Dexamethasone Induction, MEL140 with Autologous Blood Stem Cell Transplantation and Single Agent Lenalidomide Maintenance in Patients of Age 60-75 Years with Newly Diagnosed Multiple Myeloma - Straka, Christian; Schaefer-Eckart, Kerstin; Hertenstein, Bernd; Bassermann, Florian; Salwender, Hans; Langer, Christian; Kroenke, Jan; Kull, Miriam; Schilling, Georgia; Schieferdecker, Aneta; Engelhardt, Monika; Knop, Stefan; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Long-Term Results of Allogeneic Stem Cell Transplantation in Adult Ph- Negative High-Risk Acute Lymphoblastic Leukemia - Beelen, Dietrich W.; Arnold, Renate; Stelljes, Matthias; Alakel, Nael; Brecht, Arne; Bug, Gesine; Bunjes, Donald; Faul, Christoph; Finke, Jürgen; Franke, Georg Nikolaus; Holler, Ernst; Kobbe, Guido; et al. (Transplantation and Cellular Therapy, 2022)
Allogeneic hematopoietic stem cell transplantation (HCT) is standard treatment for adult high-risk (HR) acute lymphoblastic leukemia (ALL) and contributed to the overall improved outcome. We report a consecutive cohort of prospectively defined HR patients treated on German Multicenter Acute Lymphoblastic Leukemia trials 06/99-07/03 with similar induction/consolidation therapy and HCT in first remission. A total of 542 patients (15-55 years) with BCR-ABL–negative ALL were analyzed. Sixty-seven percent received HCT from matched unrelated donors (MUD) and 32% from matched sibling donors (MSD). The incidence of non-relapse mortality (NRM) was 20% at 5 years. NRM occurred after median 6.6 months; the leading cause (46%) was infection. NRM after MUD decreased from 39% in trial 06/99 to 16% in trial 07/03 (P < .00001). Patient age was the strongest predictor of NRM. The 5-year relapse incidence was 23% using MSD and 25% using MUD. Minimal residual disease (MRD) was the strongest predictor of relapse (45% for molecular failure versus 6% for molecular CR; P < .0001). The median follow-up was 67 months, and the 5-year survival rate was 58%. Age, subtype/high risk feature, MRD status, trial and acute GvHD were significant prognostic factors. We provide a large reference analysis with long follow-up confirming a similar outcome of MSD and MUD HCT and improved NRM for MUD HCT over years. MRD has a strong impact on relapse risk, whereas age was the strongest predictor of NRM. New adapted conditioning strategies should be considered for older patients combined with the goal to reduce the MRD level before stem cell transplantation.
CRIS-Team Scopus Importer:2022-10-28
Keywords: Adult High-risk ALL; Allogeneic SCT; Prospective GMALL Trials

Long-Term Survivors after Failure of Chimeric Antigen Receptor T Cell Therapy for Large B Cell Lymphoma: A Role for Allogeneic Hematopoietic Cell Transplantation? A German Lymphoma Alliance and German Registry for Stem Cell Transplantation Analysis - Derigs, Patrick; Bethge, Wolfgang A.; Krämer, Isabelle; Holtick, Udo; von Tresckow, Bastian; Ayuk, Francis; Penack, Olaf; Vucinic, Vladan; von Bonin, Malte; Baldus, Claudia; Mougiakakos, Dimitrios; Wulf, Gerald; et al. (Transplantation and Cellular Therapy, 2023)
The outcome of patients with large B cell lymphoma (LBCL) who relapse or progress after CD19-directed chimeric antigen receptor T cell therapy (CAR-T) administered as salvage therapy beyond the second treatment line is poor. However, a minority of patients become long-term survivors despite CAR-T failure. The German Lymphoma Alliance (GLA) has proposed a hierarchical management algorithm for CAR-T failure in LBCL, aimed at allogeneic hematopoietic cell transplantation (alloHCT) as definite therapy in eligible patients. The purpose of this study was to investigate characteristics, relapse patterns, and management strategies in long-term survivors after CAR-T failure, with a particular focus on the feasibility and outcome of alloHCT. This was a retrospective analysis of all evaluable patients with a relapse/progression event (REL) observed in a previously reported GLA sample between November 2018 and May 2021. REL occurred in 214 of 356 patients (60%) who underwent CAR-T for LBCL in the previous GLA study. An evaluable dataset was available for 143 of these 214 patients (67%). Twenty-six of 143 patients (18%) survived 12 months or longer from REL, 109 (76%) died within the first year after REL, and 8 (6%) were alive but had not reached the 12-month landmark. Long-term survivors had more favorable pre-CAR-T features, had a longer interval between CAR-T and REL, and had more often received a tumor biopsy after CAR-T failure, whereas the choice of the first salvage regimen had no impact. AlloHCT was feasible in 40 of 53 patients (75%) intended and resulted in a 12-month post-transplantation overall survival of 36% in those patients who underwent transplantation with sensitive or untreated REL. AlloHCT after CAR-T failure in LBCL is feasible and may be an important contributor to long-term survival, although selection bias must be taken into account. Thus, alloHCT should be considered as a reasonable treatment option for eligible patients in this setting. However, because the overall outlook after CAR-T failure remains poor, novel effective therapeutic approaches are needed, either to allow long-term disease control per se or to improve the preconditions for successful alloHCT.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Allogeneic hematopoietic cell transplantation; CAR-T; Lymphoma; Relapse

Loss-of-function mutations of bcor are an independent marker of adverse outcomes in intensively treated patients with acute myeloid leukemia - Eckardt, Jan Niklas; Stasik, Sebastian; Kramer, Michael; Röllig, Christoph; Krämer, Alwin; Scholl, Sebastian; Hochhaus, Andreas; Crysandt, Martina; Brümmendorf, Tim H.; Naumann, Ralph; Steffen, Björn; Kunzmann, Volker; et al. (Cancers, 2021)
Acute myeloid leukemia (AML) is characterized by recurrent genetic events. The BCL6 corepressor (BCOR) and its homolog, the BCL6 corepressor-like 1 (BCORL1), have been reported to be rare but recurrent mutations in AML. Previously, smaller studies have reported conflicting results regarding impacts on outcomes. Here, we retrospectively analyzed a large cohort of 1529 patients with newly diagnosed and intensively treated AML. BCOR and BCORL1 mutations were found in 71 (4.6%) and 53 patients (3.5%), respectively. Frequently co-mutated genes were DNTM3A, TET2 and RUNX1. Mutated BCORL1 and loss-of-function mutations of BCOR were significantly more common in the ELN2017 intermediate-risk group. Patients harboring loss-of-function mutations of BCOR had a significantly reduced median event-free survival (HR = 1.464 (95%-Confidence Interval (CI): 1.005–2.134), p = 0.047), relapse-free survival (HR = 1.904 (95%-CI: 1.163–3.117), p = 0.01), and trend for reduced overall survival (HR = 1.495 (95%-CI: 0.990–2.258), p = 0.056) in multivariable analysis. Our study establishes a novel role for loss-of-function mutations of BCOR regarding risk stratification in AML, which may influence treatment allocation.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Acute myeloid leukemia; BCOR; BCORL1; Loss-of-function; Risk stratification; Survival

Loss of MTUS1/ATIP expression is associated with adverse outcome in advanced bladder carcinomas: data from a retrospective study - Rogler, Anja; Hoja, Sabine; Giedl, Josef; Ekici, Arif Bülent; Wach, Sven; Taubert, Helge; Goebell, Peter; Wullich, Bernd; Stoeckle, Michael; Lehmann, Jan; Petsch, Sabrina; Hartmann, Arndt; et al. (BMC Cancer, 2014)
Seventy percent of all bladder tumours tend to recur and need intensive surveillance, and a subset of tumours progress to muscle-invasive and metastatic disease. However, it is still difficult to find the adequate treatment for every individual patient as it is a very heterogeneous disease and reliable biomarkers are still missing. In our study we searched for new target genes in the critical chromosomal region 8p and investigated the potential tumour suppressor gene candidate MTUS1/ATIP in bladder cancer.MTUS1 was identified to be the most promising deleted target gene at 8p in aCGH analysis with 19 papillary bladder tumours. A correlation with bladder cancer was further validated using immunohistochemistry of 85 papillary and 236 advanced bladder tumours and in functional experiments. Kaplan-Meier analysis and multivariate Cox-regression addressed overall survival (OS) and disease-specific survival (DSS) as a function of MTUS1/ATIP expression. Bivariate correlations investigated associations between MTUS1/ATIP expression, patient characteristics and histopathology. MTUS1 expression was analysed in cell lines and overexpressed in RT112, where impact on viability, proliferation and migration was measured.MTUS1 protein expression was lost in almost 50% of all papillary and advanced bladder cancers. Survival, however, was only influenced in advanced carcinomas, where loss of MTUS1 was associated with adverse OS and DSS. In this cohort, there was also a significant correlation of MTUS1 expression and histological subtype: positive expression was detected in all micropapillary tumours and aberrant nuclear staining was detected in a subset of plasmocytoid urothelial carcinomas. MTUS1 was expressed in all investigated bladder cell lines and overexpression in RT112 led to significantly decreased viability.MTUS1 is a tumour suppressor gene in cultured bladder cancer cells and in advanced bladder tumours. It might represent one new target gene at chromosome 8p and can be used as an independent prognostic factor for advanced bladder cancer patients. The limitation of the study is the retrospective data analysis. Thus, findings should be validated with a prospective advanced bladder tumour cohort.
EVALuna2:6624

Loss of TP53 modifies the quantity and protein load of extracellular vesicles in leukemic B-cells and influences functional crosstalk within the tumor microenvironment - Izquierdo-Alvarez, E.; Vorholt, D.; Wiederstein, J.; Lobastova, L.; Blakemore, S. J.; Krueger, M.; Hansen, H.; Bruns, Heiko; Hallek, M.; Pallasch, C. (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Low-dose eplerenone decreases left ventricular mass in treatment-resistant hypertension - Schneider, Andreas; Schwab, Johannes; Karg, Margarete; Kalizki, Tatjana; Reinold, Annemarie; Schneider, Markus; Schmieder, Roland; Schmidt, Bernhard M. W. (Journal of Hypertension, 2017)
Mineralocorticoid receptor antagonists are increasingly used in patients with treatment-resistant hypertension (TRH). There is experimental evidence for blood pressure (BP) independent effects of mineralocorticoid receptor blockade on cardiovascular target organ damage. We hypothesized that low-dose eplerenone (50 mg) will reduce left ventricular mass (LVM) beyond its BP-lowering effects.We performed a randomized, double-blind, placebo-controlled, parallel group study in 51 patients with TRH. Patients were allocated to receive either eplerenone 50 mg or placebo for 6 months, while other antihypertensive agents could be added in both groups to achieve a BP target of less than 140/90 mmHg. LVM was assessed by MRI before and after treatment.Baseline office BP was similar in the eplerenone and the placebo group (166 ± 21/91 ± 15 versus 159 ± 19/94 ± 8 mmHg, n.s.). BP was similarly reduced in the eplerenone versus the placebo group (-35 ± 20/-15 ± 11 versus -30 ± 19/-13 ± 7 mmHg, n.s.). However, LVM was reduced only in the eplerenone group (from 155 ± 33 to 136 ± 33 g, P < 0.001), but not in the placebo group (152 ± 32 versus 148 ± 38 g, P = 0.45).Despite similar BP-lowering, only patients with TRH who were allocated to eplerenone experienced a reduction of LVM. Thus, our data suggest that in patients with TRH, mineralocorticoid receptor antagonists should be used preferentially in order to achieve an effective reduction of LVM along with the improvement of BP control.
EVALuna2:3937

Low-dose interleukin-2 for the treatment of glucocorticoid-refractory acute graft-versus-host disease: a single center experience - Brandt, Adrian; Vasova, Ingrid; Winkler, Julia; Mackensen, Andreas; Rösler, Wolf; Spoerl, S.; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Lymphatic and vascular invasion in oral squamous cell carcinoma: Implications for recurrence and survival in a population-based cohort study - Spoerl, Steffen; Gerken, Michael; Fischer, René; Mamilos, Andreas; Spoerl, Silvia; Wolf, Stefanie; Pohl, Fabian; Klingelhöffer, Christoph; Ettl, Tobias; Reichert, Torsten E.; Spanier, Gerrit (Oral Oncology, 2020)
Objective: Numerous studies analyzed lymphovascular invasion (LVI) in various malignant diseases, however, little is known about the role of lymphatic invasion (LI) as well as vascular invasion (VI) in oral squamous cell carcinoma (OSCC). The aim of this study is to illuminate the role of LI and VI in a population-based cohort study. Methods: We retrospectively analyzed 745 primarily resected OSCC patients in Eastern Bavaria for histopathologically verified LI and VI. Overall survival (OS) and recurrence-free survival (RFS) were calculated, whereas analysis was performed by uni- and multivariate statistics. Mean follow-up time was 7.4 years. Results: LI was found in 115 patients (15.4%), VI was diagnosed in 23 cases (3.1%). LI correlated significantly with distinct anatomical sites (p = 0.004), increasing pT-classification (p < 0.001), lymph node involvement (p < 0.001), higher grading (p < 0.001), advanced UICC-stages (p < 0.001) and adjuvant therapies (p < 0.001). Similar results were found for VI. Survival analysis resulted in a significantly decreased five-year OS and RFS in patients with diagnosed LI (OS: 41.1%, RFS: 38.3%) in contrast to LI-negative cases (OS: 66.8%, RFS: 59.7.7%, p < 0.001). Analogous outcomes were seen for patients with VI. Additionally, LI was identified as a predictive parameter, indicating individual patients’ response to adjuvant therapies. Conclusion: This population-based cohort study underlines the unfavorable aspect of LI and VI on outcome in OSCC. Including LI and VI in existing staging systems could help to stratify patients’ risk for adverse outcome and consecutively determine adjuvant treatment in malignant disease.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Adjuvant therapy; Blood vessel invasion; Lymphatic vessel invasion; Lymphovascular invasion; Oral squamous cell carcinoma; Survival

Lymph node ratio as a predictor for outcome in oral squamous cell carcinoma: a multicenter population-based cohort study - Spoerl, Steffen; Gerken, Michael; Mamilos, Andreas; Fischer, René; Wolf, Stefanie; Nieberle, Felix; Klingelhöffer, Christoph; Meier, Johannes K.; Spoerl, Silvia; Ettl, Tobias; Reichert, Torsten E.; Spanier, Gerrit (Clinical Oral Investigations, 2020)
Objectives: Recently, multiple studies addressed the importance of lymph node ratio (LNR) in specifying patients’ risk of disease recurrence in various malignancies. The present study examines the prognostic significance of LNR in predicting outcome of oral squamous cell carcinoma (OSCC) patients after surgical treatment with curative intent. Methods: Here, we describe a retrospective population-based cohort with 717 patients previously diagnosed with OSCC. Histopathologically verified lymph node metastasis was diagnosed in 290 patients. Among these patients, we evaluated the impact of LNR on overall survival (OAS) and recurrence-free survival (RFS) in uni- as well as multivariate analysis. Results: A median cutoff (0.055) in LNR was found to significantly predict outcome in OSCC patients. Five-year OAS was 54.1% in patients with a low LNR, whereas a high LNR was associated with a 5-year OAS of 33.3% (p < 0.001). Similar results were detected for RFS with a 5-year survival rate of 49.8% (LNR low) and 30.3% (LNR high) (p = 0.002). Results were confirmed in multivariate Cox regression which substantiated the importance of LNR in predicting survival in OSCC patients. Conclusions: LNR was shown to be an independent prognostic factor for outcome of OSCC in a population-based cohort in uni- as well as multivariate analysis. Hereby, a LNR ≥ 0.055 predicted a shorter OAS and RFS in our cohort. Clinical relevance: Besides established histopathological factors, LNR can be used as a reliable predictor of outcome in OSCC and might therefore be further applied in evaluating adjuvant treatment after resection in curative intention.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Lymph node density; Lymph node ratio; Oral squamous cell carcinoma; Recurrence; Survival

Lymphocyte Immune Response and T Cell Differentiation in Fontan Patients with protein-losing enteropathy - Moosmann, Julia; Toka, Okan; Lukassen, Sören; Ekici, Arif Bülent; Mackensen, Andreas; Dittrich, Sven; Völkl, Simon (Thoracic and Cardiovascular Surgeon, Supplement, 2021)
Background Protein-losing enteropathy (PLE) is a severe complication of the Fontan circulation. There is increasing discussion about whether lymphatic dysregulation is involved as pathomechanism of PLE. This investigation focuses on the interplay between alteration of lymphatic cells and immunologic pathway alterations. Methods Micro-ribonucleic acid (miRNA) expression profiling was performed in 49 patients (n = 10 Fontan patients with PLE, n = 30 Fontan patients without PLE, and n = 9 patients with dextro-transposition of the great arteries (dTGA). miRNA pathway analysis was performed to identify significantly enriched pathways. To determine lymphocyte populations and subtypes multiparameter flow cytometry was used. Results miRNAs pathway analysis of Fontan patients with PLE revealed 20 significantly changed networks of which four of the ten largest were associated with immunologic processes. This finding is supported by significant T cell deficiency with decreased CD4+ count (p = 0.0002), altered CD4 +/CD8+ ratio, and significantly modified CD4+ (p < 0.0001) and CD8+ (p = 0.0002) T cell differentiation toward effector and terminal differentiated T cells in Fontan patients with PLE. Analyses of CD4+ T cell subsets demonstrated significantly increased frequencies of CD4+ CD25+ CD127- regulatory T cells (Treg) in Fontan patients with PLE (p = 0.0011). Conclusion PLE in Fontan patients is associated with severe lymphopenia, T cell deficiency, significant alterations of T cell differentiation, and increased Treg frequency reflecting an immune status of chronic inflammation and shortened protection against pathogens and autoimmunity. These cellular alterations seemed to be dysregulated by several miRNA controlled immunological pathways.
CRIS-Team Scopus Importer:2021-03-05
Keywords: congenital heart disease (CHD); genetics; genomics; inflammation; systemic

Macrophages and dendritic cells as actors in the immune reaction of classical hodgkin lymphoma - Tudor, Christiane; Bruns, Heiko; Daniel, Christoph; Distel, Luitpold; Hartmann, Arndt; Gerbitz, Armin; Büttner, Maike (PLoS ONE, 2014)
The inflammatory infiltrate plays a pivotal role in classical Hodgkin lymphoma (cHL). Here, we focussed on the role of macrophages (M?) and dendritic cells (DC).M? and DC infiltration was investigated in 106 cHL specimens using immunohistochemistry and cytokine expression was analyzed in a subset by real-time PCR. Human peripheral blood-derived monocytes, DC, M? stimulated with GM-CSF (M?GM-CSF, pro-inflammatory M?-1-model) or M-CSF (M?M-CSF, immunomodulatory M?-2-model) were incubated with cHL cell line (L1236, HDLM2) supernatants (SN). DC maturation or M? polarization were investigated by flow cytometry. Furthermore, the impact of DC or M? on cHL cell proliferation was analyzed by BrdU/CFSE assay.In cHL tissues mature myeloid (m)DC and M? predominated. High numbers of CD83+ mDC and low numbers of CD163+ M? were associated with improved disease specific survival. In numerous cHL specimens increased levels of both pro- and anti-inflammatory cytokines and of IL13 and GM-CSF were observed compared to reactive lymphadenopathies. Maturation of DC and induction and maintenance of an immunomodulatory M? phenotype were promoted by SN derived from cHL cell lines. TNF? neutralization in SN resulted in a significant inhibition of mDC maturation. DC and pro-inflammatory M? inhibited the proliferation of cHL cells.Adopting an immunomodulatory phenotype is a potential mechanism for how M? promote immune evasion in cHL. Mature DC, in contrast, might participate in antitumoral immunit
EVALuna2:6630

MAGIC biomarkers predict long term outcomes for steroid-resistant acute GVHD - Major-Monfried, Hannah; Renteria, Anne S.; Pawarode, Attaphol; Reddy, Pavan; Ayuk, Francis; Holler, Ernst; Efebera, Yvonne A.; Hogan, William J.; Woelfl, Matthias; Qayed, Muna; Hexner, Elizabeth O.; Wudhikarn, Kitsada; et al. (Blood, 2018)
Acute graft versus host disease (GVHD) is treated with systemic corticosteroid immunosuppression. Clinical response after one week of therapy often guides further treatment decisions, but long term outcomes vary widely between centers and more accurate predictive tests are urgently needed. We analyzed clinical data and blood samples taken after one week of systemic treatment for GVHD from 507 patients from 17 centers of the Mount Sinai Acute GVHD International Consortium (MAGIC), dividing them into test (n=236) and two validation cohorts separated in time (n = 142 and 129, respectively). Initial response to systemic steroids correlated with response at four weeks, one-year non-relapse mortality (NRM) and overall survival (OS). A previously validated algorithm of two MAGIC biomarkers (ST2 and REG3α) consistently separated steroid resistant patients into two groups with dramatically different NRM and OS (p<0.001 for all three cohorts). High biomarker probability, resistance to steroids and GVHD severity (Minnesota risk) were all significant predictors of NRM in multivariate analysis. A direct comparison of receiver operating curves showed the area under the curve for biomarker probability (0.82) was significantly greater than that for steroid response (0.68, p=0.004) and for Minnesota risk (0.72, p=0.005). In conclusion, MAGIC biomarker probabilities generated after one week of systemic treatment for GVHD predict long term outcomes in steroid resistant GVHD better than clinical criteria and should prove useful in developing better treatment strategies.
EVALuna2:34167

Malignant melanoma S3-guideline "diagnosis, therapy and follow-up of melanoma" - Pflugfelder, Annette; Kochs, Corinna; Blum, Andreas; Capellaro, Marcus; Czeschik, Christina; Dettenborn, Therese; Dill, Dorothee; Dippel, Edgar; Eigentler, Thomas; Feyer, Petra; Follmann, Markus; Frerich, Bernhard; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2013)
This first German evidence-based guideline for cutaneous melanoma was developed under the auspices of the German Dermatological Society (DDG) and the Dermatologic Cooperative Oncology Group (DeCOG) and funded by the German Guideline Program in Oncology. The recommendations are based on a systematic literature search, and on the consensus of 32 medical societies, working groups and patient representatives. This guideline contains recommendations concerning diagnosis, therapy and follow-up of melanoma. The diagnosis of primary melanoma based on clinical features and dermoscopic criteria. It is confirmed by histopathologic examination after complete excision with a small margin. For the staging of melanoma, the AJCC classification of 2009 is used. The definitive excision margins are 0.5 cm for in situ melanomas, 1 cm for melanomas with up to 2 mm tumor thickness and 2 cm for thicker melanomas, they are reached in a secondary excision. From 1 mm tumor thickness, sentinel lymph node biopsy is recommended. For stages II and III, adjuvant therapy with interferon-alpha should be considered after careful analysis of the benefits and possible risks. In the stage of locoregional metastasis surgical treatment with complete lymphadenectomy is the treatment of choice. In the presence of distant metastasis mutational screening should be performed for BRAF mutation, and eventually for CKIT and NRAS mutations. In the presence of mutations in case of inoperable metastases targeted therapies should be applied. Furthermore, in addition to standard chemotherapies, new immunotherapies such as the CTLA-4 antibody ipilimumab are available. Regular follow-up examinations are recommended for a period of 10 years, with an intensified schedule for the first three years.
EVALuna2:39292

Mammographic density as a risk factor for breast cancer in a German case-control study - Heusinger, Katharina; Löhberg, Christian; Häberle, Lothar; Jud, Sebastian; Klingsiek, Peter; Hein, Alexander; Bayer, Christian M.; Rauh, Claudia; Uder, Michael; May, Matthias; Adamietz, Boris; Schulz-Wendtland, Rüdiger; et al. (European Journal of Cancer Prevention, 2011)
Mammographic percent density (MD) is recognized as one of the strongest risk factors associated with breast cancer. This matched case-control study investigated whether MD represents an independent risk factor. Mammograms were obtained from 1025 breast cancer patients and from 520 healthy controls. MD was measured using a quantitative computer-based threshold method (0-100%). Breast cancer patients had a higher MD than healthy controls (38 vs. 32%, P<0.01). MD was significantly higher in association with factors such as age over 60 years, body mass index (BMI) of 25-30 kg/m, nulliparity or low parity (one to two births). Average MD was inversely associated with age, BMI, parity and positively associated with age at first full-term pregnancy. MD was higher in women with at least one first-degree relative affected, but only among patients and not in the group of healthy controls (P<0.01/P=0.61). In women with an MD of 25% or more, the risk of breast cancer was doubled compared with women with an MD of less than 10% (odds ratio: 2.1; 95% confidence interval: 1.3-3.4; P<0.01); in the postmenopausal subgroup, the risk was nearly tripled (odds ratio: 2.7; 95% confidence interval: 1.6-4.7; P<0.001). This study provides further evidence that MD is an important risk factor for breast cancer. These results indicate strong associations between MD and the risk of breast cancer in a matched case-control study in Germany © 2010 Wolters Kluwer Health.
CRIS-Team Scopus Importer:2021-07-19

Matched-paired analysis of patients treated for invasive mucormycosis: Standard treatment versus posaconazole new formulations (MoveOn) - Salmanton-Garcia, Jon; Seidel, Danila; Koehler, Philipp; Mellinghoff, Sibylle C.; Herbrecht, Raoul; Klimko, Nikolai; Racil, Zdenek; Falces-Romero, Iker; Ingram, Paul; Benitez-Penuela, Miguel-Angel; Yesid Rodriguez, Jose; Desoubeaux, Guillaume; et al. (Journal of Antimicrobial Chemotherapy, 2019)
Background: First-line antifungal treatment for invasive mucormycosis (IM) consists of liposomal amphotericin B. Salvage treatment options are limited and often based on posaconazole oral suspension. With the approval of posaconazole new formulations, patients could benefit from improved pharmacokinetics, safety and tolerability. Objectives: Our aim was to assess the effectiveness of posaconazole new formulations for IM treatment. Methods: We performed a case-matched analysis with proven or probable IM patients from the FungiScope® Registry. First-line posaconazole new formulations (1st-POSnew) and first-line amphotericin B plus posaconazole new formulations (1st-AMB+POSnew) cases were matched with first-line amphotericin B-based (1st-AMB) treatment controls. Salvage posaconazole new formulations (SAL-POSnew) cases were matched with salvage posaconazole oral suspension (SAL-POSsusp) controls. Each case was matched with up to three controls (based on severity, haematological/oncological malignancy, surgery and/or renal dysfunction). Results: Five patients receiving 1st-POSnew, 18 receiving 1st-AMB+POSnew and 22 receiving SAL-POSnew were identified. By day 42, a favourable response was reported for 80.0% (n=4/5) of patients receiving 1st-POSnew, for 27.8% (n=5/18) receiving 1st-AMB+POSnew and for 50.0% (n=11/22) receiving SAL-POSnew. Day 42 all-cause mortality of patients receiving posaconazole new formulations was lower compared with controls [20.0% (n=1/5) in 1st-POSnew versus 53.3% (n=8/15) in 1st-AMB; 33.3% (n=6/18) in 1st-AMB+POSnew versus 52.0% (n=26/50) in 1st-AMB; and 0.0% (n=0/22) in SAL-POSnew versus 4.4% (n=2/45) in SAL-POSsusp]. Conclusions: Posaconazole new formulations were effective in terms of treatment response and associated mortality of IM. While posaconazole new formulations may be an alternative for treatment of IM, the limited sample size of our study calls for a cautious interpretation of these observations.
Created from Fastlane, Scopus look-up

Measurement of immature platelets with Abbott CD-Sapphire and Sysmex XE-5000 in haematology and oncology patients - Meintker, Lisa; Haimerl, Maria; Ringwald, Juergen; Krause, Stefan (Clinical Chemistry and Laboratory Medicine, 2013)
Background: Measurement of immature platelets was introduced into routine diagnostics by Sysmex as immature platelet fraction (IPF) some years ago and recently by Abbott as reticulated platelet fraction (rPT). Here, we compare both methods. Methods: We evaluated the precision and agreement of these parameters between Sysmex XE-5000 and Abbott CD-Sapphire in three distinct thrombocytopaenic cohorts: 30 patients with beginning thrombocytopaenia and 64 patients with recovering platelets (PLT) after chemotherapy, 16 patients with immune thrombocytopaenia (ITP) or heparin-induced thrombocytopaenia type 2 (HIT) and 110 additional normal controls. Furthermore, we analysed, how IPF/rPT differed between these thrombocytopaenic cohorts and controls. Results: Both analysers demonstrated acceptable overall precision (repeatability) of IPF/rPT with lower precision at low PLT counts. IPF/rPT artificially increased during storage of blood samples overnight. Inter-instrument comparison showed a moderate correlation (Pearson rÂ0.38) and a systematic bias of 1.04 towards higher IPF-values with the XE-5000. IPF/rPT was highest in recovering thrombopoesis after chemotherapy and moderately increased in ITP/HIT. The normal range deduced from control samples was much narrower with CD-Sapphire (1.0%-3.8%, established here for the first time) in comparison to XE-5000 (0.8%-7.9%) leading to a smaller overlap of samples with increased PLT turnover and normal controls. Conclusions: IPF and rPT both give useful information on PLT turnover, although the two analysers only show a moderate inter-instrument correlation and have different reference ranges. A better separation of patient groups with high PLT turnover like ITP/HIT from normal controls is obtained by CD-Sapphire. © 2013 by Walter de Gruyter Berlin Boston.
Created from Fastlane, Scopus look-up
Keywords: heparin-induced thrombocytopaenia type 2 (HIT); immature platelet; immature platelet fraction (IPF); immune thrombocytopaenia (ITP); reticulated platelet; thrombocytopaenia

Measurements of immature platelets with haematology analysers are of limited value to separate immune thrombocytopenia from bone marrow failure - Cybulska, Annalina; Meintker, Lisa; Ringwald, Juergen; Krause, Stefan (British Journal of Haematology, 2017)
Detection of immature platelets in the circulation may help to dissect thrombocytopenia due to platelet destruction from bone marrow failure (BMF). We prospectively tested the predictive value of immature platelets, measured as immature platelet fraction (IPF) on the XE-5000 (Sysmex, Kobe, Japan) or percentage of reticulated platelets (rPT) on the CD Sapphire (Abbott Diagnostics, Santa Clara, CA, USA) to separate immune thrombocytopenia (ITP) from BMF (leukaemia, myelodysplastic syndrome, aplastic anaemia). We analysed 58 samples of patients with BMF, 47 samples of patients with ITP and 97 controls. Median rPT (CD Sapphire) was increased to 9·0% in ITP and to 10·9% in BMF, compared to 1·9% in controls. Median IPF (XE-5000) was 16·2% in ITP, 10·2% in BMF and 2·5% in controls. We found an inverse correlation between high fractions of immature platelets and low platelet counts in thrombocytopenic samples regardless of the diagnosis. In conclusion, we observed a broad overlap of immature platelets between ITP and BMF, which may be caused by an accelerated release of immature platelets in any thrombocytopenic state and decreased production in many patients with ITP. Despite this, IPF (XE-5000) had some power to discriminate ITP from BMF, whereas rPT (CD Sapphire) was of no predictive value.
EVALuna2:25762

Measuring the cellular memory B cell response after vaccination in patients after allogeneic stem cell transplantation - Winkler, Julia; Tittlbach, Hannes; Schneider, Andrea; Buchstaller, Corinna; Mayr, Andreas; Vasova, Ingrid; Rösler, Wolf; Mach, Michael; Mackensen, Andreas; Winkler, Thomas (Annals of Hematology, 2020)
After allogeneic hematopoietic stem cell transplantation (HSCT), patients are repetitively vaccinated to reduce the risk of infection caused by the immune deficiency following allogeneic HSCT. By the vaccination of transplanted patients, the humoral memory function can be restored in the majority of cases. It is unknown, however, to what extent memory B cells derived from the donor contribute to the mobilization of antibody-secreting cells and long-term humoral memory in patients after allogeneic HSCT. We therefore analyzed patients after allogeneic HSCT for memory B cell responses 7 days after single vaccination against tetanus toxoid (TT), diphtheria toxoid (DT), pertussis toxoid (PT), Haemophilus influenzae type b (Hib), and poliovirus. Patients showed an insufficient mobilization of plasmablasts (PB) after vaccination, whereas healthy subjects (HD, n = 13) exhibited a significant increase of PB in the peripheral blood. Regarding vaccine-specific antibody-secreting PB, all HD responded against all vaccine antigens, as expected. However, only 65% of the patients responded with a measurable increase in IgG-secreting PB against TT, 65% against DT, 33% against PT, and 53% against poliovirus. Correspondingly, the antibody titers on day 7 after vaccination did not increase in patients. A significant increase of serum titers for the vaccine antigens was detectable in the majority of patients only after repetitive vaccinations. In contrast to the low mobilization of vaccine-specific PB after vaccination, a high number of PB before vaccination was detectable in patients following allogeneic HSCT. High frequencies of circulating PB correlated with the incidence of moderate/severe chronic GVHD. In summary, patients showed a weak mobilization of antigen-specific PB and an inadequate increase in antibody titers 7 days after the first vaccination. Patients with moderate or severe chronic GVHD in their history had a significantly higher percentage of IgG-secreting PB prior to vaccination. The antigen specificity of these IgG-secreting PB is currently unknown.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Allogeneic stem cell transplantation; Memory B cells; Plasmablast; Vaccination after transplantation

Mechanistic Characterization of Tafasitamab-Mediated Antibody-Dependent Cellular Phagocytosis Alone or in Combination with Lenalidomide - Mougiakakos, Dimitrios; Völkl, Simon; Bach, Christian; Stoll, Andrej; Bitterer, Katrin; Beier, Fabian; Endell, Jan; Boxhammer, Rainer; Bittenbring, Joerg Thomas; Mackensen, Andreas; Bruns, Heiko (BLOOD, 2019)
CRIS-Team WoS Importer:2021-10-18

Medication safety in patients treated with new oral antitumor agents: A prospective, randomized investigation on the impact of intensified clinical pharmaceutical/clinical pharmacological care on patient safety, patient knowledge and patient well-being (AMBORA). Supported by the German Cancer Aid within the Comprehensive Cancer Center Erlangen-EMN - Schlichtig, Katja; Lechner, P.; Grafe, Carolin; Ferstl, B.; Fuchs, F.; Hein, Alexander; Meidenbauer, N.; Sell, C.; Semrau, S.; Pavel, Marianne Ellen; Wullich, Bernd; Neurath, Markus; et al. (2018)
EVALuna2:33795

Mesenchymal Stromal Cells Disrupt mTOR-Signaling and Aerobic Glycolysis During T-Cell Activation - Böttcher, Martin; Hofmann, Andreas D.; Bruns, Heiko; Haibach, Martina; Loschinski, Romy; Saul, Domenica; Mackensen, Andreas; Le Blanc, Katarina; Jitschin, Regina; Mougiakakos, Dimitrios (Stem Cells, 2016)
Mesenchymal stromal cells (MSCs) possess numerous regenerative and immune modulating functions. Transplantation across histocompatibility barriers is feasible due to their hypo-immunogenicity. MSCs have emerged as promising tools for treating graft-versus-host disease following allogeneic stem cell transplantation. It is well established that their clinical efficacy is substantially attributed to fine-tuning of T-cell responses. At the same time, increasing evidence suggests that metabolic processes control T-cell function and fate. Here, we investigated the MSCs' impact on the metabolic framework of activated T-cells. In fact, MSCs led to mitigated mTOR signaling. This phenomenon was accompanied by a weaker glycolytic response (including glucose uptake, glycolytic rate, and upregulation of glycolytic machinery) toward T-cell activating stimuli. Notably, MSCs express indoleamine-2,3-dioxygenase (IDO), which mediates T-cell suppressive tryptophan catabolism. Our observations suggest that IDO-induced tryptophan depletion interferes with a tryptophan-sufficiency signal that promotes cellular mTOR activation. Despite an immediate suppression of T-cell responses, MSCs foster a metabolically quiescent T-cell phenotype characterized by reduced mTOR signaling and glycolysis, increased autophagy, and lower oxidative stress levels. In fact, those features have previously been shown to promote generation of long-lived memory cells and it remains to be elucidated how MSC-induced metabolic effects shape in vivo T-cell immunity. Stem Cells 2016;34:516-52
EVALuna2:25707

Metabolic reprogramming of osteoclasts represents a therapeutic target during the treatment of osteoporosis - Taubmann, Jule; Krishnacoumar, Brenda; Böhm, Christina; Faas, Maria; Müller, Dorothea; Adam, Susanne; Stoll, Cornelia; Böttcher, Martin; Mougiakakos, Dimitrios; Sonnewald, Uwe; Hofmann, Jörg; Schett, Georg; et al. (Scientific Reports, 2020)
Osteoclasts are specialised bone resorbing cells that control both physiological and pathological bone turnover. Functional changes in the differentiation and activity of osteoclasts are accompanied by active metabolic reprogramming. However, the biological significance and the in vivo relevance of these events has remained unclear. Here we show that bone resorption of differentiated osteoclasts heavily relies on increased aerobic glycolysis and glycolysis-derived lactate production. While pharmacological inhibition of glycolysis did not affect osteoclast differentiation or viability, it efficiently blocked bone resorption in vitro and in vivo and consequently ameliorated ovariectomy-induced bone loss. Our experiments thus highlight the therapeutic potential of interfering with osteoclast-intrinsic metabolic pathways as possible strategy for the treatment of diseases characterized by accelerated bone loss.
CRIS-Team Scopus Importer:2020-12-11

Methodological Establishment of an in-vitro ADCC Assay by using patient-specific Immune Cells - Lehle, Sarah; Völkl, Simon; Rübner, Matthias; Emons, Julius; Seitz, Katharina; Beckmann, Matthias; Fasching, Peter; Hübner, Hanna (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Methylcholanthrene-Induced Sarcomas Develop Independently from NOX2-Derived ROS - Ligtenberg, Maarten A.; Cinar, Ozcan; Holmdahl, Rikard; Mougiakakos, Dimitrios; Kiessling, Rolf (PLoS ONE, 2015)
Reactive oxygen species (ROS) produced by the inducible NADPH oxidase type 2 (NOX2) complex are essential for clearing certain infectious organisms but may also have a role in regulating inflammation and immune response. For example, ROS is involved in myeloid derived suppressor cell (MDSC)- and regulatory T cell (T(reg)) mediated T- and NK-cell suppression. However, abundant ROS produced within the tumor microenvironment, or by the tumor itself may also yield oxidative stress, which can blunt anti-tumor immune responses as well as eventually leading to tumor toxicity. In this study we aimed to decipher the role of NOX2-derived ROS in a chemically (by methylcholanthrene (MCA)) induced sarcoma model. Superoxide production by NOX2 requires the p47(phox) (NCF1) subunit to organize the formation of the NOX2 complex on the cell membrane. Homozygous mutant mice (NCF1*/*) have a functional loss of their super oxide burst while heterozygous mice (NCF1*/+) retain this key function. Mice harboring either a homo- or a heterozygous mutation were injected intramuscularly with MCA to induce sarcoma formation. We found that NOX2 functionality does not determine tumor incidence in the tested MCA model. Comprehensive immune monitoring in tumor bearing mice showed that infiltrating immune cells experienced an increase in their oxidative state regardless of the NOX2 functionality. While MCA-induced sarcomas where characterized by a T(reg) and MDSC accumulation, no significant differences could be found between NCF1*/* and NCF1*/+ mice. Furthermore, infiltrating T cells showed an increase in effector-memory cell phenotype markers in both NCF1*/* and NCF1*/+ mice. Tumors established from both NCF1*/* and NCF1*/+ mice were tested for their in vitro proliferative capacity as well as their resistance to cisplatin and radiation therapy, with no differences being recorded. Overall our findings indicate that NOX2 activity does not play a key role in tumor development or immune cell infiltration in the chemically induced MCA sarcoma model.
EVALuna2:25721

Microarray Gene Expression Analysis to Evaluate Cell Type Specific Expression of Targets Relevant for Immunotherapy of Hematological Malignancies - Pont, M. J.; Honders, M. W.; Kremer, Anita; Van Kooten, C.; Out, C.; Hiemstra, P. S.; De Boer, H. C.; Jager, M. J.; Schmelzer, E.; Vries, R. G.; Al Hinai, A. S.; Kroes, W. G.; et al. (PLoS ONE, 2016)
Cellular immunotherapy has proven to be effective in the treatment of hematological cancers by donor lymphocyte infusion after allogeneic hematopoietic stem cell transplantation and more recently by targeted therapy with chimeric antigen or T-cell receptor-engineered T cells. However, dependent on the tissue distribution of the antigens that are targeted, anti-tumor responses can be accompanied by undesired side effects. Therefore, detailed tissue distribution analysis is essential to estimate potential efficacy and toxicity of candidate targets for immunotherapy of hematological malignancies. We performed microarray gene expression analysis of hematological malignancies of different origins, healthy hematopoietic cells and various non-hematopoietic cell types from organs that are often targeted in detrimental immune responses after allogeneic stem cell transplantation leading to graft-versus-host disease. Non-hematopoietic cells were also cultured in the presence of IFN-? to analyze gene expression under inflammatory circumstances. Gene expression was investigated by Illumina HT12.0 microarrays and quality control analysis was performed to confirm the cell-type origin and exclude contamination of non-hematopoietic cell samples with peripheral blood cells. Microarray data were validated by quantitative RT-PCR showing strong correlations between both platforms. Detailed gene expression profiles were generated for various minor histocompatibility antigens and B-cell surface antigens to illustrate the value of the microarray dataset to estimate efficacy and toxicity of candidate targets for immunotherapy. In conclusion, our microarray database provides a relevant platform to analyze and select candidate antigens with hematopoietic (lineage)-restricted expression as potential targets for immunotherapy of hematological cancers.
EVALuna2:25742

Microbiota-Derived Propionate Modulates Megakaryopoiesis and Platelet Function - Dürholz, Kerstin; Schmid, Eva; Frech, Michael; Azizov, Vugar; Otterbein, Nadine; Lucas, Sébastien; Rauh, Manfred; Schett, Georg; Bruns, Heiko; Zaiss, Mario (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is associated with an increased risk for cardiovascular events driven by abnormal platelet clotting effects. Platelets are produced by megakaryocytes, deriving from megakaryocyte erythrocyte progenitors (MEP) in the bone marrow. Increased megakaryocyte expansion across common autoimmune diseases was shown for RA, systemic lupus erythematosus (SLE) and primary Sjögren’s syndrome (pSS). In this context, we evaluated the role of the microbial-derived short chain fatty acid (SCFA) propionate on hematopoietic progenitors in the collagen induced inflammatory arthritis model (CIA) as we recently showed attenuating effects of preventive propionate treatment on CIA severity. In vivo, propionate treatment starting 21 days post immunization (dpi) reduced the frequency of MEPs in the bone marrow of CIA and naïve mice. Megakaryocytes numbers were reduced but increased the expression of the maturation marker CD61. Consistent with this, functional analysis of platelets showed an upregulated reactivity state following propionate-treatment. This was confirmed by elevated histone 3 acetylation and propionylation as well as by RNAseq analysis in Meg-01 cells. Taken together, we identified a novel nutritional axis that skews platelet formation and function.
CRIS-Team Scopus Importer:2022-08-05
Keywords: hematopoietic progenitors; megakaryocytes; microbiota; platelets; rheumatoid arthritis; short-chain fatty acids

Microbiota-derived propionate modulates megakaryopoiesis and platelet function - Schmid, Erik; Dürholz, Kerstin; Frech, Michael; Otterbein, N.; Lucas, Sébastien; Rauh, Manfred; Schett, Georg; Bruns, Heiko; Zaiss, Mario (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Microenvironmental Triggers Induce a Chemoresistant, Differentiated Subset of S100A8/A9(high) AML Cells Via the Jak/STAT3 Signaling Axis - Böttcher, Martin; Panagiotidis, Konstantinos; Mentz, Kristin; Völkl, Simon; Bruns, Heiko; Slany, Robert; Mackensen, Andreas; Mougiakakos, Dimitrios (BLOOD, 2019)
CRIS-Team WoS Importer:2021-10-18

Midkine is a tumor cell survival factor that displays metastatic and therapeutic resistance functions in uveal melanoma - Karg, Margarete; John, Lukas; Refaian, Narin; Büttner, Christian; Rottmar, Tanja; Sommer, Jonas; Bock, Barbara; Resheq, Yazid; Ksander, Bruce; Heindl, Ludwig M.; Mackensen, Andreas; Bosch, Jacobus (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Midkine Promotes Metastasis and Therapeutic Resistance via mTOR/RPS6 in Uveal Melanoma. - Karg, Margarete; John, Lukas; Refaian, Nasrin; Büttner, Christian; Rottmar, Tanja; Sommer, Jonas; Bock, Barbara; Resheq, Yazid; Ksander, Bruce R.; Heindl, Ludwig M.; Mackensen, Andreas; Bosch, Jacobus J. (Molecular Cancer Research, 2022)
Uveal melanoma is a rare form of melanoma that originates in the eye, exerts widespread therapeutic resistance, and displays an inherent propensity for hepatic metastases. Because metastatic disease is characterized by poor survival, there is an unmet clinical need to identify new therapeutic targets in uveal melanoma. Here, we show that the pleiotropic cytokine midkine is expressed in uveal melanoma. Midkine expression in primary uveal melanoma significantly correlates with poor survival and is elevated in patients that develop metastatic disease. Monosomy 3 and histopathologic staging parameters are associated with midkine expression. In addition, we demonstrate that midkine promotes survival, migration across a barrier of hepatic sinusoid endothelial cells and resistance to AKT/mTOR inhibition. Furthermore, midkine is secreted and mediates mTOR activation by maintaining phosphorylation of the mTOR target RPS6 in uveal melanoma cells. Therefore, midkine is identified as a uveal melanoma cell survival factor that drives metastasis and therapeutic resistance, and could be exploited as a biomarker as well as a new therapeutic target. IMPLICATIONS: Midkine is identified as a survival factor that drives liver metastasis and therapeutic resistance in melanoma of the eye.
EVALuna2:503899

Missing in action-The meaning of cell death in tissue damage and inflammation - Munoz Becerra, Luis; Leppkes, Moritz; Fuchs, Tobias A.; Hoffmann, Markus; Herrmann, Martin (Immunological Reviews, 2017)
Billions of cells die every day in higher organisms as part of the normal process of tissue homeostasis. During special conditions like in development, acute infections, mechanical injuries, and immunity, cell death is a common denominator and it exerts profound effects in the outcome of these scenarios. To prevent the accumulation of aged, superfluous, infected, damaged and dead cells, professional phagocytes act in a rapid and efficient manner to clear the battle field and avoid spread of the destruction. Neutrophils are the most abundant effector immune cells that extravasate into tissues and can turn injured tissues into gory battle fields. In peace times, neutrophils tend to patrol tissues without provoking inflammatory reactions. We discuss in this review actual and forgotten knowledge about the meaning of cell death during homeostatic processes and drive the attention to the importance of the action of neutrophils during patrolling and for the maintenance or recovery of the homeostatic state once the organism gets attacked or injured, respectively. In this fashion, we disclose several disease conditions that arise as collateral damage of physiological responses to death.
EVALuna2:13451

Mitochondrial metabolism contributes to oxidative stress and reveals therapeutic targets in chronic lymphocytic leukemia - Jitschin, Regina; Hofmann, Andreas D.; Bruns, Heiko; Gießl, Andreas; Bricks, Juliane; Berger, Jana; Saul, Domenica; Eckart, Michael J.; Mackensen, Andreas; Mougiakakos, Dimitrios (Blood, 2014)
Alterations of cellular metabolism represent a hallmark of cancer. Numerous metabolic changes are required for malignant transformation, and they render malignant cells more prone to disturbances in the metabolic framework. Despite the high incidence of chronic lymphocytic leukemia (CLL), metabolism of CLL cells remains a relatively unexplored area. The examined untreated CLL patients displayed a metabolic condition known as oxidative stress, which was linked to alterations in their lymphoid compartment. Our studies identified mitochondrial metabolism as the key source for abundant reactive oxygen species (ROS). Unlike in other malignant cells, we found increased oxidative phosphorylation in CLL cells but not increased aerobic glycolysis. Furthermore, CLL cells adapted to intrinsic oxidative stress by upregulating the stress-responsive heme-oxygenase-1 (HO-1). Our data implicate that HO-1 was, beyond its function as an antioxidant, involved in promoting mitochondrial biogenesis. Thus ROS, adaptation to ROS, and mitochondrial biogenesis appear to form a self-amplifying feedback loop in CLL cells. Taking advantage of the altered metabolic profile, we were able to selectively target CLL cells by PK11195. This benzodiazepine derivate blocks the mitochondrial F1F0-ATPase, leads to a surplus production of mitochondrial superoxide, and thereby induces cell death in CLL cells. Taken together, our findings depict how bioenergetics and redox characteristics could be therapeutically exploited in CL
EVALuna2:25687

Mitochondrial metabolism influences plasma cell differentiation - Urbanczyk, Sophia; Baris, O.; Reimer, Dorothea; Steinmetz, Tobit; Mougiakakos, Dimitrios; Wiesner, R.; Mielenz, Dirk (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Modified Risk-Stratified Sequential Treatment in B-Cell Post-Transplant Lymphoproliferative Disorder (PTLD) after Solid Organ Transplantation (SOT): The Prospective Multicenter Phase II PTLD-2 Trial - Zimmermann, Heiner; Koenecke, Christian; Dreyling, Martin H.; Pott, Christiane; Duhrsen, Ulrich; Hahn, Dennis; Meidenbauer, Norbert; Hauser, Ingeborg A.; Rummel, Mathias J.; Wolf, Dominik; Heuser, Michael; Schmidt, Christian; et al. (BLOOD, 2021)
CRIS-Team WoS Importer:2022-09-09

Modified risk-stratified sequential treatment (subcutaneous rituximab with or without chemotherapy) in B-cell Post-transplant lymphoproliferative disorder (PTLD) after Solid organ transplantation (SOT): the prospective multicentre phase II PTLD-2 trial - Zimmermann, Heiner; Koenecke, Christian; Dreyling, Martin H.; Pott, Christiane; Duehrsen, Ulrich; Hahn, Dennis; Meidenbauer, Norbert; Hauser, Ingeborg A.; Rummel, Mathias J.; Wolf, Dominik; Heuser, Michael; Schmidt, Christian; et al. (Leukemia, 2022)
The prospective multicentre Phase II PTLD-2 trial (NCT02042391) tested modified risk-stratification in adult SOT recipients with CD20-positive PTLD based on principles established in the PTLD-1 trials: sequential treatment and risk-stratification. After rituximab monotherapy induction, patients in complete remission as well as those in partial remission with IPI < 3 at diagnosis (low-risk) continued with rituximab monotherapy and thus chemotherapy free. Most others (high-risk) received R-CHOP-21. Thoracic SOT recipients who progressed (very-high-risk) received alternating R-CHOP-21 and modified R-DHAOx. The primary endpoint was event-free survival (EFS) in the low-risk group. The PTLD-1 trials provided historical controls. Rituximab was applied subcutaneously. Of 60 patients enrolled, 21 were low-risk, 28 high-risk and 9 very-high-risk. Overall response was 45/48 (94%, 95% CI 83-98). 2-year Kaplan-Meier estimates of time to progression and overall survival were 78% (95% CI 65-90) and 68% (95% CI 55-80) - similar to the PTLD-1 trials. Treatment-related mortality was 4/59 (7%, 95% CI 2-17). In the low-risk group, 2-year EFS was 66% (95% CI 45-86) versus 52% in the historical comparator that received CHOP (p = 0.432). 2-year OS in the low-risk group was 100%. Results with R-CHOP-21 in high-risk patients confirmed previous results. Immunochemotherapy intensification in very-high-risk patients was disappointing.
CRIS-Team WoS Importer:2022-08-26

Molecular characterization of TCF3::PBX1 chromosomal breakpoints in acute lymphoblastic leukemia and their use for measurable residual disease assessment - Burmeister, Thomas; Gröger, Daniela; Gökbuget, Nicola; Spriewald, Bernd; Starck, Michael; Elmaagacli, Ahmet; Hoelzer, Dieter; Keller, Ulrich; Schwartz, Stefan (Scientific Reports, 2023)
The translocation t(1;19)(q23;p13) with the resulting chimeric TCF3::PBX1 gene is the third most prevalent recurrent chromosomal translocation in acute lymphoblastic leukemia and accounts for 3–5% of cases. The molecular background of this translocation has been incompletely studied, especially in adult cases. We characterized the chromosomal breakpoints of 49 patients with TCF3::PBX1 and the corresponding reciprocal PBX1::TCF3 breakpoints in 15 cases at the molecular level, thus providing an extensive molecular overview of this translocation in a well-defined study patient population. Breakpoints were found to be remarkably clustered not only in TCF3 but also in PBX1. No association with DNA repeats or putative cryptic recombination signal sequence sites was observed. A simplified detection method for breakpoint identification was developed and the feasibility of patient-specific chromosomal break sites as molecular markers for detecting measurable residual disease (MRD) was explored. A highly sensitive generic real-time PCR for MRD assessment using these breakpoint sequences was established that could serve as a useful alternative to the classical method utilizing rearranged immune gene loci. This study provides the first extensive molecular data set on the chromosomal breakpoints of the t(1;19)/TCF3::PBX1 aberration in adult ALL. Based on the obtained data a generic MRD method was developed that has several theoretical advantages, including an on average higher sensitivity and a greater stability of the molecular marker in the course of disease.
CRIS-Team Scopus Importer:2023-09-22

Molecular profiling and clinical implications of patients with acute myeloid leukemia and extramedullary manifestations - Eckardt, Jan-Niklas; Stoelzel, Friedrich; Kunadt, Desiree; Roellig, Christoph; Stasik, Sebastian; Wagenfuehr, Lisa; Joehrens, Korinna; Kuithan, Friederike; Kraemer, Alwin; Scholl, Sebastian; Hochhaus, Andreas; Crysandt, Martina; et al. (Journal of Hematology & Oncology, 2022)
Background Extramedullary manifestations (EM) are rare in acute myeloid leukemia (AML) and their impact on clinical outcomes is controversially discussed. Methods We retrospectively analyzed a large multi-center cohort of 1583 newly diagnosed AML patients, of whom 225 (14.21%) had EM. Results AML patients with EM presented with significantly higher counts of white blood cells (p < 0.0001), peripheral blood blasts (p < 0.0001), bone marrow blasts (p = 0.019), and LDH (p < 0.0001). Regarding molecular genetics, EM AML was associated with mutations of NPM1 (OR: 1.66, p < 0.001), FLT3-ITD (OR: 1.72, p < 0.001) and PTPN11 (OR: 2.46, p < 0.001). With regard to clinical outcomes, EM AML patients were less likely to achieve complete remissions (OR: 0.62, p = 0.004), and had a higher early death rate (OR: 2.23, p = 0.003). Multivariable analysis revealed EM as an independent risk factor for reduced overall survival (hazard ratio [HR]: 1.43, p < 0.001), however, for patients who received allogeneic hematopoietic cell transplantation (HCT) survival did not differ. For patients bearing EM AML, multivariable analysis unveiled mutated TP53 and IKZF1 as independent risk factors for reduced event-free (HR: 4.45, p < 0.001, and HR: 2.05, p = 0.044, respectively) and overall survival (HR: 2.48, p = 0.026, and HR: 2.63, p = 0.008, respectively). Conclusion Our analysis represents one of the largest cohorts of EM AML and establishes key molecular markers linked to EM, providing new evidence that EM is associated with adverse risk in AML and may warrant allogeneic HCT in eligible patients with EM.
CRIS-Team WoS Importer:2022-06-03

Monitoring of hematopoietic chimerism by real-time quantitative PCR of micro insertions/deletions in samples with low DNA quantities - Bach, Christian; Tomova, Elmira; Goldmann, Katja; Weisbach, Volker Günter; Rösler, Wolf; Mackensen, Andreas; Winkler, Jürgen; Spriewald, Bernd M. (Transfusion Medicine and Hemotherapy, 2015)
Sensitive and accurate methods to detect hematopoietic chimerism after hematopoietic stem cell transplantation (HSCT) are essential to evaluate engraftment and to monitor response to therapeutic procedures such as donor lymphocyte infusion. Continuous long-term follow up, however, requires large amounts of pre-HSCT samples limiting the application of many widely used techniques for sensitive chimerism monitoring.DNAs from 42 normal healthy donors and 16 HSCT donor/recipient pairs were employed to validate the use of allele-specific insertion/deletion (indel) quantitative real-time polymerase chain reaction (qPCR) to quantify chimerism in samples with low amounts of DNA. Consequently, indel-qPCR analyses of samples from 16 HSCT patients were compared to short-tandem repeat (STR) specific PCR analyses.Typing with reduced amounts of input DNA (15 vs. 60 ng) allowed for the reliable distinction of positive (mean threshold cycle (ct) 28.05) and negative (ct >36) signals. The high informativity of primer/probe sets, with 12 out of 19 markers exceeding 20% informativity, was confirmed in our cohort (n = 74). Importantly, a fourfold reduction of input DNA compared to published protocols did not alter PCR efficiencies and allowed for a more sensitive detection of chimerism in 7 of 16 HSCT patients compared to results obtained by STR-PCR.Our data suggest that indel-qPCR is a more sensitive technique for the detection of hematopoietic chimerism compared to STR-PCR and works efficiently for samples with low amounts of DNA.
EVALuna2:15988

Monitoring of the immunometabolic profile of reconstituting leukocytes upon autologous peripheral blood stem cell transplantation - Richter, Swetlana; Jacobs, Benedikt; Böttcher, Martin; Stoll, Andrej; Böttcher-Loschinski, Romy; Mackensen, Andreas; Mougiakakos, Dimitrios (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Moonlighting osteoclasts as undertakers of apoptotic cells - Harre, Ulrike; Keppeler, Hildegard; Ipseiz, Natacha; Derer, Anja; Poller, Kerstin; Aigner, Michael; Schett, Georg; Herrmann, Martin; Lauber, Kirsten (Autoimmunity, 2012)
Created from Fastlane, Scopus look-up
Keywords: Apoptotic cell clearance; Dying cell clearance; Efferocytosis; Osteoclasts; Phagocytosis; Rheumatoid arthritis

MOR202, a novel anti-CD38 monoclonal antibody, in patients with relapsed or refractory multiple myeloma: a first-in-human, multicentre, phase 1–2a trial - Raab, Marc S.; Engelhardt, Monika; Blank, Antje; Goldschmidt, Hartmut; Agis, Hermine; Blau, Igor W.; Einsele, Hermann; Ferstl, Barbara; Schub, Natalie; Röllig, Christoph; Weisel, Katja; Winderlich, Mark; et al. (Lancet Haematology, 2020)
Background: Treatment of multiple myeloma is not curative, but targeting CD38 improves patient survival. To further explore this therapeutic approach, we investigated the safety and activity of MOR202, a novel monoclonal antibody targeting CD38, in patients with multiple myeloma. Methods: This is a multicentre, open-label, phase 1–2a trial done at ten hospitals in Germany and Austria. Enrolled patients were aged 18 years or older with relapsed or refractory multiple myeloma and Karnofsky performance status of 60% or higher. Patients were assigned to the different treatment regimens with MOR202 ranging between 0·01 mg/kg and 16 mg/kg in a 3 + 3 design. Dose-escalation and expansion was done either with MOR202 intravenous infusions alone (MOR202 q2w [twice a week] and q1w [weekly] groups) or in combination with dexamethasone (MOR202 with dexamethasone group), with dexamethasone plus pomalidomide (MOR202 with dexamethasone plus pomalidomide group) or plus lenalidomide (MOR202 with dexamethasone plus lenalidomide group). Primary endpoints were safety, MOR202 maximum tolerated dose (or recommended dose) and regimen, and immunogenicity. The primary analysis was assessed in the safety population, which included patients who received at least one dose of any study drug. This trial is registered with ClinicalTrials.gov, NCT01421186. Findings: Between Aug 24, 2011, and Aug 1, 2017, 91 patients were treated, 35 with MOR202 monotherapy, and 56 with MOR202 combination regimens (18 in the MOR202 with dexamethasone group, 21 in the MOR202 with dexamethasone plus pomalidomide group, and 17 in the MOR202 with dexamethasone plus lenalidomide group). MOR202 intravenous infusions were safely administered within 30 min. Infusion-related reactions occurred in 14 (40%) of 35 patients receiving MOR202 monotherapy without steroids, and in four (7%) of 56 patients receiving MOR202 combination treatment. MOR202 maximum tolerated dose was not reached and the recommended regimens were MOR202 administered as an intravenous infusion for 30 min at doses up to 16 mg/kg with dexamethasone (40 mg), or in combination with dexamethasone plus lenalidomide (25 mg) or pomalidomide (4 mg). 35 (38%) of 91 patients developed lymphopenia, 30 (33%) developed neutropenia, and 27 (30%) developed leukopenia; these were the most common grade 3 or higher treatment-emergent adverse events. Serious adverse events were reported in 51 (56%) of 91 patients. None of the deaths were associated with MOR202. One pomalidomide-associated death occurred in the MOR202 with dexamethasone plus pomalidomide group. No anti-MOR202 antibodies were detected in patients. Interpretation: MOR202 is safe and its clinical activity in patients with relapsed or refractory multiple myeloma is promising. Further clinical investigations of combinations with an immunomodulatory drug and dexamethasone are recommended. Funding: MorphoSys AG.
CRIS-Team Scopus Importer:2020-05-05

MOR202 with Low-Dose Dexamethasone (Dex) or Pomalidomide/Dex or Lenalidomide/Dex in Relapsed or Refractory Multiple Myeloma (RRMM): Primary Analysis of a Phase I/IIa, Multicenter, Dose-Escalation Study - Raab, Marc S.; Chatterjee, Manik; Goldschmidt, Hartmut; Agis, Hermine; Blau, Igor; Einsele, Hermann; Engelhardt, Monika; Ferstl, Barbara; Gramatzki, Martin; Rollig, Christoph; Weisel, Katja; Jarutat, Tiantom; et al. (BLOOD, 2018)
CRIS-Team WoS Importer:2019-03-06

More on CD19-CAR T Cells in Systemic Lupus Erythematosus - Mougiakakos, Dimitrios; Krönke, Gerhard; Schett, Georg (New England Journal of Medicine, 2021)
CRIS-Team WoS Importer:2021-11-12

Multidisciplinary Late Effects Clinics for Childhood Cancer Survivors in Germany - a Two-Center Study - Gebauer, Judith; Rieken, Sarah; Schuster, Sonja; Hahn, Birgit; Gebauer, Niklas; Meidenbauer, Norbert; Brabant, Georg; Metzler, Markus; Langer, Thorsten (Oncology Research and Treatment, 2018)
EVALuna2:34277

Multi-omics reveals clinically relevant proliferative drive associated with mTOR-MYC-OXPHOS activity in chronic lymphocytic leukemia - Lu, Junyan; Cannizzaro, Ester; Meier-Abt, Fabienne; Scheinost, Sebastian; Bruch, Peter-Martin; Giles, Holly A. R.; Lutge, Almut; Huellein, Jennifer; Wagner, Lena; Giacopelli, Brian; Nadeu, Ferran; Delgado, Julio; et al. (Nature Cancer, 2021)
Chronic lymphocytic leukemia (CLL) has a complex pattern of driver mutations and much of its clinical diversity remains unexplained. We devised a method for simultaneous subgroup discovery across multiple data types and applied it to genomic, transcriptomic, DNA methylation and ex vivo drug response data from 217 patients with CLL. We uncovered a biological axis of heterogeneity strongly associated with clinical behavior and orthogonal to known biomarkers. We validated its presence and clinical relevance in four independent cohorts (n = 547 patients). We found that this axis captures the proliferative drive (PD) of CLL cells, as it associates with lymphocyte doubling rate, global hypomethylation, accumulation of driver aberrations and response to pro-proliferative stimuli. CLL–PD was linked to the activation of mTOR–MYC–oxidative phosphorylation through transcriptomic, proteomic and single-cell resolution analysis. CLL–PD is a key determinant of disease outcome in CLL. Our multi-table integration approach may be applicable to other tumors whose inter-individual differences are currently unexplained.
CRIS-Team Scopus Importer:2021-07-16

Mutated IKZF1 is an independent marker of adverse risk in acute myeloid leukemia - Eckardt, Jan Niklas; Stasik, Sebastian; Röllig, Christoph; Petzold, Andreas; Sauer, Tim; Scholl, Sebastian; Hochhaus, Andreas; Crysandt, Martina; Brümmendorf, Tim H.; Naumann, Ralph; Steffen, Björn; Kunzmann, Volker; et al. (Leukemia, 2023)
Genetic lesions of IKZF1 are frequent events and well-established markers of adverse risk in acute lymphoblastic leukemia. However, their function in the pathophysiology and impact on patient outcome in acute myeloid leukemia (AML) remains elusive. In a multicenter cohort of 1606 newly diagnosed and intensively treated adult AML patients, we found IKZF1 alterations in 45 cases with a mutational hotspot at N159S. AML with mutated IKZF1 was associated with alterations in RUNX1, GATA2, KRAS, KIT, SF3B1, and ETV6, while alterations of NPM1, TET2, FLT3-ITD, and normal karyotypes were less frequent. The clinical phenotype of IKZF1-mutated AML was dominated by anemia and thrombocytopenia. In both univariable and multivariable analyses adjusting for age, de novo and secondary AML, and ELN2022 risk categories, we found mutated IKZF1 to be an independent marker of adverse risk regarding complete remission rate, event-free, relapse-free, and overall survival. The deleterious effects of mutated IKZF1 also prevailed in patients who underwent allogeneic hematopoietic stem cell transplantation (n = 519) in both univariable and multivariable models. These dismal outcomes are only partially explained by the hotspot mutation N159S. Our findings suggest a role for IKZF1 mutation status in AML risk modeling. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-12-01

Myc-Driven, Primary Mouse Lymphoma Expressing Human CD22 Are Highly Infiltrated By Syngeneic Immune Cells and Provide a Unique Model to Test CD22-Targeted Therapies - Wagner, Franziska; Brandl, Carolin; Emmerich, Charlotte; Mackensen, Andreas; Nitschke, Lars; Müller, Fabian (BLOOD, 2018)
CRIS-Team WoS Importer:2019-03-06

Mycobacterial lipopeptides elicit CD4+ CTLs in Mycobacterium tuberculosis-infected humans. - Bruns, Heiko; et al. (Journal of Immunology, 2008)
In searching for immunogenic molecules with the potential to induce protective immune responses against tuberculosis, we developed an ex vivo model to study frequency, phenotype, and effector functions of human T lymphocytes recognizing hydrophobic Ags of Mycobacterium tuberculosis (M.Tb). To obtain unbiased results, we characterized T lymphocytes responding to a crude cell wall extract (chloroform methanol extract of M.Tb (M.Tb-CME)) containing a broad spectrum of mycobacterial glycolipids and lipopeptides. A significant proportion of T lymphocytes recognized M.Tb-CME (290 IFN-gamma+ T cells/10(5) PBMCs) and developed to effector memory cells as determined by the expression of CD45RO and the chemokine receptors CXCR3 and CCR5. Expanded lymphocytes fulfilled all criteria required for an efficient immune response against tuberculosis: 1) release of macrophage-activating Th1 cytokines and chemokines required for the spatial organization of local immune responses, 2) cytolytic activity against Ag-pulsed macrophages, and 3) recognition of infected macrophages and killing of the intracellular bacteria. Phenotypically, M.Tb-CME-expanded cells were CD4+ and MHC class II restricted, challenging current concepts that cytotoxic and antimicrobial effector cells are restricted to the CD8+ T cell subset. Pretreatment of M.Tb-CME with protease or chemical delipidation abrogated the biological activity, suggesting that responses were directed toward mycobacterial lipopeptides. These findings suggest that lipidated peptides are presented by M.Tb-infected macrophages and elicit CD4+ cytolytic and antimicrobial T lymphocytes. Our data support an emerging concept to include hydrophobic microbial Ags in vaccines against tuberculosis.

Myeloperoxidase Modulates Inflammation in Generalized Pustular Psoriasis and Additional Rare Pustular Skin Diseases - Haskamp, Stefan; Bruns, Heiko; Hahn, Madelaine; Hoffmann, Markus; Gregor, Anne; Löhr, Sabine; Hahn, Jonas; Ringer, Mark; Flamann, Cindy; Frey, Benjamin; Lesner, Adam; Thiel, Christian; et al. (American Journal of Human Genetics, 2020)
Generalized pustular psoriasis (GPP) is a severe multi-systemic inflammatory disease characterized by neutrophilic pustulosis and triggered by pro-inflammatory IL-36 cytokines in skin. While 19%–41% of affected individuals harbor bi-allelic mutations in IL36RN, the genetic cause is not known in most cases. To identify and characterize new pathways involved in the pathogenesis of GPP, we performed whole-exome sequencing in 31 individuals with GPP and demonstrated effects of mutations in MPO encoding the neutrophilic enzyme myeloperoxidase (MPO). We discovered eight MPO mutations resulting in MPO -deficiency in neutrophils and monocytes. MPO mutations, primarily those resulting in complete MPO deficiency, cumulatively associated with GPP (p = 1.85E−08; OR = 6.47). The number of mutant MPO alleles significantly differed between 82 affected individuals and >4,900 control subjects (p = 1.04E−09); this effect was stronger when including IL36RN mutations (1.48E−13) and correlated with a younger age of onset (p = 0.0018). The activity of four proteases, previously implicated as activating enzymes of IL-36 precursors, correlated with MPO deficiency. Phorbol-myristate-acetate-induced formation of neutrophil extracellular traps (NETs) was reduced in affected cells (p = 0.015), and phagocytosis assays in MPO-deficient mice and human cells revealed altered neutrophil function and impaired clearance of neutrophils by monocytes (efferocytosis) allowing prolonged neutrophil persistence in inflammatory skin. MPO mutations contribute significantly to GPP's pathogenesis. We implicate MPO as an inflammatory modulator in humans that regulates protease activity and NET formation and modifies efferocytosis. Our findings indicate possible implications for the application of MPO inhibitors in cardiovascular diseases. MPO and affected pathways represent attractive targets for inducing resolution of inflammation in neutrophil-mediated skin diseases.
CRIS-Team Scopus Importer:2020-09-11
Keywords: ACH; acrodermatitis continua suppurativa Hallopeau; activation of IL-36 precursors; acute generalized 4 exanthematous pustulosis; AGEP; efferocytosis; generalized pustular psoriasis; GPP; impaired NETosis; MPO deficiency; myeloperoxidase; oligogenic inheritance

Natural NADH and FAD Autofluorescence as Label-Free Biomarkers for Discriminating Subtypes and Functional States of Immune Cells - Lemire, Sarah; Thoma, Oana-Maria; Kreiß, Lucas; Völkl, Simon; Friedrich, Oliver; Neurath, Markus; Schürmann, Sebastian; Waldner, Maximilian (International Journal of Molecular Sciences, 2022)
Immune cell activity is a major factor for disease progression in inflammatory bowel diseases (IBD). Classifying the type and functional state of immune cells is therefore crucial in clinical diagnostics of IBD. Label-free optical technologies exploiting NADH and FAD autofluorescence, such as multiphoton microscopy, have been used to describe tissue morphology in healthy and inflamed colon samples. Nevertheless, a strategy for the identification of single immune cell subtypes within the tissue is yet to be developed. This work aims to initiate an understanding of autofluorescence changes depending on immune cell type and activation state. For this, NADH and FAD autofluorescence signals of different murine immune cell subtypes under native conditions, as well as upon in vitro stimulation and cell death, have been evaluated. Autofluorescence was assessed using flow cytometry and multiphoton microscopy. Our results reveal significantly increased NADH and FAD signals in innate immune cells compared to adaptive immune cells. This allowed identification of relative amounts of neutrophils and CD4+ T cells in mixed cell suspensions, by using NADH signals as a differentiation marker. Furthermore, in vitro stimulation significantly increased NADH and FAD autofluorescence in adaptive immune cells and macrophages. Cell death induced a significant drop in NADH autofluorescence, while FAD signals were hardly affected. Taken together, these results demonstrate the value of autofluorescence as a tool to characterize immune cells in different functional states, paving the way to the label-free clinical classification of IBD in the future.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Cell autofluorescence; FAD; Flow cytometry; Immune cells; Inflammatory bowel diseases; Multiphoton microscopy; NADH

Natural T-cell ligands that are created by genetic variants can be transferred between cells by extracellular vesicles - Kremer, Anita; Zonneveld, Marijke I.; Kremer, Andreas E.; Van Der Meijden, Edith D.; Falkenburg, J. H. Frederik; Wauben, Marca H. M.; Nolte-'T Hoen, Esther N. M.; Griffioen, Marieke (European Journal of Immunology, 2018)
CD4 T-cells play a central role as helper cells in adaptive immunity. Presentation of exogenous antigens in MHC class II by professional antigen-presenting cells is a crucial step in induction of specific CD4 T-cells in adaptive immune responses. For efficient induction of immunity against intracellular threats such as viruses or malignant transformations, antigens from HLA class II-negative infected or transformed cells need to be transferred to surrounding antigen-presenting cells to allow efficient priming of naive CD4 T-cells. Here we show indirect antigen presentation for a subset of natural HLA class II ligands that are created by genetic variants and demonstrated that (neo)antigens can be transferred between cells by extracellular vesicles. Intercellular transfer by extracellular vesicles was not dependent on the T-cell epitope, but rather on characteristics of the full-length protein. This mechanism of (neo)antigen transfer from HLA class II-negative cells to surrounding antigen-presenting cells may play a crucial role in induction of anti-tumor immunity. This article is protected by copyright. All rights reserved.
EVALuna2:34446

Neoadjuvant concurrent chemoradiotherapy with and without hyperthermia in retroperitoneal sarcomas: feasibility, efficacy, toxicity, and long-term outcome - Willner, Alexander; Fechner, Katja; Agaimy, Abbas; Haller, Florian; Eckstein, Markus; Ott, Oliver; Putz, Florian; Gaipl, Udo; Kersting, S.; Meidenbauer, Norbert; Grützmann, Robert; Fietkau, Rainer; et al. (Strahlentherapie und Onkologie, 2021)
Purpose Retroperitoneal (RPS) sarcomas are associated with poor local and abdominal tumor control. However, the benefit of preoperative radio- or chemotherapy alone for these entities is currently unclear. Moreover, as intermediate- and high-grade sarcomas have a tendency toward early metastasis, exploration of neoadjuvant strategies is of high importance. This analysis reports the results of our 20-year single-institution experience with preoperative neoadjuvant concurrent chemoradiation. Methods From 2000-2019, 27 patients with intermediate- or high-grade RPS (12 dedifferentiated liposarcoma, 10 leiomyosarcoma, 5 others) were treated with radiotherapy (median dose: 50.4 Gy; range 45-75 Gy) and two cycles of chemotherapy (doxorubicin 50 mg/m(2) BSA/d3 q28 and ifosfamide 1.5 g/m(2) BSA/d1-5 q28) in neoadjuvant intent. Chemotherapy consisted of doxorubicin alone in two cases and ifosfamide alone in one case. Fifteen patients (56%) additionally received deep regional hyperthermia. Results The median follow-up time was 53 months (+/- 56.7 months). 92% of patients received two cycles of chemotherapy as planned and 92% underwent surgery. At 5 and 10 years, abdominal-recurrence-free survival was 74.6% (+/- 10.1%) and 66.3% (+/- 11.9%), distant metastasis-free survival was 67.2% (+/- 9.7%) and 59.7% (+/- 11.1%), and overall survival was 60.3% (+/- 10.5%) and 60.3% (+/- 10.5%), respectively. CTC grade III and IV toxicities were leukocytopenia (85%), thrombocytopenia (33%), and anemia (11%). There were no treatment-related deaths. Conclusion Neoadjuvant chemoradiotherapy with and without hyperthermia for retroperitoneal sarcomas is feasible and provided high local control of intermediate- and high-grade sarcoma.
CRIS-Team WoS Importer:2021-11-12

Neue antikörperbasierte Therapien in der Hämatologie - Müller, Fabian (Best Practice Onkologie, 2021)
Antibody-based therapies are increasingly used as targeted therapy that combine strong on-target effects with relatively low side effects by sparing antigen-negative tissue. Focusing on the idea of target-mediated therapy, antibodies alone but also antibodies conjugated to an effector such as antibody–drug conjugates, fusion proteins, bispecific antibodies, or chimeric antigen receptor (CAR-) T cells will be discussed. Side effects, however, can sometimes be substantial and sometimes affect unexpected organs. We aim to discuss newly approved therapeutic antibodies, to highlight clinical efficacy, and to create a general understanding of the mechanisms of action. Given the large number of new antibody-based therapies, it is not possible to address every newly approved substance in detail and only the most important clinical studies are cited. We assess side effects of antibody therapies and discuss their clinical management. This article highlights a rapidly increasing number of therapeutic antibodies with the promise of a substantial improvement of standard of care treatment. The aim of this article is to provide an overview of approved therapy options and new therapy concepts. A general understanding of the mechanisms of action should be conveyed for the substance groups based on a selection of clinically relevant therapeutic agents. General side effects are then derived from the general and specific active principles and their clinical management is discussed. With this knowledge, side effects of substances that will be approved in the future as well as useful combinations of the rapidly increasing number of therapeutic antibodies can be anticipated.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Antibody-drug conjugate; Bispecific antibodies; CAR T‑cell therapy; Immunotoxins; Molecular targeted therapy

Neurosurgical Treatment of Acromegaly - Buchfelder, Michael; Feulner, Julian (Progress in Nucleic Acid Research and Molecular Biology, 2016)
Surgical removal of as much tumor mass as possible is usually considered the first step of treatment in acromegaly, unless the patients are unfit for surgery or refuse an operation. To date, in almost all cases, minimally invasive, transsphenoidal microscopic or endoscopic approaches are used. Whether a curative approach is feasible or a debulking procedure is planned, can be anticipated on the basis of preoperative magnetic resonance imaging. It mostly depends on localization, size, and the invasive character of the lesion. The surgical results depend on tumor-related factors such as size, extension, the presence or absence of invasion, and the magnitude of IGF-1 and growth hormone oversecretion, respectively. However, even surgeon-related factors such as experience and case load of the centers have been shown to strongly affect surgical results and complication rates. A reoperation can be considered at various stages in the treatment algorithm. There are several new technical gadgets which might aid in the surgical procedure: navigation, the Doppler probe, and variants of intraoperative imaging.
EVALuna2:33862

Neutrophil extracellular traps drive epithelial‐mesenchymal transition of human colon cancer - Stehr, Antonia; Wang, Guangxia; Demmler, Richard; Stemmler, Marc; Straube, Julia; Tripal, Philipp; Schmid, Benjamin; Geppert, Carol-Immanuel; Hartmann, Arndt; Munoz, Luis Enrique; Schoen, Janina; Völkl, Simon; et al. (Journal of Pathology, 2021)
Neutrophil extracellular traps (NETs) are extracellular structures, composed of nuclear DNA and various proteins released from neutrophils. Evidence is growing that NETs exert manifold functions in infection, immunity, and cancer. Recently, NETs have been detected in colorectal cancer (CRC) tissues but their association with disease progression and putative functional impact on tumourigenesis remained elusive. Using high-resolution stimulated emission depletion (STED) microscopy we showed that citrullinated histone H3 (H3cit) is sufficient to specifically detect citrullinated NETs in colon cancer tissues. Among other evidence this was supported by the close association of H3cit with de-condensed extracellular DNA, the hallmark of NETs. Extracellular DNA was reliably differentiated from nuclear condensed DNA by staining with an anti-DNA-antibody providing a novel and valuable tool to detect NETs in FFPE tissues. Using these markers, the clinical association of NETs has been investigated in a cohort of 85 patients with colon cancer. NETs were frequently detected (n = 37/n = 85, 44%) in colon cancer tissue sections and preferentially localized either only in the tumour centre or both, in the tumour centre and the invasive front. Of note, citrullinated NETs were significantly associated with high histopathologic tumour grades and lymph node metastasis. In vitro, purified NETs induced filopodia formation and cell motility in CRC cell lines. This was associated with increased expression of mesenchymal marker mRNAs (vimentin [VIM], fibronectin [FN1]) and epithelial- mesenchymal transition (EMT) promoting transcription factors (ZEB1 and Slug [SNAI2]) as well as decreased expression of the epithelial markers E-cadherin (CDH1) and EpCAM (EPCAM). These findings indicated that NETs activate an EMT-like process in CRC cells and may contribute to the metastatic progression of CRC.

Neutrophil Extracellular Traps Initiate Gallstone Formation - Munoz, Luis Enrique; Boeltz, Sebastian; Bilyy, Rostyslav; Schauer, Christine; Mahajan, Aparna; Widulin, Navena; Grüneboom, Anika; Herrmann, Irmgard; Boada, Edgyda; Rauh, Manfred; Krenn, Veit; Biermann, Mona H.C.; et al. (Immunity, 2019)
The presence of gallstones (cholelithiasis) is a highly prevalent and severe disease and one of the leading causes of hospital admissions worldwide. Due to its substantial health impact, we investigated the biological mechanisms that lead to the formation and growth of gallstones. We show that gallstone assembly essentially requires neutrophil extracellular traps (NETs). We found consistent evidence for the presence of NETs in human and murine gallstones and describe an immune-mediated process requiring activation of the innate immune system for the formation and growth of gallstones. Targeting NET formation via inhibition of peptidyl arginine deiminase type 4 or abrogation of reactive oxygen species (ROS) production, as well as damping of neutrophils by metoprolol, effectively inhibit gallstone formation in vivo. Our results show that after the physicochemical process of crystal formation, NETs foster their assembly into larger aggregates and finally gallstones. These insights provide a feasible therapeutic concept to prevent cholelithiasis in patients at risk.
CRIS-Team Scopus Importer:2019-09-17
Keywords: calcium carbonate crystals; cholesterol crystals; gallstone growth; gallstones; lisosomal leakage; lithogenic diet; neutrophil extracellular traps; neutrophils; NOX2; PADi4

Neutrophil Extracellular Traps Promote the Development and Growth of Human Salivary Stones - Schapher, Mirco; Koch, Michael; Weidner, Daniela; Scholz, Michael; Wirtz, Stefan; Mahajan, Aparna; Herrmann, Irmgard; Singh, Jeeshan; Knopf, Jasmin; Leppkes, Moritz; Grüneboom, Anika; Alexiou, Christoph; et al. (Cells, 2020)
Salivary gland stones, or sialoliths, are the most common cause of the obstruction of salivary glands. The mechanism behind the formation of sialoliths has been elusive. Symptomatic sialolithiasis has a prevalence of 0.45% in the general population, is characterized by recurrent painful periprandial swelling of the affected gland, and often results in sialadenitis with the need for surgical intervention. Here, we show by the use of immunohistochemistry, immunofluorescence, computed tomography (CT) scans and reconstructions, special dye techniques, bacterial genotyping, and enzyme activity analyses that neutrophil extracellular traps (NETs) initiate the formation and growth of sialoliths in humans. The deposition of neutrophil granulocyte extracellular DNA around small crystals results in the dense aggregation of the latter, and the subsequent mineralization creates alternating layers of dense mineral, which are predominantly calcium salt deposits and DNA. The further agglomeration and appositional growth of these structures promotes the development of macroscopic sialoliths that finally occlude the efferent ducts of the salivary glands, causing clinical symptoms and salivary gland dysfunction. These findings provide an entirely novel insight into the mechanism of sialolithogenesis, in which an immune system-mediated response essentially participates in the physicochemical process of concrement formation and growth.
CRIS-Team Scopus Importer:2020-10-09
Keywords: lithogenesis; neutrophil extracellular traps; neutrophils; salivary glands; salivary stones; sialadenitis; sialolithiasis; stone development; stone growth

Neutrophil-to-Lymphocyte Ratio Is an Independent Predictor for In-Hospital Mortality in Spontaneous Intracerebral Hemorrhage - Giede-Jeppe, Antje; Bobinger, Tobias; Gerner, Stefan; Sembill, Jochen; Sprügel, Maximilian; Beuscher, Vanessa D.; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen; Hölter, Philip (Cerebrovascular Diseases, 2017)
Stroke-associated immunosuppression and inflammation are increasingly recognized as factors that trigger infections and thus, potentially influence the outcome after stroke. Several studies demonstrated that elevated neutrophil-to-lymphocyte ratio (NLR) is a significant predictor of adverse outcomes in patients with ischemic stroke. However, little is known about the impact of NLR on short-term mortality in intracerebral hemorrhage (ICH).This observational study included 855 consecutive ICH-patients. Patient demographics, clinical, laboratory, and in-hospital measures as well as neuroradiological data were retrieved from institutional databases. Functional 3-months-outcome was assessed and categorized as favorable (modified Rankin Scale [mRS] 0-3) and unfavorable (mRS 4-6). We (i) studied the natural course of NLR in ICH, (ii) analyzed parameters associated with NLR on admission (NLROA), and (iii) evaluated the clinical impact of NLR on mortality and functional outcome.The median NLROA of the entire cohort was 4.66 and it remained stable during the entire hospital stay. Patients with NLR >=4.66 showed significant associations with poorer neurological status (National Institute of Health Stroke Scale [NIHSS] 18 [9-32] vs. 10 [4-21]; p < 0.001), larger hematoma volume on admission (17.6 [6.9-47.7] vs. 10.6 [3.8-31.7] mL; p = 0.001), and more frequently unfavorable outcome (mRS 4-6 at 3 months: 317/427 [74.2%] vs. 275/428 [64.3%]; p = 0.002). Patients with an NLR under the 25th percentile (NLR <2.606) - compared to patients with NLR >2.606 - presented with a better clinical status (NIHSS 12 [5-21] vs. 15 [6-28]; p = 0.005), lower hematoma volumes on admission (10.6 [3.6-30.1] vs. 15.1 [5.7-42.3] mL; p = 0.004) and showed a better functional outcome (3 months mRS 0-3: 82/214 [38.3%] vs. 185/641 [28.9%]; p = 0.009). Patients associated with high NLR (>=8.508 = above 75th-percentile) showed the worst neurological status on admission (NIHSS 21 [12-32] vs. 12 [5-23]; p < 0.001), larger hematoma volumes (21.0 [8.6-48.8] vs. 12.2 [4.1-34.9] mL; p < 0.001), and higher proportions of unfavorable functional outcome at 3 months (mRS 4-6: 173/214 vs. 418/641; p < 0.001). Further, NLR was linked to more frequently occurring infectious complications (pneumonia 107/214 vs. 240/641; p = 0.001, sepsis: 78/214 vs. 116/641; p < 0.001), and increased c-reactive-protein levels on admission (p < 0.001; R2 = 0.064). Adjusting for the above-mentioned baseline confounders, multivariable logistic analyses revealed independent associations of NLROA with in-hospital mortality (OR 0.967, 95% CI 0.939-0.997; p = 0.029).NLR represents an independent parameter associated with increased mortality in ICH patients. Stroke physicians should focus intensely on patients with increased NLR, as these patients appear to represent a population at risk for infectious complications and increased short-mortality. Whether these patients with elevated NLR may benefit from a close monitoring and specially designed therapies should be investigated in future studies.
EVALuna2:22531

New Aspects of an Old Drug - Diclofenac Targets MYC and Glucose Metabolism in Tumor Cells - Gottfried, Eva; Lang, Sven A.; Renner, Kathrin; Bosserhoff, Anja; Gronwald, Wolfram; Rehli, Michael; Einhell, Sabine; Gedig, Isabel; Singer, Katrin; Seilbeck, Anton; Mackensen, Andreas; Grauer, Oliver; et al. (PLoS ONE, 2013)
Non-steroidal anti-inflammatory drugs such as diclofenac exhibit potent anticancer effects. Up to now these effects were mainly attributed to its classical role as COX-inhibitor. Here we show novel COX-independent effects of diclofenac. Diclofenac significantly diminished MYC expression and modulated glucose metabolism resulting in impaired melanoma, leukemia, and carcinoma cell line proliferation in vitro and reduced melanoma growth in vivo. In contrast, the non-selective COX inhibitor aspirin and the COX-2 specific inhibitor NS-398 had no effect on MYC expression and glucose metabolism. Diclofenac significantly decreased glucose transporter 1 (GLUT1), lactate dehydrogenase A (LDHA), and monocarboxylate transporter 1 (MCT1) gene expression in line with a decrease in glucose uptake and lactate secretion. A significant intracellular accumulation of lactate by diclofenac preceded the observed effect on gene expression, suggesting a direct inhibitory effect of diclofenac on lactate efflux. While intracellular lactate accumulation impairs cellular proliferation and gene expression, it does not inhibit MYC expression as evidenced by the lack of MYC regulation by the MCT inhibitor α-cyano-4-hydroxycinnamic acid. Finally, in a cell line with a tetracycline-regulated c-MYC gene, diclofenac decreased proliferation both in the presence and absence of c-MYC. Thus, diclofenac targets tumor cell proliferation via two mechanisms, that is inhibition of MYC and lactate transport. Based on these results, diclofenac holds potential as a clinically applicable MYC and glycolysis inhibitor supporting established tumor therapies. © 2013 Gottfried et al.
CRIS-Team Scopus Importer:2022-08-05

New insights into the interaction of Mycobacterium tuberculosis and human macrophages - Bruns, Heiko; Stenger, Steffen (Future Microbiology, 2014)
Mycobacterium tuberculosis is a facultative intracellular pathogen. It infects macrophages where it avoids elimination by interfering with host defense mechanisms. Until recently, it was assumed that the acidification of phagosomes is the major strategy of macrophages to eliminate M. tuberculosis. However, there is emerging evidence demonstrating that human macrophages are equipped with additional antimicrobial effector functions. Specifically, autophagy, efferocytosis and antimicrobial peptides have been identified as mechanisms to restrict mycobacterial proliferation. Here we review recent findings on effector functions of human macrophages and mechanisms of the pathogen to interfere with the
EVALuna2:25690

New Oral Antitumor Drugs and Medication Safety in Uro-Oncology: Implications for Clinical Practice Based on a Subgroup Analysis of the AMBORA Trial - Schlichtig, Katja; Cuba, Lisa; Dürr, Pauline; Bellut, Laura; Meidenbauer, Norbert; Kunath, Frank; Goebell, Peter; Mackensen, Andreas; Dörje, Frank; Fromm, Martin; Wullich, Bernd (Journal of Clinical Medicine, 2022)
Oral antitumor therapeutics (OAT) bear a high risk for medication errors, e.g., due to drug-drug or drug-food interactions or incorrect drug intake. Advanced age, organ insufficiencies, and polymedication are putting uro-oncological patients at an even larger risk. This analysis sets out to (1) investigate the frequency and relevance of medication errors in patients with prostate cancer or renal cell carcinoma treated with OAT and (2) compile recommendations for clinical practice. This post-hoc subgroup analysis used data collected in the randomized AMBORA trial (2017-2020; DRKS00013271). Clinical pharmacologists/pharmacists conducted advanced medication reviews over 12 weeks after initiation of a new oral regimen and assessed the complete medication process for drug-related problems. Medication errors related to either the OAT, prescribed or prescription-free concomitant medication, or food were classified regarding cause and severity. We identified 67 medication errors in 38 patients within the complete medication within 12 weeks. Thereof, 55% were detected at therapy initiation, 27% were caused by the patients, and 25% were drug-drug or drug-food interactions. Problem-prone issues are summarized in a 'medication safety table' to provide recommendations for clinical practice in uro-oncology. Tailored strategies including intensified care by clinical pharmacologists/pharmacists should be implemented in clinical practice to improve medication safety.
CRIS-Team WoS Importer:2022-08-26

New Therapeutic Approaches in Inflammatory Diseases of the Eye - Targeting Lymphangiogenesis and Cellular Immunity: Research Unit FOR 2240 Presents Itself - Cursiefen, Claus; Bock, Felix; Clahsen, Thomas; Regenfuss, Birgit; Reis, André; Steven, Philipp; Heindl, Ludwig M.; Bosch, Jacobus J.; Hos, Deniz; Eming, Sabine; Grajewski, Rafael; Heiligenhaus, Arnd; et al. (Klinische Monatsblätter für Augenheilkunde, 2017)
Background Ophthalmology, principally, is a very successful subdiscipline in medicine. Nonetheless, there are still unmet medical needs which necessitate translational research. Methods The funding instrument of a Research Unit (RU) of the German Research Foundation (DFG) is presented as exemplified by the RU 2240 at the Department of Ophthalmology at the University of Cologne. Results The Research Unit integrates different research groups working on pathologic ocular inflammation, macrophages/microglia and (lymph)angiogenesis to collaborate in a synergistic way. Rotation positions allow young clinicians to rotate into research labs for a defined period of time. A Research Unit is also a powerful strategic tool to strengthen clinical and experimental ophthalmology at individual medical faculties. Conclusions The funding instrument of a Research Unit is highly suitable for fostering translational research in a medical subdiscipline such as ophthalmology, supporting the next generation of (clinician) scientists in ophthalmology and finding new cures for our patients.
EVALuna2:9372

N-glycosylation controls inflammatory licensing-triggered PD-L1 upregulation in human mesenchymal stromal cells - Strauch, Vivien; Saul, Domenica; Berisha, Mirjeta; Mackensen, Andreas; Mougiakakos, Dimitrios; Jitschin, Regina (Stem Cells, 2020)
Mesenchymal stromal cells (MSCs) are characterized by their multipotency, regenerative potential, and immunoregulatory properties. Nowadays, MSCs represent a promising cell-therapeutic option for hyperinflammatory conditions such as graft-vs-host disease following allogeneic hematopoietic stem cell transplantation. A better understanding of their biology is a prerequisite for improving their treatment efficacy. Emerging evidence suggests that immunosuppressive properties are not constitutively active in MSCs. Instead, microenvironmental inflammatory stimuli such as the cytokines interferon (IFN)-γ or tumor necrosis factor (TNF)-α license MSCs to acquire a tolerance-promoting phenotype. The immunological checkpoint molecule programmed death-ligand 1 (PD-L1) is an important regulator of T-cell responses. Binding of PD-L1 to the programmed cell death protein 1 (PD-1) receptor on T cells suppresses their activation, proliferation, and induces apoptosis. Previous studies have revealed that cell surface expression and secretion of PD-L1 are part of the MSCs' immunomodulatory armamentarium. Here, we report that inflammatory licensing leads to an enhanced PD-L1 cell surface expression and secretion, which are both accompanied by an increased posttranslational protein N-glycosylation. These post-translational modifications have been shown to be critical for key biological processes such as cell trafficking, receptor signaling, and immunohomeostasis. In fact, promoting N-glycosylation in MSCs yielded increased PD-L1 levels. We report for the first time that PD-L1 N-glycosylation plays a decisive role for its transport to the MSCs' cell surface and its subsequent secretion (in response to proinflammatory trigger). Our data offer insights into a novel regulatory mechanism with the potential to be exploited as a means to foster the immunosuppressive potency of human MSCs. © AlphaMed Press 2020 SIGNIFICANCE STATEMENT: Mesenchymal stromal cells (MSCs) possess immunoregulatory properties and are hypoimmunogenic. These characteristics of MSCs make them promising candidates for cell therapeutic approaches in hyperinflammatory conditions such as graft-vs-host disease following allogeneic stem cell transplantation. This study shows that inflammatory stimuli promote expression and secretion of PD-L1 in human MSCs. It reveals for the first time that this adaptive process is accompanied by an enhanced N-glycosylation, which is a prerequisite for PD-L1 to be transported to the cell surface and to be secreted. Therefore, promoting N-glycosylation could be explored as a means to improve the MSCs' therapeutic efficacy.
EVALuna2:216179

N-glycosylation controls inflammatory licensing-triggered PD-L1 upregulation in human mesenchymal stromal cells - Strauch, Vivien; Saul, Domenica; Mackensen, Andreas; Jitschin, R.; Mougiakakos, Dimitrios (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Nilotinib combined with interleukin-2 mediates antitumor and immunological effects in a B16 melanoma model - Geisler, K.; Reischer, Anna; Kroeger, I.; Jacobs, B.; Meinhardt, K.; Bauer, R.; Ryffel, B.; Mackensen, Andreas; Ullrich, E. (Oncology Reports, 2014)
The immune system contributes to tumor cell killing which can be enhanced by cancer chemotherapeutics and immune modulatory pharmaceuticals such as tyrosine kinase inhibitors (TKIs). Recently, the beneficial effect of natural killer (NK) cells was demonstrated when combining interleukin-2 (IL-2) with the TKI imatinib. The aim of the present study was to address the antitumor and immunological effects of recently approved TKIs. Therefore, we focused on the comparison of the efficacy between imatinib and nilotinib in combination with IL-2 in a murine B16F10 melanoma model. Both TKIs possessed antitumor activity in vivo. However, the combination of nilotinib and IL-2 showed a superior outcome. Importantly, both the use of immunodeficient Rag2?c-/- mice, which lack T-lymphocytes, B-lymphocytes and NK cells, as well as NK cell-depletion in C57Bl/6 mice reduced the therapeutic effect of nilotinib. Flow cytometry revealed a significant increase in the IFN-?-producing CD27+ NK cell subpopulation following treatment with nilotinib and IL-2. Furthermore, the therapeutic antitumor effect of nilotinib/IL-2 was completely lost in IFN-?-/- mice. In summary, we suggest that nilotinib combined with IL-2 confers high antitumor activity involving the subset of IFN-?-producing CD27+ NK cells. These new insights are of high importance for the understanding and development of immunotherapeutic protocols using TKIs.
EVALuna2:25694

Nilotinib (NIL) vs. NIL Plus Pegylated Interferon alpha2B (IFN) Induction and NIL or IFN Maintenance Therapy for Newly Diagnosed BCR-ABL1+Chronic Myeloid Leukemia (CML) Patients (PTS) in Chronic Phase - Ernst, Thomas; Saussele, Susanne; Burchert, Andreas; Baerlocher, Gabriela Maria; Bruemmendorf, Tim Henrik; La Rosee, Paul Graf; Heim, Dominik; Krause, Stefan; Le Coutre, Philipp; Niederwieser, Dietger; Lange, Thoralf; Haenel, Mathias; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Nilotinib Vs Nilotinib Plus Pegylated Interferon-alpha2b Induction and Nilotinib or Pegylated Interferon-alpha2b Maintenance Therapy for Newly Diagnosed BCR-ABL plus Chronic Myeloid Leukemia Patients in Chronic Phase: Interim Analysis of the Tiger (CML V)-Study - Hochhaus, Andreas; Saussele, Susanne; Baerlocher, Gabriela M.; Bruemmendorf, Tim H.; Burchert, Andreas; La Rosee, Paul; Hasford, Joerg; Hehlmann, Ruediger; Heim, Dominik; Krause, Stefan; Le Coutre, Philipp; Niederwieser, Dietger; et al. (BLOOD, 2018)
CRIS-Team WoS Importer:2019-03-06

Nilotinib Vs Nilotinib Plus Pegylated Interferon a (Peg-IFN) Induction and Nilotinib or Peg-IFN Maintenance Therapy for Newly Diagnosed BCR-ABL1 Positive Chronic Myeloid Leukemia Patients in Chronic Phase (TIGER Study): The Addition of Peg-IFN Is Associated with Higher Rates of Deep Molecular Response - Hochhaus, Andreas; Burchert, Andreas; Saussele, Susanne; Baerlocher, Gabriela M.; Brummendorf, Tim H.; Rosee, Paul La; Heim, Dominik; Krause, Stefan; Le Coutre, Philipp D.; Niederwieser, Dietger; Lange, Thoralf; Fabarius, Alice; et al. (BLOOD, 2019)
CRIS-Team WoS Importer:2021-10-18

NK cell metabolism is altered in early relapsing/refractory lymphoma patients upon autologous stem cell transplantation - Jacobs, Benedikt; Richter, Steffi; Böttcher, Martin; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

NK Cell Subgroups, Phenotype, and Functions After Autologous Stem Cell Transplantation - Jacobs, Benedikt; Tognarelli, Sara; Poller, Kerstin; Bader, Peter; Mackensen, Andreas; Evelyn, Ullrich (Frontiers in Immunology, 2015)
High-dose chemotherapy with consecutive autologous stem cell transplantation (autoSCT) is a well-established treatment option for patients suffering from malignant lymphoma or multiple myeloma. Natural killer (NK) cells are an important part of the immune surveillance, and their cell number after autoSCT is predictive for progression-free and overall survival. To improve knowledge about the role of NK cells after autoSCT, we investigated different NK cell subgroups, their phenotype, and their functions in patients treated with autoSCT. Directly after leukocyte regeneration (>1000 leukocytes/?l) following autoSCT, CD56(++) NK cells were the major NK cell subset. Surprisingly, these cells showed unusually high surface expression levels of CD57 and killer Ig-like receptors (KIRs) compared to expression levels before or at later time points after autoSCT. Moreover, these NK cells strongly upregulated KIR2DL2/3/S2 and KIR3DL1, whereas KIR2DL1/S1 remained constant, indicating that this cell population arose from more immature NK cells instead of from activated mature ones. Remarkably, NK cells were already able to degranulate and produce IFN-? and MIP-1? upon tumor interaction early after leukocyte regeneration. In conclusion, we describe an unusual upregulation of CD57 and KIRs on CD56(++) NK cells shortly after autoSCT. Importantly, these NK cells were functionally competent upon tumor interaction at this early time point.
EVALuna2:25729

Noncanonical effector functions of the T-memory-like T-PLL cell are shaped by cooperative TCL1A and TCR signaling - Oberbeck, S.; Schrader, A.; Warner, K.; Jungherz, D.; Crispatzu, G.; Von Jan, J.; Chmielewski, M.; Ianevski, A.; Diebner, H. H.; Mayer, P.; Ados, A. Kondo; Wahnschaffe, L.; et al. (Blood, 2020)
T-cell prolymphocytic leukemia (T-PLL) is a poor-prognostic neoplasm. Differentiation stage and immune-effector functions of the underlying tumor cell are insufficiently characterized. Constitutive activation of the T-cell leukemia 1A (TCL1A) oncogene distinguishes the (pre) leukemic cell from regular postthymic T cells. We assessed activation-response patterns of the T-PLL lymphocyte and interrogated the modulatory impact by TCL1A. Immunophenotypic and gene expression profiles revealed a unique spectrum of memory-type differentiation of T-PLL with predominant central-memory stages and frequent noncanonical patterns. Virtually all T-PLL expressed a T-cell receptor (TCR) and/or CD28-coreceptor without overrepresentation of specific TCR clonotypes. The highly activated leukemic cells also revealed losses of negative regulatory TCR coreceptors (eg, CTLA4). TCR stimulation of T-PLL cells evoked higher-than normal cell-cycle transition and profiles of cytokine release that resembled those of normal memory T cells. More activated phenotypes and higher TCL1A correlated with inferior clinical outcomes. TCL1A was linked to the marked resistance of T-PLL to activationand FAS-induced cell death. Enforced TCL1A enhanced phospho-activation of TCR kinases, second-messenger generation, and JAK/STAT or NFAT transcriptional responses. This reduced the input thresholds for IL-2 secretion in a sensitizer-like fashion. Mice of TCL1A-initiated protracted T-PLL development resembled such features. When equipped with epitope-defined TCRs or chimeric antigen receptors, these Lckpr-hTCL1AtgT cells gained a leukemogenic growth advantage in scenarios of receptor stimulation. Overall, we propose a model of T-PLL pathogenesis in which TCL1A enhances TCR signals and drives the accumulation of death-resistant memory-type cells that use amplified low-level stimulatory input, and whose loss of negative coregulators additionally maintains their activated state. Treatment rationales are provided by combined interception in TCR and survival signaling.
CRIS-Team WoS Importer:2021-01-01

Norm- and hypo-fractionated radiotherapy is capable of activating human dendritic cells - Kulzer, Lorenz; Rubner, Yvonne; Deloch, Lisa; Allgäuer, Andrea; Frey, Benjamin; Fietkau, Rainer; Dörrie, Jan; Schaft, Niels; Gaipl, Udo (Journal of Immunotoxicology, 2014)
Abstract Despite the transient immunosuppressive properties of local radiotherapy (RT), this classical treatment modality of solid tumors is capable of inducing immunostimulatory forms of tumor-cell death. The resulting 'immunotoxicity' in the tumor, but not in healthy tissues, may finally lead to immune-mediated destruction of the tumor. However, little is known about the best irradiation scheme in this setting. This study examines the immunological effects of differently irradiated human colorectal tumor cells on human monocyte-derived dendritic cells (DC). Human SW480 tumor cells were irradiated with a norm-fractionation scheme (5 × 2 Gy), a hypo-fractionated protocol (3 × 5 Gy), and with a high single irradiation dose (radiosurgery; 1 × 15 Gy). Subsequently, human immature DC (iDC) were co-incubated with supernatants (SN) of these differently treated tumor cells. Afterwards, DC were analyzed regarding the expression of maturation markers, the release of cytokines, and the potential to stimulate CD4(+) T-cells. The co-incubation of iDC with SN of tumor cells exposed to norm- or hypo-fractionated RT resulted in a significantly increased secretion of the immune activating cytokines IL-12p70, IL-8, IL-6, and TNF?, compared to iDC co-incubated with SN of tumor cells that received a high single irradiation dose or were not irradiated. In addition, DC-maturation markers CD80, CD83, and CD25 were also exclusively elevated after co-incubation with the SN of fractionated irradiated tumor cells. Furthermore, the SN of tumor cells that were irradiated with norm- or hypo-fractionated RT triggered iDC to stimulate CD4(+) T-cells not only in an allogenic, but also in an antigen-specific manner like mature DC. Collectively, these results demonstrate that norm- and hypo-fractionated RT induces a fast human colorectal tumor-cell death with immunogenic potential that can trigger DC maturation and activation in vitro. Such findings may contribute to the improvement of irradiation protocols for the most beneficial induction of anti-tumor immunity.
EVALuna2:18178

Notch2 controls non-autonomous Wnt-signalling in chronic lymphocytic leukaemia - Mangolini, Maurizio; Goette, Frederik; Moore, Andrew; Ammon, Tim; Oelsner, Madlen; Lutzny-Geier, Gloria; Klein-Hitpass, Ludger; Williamson, James C.; Lehner, Paul J.; Duerig, Jan; Moellmann, Michael; Raso-Barnett, Livia; et al. (Nature Communications, 2018)
The Wnt signalling pathway, one of the core de-regulated pathways in chronic lymphocytic leukaemia (CLL), is activated in only a subset of patients through somatic mutations. Here we describe alternative, microenvironment-dependent mechanisms of Wnt activation in malignant B cells. We show that tumour cells specifically induce Notch2 activity in mesenchymal stromal cells (MSCs) required for the transcription of the complement factor C1q. MSC-derived C1q in turn inhibits Gsk3-β mediated degradation of β-catenin in CLL cells. Additionally, stromal Notch2 activity regulates N-cadherin expression in CLL cells, which interacts with and further stabilises β-catenin. Together, these stroma Notch2-dependent mechanisms induce strong activation of canonical Wnt signalling in CLL cells. Pharmacological inhibition of the Wnt pathway impairs microenvironment-mediated survival of tumour cells. Similarly, inhibition of Notch signalling diminishes survival of stroma-protected CLL cells in vitro and disease engraftment in vivo. Notch2 activation in the microenvironment is a pre-requisite for the activation of canonical Wnt signalling in tumour cells.
EVALuna2:34644

Novel Adjuvant Therapy for Ocular Melanoma - Bosch, Jacobus J.; Heindl, Ludwig M. (Klinische Monatsblätter für Augenheilkunde, 2017)
Background Malignant melanoma is the most common cancer of the eye in adults that originates either in the intra-ocular uveal tract or extra-ocular conjunctiva. Although the primary tumor can be treated successfully, no effective therapy for both metastatic conjunctival and uveal melanoma currently exits. Tumor-associated lymphangiogenesis and immune cell infiltration play a pivotal role in the development and therapeutic targeting of metastases. Project description Here, we provide an overview of current translational research on lymphangiogenesis and its therapeutic inhibition as well as modulation of immune cell infiltration by passive and active immunotherapy in melanoma of the eye. Specifically, our previous and ongoing work on lymphangiogenesis and immune cells in ocular melanoma within the clinical research unit FOR 2240 "(Lymph)Angiogenesis and Cellular Immunity in Inflammatory Diseases of the Eye" is summarized. Conclusions Translational research on the modulation of tumor-associated lymphangiogenesis and immune cell infiltration could provide novel targets for adjuvant therapy in melanoma of the eye.
EVALuna2:25785

NSD3-NUTM1-rearranged carcinoma of the median neck/thyroid bed developing after recent thyroidectomy for sclerosing mucoepidermoid carcinoma with eosinophilia: report of an extraordinary case - Agaimy, Abbas; Tögel, Lars; Stöhr, Robert; Meidenbauer, Norbert; Semrau, Sabine; Hartmann, Arndt; Mantsopoulos, Konstantinos (Virchows Archiv, 2021)
Sclerosing mucoepidermoid carcinoma with eosinophilia (SMECE) is an exceedingly rare low-grade thyroid malignancy of unknown histogenesis. NUT carcinoma is another rare, highly aggressive neoplasm with predilection for the midline, defined by recurrent NUTM1 fusions. The bromodomain family genes (BRD4 or BRD3) and rarely NSD3, ZNF532, or others are known fusion partners. We describe an extraordinary case of a 42-year-old female with a thyroid SMECE treated by thyroidectomy and neck dissection. She presented 6 months later with extensive midline recurrence encasing/compressing the trachea. Biopsy revealed poorly differentiated carcinoma with abrupt squamous differentiation, suggestive of NUT carcinoma. Immunohistochemistry confirmed expression of monoclonal NUT antibody. Targeted RNA sequencing revealed the NSD3-NUTM1 fusion in the NUT carcinoma, but not in the SMECE. This unique case highlights unusual sequential origin of two exceptionally rare entities at same anatomic site and underlines the necessity of sampling unexpectedly aggressive recurrences of otherwise indolent malignancies.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Head and neck; Midline carcinoma; NSD3; NUT carcinoma; NUTM1; Sclerosing mucoepidermoid carcinoma with eosinophilia; Thyroid gland

Null mutation in PGAP1 impairing Gpi-anchor maturation in patients with intellectual disability and encephalopathy - Murakami, Yoshiko; Tawamie, Hasan; Maeda, Yusuke; Büttner, Christian; Buchert, Rebecca; Radwan, Farah; Schaffer, Susann; Sticht, Heinrich; Aigner, Michael; Reis, André; Kinoshita, Taroh; Abou Jamra, Rami (PLoS Genetics, 2014)
Many eukaryotic cell-surface proteins are anchored to the membrane via glycosylphosphatidylinositol (GPI). There are at least 26 genes involved in biosynthesis and remodeling of GPI anchors. Hypomorphic coding mutations in seven of these genes have been reported to cause decreased expression of GPI anchored proteins (GPI-APs) on the cell surface and to cause autosomal-recessive forms of intellectual disability (ARID). We performed homozygosity mapping and exome sequencing in a family with encephalopathy and non-specific ARID and identified a homozygous 3 bp deletion (p.Leu197del) in the GPI remodeling gene PGAP1. PGAP1 was not described in association with a human phenotype before. PGAP1 is a deacylase that removes an acyl-chain from the inositol of GPI anchors in the endoplasmic reticulum immediately after attachment of GPI to proteins. In silico prediction and molecular modeling strongly suggested a pathogenic effect of the identified deletion. The expression levels of GPI-APs on B lymphoblastoid cells derived from an affected person were normal. However, when those cells were incubated with phosphatidylinositol-specific phospholipase C (PI-PLC), GPI-APs were cleaved and released from B lymphoblastoid cells from healthy individuals whereas GPI-APs on the cells from the affected person were totally resistant. Transfection with wild type PGAP1 cDNA restored the PI-PLC sensitivity. These results indicate that GPI-APs were expressed with abnormal GPI structure due to a null mutation in the remodeling gene PGAP1. Our results add PGAP1 to the growing list of GPI abnormalities and indicate that not only the cell surface expression levels of GPI-APs but also the fine structure of GPI-anchors is important for the normal neurological development.
EVALuna2:9210

Older patients with chronic myeloid leukemia (>=65 years) profit more from higher imatinib doses than younger patients: a subanalysis of the randomized CML-Study IV - Proetel, Ulrike; Pletsch, Nadine; Lauseker, Michael; Müller, Martin C.; Hanfstein, Benjamin; Krause, Stefan; Kalmanti, Lida; Schreiber, Annette; Heim, Dominik; Baerlocher, Gabriela M.; Hofmann, Wolf-Karsten; Lange, Elisabeth; et al. (Annals of Hematology, 2014)
The impact of imatinib dose on response rates and survival in older patients with chronic myeloid leukemia in chronic phase has not been studied well. We analyzed data from the German CML-Study IV, a randomized five-arm treatment optimization study in newly diagnosed BCR-ABL-positive chronic myeloid leukemia in chronic phase. Patients randomized to imatinib 400 mg/day (IM400) or imatinib 800 mg/day (IM800) and stratified according to age (>=65 years vs. <65 years) were compared regarding dose, response, adverse events, rates of progression, and survival. The full 800 mg dose was given after a 6-week run-in period with imatinib 400 mg/day. The dose could then be reduced according to tolerability. A total of 828 patients were randomized to IM400 or IM800. Seven hundred eighty-four patients were evaluable (IM400, 382; IM800, 402). One hundred ten patients (29 %) on IM400 and 83 (21 %) on IM800 were >=65 years. The median dose per day was lower for patients >=65 years on IM800, with the highest median dose in the first year (466 mg/day for patients >=65 years vs. 630 mg/day for patients <65 years). Older patients on IM800 achieved major molecular remission and deep molecular remission as fast as younger patients, in contrast to standard dose imatinib with which older patients achieved remissions much later than younger patients. Grades 3 and 4 adverse events were similar in both age groups. Five-year relative survival for older patients was comparable to that of younger patients. We suggest that the optimal dose for older patients is higher than 400 mg/day. ClinicalTrials.gov identifier: NCT00055874
EVALuna2:25701
Keywords: Early applied higher imatinib dosages; Different imatinib dose regimens; Chronic myeloid leukemia; Older patients

Omission of dacarbazine or bleomycin, or both, from the ABVD regimen in treatment of early-stage favourable Hodgkin's lymphoma (GHSG HD13): an open-label, randomised, non-inferiority trial - Behringer, Karolin; Goergen, Helen; Hitz, Felicitas; Zijlstra, Josee M.; Greil, Richard; Markova, Jana; Sasse, Stephanie; Fuchs, Michael; Topp, Max S.; Soekler, Martin; Mathas, Stephan; Meissner, Julia; et al. (Lancet, 2015)
The role of bleomycin and dacarbazine in the ABVD regimen (ie, doxorubicin, bleomycin, vinblastine, and dacarbazine) has been questioned, especially for treatment of early-stage favourable Hodgkin's lymphoma, because of the drugs' toxicity. We aimed to investigate whether omission of either bleomycin or dacarbazine, or both, from ABVD reduced the efficacy of this regimen in treatment of Hodgkin's lymphoma.In this open-label, randomised, multicentre trial (HD13) we compared two cycles of ABVD with two cycles of the reduced-intensity regimen variants ABV (doxorubicin, bleomycin, and vinblastine), AVD (doxorubicin, vinblastine, and dacarbazine), and AV (doxorubicin and vinblastine), in patients with newly diagnosed, histologically proven, classic or nodular, lymphocyte predominant Hodgkin's lymphoma. In each treatment group, 30 Gy involved-field radiotherapy (IFRT) was given after both cycles of chemotherapy were completed. From Jan 28, 2003, patients were centrally randomly assigned (1:1:1:1) with a minimisation method to the four groups. Because of high event rates, assignment to the AV and ABV groups stopped early, on Sept 30, 2005, and Feb 10, 2006; assignment to ABVD and AVD continued (1:1) until Sept 30, 2009. Our primary objective was to show non-inferiority of the experimental variants compared with ABVD in terms of freedom from treatment failure (FFTF), by excluding a difference of 6% after 5 years corresponding to a hazard ratio (HR) of 1.72, via a 95% CI. Analyses reported here include qualified patients only, and between-group comparisons include only patients recruited during the same period. The trial was registered, number ISRCTN63474366.Of 1502 qualified patients, 566, 198, 571, and 167 were randomly assigned to receive ABVD, ABV, AVD, or AV, respectively. 5 year FFTF was 93.1%, 81.4%, 89.2%, and 77.1% with ABVD, ABV, AVD, and AV, respectively. Compared with ABVD, inferiority of the dacarbazine-deleted variants was detected with 5 year differences of -11.5% (95% CI -18.3 to -4.7; HR 2.06 [1.21 to 3.52]) for ABV and -15.2% (-23.0 to -7.4; HR 2.57 [1.51 to 4.40]) for AV. Non-inferiority of AVD compared with ABVD could also not be detected (5 year difference -3.9%, -7.7 to -0·1; HR 1.50, 1.00 to 2.26). 178 (33%) of 544 patients given ABVD had WHO grade III or IV toxicity, compared with 53 (28%) of 187 given ABV, 142 (26%) of 539 given AVD, and 40 (26%) of 151 given AV. Leucopenia was the most common event, and highest in the groups given bleomycin.Dacarbazine cannot be omitted from ABVD without a substantial loss of efficacy. With respect to our predefined non-inferiority margin, bleomycin cannot be safely omitted either, and the standard of care for patients with early-stage favourable Hodgkin's lymphoma should remain ABVD followed by IFRT.Deutsche Krebshilfe and Swiss State Secretariat for Education and Research.
EVALuna2:25705

On Its Way to Primetime: Artificial Intelligence in Flow Cytometry Diagnostics - Krause, Stefan (Cytometry Part A, 2020)
CRIS-Team Scopus Importer:2020-08-14

Organometallic nucleosides induce non-classical leukemic cell death that is mitochondrial-ROS dependent and facilitated by TCL1-oncogene burden - Prinz, Christian; Vasyutina, Elena; Lohmann, Gregor; Schrader, Alexandra; Romanski, Steffen; Hirschhaeuser, Christoph; Mayer, Petra; Frias, Corazon; Herling, Carmen D.; Hallek, Michael; Schmalz, Hans-Guenther; Prokop, Aram; et al. (Molecular Cancer, 2015)
Redox stress is a hallmark of the rewired metabolic phenotype of cancer. The underlying dysregulation of reactive oxygen species (ROS) is interconnected with abnormal mitochondrial biogenesis and function. In chronic lymphocytic leukemia (CLL), elevated ROS are implicated in clonal outgrowth and drug resistance. The pro-survival oncogene T-cell leukemia 1 (TCL1) is causally linked to the high threshold towards classical apoptosis in CLL. We investigated how aberrant redox characteristics and bioenergetics of CLL are impacted by TCL1 and if this is therapeutically exploitable.Bio-organometallic chemistry provided compounds containing a cytosine nucleobase, a metal core (ferrocene, ruthenocene, Fe(CO)3), and a 5'-CH2O-TDS substituent. Four of these metal-containing nucleoside analogues (MCNA) were tested for their efficacy and mode of action in CLL patient samples, gene-targeted cell lines, and murine TCL1-transgenic splenocytes.The MCNA showed a marked and selective cytotoxicity towards CLL cells. MCNA activity was equally observed in high-risk disease groups, including those of del11q/del17p cytogenetics and of clinical fludarabine resistance. They overcame protective stromal cell interactions. MCNA-evoked PARP-mediated cell death was non-autophagic and non-necrotic as well as caspase- and P53-independent. This unconventional apoptosis involved early increases of ROS, which proved indispensible based on mitigation of MCNA-triggered death by various scavengers. MCNA exposure reduced mitochondrial respiration (oxygen consumption rate; OCR) and induced a rapid membrane depolarization (??M). These characteristics distinguished the MCNA from the alkylator bendamustine and from fludarabine. Higher cellular ROS and increased MCNA sensitivity were linked to TCL1 expression. The presence of TCL1 promoted a mitochondrial release of in part caspase-independent apoptotic factors (AIF, Smac, Cytochrome-c) in response to MCNA. Although basal mitochondrial respiration (OCR) and maximal respiratory capacity were not affected by TCL1 overexpression, it mediated a reduced aerobic glycolysis (lactate production) and a higher fraction of oxygen consumption coupled to ATP-synthesis.Redox-active substances such as organometallic nucleosides can confer specific cytotoxicity to ROS-stressed cancer cells. Their P53- and caspase-independent induction of non-classical apoptosis implicates that redox-based strategies can overcome resistance to conventional apoptotic triggers. The high TCL1-oncogenic burden of aggressive CLL cells instructs their particular dependence on mitochondrial energetic flux and renders them more susceptible towards agents interfering in mitochondrial homeostasis.
EVALuna2:25720

Outcome of 841 Older Patients (> 55 yrs) with Newly Diagnosed Ph/BCR-ABL Negative ALL Prospectively Treated According to Pediatric-Based, Age-Adapted GMALL Protocols - Goekbuget, Nicola; Viardot, Andreas; Steffen, Bjorn; Hahn, Joachim; Spriewald, Bernd; Martin, Sonja; Raffel, Simon; Teichmann, Lino L.; Trummer, Arne; Alsdorf, Winfried; Morgner, Anke; Schwartz, Stefan; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Outcomes of axicabtagene ciloleucel in PMBCL compare favorably with those in DLBCL: a GLA/DRST registry study - Schubert, Maria Luisa; Bethge, Wolfgang A.; Ayuk, Francis A.; von Bonin, Malte; Vucinic, Vladan; Wagner-Drouet, Eva Marie; Subklewe, Marion; Baldus, Claudia D.; Glass, Bertram; Marks, Reinhard; Mougiakakos, Dimitrios; Schroers, Roland; et al. (Blood Advances, 2023)
CRIS-Team Scopus Importer:2023-11-10

Outcomes of Haploidentical Transplantation in Patients with Relapsed Multiple Myeloma: An EBMT/CIBMTR Report - Sahebi, Firoozeh; Garderet, Laurent; Kanate, Abraham S.; Eikema, Diderik Jan; Knelange, Nina Simone; Alvelo, Omar F.Dávila; Koc, Yener; Blaise, Didier; Bashir, Qaiser; Moraleda, José M.; Dreger, Peter; Sanchez, James F.; et al. (Biology of Blood and Marrow Transplantation, 2018)
Allogeneic hematopoietic cell transplantation (allo-HCT) using siblings and matched donors has the potential for long-term disease control in a subset of high-risk patients with multiple myeloma (MM); however, the data on using haploidentical donors in this disease are limited. We conducted a retrospective analysis to examine the outcomes of patients with MM who underwent haploidentical allo-HCT within European Society for Blood and Marrow Transplantation/Center for International Blood and Marrow Transplant Research centers. A total of 96 patients underwent haploidentical allo-HCT between 2008 and 2016. With a median follow-up of 24.0 months (range, 13.2 to 24.9 months), 97% (95% confidence interval [CI], 93% to 100%) of patients had neutrophil engraftment by day 28, and 75% (95% CI, 66% to 84%) achieved platelet recovery by day 60. Two-year progression-free survival (PFS) was 17% (95% CI, 8% to 26%), and overall survival (OS) was 48% (95% CI, 36% to 59%). At 2 years, the cumulative risk of relapse/progression was 56% (95% CI, 45% to 67%), and 1-year nonrelapse mortality (NRM) was 21% (95% CI, 13% to 29%). The incidences of acute graft-versus-host-disease (GVHD) grades II-IV by 100 days and chronic GVHD at 2 years were 39% (95% CI, 28% to 49%) and 46% (95% CI, 34% to 59%), respectively. On univariate analysis, use of post-transplantation cyclophosphamide (PT-Cy) (54% [95% CI, 41% to 68%] versus 25% [95% CI, 1% to 48%]; P =.009) and use of bone marrow as source of stem cells (72% [95% CI, 55% to 89%] versus 31% [95% CI, 17% to 46%]; P = .001) were associated with improved OS at 2 years. Disease status, patient sex, intensity of conditioning regimen, recipient/donor sex mismatch, and cytomegalovirus serostatus had no impact on OS, PFS, or NRM. Haploidentical transplantation is feasible for patients with multiply relapsed or high-risk MM, with an encouraging 2-year OS of 48% and an NRM of 21% at 1 year, supporting further investigation of haploidentical allo-HCT in suitable candidates with MM.
EVALuna2:35108

Over-the-scope-clipping in colonic perforation caused small-bowel fixation and pneumoperitoneum requiring surgical repair - Albrecht, Heinz; Naegel, Andreas; Hagel, Alexander; Rösler, Wolf; Förtsch, Thomas; Neurath, Markus; Atreya, Raja; Raithel, Martin (Endoscopy, 2014)
EVALuna2:1835

Oxidative DNA damage in reconstituting T cells is associated with relapse and inferior survival after allo-SCT - Karl, Franziska; Liang, C.; Böttcher-Loschinski, R.; Stoll, Andrej; Flamann, Cindy; Richter, Silja; Lischer, Christopher; Völkl, Simon; Jacobs, Benedikt; Böttcher, M.; Jitschin, R.; Bruns, Heiko; et al. (Blood, 2023)
Allogeneic hematopoietic stem cell transplantation (allo-SCT) is the only curative treatment option for a number of hematologic malignancies. Its therapeutic potential relies on the potency of donor T cells to eliminate residual malignant cells, the so-called graft-versus-leukemia (GVL) effect. Disease relapse remains the most frequent treatment failure and is associated with poor outcome. Therefore, it is inevitable to decipher mechanisms that weaken GVL. In recent years, studies of tumor biology have revealed that metabolic remodeling of the micromilieu can critically regulate immune responses. Accumulation of reactive oxygen species leads to a metabolic condition known as oxidative stress, which can severely hamper T cells. Currently, only a few studies, mainly using preclinical models, have demonstrated the occurrence of oxidative stress after allo-SCTs. Therefore, we sought to investigate oxidative stress in a well-characterized group of patients who underwent allo-SCT and its impact on reconstituting T cells. We identified high concentrations of serum 8-hydroxydeoxyguanosine (8-OHdG) as an established biomarker for oxidative stress. 8-OHdG is one of the major products of DNA oxidation, which is normally rapidly removed. After allo-SCT, T cells accumulated oxidative DNA damage. High cellular 8-OHdG content (8-OHdGhi) was associated not only with signs of enhanced T-cell activation but also premature exhaustion. The inability of 8-OHdGhi T cells to efficiently target malignant cells or produce cytotoxic granzyme B and interferon gamma was associated with a significantly increased relapse risk and a shorter overall survival. Taken together, our novel findings could give reason to focus on bolstering DNA repair in reconstituting T cells as a means to improve GVL efficacy.
CRIS-Team Scopus Importer:2023-03-31

Oxidative stress upon allogeneic hematopoietic stem cell transplantation and its impact on the reconstituting immune system - Karl, Franziska; Böttcher-Loschinski, Romy; Stoll, Andrej; Rösler, Wolf; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Paclitaxel synergizes with exposure time adjusted CD22-targeting immunotoxins against B-cell malignancies - Müller, Fabian; Stookey, Stephanie; Cunningham, Tyler; Pastan, Ira (Oncotarget, 2017)
CD22-targeted recombinant immunotoxins (rIT) are active in hairy cell leukemia or acute lymphoblastic leukemia (ALL), but not in mantle cell lymphoma (MCL) patients. The goal was to enhance rIT efficacy in vivo and to define a strong combination treatment. Activity of Moxetumomab pasudotox (Moxe) and LR combined with paclitaxel was tested against MCL cell lines in vitro and as bolus doses or continuous infusion in xenograft models. In the KOPN-8 ALL xenograft, Moxe or paclitaxel alone was active, but all mice died from leukemia; when combined, 60% of the mice achieved a sustained complete remission. Against MCL cells in vitro, LR was more active than Moxe and the cells had to be exposed to rIT for more than 24 hours for them to die. To maintain high blood levels in vivo, LR was administered continuously by 7-day pumps achieving a well-tolerated steady plasma concentration of 45 ng/ml. In JeKo-1 xenografts, continuously administered LR was 14-fold more active than bolus doses and the combination with paclitaxel additionally improved responses by 135-fold. Maintaining high rIT-plasma levels greatly improves responses in the JeKo-1 model and paclitaxel substantially enhances bolus and continuously infused rIT, supporting a clinical evaluation against B-cell malignancies.
EVALuna2:25765

Palliative Care Patients' Quality of Dying and Circumstances of Death-Comparison of Informal Caregivers' and Health-Care Professionals' Estimates - Stiel, Stephanie; Heckel, Maria; Wendt, Kim Nikola; Weber, Martin; Ostgathe, Christoph (American Journal of Hospice & Palliative Medicine, 2018)
BACKGROUND: Patient-reported outcomes are usually considered to be the gold standard assessment. However, for the assessment of quality of dying and death, ratings of informal caregivers (ICGs) or health-care professionals (HCPs) must be considered for ethical and methodological reasons. This article aims to present results of ICGs' and HCPs' estimates of the questionnaire, quality of dying and death (QoDD) on patients who died in PCUs and to compare the level of agreement of both ratings/raters. METHODS: The parent validation study to this analysis assessed the ICG and HCP versions of the QoDD. Descriptive statistics are presented for each item in both versions. T tests for the estimation of differences between ICG and HCP were performed. Case-related absolute differences between estimates were analyzed regarding the extent of agreement and deviation. RESULTS: Two hundred fifteen matched ICG and HCP ratings were analyzed. The ratings in all 6 QoDD dimensions were high; single items scored low. Mean absolute difference between both ratings was 0.33 (standard deviation [SD]: 3.08; median 0.05) on a 0 to 10 numerical rating scale and ranges between -8.24 (higher rating of ICGs compared to HCPs) and 9.33 (higher rating of HCPs compared to ICGs). CONCLUSIONS: The findings appear to show a high satisfaction with quality of dying and death as rated by ICGs and HCPs, but we suspect this might be indicative of a methodological challenge, that is, a ceiling effect in both assessments. Single low scoring items may provide important clues for improvement in end-of-life care. Although descriptive data show comparable mean values and standard deviations, the actual congruence of ratings is low. In summary, replacing one rating by another cannot be recommended.
EVALuna2:33773

Palmitoylated Proteins on AML-Derived Extracellular Vesicles Promote Myeloid-Derived Suppressor Cell Differentiation via TLR2/Akt/mTOR Signaling - Tohumeken, Sehmus; Böttcher, Martin; Stoll, Andrej; Loschinski, Romy; Panagiotidis, Konstantinos; Braun, Martina; Saul, Domenica; Baur, Andreas; Bruns, Heiko; Mackensen, Andreas; Jitschin, Regina; Mougiakakos, Dimitrios; et al. (Cancer Research, 2020)
Acute myeloid leukemia (AML) represents the most common acute leukemia among adults. Despite recent progress in diagnosis and treatment, long-term outcome remains unsatisfactory. The success of allogeneic stem cell transplantation underscores the immunoresponsive nature of AML, creating the basis for further exploiting immunotherapies. However, emerging evidence suggests that AML, similar to other malignant entities, employs a variety of mechanisms to evade immunosurveillance. In light of this, T-cell inhibitory myeloid-derived suppressor cells (MDSC) are gaining interest as key facilitators of immunoescape. Accumulation of CD14(+) HLA-DRlow monocyticMDSCs has been described in newly diagnosed AML patients, and deciphering the underlying mechanisms could help to improve anti-AML immunity. Here, we report that conventional monocytes readily takeup AML-derived extracellular vesicles (EV) and subsequently undergo MDSC differentiation. They acquired an CD14(+)HLA-DRlow phenotype, expressed the immunomodulatory indoleamine-2,3-dioxygenase, and upregulated expression of genes characteristic for MDSCs, such as S100A8/9 and cEBP beta. The Akt/mTOR pathway played a critical role in the AML-EV-induced phenotypical and functional transition of monocytes. Generated MDSCs displayed a glycolytic switch, which rendered them more susceptible toward glycolytic inhibitors. Furthermore, palmitoylated proteins on the AML-EV surface activated Toll-like receptor 2 as the initiating event of Akt/mTOR-dependent induction of MDSC. Therefore, targeting protein palmitoylation in AML blasts could block MDSC accumulation to improve immune responses.
CRIS-Team WoS Importer:2020-09-25

Patients with immune-mediated inflammatory diseases receiving cytokine inhibitors have low prevalence of SARS-CoV-2 seroconversion - Simon, David; Tascilar, Koray; Krönke, Gerhard; Kleyer, Arnd; Zaiss, Mario; Heppt, Franz; Meder, Christine; Atreya, Raja; Klenske, Entcho; Dietrich, Peter; Abdullah, Abdullah; Kliem, Thorsten; et al. (Nature Communications, 2020)
Immune-mediated inflammatory diseases (IMIDs) of the joints, gut and skin are treated with inhibitors of inflammatory cytokines. These cytokines are involved in the pathogenesis of coronavirus disease 2019 (COVID-19). Investigating anti-SARS-CoV-2 antibody responses in IMIDs we observe a reduced incidence of SARS-CoV-2 seroconversion in IMID patients treated with cytokine inhibitors compared to patients receiving no such inhibitors and two healthy control populations, despite similar social exposure. Hence, cytokine inhibitors seem to at least partially protect from SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2020-08-07

PD-L1/PD-1: new kid on the "immune metabolic" block - Qorraj, Mirjeta; Böttcher, Martin; Mougiakakos, Dimitrios (Oncotarget, 2017)
EVALuna2:25774

Perihemorrhagic edema: Revisiting hematoma volume, location, and surface - Sprügel, Maximilian; Kuramatsu, Joji; Volbers, Bastian; Gerner, Stefan; Sembill, Jochen; Madžar, Dominik; Bobinger, Tobias; Kölbl, Kathrin; Lücking, Hannes; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; et al. (Neurology, 2019)
OBJECTIVE: To determine the influence of intracerebral hemorrhage (ICH) location and volume and hematoma surface on perihemorrhagic edema evolution. METHODS: Patients with ICH of the prospective Universitätsklinikum Erlangen Cohort of Patients With Spontaneous Intracerebral Hemorrhage (UKER-ICH) cohort study (NCT03183167) between 2010 and 2013 were analyzed. Hematoma and edema volume during hospital stay were volumetrically assessed, and time course of edema evolution and peak edema correlated to hematoma volume, location, and surface to verify the strength of the parameters on edema evolution. RESULTS: Overall, 300 patients with supratentorial ICH were analyzed. Peak edema showed a high correlation with hematoma surface (R2 = 0.864, p < 0.001) rather than with hematoma volumes, regardless of hematoma location. Smaller hematomas with a higher ratio of hematoma surface to volume showed exponentially higher relative edema (R2 = 0.755, p < 0.001). Multivariable logistic regression analysis revealed a cutoff ICH volume of 30 mL, beyond which an increase of total mass lesion volume (combined volume of hematoma and edema) was not associated with worse functional outcome. Specifically, peak edema was associated with worse functional outcome in ICH <30 mL (odds ratio [OR] 2.63, 95% confidence interval [CI] 1.68-4.12, p < 0.001), contrary to ICH ≥30 mL (OR 1.20, 95% CI 0.88-1.63, p = 0.247). There were no significant differences between patients with lobar and those with deep ICH after adjustment for hematoma volumes. CONCLUSIONS: Peak perihemorrhagic edema, although influencing mortality, is not associated with worse functional outcomes in ICH volumes >30 mL. Although hematoma volume correlates with peak edema extent, hematoma surface is the major parameter for edema evolution. The effect of edema on functional outcome is therefore more pronounced in smaller and irregularly shaped hematomas, and these patients may particularly benefit from edema-modifying therapies.
CRIS-Team Scopus Importer:2019-09-27

Pet positivity after 2 cycles of abvd is a risk factor in patients with early-stage favorable Hodgkin lymphoma treated in the phase 3 GHSG HD16 study - Fuchs, M.; Goergen, H.; Kobe, C.; Kuhnert, G.; Hitz, F.; Greil, R.; Sasse, S.; Topp, M. S.; Schaefer, E.; Hertenstein, B.; Soekler, M.; Vogelhuber, M.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

PGAM5 acts as a key mediator of lung fibrosis by disrupting mitochondrial homeostasis - Ganzleben, Ingo; He, Gui-Wei; Günther, Claudia; Prigge, Elena-Sophie; Richter, Karsten; Rieker, Ralf; Mougiakakos, Dimitrios; Neurath, Markus; Becker, Christoph (EUROPEAN RESPIRATORY JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

PGAM5 is a key driver of mitochondrial dysfunction in experimental lung fibrosis - Ganzleben, Ingo; He, Gui Wei; Günther, Claudia; Prigge, Elena Sophie; Richter, Karsten; Rieker, Ralf; Mougiakakos, Dimitrios; Neurath, Markus; Becker, Christoph (Cellular and Molecular Life Sciences, 2019)
Rationale: Mitochondrial homeostasis has recently emerged as a focal point in the pathophysiology of idiopathic pulmonary fibrosis (IPF), but conflicting data have been reported regarding its regulation. We speculated that phosphoglycerate mutase family member 5 (PGAM5), a mitochondrial protein at the intersection of multiple cell death and mitochondrial turnover pathways, might be involved in the pathogenesis of IPF. Methods: PGAM5-deficient mice and human pulmonary epithelial cells were analyzed comparatively with PGAM5-proficient controls in a bleomycin-based model of pulmonary fibrogenesis. Mitochondria were visualized by confocal and transmission electron microscopy. Mitochondrial homeostasis was assessed using JC1 (ΔΨ) and flow cytometry. Results: PGAM5 plays an important role in pulmonary fibrogenesis. Pgam5−/− mice displayed significantly attenuated lung fibrosis compared to controls. Complementary, in vitro studies demonstrated that PGAM5 impaired mitochondrial integrity on a functional and structural level independently of mtROS-production. On a molecular level, reduced mitophagy caused by PGAM5 deficiency improved mitochondrial homeostasis. Conclusions: Our study identifies PGAM5 as an important regulator of mitochondrial homeostasis in pulmonary fibrosis. Our data further indicate PGAM5-mediated mitophagy itself as a pivotal gateway event in the mediation of self-sustaining mitochondrial damage and membrane depolarization. Our work hereby highlights the importance of mitochondrial dynamics and identifies a potential therapeutic target that warrants further studies. Graphical abstract: Toxic agents lead to mitochondrial damage resulting in depolarization of the mitochondrial membrane potential (ΔΨ) which is a gateway event for the initiation of PGAM5-mediated mitophagy. PGAM5-mediated mitophagy in turn leads to a self-perpetuating escalation of ΔΨ depolarization. Loss of the mitophagy-based damage-enhancing loop under PGAM5-deficient conditions breaks this vicious cycle, leading to improved mitochondrial homeostasis.[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2019-06-21
Keywords: Bleomycin; IPF; Mitophagy

Phase 2 study of anti-human cytomegalovirus monoclonal antibodies for prophylaxis in hematopoietic cell transplantation - Maertens, Johan; Logan, Aaron C.; Jang, Junho; Long, Gwynn; Tang, Jih Luh; Hwang, William Y.K.; Koh, Liang Piu; Chemaly, Roy; Gerbitz, Armin; Winkler, Julia; Yeh, Su Peng; Hiemenz, John; et al. (Antimicrobial Agents and Chemotherapy, 2020)
Human cytomegalovirus (HCMV) can cause significant disease in immunocompromised patients, and treatment options are limited by toxicities. CSJ148 is a combination of two anti-HCMV human monoclonal antibodies (LJP538 and LJP539) that bind to and inhibit the functions of viral HCMV glycoprotein B (gB) and the pentameric complex, consisting of glycoproteins gH, gL, UL128, UL130, and UL131. In this phase 2, randomized, placebo-controlled trial, we evaluated the safety and efficacy of CSJ148 for prophylaxis of HCMV in patients undergoing allogeneic hematopoietic stem cell transplantation. As would be expected in the study population, all the patients (100%) reported at least one treatment-emergent adverse event. There were 22 deaths during this study, and over 80% of the patients receiving placebo or CSJ148 developed at least one adverse event of grade 3 or higher severity. No subject who received antibody developed a hypersensitivity- or infusion-related reaction. CSJ148-treated patients showed trends toward decreased viral load, shorter median duration of preemptive therapy, and fewer courses of preemptive therapy. However, the estimated probability that CSJ148 decreases the need for preemptive therapy compared to placebo was 69%, with a risk ratio of 0.89 and a 90% credible interval of 0.61 to 1.31. The primary efficacy endpoint was therefore not met, indicating that CSJ148 did not prevent clinically significant HCMV reactivation in recipients of allogeneic hematopoietic cell transplants.
CRIS-Team Scopus Importer:2020-04-03
Keywords: Hematopoietic stem cell transplantation; Human cytomegalovirus; Prophylaxis

Phase 2 study of natalizumab plus standard corticosteroid treatment for high-risk acute graft-versus-host disease - Al Malki, Monzr M.; London, Kaitlyn; Baez, Janna; Akahoshi, Yu; Hogan, William J.; Etra, Aaron; Choe, Hannah; Hexner, Elizabeth; Langston, Amelia; Abhyankar, Sunil; Ponce, Doris M.; DeFilipp, Zachariah; et al. (Blood Advances, 2023)
Graft-versus-host disease (GVHD) of the gastrointestinal (GI) tract is the main cause of nonrelapse mortality (NRM) after allogeneic hematopoietic cell transplantation. Ann Arbor (AA) scores derived from serum biomarkers at onset of GVHD quantify GI crypt damage; AA2/3 scores correlate with resistance to treatment and higher NRM. We conducted a multicenter, phase 2 study using natalizumab, a humanized monoclonal antibody that blocks T-cell trafficking to the GI tract through the α4 subunit of α4β7 integrin, combined with corticosteroids as primary treatment for patients with new onset AA2/3 GVHD. Seventy-five patients who were evaluable were enrolled and treated; 81% received natalizumab within 2 days of starting corticosteroids. Therapy was well tolerated with no treatment emergent adverse events in <10% of patients. Outcomes for patients treated with natalizumab plus corticosteroids were compared with 150 well-matched controls from the MAGIC database whose primary treatment was corticosteroids alone. There were no significant differences in overall or complete response between patients treated with natalizumab plus corticosteroids and those treated with corticosteroids alone (60% vs 58%; P = .67% and 48% vs 48%; P = 1.0, respectively) including relevant subgroups. There were also no significant differences in NRM or overall survival at 12 months in patients treated with natalizumab plus corticosteroids compared with controls treated with corticosteroids.
CRIS-Team Scopus Importer:2023-09-29

Phase II study of bortezomib, cyclophosphamide and dexamethasone as induction therapy in multiple myeloma: DSMM XI trial - Einsele, Hermann; Engelhardt, Monika; Tapprich, Christoph; Mueller, Juergen; Liebisch, Peter; Langer, Christian; Kropff, Martin; Muegge, Lars O.; Jung, Wolfram; Wolf, Hans-Heinrich; Metzner, Bernd; Hart, Christina; et al. (British Journal of Haematology, 2017)
We assessed the safety and efficacy of bortezomib, cyclophosphamide and dexamethasone (VCD) induction therapy in previously untreated multiple myeloma patients. A total of 414 patients received three 21-day cycles of VCD prior to autologous stem-cell transplantation (ASCT). Most common grade >=3 adverse events were leucopenia (31·4%) and thrombocytopenia (6·8%). The overall response rate (ORR) by investigator-based assessment was 85·4%. Most patients (74%) underwent successful central laboratory-based molecular cytogenetic analysis. No clinically relevant differences in ORR post-induction were seen between patients with or without high-risk cytogenetic abnormalities (86·2% vs. 84·3%). Further follow-up data are available for 113 patients receiving ASCT who were included in a prospective consolidation trial (median follow-up, 55·5 months); median progression-free survival (PFS) was 35·3 months and median overall survival (OS) was not reached. In patients with high-risk versus standard-risk cytogenetics, median PFS was 19·9 vs. 43·6 months (P < 0·0001), and median OS was 54·7 months versus not reached (P = 0·0022). VCD is an effective and tolerable induction regimen; results suggest that VCD induces high response rates independently of cytogenetic risk status, but after long-term follow-up, cytogenetic high risk is associated with markedly reduced PFS and OS post-ASCT.
EVALuna2:25779

Phenotypic and functional alterations of myeloid-derived suppressor cells during the disease course of multiple sclerosis - Iacobaeus, Ellen; Douagi, Iyadh; Jitschin, Regina; Marcusson-Stahl, Maritha; Andren, Anton Toernqvist; Gavin, Caroline; Lefsihane, Katia; Davies, Lindsay C.; Mougiakakos, Dimitrios; Kadri, Nadir; Le Blanc, Katarina (Immunology and Cell Biology, 2018)
Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system involving dysregulated encephalitogenic T cells. Myeloid-derived suppressor cells (MDSCs) have been recognized for their important function in regulating T-cell responses. Recent studies have indicated a role for MDSCs in autoimmune diseases, but their significance in MS is not clear. Here, we assessed the frequencies of CD14+ HLA-DRlow monocytic MDSCs (Mo-MDSCs) and CD33+ CD15+ CD11b+ HLA-DRlow granulocytic MDSCs (Gr-MDSCs) and investigated phenotypic and functional differences of Mo-MDSCs at different clinical stages of MS and in healthy subjects (HC). Increased frequencies of Mo-MDSCs (P < 0.05) and Gr-MDSCs (P < 0.05) were observed in relapsing-remitting MS patients during relapse (RRMS-relapse) compared to stable RRMS (RRMS-rem). Secondary progressive MS (SPMS) patients displayed a decreased frequency of Mo-MDSCs and Gr-MDSCs compared to HC (P < 0.05). Mo-MDSCs within RRMS patients expressed significantly higher cell surface protein levels of CD86 and CD163 compared to SPMS patients. Mo-MDSCs within SPMS exhibited decreased mRNA expression of interleukin-10 and heme oxygenase 1 compared to RRMS and HC. Analysis of T-cell regulatory function of Mo-MDSCs demonstrated T-cell suppressive capacity in RRMS and HCs, while Mo-MDSCs of SPMS promoted autologous T-cell proliferation, which aligned with a differential cytokine profile compared to RRMS and HCs. This study is the first to show phenotypic and functional shifts of MDSCs between clinical stages of MS, suggesting a role for MDSCs as a therapeutic target to prevent MS disease progression.
EVALuna2:35092

Physiological levels of 25-hydroxyvitamin D3 induce a suppressive CD4+ T cell phenotype not reflected in the epigenetic landscape - Matos, Carina; Renner, Kathrin; Peuker, Alice; Schoenhammer, Gabriele; Schreiber, Laura; Bruss, Christina; Eder, Ruediger; Bruns, Heiko; Flamann, Cindy; Hoffmann, Petra; Gebhard, Claudia; Herr, Wolfgang; et al. (Scandinavian Journal of Immunology, 2022)
1,25-dihydroxyvitamin D3 (1,25(OH)2D3), the active metabolite of vitamin D3 has a strong impact on the differentiation and function of immune cells. Here we analysed the influence of its precursor 25-hydroxyvitamin D3 (25(OH)D3) on the differentiation of human CD4+ T cells applying physiological concentrations in vitro. Our data show that 25(OH)D3 is converted to its active form 1,25(OH)2D3 by T cells, which in turn supports FOXP3, CD25 and CTLA-4 expression and inhibits IFN-γ production. These changes were not reflected in the demethylation of the respective promoters. Furthermore, we investigated the impact of vitamin D3 metabolites under induced Treg (iTreg) polarization conditions using TGF-β. Surprisingly, no additive effect but a decreased percentage of FOXP3 expressing cells was observed. However, the combination of 25(OH)D3 or 1,25(OH)2D3 together with TGF-β further upregulated CD25 and CTLA-4 and significantly increased soluble CTLA-4 and IL-10 secretion whereas IFN-γ expression of iTreg was decreased. Our data suggest that physiological levels of 25(OH)D3 act as potent modulator of human CD4+ T cells and autocrine or paracrine production of 1,25(OH)2D3 by T cells might be crucial for the local regulation of an adaptive immune response. However, since no epigenetic changes are detected by 25(OH)D3 a rather transient phenotype is induced.
CRIS-Team Scopus Importer:2022-02-11

Piwi-like 1 protein expression is a prognostic factor for renal cell carcinoma patients - Stoehr, Christine; Steffens, Sandra; Polifka, Iris; Jung, Rudolf; Kahlmeyer, Andreas; Ivanyi, Philipp; Weber, Florian; Hartmann, Arndt; Wullich, Bernd; Wach, Sven; Taubert, Helge (Scientific Reports, 2019)
The Piwi-like genes belong to the Argonaute gene family and are conserved in plants, animals and humans. In addition to their essential role in the germ line and as stem cell-associated genes, Piwi-like proteins play a role in different cancer types but have yet to be studied in renal cell carcinoma (RCC). We investigated tissue micro arrays (TMAs) with tumor samples of two independent cohorts of RCC patients (N = 265 and N = 345); we used immunohistochemistry to assess the protein expression of Piwi-like 1. Applying an immunoreactive score (IRS), we found Piwi-like 1 positivity (IRS > 0) in 28.3% and 14.8% of the tumors in cohorts 1 and 2, respectively. Piwi-like 1 positivity was correlated with Fuhrman grade, tumor stage and the presence of distant metastasis (P < 0.005). Moreover, in univariate and multivariate analyses (adjusted to Fuhrman grade and tumor stage), Piwi-like 1 positivity was associated with a shorter cancer-specific survival in the patients in the second cohort. In addition, Piwi-like 1 expression allowed to further distinguish the RCC patients with high Fuhrman grade, high tumor stage, distant metastasis or high pre-operative levels of C-reactive protein, as Piwi-like 1 positivity was associated with a shorter cancer-specific survival in both cohorts. Our data encourage further investigations to enlighten the role of Piwi-like 1 and its function as a marker of poor prognosis in RCC patients.
CRIS-Team WoS Importer:2019-02-22

Point Mutations in the FLT3-ITD Region Are Rare but Recurrent Alterations in Adult AML and Associated With Concomitant KMT2A-PTD - Stasik, Sebastian; Kramer, Michael; Zukunft, Sven; Rollig, Christoph; Baldus, Claudia D.; Platzbecker, Uwe; Serve, Hubert; Muller-Tidow, Carsten; Schafer-Eckart, Kerstin; Kaufmann, Martin; Krause, Stefan; Sauer, Tim; et al. (Frontiers in Oncology, 2022)
FLT3-ITD mutations are common druggable alterations in patients with acute myeloid leukemia (AML) and associated with poor prognosis. Beside typical ITD mutations, point mutations and deletions in the juxtamembrane domain (JMD) have been observed. However, due to the low frequency of these alterations, there is only limited information on molecular and clinical associations. To evaluate the prognostic impact of non-ITD mutations in the FLT3 JMD region, we analyzed a large cohort of 1,539 adult AML patients treated in different protocols of the Study Alliance Leukemia, using next-generation sequencing. Non-ITD point mutations and deletions within the FLT3 JMD were identified with a prevalence of 1.23% (n = 19). Both FLT3-ITD and non-ITD mutations were associated with a higher rate of NPM1 (42%-61%; p < 0.001) and DNMT3A mutations (37%-43%; p < 0.001), as well as an increased percentage of peripheral blood (54%-65%) and bone marrow blast cells (74%; p < 0.001), compared to FLT3-wild-type patients. Most significantly, AML patients with FLT3 non-ITD mutations had a higher rate of concomitant KMT2A-PTD mutations (37.5%; p < 0.001) as compared to FLT3-ITD (7%) or FLT3-wild-type cases (4.5%). In a multivariable analysis, FLT3 non-ITD mutations were not an independent prognostic factor. However, patients with dual FLT3 non-ITD and KMT2A-PTD mutations showed a trend for inferior outcome, which points at a functional interaction in this subset of AML.
CRIS-Team WoS Importer:2022-04-29

Polatuzumab vedotin as a salvage and bridging treatment in relapsed or refractory large B-cell lymphomas - Liebers, Nora; Duell, Johannes; Fitzgerald, Donnacha; Kerkhoff, Andrea; Noerenberg, Daniel; Kaebisch, Eva; Acker, Fabian; Fuhrmann, Stephan; Leng, Corinna; Welslau, Manfred; Chemnitz, Jens; Middeke, Jan-Moritz; et al. (Blood Advances, 2021)
The antibody-drug conjugate polatuzumab vedotin (pola) has recently been approved in combination with bendamustine and rituximab (pola-BR) for patients with refractory or relapsed (r/r) large B-cell lymphoma (LBCL). To investigate the efficacy of pola-BR in a real-world setting, we retrospectively analyzed 105 patients with LBCL who were treated in 26 German centers under the national compassionate use program. Fifty-four patients received pola as a salvage treatment and 51 patients were treated with pola with the intention to bridge to chimeric antigen receptor (CAR) T-cell therapy (n 5 41) or allogeneic hematopoietic cell transplantation (n = 10). Notably, patients in the salvage and bridging cohort had received a median of 3 prior treatment lines. In the salvage cohort, the best overall response rate was 48.1%. The 6-month progression-free survival and overall survival (OS) was 27.7% and 49.6%, respectively. In the bridging cohort, 51.2% of patients could be successfully bridged with pola to the intended CAR T-cell therapy. The combination of pola bridging and successful CAR T-cell therapy resulted in a 6-month OS of 77.9% calculated from pola initiation. Pola vedotin-rituximab without a chemotherapy backbone demonstrated encouraging overall response rates up to 40%, highlighting both an appropriate alternative for patients unsuitable for chemotherapy and a new treatment option for bridging before leukapheresis in patients intended for CAR T-cell therapy. Furthermore, 7 of 12 patients with previous failure of CAR T-cell therapy responded to a pola-containing regimen. These findings suggest that pola may serve as effective salvage and bridging treatment of r/r LBCL patients.
CRIS-Team Scopus Importer:2021-07-30

Polymorphisms in the Hsp70 gene locus are genetically associated with systemic lupus erythematosus - Fuernrohr, Barbara G.; Wach, Sven; Kelly, Jennifer A.; Haslbeck, Martin; Weber, Christian K.; Stach, Christian M.; Hueber, Axel J.; Graef, Daniela; Spriewald, Bernd M.; Manger, Karin; Herrmann, Martin; Kaufman, Kenneth M.; et al. (Annals of the Rheumatic Diseases, 2010)
Background: Heat shock proteins (Hsps) play a role in the delivery and presentation of antigenic peptides and are thought to be involved in the pathogenesis of multifactorial diseases. Objective: To investigate genes encoding cytosolic Hsp70 proteins for associations of allelic variants with systemic lupus erythematosus (SLE). Methods: Case-control studies of two independent Caucasian SLE cohorts were performed. In a haplotype-tagging single-nucleotide polymorphism approach, common variants of HspA1L, HspA1A and HspA1B were genotyped and principal component analyses were performed for the cohort from the Oklahoma Medical Research Foundation (OMRF). Relative quantification of mRNA was carried out for each Hsp70 gene in healthy controls. Conditional regression analysis was performed to determine if allelic variants in Hsp70 act independently of HLA-DR3. Results: On analysis of common genetic variants of HspA1L, HspA1A and HspA1B, a haplotype significantly associated with SLE in the Erlangen-SLE cohort was identified, which was confirmed in the OMRF cohort. Depending on the cohorts, OR ranging from 1.43 to 1.88 and 2.64 to 3.16 was observed for individuals heterozygous and homozygous for the associated haplotype, respectively. Patients carrying the risk haplotype or the risk allele more often displayed autoantibodies to Ro and La in both cohorts. In healthy controls bearing this haplotype, the amount of HspA1A mRNA was significantly increased, whereas total Hsp70 protein concentration was not altered. Conclusions: Allelic variants of the Hsp70 genes are significantly associated with SLE in Caucasians, independently of HLA-DR3, and correlate with the presence of autoantibodies to Ro and La. Hence, the Hsp70 gene locus appears to be involved in SLE pathogenesis.

Polyol pathway links glucose metabolism to the aggressiveness of cancer cells - Schwab, Annemarie; Siddiqui, Aarif; Vazakidou, Maria Eleni; Napoli, Francesca; Böttcher, Martin; Menchicchi, Bianca; Raza, Umar; Saatci, Ozge; Krebs, Angela; Ferrazzi, Fulvia; Rapa, Ida; Dettmer-Wilde, Katja; et al. (Cancer Research, 2018)
Cancer cells alter their metabolism to support their malignant properties. In this study, we report that the glucose-transforming polyol pathway (PP) gene aldo-keto-reductase-1-member-B1 (AKR1B1) strongly correlates with epithelial-to-mesenchymal transition (EMT). This association was confirmed in samples from lung cancer patients and from an EMT-driven colon cancer mouse model with p53 deletion. In vitro, mesenchymal-like cancer cells showed increased AKR1B1 levels, and AKR1B1 knockdown was sufficient to revert EMT. An equivalent level of EMT suppression was measured by targeting the downstream enzyme sorbitol-dehydrogenase (SORD), further pointing at the involvement of the PP. Comparative RNA sequencing confirmed a profound alteration of EMT in PP-deficient cells, revealing a strong repression of TGF-? signature genes. Excess glucose was found to promote EMT through autocrine TGF-? stimulation, while PP-deficient cells were refractory to glucose-induced EMT. These data show that PP represents a molecular link between glucose metabolism, cancer differentiation, and aggressiveness, and may serve as a novel therapeutic target.
EVALuna2:10237

Positron Emission Tomography-Guided Treatment in Early-Stage Favorable Hodgkin Lymphoma: Final Results of the International, Randomized Phase III HD16 Trial by the German Hodgkin Study Group - Fuchs, Michael; Goergen, Helen; Kobe, Carsten; Kuhnert, Georg; Lohri, Andreas; Greil, Richard; Sasse, Stephanie; Topp, Max S.; Schäfer, Erhardt; Hertenstein, Bernd; Soekler, Martin; Vogelhuber, Martin; et al. (Journal of Clinical Oncology, 2019)
PURPOSE: Combined-modality treatment (CMT) with 2× ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine) and small-field radiotherapy is standard of care for patients with early-stage favorable Hodgkin lymphoma (HL). However, the role of radiotherapy has been challenged. Positron emission tomography (PET) after 2× ABVD (PET-2) might help to predict individual outcomes and guide treatment. METHODS: Between November 2009 and December 2015, we recruited patients age 18 to 75 years with newly diagnosed, early-stage favorable HL for this international randomized phase III trial. Patients were assigned to standard CMT of 2× ABVD and 20-Gy involved-field radiotherapy or PET-guided treatment, omitting involved-field radiotherapy after negative PET-2 (Deauville score < 3). Primary objectives were to exclude inferiority of 10% or more in 5-year progression-free survival (PFS) of ABVD alone compared with CMT in a per-protocol analysis among PET-2-negative patients (noninferiority margin for hazard ratio, 3.01) and to confirm PET-2 positivity (Deauville score ≥ 3) as a risk factor for PFS among CMT-treated patients. RESULTS: We enrolled 1,150 patients. Median follow-up was 45 months. Among 628 PET-2-negative, per-protocol-treated patients, 5-year PFS was 93.4% (95% CI, 90.4% to 96.5%) with CMT and 86.1% (95% CI, 81.4% to 90.9%) with ABVD (difference 7.3% [95% CI, 1.6% to 13.0%]; hazard ratio, 1.78 [95% CI, 1.02 to 3.12]). Five-year overall survival was 98.1% (95% CI, 96.5% to 99.8%) with CMT and 98.4% (95% CI, 96.5% to 100.0%) with ABVD. Among 693 patients who were assigned to CMT, 5-year PFS was 93.2% (95% CI, 90.2% to 96.2%) among PET-2-negative patients and 88.4% (95% CI, 84.2% to 92.6%) in PET-2-positive patients (P = .047). When using the more common liver cutoff (Deauville score, 4) for PET-2 positivity, the difference was more pronounced (5-year PFS, 93.1% [95% CI, 90.7% to 95.5%] v 80.9% [95% CI, 72.2% to 89.7%]; P = .0011). CONCLUSION: In early-stage favorable HL, a positive PET after two cycles ABVD indicates a high risk for treatment failure, particularly when a Deauville score of 4 is used as a cutoff for positivity. In PET-2-negative patients, radiotherapy cannot be omitted from CMT without clinically relevant loss of tumor control.
CRIS-Team Scopus Importer:2019-11-08

PPARδ-mediated mitochondrial rewiring of osteoblasts determines bone mass - Müller, Dorothea; Stoll, Cornelia; Palumbo-Zerr, Katrin; Böhm, Christina; Krishnacoumar, Brenda; Ipseiz, Natacha; Taubmann, Jule; Zimmermann, Max; Böttcher, Martin; Mougiakakos, Dimitrios; Tuckermann, Jan; Djouad, Farida; et al. (Scientific Reports, 2020)
Bone turnover, which is determined by osteoclast-mediated bone resorption and osteoblast-mediated bone formation, represents a highly energy consuming process. The metabolic requirements of osteoblast differentiation and mineralization, both essential for regular bone formation, however, remain incompletely understood. Here we identify the nuclear receptor peroxisome proliferator-activated receptor (PPAR) δ as key regulator of osteoblast metabolism. Induction of PPARδ was essential for the metabolic adaption and increased rate in mitochondrial respiration necessary for the differentiation and mineralization of osteoblasts. Osteoblast-specific deletion of PPARδ in mice, in turn, resulted in an altered energy homeostasis of osteoblasts, impaired mineralization and reduced bone mass. These data show that PPARδ acts as key regulator of osteoblast metabolism and highlight the relevance of cellular metabolic rewiring during osteoblast-mediated bone formation and bone-turnover.
CRIS-Team Scopus Importer:2020-06-02

Predicting Triple-Negative Breast Cancer Subtype Using Multiple Single Nucleotide Polymorphisms for Breast Cancer Risk and Several Variable Selection Methods - Häberle, Lothar; Hein, Alexander; Rübner, Matthias; Schneider, Michael; Ekici, Arif Bülent; Gaß, Paul; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Lo, Wing-Yee; Schroth, Werner; Brauch, Hiltrud; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Studies of triple-negative breast cancer have recently been extending the inclusion criteria and incorporating additional molecular markers into the selection criteria, opening up scope for targeted therapies. The screening phases required for studies of this type are often prolonged, since the process of determining the molecular subtype and carrying out additional biomarker assessment is time-consuming. Parameters such as germline genotypes capable of predicting the molecular subtype before it becomes available from pathology might be helpful for treatment planning and optimizing the timing and cost of screening phases. This appears to be feasible, as rapid and low-cost genotyping methods are becoming increasingly available. The aim of this study was to identify single nucleotide polymorphisms (SNPs) for breast cancer risk capable of predicting triple negativity, in addition to clinical predictors, in breast cancer patients.This cross-sectional observational study included 1271 women with invasive breast cancer who were treated at a university hospital. A total of 76 validated breast cancer risk SNPs were successfully genotyped. Univariate associations between each SNP and triple negativity were explored using logistic regression analyses. Several variable selection and regression techniques were applied to identify a set of SNPs that together improve the prediction of triple negativity in addition to the clinical predictors of age at diagnosis and body mass index (BMI). The most accurate prediction method was determined by cross-validation.The SNP rs10069690 (TERT, CLPTM1L) was the only significant SNP (corrected p = 0.02) after correction of p values for multiple testing in the univariate analyses. This SNP and three additional SNPs from the genes RAD51B, CCND1, and FGFR2 were selected for prediction of triple negativity. The addition of these SNPs to clinical predictors increased the cross-validated area under the curve (AUC) from 0.618 to 0.625. Age at diagnosis was the strongest predictor, stronger than any genetic characteristics.Prediction of triple-negative breast cancer can be improved if SNPs associated with breast cancer risk are added to a prediction rule based on age at diagnosis and BMI. This finding could be used for prescreening purposes in complex molecular therapy studies for triple-negative breast cancer.
EVALuna2:6850

Prediction and Prophylaxis of Immune Checkpoint Inhibitor-mediated Hepatitis - Schilling, H. L.; Hutchinson, J.; Kronenberg, K.; Riquelme, P.; Wenzel, J.; Glehr, G.; Zeman, F.; Evert, K.; Schmiedel, M.; Mickler, M.; Drexler, K.; Bitterer, F.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Prediction of Clinical Outcomes with Explainable Artificial Intelligence in Patients with Chronic Lymphocytic Leukemia - Hoffmann, Joerg; Eminovic, Semil; Wilhelm, Christian; Krause, Stefan; Neubauer, Andreas; Thrun, Michael C.; Ultsch, Alfred; Brendel, Cornelia (Current Oncology, 2023)
Background: The International Prognostic Index (IPI) is applied to predict the outcome of chronic lymphocytic leukemia (CLL) with five prognostic factors, including genetic analysis. We investigated whether multiparameter flow cytometry (MPFC) data of CLL samples could predict the outcome by methods of explainable artificial intelligence (XAI). Further, XAI should explain the results based on distinctive cell populations in MPFC dot plots. Methods: We analyzed MPFC data from the peripheral blood of 157 patients with CLL. The ALPODS XAI algorithm was used to identify cell populations that were predictive of inferior outcomes (death, failure of first-line treatment). The diagnostic ability of each XAI population was evaluated with receiver operating characteristic (ROC) curves. Results: ALPODS defined 17 populations with higher ability than the CLL-IPI to classify clinical outcomes (ROC: area under curve (AUC) 0.95 vs. 0.78). The best single classifier was an XAI population consisting of CD4+ T cells (AUC 0.78; 95% CI 0.70-0.86; p < 0.0001). Patients with low CD4+ T cells had an inferior outcome. The addition of the CD4+ T-cell population enhanced the predictive ability of the CLL-IPI (AUC 0.83; 95% CI 0.77-0.90; p < 0.0001). Conclusions: The ALPODS XAI algorithm detected highly predictive cell populations in CLL that may be able to refine conventional prognostic scores such as IPI.
CRIS-Team WoS Importer:2023-03-17

Prediction of Complete Remission and Survival in Acute Myeloid Leukemia Using Supervised Machine Learning - Eckardt, Jan-Niklas; Rollig, Christoph; Kramer, Michael; Stasik, Sebastian; Georgi, Julia-Annabell; Heisig, Peter; Kroschinsky, Frank P.; Schetelig, Johannes; Platzbecker, Uwe; Mueller-Tidow, Carsten; Sauer, Tim; Serve, Hubert; et al. (BLOOD, 2021)
CRIS-Team WoS Importer:2022-09-09

Prediction of complete remission and survival in acute myeloid leukemia using supervised machine learning - Eckardt, Jan Niklas; Röllig, Christoph; Metzeler, Klaus; Kramer, Michael; Stasik, Sebastian; Georgi, Julia Annabell; Heisig, Peter; Spiekermann, Karsten; Krug, Utz; Braess, Jan; Görlich, Dennis; Sauerland, Cristina M.; et al. (Haematologica, 2023)
Achievement of complete remission signifies a crucial milestone in the therapy of acute myeloid leukemia (AML) while refractory disease is associated with dismal outcomes. Hence, accurately identifying patients at risk is essential to tailor treatment concepts individually to disease biology. We used nine machine learning (ML) models to predict complete remission and 2-year overall survival in a large multicenter cohort of 1,383 AML patients who received intensive induction therapy. Clinical, laboratory, cytogenetic and molecular genetic data were incorporated and our results were validated on an external multicenter cohort. Our ML models autonomously selected predictive features including established markers of favorable or adverse risk as well as identifying markers of so-far controversial relevance. De novo AML, extramedullary AML, double-mutated CEBPA, mutations of CEBPA-bZIP, NPM1, FLT3-ITD, ASXL1, RUNX1, SF3B1, IKZF1, TP53, and U2AF1, t(8;21), inv(16)/t(16;16), del(5)/del(5q), del(17)/del(17p), normal or complex karyotypes, age and hemoglobin concentration at initial diagnosis were statistically significant markers predictive of complete remission, while t(8;21), del(5)/del(5q), inv(16)/t(16;16), del(17)/del(17p), double-mutated CEBPA, CEBPA-bZIP, NPM1, FLT3-ITD, DNMT3A, SF3B1, U2AF1, and TP53 mutations, age, white blood cell count, peripheral blast count, serum lactate dehydrogenase level and hemoglobin concentration at initial diagnosis as well as extramedullary manifestations were predictive for 2-year overall survival. For prediction of complete remission and 2-year overall survival areas under the receiver operating characteristic curves ranged between 0.77-0.86 and between 0.63-0.74, respectively in our test set, and between 0.71-0.80 and 0.65-0.75 in the external validation cohort. We demonstrated the feasibility of ML for risk stratification in AML as a model disease for hematologic neoplasms, using a scalable and reusable ML framework. Our study illustrates the clinical applicability of ML as a decision support system in hematology.
CRIS-Team Scopus Importer:2023-03-10

Prediction of Hearing Preservation in Vestibular Schwannoma Surgery According to Tumor Size and Anatomic Extension - Bozhkov, Yavor; Shawarba, Julia; Feulner, Julian; Winter, Fabian; Rampp, Stefan; Hoppe, Ulrich; Dörfler, Arnd; Iro, Heinrich; Buchfelder, Michael; Rössler, Karl (Otolaryngology-Head and Neck Surgery, 2021)
Objective: Vestibular schwannoma (VS) surgery is feasible for various tumor sizes that are inappropriate for wait and scan or radiosurgery. The predictive value of 2 grading systems was investigated for postoperative hearing preservation (HP) in a large series. Study Design: Retrospective analysis. Setting: Neurosurgical patient database of the University of Erlangen was queried between 2014 and 2017. Methods: Retrospective single-center analysis on 138 VSs operated on via a retrosigmoidal approach. The mean tumor size was 20.4 mm (SD, 7.6 mm) with fundal infiltration in 67.4%. The overall resection rate was 93.5%. Tumors were classified preoperatively by the 3-tier Erlangen grading system depending on size or the anatomically based 4-tier Koos grading system. Results: Preoperative hearing preservation was found in 70.3% of patients and was significantly correlated to tumor size (P =.001). For Erlangen grading, a mean postoperative serviceable hearing preservation rate of 32% was achieved: 83.3% for tumors <12 mm, 30.3% for tumors between 12 and 25 mm, and 5.3% for tumors >25 mm. In contrast, according to Koos grading, postoperative serviceable hearing preservation was 100% for grade 1 tumors (meatal), 35.6% for grade 2 (cisternal), 23.1% for grade 3 (brainstem contact), and 21.7% for grade 4 (brainstem compression). Of the total cohort, 86% had normal or nearly normal postoperative facial function (House-Brackmann grades 1 and 2). Conclusion: Surgery on small VSs can achieve excellent hearing preservation. Different grading has a significant influence on and correlates with postoperative hearing preservation. Tumor size seems more important than anatomic relationship.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Erlangen vestibula schwannoma grading; grading systems; hearing preservation; Koos vestibular schwannoma grading; vestibular schwannoma surgery

Preface - Hauschild, Axel; Koelbl, Oliver; Mackensen, Andreas; Schadendorf, Dirk (Oncology research and treatment, 2015)
EVALuna2:25749

Preformed Donor-Specific HLA Antibodies in Living and Deceased Donor Transplantation: A Multicenter Study - Ziemann, Malte; Altermann, Wolfgang; Angert, Katharina; Arns, Wolfgang; Bachmann, Anette; Bakchoul, Tamam; Banas, Bernhard; von Borstel, Annette; Budde, Klemens; Ditt, Vanessa; Einecke, Gunilla; Eisenberger, Ute; et al. (Clinical Journal of the American Society of Nephrology, 2019)
BACKGROUND AND OBJECTIVES: The prognostic value of preformed donor-specific HLA antibodies (DSA), which are only detectable by sensitive methods, remains controversial for kidney transplantation. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: The outcome of 4233 consecutive kidney transplants performed between 2012 and 2015 in 18 German transplant centers was evaluated. Most centers used a stepwise pretransplant antibody screening with bead array tests and differentiation of positive samples by single antigen assays. Using these screening results, DSA against HLA-A, -B, -C, -DRB1 and -DQB1 were determined. Data on clinical outcome and possible covariates were collected retrospectively. RESULTS: Pretransplant DSA were associated with lower overall graft survival, with a hazard ratio of 2.53 for living donation (95% confidence interval [95% CI], 1.49 to 4.29; P<0.001) and 1.59 for deceased donation (95% CI, 1.21 to 2.11; P=0.001). ABO-incompatible transplantation was associated with worse graft survival (hazard ratio, 2.09; 95% CI, 1.33 to 3.27; P=0.001) independent from DSA. There was no difference between DSA against class 1, class 2, or both. Stratification into DSA <3000 medium fluorescence intensity (MFI) and DSA ≥3000 MFI resulted in overlapping survival curves. Therefore, separate analyses were performed for 3-month and long-term graft survival. Although DSA <3000 MFI tended to be associated with both lower 3-month and long-term transplant survival in deceased donation, DSA ≥3000 MFI were only associated with worse long-term transplant survival in deceased donation. In living donation, only strong DSA were associated with reduced graft survival in the first 3 months, but both weak and strong DSA were associated with reduced long-term graft survival. A higher incidence of antibody-mediated rejection within 6 months was only associated with DSA ≥3000 MFI. CONCLUSIONS: Preformed DSA were associated with an increased risk for graft loss in kidney transplantation, which was greater in living than in deceased donation. Even weak DSA <3000 MFI were associated with worse graft survival. This association was stronger in living than deceased donation.
EVALuna2:184898

Presence of HLA-B27 is associated with changes of serum levels of mediators of the Wnt and hedgehog pathway - Aschermann, Sarah; Englbrecht, Matthias; Bergua, Antonio; Spriewald, Bernd M.; Said-Nahal, Rhula; Breban, Maxime; Schett, Georg; Rech, Juergen (Joint Bone Spine, 2016)
HLA-B27 is present in 5% of the Caucasian population and is strongly associated with the development of spondyloarthritis (SpA), a disease characterized by inflammation and substantial bone changes. We hypothesized that the presence of HLA-B27 in itself is associated with alterations of key regulatory of bone homeostasis.Sera of 241 individuals were assessed for the serum levels of Wnt pathway regulators, sclerostin and dickkopf (Dkk)-1 as well as Indian hedgehog (IHH) and collagen type I cleavage products (CTX1). Of the 151 HLA-B27+ subjects, 31 had SpA, 30 had anterior uveitis, 30 were healthy individuals and 60 healthy siblings of patients with SpA.Sclerostin levels were significantly (P<0.001) lower in HLA-B27+ subjects (314±21pg/mL) compared to HLA-B27 negative controls (mean±SEM: 492±30pg/mL), no matter if subjects were either healthy, or affected by SpA or uveitis. Similar results were found for Dkk-1. No differences between the groups with respect to the bone resorption marker CTX1 were found. In contrast, IHH levels were significantly (P<0.001) higher in the carriers of HLA-B27 than in the negative controls.Changes in key regulators of the Wnt pathway as well as IHH, a molecule regulating endochondral ossification, are found in HLA-B27 carriers, independent if they were healthy or affected by uveitis or SpA.
EVALuna2:13168

PREVALENCE AND IMPACT OF PREFORMED ANTI-HLA ANTIBODIES OF THE IGA ISOTYPE IN KIDNEY TRANSPLANTATION - Preiss, A.; Bach, Christian; Spriewald, B.; Banas, B.; Zecher, D.; Arnold, Martin (2018)
EVALuna2:35090

Prevention of CMV/EBV reactivation by double-specific T cells in patients after allogeneic stem cell transplantation: results from the randomized phase I/IIa MULTIVIR-01 study - Gerbitz, Armin; Gary, Regina; Aigner, Michael; Moosmann, Andreas; Kremer, Anita; Schmid, Christoph; Hirschbuehl, Klaus; Wagner, Eva; Hauptrock, Beate; Teschner, Daniel; Rösler, Wolf; Spriewald, Bernd; et al. (Frontiers in Immunology, 2023)
Introduction: Allogeneic stem cell transplantation is used to cure hematologic malignancies or deficiencies of the hematopoietic system. It is associated with severe immunodeficiency of the host early after transplant and therefore early reactivation of latent herpesviruses such as CMV and EBV within the first 100 days are frequent. Small studies and case series indicated that application of herpes virus specific T cells can control and prevent disease in this patient population. Methods: We report the results of a randomized controlled multi centre phase I/IIa study (MULTIVIR-01) using a newly developed T cell product with specificity for CMV and EBV derived from the allogeneic stem cell grafts used for transplantation. The study aimed at prevention and preemptive treatment of both viruses in patients after allogeneic stem cell transplantation targeting first infusion on day +30. Primary endpoints were acute transfusion reaction and acute-graft versus-host-disease after infusion of activated T cells. Results: Thirty-three patients were screened and 9 patients were treated with a total of 25 doses of the T cell product. We show that central manufacturing can be achieved successfully under study conditions and the product can be applied without major side effects. Overall survival, transplant related mortality, cumulative incidence of graft versus host disease and number of severe adverse events were not different between treatment and control groups. Expansion of CMV/EBV specific T cells was observed in a fraction of patients, but overall there was no difference in virus reactivation. Discussion: Our study results indicate peptide stimulated epitope specific T cells derived from stem cell grafts can be administered safely for prevention and preemptive treatment of reactivation without evidence for induction of acute graft versus host disease. Clinical trial registration: https://clinicaltrials.gov, identifier NCT02227641.
CRIS-Team Scopus Importer:2023-11-24
Keywords: allogeneic; cytomegalovirus CMV; epitope specificity; Epstein-Barr virus EBV; prevention; reactivation; stem cell transplantation (SCT)

Primary parotid gland lymphoma: pitfalls in the use of ultrasound imaging by a great pretender - Mantsopoulos, Konstantinos; Koch, M.; Fauck, Vanessa; Schinz, Katharina; Schapher, Mirco; Constantinidis, J.; Rösler, Wolf; Iro, Heinrich (International journal of oral and maxillofacial surgery, 2020)
The aim of this study was to highlight several misleading imaging and clinical aspects of parotid gland lymphoma, taking our personal experience and relevant literature reports into consideration. The records of all patients diagnosed with lymphoma in the parotid gland between 2005 and 2017 were examined retrospectively. Sixty-seven patients were included in this study. The mean age was 61.4 years. The most frequent histological entities were marginal zone B-cell lymphoma (31.3%) and follicular lymphoma (28.4%). The tumour was stage I in 35 cases (52.2%), stage II in 13 cases (19.4%), stage III in 11 cases (16.4%), and stage IV in eight cases (11.9%). B symptoms were seen in only three patients (4.5%). The diagnosis was made after parotidectomy in 51 cases (76.1%), by core needle biopsy in 14 cases (20.9%), and by means of open biopsy in the remaining two cases (3.0%). Parotid gland lymphoma represents a diagnostically challenging, multifaceted entity that can easily mimic both benign and malignant conditions. This entity should be included in the differential diagnosis of almost all types of parotid lesion, as it seems to play the role of a great pretender.
CRIS-Team Scopus Importer:2021-04-19
Keywords: diffuse large B-cell lymphoma; follicular lymphoma; lymphoma; MALT lymphoma; marginal zone B-cell lymphoma; parotid gland; parotidectomy; ultrasound

Primary prophylaxis of bacterial infections and Pneumocystis jirovecii pneumonia in patients with hematologic malignancies and solid tumors: 2020 updated guidelines of the Infectious Diseases Working Party of the German Society of Hematology and Medical Oncology (AGIHO/DGHO) - Classen, Annika Y.; Henze, Larissa; Von Lilienfeld-Toal, Marie; Maschmeyer, Georg; Sandherr, Michael; Graeff, Luisa Duran; Alakel, Nael; Christopeit, Maximilian; Krause, Stefan; Mayer, Karin; Neumann, Silke; Cornely, Oliver A.; et al. (Annals of Hematology, 2021)
Hematologic and oncologic patients with chemo- or immunotherapy-related immunosuppression are at substantial risk for bacterial infections and Pneumocystis jirovecii pneumonia (PcP). As bacterial resistances are increasing worldwide and new research reshapes our understanding of the interactions between the human host and bacterial commensals, administration of antibacterial prophylaxis has become a matter of discussion. This guideline constitutes an update of the 2013 published guideline of the Infectious Diseases Working Party (AGIHO) of the German Society for Hematology and Medical Oncology (DGHO). It gives an overview about current strategies for antibacterial prophylaxis in cancer patients while taking into account the impact of antibacterial prophylaxis on the human microbiome and resistance development. Current literature published from January 2012 to August 2020 was searched and evidence-based recommendations were developed by an expert panel. All recommendations were discussed and approved in a consensus conference of the AGIHO prior to publication. As a result, we present a comprehensive update and extension of our guideline for antibacterial and PcP prophylaxis in cancer patients.
CRIS-Team WoS Importer:2021-05-21

Primary prophylaxis of invasive fungal infections in patients with haematological malignancies: 2017 update of the recommendations of the Infectious Diseases Working Party (AGIHO) of the German Society for Haematology and Medical Oncology (DGHO) - Mellinghoff, Sibylle C.; Panse, Jens; Alakel, Nael; Behre, Gerhard; Buchheidt, Dieter; Christopeit, Maximilian; Hasenkamp, Justin; Kiehl, Michael; Koldehoff, Michael; Krause, Stefan; Lehners, Nicola; von Lilienfeld-Toal, Marie; et al. (Annals of Hematology, 2017)
Immunocompromised patients are at high risk of invasive fungal infections (IFI), in particular those with haematological malignancies undergoing remission-induction chemotherapy for acute myeloid leukaemia (AML) or myelodysplastic syndrome (MDS) and recipients of allogeneic haematopoietic stem cell transplants (HSCT). Despite the development of new treatment options in the past decades, IFI remains a concern due to substantial morbidity and mortality in these patient populations. In addition, the increasing use of new immune modulating drugs in cancer therapy has opened an entirely new spectrum of at risk periods. Since the last edition of antifungal prophylaxis recommendations of the German Society for Haematology and Medical Oncology in 2014, seven clinical trials regarding antifungal prophylaxis in patients with haematological malignancies have been published, comprising 1227 patients. This update assesses the impact of this additional evidence and effective revisions. Our key recommendations are the following: prophylaxis should be performed with posaconazole delayed release tablets during remission induction chemotherapy for AML and MDS (AI). Posaconazole iv can be used when the oral route is contraindicated or not feasible. Intravenous liposomal amphotericin B did not significantly decrease IFI rates in acute lymphoblastic leukaemia (ALL) patients during induction chemotherapy, and there is poor evidence to recommend it for prophylaxis in these patients (CI). Despite substantial risk of IFI, we cannot provide a stronger recommendation for these patients. There is poor evidence regarding voriconazole prophylaxis in patients with neutropenia (CII). Therapeutic drug monitoring TDM should be performed within 2 to 5 days of initiating voriconazole prophylaxis and should be repeated in case of suspicious adverse events or of dose changes of interacting drugs (BIItu). General TDM during posaconazole prophylaxis is not recommended (CIItu), but may be helpful in cases of clinical failure such as breakthrough IFI for verification of compliance or absorption.
EVALuna2:25780

Primary prophylaxis of invasive fungal infections in patients with haematologic malignancies. 2014 update of the recommendations of the Infectious Diseases Working Party of the German Society for Haematology and Oncology - Tacke, Daniela; Buchheidt, Dieter; Karthaus, Meinolf; Krause, Stefan; Maschmeyer, Georg; Neumann, Silke; Ostermann, Helmut; Penack, Olaf; Rieger, Christina; Ruhnke, Markus; Sandherr, Michael; Schweer, Katharina E.; et al. (Annals of Hematology, 2014)
Invasive fungal infections cause substantial morbidity and mortality in immunocompromised patients, particularly in those with haematological malignancies and recipients of allogeneic haematopoietic stem cell transplantation. Difficulties in diagnosing invasive fungal infections and subsequent delays in treatment initiation lead to unfavourable outcomes and emphasise the importance of prophylaxis. Since the recommendations of the Infectious Diseases Working Party of the German Society for Haematology and Oncology in 2009, results of 14 additional clinical studies have been published comprising 2,899 patients and initiating this update. Key recommendations for adult patients are as follows: Posaconazole remains the drug of choice during remission-induction chemotherapy in acute myeloid leukaemia, myelodysplastic syndrome and allogeneic haematopoietic stem cell transplantation with graft versus host disease (AI). In the pre-engraftment period of allogeneic transplantation, several antifungals are appropriate and can be recommended with equal strength: voriconazole (BI), micafungin (BI), fluconazole (BI) and posaconazole (BII). There is poor evidence regarding antifungal prophylaxis in the post-engraftment period of allogeneic haematopoietic stem cell transplantation if no steroids for treatment of graft versus host disease are required. Aerosolised liposomal amphotericin B inhalation in conjunction with fluconazole can be used in patients with prolonged neutropenia (BII).
EVALuna2:25698

Primary vaccination in adult patients after allogeneic hematopoietic stem cell transplantation – A single center retrospective efficacy analysis - Sattler, Clara; Hoffmann, Petra; Herzberg, Philipp Yorck; Weber, Daniela; Holler, Barbara; Fehn, Ute; Plentz, Annelie; Beckhove, Philipp; Winkler, Julia; Edinger, Matthias; Herr, Wolfgang; Holler, Ernst; et al. (Vaccine, 2021)
Allogeneic hematopoietic stem cell transplantation (alloHSCT) results in a loss of humoral immunity and subsequent risk for severe infections. Thus, re-vaccination is required but may fail due to incomplete immune reconstitution. We retrospectively analyzed predictors of immune response to primary vaccination applied according to the EBMT (European Blood and Marrow Transplantation Group) recommendations. Serologic response to vaccination against diphtheria (D), tetanus (T), Bordetella pertussis (aP) and Haemophilus influenzae (Hib) (administrated as combined DTaP-Hib-IPV vaccination) was studied in 84 alloHSCT patients transplanted between 2008 and 2015 (age at alloHSCT: 18.6–70.6 years). All patients with a relapse-free survival of ≥9 months, at least 3 consecutive vaccinations and absence of intravenous immunoglobulin administration within 3 months before and after vaccination met the primary inclusion criteria. Additionally, immunological response to a pneumococcal conjugate vaccine was analyzed in a subgroup of 67 patients. Patients’ characteristics at the time of first vaccination were recorded. Responses were measured as vaccine-specific antibody titers. Regarding DTaP-Hib-IPV vaccination, 89.3% (n = 75) of all patients achieved protective titers to at least 3 of the 4 vaccine components and were thus considered responders. 10.7% (n = 9) of the patients were classified as non-responders with positive immune response to less than 3 components. Highest response was observed for Hib (97.4%), tetanus (95.2%) and pneumococcal vaccination (83.6%) while only 68.3% responded to vaccination against Bordetella pertussis. Significant risk factors for failure of vaccination response included low B cell counts (p < 0.001; cut-off: 0.05 B cells/nl) and low IgG levels (p = 0.026; mean IgG of responders 816 mg/dl vs. 475 mg/dl of non-responders). Further, a trend was observed that prior cGvHD impairs vaccination response as 88.9% of the non-responders but only 54.7% of the responders had prior cGvHD (p = 0.073). The results demonstrate, that the currently proposed vaccination strategy leads to seroprotection in the majority of alloHSCT patients.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Allogeneic hematopoietic stem cell transplantation; B cell reconstitution; GvHD; Immune response; Vaccination

Primary vaccination in adult patients after allogeneic hematopoietic stem cell transplantation - a single center retrospective efficacy analysis - Sattler, C.; Hoffmann, P.; Weber, D.; Holler, B.; Fehn, U.; Plentz, A.; Beckhove, P.; Winkler, Julia; Edinger, M.; Herr, W.; Holler, E.; Wolff, D. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Priorities of German Oncologists. Results of the "choosing wisely" survey of the German Society of Hematology and Medical Oncology (DGHO) - Krause, Stefan; Oldenburg, Michael; Hallek, Michael; Neubauer, Andreas (Deutsche Medizinische Wochenschrift, 2017)
Background During the preparation of "choosing wisely" recommendations, the German Society of Hematology and Medical Oncology (DGHO) had performed a member survey. The large body of replies was systematically and quantitatively analyzed for this report. Methods Replies to the draft recommendations are quantified. Free text replies were iteratively categorized in three levels according to medical categories and additionally, according to their general target of necessary action. Results 492 members completed the survey within the given limit of 2 weeks. Draft recommendations against oversupply were widely supported (77 %-88 %). 1598 free text replies were analyzed. Unnecessary use of resources was requested in several fields in accordance with our recommendations. Strong demand was put forward regarding soft factors: "talking medicine", individually tailored therapy, supportive medicine and palliative care (51 % together) and social resources (11 %). Possible under-supply was less frequently described in fields of expensive measures (17 % of replies). Conclusion In the replies to our survey, we found a strong statement for a plus in talking medicine in oncology. Every physician caring for these patients can contribute to this demand. Structural improvements in continuing education and reimbursement in this field are desirable.
EVALuna2:25777

Profiling extracellular vesicles (EV) in patients with acute GvHD after allogeneic stem cell transplantation - Böttcher, Martin; Stoll, Andrej; Böttcher-Loschinski, Romy; Rösler, Wolf; Winkler, Julia; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon; Baur, Rebecca (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Prognostic Relevance of Type 2 Diabetes and Metformin Treatment in Head and Neck Melanoma: Results from a Population-Based Cohort Study - Spoerl, Steffen; Gerken, Michael; Schimnitz, Susanne; Taxis, Juergen; Fischer, Rene; Lindner, Sophia R. R.; Ettl, Tobias; Ludwig, Nils; Spörl, Silvia; Reichert, Torsten E. E.; Spanier, Gerrit (Current Oncology, 2022)
Background: Type 2 Diabetes (DM2) and the consecutively daily use of antidiabetic medication are characterized by a frequent prevalence worldwide and were shown to impact the initiation and progression of malignant diseases. While these effects were observed in a variety of malignancies, comprehensive data about the role of DM2 and antidiabetic drugs in the outcome of head and neck melanoma (HNM) patients are missing. Methods: This retrospective population-based cohort study included 382 HNM patients from Eastern Bavaria having received tumor resection to negative margins between 2010 and 2017. Recurrence-free survival (RFS) was evaluated with regard to DM2 and routine metformin intake. Statistical analysis was performed by uni- and multivariate analyses. The median follow-up time was 5.6 years. Results: DM2 was diagnosed in 68 patients (17.8%), routine metformin intake was found in 39 cases (10.2%). The univariate survival analysis revealed impaired 5-year RFS in HNM patients with DM2 compared to non-diabetic controls (p = 0.016; 64.0% and 74.5%, respectively). The multivariate Cox regression substantiated this effect (HR = 1.980, 95% CI = 1.108-3.538, p = 0.021). In detail, the cumulative locoregional recurrence rate displayed the most far-reaching negative effect on the RFS of diabetic HNM patients (HR = 4.173, 95% CI = 1.628-10.697, p = 0.003). For metformin intake, a profound positive effect on the RFS in multivariate statistics was observed, both in the complete cohort (HR = 0.396, 95% CI = 0.177-0.884, p = 0.024) as well as in the cohort of diabetic HNM patients (HR = 0.352, 95% CI = 0.135-0.913, p = 0.032). Conclusions: This study emphasizes that DM2 is a relevant comorbid condition in HNM patients, impairing patient survival. Metformin intake was associated with a favorable outcome in HNM patients, providing possible therapeutic implications for future adjuvant treatment regimes.
CRIS-Team WoS Importer:2023-01-06

Prognostic significance of tumor-associated lymphangiogenesis in malignant melanomas of the conjunctiva - Heindl, Ludwig M.; Hofmann-Rummelt, Carmen; Adler, Werner; Bosch, Jacobus J.; Holbach, Leonard M.; Naumann, Gottfried; Kruse, Friedrich; Cursiefen, Claus (Ophthalmology, 2011)
To evaluate whether tumor-associated lymphangiogenesis contributes to prognosis of conjunctival malignant melanomas and to study its association with other tumor characteristics.Nonrandomized, retrospective case series.A total of 109 consecutive patients with primary conjunctival malignant melanoma.Proliferating lymphatic vessels were identified immunohistochemically using lymphatic vascular endothelial hyaluronan receptor-1 and podoplanin as specific lymphatic endothelial markers and Ki-67 as proliferation marker. Baseline tumor characteristics included tumor location, tumor thickness, tumor diameter, tumor origin, and tumor growth pattern. Kaplan-Meier and Cox regression analyses of the risk of local recurrence, lymphatic spread, distant metastasis, and melanoma-related death were performed.Intratumoral lymphatic vascular density and its association with tumor characteristics and recurrence-free, lymphatic spread-free, distant metastasis-free, and melanoma-specific survival.Intratumoral and peritumoral proliferating lymphatic vessels could be detected in all of the 109 conjunctival melanoma samples. High intratumoral lymphatic density was significantly associated with palpebral tumor location (P<0.001), greater tumor thickness (P<0.001), larger tumor diameter (P = 0.001), tumor origin de novo (P= 0.002), and nodular tumor growth pattern (P = 0.037). Patients with high intratumoral lymphatic density revealed significantly lower recurrence-free, lymphatic spread-free, distant metastasis-free, and melanoma-specific survival rates (P<0.001 for all). By multivariate Cox regression, factors predictive of local recurrence included palpebral tumor location (hazard ratio [HR] 2.66, P = 0.014), large tumor diameter (HR 5.48, P<0.001), and high intratumoral lymphatic density (HR 2.48, P = 0.043); factors predictive of lymphatic spread included palpebral tumor location (HR 4.13, P = 0.009), high tumor thickness (HR 12.17, P<0.001), and high intratumoral lymphatic density (HR 6.79, P = 0.019); factors predictive of distant metastasis included palpebral tumor location (HR 7.63, P<0.001), high tumor thickness (HR 8.60, P<0.001), large tumor diameter (HR 0.30, P = 0.029), and high intratumoral lymphatic density (HR 8.90, P = 0.047); and factors predictive of melanoma-related death included palpebral tumor location (HR 7.74, P<0.001), high tumor thickness (HR 10.88, P<0.001), large tumor diameter (HR 0.28, P = 0.018), and, with borderline significance, high intratumoral lymphatic density (HR 8.46, P = 0.052).Tumor-associated lymphangiogenesis seems to be associated with an increased risk of local recurrence, lymphatic spread, distant metastasis, and melanoma-related death in patients with conjunctival malignant melanomas.The author(s) have no proprietary or commercial interest in any materials discussed in this article.
EVALuna2:5322

Prognostic Value of Elafin in Acute Graft-Versus-Host Disease - Zewde, Makda Getachew; Morales, George; Gandhi, Isha; Ozbek, Umut; Aguayo-Hiraldo, Paibel; Ayuk, Francis A.; Baez, Janna; Chanswangphuwana, Chantiya; Choe, Hannah; Defilipp, Zachariah; Etra, Aaron; Grupp, Stephan A.; et al. (BLOOD, 2021)
CRIS-Team WoS Importer:2022-09-09

Prognostic Value of Perineural Invasion on Survival and Recurrence in Oral Squamous Cell Carcinoma - Spoerl, Steffen; Spörl, Silvia; Reil, Stephanie; Gerken, Michael; Ludwig, Nils; Taxis, Juergen; Fischer, René; Ettl, Tobias; Reichert, Torsten E.; Spanier, Gerrit (Diagnostics, 2022)
A diagnosis of perineural invasion (PNI) is widely accepted as an unfavorable prognostic factor in various solid malignancies. Although PNI has been described as a high-risk parameter in oral squamous cell carcinoma (OSCC), its role in the current staging manuals of the American Joint Committee on Cancer (AJCC) is rather subordinate. We analysed the prognostic value of PNI on survival and recurrence in a large, multicenter OSCC cohort and a population-based approach. A total of 493 OSCC patients with primary tumor resection to negative margins and concomitant neck dissection between 2010 and 2017 were enrolled. PNI was evaluated in relation to overall survival (OAS) and recurrence-free survival (RFS) using uni-and multi-variable Cox regression. The median follow-up time was 5.0 years and PNI was diagnosed in 48 patients (9.7%). A patho-histological verification of PNI correlated significantly with a deteriorated OAS in uni-(HR 2.312; 95% CI 2.312–3.493, p = 0.001) and multivariable Cox regression (HR 1.820; 95% CI 1.164–2.847, p = 0.009). Additionally, a diagnosis of PNI correlated with increased cumulative, as well as distant, metastasis 5-year-recurrence rates (p = 0.027 and p = 0.011, respectively). The application of adjuvant radiotherapy (RT) or radiochemotherapy (RCT) in patients with PNI did not alter OAS or RFS in survival analysis when compared to patients without PNI. The results underline the adverse impact of PNI on the survival and recurrence of surgically treated OSCC patients. Based on our findings, we highly recommend an emphasis on PNI in the TNM staging concept.
CRIS-Team Scopus Importer:2022-05-20
Keywords: oral cancer; oral squamous cell carcinoma; perineural invasion; PNI; recurrence; survival

Prolyl Hydroxylase 3 (Phd3) Is a Therapeutic Target in Isocitrate Dehydrogenase 1 (IDH1) Mutated Acute Myeloid Leukemia - Chaturvedi, Anuhar; Cruz, Michelle Maria Araujo; Goparaju, Ramya; Gabdoulline, Razif; Schottmann, Renate; Goerlich, Kerstin; Kloos, Arnold; Thol, Felicitas; Geffers, Robert; Mougiakakos, Dimitrios; Carmeliet, Peter; Ganser, Arnold; et al. (BLOOD, 2018)
CRIS-Team WoS Importer:2019-03-06

Prophylaxis of bacterial Infections and Pneumocystis jirovecii pneumonia in Female Patients with hematological and oncological Diseases: Updated Guideline of the Working Group on Infections (AGIHO) of the German Society for Hematology and Oncology (DGHO) - Classen, A. Y.; Henze, L.; Von Lilienfeld-Toal, M.; Maschmeyer, G.; Sandherr, M.; Duran, Graeff L.; Alakel, N.; Christopeit, M.; Krause, Stefan; Mayer, K.; Neumann, S.; Cornely, O. A.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Prospective Multicenter BAL Study: Focus real-time PCR - Springer, J.; Rickerts, V.; Teschner, D.; Kessel, J.; Liebregts, T.; Cornely, A.; Schwartz, S.; Meintker, Lisa; Heinz, W.; Willinger, B.; Kiehl, M.; Maschmeyer, G.; et al. (MYCOSES, 2020)
CRIS-Team WoS Importer:2020-10-02

Protein kinase C-β-dependent changes in the glucose metabolism of bone marrow stromal cells of chronic lymphocytic leukemia - Von Heydebrand, Franziska; Fuchs, Maximilian; Kunz, Meik; Kremer, Anita; Oostendorp, Robert A. J.; Wilke, Jochen; Leitges, Michael; Egle, Alexander; Mackensen, Andreas; Lutzny-Geier, Gloria; Völkl, Simon (Stem Cells, 2021)
Survival of chronic lymphocytic leukemia (CLL) cells critically depends on the support of an adapted and therefore appropriate tumor microenvironment. Increasing evidence suggests that B-cell receptor-associated kinases such as protein kinase C-β (PKCβ) or Lyn kinase are essential for the formation of a microenvironment supporting leukemic growth. Here, we describe the impact of PKCβ on the glucose metabolism in bone marrow stromal cells (BMSC) upon CLL contact. BMSC get activated by CLL contact expressing stromal PKCβ that diminishes mitochondrial stress and apoptosis in CLL cells by stimulating glucose uptake. In BMSC, the upregulation of PKCβ results in increased mitochondrial depolarization and leads to a metabolic switch toward oxidative phosphorylation. In addition, PKCβ-deficient BMSC regulates the expression of Hnf1 promoting stromal insulin signaling after CLL contact. Our data suggest that targeting PKCβ and the glucose metabolism of the leukemic niche could be a potential therapeutic strategy to overcome stroma-mediated drug resistance.
CRIS-Team Scopus Importer:2021-03-05
Keywords: BMSC; CLL; glucose metabolism; PKCβ

Proteomics of diphtheria toxoid vaccines reveals multiple proteins that are immunogenic and may contribute to protection of humans against Corynebacterium diphtheriae - Möller, Jens; Kraner, Max; Sonnewald, Uwe; Sangal, Vartul; Tittlbach, Hannes; Winkler, Julia; Winkler, Thomas; Melnikov, Vyacheslav; Lang, Roland; Sing, Andreas; Mattos-Guaraldi, Ana Luiza; Burkovski, Andreas (Vaccine, 2019)
Introduced for mass immunization in the 1920s, vaccines against diphtheria are among the oldest and safest vaccines known. The basic principle of their production is the inactivation of purified diphtheria toxin by formaldehyde cross-linking, which converts the potentially fatal toxin in a completely harmless protein aggregate, which is still immunogenic. Since in addition to diphtheria toxin also other proteins may be secreted by Corynebacterium diphtheriae during cultivation, we assumed that diphtheria toxoid might not be the only component present in the vaccine. To address this question, we established a protocol to reverse formaldehyde cross-linking and carried out mass spectrometric analyses. Different secreted, membrane-associated and cytoplasmic proteins of C. diphtheriae were detected in several vaccine preparations from across the world. Based on these results, bioinformatics and Western blot analyses were applied to characterize if these proteins are immunogenic and may therefore support protection against C. diphtheriae. In frame of this study, we could show that the C. diphtheriae toxoid vaccines induce antibodies against different C. diphtheriae proteins and against diphtheria toxin secreted by Corynebacterium ulcerans, an emerging pathogen which is outnumbering C. diphtheriae as cause of diphtheria-like illness in Western Europe.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Corynebacteria; Corynebacterium ulcerans; Exoproteome; Mass spectrometry; Proteomics; Secretome; Vaccination

Purification and functional characterization of CD34(+) cells from cryopreserved apheresis products of patients with bone marrow infiltrating malignancies - Wendland, Kerstin; Petkovic, S.; Aigner, Michael; Strobel, Julian; Mackensen, Andreas; Müller, Fabian (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Randomized, Double-Blind, Phase III Trial of Enzastaurin Versus Placebo in Patients Achieving Remission After First-Line Therapy for High-Risk Diffuse Large B-Cell Lymphoma - Crump, Michael; Leppa, Sirpa; Fayad, Luis; Lee, Je Jung; Di Rocco, Alice; Ogura, Michinori; Hagberg, Hans; Schnell, Frederick; Rifkin, Robert; Mackensen, Andreas; Offner, Fritz; Pinter-Brown, Lauren; et al. (Journal of Clinical Oncology, 2016)
To compare disease-free survival (DFS) after maintenance therapy with the selective protein kinase C ? (PKC?) inhibitor, enzastaurin, versus placebo in patients with diffuse large B-cell lymphoma (DLBCL) in complete remission and with a high risk of relapse after first-line therapy.This multicenter, phase III, randomized, double-blind, placebo-controlled trial enrolled patients who were at high risk of recurrence after rituximab-cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP). Patients (N = 758) with stage II bulky or stage III to IV DLBCL, three or more International Prognostic Index risk factors at diagnosis, and a complete response or unconfirmed complete response after 6 to 8 cycles of R-CHOP were assigned 2:1 to receive oral enzastaurin 500 mg daily or placebo for 3 years or until disease progression or unacceptable toxicity. Primary end point was DFS 3 years after the last patient entered treatment. Correlative analyses of biomarkers, including cell of origin by immunohistochemistry and PKC? expression, with efficacy outcomes were exploratory objectives.After a median follow-up of 48 months, DFS hazard ratio for enzastaurin versus placebo was 0.92 (95% CI, 0.689 to 1.216; two-sided log-rank P = .541; 4-year DFS, 70% v 71%, respectively). Independent of treatment, no significant associations were observed between PKC? protein expression or cell of origin and DFS or overall survival.Enzastaurin did not significantly improve DFS in patients with high-risk DLBCL after achieving complete response to R-CHOP. Achievement of a complete response may have abrogated the prognostic significance of cell of origin by immunohistochemistry.
EVALuna2:25745

Rapid and Efficient Gene Editing for Direct Transplantation of Naive Murine Cas9+ T Cells - Majumder, Snigdha; Jugovic, Isabelle; Saul, Domenica; Bell, Luisa; Hundhausen, Nadine; Seal, Rishav; Beilhack, Andreas; Rosenwald, Andreas; Mougiakakos, Dimitrios; Berberich-Siebelt, Friederike (Frontiers in Immunology, 2021)
Gene editing of primary T cells is a difficult task. However, it is important for research and especially for clinical T-cell transfers. CRISPR/Cas9 is the most powerful gene-editing technique. It has to be applied to cells by either retroviral transduction or electroporation of ribonucleoprotein complexes. Only the latter is possible with resting T cells. Here, we make use of Cas9 transgenic mice and demonstrate nucleofection of pre-stimulated and, importantly, of naive CD3+ T cells with guideRNA only. This proved to be rapid and efficient with no need of further selection. In the mixture of Cas9+CD3+ T cells, CD4+ and CD8+ conventional as well as regulatory T cells were targeted concurrently. IL-7 supported survival and naivety in vitro, but T cells were also transplantable immediately after nucleofection and elicited their function like unprocessed T cells. Accordingly, metabolic reprogramming reached normal levels within days. In a major mismatch model of GvHD, not only ablation of NFATc1 and/or NFATc2, but also of the NFAT-target gene IRF4 in naïve primary murine Cas9+CD3+ T cells by gRNA-only nucleofection ameliorated GvHD. However, pre-activated murine T cells could not achieve long-term protection from GvHD upon single NFATc1 or NFATc2 knockout. This emphasizes the necessity of gene-editing and transferring unstimulated human T cells during allogenic hematopoietic stem cell transplantation.
CRIS-Team Scopus Importer:2021-08-13
Keywords: CRISPR/Cas9; gRNA-only; GvHD; IRF4; metabolism; naive T-cell gene editing; NFAT; T-cell transfer

Rapidly fatal SMARCA4-deficient undifferentiated sarcoma originating from hybrid hemosiderotic fibrolipomatous tumor/pleomorphic hyalinizing angiectatic tumor of the foot - Agaimy, Abbas; Meidenbauer, Norbert; Sukov, William R.; Stöhr, Robert; Vieth, Michael; Roemer, Frank; Grützmann, Robert; Folpe, Andrew L. (Virchows Archiv, 2021)
Pleomorphic hyalinizing angiectatic tumor (PHAT) of soft parts and hemosiderotic fibrolipomatous tumor (HFLT) are two rare low-grade locally recurring neoplasms with predilection for the foot/ankle. Recent studies support a close link between the two entities, and origin of PHAT from HFLT and occurrence of hybrid HFLT/PHAT have been documented. Both lesions often harbor TGFBR3 or MGEA5 rearrangements. Rare sarcomas originating from HFLT/PHAT have been reported, typically resembling myxofibrosarcoma or myxoinflammatory fibroblastic sarcoma. We describe a novel SMARCA4-deficient undifferentiated sarcoma with rhabdoid features originating from hybrid HFLT/PHAT in the foot of a 54-year-old male. The tumor pursued a highly aggressive course with rapid regrowth after resection and multiple metastases resulting in patient's death within 5 months, despite systemic chemotherapy. Immunohistochemistry revealed SMARCA4 loss in the undifferentiated sarcoma, but not in the HFLT/PHAT. Molecular testing confirmed TGFBR3/MGEA5 rearrangements. This report expands the phenotypes of sarcomas developing from pre-existing PHAT/HFLT.
CRIS-Team WoS Importer:2021-08-27

Rapid single-cell identification of Epstein–Barr virus-specific T-cell receptors for cellular therapy - Lammoglia Cobo, María Fernanda; Welters, Carlotta; Rosenberger, Leonie; Leisegang, Matthias; Dietze, Kerstin; Pircher, Christian; Penter, Livius; Gary, Regina; Bullinger, Lars; Takvorian, Anna; Moosmann, Andreas; Dornmair, Klaus; et al. (Cytotherapy, 2022)
Background and aims: Epstein–Barr virus (EBV) is associated with solid and hematopoietic malignancies. After allogeneic stem cell transplantation, EBV infection or reactivation represents a potentially life-threatening condition with no specific treatment available in clinical routine. In vitro expansion of naturally occurring EBV-specific T cells for adoptive transfer is time-consuming and influenced by the donor's T-cell receptor (TCR) repertoire and requires a specific memory compartment that is non-existent in seronegative individuals. The authors present highly efficient identification of EBV-specific TCRs that can be expressed on human T cells and recognize EBV-infected cells. Methods and Results: Mononuclear cells from six stem cell grafts were expanded in vitro with three HLA-B*35:01- or four HLA-A*02:01-presented peptides derived from six EBV proteins expressed during latent and lytic infection. Epitope-specific T cells expanded on average 42-fold and were single-cell-sorted and TCRαβ-sequenced. To confirm specificity, 11 HLA-B*35:01- and six HLA-A*02:01-restricted dominant TCRs were expressed on reporter cell lines, and 16 of 17 TCRs recognized their presumed target peptides. To confirm recognition of virus-infected cells and assess their value for adoptive therapy, three selected HLA-B*35:01- and four HLA-A*02:01-restricted TCRs were expressed on human peripheral blood lymphocytes. All TCR-transduced cells recognized EBV-infected lymphoblastoid cell lines. Conclusions: The authors’ approach provides sets of EBV epitope-specific TCRs in two different HLA contexts. Resulting cellular products do not require EBV-seropositive donors, can be adjusted to cell subsets of choice with exactly defined proportions of target-specific T cells, can be tracked in vivo and will help to overcome unmet clinical needs in the treatment and prophylaxis of EBV reactivation and associated malignancies.
CRIS-Team Scopus Importer:2022-05-20
Keywords: adoptive T-cell therapy; allogeneic stem cell transplantation; Epstein–Barr virus; single-cell technologies; virus-associated malignancies

Rationale and design of the 2 by 2 factorial design GnG-trial: a randomized phase-III study to compare two schedules of gemtuzumab ozogamicin as adjunct to intensive induction therapy and to compare double-blinded intensive postremission therapy with or without glasdegib in older patients with newly diagnosed AML - Jaramillo, Sonia; Krisam, Johannes; Le Cornet, Lucian; Kratzmann, Markus; Baumann, Lukas; Sauer, Tim; Crysandt, Martina; Rank, Andreas; Behringer, Dirk; Teichmann, Lino; Görner, Martin; Trappe, Ralf Ulrich; et al. (Trials, 2021)
Background: Overall survival remains poor in older patients with acute myeloid leukemia (AML) with less than 10% being alive after 5 years. In recent studies, a significant improvement in event-free, relapse-free and overall survival was shown by adding gemtuzumab ozogamicin (GO), a humanized antibody-drug conjugate directed against CD33, to intensive induction therapy once or in a sequential dosing schedule. Glasdegib, the small-molecule inhibitor of smoothened (SMO), also showed improved overall survival in patients not eligible for intensive chemotherapy when combined with low-dose cytarabine compared to low-dose cytarabine alone. These findings warrant further investigations in the phase III GnG trial. Methods/Design: This is a randomized phase III trial with measurable residual disease (MRD) after induction therapy and event-free survival (EFS) as primary endpoints. The two research questions are addressed in a 2 by 2 factorial design. Patients age 60 years and older are upfront randomized 1:1 in one of the two induction arms: GO administered to intensive induction therapy on days 1,4, and 7 versus GO administered once on day 1 (GO-147 versus GO-1), and double-blinded 1:1 in one of the subsequent treatment arms glasdegib vs. placebo as adjunct to consolidation therapy and as single-agent maintenance therapy for six months. Chemotherapy backbone for induction therapy consists of standard 7 + 3 schedule with cytarabine 200 mg/m2 continuously days 1 to 7, daunorubicin 60 mg/m2 days 1, 2, and 3 and high-dose cytarabine (1 g/m2, bi-daily, days 1, 2, and 3) for consolidation therapy. Addressing two primary endpoints, MRD-negativity after induction therapy and event-free survival (EFS), 252 evaluable patients are needed to reject each of the two null hypotheses at a two-sided significance level of 2.5% with a power of at least 85%. Ethics and dissemination: Ethical approval and approvals from the local and federal competent authorities were granted. Trial results will be reported via peer-reviewed journals and presented at conferences and scientific meetings. Trial status: Protocol version: 1st version 20.10.2020, no amendments yet. Study initiation on February 16, 2021. First patient was recruited on April 1st. Trial registration: ClinicalTrials.govNCT04093505; EudraCT 2019-003913-32. Registered on October 30, 2018.
CRIS-Team Scopus Importer:2021-11-19
Keywords: acute myeloid leukemia; gemtuzumab ozogamicin; glasdegib; measurable residual disease

Real-world experience of CPX-351 as first-line treatment for patients with acute myeloid leukemia - Rautenberg, Christina; Stoelzel, Friedrich; Roellig, Christoph; Stelljes, Matthias; Gaidzik, Verena; Lauseker, Michael; Kriege, Oliver; Verbeek, Mareike; Unglaub, Julia Marie; Thol, Felicitas; Krause, Stefan; Haenel, Mathias; et al. (Blood Cancer Journal, 2021)
To investigate the efficacy and toxicities of CPX-351 outside a clinical trial, we analyzed 188 patients (median age 65 years, range 26-80) treated for therapy-related acute myeloid leukemia (t-AML, 29%) or AML with myelodysplasia-related changes (AML-MRC, 70%). Eighty-six percent received one, 14% two induction cycles, and 10% received consolidation (representing 22% of patients with CR/CRi) with CPX-351. Following induction, CR/CRi rate was 47% including 64% of patients with available information achieving measurable residual disease (MRD) negativity (<10(-3)) as measured by flow cytometry. After a median follow-up of 9.3 months, median overall survival (OS) was 21 months and 1-year OS rate 64%. In multivariate analysis, complex karyotype predicted lower response (p = 0.0001), while pretreatment with hypomethylating agents (p = 0.02) and adverse European LeukemiaNet 2017 genetic risk (p < 0.0001) were associated with lower OS. Allogeneic hematopoietic cell transplantation (allo-HCT) was performed in 116 patients (62%) resulting in promising outcome (median survival not reached, 1-year OS 73%), especially in MRD-negative patients (p = 0.048). With 69% of patients developing grade III/IV non-hematologic toxicity following induction and a day 30-mortality of 8% the safety profile was consistent with previous findings. These real-world data confirm CPX-351 as efficient treatment for these high-risk AML patients facilitating allo-HCT in many patients with promising outcome after transplantation.
CRIS-Team WoS Importer:2021-10-15

Real-World Experience of CPX-351 As First-Line Treatment in 188 Patients with Acute Myeloid Leukemia - Rautenberg, Christina; Stoelzel, Friedrich; Roellig, Christoph; Stelljes, Matthias; Gaidzik, Verena; Lauseker, Michael; Kriege, Oliver; Verbee, Mareike; Unglaub, Julia Marie; Thol, Felicitas; Krause, Stefan; Haenel, Mathias; et al. (BLOOD, 2021)
CRIS-Team WoS Importer:2022-09-09

Recent development of hypertension and acute renal failure in a 59-year-old woman - Uebner, M.; Jacobi, Johannes; Schmidt, D.; Büttner-Herold, M.; Mackensen, Andreas; Spriewald, B. M. (Internist, 2017)
We report on a 59-year-old woman who presented with nausea, fatigue, arterial hypertension, and acute renal failure. Clinical examination, laboratory findings of blood and urine and abdominal sonography were inconclusive. Renal biopsy revealed infiltration by a diffuse large B-cell lymphoma. In fluorodeoxyglucose positron emission tomography/computed tomography tracer enrichment was demonstrated in both kidneys, skeletal system and retroperitoneal lymph nodes. Renal function improved already after the first cycle of R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone). After chemotherapy, a complete remission, normalization of blood pressure and renal function were achieved.
EVALuna2:25508

Reconstitution of EBV-directed T cell immunity by adoptive transfer of peptide-stimulated T cells in a patient after allogeneic stem cell transplantation for AITL - Cobo, María Fernanda Lammoglia; Ritter, Julia; Gary, Regina; Seitz, Volkhard; Mautner, Josef; Aigner, Michael; Völkl, Simon; Schaffer, Stefanie; Moi, Stephanie; Seegebarth, Anke; Bruns, Heiko; Rösler, Wolf; et al. (PLoS Pathogens, 2022)
Reconstitution of the T cell repertoire after allogeneic stem cell transplantation is a long and often incomplete process. As a result, reactivation of Epstein-Barr virus (EBV) is a frequent complication that may be treated by adoptive transfer of donor-derived EBV-specific T cells. We generated donor-derived EBV-specific T cells by stimulation with peptides representing defined epitopes covering multiple HLA restrictions. T cells were adoptively transferred to a patient who had developed persisting high titers of EBV after allogeneic stem cell transplantation for angioimmunoblastic T-cell lymphoma (AITL). T cell receptor beta (TCRβ) deep sequencing showed that the T cell repertoire of the patient early after transplantation (day 60) was strongly reduced and only very low numbers of EBV-specific T cells were detectable. Manufacturing and in vitro expansion of donor-derived EBV-specific T cells resulted in enrichment of EBV epitope-specific, HLA-restricted T cells. Monitoring of T cell clonotypes at a molecular level after adoptive transfer revealed that the dominant TCR sequences from peptide-stimulated T cells persisted long-term and established an EBV-specific TCR clonotype repertoire in the host, with many of the EBV-specific TCRs present in the donor. This reconstituted repertoire was associated with immunological control of EBV and with lack of further AITL relapse.
CRIS-Team Scopus Importer:2022-05-20

Recording of the regional Origin Areas of Patients from the Molecular Tumor Board to Identify the "white Spots" in the Service Area - A joint Initiative of the Bavarian CCC WERA Alliance - Lueke, F.; Haller, F.; Utpatel, K.; Krebs, M.; Meidenbauer, Norbert; Scheiter, A.; Spörl, Silvia; Heudobler, D.; Keil, F.; Schubart, Christoph; Tögel, Lars; Einhell, S.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Reduced cytotoxicity by mutation of lysine 590 of Pseudomonas exotoxin can be restored in an optimized, lysine-free immunotoxin. - Ammon, Anna-Maria; Mellenthin, Lisa; Emmerich, C.; Naschberger, Elisabeth; Stürzl, Michael; Mackensen, Andreas; Müller, Fabian (Immunotherapy Advances, 2022)
Immunotoxins, which are fusion proteins of an antibody fragment and a fragment of a bacterial or a plant toxin, induce apoptosis in target cells by inhibition of protein synthesis. ADP-ribosylating toxins often have few lysine residues in their catalytic domain. As they are the target for ubiquitination, the low number of lysines possibly prevents ubiquitin-dependent degradation of the toxin in the cytosol. To reduce this potential degradation, we aimed to generate a lysine-free (noK), Pseudomonas exotoxin (PE)-based immunotoxin. The new generation 24 kDa PE, which lacks all but the furin-cleavage site of domain II, was mutated at lysine 590 (K590) and at K606 in a CD22-targeting immunotoxin and activity was determined against various B cell malignancies in vitro and in vivo. On average, K590 mutated to arginine (R) reduced cytotoxicity by 1.3-fold and K606R enhanced cytotoxicity by 1.3-fold compared to wild type (wt). Mutating K590 to histidine or deleting K590 did not prevent this loss in cytotoxicity. Neither stability nor internalization rate of K590R could explain reduced cytotoxicity. These results highlight the relevance of lysine 590 for PE intoxication. In line with in vitro results, the K606R mutant was more than 1.8-fold more active than the other variants in vivo suggesting that this single mutation may be beneficial when targeting CD22-positive malignancies. Finally, reduced cytotoxicity by K590R was compensated for by K606R and the resulting lysine-free variant achieved wt-like activity in vitro and in vivo. Thus, PE24-noK may represent a promising candidate for down-stream applications that would interfere with lysines.
EVALuna2:505954

Reg3α concentrations at day of allogeneic stem cell transplantation predict outcome and correlate with early antibiotic use - Weber, Daniela; Weber, Markus; Meedt, Elisabeth; Ghimire, Sakhila; Wolff, Daniel; Edinger, Matthias; Poeck, Hendrik; Hiergeist, Andreas; Gessner, André; Ayuk, Francis; Rösler, Wolf; Wölfl, Matthias; et al. (Blood Advances, 2023)
Intestinal microbiome diversity plays an important role in the pathophysiology of acute gastrointestinal (GI) graft-versus-host disease (GVHD) and influences the outcome of patients after allogeneic stem cell transplantation (ASCT). We analyzed clinical data and blood samples taken preconditioning and on the day of ASCT from 587 patients from 7 German centers of the Mount Sinai Acute GVHD International Consortium, dividing them into single-center test (n = 371) and multicenter validation (n = 216) cohorts. Regenerating islet–derived 3α (Reg3α) serum concentration of day 0 correlated with clinical data as well as urinary 3-indoxylsulfate (3-IS) and Clostridiales group XIVa, indicators of intestinal microbiome diversity. High Reg3α concentration at day 0 of ASCT was associated with higher 1-year transplant-related mortality (TRM) in both cohorts (P < .001). Cox regression analysis revealed high Reg3α at day 0 as an independent prognostic factor for 1-year TRM. Multivariable analysis showed an independent correlation of high Reg3α concentrations at day 0 with early systemic antibiotic (AB) treatment. Urinary 3-IS (P = .04) and Clostridiales group XIVa (P = .004) were lower in patients with high vs those with low day 0 Reg3α concentrations. In contrast, Reg3α concentrations before conditioning therapy correlated neither with TRM nor disease or treatment-related parameters. Reg3α, a known biomarker of acute GI GVHD correlates with intestinal dysbiosis, induced by early AB treatment in the period of pretransplant conditioning. Serum concentrations of Reg3α measured on the day of graft infusion are predictive of the risk for TRM of ASCT recipients.
CRIS-Team Scopus Importer:2023-05-26

Registry Data Indicate a Meaningful Chance for Successful Pregnancies after Allogeneic Stem Cell Transplantation: Results from the German Stem Cell Transplant Registry (DRST) - Sockel, Katja; Frank, Sandra; Neu, Annika; Ditschkowski, Markus; Hilgendorf, Inken; Goeckenjan, Mareen; Stoelzel, Friedrich; Middeke, Jan Moritz; Kroeger, Nicolaus; Ayuk, Francis A.; Eder, Matthias; Bethge, Wolfgang; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-17

Regulation of Energy Metabolism during Early B Lymphocyte Development - Urbanczyk, Sophia; Stein, Merle; Schuh, Wolfgang; Jäck, Hans-Martin; Mougiakakos, Dimitrios; Mielenz, Dirk (International Journal of Molecular Sciences, 2018)
The most important feature of humoral immunity is the adaptation of the diversity of newly generated B cell receptors, that is, the antigen receptor repertoire, to the body's own and foreign structures. This includes the transient propagation of B progenitor cells and B cells, which possess receptors that are positively selected via anabolic signalling pathways under highly competitive conditions. The metabolic regulation of early B-cell development thus has important consequences for the expansion of normal or malignant pre-B cell clones. In addition, cellular senescence programs based on the expression of B cell identity factors, such as Pax5, act to prevent excessive proliferation and cellular deviation. Here, we review the basic mechanisms underlying the regulation of glycolysis and oxidative phosphorylation during early B cell development in bone marrow. We focus on the regulation of glycolysis and mitochondrial oxidative phosphorylation at the transition from non-transformed pro- to pre-B cells and discuss some ongoing issues. We introduce Swiprosin-2/EFhd1 as a potential regulator of glycolysis in pro-B cells that has also been linked to Ca2+-mediated mitoflashes. Mitoflashes are bioenergetic mitochondrial events that control mitochondrial metabolism and signalling in both healthy and disease states. We discuss how Ca2+ fluctuations in pro- and pre-B cells may translate into mitoflashes in early B cells and speculate about the consequences of these changes.
EVALuna2:35105

Regulation of immunological checkpoints in human mesenchymal stromal cells - Strauch, Vivien; Saul, D.; Mackensen, Andreas; Jitschin, R.; Mougiakakos, Dimitrios (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Regulation of the Immune Balance During Allogeneic Hematopoietic Stem Cell Transplantation by Vitamin D - Flamann, Cindy; Peter, Katrin; Kreutz, Marina; Bruns, Heiko (Frontiers in Immunology, 2019)
One of the most promising therapeutic approaches for numerous hematological malignancies represents the allogeneic hematopoietic stem cell transplantation (allo-HSCT). One major complication is the development of the life-threatening graft-vs.-host disease (GvHD) which limits beneficial effects of graft-vs.-leukemia (GvL) responses during allo-HSCT. Strengthening GvL effects without induction of severe GvHD is essential to decrease the relapse rate after allo-HSCT. An interesting player in this context is vitamin D3 since it has modulatory capacity in both preventing GvHD and boosting GvL responses. Current studies claim that vitamin D3 induces an immunosuppressive environment by dendritic cell (DC)-dependent generation of regulatory T cells (Tregs). Since vitamin D3 is known to support the antimicrobial defense by re-establishing the physical barrier as well as releasing defensins and antimicrobial peptides, it might also improve graft-vs.-infection (GvI) effects in patients. Beyond that, alloreactive T cells might be attenuated by vitamin D3-mediated inhibition of proliferation and activation. Despite the inhibitory effects of vitamin D3 on T cells, anti-tumor responses of GvL might be reinforced by vitamin D3-triggered phagocytic activity and antibody-based immunotherapy. Therefore, vitamin D3 treatment does not only lead to a shift from a pro-inflammatory toward a tolerogenic state but also promotes tumoricidal activity of immune cells. In this review we focus on vitamin D3 and its immunomodulatory effects by enhancing anti-tumor activity while alleviating harmful allogeneic responses in order to restore the immune balance.
CRIS-Team Scopus Importer:2019-12-03
Keywords: GvH; GvL; immune balance; infection; macrophages; T cells; vitamin D

Relevance of different prognostic scores in primary CNS lymphoma in the era of intensified treatment regimens: A retrospective, multicenter analysis of 174 patients - Zeremski, Vanja; Adolph, Louisa; Beer, Sina; Berisha, Mirjeta; Jacobs, Benedikt; Kahl, Christoph; Koenecke, Christian; Kropf, Siegfried; Panse, Jens; Petersen, Judith; Schmidt-Hieber, Martin; Schneider, Jessica; et al. (European Journal of Haematology, 2024)
Objectives: Treatment intensification (including consolidative high-dose chemotherapy with autologous stem cell transplantation [HDT-ASCT]) significantly improved outcome in primary central nervous system lymphoma (PCNSL) patients. Methods: We conducted a multicenter, retrospective analysis of newly diagnosed PCNSL patients, treated with intensified treatment regimens. The following scores were evaluated in terms of overall survival (OS) and progression-free survival (PFS): Memorial Sloan-Kettering Cancer Center (MSKCC), International Extranodal Lymphoma Study Group (IELSG), and three-factor (3F) prognostic score. Further, all scores were comparatively investigated for model quality and concordance. Results: Altogether, 174 PCNSL patients were included. One hundred and five patients (60.3%) underwent HDT-ASCT. Two-year OS and 2-year PFS for the entire population were 73.3% and 48.5%, respectively. The MSKCC (p =.003) and 3F score (p <.001), but not the IELSG score (p =.06), had the discriminatory power to identify different risk groups for OS. In regard to concordance, the 3F score (C-index [0.71]) outperformed both the MSKCC (C-index [0.64]) and IELSG (C-index [0.53]) score. Moreover, the superiority of the 3F score was shown for PFS, successfully stratifying patients in three risk groups, which also resulted in the highest C-index (0.66). Conclusion: The comparative analysis of established PCNSL risk scores affirm the clinical utility of the 3F score stratifying the widest prognostic spectrum among PCNSL patients treated with intensified treatment approaches.
CRIS-Team Scopus Importer:2024-01-12
Keywords: HDT-ASCT; primary CNS lymphoma; prognostic scores; survival; toxicity

Reproducibility of measurable residual disease detection by flow cytometry in acute myeloid leukemia - Roehnert, M. A.; Kramer, M.; Schadt, J.; Ensel, P.; Thiede, C.; Krause, Stefan; Buecklein, V.; Hoffmann, J.; Jaramillo, S.; Schlenk, R.; Roellig, C.; Bornhaeuser, M.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Reproducible measurable residual disease detection by multiparametric flow cytometry in acute myeloid leukemia - Roehnert, Maximilian A.; Kramer, Michael; Schadt, Jonas; Ensel, Philipp; Thiede, Christian; Krause, Stefan; Buecklein, Veit; Hoffmann, Joerg; Jaramillo, Sonia; Schlenk, Richard F.; Roellig, Christoph; Bornhaeuser, Martin; et al. (Leukemia, 2022)
Measurable residual disease (MRD) detected by multiparametric flow cytometry (MFC) is associated with unfavorable outcome in patients with AML. A simple, broadly applicable eight-color panel was implemented and analyzed utilizing a hierarchical gating strategy with fixed gates to develop a clear-cut LAIP-based DfN approach. In total, 32 subpopulations with aberrant phenotypes with/without expression of markers of immaturity were monitored in 246 AML patients after completion of induction chemotherapy. Reference values were established utilizing 90 leukemia-free controls. Overall, 73% of patients achieved a response by cytomorphology. In responders, the overall survival was shorter for MRDpos patients (HR 3.8, p = 0.006). Overall survival of MRDneg non-responders was comparable to MRDneg responders. The inter-rater-reliability for MRD detection was high with a Krippendorffs alpha of 0.860. The mean time requirement for MRD analyses at follow-up was very short with 04:31 minutes. The proposed one-tube MFC approach for detection of MRD allows a high level of standardization leading to a promising inter-observer-reliability with a fast turnover. MRD defined by this strategy provides relevant prognostic information and establishes aberrancies outside of cell populations with markers of immaturity as an independent risk feature. Our results imply that this strategy may provide the base for multicentric immunophenotypic MRD assessment.
CRIS-Team WoS Importer:2022-07-29

Rescue therapy of antisynthetase syndrome with CD19-targeted CAR-T cells after failure of several B-cell depleting antibodies - Taubmann, Jule; Knitza, Johannes; Müller, Fabian; Völkl, Simon; Aigner, Michael; Kleyer, Arnd; Gary, Regina; Kretschmann, Sascha; Böltz, Sebastian; Atzinger, Armin; Kuwert, Torsten; Roemer, Frank; et al. (Rheumatology, 2024)
EVALuna2:539551

Resection of dominant fusiform gyrus is associated with decline of naming function when temporal lobe epilepsy manifests after the age of five: A voxel-based lesion-symptom mapping study - Reindl, Caroline; Allgäuer, Andrea; Kleiser, Benedict; Onugoren, Müjgan Dogan; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Winder, Klemens; Schwarz, Michael; Gollwitzer, Stephanie; Trollmann, Regina; Rösch, Julie; et al. (NeuroImage: Clinical, 2022)
Objective: To determine patients’ characteristics and regions in the temporal lobe where resections lead to a decline in picture naming. Methods: 311 patients with left hemispheric dominance for language were included who underwent epilepsy surgery at the Epilepsy Center of Erlangen and whose picture naming scores (Boston Naming Test, BNT) were available preoperatively and 6-months postoperatively. Surgical lesions were mapped to an averaged template based on preoperative and postoperative MRI using voxel-based lesion-symptom mapping (VBLSM). Postoperative brain shifts were corrected. The relationship between lesioned brain areas and the presence of a postoperative naming decline was examined voxel-wise while controlling for effects of overall lesion size at first in the total cohort and then restricted to temporal lobe resections. Results: In VBLSM in the total sample, a decline in BNT score was significantly related to left temporal surgery. When only considering patients with left temporal lobe resections (n = 121), 40 (33.1%) significantly worsened in BNT postoperatively. VBLSM including all patients with left temporal resections generated no significant results within the temporal lobe. However, naming decline of patients with epilepsy onset after 5 years of age was significantly associated with resections in the left inferior temporal (extent of BNT decline range: 10.8− 14.4%) and fusiform gyrus (decline range: 12.1−18.4%). Significance: Resections in the posterior part of the dominant fusiform and inferior temporal gyrus was associated with a risk of deterioration in naming performance at six months after surgery in patients with epilepsy onset after 5 years of age but not with earlier epilepsy onset.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Basal temporal language area; Epilepsy surgery; Gyrus fusiformis; Lesion localization; Naming; Neuropsychological outcome

Reset of inflammatory priming of joint tissue and reduction of the severity of arthritis flares by bromodomain inhibition - Friščić, Jasna; Reinwald, Christiane; Böttcher, Martin; Houtman, Miranda; Euler, Maximilien; Chen, Xi; Walker, Kellie I.; Kirchner, Philipp; Zhu, Honglin; Wirth, Benjamin; Weidner, Daniela; Krüger, René; et al. (Arthritis and Rheumatology, 2023)
Objective: We have recently shown that priming of synovial fibroblasts (SFs) drives arthritis flares. Pathogenic priming of SFs is essentially mediated by epigenetic reprogramming. Bromodomain and extra-terminal motif (BET) proteins translate epigenetic changes into transcription. Here we used a BET inhibitor to target inflammatory tissue priming and reduce flare severity in experimental arthritis. Methods: BALB/c mice were treated intraperitoneally or locally into the paw with I-BET151, which blocks interaction of BET proteins with acetylated histones. Effect of I-BET151 on acute arthritis and/or inflammatory tissue priming was assessed in a model of repeated injections of monosodium urate crystals or zymosan into the paw. I-BET151 was given either from before arthritis induction, at peak inflammation, or after healing of the first arthritis bout. Transcriptomic (RNA-Seq), epigenomic (ATAC-Seq) and functional analysis (invasion, cytokine production, migration, senescence, metabolic flux) was performed on murine and human SFs treated with I-BET151 in vitro or in vivo. Results: Systemic I-BET151 administration did not affect acute inflammation but abolished inflammatory tissue priming and diminished flare severity in both preventive and therapeutic treatment settings. I-BET151 was also effective when applied locally in the joint. BET inhibition also inhibited osteoclast differentiation, while macrophage activation in the joint was not affected. Flare reduction after BET inhibition was mediated, at least in part, by rolling back the primed transcriptional, metabolic and pathogenic phenotype of SFs. Conclusion: Inflammatory tissue priming is dependent on transcriptional regulation by BET proteins, which makes them promising therapeutic targets for preventing arthritis flares in previously affected joints.
CRIS-Team Scopus Importer:2023-01-27

Resolution of ulcerative colitis - Neurath, Markus; Leppkes, Moritz (Seminars in Immunopathology, 2019)
Ulcerative colitis designates an idiopathic chronic inflammatory bowel disease leading to bloody diarrhea and inflammatory alterations mostly restricted to the large intestine. Many studies continue to unravel important aspects of its etiopathogenesis, and recent pharmaceutical developments broaden the arsenal of therapeutic opportunity. In this review, we delve into the cellular and molecular determinants of successful resolution of ulcerative colitis, describing novel insights in each of the phases of mucosal healing starting from damaging insults to the mucosa, epithelial restitution, and its adaption to inflammation as well as lymphocyte-driven maintenance and resolution of chronic inflammation. Additionally, molecular switches from inflammation to resolution are explored, paving the way for future avenues to resolve ulcerative colitis.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Epithelium; Intestine; Lymphocytes; Resolution of inflammation; Ulcerative colitis

Response-adapted consolidation with bortezomib after ASCT improves progression-free survival in newly diagnosed multiple myeloma - Einsele, H.; Knop, S.; Vogel, M.; Mueller, J.; Kropff, M.; Metzner, B.; Langer, C.; Sayer, H.; Jung, W.; Duerk, H. A.; Salwender, H.; Wandt, Hannes; et al. (Leukemia, 2017)
Leukemia accepted article preview online, 15 March 2017. doi:10.1038/leu.2017.83.
EVALuna2:25758

RESULTS OF THE IELSG32 TRIAL AT A MEDIAN FOLLOW-UP OF 88 MONTHS DEMONSTRATE THAT MATRIX FOLLOWED BY AUTOLOGOUS TRANSPLANT IS ASSOCIATED WITH EXCELLENT SURVIVAL AND NEUROTOLERABILITY IN PATIENTS WITH PRIMARY CNS LYMPHOMA - Calimeri, T.; Cwynarski, K.; Pulczynski, E.; Fox, C. P.; Schorb, E.; Steffanoni, S.; Foppoli, M.; Celico, C.; Falautano, M.; Nonis, A.; La Rosee, P.; Binder, M.; et al. (HAEMATOLOGICA, 2021)
CRIS-Team WoS Importer:2021-12-03

Reticulated platelets - Clinical application and future perspectives - Meintker, Lisa; Krause, Stefan (Journal of Laboratory Medicine, 2020)
Reticulated platelets are immature platelets freshly released from the bone marrow into the circulation and contain vestigial amounts of ribonucleic acid. Thus, they can serve as an indicator for the activity of thrombopoiesis. Despite the current lack of a standardized reference method, two types of hematology analyzers have incorporated a fully automated measurement of reticulated platelets. The "immature platelet fraction" (IPF; Sysmex XE-/XN-series) has some clinical utility in the differential diagnosis of thrombocytopenia. This is less clear for "reticulated platelets" (retPLT; Abbott CELL-DYN Sapphire/Alinity HQ). The usefulness of these parameters in the prediction of platelet recovery after chemotherapy or stem cell transplantation and as a decision aid for platelet transfusions has not been unequivocally confirmed. Recent findings have shown an association of reticulated platelets with an adverse risk in patients with coronary artery disease and stroke as well as resistance to anti-platelet therapy. Furthermore, a role of reticulated platelets for the prediction of sepsis was indicated. However, validation in larger prospective trials is necessary to establish the clinical benefit of reticulated platelets in these conditions. This review gives an overview of the available analytical methods and summarizes the current knowledge regarding the clinical application of reticulated platelets.
CRIS-Team Scopus Importer:2020-02-28
Keywords: immature platelets; IPF; reticulated platelets

Retrograde inspection vs standard forward view for the detection of colorectal adenomas during colonoscopy: A back-to-back randomized clinical trial - Rath, Timo; Pfeifer, Lukas; Neufert, Clemens; Kremer, Andreas; Leppkes, Moritz; Hoffman, Arthur; Neurath, Markus; Zopf, Steffen (World Journal of Gastroenterology, 2020)
BACKGROUND: The adenoma detection rate (ADR) is inversely associated with the incidence of interval colorectal cancer and serves as a benchmark quality criterion during screening colonoscopy. However, adenoma miss rates reach up to 26% and studies have shown that a second inspection of the right colon in retroflected view (RFV) can increase ADR. AIM: To assess whether inspection of the whole colon in RFV compared to standard forward view (SFV) can increase ADR. METHODS: Patients presenting for screening or surveillance colonoscopy were invited to participate in this randomized controlled trial and randomized into two arms. In RFV arm colonoscopy was initially performed with SFV, followed by a second inspection of the whole colon in RFV. In the SFV arm first withdrawal was performed with SFV, followed by a second inspection of the whole colon again with SFV. Number, size and morphology of polyps found during first and second inspection in each colonic segment were recorded and all polyps were removed and sent for histopathology in separate containers. RESULTS: Two hundred and five patients were randomly assigned to the RFV (n = 101) and SFV (n = 104) arm. In the RFV arm, both polyp detection rate (PDR) and ADR were increased under second inspection in RFV (PDR 1st SFV: 39.8%, PDR 2nd RFV: 46.6%; ADR 1st SFV: 35.2%, ADR 2nd RFV: 42%). Likewise, in the SFV arm, PDR and ADR were increased under second inspection (PDR 1st SFV: 37.5%, PDR 2nd SFV: 46.6%; ADR 1st SFV: 34.1%, ADR 2nd SFV: 44.3%) with no significant differences in ADR and PDR between the SFV and RFV arm. Mean number of adenomas per patient (APP) was increased in the RFV and SFV (APP RFV arm: 1st SFV: 1.71; 2nd RFV: 2.38; APP SFV arm: 1st SFV: 1.83, 2nd SFV:2.2). The majority of adenomas additionally found during second inspection in RFV or in SFV were located in the transverse and left-sided colon and were > 5 mm in size. CONCLUSION: Second inspection of the whole colon leads to increased adenoma detection with no differences between SFV and RFV. Hence, increased detection is most likely a feature of the second inspection itself but not of the inspection mode.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Adenoma; Adenoma detection rate; Colonoscopy; Colorectal cancer

Risk factors and mortality in invasive Rasamsonia spp. infection: Analysis of cases in the FungiScope registry and from the literature - Stemler, Jannik; Salmanton-Garcia, Jon; Seidel, Danila; Alexander, Barbara D.; Bertz, Hartmut; Hoenigl, Martin; Herbrecht, Raoul; Meintker, Lisa; Meissner, Arne; Mellinghoff, Sibylle C.; Sal, Ertan; Zarrouk, Marouan; et al. (Mycoses, 2019)
BACKGROUND: The new Rasamsonia spp. complex can develop invasive infection in immunosuppression or chronic pulmonary disease. It has potential to be misidentified as other genera due to morphological similarities. Nowadays, there is a gap of knowledge on this fungi. OBJECTIVES: To provide knowledge base of risk factors and therapeutic decisions in invasive Rasamsonia spp. complex infection. PATIENTS/METHODS: Cases of invasive infection due to Rasamsonia spp. (formerly Geosmithia/Penicillium spp.) from FungiScope® registry and all reported cases from a literature were included. RESULTS: We identified 23 invasive infections due to Rasamsonia spp., six (26.1%) in the FungiScope® registry. Main risk factors were chronic granulomatous disease (n = 12, 52.2%), immunosuppressive treatment (n = 10, 43.5%), haematopoietic stem cell transplantation (n = 7, 30.4%), graft-versus-host disease and major surgery (n = 4, 17.4%, each). Predominantly affected organs were the lungs (n = 21, 91.3%), disease disseminated in seven cases (30.4%). Fungal misidentification occurred in 47.8% (n = 11), and sequencing was used in 69.6% of the patients (n = 16) to diagnose. Breakthrough infection occurred in 13 patients (56.5%). All patients received antifungal treatment, mostly posaconazole (n = 11), caspofungin (n = 10) or voriconazole (n = 9). Combination therapy was administered in 13 patients (56.5%). Susceptibility testing showed high minimum inhibitory concentrations for azoles and amphotericin B, but not for echinocandins. No preferable treatment influencing favourable outcome was identified. Overall mortality was 39% (n = 9). CONCLUSION: Rasamsonia spp. are emerging fungi causing life-threatening infections, especially in immunocompromised and critically ill patients. Mortality is high. Treatment is challenging and clinicians dealing with this patient population should become aware of this infection constituting a medical emergency.
EVALuna2:216176

Rituximab for treatment of T-cell large granular lymphocytic leukaemia associated with rheumatoid arthritis - Meintker, Lisa; Mackensen, Andreas; Meidenbauer, Norbert; Ferstl, B. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Role of CAR T Cell Metabolism for Therapeutic Efficacy - Rial Saborido, Judit; Völkl, Simon; Aigner, Michael; Mackensen, Andreas; Mougiakakos, Dimitrios (Cancers, 2022)
Chimeric antigen receptor (CAR) T cells hold enormous potential. However, a substantial proportion of patients receiving CAR T cells will not reach long-term full remission. One of the causes lies in their premature exhaustion, which also includes a metabolic anergy of adoptively transferred CAR T cells. T cell phenotypes that have been shown to be particularly well suited for CAR T cell therapy display certain metabolic characteristics; whereas T-stem cell memory (TSCM) cells, characterized by self-renewal and persistence, preferentially meet their energetic demands through oxidative phosphorylation (OXPHOS), effector T cells (TEFF) rely on glycolysis to support their cytotoxic function. Various parameters of CAR T cell design and manufacture co-determine the metabolic profile of the final cell product. A co-stimulatory 4-1BB domain promotes OXPHOS and formation of central memory T cells (TCM), while T cells expressing CARs with CD28 domains predominantly utilize aerobic glycolysis and differentiate into effector memory T cells (TEM). Therefore, modification of CAR co-stimulation represents one of the many strategies currently being investigated for improving CAR T cells’ metabolic fitness and survivability within a hostile tumor microenvironment (TME). In this review, we will focus on the role of CAR T cell metabolism in therapeutic efficacy together with potential targets of intervention.
CRIS-Team Scopus Importer:2022-11-25
Keywords: bioenergetics; CAR T cells; immune escape; immunometabolism; metabolism; tumor microenvironment

Role of N6-Methyladenosine (m6A) RNA Modification in Multiple Myeloma - Bach, Christian; Leffler, Magdalena; Flamann, Cindy; Kronke, Jan; Mougiakakos, Dimitrios; Mackensen, Andreas; Bruns, Heiko (BLOOD, 2018)
CRIS-Team WoS Importer:2019-02-27

Round-Robin test for the histological diagnosis of acute colonic Graft-versus-Host disease validating established histological criteria and grading systems - Hippe, Katrin; Kreft, Andreas; Reu-Hofer, Simone; Rosenwald, Andreas; Ferrazzi, Fulvia; Daniel, Christoph; Amann, Kerstin Ute; Kraus, Sabrina; Holler, Ernst; Kandulski, Arne; Hirsch, Daniela; Buttner, Anke; et al. (Virchows Archiv, 2023)
Histomorpholgy is one of the mainstays of acute Graft-versus-host disease (GvHD) diagnosis. However, concerns about reproducibility and the most appropriate grading system question its usefulness. Our aim was to assess histomorphological parameters and previously reported grading systems for GvHD regarding reproducibility and validity. Moreover, we propose that sum scores, derived by combining separately scored morphological parameters into a total score, might provide a simplified but equally effective means to grade GvHD. A total of 123 colon biopsies were assessed across four pathologists for intestinal GvHD using a Round-Robin test and results were correlated with clinical findings. Interobserver reproducibility was high for histological parameters that were evaluated as indicators of acute GvHD. Published grading systems were moderately reproducible (ICC 0.679–0.769) while simplified sum scores, in comparison, showed better interrater reliability (ICC 0.818–0.896). All grading systems and sum scores were associated with clinical signs of GvHD and in part with therapy response and survival. However, they were not able to stratify patients according to the clinical severity of GvHD. In a hot-spot analysis 1 crypt apoptotic body (CAB) in 10 crypts was a reasonable cut-off value for minimal diagnostic criteria of GvHD. In conclusion, histology can contribute to the diagnosis of GvHD and is reproducible. Published grading systems are able to reflect clinical findings as are simplified sum scores, which showed improved reproducibility and might be easier to handle as they are based on adding up histological parameters rather than transferring histological findings into a separate grading system. Sum scores will have to be further tested in a prospective setting.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Acute Graft-versus-host disease; Colon biopsy; Grading; Interobserver agreement; Round-Robin test

Safety and efficacy of imatinib in CML over a period of 10 years: data from the randomized CML-study IV - Kalmanti, L.; Saussele, S.; Lauseker, M.; Mueller, M. C.; Dietz, C. T.; Heinrich, L.; Hanfstein, B.; Proetel, U.; Fabarius, A.; Krause, Stefan; Rinaldetti, S.; Dengler, J.; et al. (Leukemia, 2015)
Tyrosine kinase inhibitors (TKI) have changed the natural course of chronic myeloid leukemia (CML). With the advent of second-generation TKI safety and efficacy issues have gained interest. The randomized CML - Study IV was used for a long-term evaluation of imatinib (IM). 1503 patients have received IM, 1379 IM monotherapy. After a median observation of 7.1 years, 965 patients (64%) still received IM. At 10 years, progression-free survival was 82%, overall survival 84%, 59% achieved MR(5), 72% MR(4.5), 81% MR(4), 89% major molecular remission and 92% MR(2) (molecular equivalent to complete cytogenetic remission). All response levels were reached faster with IM800 mg except MR(5). Eight-year probabilities of adverse drug reactions (ADR) were 76%, of grades 3-4 22%, of non-hematologic 73%, and of hematologic 28%. More ADR were observed with IM800 mg and IM400 mg plus interferon ? (IFN). Most patients had their first ADR early with decreasing frequency later on. No new late toxicity was observed. ADR to IM are frequent, but mostly mild and manageable, also with IM 800 mg and IM 400 mg+IFN. The deep molecular response rates indicate that most patients are candidates for IM discontinuation. After 10 years, IM continues to be an excellent initial choice for most patients with CML.
EVALuna2:25726

Saliva samples as a source of DNA for high throughput genotyping: an acceptable and sufficient means in improvement of risk estimation throughout mammographic diagnostics - Poehls, U. G.; Hack, Caroline; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Rübner, Matthias; Hübner, Hanna (European Journal of Medical Research, 2018)
BACKGROUND: Breast cancer screening programs seem to be an insufficient tool for women at high genetic risk for breast cancer. These women are not adequately monitored yet. Genetic testing may improve clearly the quality of breast cancer prevention programs. At present, blood samples are favored for obtaining high-quality DNA; however, DNA can also be obtained by collecting saliva. The aim of this study was, on the one hand, to determine whether saliva sampling is a practicable means to obtain sufficient quantity and quality of DNA and, on the other hand, whether it is accepted by patients throughout mammographic diagnostics. METHODS: 67 consecutive women with diagnostic need for mammography with or without a family history for breast cancer were asked for their basic willingness to undergo a genetic testing by saliva sample in addition to standard diagnostics. Saliva samples were analyzed in terms of DNA quantity and quality. RESULTS: 64 (95.6%) women agreed to provide a saliva sample; 3 of them denied participation. And even 63 out of 64 (98.4%) were interested in their specific results. 45 out of 64 samples contained a DNA concentration above 50 ng/µl, 12 samples were between 25 and 50 ng/µl and only 7 of them were under 25 ng/µl with the standard extraction procedure. CONCLUSION: A high number of patients seem to accept salvia samples as a risk assessment tool in breast diagnostics and are interested in their specific risk situation. At the same time, it could be demonstrated that it is an effective way to provide high-quality DNA for breast cancer gene analysis. However, it remains to be shown whether it would be possible to integrate it with the same acceptance in a nationwide breast cancer screening program.
EVALuna2:34632

SARS-CoV-2 in severe COVID-19 induces a TGF-β-dominated chronic immune response that does not target itself - Ferreira-Gomes, Marta; Kruglov, Andrey; Durek, Pawel; Heinrich, Frederik; Tizian, Caroline; Heinz, Gitta Anne; Pascual-Reguant, Anna; Du, Weijie; Mothes, Ronja; Fan, Chaofan; Frischbutter, Stefan; Habenicht, Katharina Marie; et al. (Nature Communications, 2021)
The pathogenesis of severe COVID-19 reflects an inefficient immune reaction to SARS-CoV-2. Here we analyze, at the single cell level, plasmablasts egressed into the blood to study the dynamics of adaptive immune response in COVID-19 patients requiring intensive care. Before seroconversion in response to SARS-CoV-2 spike protein, peripheral plasmablasts display a type 1 interferon-induced gene expression signature; however, following seroconversion, plasmablasts lose this signature, express instead gene signatures induced by IL-21 and TGF-β, and produce mostly IgG1 and IgA1. In the sustained immune reaction from COVID-19 patients, plasmablasts shift to the expression of IgA2, thereby reflecting an instruction by TGF-β. Despite their continued presence in the blood, plasmablasts are not found in the lungs of deceased COVID-19 patients, nor does patient IgA2 binds to the dominant antigens of SARS-CoV-2. Our results thus suggest that, in severe COVID-19, SARS-CoV-2 triggers a chronic immune reaction that is instructed by TGF-β, and is distracted from itself.
CRIS-Team Scopus Importer:2021-04-09

SARS-CoV-2-seronegative HIV-1-infected subjects target CTL epitopes in the SARS-CoV-2 nucleoprotein cross-reactive to common cold coronaviruses - Schmidt, Katja; Nganou-Makamdop, Krystelle; Tenbusch, Matthias; El Kenz, Boutaina; Maier, Clara; Lapuente, Dennis; Überla, Klaus; Spriewald, Bernd; Bergmann, Silke; Harrer, Ellen; Harrer, Thomas (INFECTION, 2021)
CRIS-Team WoS Importer:2021-04-09

Sars-Cov-2 Vaccine-Induced Cellular and Humoral Immunity in Patients after CD19.CAR-T Cell Therapy - Reimann, Hannah; Kremer, Anita; Blumenberg, Viktoria; Schmidt, Katja; Aigner, Michael; Kremer, Andreas; Tenbusch, Matthias; Bruns, Heiko; Harrer, Thomas; Schett, Georg; Müller, Fabian; Mackensen, Andreas; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-17

Second allogeneic stem cell transplantation in acute lymphoblastic leukemia patients in second complete remission or relapse: A study on behalf of the ALWP / EBMT - Nagler, Arnon; Labopin, Myriam; Finke, Juergen; Brecht, Arne; Schanz, Urs; Niittyvuopio, Riitta; Neubauer, Andreas; Bornhaeuser, Martin; Santarone, Stella; Beelen, Dietrich; Shimoni, Avichai; Rösler, Wolf; et al. (BONE MARROW TRANSPLANTATION, 2019)
CRIS-Team WoS Importer:2019-10-11

Second allogeneic stem cell transplantation in patients with acute lymphoblastic leukaemia: a study on behalf of the Acute Leukaemia Working Party of the European Society for Blood and Marrow Transplantation - Nagler, Arnon; Labopin, Myriam; Dholaria, Bhagirathbhai; Finke, Jürgen; Brecht, Arne; Schanz, Urs; Niittyvuopio, Riitta; Neubauer, Andreas; Bornhäuser, Martin; Santarone, Stella; Beelen, Dietrich; Shimoni, Avichai; et al. (British Journal of Haematology, 2019)
Although second allogeneic haematopoietic cell transplantation (allo-HCT2) is a therapeutic option for patients relapsing after first HCT (allo-HCT1), there is limited data on allo-HCT2 in patients with acute lymphoblastic leukaemia (ALL). We retrospectively studied 245 patients receiving allo-HCT2 as a salvage treatment for relapse following allo-HCT1 between the 2000 and 2017. The median age at allo-HCT2 was 34·6 years (range: 18-74). One hundred and one patients (41%) received sibling donor and 144 (59%) unrelated donor allo-HCT2. Acute graft-versus-host disease (GVHD) grade II-IV and III-IV occurred in 33% and 17% of the patients, respectively. The incidence of 2-year total and extensive chronic GVHD was 38% and 19%, respectively. The 2- and 5-year cumulative incidence of non-relapse mortality, relapse incidence, leukaemia-free survival, overall survival and GVHD-free, relapse-free survival (GRFS) were 24% and 26%, 56% and 62%, 20% and 12%, 30% and 14% and 12% & 7%, respectively. In multivariate analysis, factors associated with overall survival were age, time from allo-HCT1 to relapse, conditioning for allo-HCT1, Karnofsky score at allo-HCT2 and donor type for allo-HCT2. In conclusion, outcomes of allo-HCT2 in ALL patients were poor, with only 14% overall survival and 7% GRFS at 5 years with very high relapse incidence.
EVALuna2:184253

Secondary malignancies in chronic myeloid leukemia patients after imatinib-based treatment: long-term observation in CML Study IV - Miranda, M. B.; Lauseker, M.; Kraus, M-P; Proetel, U.; Hanfstein, B.; Fabarius, A.; Baerlocher, G. M.; Heim, D.; Hossfeld, D. K.; Kolb, H-J; Krause, Stefan; Nerl, C.; et al. (Leukemia, 2016)
Treatment of chronic myeloid leukemia (CML) has been profoundly improved by the introduction of tyrosine kinase inhibitors (TKIs). Long-term survival with imatinib is excellent with a 8-year survival rate of 88%. Long-term toxicity of TKI treatment, especially carcinogenicity, has become a concern. We analyzed data of the CML study IV for the development of secondary malignancies. In total, 67 secondary malignancies were found in 64 of 1525 CML patients in chronic phase treated with TKI (n=61) and interferon-? only (n=3). The most common malignancies (n?4) were prostate, colorectal and lung cancer, non-Hodgkin's lymphoma (NHL), malignant melanoma, non-melanoma skin tumors and breast cancer. The standardized incidence ratio (SIR) for all malignancies excluding non-melanoma skin tumors was 0.88 (95% confidence interval (0.63-1.20)) for men and 1.06 (95% CI 0.69-1.55) for women. SIRs were between 0.49 (95% CI 0.13-1.34) for colorectal cancer in men and 4.29 (95% CI 1.09-11.66) for NHL in women. The SIR for NHL was significantly increased for men and women. An increase in the incidence of secondary malignancies could not be ascertained. The increased SIR for NHL has to be considered and long-term follow-up of CML patients is warranted, as the rate of secondary malignancies may increase over time.
EVALuna2:25736

Sedation assessment in a mobile intensive care unit: a prospective pilot-study on the relation of clinical sedation scales and the bispectral index - Prottengeier, Johannes; Moritz, Andreas; Heinrich, Stefan; Gall, Christine; Schmidt, Joachim (Critical Care, 2014)
The critically-ill undergoing inter-hospital transfers commonly receive sedatives in continuation of their therapeutic regime or to facilitate a safe transfer shielded from external stressors. While sedation assessment is well established in critical care in general, there is only little data available relating to the special conditions during patient transport and their effect on patient sedation levels. The aim of this prospective study was to investigate the feasibility and relationship of clinical sedation assessment (Richmond Agitation-Sedation Scale (RASS)) and objective physiological monitoring (bispectral index (BIS)) during patient transfers in our Mobile-ICU.The levels of sedation of 30 pharmacologically sedated patients were evaluated at 12 to 17 distinct measurement points spread strategically over the course of a transfer by use of the RASS and BIS. To investigate the relation between the RASS and the BIS, Spearman's squared rank correlation coefficient (?(2)) and the Kendall's rank correlation coefficient (?) were calculated. The diagnostic value of the BIS with respect to the RASS was investigated by its sensitivity and positive predictive value for possible patient awakening. Therefore, measurements were dichotomized considering a clinically sensible threshold of 80 for BIS-values and classifying RASS values being nonnegative.Spearman's rank correlation resulted to ?(2) = 0.431 (confidence interval (CI) = 0.341 to 0.513). The Kendall's correlation coefficient was calculated as ? = 0.522 (CI = 0.459 to 0.576). Awakening of patients (RASS >= 0) was detected by a BIS value of 80 and above with a sensitivity of 0.97 (CI = 0.89 to 1.00) and a positive predictive value of 0.59 (CI = 0.45 to 0.71).Our study demonstrates that the BIS-Monitor can be used for the assessment of sedation levels in the intricate environment of a Mobile-ICU, especially when well-established clinical scores as the RASS are impracticable. The use of BIS is highly sensitive in the detection of unwanted awakening of patients during transfers.
EVALuna2:5483

Select hyperactivating NLRP3 ligands enhance the TH1-and TH17-inducing potential of human type 2 conventional dendritic cells - Hatscher, Lukas; Lehmann, Christian; Purbojo, Ariawan; Onderka, Constantin; Liang, Chunguang; Hartmann, Arndt; Cesnjevar, Robert; Bruns, Heiko; Gross, Olaf; Nimmerjahn, Falk; Burmazovic, Ivana Ivanovic; Kunz, Meik; et al. (Science Signaling, 2021)
The detection of microorganisms and danger signals by pattern recognition receptors on dendritic cells (DCs) and the consequent formation of inflammasomes are pivotal for initiating protective immune responses. Although the activation of inflammasomes leading to secretion of the cytokine IL-1 is typically accompanied by pyroptosis (an inflammatory form of lytic programmed cell death), some cells can survive and exist in a state of hyperactivation. Here, we found that the conventional type 2 DC (cDC2) subset is the major human DC subset that is transcriptionally and functionally poised for inflammasome formation and response without pyroptosis. When cDC2 were stimulated with ligands that relatively weakly activated the inflammasome, the cells did not enter pyroptosis but instead secreted IL-12 family cytokines and IL-1. These cytokines induced prominent T helper type 1 (TH1) and TH17 responses that were superior to those seen in response to Toll-like receptor (TLR) stimulation alone or to stronger, classical inflammasome ligands. These findings not only define the human cDC2 subpopulation as a prime target for the treatment of inflammasome-dependent inflammatory diseases but may also inform new approaches for adjuvant and vaccine development.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Dendritic cells; cDC2; CD1c; inflammasome; hyperactivation; L18-MDP; T cell differentiation

Select hyperactivating NLRP3 ligands enhance the TH1-and TH17-inducing potential of human type 2 conventional dendritic cells - Heger, Lukas; Hatscher, Lukas; Lehmann, Christian; Purbojo, Ariawan; Onderka, Constantin; Liang, C.; Hartmann, Arndt; Cesnjevar, Robert; Bruns, Heiko; Gross, O.; Nimmerjahn, Falk; Ivanovic-Burmazovic, I.; et al. (EXPERIMENTAL DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-03-04

Selective elimination of immunosuppressive T cells in patients with multiple myeloma - Awwad, Mohamed H. S.; Mahmoud, Abdelrahman; Bruns, Heiko; Echchannaoui, Hakim; Kriegsmann, Katharina; Lutz, Raphael; Raab, Marc S.; Bertsch, Uta; Munder, Markus; Jauch, Anna; Weisel, Katja; Maier, Bettina; et al. (Leukemia, 2021)
Elimination of suppressive T cells may enable and enhance cancer immunotherapy. Here, we demonstrate that the cell membrane protein SLAMF7 was highly expressed on immunosuppressive CD8+CD28-CD57+ Tregs in multiple myeloma (MM). SLAMF7 expression associated with T cell exhaustion surface markers and exhaustion-related transcription factor signatures. T cells from patients with a high frequency of SLAMF7+CD8+ T cells exhibited decreased immunoreactivity towards the MART-1aa26–35*A27L antigen. A monoclonal anti-SLAMF7 antibody (elotuzumab) specifically depleted SLAMF7+CD8+ T cells in vitro and in vivo via macrophage-mediated antibody-dependent cellular phagocytosis (ADCP). Anti-SLAMF7 treatment of MM patients depleted suppressive T cells in peripheral blood. These data highlight SLAMF7 as a marker for suppressive CD8+ Treg and suggest that anti-SLAMF7 antibodies can be used to boost anti-tumoral immune responses in cancer patients.
CRIS-Team Scopus Importer:2021-03-05

Selective PRMT5 Inhibitors Suppress Human CD8+ T Cells by Upregulation of p53 and Impairment of the AKT Pathway Similar to the Tumor Metabolite MTA - Strobl, Carolin; Schaffer, Susann; Haug, Tabea; Peter, Katrin; Singer, Katrin; Böttcher, Martin; Mougiakakos, Dimitrios; Mackensen, Andreas; Aigner, Michael; Völkl, Simon (Molecular Cancer Therapeutics, 2020)
Genetic alterations in tumor cells provide promising targets for antitumor therapy. Recently, loss of methylthioadenosine phosphorylase (MTAP), a deletion frequently occurring in cancer, has been shown to create vulnerability to the inhibition of the protein arginine methyltransferase 5 (PRMT5). MTAP deficiency leads to accumulation of methylthioadenosine (MTA), which reduces PRMT5 activity, and thus, sensitizes the tumor cells to selective PRMT5 inhibitors (PRMT5i). PRMT5i are investigated as a new strategy to selectively kill MTAP-deficient tumor cells by blocking residual PRMT5 activity, but also to treat PRMT5-overexpressing tumors. Although many studies investigated the role of PRMT5 in cancer, only little data exist about the effect of PRMT5 inhibition on immune cells. As we could show that the tumor metabolite MTA suppresses T cells, we asked whether selective PRMT5 inhibition is detrimental for T-cell immune responses. Therefore, we examined the effect of the synthetic PRMT5 inhibitor EPZ015666 on human CD8+ T cells in direct comparison with the naturally occurring PRMT5-inhibiting molecule MTA. Both compounds reduced T-cell proliferation, viability, and functionality. In addition, T-cell metabolism was impaired upon PRMT5 inhibition. These effects coincided with the induction of p53 expression and reduced AKT/mTOR signaling. Our data clearly demonstrate that PRMT5 activity is involved in various cellular processes of human CD8+ T cells associated with essential T-cell functions. Therefore, not only tumor cells, but also antitumor immune responses, are compromised by PRMT5 inhibitors. This emphasizes the importance of considering side effects on the immune system when developing new strategies to specifically target not only MTAP-deficient tumors.
CRIS-Team Scopus Importer:2020-02-18

Semi-automated delineation of breast cancer tumors and subsequent materialization using three-dimensional printing (rapid prototyping) - Schulz-Wendtland, Rüdiger; Harz, Markus; Meier-Meitinger, Martina; Brehm, Barbara; Wacker, Till; Hahn, Horst K.; Wagner, Florian; Wittenberg, Thomas; Beckmann, Matthias; Uder, Michael; Fasching, Peter; Emons, Julius (Journal of Surgical Oncology, 2017)
Three-dimensional (3D) printing has become widely available, and a few cases of its use in clinical practice have been described. The aim of this study was to explore facilities for the semi-automated delineation of breast cancer tumors and to assess the feasibility of 3D printing of breast cancer tumors.In a case series of five patients, different 3D imaging methods-magnetic resonance imaging (MRI), digital breast tomosynthesis (DBT), and 3D ultrasound-were used to capture 3D data for breast cancer tumors. The volumes of the breast tumors were calculated to assess the comparability of the breast tumor models, and the MRI information was used to render models on a commercially available 3D printer to materialize the tumors.The tumor volumes calculated from the different 3D methods appeared to be comparable. Tumor models with volumes between 325 mm(3) and 7,770 mm(3) were printed and compared with the models rendered from MRI. The materialization of the tumors reflected the computer models of them.3D printing (rapid prototyping) appears to be feasible. Scenarios for the clinical use of the technology might include presenting the model to the surgeon to provide a better understanding of the tumor's spatial characteristics in the breast, in order to improve decision-making in relation to neoadjuvant chemotherapy or surgical approaches. J. Surg. Oncol. 2017;115:238-242. © 2016 Wiley Periodicals, Inc.
EVALuna2:14618

Serial Biomarker Monitoring Early after HCT Identifies Different Risks for Relapse and Graft-Vs-Host Disease - Aziz, Mina D.; Shah, Jay; Kapoor, Urvi; Dimopoulos, Christina N.; Ayuk, Francis A.; Hogan, William J.; Schreiner, Elisabeth; Choe, Hannah K.; Chen, Yi-Bin; Hexner, Elizabeth O.; Etra, Aaron; Merli, Pietro; et al. (BLOOD, 2018)
CRIS-Team WoS Importer:2019-03-06

SERIO - Side Effect Registry Immuno-Oncology Side Effect Registry for rare, severe and complex Side Effects of Immunotherapy - Kramer, Rafaela; Mentzer, D.; Erdmann, M.; Knauss, S.; Broeckelmann, P. J.; Hassel, J. C.; Ugurel, S.; Pavel, Marianne Ellen; Nickel, Franziska; Landendinger, M.; Fuchs, Friederike; Meidenbauer, Norbert; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Serio - Side Effect Registry in Immuno-Oncology - Koutzamanidis, Rafaela; Mentzer, Dirk; Knauss, Samuel; Broeckelmann, Paul J.; Hassel, Jessica Cecile; Ugurel-Becker, Selma; Pavel, Marianne Ellen; Nickel, Florian; Landendinger, Melanie; Fuchs, Florian; Meidenbauer, Norbert; Jefremow, Andre; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Severity of COVID-19 disease is related to hyperactivation and altered migratory capacity of T cells - Spörl, Silvia; Kremer, Anna-Lena; Aigner, Michael; Eisenhauer, Nina; Koch, P.; Meretuk, L.; Loeffler, P.; Lutzny-Geier, Gloria; Vetter, Marcel; Bruns, Heiko; Mackensen, Andreas; Kremer, Andreas; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

SGLT-2-inhibition with dapagliflozin reduces tissue sodium content: a randomised controlled trial - Karg, Margarete; Bosch, A.; Kannenkeril, D.; Striepe, Kristina; Ott, Christian; Schneider, M. P.; Boemke-Zelch, Franziska; Linz, Peter; Nagel, Armin Michael; Titze, Jens; Uder, Michael; Schmieder, Roland (Cardiovascular Diabetology, 2018)
Sodium tissue content by 23Na magnetic resonance imaging (Na-MRI) has been validated in experimental and human studies. SGLT-2 inhibition blocks the reabsorption of glucose and of sodium in the proximal tubular cells in a 1:1 fashion. We hypothesized that SGLT-2 inhibition in patients with type 2 diabetes characterized by sodium retention leads to decreased tissue sodium content due to its pharmacological action.In a prospective double blind, placebo controlled, cross-over trial 59 patients (61 ± 7.6 years) with type 2 diabetes were randomized to either dapagliflozin 10 mg or placebo once daily for 6 weeks each. In addition to metabolic parameters and ambulatory blood pressure (BP) we analysed the sodium content in the skin and muscles of the lower leg by Na-MRI.Compared to baseline 6 weeks treatment with the SGLT-2 inhibitor dapagliflozin decreased fasting (132 ± 28 vs. 114 ± 19 mg/dl, p < 0.001), postprandial blood glucose (178 ± 66 mg/dl vs. 153 ± 46 mg/dl, p < 0.001), body weight (87.6 vs. 86.6 kg, p < 0.001) and systolic (129 ± 12 vs. 126 ± 11 mmHg, p = 0.010), and diastolic (77.4 ± 9 vs. 75.6 ± 8 mmHg, p = 0.024), 24-h ambulatory BP. Tissue sodium content in the skin was reduced after 6 weeks treatment with dapagliflozin compared to baseline [24.1 ± 6.6 vs. 22.7 ± 6.4 A.U.(arbitrary unit) p = 0.013]. No significant reduction of tissue sodium content was observed in the muscle (M. triceps surae: 20.5 ± 3.5 vs. 20.4 ± 3.7 A.U. p = 0.801). No clear significant difference in tissue water content of muscle and skin was observed after 6 weeks of treatment with dapagliflozin, compared to baseline.SGLT-2 inhibition with dapagliflozin resulted in a significant decrease in tissue sodium content of the skin after 6 weeks. This observation point to a decrease of total sodium content in patients with type 2 diabetes prone to cardiovascular complications, that might be mitigated by SGLT-2 inhibition. Trial registration The study was registered at http://www.clinicaltrials.gov (NCT02383238) retrospectively registered.
EVALuna2:4043

Short- and long term effects of epidural analgesia on morbidity and mortality of esophageal cancer surgery - Heinrich, Stefan; Janitz, Katrin; Merkel, Susanne; Klein, Peter; Schmidt, Joachim (Langenbecks Archives of Surgery, 2015)
Perioperative regional anesthesia with consecutive reduction of intra- and postoperative systemic opioid requirements in order to improve oncological result after cancer surgery has only been addressed by a few reports. This hypothesis has never been proved in esophageal cancer with a long-term follow-up of more than 5 years. Therefore, we addressed the impact on short- and long-term outcomes of epidural analgesia for esophagus cancer surgery.All available records from patients who underwent esophageal cancer surgery from 1995 to 2005 were retrospectively analyzed. Short- and long-term outcome variables including opioid requirements, duration of ICU-stay, survival, and cancer recurrence were compared between patients with and patients without epidural analgesia for abdomino-right-thoracic esophagectomy.Overall, the analysis included 153 patients, 118 received epidural analgesia; in 35 patients, epidural analgesia was avoided. We found significantly increased postoperative median opioid consumption (10-day intravenous morphine equivalent 187 versus 104 mg) and duration of ICU hospitalization (10.1 vs. 5.9 days, p < 0.05) in the non-epidural group compared with the epidural group. However, there were no significant differences in cancer recurrence (23 % non-epidural group, 27 % epidural group), 1-year mortality (14 vs. 11 %), or 5-year survival (29 vs. 28 %) between the two patient groups.The results of our study underline the well-known clinical benefits of epidural analgesia for esophagus surgery. However, we found no evidence that the further oncological outcome is determined or significantly influenced by the presence or absence of epidural analgesia.
EVALuna2:15179

Short chain fatty acids are potent regulators of systemic bone mass and protect for pathological bone loss by inhibiting osteoclasts - Lucas, S.; Omata, Y.; Böttcher, Martin; Hofmann, Jörg; Krishnacoumar, B.; Krönke, Gerhard; Mougiakakos, Dimitrios; Iljazovic, A.; Sonnewald, Uwe; Strowig, T.; Schett, Georg; Zaiss, Mario (European Journal of Immunology, 2017)

Short-chain fatty acids regulate systemic bone mass and protect from pathological bone loss - Lucas, Sebastien; Omata, Yasunori; Hofmann, Jörg; Böttcher, Martin; Iljazovic, Aida; Sarter, Kerstin; Albrecht, Olivia; Schulz, Oscar; Krishnacoumar, Brenda; Krönke, Gerhard; Herrmann, Martin; Mougiakakos, Dimitrios; et al. (Nature Communications, 2018)
Microbial metabolites are known to modulate immune responses of the host. The main metabolites derived from microbial fermentation of dietary fibers in the intestine, short-chain fatty acids (SCFA), affect local and systemic immune functions. Here we show that SCFA are regulators of osteoclast metabolism and bone mass in vivo. Treatment of mice with SCFA as well as feeding with a high-fiber diet significantly increases bone mass and prevents postmenopausal and inflammation-induced bone loss. The protective effects of SCFA on bone mass are associated with inhibition of osteoclast differentiation and bone resorption in vitro and in vivo, while bone formation is not affected. Mechanistically, propionate (C3) and butyrate (C4) induce metabolic reprogramming of osteoclasts resulting in enhanced glycolysis at the expense of oxidative phosphorylation, thereby downregulating essential osteoclast genes such as TRAF6 and NFATc1. In summary, these data identify SCFA as potent regulators of osteoclast metabolism and bone homeostasis.
EVALuna2:13520

Should Breast Cancer Surgery Be Done in an Outpatient Setting?: Health Economics From the Perspective of Service Providers - Formago, Margaret; Schrauder, Michael G.; Rauh, Claudia; Hack, Carolin; Jud, Sebastian; Hildebrandt, Thomas; Schulz-Wendtland, Rüdiger; Frentz, S.; Graubert, S.; Beckmann, Matthias; Lux, Michael P. (Geburtshilfe und Frauenheilkunde, 2017)
INTRODUCTION: The care of patients with breast cancer is extremely complex and requires interdisciplinary care in certified facilities. These specialized facilities provide numerous services without being correspondingly remunerated. The question whether breast cancer surgery should be performed in an outpatient setting to reduce costs is increasingly being debated. This study compares inpatient surgical treatment with a model of the same surgery performed on an outpatient basis to examine the potential financial impact. MATERIAL AND METHODS: A theoretical model was developed and the DRG fees for surgical interventions to treat primary breast cancer were calculated. A theoretical 1-day DRG was then calculated to permit comparisons with outpatient procedures. The costs of outpatient surgery were calculated based on the remuneration rates of the AOP (Outpatient Surgery) Contract and the EBM (Uniform Assessment Scale) and compared to the costs of the 1-day DRG. RESULTS: The DRG fee for both breast-conserving surgery and mastectomy is higher than the fee paid in the context of the EBM system, although the same procedures were carried out in both systems. If a hospital were to carry out breast-conserving surgery as an outpatient procedure, the fee would be € 1313.81; depending on the type of surgery, the hospital would therefore only receive between 39.20% and 52.82% of the DRG fee. This was the case even for a 1-day treatment. Compared to the real DRG fees the difference would be even more striking. CONCLUSION: Carrying out breast cancer surgery as an outpatient procedure would result in a significant shortfall of revenues. Additional services from certified centers, such as the interdisciplinary planning of treatment, psycho-oncological and social-medical care with the involvement of relatives, detailed documentation, etc., which are currently provided without surcharge or adequate remuneration, could no longer be maintained. The quality of processes and excellent results which have been achieved and ultimately the care given by certified facilities would be significantly at risk.
EVALuna2:34710

Side effect management of tyrosine kinase inhibitors in urology : Hypertension - Sikic, D.; Meidenbauer, N.; Lieb, V.; Keck, Bastian (Urologe, 2016)
Tyrosine kinase inhibitors like sunitinib, sorafenib, pazopanib or axintinib are regarded the standard of care in the systemic therapy of metastatic renal cell carcinoma. However, the many side effects associated with this therapy pose challenges for the treating physician and the patient. This review offers an overview of the classification and the treatment of hypertension, which is one of the major side effects induced by all tyrosine kinase inhibitors, in order to improve treatment efficacy and patient compliance.
EVALuna2:25744

Similar Inhibition of Dynamic Adhesion of Lymphocytes From IBD Patients to MAdCAM-1 by Vedolizumab and Etrolizumab-s - Binder, Marie-Theres; Becker, Emily; Wiendl, Maximilian; Schleier, Lena; Fuchs, Florian; Leppkes, Moritz; Atreya, Raja; Neufert, Clemens; Atreya, Imke; Neurath, Markus; Zundler, Sebastian (Inflammatory Bowel Diseases, 2018)
Background: Although anti-adhesion therapies are a novel mainstay in the treatment of inflammatory bowel diseases (IBDs), the mechanisms controlling integrin-dependent gut homing are poorly elucidated, and the available techniques for translational functional investigations are limited. Methods: We used dynamic adhesion assays to study adhesion of CD4+ T cells, CD8+ T cells, CD19+ B cells, and granulocytes to the addressins MAdCAM-1, VCAM-1, and ICAM-1. The effects of vedolizumab, natalizumab, etrolizumab-s, anti-CD11a, and anti-CD18 antibodies were explored. Results: Adhesion of peripheral blood leukocytes from IBD patients and control donors could be validly assessed, and integrin-mediated addressin adhesion could be specifically inhibited by anti-integrin antibodies. Numbers of adhering cells were partly, but not completely, related to integrin expression. Vedolizumab and etrolizumab-s resulted in similar reduction of adhesion to MAdCAM-1, and preliminary data proposed an association of dynamic adhesion to MAdCAM-1 with response to vedolizumab therapy. Conclusions: Dynamic adhesion assays are an easy and broadly applicable method for IBD research that is useful for future translational studies and potentially also for supporting clinical treatment decisions. 10.1093/ibd/izy077_video1izy077_Video_15786486962001.
EVALuna2:35167

Single cell identification of defined ebv epitope-specific TCR alpha beta pairs for adoptive T cell transfer against EBV infection and EBV-associated malignancies - Cobo, Maria Fernanda Lammoglia; Pircher, Christian; Dietze, Kerstin; Kammertons, Thomas; Gary, Regina; Moosmann, Andreas; Mautner, Josef; Dornmair, Klaus; Takvorian, Anna; Bullinger, Lars; Blankenstein, Thomas; Gerbitz, Armin; et al. (BONE MARROW TRANSPLANTATION, 2019)
CRIS-Team WoS Importer:2019-10-11

Single-cell Transcriptome Analysis and clonal Kinetics in a Patient after CD19.CAR-T Cell Therapy - Lischer, Christopher; Eisenhauer, Nina; Aigner, Michael; Jacobs, Benedikt; Schletter, M.; Gebhard, C.; Rehli, M.; Bruns, Heiko; Müller, Fabian; Mackensen, Andreas; Vera González, Julio; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Single nucleotide polymorphism D1853N of the ATM gene may alter the risk for breast cancer - Schrauder, M.; Frank, S.; Strissel, Pamela; Lux, Michael P.; Bani, Mayada; Rauh, C.; Sieber, Cornel; Heusinger, K.; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Strick, Reiner; Beckmann, Matthias; et al. (Journal of Cancer Research and Clinical Oncology, 2008)
Purpose Various ATM (ataxia telangiectasia-mutated) mutations and polymorphisms have been reported to be associated with an increased breast cancer risk. Recent studies have produced contradictory results regarding the association between ATM genetic variants and breast cancer risk.Materials and methods The common ATM polymorphism 5557G > A (p.D1853N) (rs1801516), previously suggested to be associated with bilateral breast cancer, was analyzed using real-time PCR in 514 unselected patients with breast cancer and 511 age-matched healthy control individuals. DNA was obtained from peripheral blood draw.Results The ATM genotype was weakly associated with the risk for breast cancer (P = 0.04 for the overall test). The odds ratio for women with a heterozygous genotype was 0.70 (95% CI, 0.52-0.94) and for the homozygous variant 0.63 (95% CI, 0.27-1.49). Disease-free survival and overall survival showed no significant association with specific genotypes.Conclusions The results of this study might suggest a minor association between polymorphism 5557G > A and a reduced risk of breast cancer.
Keywords: TM gene variants; polymorphism; breast cancer; DNA damage; epidemiology; association

Single Versus Double Induction with "7+3" Containing 60 Versus 90 Mg Daunorubicin for Newly Diagnosed AML: Results from the Randomized Controlled SAL Dauno-Double Trial - Roellig, Christoph; Steffen, Bjoern; Schliemann, Christoph; Mikesch, Jan-Henrik; Alakel, Nael; Herbst, Regina; Haenel, Mathias; Noppeney, Richard; Hanoun, Maher; Kaufmann, Martin; Racil, Zdenek; Schaefer-Eckart, Kerstin; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Siponimod (BAF-312) Attenuates Perihemorrhagic Edema And Improves Survival in Experimental Intracerebral Hemorrhage - Bobinger, Tobias; Manaenko, Anatol; Burkardt, Petra; Beuscher, Vanessa; Sprügel, Maximilian; Röder, Sebastian; Bäuerle, Tobias; Seyler, Lisa; Nagel, Armin Michael; Linker, Ralf; Engelhorn, Tobias; Dörfler, Arnd; et al. (Stroke, 2019)
Background and Purpose- Perihemorrhagic edema (PHE) is associated with poor outcome after intracerebral hemorrhage (ICH). Infiltration of immune cells is considered a major contributor of PHE. Recent studies suggest that immunomodulation via S1PR (sphingosine-1-phosphate receptor) modulators improve outcome in ICH. Siponimod, a selective modulator of sphingosine 1-phosphate receptors type 1 and type 5, demonstrated an excellent safety profile in a large study of patients with multiple sclerosis. Here, we investigated the impact of siponimod treatment on perihemorrhagic edema, neurological deficits, and survival in a mouse model of ICH. Methods- ICH was induced by intracranial injection of 0.075 U of bacterial collagenase in 123 mice. Mice were randomly assigned to different treatment groups: vehicle, siponimod given as a single dosage 30 minutes after the operation or given 3× for 3 consecutive days starting 30 minutes after operation. The primary outcome of our study was evolution of PHE measured by magnetic resonance-imaging on T2-maps 72 hours after ICH, secondary outcomes included evolution of PHE 24 hours after ICH, survival and neurological deficits, as well as effects on circulating blood cells and body weight. Results- Siponimod significantly reduced PHE measured by magnetic resonance imaging (P=0.021) as well as wet-dry method (P=0.04) 72 hours after ICH. Evaluation of PHE 24 hours after ICH showed a tendency toward attenuated brain edema in the low-dosage group (P=0.08). Multiple treatments with siponimod significantly improved neurological deficits measured by Garcia Score (P=0.03). Survival at day 10 was improved in mice treated with multiple dosages of siponimod (P=0.037). Mice treated with siponimod showed a reduced weight loss after ICH (P=0.036). Conclusions- Siponimod (BAF-312) attenuated PHE after ICH, increased survival, and reduced ICH-induced sensorimotor deficits in our experimental ICH-model. Findings encourage further investigation of inflammatory modulators as well as the translation of BAF-312 to a human study of ICH patients.
EVALuna2:204480

Siponimod reduces perihemorrhagic edema and improves neurological outcome in experimental intracerebral hemorrhage - Bobinger, Tobias; Manaenko, A.; Baeurele, T.; Seyler, L.; Nagel, Armin Michael; Engelhorn, Tobias; Dörfler, Arnd; Kuramatsu, J. B.; Schwab, Stefan; Huttner, Hagen (JOURNAL OF CEREBRAL BLOOD FLOW AND METABOLISM, 2019)
CRIS-Team WoS Importer:2019-07-19

Sorafenib induces sustained molecular remission in FLT3-ITD positive AML with relapse after second allogeneic stem cell transplantation without exacerbation of acute GVHD: A case report - Winkler, Julia; Rech, D.; Kallert, Siegfried; Rech, Jürgen; Meidenbauer, Norbert; Rösler, Wolf; Mackensen, Andreas (Leukemia Research, 2010)
CRIS-Team Scopus Importer:2021-02-03

Sorafenib or placebo in patients with newly diagnosed acute myeloid leukaemia: long-term follow-up of the randomized controlled SORAML trial - Röllig, Christoph; Serve, Hubert; Noppeney, Richard; Hanoun, Maher; Krug, Utz; Baldus, Claudia D.; Brandts, Christian H.; Kunzmann, Volker; Einsele, Hermann; Krämer, Alwin; Müller-Tidow, Carsten; Schäfer-Eckart, Kerstin; et al. (Leukemia, 2021)
Early results of the randomized placebo-controlled SORAML trial showed that, in patients with newly diagnosed acute myeloid leukaemia (AML), sorafenib led to a significant improvement in event-free (EFS) and relapse-free survival (RFS). In order to describe second-line treatments and their implications on overall survival (OS), we performed a study after a median follow-up time of 78 months. Newly diagnosed fit AML patients aged ≤60 years received sorafenib (n = 134) or placebo (n = 133) in addition to standard chemotherapy and as maintenance treatment. The 5-year EFS was 41 versus 27% (HR 0.68; p = 0.011) and 5-year RFS was 53 versus 36% (HR 0.64; p = 0.035). Allogeneic stem cell transplantation (allo SCT) was performed in 88% of the relapsed patients. Four years after salvage allo SCT, the cumulative incidence of relapse was 54 versus 35%, and OS was 32 versus 50%. The 5-year OS from randomization in all study patients was 61 versus 53% (HR 0.82; p = 0.282). In conclusion, the addition of sorafenib to chemotherapy led to a significant prolongation of EFS and RFS. Although the OS benefit did not reach statistical significance, these results confirm the antileukaemic activity of sorafenib.
CRIS-Team Scopus Importer:2021-03-05

Sorafenib promotes graft-versus-leukemia activity in mice and humans through IL-15 production in FLT3-ITD-mutant leukemia cells - Mathew, Nimitha R.; Baumgartner, Francis; Braun, Lukas; O'Sullivan, David; Thomas, Simone; Waterhouse, Miguel; Mueller, Tony A.; Hanke, Kathrin; Taromi, Sanaz; Apostolova, Petya; Illert, Anna L.; Melchinger, Wolfgang; et al. (Nature Medicine, 2018)
Individuals with acute myeloid leukemia (AML) harboring an internal tandem duplication (ITD) in the gene encoding Fms-related tyrosine kinase 3 (FLT3) who relapse after allogeneic hematopoietic cell transplantation (allo-HCT) have a 1-year survival rate below 20%. We observed that sorafenib, a multitargeted tyrosine kinase inhibitor, increased IL-15 production by FLT3-ITD+leukemia cells. This synergized with the allogeneic CD8+T cell response, leading to long-term survival in six mouse models of FLT3-ITD+AML. Sorafenib-related IL-15 production caused an increase in CD8+CD107a+IFN-γ+T cells with features of longevity (high levels of Bcl-2 and reduced PD-1 levels), which eradicated leukemia in secondary recipients. Mechanistically, sorafenib reduced expression of the transcription factor ATF4, thereby blocking negative regulation of interferon regulatory factor 7 (IRF7) activation, which enhanced IL-15 transcription. Both IRF7 knockdown and ATF4 overexpression in leukemia cells antagonized sorafenib-induced IL-15 production in vitro. Human FLT3-ITD+AML cells obtained from sorafenib responders following sorafenib therapy showed increased levels of IL-15, phosphorylated IRF7, and a transcriptionally active IRF7 chromatin state. The mitochondrial spare respiratory capacity and glycolytic capacity of CD8+T cells increased upon sorafenib treatment in sorafenib responders but not in nonresponders. Our findings indicate that the synergism of T cells and sorafenib is mediated via reduced ATF4 expression, causing activation of the IRF7-IL-15 axis in leukemia cells and thereby leading to metabolic reprogramming of leukemia-reactive T cells in humans. Therefore, sorafenib treatment has the potential to contribute to an immune-mediated cure of FLT3-ITD-mutant AML relapse, an otherwise fatal complication after allo-HCT.
EVALuna2:33530

Specific inhibition of PRMT5 suppresses human CD8+T cells by upregulation of p53 and impairment of the AKT pathway similar to the tumor metabolite MTA - Strobl, Carolin; Schaffer, Susann; Haug, T.; Peter, K.; Böttcher, Martin; Mougiakakos, Dimitrios; Mackensen, Andreas; Aigner, Michael; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Specific phenotype and function of CD56-expressing innate immune cell subsets in human thymus - Gerstner, Stephanie; Köhler, Wolfgang; Heidkamp, Gordon Frederik; Purbojo, Ariawan; Uchida, Shizuka; Ekici, Arif Bülent; Heger, Lukas; Luetke-Eversloh, Merlin; Schubert, Ralf; Bader, Peter; Klingebiel, Thomas; Koehl, Ulrike; et al. (Journal of Leukocyte Biology, 2016)
Whereas innate immune cells, such as NK and innate lymphoid cells (ILCs), have been characterized in different human tissues, knowledge on the thymic CD56-expressing cell subsets is limited. In this study, the rare subpopulations of thymic CD56(+)CD3(-) cells from samples of >100 patients have been successfully analyzed. The results revealed fundamental differences between thymic and peripheral blood (PB) CD56(+)CD3(-) cells. Thymic tissues lacked immunoregulatory CD56(high)CD16(dim) NK cells but showed two Eomes(+)CD56(dim) subsets on which common NK cell markers were significantly altered. CD56(dim)CD16(high) cells expressed high amounts of NKG2A, NKG2D, and CD27 with low CD57. Conversely, CD56(dim)CD16(dim) cells displayed high CD127 but low expression of KIR, NKG2D, and natural cytotoxicity receptors (NCRs). Thymic CD56(+)CD3(-) cells were able to gain cytotoxicity but were especially immunoregulatory cells, producing a broad range of cytokines. Finally, one population of thymic CD56(+) cells resembled conventional NK cells, whereas the other represented a novel, noncanonical NK subset.
EVALuna2:9311

Statin Use Ameliorates Survival in Oral Squamous Cell Carcinoma-Data from a Population-Based Cohort Study Applying Propensity Score Matching - Spoerl, Steffen; Gerken, Michael; Fischer, Rene; Spörl, Silvia; Kirschneck, Christian; Wolf, Stefanie; Taxis, Juergen; Ludwig, Nils; Biermann, Niklas; Reichert, Torsten E.; Spanier, Gerrit (Biomedicines, 2023)
The anti-cancer properties of statins have attracted much attention recently, but little is known about the prognostic role of statins in oral squamous cell carcinoma (OSCC). In a retrospective approach, we analyzed a population-based cohort of 602 OSCC patients with primary curative tumor resection to negative margins and concomitant neck dissection between 2005-2017. Long-term medication with statins was correlated with overall survival (OAS) as well as recurrence-free survival (RFS) using uni- and multivariable Cox regression. Additionally, propensity score matching was applied to adjust for confounders. Statin use was present in 96 patients (15.9%) at a median age of 65.7 years. Statin treatment correlated with ameliorated survival in multivariable Cox regression in the complete cohort (OAS: HR 0.664; 95% CI 0.467-0.945, p = 0.023; RFS: HR 0.662; 95% CI 0.476-0.920, p = 0.014) as well as matched-pair cohort of OSCC patients (OAS: HR 0.691; 95% CI 0.479-0.997, p = 0.048; RFS: HR 0.694; 95% CI 0.493-0.976, p = 0.036) when compared to patients not taking statins at time of diagnosis. These findings were even more pronounced by sub-group analysis in the matched-pair cohort (age < 70 years). These data indicate that statin use might ameliorate the oncological outcome in primarily resected OSCC patients, but prospective clinical trials are highly recommended.
CRIS-Team WoS Importer:2023-03-17

Strain specific differences in vitamin D3 response: impact on gut homeostasis - Schreiber, Laura; Ghimire, Sakhila; Hiergeist, Andreas; Renner, Kathrin; Althammer, Michael; Babl, Nathalie; Peuker, Alice; Schoenhammer, Gabriele; Hippe, Katrin; Gessner, Andre; Albrecht, Christin; Pielmeier, Fransziska; et al. (Frontiers in Immunology, 2024)
Vitamin D3 regulates a variety of biological processes irrespective of its well-known importance for calcium metabolism. Epidemiological and animal studies indicate a role in immune regulation, intestinal barrier function and microbiome diversity. Here, we analyzed the impact of different vitamin D3- containing diets on C57BL/6 and BALB/c mice, with a particular focus on gut homeostasis and also investigated effects on immune cells in vitro. Weak regulatory effects were detected on murine T cells. By trend, the active vitamin D3 metabolite 1,25-dihydroxyvitamin D3 suppressed IFN, GM-CSF and IL-10 cytokine secretion in T cells of C57BL/6 but not BALB/c mice, respectively. Using different vitamin D3-fortified diets, we found a tissue–specific enrichment of mainly CD11b+ myeloid cells but not T cells in both mouse strains e.g. in spleen and Peyer’s Patches. Mucin Reg3γ and Batf expression, as well as important proteins for gut homeostasis, were significantly suppressed in the small intestine of C57BL76 but not BALB/c mice fed with a high-vitamin D3 containing diet. Differences between both mouse stains were not completely explained by differences in vitamin D3 receptor expression which was strongly expressed in epithelial cells of both strains. Finally, we analyzed gut microbiome and again an impact of vitamin D3 was detected in C57BL76 but not BALB/c. Our data suggest strain-specific differences in vitamin D3 responsiveness under steady state conditions which may have important implications when choosing a murine disease model to study vitamin D3 effects.
CRIS-Team Scopus Importer:2024-03-29
Keywords: BALB/c; barrier function; C57BL/6; intestinal; vitamin D3

Stroma Cells Promote a S100A8/A9(high)-Subset of AML Blasts with Distinct Metabolic Features in a Jak/STAT3-Dependent Manner - Böttcher, Martin; Panagiotidis, Konstantinos; Mackensen, Andreas; Mougiakakos, Dimitrios (BLOOD, 2018)
CRIS-Team WoS Importer:2019-02-27

Stroma cells promote a S100A8/A9(high) subset of chemoresistant AML blasts with distinct metabolic features in a Jak/STAT-dependent manner - Böttcher, Martin; Panagiotidis, Konstantinos; Mentz, K.; Popp, Sebastian; Geyh, S.; Jaeger, P.; Schroeder, T.; Bruns, Heiko; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Stromal cell-mediated glycolytic switch in CLL cells involves Notch-c-Myc signaling - Jitschin, Regina; Braun, Martina; Qorraj, Mirjeta; Saul, Domenica; Le Blanc, Katarina; Zenz, Thorsten; Mougiakakos, Dimitrios (Blood, 2015)
It is well established that the stromal niche exerts a protective effect on chronic lymphocytic leukemia (CLL) cells, thereby also affecting their drug sensitivity. One hallmark of malignant cells is metabolic reprogramming, which is mostly represented by a glycolytic shift known as the Warburg effect. Because treatment resistance can be linked to metabolic alterations, we investigated whether bone marrow stromal cells impact the bioenergetics of primary CLL cells. In fact, stromal contact led to an increase of aerobic glycolysis and the cells' overall glycolytic capacity accompanied by an increased glucose uptake, expression of glucose transporter, and glycolytic enzymes. Activation of Notch signaling and of its direct transcriptional target c-Myc contributed to this metabolic switch. Based on these observations, CLL cells' acquired increased glucose dependency as well as Notch-c-Myc signaling could be therapeutically exploited in an effort to overcome stroma-mediated drug resistance.
EVALuna2:25708

Stromal cells enhance PD-L1 expression on CLL cells via the oncogenic Notch-cMyc-EZH2 signaling axis - Böttcher, Martin; Mentz, K.; Popp, S.; Saul, D.; Bruns, Heiko; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Successful Generation of CD19 Chimeric Antigen Receptor T Cells from Patients with Advanced Systemic Lupus Erythematosus - Kretschmann, S.; Völkl, Simon; Reimann, Hannah; Krönke, Gerhard; Schett, Georg; Achenbach, Susanne; Lutzny-Geier, Gloria; Müller, Fabian; Mougiakakos, Dimitrios; Dingfelder, Janin; Flamann, Cindy; Hanssens, L.; et al. (Transplantation and Cellular Therapy, 2022)
Although it has been shown that the production of functional chimeric antigen receptor T cells is feasible in patients with B-cell malignancies, it is currently unclear whether sufficient amounts of functional autologous CAR T cells can be generated from patients with autoimmune diseases. Intrinsic T-cell abnormalities and T-cell–targeted immune suppression in patients with autoimmunity may hamper the retrieval of sufficient T cells and their transduction and expansion into CAR T cells. Patients with active systemic lupus erythematosus (SLE) underwent leukapheresis after tapering glucocorticoids and stopping T-cell–suppressive drugs. This material was used as source for manufacturing anti-CD19 CAR T-cell products (CAR) in clinical scale. Cells were transduced with a lentiviral anti-CD19 CAR vector and expanded under good manufacturing practice (GMP) conditions using a closed, semi-automatic system. Functionality of these CAR T cells derived from autoimmune patient cells was tested in vitro. Six SLE patients were analyzed. Leukapheresis could be successfully performed in all patients yielding sufficient T-cell numbers for clinical scale CAR T-cell production. In addition, CAR T cells showed high expansion rates and viability, leading to CAR T cells in sufficient doses and quality for clinical use. CAR T cells from all patients showed specific cytotoxicity against CD19+ cell lines in vitro. GMP grade generation of CD19 CAR T-cell products suitable for clinical use is feasible in patients with autoimmune disease.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Chimeric antigen receptor; Systemic lupus erythematosus; T cells

Successful targeting of BRAF V600E mutation with vemurafenib in a treatment-resistant extragonadal non-seminomatous germ cell tumor - Meintker, Lisa; Haller, Florian; Tögel, Lars; Schmidt, Daniela; Waibel, Heidi; Mackensen, Andreas; Meidenbauer, Norbert (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Successful Targeting of BRAF V600E Mutation With Vemurafenib in a Treatment-Resistant Extragonadal Nonseminomatous Germ-Cell Tumor - Meintker, Lisa; Haller, Florian; Tögel, Lars; Schmidt, Daniela; Waibel, Heidi; Hartmann, Arndt; Mackensen, Andreas; Meidenbauer, Norbert (JCO Precision Oncology, 2020)

Successful treatment of COVID-19 infection with convalescent plasma in B-cell-depleted patients may promote cellular immunity - Kremer, Andreas E.; Kremer, Anita; Willam, Carsten; Völkl, Simon; Verhagen, Johan; Achenbach, Susanne; van der Meijden, Edith; Lang, Vanessa; Aigner, Michael; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; et al. (European Journal of Immunology, 2021)
Treatment with convalescent plasma has been shown to be safe in coronavirus disease in 2019 (COVID-19) infection, although efficacy reported in immunocompetent patients varies. Nevertheless, neutralizing antibodies are a key requisite in the fight against viral infections. Patients depleted of antibody-producing B cells, such as those treated with rituximab (anti-CD20) for hematological malignancies, lack a fundamental part of their adaptive immunity. Treatment with convalescent plasma appears to be of general benefit in this particularly vulnerable cohort. We analyzed clinical course and inflammation markers of three B-cell-depleted patients suffering from COVID-19 who were treated with convalescent plasma. In addition, we measured serum antibody levels as well as peripheral blood CD38/HLA-DR-positive T-cells ex vivo and CD137-positive T-cells after in vitro stimulation with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-derived peptides in these patients. We observed that therapy with convalescent plasma was effective in all three patients and analysis of CD137-positive T-cells after stimulation with SARS-CoV-2 peptides showed an increase in peptide-specific T-cells after application of convalescent plasma. In conclusion, we here demonstrate efficacy of convalescent plasma therapy in three B-cell-depleted patients and present data that suggest that while application of convalescent plasma elevates systemic antibody levels only transiently, it may also boost specific T-cell responses.
CRIS-Team Scopus Importer:2021-09-17
Keywords: B-cell deficiency; convalescent plasma; COVID-19; SARS-CoV-2; T-cell immunity

Successful treatment of COVID-19 with convalescent plasma in B-cell depleted patients may promote cellular immunity - Kremer, Andreas; Kremer, Anita; Willam, Carsten; Verhagen, Johan; Achenbach, Susanne; Van Der Meiden, E.; Lang, Vanessa; Aigner, M.; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; Lutzny-Geier, Gloria; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Sunitinib does not impair natural killer cell function in patients with renal cell carcinoma - Möckel, Jennifer; Staiger, Nina; Mackensen, Andreas; Meidenbauer, Norbert; Evelyn, Ullrich (Oncology Letters, 2017)
Although the available treatment options have expanded, the survival of patients with metastatic renal cell carcinoma (RCC) remains poor. As patients with RCC lack responsiveness to chemotherapy or radiation, therapeutic options predominantly include surgical interventions and immunomodulatory approaches, including the administration of tyrosine kinase inhibitors (TKIs) such as sunitinib. Natural killer (NK) cells have been reported to be key players in TKI-mediated off-target effects on the immune system. However, only limited information is available regarding the possible impact of sunitinib on the function of NK cells of individual patients. The present study reports on the immunomonitoring results of three patients with metastatic RCC who underwent sunitinib treatment. These results were compared with age-matched, healthy controls in terms of the immune status of T, B and NK cells, focusing on functional in vitro analyses of NK cells. In all three patients, NK cell number, subset distribution and function, as measured by cluster of differentiation 107a degranulation, did not exhibit any significant alterations as a result of sunitinib treatment. These results indicate that sunitinib does not negatively affect NK cell function, which supports the pursuit of therapeutic modalities that combine immunomodulation and NK cell-stimulating approaches.
EVALuna2:25767

Suppressive effects of tumor cell-derived 5'-deoxy-5'-methylthioadenosine on human T cells - Henrich, Frederik; Singer, Katrin; Poller, Kerstin; Bernhardt, Luise; Strobl, Carolin; Limm, Katharina; Ritter, Axel P.; Gottfried, Eva; Voelkl, Simon; Jacobs, Benedikt; Peter, Katrin; Mougiakakos, Dimitrios; et al. (OncoImmunology, 2016)
The immunosuppressive tumor microenvironment represents one of the main obstacles for immunotherapy of cancer. The tumor milieu is among others shaped by tumor metabolites such as 5'-deoxy-5'-methylthioadenosine (MTA). Increased intratumoral MTA levels result from a lack of the MTA-catabolizing enzyme methylthioadenosine phosphorylase (MTAP) in tumor cells and are found in various tumor entities. Here, we demonstrate that MTA suppresses proliferation, activation, differentiation, and effector function of antigen-specific T cells without eliciting cell death. Conversely, if MTA is added to highly activated T cells, MTA exerts cytotoxic effects on T cells. We identified the Akt pathway, a critical signal pathway for T cell activation, as a target of MTA, while, for example, p38 remained unaffected. Next, we provide evidence that MTA exerts its immunosuppressive effects by interfering with protein methylation in T cells. To confirm the relevance of the suppressive effects of exogenously added MTA on human T cells, we used an MTAP-deficient tumor cell-line that was stably transfected with the MTAP-coding sequence. We observed that T cells stimulated with MTAP-transfected tumor cells revealed a higher proliferative capacity compared to T cells stimulated with Mock-transfected cells. In conclusion, our findings reveal a novel immune evasion strategy of human tumor cells that could be of interest for therapeutic targeting.
EVALuna2:4745

Surrogate endpoints for overall survival in metastatic melanoma: a meta-analysis of randomised controlled trials - Flaherty, Keith T.; Hennig, Michael; Lee, Sandra J.; Ascierto, Paolo A.; Dummer, Reinhard; Eggermont, Alexander M. M.; Hauschild, Axel; Kefford, Richard; Kirkwood, John M.; Long, Georgina V.; Lorigan, Paul; Mackensen, Andreas; et al. (Lancet Oncology, 2014)
Recent phase 3 trials have shown an overall survival benefit in metastatic melanoma. We aimed to assess whether progression-free survival (PFS) could be regarded as a reliable surrogate for overall survival through a meta-analysis of randomised trials.We systematically reviewed randomised trials comparing treatment regimens in metastatic melanoma that included dacarbazine as the control arm, and which reported both PFS and overall survival with a standard hazard ratio (HR). We correlated HRs for overall survival and PFS, weighted by sample size or by precision of the HR estimate, assuming fixed and random effects. We did sensitivity analyses according to presence of crossover, trial size, and dacarbazine dose.After screening 1649 reports and meeting abstracts published before Sept 8, 2013, we identified 12 eligible randomised trials that enrolled 4416 patients with metastatic melanoma. Irrespective of weighting strategy, we noted a strong correlation between the treatment effects for PFS and overall survival, which seemed independent of treatment type. Pearson correlation coefficients were 0·71 (95% CI 0·29-0·90) with a random-effects assumption, 0·85 (0·59-0·95) with a fixed-effects assumption, and 0·89 (0·68-0·97) with sample-size weighting. For nine trials without crossover, the correlation coefficient was 0·96 (0·81-0·99), which decreased to 0·93 (0·74-0·98) when two additional trials with less than 50% crossover were included. Inclusion of mature follow-up data after at least 50% crossover (in vemurafenib and dabrafenib phase 3 trials) weakened the PFS to overall survival correlation (0·55, 0·03-0·84). Inclusion of trials with no or little crossover with the random-effects assumption yielded a conservative statement of the PFS to overall survival correlation of 0·85 (0·51-0·96).PFS can be regarded as a robust surrogate for overall survival in dacarbazine-controlled randomised trials of metastatic melanoma; we postulate that this association will hold as treatment standards evolve and are adopted as the control arm in future trials.None.
EVALuna2:25692

Synergistic lethality in chronic myeloid leukemia – targeting oxidative phosphorylation and unfolded protein response effectively complements tyrosine kinase inhibitor treatment - Häselbarth, Lukas; Gamali, Sara; Saul, Domenica; Krumbholz, Manuela; Böttcher-Loschinski, Romy; Böttcher, Martin; Zou, Deyu; Metzler, Markus; Karow, Axel; Mougiakakos, Dimitrios (BMC Cancer, 2023)
Chronic myeloid leukemia (CML) is effectively treated with tyrosine kinase inhibitors (TKIs), targeting the BCR::ABL1 oncoprotein. Still, resistance to therapy, relapse after treatment discontinuation, and side effects remain significant issues of long-term TKI treatment. Preliminary studies have shown that targeting oxidative phosphorylation (oxPhos) and the unfolded protein response (UPR) are promising therapeutic approaches to complement CML treatment. Here, we tested the efficacy of different TKIs, combined with the ATP synthase inhibitor oligomycin and the ER stress inducer thapsigargin in the CML cell lines K562, BV173, and KU812 and found a significant increase in cell death. Both, oligomycin and thapsigargin, triggered the upregulation of the UPR proteins ATF4 and CHOP, which was inhibited by imatinib. We observed comparable effects on cell death when combining TKIs with the ATP synthase inhibitor 8-chloroadenosine (8-Cl-Ado) as a potentially clinically applicable therapeutic agent. Stress-related apoptosis was triggered via a caspase cascade including the cleavage of caspase 3 and the inactivation of poly ADP ribose polymerase 1 (PARP1). The inhibition of PARP by olaparib also increased CML death in combination with TKIs. Our findings suggest a rationale for combining TKIs with 8-Cl-Ado or olaparib for future clinical studies in CML.
CRIS-Team Scopus Importer:2023-12-15
Keywords: 8-chloroadenosine; ATF4; Caspase 3; CML; Olaparib; Oligomycin; Oxidative phosphorylation; PARP; Thapsigargin; TKI; UPR

Synergy of simultaneous activation of cell death pathways of unfolded protein response and of protein synthesis inhibition converges at IRE1a-immunotoxins generate a therapeutic window - Gsottberger, Franziska; Meier, Christina; Ammon, Anna-Maria; Petkovic, S.; Mellenthin, Lisa; Krumbholz, Manuela; Metzler, Markus; Mackensen, Andreas; Müller, Fabian (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Systematic comparison of donor chimerism in peripheral blood and bone marrow after hematopoietic stem cell transplantation - Bach, Christian; Steffen, M.; Rösler, Wolf; Winkler, Jürgen; Mackensen, Andreas; Stachel, Daniel; Metzler, Markus; Spriewald, B. M. (Blood Cancer Journal, 2017)
EVALuna2:13436

Systemic and Intra-Nodal Activation of NK Cells After Rituximab Monotherapy for Follicular Lymphoma - Enqvist, Monika; Jacobs, Benedikt; Junlen, Henna R.; Schaffer, Marie; Melen, Christopher M.; Friberg, Danielle; Wahlin, Bjorn Engelbrekt; Malmberg, Karl-Johan (Frontiers in Immunology, 2019)
Monotherapy with the anti-CD20 monoclonal antibody rituximab can induce complete responses (CR) in patients with follicular lymphoma (FL). Resting FcR gamma III+ (CD16(+)) natural killer (NK) cells respond strongly to rituximab-coated target cells in vitro. Yet, the contribution of NK cells in the therapeutic effect in vivo remains unknown. Here, we followed the NK cell repertoire dynamics in the lymph node and systemically during rituximab monotherapy in patients with FL. At baseline, NK cells in the tumor lymph node had a naive phenotype albeit they were more differentiated than NK cells derived from control tonsils as determined by the frequency of CD56(dim) NK cells and the expression of killer cell immunoglobulin-like receptors (KIR), CD57 and CD16. Rituximab therapy induced a rapid drop in NK cell numbers coinciding with a relative increase in the frequency of Ki67(+) NK cells both in the lymph node and peripheral blood. The Ki67(+) NK cells had slightly increased expression of CD16, CD57 and higher levels of granzyme A and perforin. The in vivo activation of NK cells was paralleled by a temporary loss of in vitro functionality, primarily manifested as decreased IFN gamma production in response to rituximab-coated targets. However, patients with pre-existing NKG2C(+) adaptive NK cell subsets showed less Ki67 upregulation and were refractory to the loss of functionality. These data reveal variable imprints of rituximab monotherapy on the NK cell repertoire, which may depend on pre-existing repertoire diversity.
CRIS-Team WoS Importer:2019-09-27

Tandem Duplications of the UBTF gene in Adult AML: A Rare but Recurrent Alteration Associated with Myelodysplasia and Poor Outcome - Georgi, Julia-Annabell; Stasik, Sebastian; Zukunft, Sven; Hartwig, Marita; Roellig, Christoph; Oelschlaegel, Uta; Krug, Utz; Sauer, Tim; Scholl, Sebastian; Hochhaus, Andreas; Bruemmendorf, Tim H.; Naumann, Ralph; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Targeted Inhibition of Protein Biosynthesis sensitizes Cancer Cells to IRE1a-mediated Apoptosis as a Consequence of the unfolded protein response - Gsottberger, Franziska; Meier, Christina; Ammon, Anna-Maria; Parker, S.; Wendland, Kerstin; George, Rebekka; Petkovic, S.; Mellenthin, Lisa; Emmerich, C.; Lutzny-Geier, Gloria; Mackensen, Andreas; Metzler, Markus; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Targeted inhibition of protein synthesis renders cancer cells vulnerable to apoptosis by unfolded protein response - Gsottberger, Franziska; Meier, Christina; Ammon, Anna-Maria; Parker, Scott; Wendland, Kerstin; George, Rebekka; Petkovic, Srdjan; Mellenthin, Lisa; Emmerich, Charlotte; Lutzny-Geier, Gloria; Metzler, Markus; Mackensen, Andreas; et al. (Cell Death & Disease, 2023)
Cellular stress responses including the unfolded protein response (UPR) decide over the fate of an individual cell to ensure survival of the entire organism. During physiologic UPR counter-regulation, protective proteins are upregulated to prevent cell death. A similar strategy induces resistance to UPR in cancer. Therefore, we hypothesized that blocking protein synthesis following induction of UPR substantially enhances drug-induced apoptosis of malignant cells. In line, upregulation of the chaperone BiP was prevented by simultaneous arrest of protein synthesis in B cell malignancies. Cytotoxicity by immunotoxins—approved inhibitors of protein synthesis—was synergistically enhanced in combination with UPR-inducers in seven distinct hematologic and three solid tumor entities in vitro. Synergistic cell death depended on mitochondrial outer membrane permeabilization via BAK/BAX, which correlated with synergistic, IRE1α-dependent reduction of BID, accompanied by an additive fall of MCL-1. The strong synergy was reproduced in vivo against xenograft mouse models of mantle cell lymphoma, Burkitt’s lymphoma, and patient-derived acute lymphoblastic leukemia. In contrast, synergy was absent in blood cells of healthy donors suggesting a tumor-specific vulnerability. Together, these data support clinical evaluation of blocking stress response counter-regulation using inhibitors of protein synthesis as a novel therapeutic strategy.
CRIS-Team Scopus Importer:2023-09-08

Targeting high-grade B cell lymphoma with CD19-specific T cells - Lehmann, Frank M.; Maurberger, Anna; Feicht, Samantha; Helm, Florian; Ladinig, Camilla; Kieback, Elisa; Uckert, Wolfgang; Kammertoens, Thomas; Kremmer, Elisabeth; Mautner, Josef; Gerbitz, Armin; Bornkamm, Georg W. (International Journal of Cancer, 2014)
Adoptive T cell therapy is an important additional treatment option for malignant diseases resistant to chemotherapy. Using a murine high-grade B cell lymphoma model, we have addressed the question whether the B cell differentiation antigen CD19 can act as rejection antigen. CD19(-/-) mice inoculated with CD19(+) B cell lymphoma cells showed higher survival rates than WT mice and were protected against additional tumor challenge. T cell depletion prior to tumor transfer completely abolished the protective response. By heterotypic vaccination of CD19(-/-) mice against murine CD19, survival after tumor challenge was significantly increased. To define protective epitopes within the CD19 molecule, T cells collected from mice that had survived the tumor transfer were analyzed for IFN? secretion in response to CD19-derived peptides. The majority of mice exhibited a CD4(+) T cell response to CD19 peptide 27, which was the most dominant epitope after CD19 vaccination. A peptide 27-specific CD4(+) T cell line protected CD19(-/-) mice against challenge with CD19(+) lymphoma and also cured a significant proportion of WT mice from recurrent disease in a model of minimal residual disease after chemotherapy. In conclusion, our data highlight CD19-specific CD4(+) T cells for adoptive T cell therapy of B cell lymphomas.
EVALuna2:25691

Targeting Inflammatory T Helper Cells via Retinoic Acid-Related Orphan Receptor Gamma t Is Ineffective to Prevent Allo-Response-Driven Colitis - Buchele, Vera; Abendroth, Benjamin; Buettner-Herold, Maike; Vogler, Tina; Rothamer, Johanna; Ghimire, Sakhila; Ullrich, Evelyn; Holler, Ernst; Neurath, Markus; Hildner, Kai (Frontiers in Immunology, 2018)
Intestinal graft-versus-host disease (GvHD) is a life-threatening, inflammatory donor T cell-mediated complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT). In the light of the reported efficacy of interleukin-23 (IL-23)-blockade to mitigate syngeneic intestinal inflammation in inflammatory bowel disease patients, targeting IL-23 and thereby interleukin-17a (IL-17a) producing T helper (Th17) cells as the T cell subset assumed to be mostly regulated by IL-23, has emerged as a putatively general concept to harness immune-mediated mucosal inflammation irrespective of the underlying trigger. However, the role of Th17 cells during allo-response driven colitis remains ambiguous due to a series of studies with inconclusive results. Interestingly, we recently identified granulocyte-macrophage colony-stimulating factor (GM-CSF+) T cells to be promoted by interleukin-7 (IL-7) signaling and controlled by the activating protein-1 transcription factor family member basic leucine zipper transcription factor ATF-like (BATF) as critical mediators of intestinal GvHD in mice. Given the dual role of BATF, the contribution of IL-23-mediated signaling within donor T cells and bona fide Th17 cells remains to be delineated from the regulation of GM-CSF+ T cells in the absence of BATF. Here, we found in a complete MHC class I-mismatched model that genetic inactivation of the IL-23 receptor (IL-23R) or the transcription factor retinoic acid-related orphan receptor gamma t (RORγt) within donor T cells similarly ablated Th17 cell formation in vivo but preserved the T cells' ability to induce intestinal GvHD in a compared to wild-type controls indistinguishable manner. Importantly, RORγt-independent manifestation of intestinal GvHD was completely dependent on BATF-regulated GM-CSF+ T cells as BATF/RORγt double-deficient T cells failed to induce colitis and the antibody-mediated blockage of IL-7/IL-7R interaction and GM-CSF significantly diminished signs of intestinal GvHD elicited by RORγt-deficient donor T cells. Finally, in analogy to our murine studies, colonic RORC expression levels inversely correlated with the presence of GvHD in allo-HSCT patients. Together, this study provides a crucial example of a BATF-dependent, however, IL-23R signaling- and RORγt-, i.e., Th17 fate-independent regulation of a colitogenic T cell population critically impacting the current understanding of intestinal GvHD.
EVALuna2:34273

Targeting metabolism effectively complements tyrosine kinase inhibitor treatment of chronic myeloid leukemia - Häselbarth, Lukas; Saul, Domenica; Krumbholz, Manuela; Mougiakaos, D.; Metzler, Markus; Karow, A. (KLINISCHE PADIATRIE, 2022)
CRIS-Team WoS Importer:2022-07-08

Targeting of canonical WNT signaling ameliorates experimental sclerodermatous chronic graft-versus-host disease - Zhang, Yun; Shen, Lichong; Dreißigacker, Katja; Zhu, Honglin; Trinh, Minh Thuong; Meng, Xianyi; TRAN MANH, CUONG; Dees, Clara; Matei, Alexandru-Emil; Chen, Chih Wei; Ditschkowski, Markus; Krauss, Stefan; et al. (Blood, 2021)
Chronic graft-versus-host disease (cGVHD) is a major life-threatening complication of allogeneic hematopoietic stem cell transplantation. The molecular mechanisms underlying cGVHD remain poorly understood, and targeted therapies for clinical use are not well established. Here, we examined the role of the canonical WNT pathway in sclerodermatous cGVHD (sclGVHD). WNT signaling was activated in human sclGVHD with increased nuclear accumulation of the transcription factor β-catenin and a WNT-biased gene expression signature in lesional skin. Treatment with the highly selective tankryase inhibitor G007-LK, the CK1α agonist pyrvinium, or the LRP6 inhibitor salinomycin abrogated the activation of WNT signaling and protected against experimental cGVHD, without a significant impact on graft-versus-leukemia effect (GVL). Treatment with G007-LK, pyrvinium, or salinomycin almost completely prevented the development of clinical and histological features in the B10.D2 (H-2d) → BALB/c (H-2d) and LP/J (H-2b) → C57BL/6 (H-2b) models of sclGVHD. Inhibition of canonical WNT signaling reduced the release of extracellular matrix from fibroblasts and reduced leukocyte influx, suggesting that WNT signaling stimulates fibrotic tissue remodeling by direct effects on fibroblasts and by indirect inflammation-dependent effects in sclGVHD. Our findings may have direct translational potential, because pyrvinium is in clinical use, and tankyrase inhibitors are in clinical trials for other indications.
CRIS-Team Scopus Importer:2021-05-28

T-Cell Metabolism in Graft Versus Host Disease - Karl, Franziska; Hudecek, Michael; Berberich-Siebelt, Friederike; Mackensen, Andreas; Mougiakakos, Dimitrios (Frontiers in Immunology, 2021)
Allogeneic-hematopoietic stem cell transplantation (allo-HSCT) represents the only curative treatment option for numerous hematological malignancies. Elimination of malignant cells depends on the T-cells' Graft-versus-Tumor (GvT) effect. However, Graft-versus-Host-Disease (GvHD), often co-occurring with GvT, remains an obstacle for therapeutic efficacy. Hence, approaches, which selectively alleviate GvHD without compromising GvT activity, are needed. As already explored for autoimmune and inflammatory disorders, immuno-metabolic interventions pose a promising option to address this unmet challenge. Being embedded in a complex regulatory framework, immunological and metabolic pathways are closely intertwined, which is demonstrated by metabolic reprograming of T-cells upon activation or differentiation. In this review, current knowledge on the immuno-metabolic signature of GvHD-driving T-cells is summarized and approaches to metabolically interfere are outlined. Furthermore, we address the metabolic impact of standard medications for GvHD treatment and prophylaxis, which, in conjunction with the immuno-metabolic profile of alloreactive T-cells, could allow more targeted interventions in the future.
CRIS-Team WoS Importer:2021-11-26

Telemedicine: Comprehensive coverage and quality - Not a contradiction : Practical experience from the stroke network with telemedicine in northern Bavaria (STENO) - Breuer, Lorenz; Erbguth, F.; Oschmann, P.; Schwab, Sibylle (Der Nervenarzt, 2017)
Telemedicine is widely used in the field of stroke treatment. Following the pioneering and implementation phase, the quality of the whole stroke treatment process needs to be ensured in telemedically connected hospitals. This is particular important for telestroke hospitals without neurological expertise and can be achieved by integrating telemedicine into the stroke unit concept and stroke networks. The Stroke Network with Telemedicine in Northern Bavaria (STENO) provides an example of how quality management can be practically implemented. The implementation of STENO has established a network-wide quality management system which has been certified according to DIN EN ISO 9001:2008 since 2011.
EVALuna2:22530

Telemedicine in General Neurology: Interrater Reliability of Clinical Neurological Examination Via Audio-Visual Telemedicine - Awadallah, Mohamed; Janssen, Frank; Koerber, Barbara; Breuer, Lorenz; Scibor, Mateusz; Handschu, Rene (European neurology, 2018)
Introduction: While there are several studies on reliability of telemedicine in assessing stroke scales, little is known about the validity of a general neurological examination performed via telemedicine. Therefore, we sought to test the agreement between bedside and remote examination in acute patients of the emergency room. Methods: Acute patients at the emergency room of a 450-bed academic teaching hospital were included in this study. A clinical neurological examination consisting of 22 items was performed at bedside and also remotely via an audio-visual link by a different neurologist; both were experienced clinicians at the consultant level. Kappa statistics were calculated for each item of the examination. Results: Forty three patients completed both examinations (mean age 58.3 years, 56% female). Patients were seen between 8 and 72 min after admission (mean 36.3 min). Total time for remote examination was 12.6 min (8-21 min) and 8.9 min (5-18 min) for bedside examination. K-coefficients ranged from 0.32 (muscle tone) - 0.82 (language) indicating a fair to excellent agreement in most items. Conclusions: Remote examination via an audio-visual link produces comparable results to bedside performance even in acute patients of the emergency room. Compared to the scarce data available, inter-observer agreement is about the same as that between 2 examiners at bedside. However, more studies on reliability and validity of clinical neurological examination are required. (c) 2019 S. Karger AG, Basel
CRIS-Team WoS Importer:2019-04-25

Telemedicine in stroke care - Breuer, Lorenz; Schwab, Sibylle (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2017)
Telemedicine is already widely used in many telestroke networks and ensures stroke treatment close to the patient's home in rural and medically underserved areas. This is particularly effective when telemedicine is integrated into a stroke unit concept. While telemedically based thrombolysis therapy has become routine practice for many years, practical implementation of comprehensive mechanical thrombectomy and the related processes remains challenging. The main tasks for the future further include development of a structured stroke aftercare system in neurologically underserved areas and permanent assurance of high-quality stroke care in telemedically connected sites.
EVALuna2:22560

The CAR-HAMATOTOX for risk stratification of severe infections and for the adjustment of antibacterial prophylaxis prior to CD19-targeted CAR T-cell therapy - Rejeski, K.; Perez, A.; Iacoboni, G.; Penack, O.; Buecklein,; Mougiakakos, Dimitrios; Blumenberg,; Hoster, E.; Bullinger, L.; Locke, F.; Von Bergwelt-Baildon, M.; Mackensen, Andreas; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

The CAR- Hematotox Identifies Patients at High Risk for Prolonged Neutropenia, Infectious Complications and Prolonged Hospitalization Following CD19-CART in R/R LBCL - Rejeski, Kai; Perez-Perez, Ariel; Iacoboni, Gloria; Penack, Olaf; Buecklein, Veit L.; Jentzsch, Liv; Mougiakakos, Dimitrios; Johnson, Grace; Arciola, Brian; Blumenberg, Viktoria; Carpio, Cecilia; Hoster, Eva; et al. (BLOOD, 2021)
CRIS-Team WoS Importer:2022-09-09

The CAR-HEMATOTOX model identifies patients with a high risk for CAR T-cell related hematotoxicity and is associated with prolonged hospitalization and poor prognosis - Rejeski, K.; Perez, A.; Sesques, P.; Berger, C.; Jentzsch, L.; Mougiakakos, Dimitrios; Froelich, L.; Ackermann, J.; Buecklein,; Blumenberg,; Schmidt, C.; Jallades, L.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

The CAR-HEMATOTOX risk-stratifies patients for severe infections and disease progression after CD19 CAR-T in R/R LBCL. - Rejeski, Kai; Perez, Ariel; Iacoboni, Gloria; Penack, Olaf; Bucklein, Veit; Jentzsch, Liv; Mougiakakos, Dimitrios; Johnson, Grace; Arciola, Brian; Carpio, Cecilia; Blumenberg, Viktoria; Hoster, Eva; et al. (Journal for ImmunoTherapy of Cancer, 2022)
BACKGROUND: CD19-directed chimeric antigen receptor T-cell therapy (CAR-T) represents a promising treatment modality for an increasing number of B-cell malignancies. However, prolonged cytopenias and infections substantially contribute to the toxicity burden of CAR-T. The recently developed CAR-HEMATOTOX (HT) score-composed of five pre-lymphodepletion variables (eg, absolute neutrophil count, platelet count, hemoglobin, C-reactive protein, ferritin)-enables risk stratification of hematological toxicity. METHODS: In this multicenter retrospective analysis, we characterized early infection events (days 0-90) and clinical outcomes in 248 patients receiving standard-of-care CD19 CAR-T for relapsed/refractory large B-cell lymphoma. This included a derivation cohort (cohort A, 179 patients) and a second independent validation cohort (cohort B, 69 patients). Cumulative incidence curves were calculated for all-grade, grade ≥3, and specific infection subtypes. Clinical outcomes were studied via Kaplan-Meier estimates. RESULTS: In a multivariate analysis adjusted for other baseline features, the HT score identified patients at high risk for severe infections (adjusted HR 6.4, 95% CI 3.1 to 13.1). HThigh patients more frequently developed severe infections (40% vs 8%, p<0.0001)-particularly severe bacterial infections (27% vs 0.9%, p<0.0001). Additionally, multivariate analysis of post-CAR-T factors revealed that infection risk was increased by prolonged neutropenia (≥14 days) and corticosteroid use (≥9 days), and decreased with fluoroquinolone prophylaxis. Antibacterial prophylaxis significantly reduced the likelihood of severe bacterial infections in HThigh (16% vs 46%, p<0.001), but not HTlow patients (0% vs 2%, p=n.s.). Collectively, HThigh patients experienced worse median progression-free (3.4 vs 12.6 months) and overall survival (9.1 months vs not-reached), and were hospitalized longer (median 20 vs 16 days). Severe infections represented the most common cause of non-relapse mortality after CAR-T and were associated with poor survival outcomes. A trend toward increased non-relapse mortality in HThigh patients was observed (8.0% vs 3.7%, p=0.09). CONCLUSIONS: These data demonstrate the utility of the HT score to risk-stratify patients for infectious complications and poor survival outcomes prior to CD19 CAR-T. High-risk patients likely benefit from anti-infective prophylaxis and should be closely monitored for potential infections and relapse.
EVALuna2:503898

The cathelicidins LL-37 and rCRAMP are associated with pathogenic events of arthritis in humans and rats. - Hoffmann, Markus H.; Bruns, Heiko; Baeckdahl, Liselotte; Neregard, Petra; Niederreiter, Birgit; Herrmann, Martin; Catrina, Anca Irinel; Agerberth, Birgitta; Holmdahl, Rikard (Annals of the Rheumatic Diseases, 2013)
In rheumatoid arthritis (RA), neutrophil granulocytes fuel inflammation and damage tissue in the joint by releasing cytotoxic agents, antimicrobial peptides, proteases and other inflammatory mediators. The human cathelicidin LL-37 has recently been implicated in the development of systemic lupus erythematosus and psoriasis. To elucidate if antimicrobial peptides (AMPs) contribute to the pathogenesis of arthritis. Expression of LL-37 was determined in synovial membranes from patients with arthritis and control subjects. Expression of the rat cathelicidin rCRAMP and defensins was characterised in joints, blood and secondary lymphoid organs during pristane-induced arthritis (PIA) in rats and in a transfer model of PIA induced by CD4 T cells. Serum samples of rats with arthritis were tested for IgG and IgM autoantibodies against rCRAMP by immunoblot and for interferon (IFNα) by ELISA. Cathelicidins are strongly upregulated in RA synovial membranes and in joints from rats with arthritis as compared with healthy joints. Expression was most prominent in neutrophil granulocytes and macrophages/osteoclasts. Cathelicidin expression is also upregulated in the blood and spleen of pristane-injected rats, with strongest expression detected in activated CD62L- cells coexpressing granulocyte and monocyte markers. Pristane injection caused accumulation of low-density granulocytes in the blood. After pristane injection, the increased expression of rCRAMP coincided with higher levels of cell death, raised levels of interferon (IFN)α and development of autoantibodies. Our results show strong upregulation of cathelicidins and β-defensins coinciding with pathological events of arthritis. Higher expression and release of AMPs might contribute to development and/or maintenance of disease by systemic or local mechanisms. BACKGROUND OBJECTIVE METHODS RESULTS CONCLUSIONS

The clinical significance of anaemia and disturbed iron homeostasis in chronic respiratory failure - Schneckenpointner, R.; Joerres, R. A.; Meidenbauer, N.; Kollert, F.; Pfeifer, M.; Budweiser, S. (International Journal of Clinical Practice, 2014)
Anaemia is a frequent, clinically relevant condition in various chronic diseases. It seems also to be prevalent in patients with chronic respiratory failure (CRF). We studied the characteristics of anaemia in CRF and its associations with clinical outcome.In a prospective design, 271 consecutive patients with CRF were evaluated; patients with other conditions often associated with anaemia were excluded. Haematological laboratory and physiological parameters, health-related quality of life (HRQL), dyspnoea and 48-month survival were determined. Anaemia was defined according to WHO [haemoglobin (Hb)< 13 g/l (male); Hb< 12 g/dl (female)] and using an established algorithm.Among 185 patients included, 18.4% showed anaemia, not depending on chronic obstructive pulmonary disease (COPD) vs. non-COPD (17.6% vs. 19.0%; p = 0.851) or on gender [16.5% (female) vs. 19.8% (male); p = 0.702]. Anaemic patients had higher age, creatinine (p < 0.05 each) and erythropoietin levels (p < 0.001), but lower transferrin saturation (TSAT), serum iron and vitamin B12 levels (p < 0.01 each). By definition, most anaemic patients (67.6%) had disturbances in iron homeostasis according to 'anaemia of chronic disease' and/or true iron deficiency anaemia. Hb was independently related to dyspnoea and HRQL, while TSAT >= 20% was linked to less dyspnoea and better subjective exercise capability. Non-survivors had lower Hb and serum iron levels (p < 0.05 each). In multivariate analysis, lower serum iron levels and TSAT were independently associated with mortality (p < 0.05 each).Anaemia was common in patients with CRF and often because of disturbed iron homeostasis. Hb and TSAT were linked to functional outcome and HRQL. Lower serum iron levels and TSAT were independent prognostic parameters.
EVALuna2:25664

The complement system drives local inflammatory tissue priming by metabolic reprogramming of synovial fibroblasts - Friščić, Jasna; Böttcher, Martin; Reinwald, Christiane; Bruns, Heiko; Wirth, Benjamin; Popp, Sebastian; Walker, Kellie Irene; Ackermann, Jochen A.; Chen, Xi; Turner, Jason; Zhu, Honglin; Seyler, Lisa; et al. (Immunity, 2021)
Arthritis typically involves recurrence and progressive worsening at specific predilection sites, but the checkpoints between remission and persistence remain unknown. Here, we defined the molecular and cellular mechanisms of this inflammation-mediated tissue priming. Re-exposure to inflammatory stimuli caused aggravated arthritis in rodent models. Tissue priming developed locally and independently of adaptive immunity. Repeatedly stimulated primed synovial fibroblasts (SFs) exhibited enhanced metabolic activity inducing functional changes with intensified migration, invasiveness and osteoclastogenesis. Meanwhile, human SF from patients with established arthritis displayed a similar primed phenotype. Transcriptomic and epigenomic analyses as well as genetic and pharmacological targeting demonstrated that inflammatory tissue priming relies on intracellular complement C3- and C3a receptor-activation and downstream mammalian target of rapamycin- and hypoxia-inducible factor 1α-mediated metabolic SF invigoration that prevents activation-induced senescence, enhances NLRP3 inflammasome activity, and in consequence sensitizes tissue for inflammation. Our study suggests possibilities for therapeutic intervention abrogating tissue priming without immunosuppression.
CRIS-Team Scopus Importer:2021-04-19
Keywords: arthritis; cell metabolism; cellular senescence; complement system; inflammasome; inflammation; mechanistic target of rapamycin; synovial fibroblasts; tissue priming; trained immunity

The dual role of NK cells in antitumor reactions triggered by ionizing radiation in combination with hyperthermia - Finkel, Patrick; Frey, Benjamin; Mayer, Friederike; Bösl, Karina; Werthmöller, Nina; Mackensen, Andreas; Gaipl, Udo; Ullrich, Evelyn (OncoImmunology, 2016)
Classical tumor therapy consists of surgery, radio(RT)- and/or chemotherapy. Additive immunotherapy has gained in impact and antitumor in situ immunization strategies are promising to strengthen innate and adaptive immune responses. Immunological effects of RT and especially in combination with immune stimulation are mostly described for melanoma. Since hyperthermia (HT) in multimodal settings is capable of rendering tumor cells immunogenic, we analyzed the in vivo immunogenic potential of RT plus HT-treated B16 melanoma cells with an immunization and therapeutic assay. We focused on the role of natural killer (NK) cells in the triggered antitumor reactions. In vitro experiments showed that RT plus HT-treated B16 melanoma cells died via apoptosis and necrosis and released especially the danger signal HMGB1. The in vivo analyses revealed that melanoma cells are rendered immunogenic by RT plus HT. Especially, the repetitive immunization with treated melanoma cells led to an increase in NK cell number in draining lymph nodes, particularly of the immune regulatory CD27(+)CD11b(-) NK cell subpopulation. While permanent NK cell depletion after immunization led to a significant acceleration of tumor outgrowth, a single NK cell depletion two days before immunization resulted in significant tumor growth retardation. The therapeutic model, a local in situ immunization closely resembling the clinical situation when solid tumors are exposed locally to RT plus HT, confirmed these effects. We conclude that a dual and time-dependent impact of NK cells on the efficacy of antitumor immune reactions induced by immunogenic tumor cells generated with RT plus HT exists.
EVALuna2:18356

The effect of erythrocyte lysing reagents on enumeration of leukocyte subpopulations compared with a no-lyse-no-wash protocol - Plank, Karin; Dorn, Carla; Krause, Stefan (International Journal of Laboratory Hematology, 2021)
Introduction: Standard protocols in flow cytometry (FCM) require lysis of erythrocytes, which may induce an unwanted loss of leukocytes as bystander effect. Methods: In the present study, we investigated the influence of 6 laboratory protocols using 4 different lysing reagents, FACS® Lysing Solution (FacsL), QUICKLYSIS® (QuickL), IOTest® 3 Lysing Solution (NH4Cl), VersaLyse® (VersaL), and VersaLyse® with added fixative (VersaFix) on the relative quantity of leukocyte subsets identified by CD3, CD4, CD8, CD19, CD14, CD16, CD56, and CD45, applying a no-lyse-no-wash (NoL) protocol as reference. In addition, we compared the efficiency of red blood cell (RBC) lysis. Results: Peripheral blood samples from 52 individuals were analyzed. NoL was suitable as reference method, but led to less clear-cut gating of lymphocyte and monocyte populations due to a wider distribution of light scatter. Best completeness of RBC lysis with remaining erythrocytes below 10% was achieved using NH4Cl and VersaL. We observed a loss of 11% of monocytes after QuickL. Lymphocyte counts were 19% lower after FacsL. Cell subsets within the lymphocyte compartment were rather similar between the different methods with the exception of lower B-cell counts (−8%) and higher NK-cell counts (+11%) after FacsL. NH4Cl and VersaL were in good accordance with the NoL method and also with the mean values of all methods. Conclusion: Our data show that the lysing reagents tested lead to specific deviations in the quantitation of leukocyte subsets and show different efficiency of erythrocyte lysis.
CRIS-Team Scopus Importer:2021-02-26
Keywords: flow cytometry; leukocyte preparation; loss of leukocytes; lymphocyte subsets; red blood cell lysis

The EMT-activator Zeb1 is a key factor for cell plasticity and promotes metastasis in pancreatic cancer - Krebs, Angela M.; Mitschke, Julia; Losada, Maria Lasierra; Schmalhofer, Otto; Boerries, Melanie; Busch, Hauke; Böttcher, Martin; Mougiakakos, Dimitrios; Reichardt, Wilfried; Bronsert, Peter; Brunton, Valerie G.; Pilarsky, Christian; et al. (Nature Cell Biology, 2017)
Metastasis is the major cause of cancer-associated death. Partial activation of the epithelial-to-mesenchymal transition program (partial EMT) was considered a major driver of tumour progression from initiation to metastasis. However, the role of EMT in promoting metastasis has recently been challenged, in particular concerning effects of the Snail and Twist EMT transcription factors (EMT-TFs) in pancreatic cancer. In contrast, we show here that in the same pancreatic cancer model, driven by Pdx1-cre-mediated activation of mutant Kras and p53 (KPC model), the EMT-TF Zeb1 is a key factor for the formation of precursor lesions, invasion and notably metastasis. Depletion of Zeb1 suppresses stemness, colonization capacity and in particular phenotypic/metabolic plasticity of tumour cells, probably causing the observed in vivo effects. Accordingly, we conclude that different EMT-TFs have complementary subfunctions in driving pancreatic tumour metastasis. Therapeutic strategies should consider these potential specificities of EMT-TFs to target these factors simultaneously.

The EMT transcription factor ZEB1 blocks osteoblastic differentiation in bone development and osteosarcoma - Ruh, Manuel; Stemmler, Marc; Frisch, Isabell; Fuchs, Kathrin; van Roey, Ruthger; Kleemann, Julia; Roas, Maike; Schuhwerk, Harald; Eccles, Rebecca; Agaimy, Abbas; Baumhoer, Daniel; Berx, Geert; et al. (Journal of Pathology, 2021)
Osteosarcoma is an often-fatal mesenchyme-derived malignancy in children and young adults. Overexpression of EMT-transcription factors (EMT-TFs) has been associated with poor clinical outcome. Here, we demonstrated that the EMT-TF ZEB1 is able to block osteoblastic differentiation in normal bone development as well as in osteosarcoma cells. Consequently, overexpression of ZEB1 in osteosarcoma characterizes poorly differentiated, highly metastatic subgroups and its depletion induces differentiation of osteosarcoma cells. Overexpression of ZEB1 in osteosarcoma is frequently associated with silencing of the imprinted DLK-DIO3 locus, which encodes for microRNAs targeting ZEB1. Epigenetic reactivation of this locus in osteosarcoma cells reduces ZEB1 expression, induces differentiation, and sensitizes to standard treatment, thus indicating therapeutic options for ZEB1-driven osteosarcomas. (c) 2021 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.
CRIS-Team WoS Importer:2021-05-14

The EMT transcription factor ZEB1 governs a fitness-promoting but vulnerable DNA replication stress response. - Schuhwerk, Harald; Kleemann, Julia; Gupta, Pooja; van Roey, Ruthger; Armstark, Isabell; Kreileder, Martina; Feldker, Nora; Ramesh, Vignesh; Hajjaj, Yussuf; Fuchs, Kathrin; Mahapatro, Mousumi; Hribersek, Mojca; et al. (Cell Reports, 2022)
The DNA damage response (DDR) and epithelial-to-mesenchymal transition (EMT) are two crucial cellular programs in cancer biology. While the DDR orchestrates cell-cycle progression, DNA repair, and cell death, EMT promotes invasiveness, cellular plasticity, and intratumor heterogeneity. Therapeutic targeting of EMT transcription factors, such as ZEB1, remains challenging, but tumor-promoting DDR alterations elicit specific vulnerabilities. Using multi-omics, inhibitors, and high-content microscopy, we discover a chemoresistant ZEB1-high-expressing sub-population (ZEB1hi) with co-rewired cell-cycle progression and proficient DDR across tumor entities. ZEB1 stimulates accelerated S-phase entry via CDK6, inflicting endogenous DNA replication stress. However, DDR buildups involving constitutive MRE11-dependent fork resection allow homeostatic cycling and enrichment of ZEB1hi cells during transforming growth factor β (TGF-β)-induced EMT and chemotherapy. Thus, ZEB1 promotes G1/S transition to launch a progressive DDR benefitting stress tolerance, which concurrently manifests a targetable vulnerability in chemoresistant ZEB1hi cells. Our study thus highlights the translationally relevant intercept of the DDR and EMT.
EVALuna2:512403

The IKZF1–IRF4/IRF5 axis controls polarization of myeloma-associated macrophages - Mougiakakos, Dimitrios; Bach, Christian; Böttcher, Martin; Beier, Fabian; Röhner, Linda; Stoll, Andrej; Rehli, Michael; Gebhard, Claudia; Lischer, Christopher; Eberhardt, Martin; Vera, Julio; Büttner-Herold, Maike; et al. (Cancer Immunology Research, 2021)
The bone marrow niche has a pivotal role in progression, survival, and drug resistance of multiple myeloma cells. Therefore, it is important to develop means for targeting the multiple myeloma bone marrow microenvironment. Myeloma-associated macrophages (MAM) in the bone marrow niche are M2 like. They provide nurturing signals to multiple myeloma cells and promote immune escape. Reprogramming M2-like macrophages toward a tumoricidal M1 phenotype represents an intriguing therapeutic strategy. This is especially interesting in view of the successful use of mAbs against multiple myeloma cells, as these therapies hold the potential to trigger macrophage-mediated phagocytosis and cytotoxicity. In this study, we observed that MAMs derived from patients treated with the immunomodulatory drug (IMiD) lenalidomide skewed phenotypically and functionally toward an M1 phenotype. Lenalidomide is known to exert its beneficial effects by modulating the CRBN-CRL4 E3 ligase to ubiquitinate and degrade the transcription factor IKAROS family zinc finger 1 (IKZF1). In M2-like MAMs, we observed enhanced IKZF1 levels that vanished through treatment with lenalidomide, yielding MAMs with a bioenergetic profile, T-cell stimulatory properties, and loss of tumor-promoting capabilities that resemble M1 cells. We also provide evidence that IMiDs interfere epigenetically, via degradation of IKZF1, with IFN regulatory factors 4 and 5, which in turn alters the balance of M1/M2 polarization. We validated our observations in vivo using the CrbnI391V mouse model that recapitulates the IMiD-triggered IKZF1 degradation. These data show a role for IKZF1 in macrophage polarization and can provide explanations for the clinical benefits observed when combining IMiDs with therapeutic antibodies. See related Spotlight on p. 254
CRIS-Team Scopus Importer:2021-03-19

The Induction of a Permissive Environment to Promote T Cell Immune Evasion in Acute Myeloid Leukemia: The Metabolic Perspective - Mougiakakos, Dimitrios (Frontiers in Oncology, 2019)
Acute myeloid leukemia (AML) is the acute leukemia with highest incidence amongst adults. Despite significant improvements in understanding the genomic landscape and the introduction of novel drugs, long-term outcome remains unsatisfactory. Recently, immunotherapeutic approaches have heralded a new era in cancer treatment. The success of allogeneic hematopoietic stem cell transplantation in AML highlights the disease's immunoresponsiveness. Several immunotherapeutic applications are currently under clinical evaluation and include immune checkpoint blockades, T cell-engaging antibodies, and genetically engineered T cells. However, immunoevasive mechanisms employed by AML blasts severely hamper our endeavors. A better understanding of the underlying mechanisms remains a prerequisite for improving treatment efficacy. One of the hallmarks of the cancer cells is metabolic reprogramming, introduced by Otto Warburg's seminal studies during the beginnings of the last century. Nowadays, it is well established that metabolic adaptation is not just an epiphenomenon during oncogenesis but rather a necessity for tumor development and progression. Furthermore, accumulating data suggest an important role of aberrant tumor cell metabolism for immune escape. AML blasts display a number of metabolic alterations that could be linked to immunoregulation, and these include competition over substrates, abundant release of bioactive metabolites, and an overall microenvironmental metabolic re-modeling that favors the induction or survival of immunoregulatory cell subsets such as regulatory T cells. In this review, we outline the immunoevasive character of the AML blasts' bioenergetics, set it into context with oncogenic mutations, and discuss potentially suitable countermeasures and their limitations.
CRIS-Team Scopus Importer:2019-12-03
Keywords: AML—acute myeloid leukemia; immunoescape mechanisms; immunotherapy; microenvironment; tumor metabolism

The International Endometriosis Evaluation Program (IEEP Study) - A Systematic Study for Physicians, Researchers and Patients - Burghaus, Stefanie; Fehm, T.; Fasching, Peter; Blum, Simon; Renner, Stefan; Baier, F.; Brodkorb, T.; Fahlbusch, C.; Findeklee, S.; Häberle, Lothar; Heusinger, K.; Hildebrandt, T.; et al. (Geburtshilfe und Frauenheilkunde, 2016)
INTRODUCTION: Endometriosis is a heterogeneous disease characterized by a range of different presentations. It is usually diagnosed when patients present with pain and/or infertility, but it has also been diagnosed in asymptomatic patients. Because of the different diagnostic approaches and diverse therapies, time to diagnosis can vary considerably and the definitive diagnosis may be delayed, with some cases not being diagnosed for several years. Endometriosis patients have many unmet needs. A systematic registration and follow-up of endometriosis patients could be useful to obtain an insight into the course of the disease. The validation of biomarkers could contribute to the development of diagnostic and predictive tests which could help select patients for surgical assessment earlier and offer better predictions about patients who might benefit from medical, surgical or other interventions. The aim is also to obtain a better understanding of the etiology, pathogenesis and progression of the disease. MATERIAL AND METHODS: To do this, an online multicenter documentation system was introduced to facilitate the establishment of a prospective multicenter case-control study, the IEEP (International Endometriosis Evaluation Program) study. We report here on the first 696 patients with endometriosis included in the program between June 2013 and June 2015. RESULTS: A documentation system was created, and the structure and course of the study were mapped out with regard to data collection and the collection of biomaterials. CONCLUSION: The documentation system permits the history and clinical data of patients with endometriosis to be recorded. The IEEP combines this information with biomaterials and uses it for scientific studies. The recorded data can also be used to evaluate clinical quality control measures such as the certification parameters used by the EEL (European Endometriosis League) to assess certified endometriosis centers.
EVALuna2:32966

The MAGIC algorithm probability is a validated response biomarker of treatment of acute graft-versus-host disease - Srinagesh, Hrishikesh K.; Özbek, Umut; Kapoor, Urvi; Ayuk, Francis; Aziz, Mina; Ben-David, Kaitlyn; Choe, Hannah K.; DeFilipp, Zachariah; Etra, Aaron; Grupp, Stephan A.; Hartwell, Matthew J.; Hexner, Elizabeth O.; et al. (Blood Advances, 2019)
The Mount Sinai Acute GVHD International Consortium (MAGIC) algorithm probability (MAP), derived from 2 serum biomarkers, measures damage to crypts in the gastrointestinal tract during graft-versus-host disease (GVHD). We hypothesized that changes in MAP after treatment could validate it as a response biomarker. We prospectively collected serum samples and clinical stages of acute GVHD from 615 patients receiving hematopoietic cell transplantation in 20 centers at initiation of first-line systemic treatment and 4 weeks later. We computed MAPs and clinical responses and compared their abilities to predict 6-month nonrelapse mortality (NRM) in the validation cohort (n = 367). After 4 weeks of treatment, MAPs predicted NRM better than the change in clinical symptoms in all patients and identified 2 groups with significantly different NRM in both clinical responders (40% vs 12%, P < .0001) and nonresponders (65% vs 25%, P < .0001). MAPs successfully reclassified patients for NRM risk within every clinical grade of acute GVHD after 4 weeks of treatment. At the beginning of treatment, patients with a low MAP that rose above the threshold of 0.290 after 4 weeks of treatment had a significant increase in NRM, whereas patients with a high MAP at onset that fell below that threshold after treatment had a striking decrease in NRM that translated into clear differences in overall survival. We conclude that a MAP measured before and after treatment of acute GVHD is a response biomarker that predicts long-term outcomes more accurately than change in clinical symptoms. MAPs have the potential to guide therapy for acute GVHD and may function as a useful end point in clinical trials.
CRIS-Team Scopus Importer:2019-12-24

The MAGIC Algorithm Probability (MAP): A Novel Laboratory Biomarker for the Response to Treatment of Acute Graft-Versus-Host Disease - Srinagesh, Hrishikesh; Ozbek, Umut; Kapoor, Urvi; Ayuk, Francis Ayuketang; Aziz, Mina D.; Ben-David, Kaitlyn; Choe, Hannah K.; Defilipp, Zachariah; Etra, Aaron; Grupp, Stephan; Hartwell, Matthew; Hexner, Elizabeth O.; et al. (BLOOD, 2019)
CRIS-Team WoS Importer:2021-10-18

The MAGIC Algorithm Probability (MAP) Is a Validated Response Biomarker of Treatment for Acute Graft-Versus-Host Disease - Srinagesh, Hrishikesh K.; Ozbek, Umut; Kapoor, Urvi; Ayuk, Francis; Aziz, Mina; Ben-David, Kaitlyn; Choe, Hannah; Defilipp, Zack; Etra, Aaron; Grupp, Stephan A.; Hartwell, Matthew J.; Hexner, Elizabeth; et al. (BIOLOGY OF BLOOD AND MARROW TRANSPLANTATION, 2020)
CRIS-Team WoS Importer:2020-03-20

The Magic Biomarker Algorithm Predicts Outcomes for Children with Acute Graft Versus Host Disease - Qayed, Muna; Kapoor, Urvi; Gillespie, Scott; Mccracken, Courtney; Abusin, Ghada; Aguayo-Hiraldo, Paibel; Ayuk, Francis; Aziz, Mina; Choe, Hannah; Grupp, Stephan; Hexner, Elizabeth; Holler, Ernst; et al. (BONE MARROW TRANSPLANTATION, 2020)
CRIS-Team WoS Importer:2021-01-22

The metabolic profile of reconstituting T-cells, NK-cells, and monocytes following autologous stem cell transplantation and its impact on outcome - Richter, Silja; Böttcher, Martin; Mackensen, Andreas; Ullrich, Evelyn; Jacobs, Benedikt; Mougiakakos, Dimitrios; Völkl, Simon (Scientific Reports, 2022)
Previous studies indicated a role of the reconstituting immune system for disease outcome upon high-dose chemotherapy (HDCT) and autologous stem cell transplantation (auto-SCT) in multiple myeloma (MM) and lymphoma patients. Since immune cell metabolism and function are closely interconnected, we used flow-cytometry techniques to analyze key components and functions of the metabolic machinery in reconstituting immune cells upon HDCT/auto-SCT. We observed increased proliferative activity and an upregulation of the glycolytic and fatty acid oxidation (FAO) machinery in immune cells during engraftment. Metabolic activation was more pronounced in T-cells of advanced differentiation stages, in CD56bright NK-cells, and CD14++CD16+ intermediate monocytes. Next, we investigated a potential correlation between the immune cells’ metabolic profile and early progression or relapse in lymphoma patients within the first twelve months following auto-SCT. Here, persistently increased metabolic parameters correlated with a rather poor disease course. Taken together, reconstituting immune cells display an upregulated bioenergetic machinery following auto-SCT. Interestingly, a persistently enhanced metabolic immune cell phenotype correlated with reduced PFS. However, it remains to be elucidated, if the clinical data can be confirmed within a larger set of patients and if residual malignant cells not detected by conventional means possibly caused the metabolic activation.
CRIS-Team Scopus Importer:2022-07-15

The Oncometabolite 5′-Deoxy-5′-Methylthioadenosine Blocks Multiple Signaling Pathways of NK Cell Activation - Jacobs, Benedikt; Schlögl, Sebastian; Strobl, Carolin; Stoll, Andrej; Mougiakakos, Dimitrios; Malmberg, Karl Johan; Mackensen, Andreas; Aigner, Michael; Völkl, Simon (Frontiers in Immunology, 2020)
Tumor cells develop various mechanisms to escape immune surveillance. In this context, oncometabolites secreted by tumor cells due to deregulated metabolic pathways, have been in the spotlight of researchers during the last years. 5′-Deoxy-5′-methylthioadenosine (MTA) phosphorylase (MTAP) deficiency in tumors results in the accumulation of MTA within the tumor microenvironment and thereby negatively influencing immune functions of various immune cells, including T and NK cells. The influence of MTA on T cell activation has been recently described in more detail, while its impact on NK cells is still largely unknown. Therefore, we aimed to illuminate the molecular mechanism of MTA-induced NK cell dysfunction. NK cell cytotoxicity against target cells was reduced in the presence of MTA in a dose-dependent manner, while NK cell viability remained unaffected. Furthermore, we revealed that MTA blocks NK cell degranulation and cytokine production upon target cell engagement as well as upon antibody stimulation. Interestingly, the immune-suppressive effect of MTA was less pronounced in healthy donors harboring an expansion of NKG2C+ NK cells. Finally, we demonstrated that MTA interferes with various signaling pathways downstream of the CD16 receptor upon NK cell activation, including the PI3K/AKT/S6, MAPK/ERK, and NF-κB pathways. In summary, we revealed that MTA blocks NK cell functions like cytotoxicity and cytokine production by interfering with the signaling cascade of activating NK cell receptors. Specific targeting of MTA metabolism in MTAP-deficient tumors therefore could offer a promising new strategy to reverse immune dysfunction of NK cells within the tumor microenvironment.
CRIS-Team Scopus Importer:2020-10-30
Keywords: 5′-deoxy-5′-methylthioadenosine; CD16 signaling; NK cells; NKG2C; tumor escape mechanism

The oncometabolite 5 '-methylthioadenosine (MTA) blocks NK cell functions early after activation - Jacobs, Benedikt; Schlögl, Sebastian; Mougiakakos, Dimitrios; Mackensen, Andreas; Aigner, M.; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

The opportunistic pathogen Aspergillus fumigatus coats its infectious propagules with antimicrobial peptides - Duemig, Michaela; Binder, Johannes; Gaculenko, Anastasia; Daul, F.; Hasenberg, M.; Gunzer, M.; Krappmann, Sven (2018)
EVALuna2:213342

The PD-1/PD-L1 axis contributes to immune metabolic dysfunctions of monocytes in chronic lymphocytic leukemia - Qorraj, M.; Bruns, Heiko; Böttcher, Martin; Weigand, L.; Saul, D.; Mackensen, Andreas; Jitschin, R.; Mougiakakos, Dimitrios (Leukemia, 2016)
Immune dysfunctions in chronic lymphocytic leukemia (CLL) contribute to tumor immune escape and attenuate immune-based therapies. Monocytes/macrophages represent key components of cancer immune surveillance and effectors for antibody-mediated antitumor effects. Monocytes display an altered subset composition in CLL. Moreover, we find a changed metabolic phenotype: glucose uptake, glucose transporters and expression of glycolytic molecules are reduced. Our data establish a link between glycolytic competence and monocyte-mediated phagocytosis of tumor cells. Furthermore, we report that CLL monocytes express Bruton's tyrosine kinase (BTK). Our observations suggest that using BTK inhibitors in CLL might further aggravate the observed immune metabolic defects in monocytes. Triggering the programmed cell death-1 (PD-1) checkpoint on monocytes hampers glycolysis, phagocytosis and BTK signaling. Conversely, disrupting PD-1/PD-L1 signaling reverses these immune metabolic dysfunctions. Taken together, our findings imply a novel metabolic interplay between CLL cells and monocytes and that blocking PD-1/PD-L1 might restore metabolic together with antitumor activity of CLL monocytes/macrophages.Leukemia advance online publication, 2 September 2016; doi:10.1038/leu.2016.21
EVALuna2:25756

The PD-1/PD-L1 axis contributes to immune metabolic dysfunctions of monocytes in chronic lymphocytic leukemia. - Qorraj, M.; Bruns, Heiko; Böttcher, Martin; Weigand, L.; Saul, D.; Mackensen, Andreas; Jitschin, R.; Mougiakakos, Dimitrios (Leukemia, 2017)
Immune dysfunctions in chronic lymphocytic leukemia (CLL) contribute to tumor immune escape and attenuate immune-based therapies. Monocytes/macrophages represent key components of cancer immune surveillance and effectors for antibody-mediated antitumor effects. Monocytes display an altered subset composition in CLL. Moreover, we find a changed metabolic phenotype: glucose uptake, glucose transporters and expression of glycolytic molecules are reduced. Our data establish a link between glycolytic competence and monocyte-mediated phagocytosis of tumor cells. Furthermore, we report that CLL monocytes express Bruton's tyrosine kinase (BTK). Our observations suggest that using BTK inhibitors in CLL might further aggravate the observed immune metabolic defects in monocytes. Triggering the programmed cell death-1 (PD-1) checkpoint on monocytes hampers glycolysis, phagocytosis and BTK signaling. Conversely, disrupting PD-1/PD-L1 signaling reverses these immune metabolic dysfunctions. Taken together, our findings imply a novel metabolic interplay between CLL cells and monocytes and that blocking PD-1/PD-L1 might restore metabolic together with antitumor activity of CLL monocytes/macrophages.

The PI3K Pathway: Background and Treatment Approaches - Lux, Michael P.; Fasching, Peter; Schrauder, Michael G.; Hein, Alexander; Jud, Sebastian; Rauh, Claudia; Beckmann, Matthias (Breast Care, 2016)
Two-thirds of all breast cancer patients with metastases have a hormone receptor (HR)-positive/human epidermal growth factor receptor 2 (HER2)-negative subtype. Endocrine therapy is the treatment of choice in these patients since in addition to its effectiveness it can also maintain the patients' quality of life over a longer term. However, 44-62% of postmenopausal patients with metastatic breast carcinoma have primary tamoxifen resistance. After 3-5 years, 30-40% of the patients receiving tamoxifen treatment develop secondary resistance. Understanding the way in which resistance develops is therefore essential for developing treatment approaches that can prevent or reverse endocrine resistance. The phosphatidylinositol 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) signaling pathway plays a central role here. As a result of the numerous interactions involved, complex issues arise that need to be taken into account in the development and use of therapeutic agents. In addition, this signaling pathway is the one that most frequently undergoes mutations in breast cancer. The prognostic and predictive significance of individual mutations has not yet been fully explained, but it might provide a basis for patient selection in clinical studies. Initial research results on the use of PI3K inhibitors suggest that this may be a highly promising therapeutic approach, with an acceptable side effect profile.
EVALuna2:33003

The prehospital intravenous access assessment: a prospective study on intravenous access failure and access delay in prehospital emergency medicine - Prottengeier, Johannes; Albermann, Matthias; Heinrich, Stefan; Birkholz, Torsten; Gall, Christine; Schmidt, Joachim (European Journal of Emergency Medicine, 2016)
Intravenous access in prehospital emergency care allows for early administration of medication and extended measures such as anaesthesia. Cannulation may, however, be difficult, and failure and resulting delay in treatment and transport may have negative effects on the patient. Therefore, our study aims to perform a concise assessment of the difficulties of prehospital venous cannulation.We analysed 23 candidate predictor variables on peripheral venous cannulations in terms of cannulation failure and exceedance of a 2 min time threshold. Multivariate logistic regression models were fitted for variables of predictive value (P<0.25) and evaluated by the area under the curve (AUC>0.6) of their respective receiver operating characteristic curve.A total of 762 intravenous cannulations were enroled. In all, 22% of punctures failed on the first attempt and 13% of punctures exceeded 2 min. Model selection yielded a three-factor model (vein visibility without tourniquet, vein palpability with tourniquet and insufficient ambient lighting) of fair accuracy for the prediction of puncture failure (AUC=0.76) and a structurally congruent model of four factors (failure model factors plus vein visibility with tourniquet) for the exceedance of the 2 min threshold (AUC=0.80).Our study offers a simple assessment to identify cases of difficult intravenous access in prehospital emergency care. Of the numerous factors subjectively perceived as possibly exerting influences on cannulation, only the universal - not exclusive to emergency care - factors of lighting, vein visibility and palpability proved to be valid predictors of cannulation failure and exceedance of a 2 min threshold.
EVALuna2:5542

The Randomized AMBORA Trial: Impact of Pharmacological/Pharmaceutical Care on Medication Safety and Patient-Reported Outcomes During Treatment With New Oral Anticancer Agents - Dürr, Pauline; Schlichtig, Katja; Kelz, Carolin; Deutsch, Birgit; Maas, Renke; Eckart, Michael J.; Wilke, Jochen; Wagner, Harald; Wolff, Kerstin; Preuß, Caroline; Brückl, Valeska; Meidenbauer, Norbert; et al. (Journal of Clinical Oncology, 2021)
PURPOSE: Oral anticancer drugs (eg, kinase inhibitors) play an important role in cancer therapy. However, considerable challenges regarding medication safety of oral anticancer drugs have been reported. Randomized, controlled, multicenter studies on the impact of intensified clinical pharmacological/pharmaceutical care on patient safety and patient treatment perception are lacking. METHODS: Patients were eligible for the randomized, multicenter AMBORA study, if they were newly started on any of the oral anticancer drugs approved in 2001 or later without restriction to certain tumor entities. Patients were randomly assigned to receive either standard of care (control group) or an additional, intensified clinical pharmacological/pharmaceutical care, which included medication management and structured patient counseling, over a period of 12 weeks (intervention group). Primary end points were the number of antitumor drug-related problems (ie, side effects and unresolved medication errors) and patient treatment satisfaction with the oral anticancer therapy after 12 weeks measured with the Treatment Satisfaction Questionnaire for Medication, category convenience. RESULTS: Two hundred two patients were included. Antitumor drug-related problems were significantly lower in the intervention compared with the control group (3.85 v 5.81 [mean], P < .001). Patient treatment satisfaction was higher in the intervention group (Treatment Satisfaction Questionnaire for Medication, convenience; 91.6 v 74.4 [mean], P < .001). The hazard ratio for the combined end point of severe side effects (Common Terminology Criteria for Adverse Events ≥ 3), treatment discontinuation, unscheduled hospital admission, and death was 0.48 (95% CI, 0.32 to 0.71, P < .001) in favor of the intervention group. CONCLUSION: Treatment with oral anticancer drugs is associated with a broad range of medication errors and side effects. An intensified clinical pharmacological/pharmaceutical care has considerable, positive effects on the number of medication errors, patient treatment perception, and severe side effects.
CRIS-Team Scopus Importer:2021-07-02

Therapy landscape in patients with metastatic HER2-positive breast cancer: Data from the PRAEGNANT real-world breast cancer registry - Lux, Michael P.; Nabieva, Naiba; Hartkopf, Andreas D.; Huober, Jens; Volz, Bernhard; Taran, Florin-Andrei; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; et al. (Cancers, 2019)
This study presents comprehensive real-world data on the use of anti-human epidermal growth factor receptor 2 (HER2) therapies in patients with HER2-positive metastatic breast cancer (MBC). Specifically, it describes therapy patterns with trastuzumab (H), pertuzumab + trastuzumab (PH), lapatinib (L), and trastuzumab emtansine (T-DM1). The PRAEGNANT study is a real-time, real-world registry for MBC patients. All therapy lines are documented. This analysis describes the utilization of anti-HER2 therapies as well as therapy sequences. Among 1936 patients in PRAEGNANT, 451 were HER2-positive (23.3%). In the analysis set (417 patients), 53% of whom were included in PRAEGNANT in the first-line setting, 241 were treated with H, 237 with PH, 85 with L, and 125 with T-DM1 during the course of their therapies. The sequence PH ! T-DM1 was administered in 51 patients. Higher Eastern Cooperative Oncology Group (ECOG) scores, negative hormone receptor status, and visceral or brain metastases were associated with more frequent use of this therapy sequence. Most patients received T-DM1 after treatment with pertuzumab. Both novel therapies (PH and T-DM1) are utilized in a high proportion of HER2-positive breast cancer patients. As most patients receive T-DM1 after PH, real-world data may help to clarify whether the efficacy of this sequence is similar to that in the approval study.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Advanced breast cancer; Antihormone therapy; Chemotherapy; Her2 c-ERBB2; Her2/neu; Lapatinib; Metastatic; Pertuzumab; T-DM1; Trastuzumab

The role of donor clonal hematopoiesis in allogeneic hematopoietic stem cell transplantation - Frick, M; Chan, W; Arends, C. M; Hablesreiter, R.; Halik, A.; Blau, O.; Heuser, M.; Michonneau, D.; Galan-Sousa, J.; Noerenberg, D.; Wais,; Stadler, M.; et al. (2018)
EVALuna2:35093

The TLR9 agonist cobitolimod induces anti-inflammatory effects and balances the Th17/T-reg cell response in ulcerative colitis - Schmitt, H.; Billmeier, Ulrike; Ulmschneider, J.; Admyre, C.; Knittel, T.; Zargari, A.; Neurath, Markus; Atreya, Raja (2018)
EVALuna2:34112

The Trojan Horse Tale Revisited: An Eye on Metastatic Spread of Carcinoma Cells - Grajewski, Rafael S.; Bosch, Jacobus J.; Bruns, Heiko; Cursiefen, Claus; Heindl, Ludwig M. (Cancer Immunology Research, 2016)
The metastatic spread of carcinoma cells is not fully understood. Here, we compare the peripheral blood mononuclear cells (PBMC) and intraocular metastatic cells in parotid gland carcinoma with the PBMCs of healthy donors by immunohistochemistry and flow cytometry. We found Ber-EP4 tumor marker-positive carcinoma cells in the aqueous humor of the patient's right eye and a CD45 and Ber-EP4-expressing PBMC population in his blood. These Ber-EP4-expressing cells exhibited a monocytic-myeloid phenotype with coexpression of CD11b, CD115, and the macrophage marker CD172a (SIRP-?). Uptake of pHrodogreen revealed their phagocytic activity. Our findings suggest that the tumor cells in the anterior chamber originally derived from cell fusions between tumor cells and myeloid cells in the peripheral blood. Thus, metastases of a solid malignancy could use monocytes-macrophages as the Trojan horse to enter the eye. Cancer Immunol Res; 4(2); 92-94. ©2015 AAC
EVALuna2:25730

The tyrosine kinase inhibitor dasatinib reduces the growth of intracellular Mycobacterium tuberculosis despite impairing T-cell function - Wehrstedt, Stephanie; Kubis, Jan; Zimmermann, Andreas; Bruns, Heiko; Mayer, Daniel; Grieshober, Mark; Stenger, Steffen (European Journal of Immunology, 2018)
Tyrosine kinases are checkpoints for multiple cellular pathways and dysregulation induces malignancies, most notably chronic myeloid leukemia (CML). Inhibition of Abl-tyrosine kinases has evolved as a new concept for the treatment of CML and other malignant diseases. Due to the multiple immune-modulatory pathways controlled by tyrosine kinases, treatment with tyrosine kinase inhibitors (TKIs) will not only affect the biology of malignant cells but also modulate physiological immune functions. To understand the effects of TKIs on host defense against intracellular bacteria, we investigated the immunological impact of the dual Abl/Src TKI dasatinib on the cellular immune response to Mycobacterium tuberculosis (Mtb). Our results demonstrate that dasatinib impaired proliferation, cytokine release (IFN-γ, TNF-α, GM-CSF), expression of granulysin and degranulation of cytotoxic effector molecules of human Mtb-specific T-lymphocytes by inhibition of lymphocyte-specific protein tyrosine kinase (Lck) phosphorylation. Despite this profound inhibition of T-cell function, dasatinib suppressed growth of virulent Mtb in human macrophages co-cultured with autologous Mtb-specific T-cells (49±15%). Functional analysis suggested that growth inhibition is due to dasatinib-triggered lysosomal acidification in Mtb-infected macrophages. These results highlight the significance of innate immune responses, i.e. acidification of lysosomes, which control the multiplication of intracellular bacteria despite the lack of efficient T-cell support.
EVALuna2:35104

The utility of biomarkers in acute GVHD prognostication - Spyrou, Nikolaos; Akahoshi, Yu; Ayuk, Francis; Holler, Ernst; Choe, Hannah; Etra, Aaron; Hogan, William J.; Rösler, Wolf; Hexner, Elizabeth; DeFilipp, Zachariah; Reshef, Ran; Chanswangphuwana, Chantiya; et al. (Blood Advances, 2023)
CRIS-Team Scopus Importer:2023-09-29

The Value of Allogeneic Hematopoietic Stem Cell Transplantation in Patients with Acute Myeloid Leukemia with and without ASXL1-, RUNX1- and TP53 Mutations - Heidrich, Katharina; Middeke, Jan Moritz; Schaefer-Eckart, Kerstin; Aulitzky, Walter E.; Einsele, Hermann; Mueller-Tidow, Carsten; Rösler, Wolf; Haenel, Mathias; Baldus, Claudia D.; Fransecky, Lars; Stoelzel, Friedrich; Roellig, Christoph; et al. (BONE MARROW TRANSPLANTATION, 2020)
CRIS-Team WoS Importer:2021-01-22

Thrombopoietin receptor agonists for acquired thrombocytopenia following anti-CD19 CAR-T-cell therapy: A case report - Jitschin, Regina; Kharboutli, Soraya; Stoll, Andrej; Büttner-Herold, Maike; Schmidt, Daniela; Rösler, Wolf; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon; Baur, Rebecca (Journal for ImmunoTherapy of Cancer, 2021)
Chimeric antigen receptor (CAR)-modified T-cells targeting CD19 represent a promising therapy for relapsed or refractory (r/r) lymphoma and leukemia. The most common adverse events are immune related and include cytokine release syndrome and neurotoxicity. However, early and late hematological toxicity has emerged as a substantial clinical hurdle leading among others to an increased risk for infections or bleeding. The underlying pathophysiology remains elusive and supportive measures comprise stem cell support or the use of growth factors. Here, we report a 66-year-old woman with r/r diffuse large B-cell lymphoma that received anti-CD19 CAR-T-cells achieving a complete metabolic remission. At month 3 after adoptive cell transfer, the patient still exhibited a grade 3 anemia and a grade 4 thrombocytopenia. The latter required regular platelet transfusions. Bone marrow smear revealed hypocellularity without dysplasia. Despite reduced megakaryopoiesis, immature platelet fraction was elevated indicating an at least partially consumptive underlying component. Based on the successful use of Romiplostim, a thrombopoietin receptor-agonist, in aplastic anemia and immune thrombocytopenia, we treated our patient accordingly. Platelet count (and hemoglobin levels) increased and the patient remains transfusion-free. Taken together, our therapeutic approach could represent a novel strategy for managing CAR-T-cell-related hematotoxicity but, self-evidently, requires further controlled clinical studies.
CRIS-Team Scopus Importer:2021-07-30
Keywords: adoptive; chimeric antigen; hematologic neoplasms; immunotherapy; receptors

TIGIT Expression on Intratumoral Lymphocytes Correlates with Improved Prognosis in Oral Squamous Cell Carcinoma. - Eichberger, Jonas; Spörl, Silvia; Spanier, Gerrit; Erber, Ramona; Taxis, Juergen; Schuderer, Johannes; Ludwig, Nils; Fiedler, Mathias; Nieberle, Felix; Ettl, Tobias; Geppert, Carol-Immanuel; Reichert, Torsten E.; et al. (Biomedicines, 2022)
(1) Background: T-cell immunoglobulin and ITIM domain (TIGIT) is a potential immunotherapeutic target in a variety of malignant entities, and antibody-based treatments are currently under investigation in clinical trials. While promising results were observed in patients with lung cancer, the role of TIGIT in oral squamous cell carcinoma (OSCC) as a biomarker as well as a therapeutic target remains elusive. Therefore, we evaluated the role of TIGIT as a prognostic factor in OSCC. (2) Methods: Here, we describe the results of a retrospective tissue microarray (TMA) OSCC cohort. Using immunohistochemistry, TIGIT expression was correlated with overall and recurrence-free survival (OAS and RFS, respectively). Additionally, in silico analysis was performed based on the TCGA Head and Neck Squamous Cell Carcinoma (HNSCC) cohort in order to correlate patients' survival with TIGIT and CD274 (encoding for PD-L1) gene expression levels. (3) Results: Database analysis revealed a beneficial outcome in OAS for tumor patients with high intraepithelial CD3-TIGIT-expression (n = 327). Hereby, OAS was 53.9 months vs. 30.1 months for patients with lower TIGIT gene expression levels (p = 0.033). In our retrospective OSCC-TMA cohort, elevated TIGIT levels on CD3+ cells correlated significantly with improved OAS (p = 0.025) as well as distant RFS (p = 0.026). (4) Conclusions: This study introduces TIGIT as a novel prognostic factor in OSCC, indicating the improved outcome of OSCC patients relative to their increased TIGIT expression. TIGIT might provide therapeutic implications for future immunotherapy in advanced-stage OSCC patients.
EVALuna2:513924

TILGen: A Program to Investigate Immune Targets in Breast Cancer Patients - First Results on the Influence of Tumor-Infiltrating Lymphocytes - Würfel, Franziska; Erber, Ramona; Hübner, Hanna; Hein, Alexander; Lux, Michael P.; Jud, Sebastian; Kremer, Anita; Kranich, Hannah; Mackensen, Andreas; Häberle, Lothar; Hack, Carolin; Rauh, Claudia; et al. (Breast Care, 2018)
Background: Despite advancements in the treatment of primary and metastatic breast cancer, many patients lack a durable response to these treatments. Patients with triplenegative breast cancer (TNBC) and human epidermal growth factor receptor 2(HER2)-positive breast cancer who do not have a pathological complete response (pCR) after neoadjuvant chemotherapy (NACT) have a very poor prognosis. Tumor-infiltrating lymphocytes (TILs) have been identified as a predictive marker for pCR after NACT in TNBC and HER2-positive breast cancer. These patient populations could also be suitable for novel treatment strategies including neoepitope-based therapies. This work analyses the effect of TILs on the pCR in neoadjuvantly treated patients in the TILGen study and presents the procedures aimed at establishing neoepitope-based therapies in this study. Methods: Neoadjuvantly treated HER2positive and TNBC patients were eligible for the presented analysis concerning the association between TILs and pCR. A total of 146 patients could be identified within the TILGen study. TILs were evaluated as percentage of stromal tumor tissue in core biopsies at primary diagnosis. The phenotype 'lymphocyte-predominant breast cancer' (LPBC) was associated with pCR by logistic regression adjusted for estrogen receptor status, progesterone receptor status, HER2 status, age at diagnosis, and grading. Results: LPBC was seen in 24 (16.4%) patients. In this patient group, 66.7% achieved a pCR, while the pCR rate was 32.8% in patients with a low TIL count. The adjusted odds ratio was 6.60 (95% confidence interval 2.02-21.56; p < 0.01). Conclusion: TILs are a strong predictor of pCR in TNBC and HER2-positive breast cancer patients. Implications for the use of this information including the effect on prognosis might help to identify patients most likely to benefit from a neoepitope-based therapy approach. (C) 2018 S. Karger GmbH, Freiburg
EVALuna2:34061

TILGen: A Program to Investigate Immune Targets in Breast Cancer Patients - First Results on the Influence of Tumor-Infiltrating Lymphocytes - Würfel, Franziska; Erber, Ramona; Hübner, Hanna; Hein, Alexander; Lux, Michael P.; Jud, Sebastian; Kremer, Anita; Kranich, Hannah; Mackensen, Andreas; Häberle, Lothar; Hack, Carolin; Rauh, Claudia; et al. (Breast Care, 2018)
Background: Despite advancements in the treatment of primary and metastatic breast cancer, many patients lack a durable response to these treatments. Patients with triple-negative breast cancer (TNBC) and human epidermal growth factor receptor 2(HER2)-positive breast cancer who do not have a pathological complete response (pCR) after neoadjuvant chemotherapy (NACT) have a very poor prognosis. Tumor-infiltrating lymphocytes (TILs) have been identified as a predictive marker for pCR after NACT in TNBC and HER2-positive breast cancer. These patient populations could also be suitable for novel treatment strategies including neoepitope-based therapies. This work analyses the effect of TILs on the pCR in neoadjuvantly treated patients in the TILGen study and presents the procedures aimed at establishing neoepitope-based therapies in this study. Methods: Neoadjuvantly treated HER2-positive and TNBC patients were eligible for the presented analysis concerning the association between TILs and pCR. A total of 146 patients could be identified within the TILGen study. TILs were evaluated as percentage of stromal tumor tissue in core biopsies at primary diagnosis. The phenotype ‘lymphocyte-predominant breast cancer' (LPBC) was associated with pCR by logistic regression adjusted for estrogen receptor status, progesterone receptor status, HER2 status, age at diagnosis, and grading. Results: LPBC was seen in 24 (16.4%) patients. In this patient group, 66.7% achieved a pCR, while the pCR rate was 32.8% in patients with a low TIL count. The adjusted odds ratio was 6.60 (95% confidence interval 2.02-21.56; p < 0.01). Conclusion: TILs are a strong predictor of pCR in TNBC and HER2-positive breast cancer patients. Implications for the use of this information including the effect on prognosis might help to identify patients most likely to benefit from a neoepitope-based therapy approach.<br

TILGen study-immunological targets in patients with breast cancer : Influence of tumor-infiltrating lymphocytes - Erber, Ramona; Hartmann, Arndt; Beckmann, Matthias; Mackensen, Andreas; Kremer, Anita; Reimann, Hannah; Hübner, Hanna; Hein, Alexander; Lux, Michael P.; Jud, Sebastian; Häberle, Lothar; Gaß, Paul; et al. (Pathologe, 2018)
BACKGROUND: The interaction of our immune system with breast cancer (BC) cells prompted the investigation of tumor-infiltrating lymphocytes (TILs) and targeted, tumor antigen-specific immunotherapy. OBJECTIVES: Correlation between TILs and pathological complete response (pCR) after neoadjuvant systemic therapy (NACT). Tumor-specific antigens (TSAs) in HER2+ and triple negative BC and establishment of TSA-specific therapies within the interdisciplinary TILGen study. METHODS: Illustration of the TILGen study design. Assessment of TILs and correlation with pCR within this BC study. RESULTS: pCR was achieved in 38.4% (56/146) and associated with estrogen receptor/progesterone receptor negative (ER-/PR-) and HER2+ tumors. Lymphocytic predominant BC (LPBC) was found in 16.4% (24/146), particularly in ER-/PR- (ER-: 27.3% vs. ER+: 9.9%, PR-: 22.3% vs. PR+: 8.2%), large, and poorly differentiated BC. TILs were significantly correlated with pCR in multivariate analysis. In LPBC, pCR was achieved in 66.7%, whereas it was 32.8% in non-LPBC. CONCLUSIONS: First results confirm the influence of the human immune system on the response to NACT in HER2+ and triple negative BC. TSA-specific immunotherapy might improve the outcome in BC patients but there is an urgent need for comprehensive studies to further investigate this issue.
EVALuna2:35097

Tim-3 is dispensable for allergic inflammation and respiratory tolerance in experimental asthma - Boehne, Carolin; Behrendt, Ann-Kathrin; Meyer-Bahlburg, Almut; Böttcher, Martin; Drube, Sebastian; Kamradt, Thomas; Hansen, Gesine (PLoS ONE, 2021)
T cell immunoglobulin and mucin domain-containing molecule-3 (Tim-3) has been described as a transmembrane protein, expressed on the surface of various T cells as well as different cells of innate immunity. It has since been associated with Th1 mediated autoimmune diseases and transplantation tolerance studies, thereby indicating a possible role of this receptor in counter-regulation of Th2 immune responses. In the present study we therefore directly examined the role of Tim-3 in allergic inflammation and respiratory tolerance. First, Tim-3(-/-) mice and wild type controls were immunized and challenged with the model allergen ovalbumin (OVA) to induce an asthma-like phenotype. Analysis of cell numbers and distribution in the bronchoalveolar lavage (BAL) fluid as well as lung histology in H&E stained lung sections demonstrated a comparable degree of eosinophilic inflammation in both mouse strains. Th2 cytokine production in restimulated cell culture supernatants and serum IgE and IgG levels were equally increased in both genotypes. In addition, cell proliferation and the distribution of different T cell subsets were comparable. Moreover, analysis of both mouse strains in our respiratory tolerance model, where mucosal application of the model allergen before immunization, prevents the development of an asthma-like phenotype, revealed no differences in any of the parameters mentioned above. The current study demonstrates that Tim-3 is dispensable not only for the development of allergic inflammation but also for induction of respiratory tolerance in mice in an OVA-based model.
CRIS-Team WoS Importer:2021-05-07

Time from Diagnosis to Treatment Does Not Affect Outcome in Intensively Treated Patients with Newly Diagnosed Acute Myeloid Leukemia - Röllig, Christoph; Kramer, Michael; Schliemann, Christoph; Mikesch, Jan Henrik; Steffen, Björn; Krämer, Alwin; Sauer, Tim; Hänel, Mathias; Herbst, Regina; Schäfer-Eckart, Kerstin; Noppeney, Richard; Jost, Edgar; et al. (Blood, 2019)
DISCLOSURES: Krämer: Daiichi-Sankyo: Honoraria, Membership on an entity's Board of Directors or advisory committees; Bayer: Research Funding; BMS: Research Funding; Roche: Consultancy, Honoraria, Membership on an entity's Board of Directors or advisory committees. Hänel:Roche: Honoraria; Amgen: Honoraria; Celgene: Other: advisory board; Novartis: Honoraria; Takeda: Other: advisory board. Jost:Daiichi: Honoraria; Sanofi: Honoraria; Gilead: Other: travel grants; Jazz Pharmaceuticals: Honoraria. Brümmendorf:Merck: Consultancy; Janssen: Consultancy; Novartis: Consultancy, Research Funding; Pfizer: Consultancy, Research Funding; University Hospital of the RWTH Aachen: Employment; Ariad: Consultancy. Krause:Siemens: Research Funding; Takeda: Honoraria; MSD: Honoraria; Gilead: Other: travel; Celgene Corporation: Other: Travel. Scholl:Novartis: Other: Project funding; Pfizer: Other: Advisory boards; Gilead: Other: Project funding; Daiichi Sankyo: Other: Advisory boards; AbbVie: Other: Advisory boards. Hochhaus:Pfizer: Research Funding; Novartis: Research Funding; BMS: Research Funding; Incyte: Research Funding; MSD: Research Funding. Kiani:Novartis: Honoraria, Membership on an entity's Board of Directors or advisory committees, Research Funding, Speakers Bureau. Middeke:Sanofi: Research Funding, Speakers Bureau; Roche: Speakers Bureau; AbbVie: Consultancy, Speakers Bureau; Gilead: Consultancy; Janssen: Consultancy, Speakers Bureau; MSD: Consultancy. Thiede:AgenDix GmbH: Employment, Equity Ownership; Novartis: Research Funding, Speakers Bureau; Bayer: Research Funding; Daiichi-Sankyo: Speakers Bureau. Stoelzel:JAZZ Pharmaceuticals: Consultancy; Neovii: Other: Travel funding; Shire: Consultancy, Other: Travel funding. Platzbecker:Celgene: Consultancy, Honoraria, Research Funding; Abbvie: Consultancy, Honoraria; Novartis: Consultancy, Honoraria, Research Funding.
CRIS-Team Scopus Importer:2019-11-22

TNF-Mediated Restriction of Arginase 1 Expression in Myeloid Cells Triggers Type 2 NO Synthase Activity at the Site of Infection - Schleicher, Ulrike; Paduch, Katrin; Debus, Andrea; Obermeyer, Stephanie; Koenig, Till; Kling, Jessica C.; Ribechini, Eliana; Dudziak, Diana; Mougiakakos, Dimitrios; Murray, Peter J.; Ostuni, Renato; Koerner, Heinrich; et al. (Cell Reports, 2016)
Neutralization or deletion of tumor necrosis factor (TNF) causes loss of control of intracellular pathogens in mice and humans, but the underlying mechanisms are incompletely understood. Here, we found that TNF antagonized alternative activation of macrophages and dendritic cells by IL-4. TNF inhibited IL-4-induced arginase 1 (Arg1) expression by decreasing histone acetylation, without affecting STAT6 phosphorylation and nuclear translocation. In Leishmania major-infected C57BL/6 wild-type mice, type 2 nitric oxide (NO) synthase (NOS2) was detected in inflammatory dendritic cells or macrophages, some of which co-expressed Arg1. In TNF-deficient mice, Arg1 was hyperexpressed, causing an impaired production of NO in situ. A similar phenotype was seen in L. major-infected BALB/c mice. Arg1 deletion in hematopoietic cells protected these mice from an otherwise lethal disease, although their disease-mediating T cell response (Th2, Treg) was maintained. Thus, deletion or TNF-mediated restriction of Arg1 unleashes the production of NO by NOS2, which is critical for pathogen control.
EVALuna2:7700

To NET or not to NET: current opinions and state of the science regarding the formation of neutrophil extracellular traps - Boeltz, Sebastian; Amini, Poorya; Anders, Hans-Joachim; Andrade, Felipe; Bilyy, Rostyslav; Chatfield, Simon; Cichon, Iwona; Clancy, Danielle M.; Desai, Jyaysi; Dumych, Tetiana; Dwivedi, Nishant; Gordon, Rachael Ann; et al. (Cell Death and Differentiation, 2019)
Since the discovery and definition of neutrophil extracellular traps (NETs) 14 years ago, numerous characteristics and physiological functions of NETs have been uncovered. Nowadays, the field continues to expand and novel mechanisms that orchestrate formation of NETs, their previously unknown properties, and novel implications in disease continue to emerge. The abundance of available data has also led to some confusion in the NET research community due to contradictory results and divergent scientific concepts, such as pro- and anti-inflammatory roles in pathologic conditions, demarcation from other forms of cell death, or the origin of the DNA that forms the NET scaffold. Here, we present prevailing concepts and state of the science in NET-related research and elaborate on open questions and areas of dispute.
CRIS-Team WoS Importer:2019-02-22

Topotecan plus cyclophosphamide in adults with relapsed or refractory pediatric-type sarcoma: a retrospective analysis from the German Sarcoma Medical Oncology Group (AIO) - Hartmann, Joerg Thomas; Issels, R. D.; Nicolo, K. San; Gruenwald, V.; Hertenstein, B.; Papesch, E.; Krause, Stefan; Sturm, I. (Investigational New Drugs, 2015)
To assess the efficacy and safety of topotecan and cyclophosphamide (TC) in adult patients with pediatric-type sarcoma subtypes who failed induction chemotherapy.Patients with pediatric sarcoma subtypes, refractory to or relapsed after at least one prior induction chemotherapy, inoperable, ECOG PS 0-2, with measurable, progressive disease (PD), adequate organ functions, who have been treated with TC combination were retrospectively analysed within the AIO and SAREZ/BMBF network.Thirty-nine patients, median age 28 years (18-58), 14 females, 25 males, have been identified. All patients had received induction treatment according to (inter)national study protocols. Second-line TC was applied in 33 patients (>=3rd-line in 6 patients). Twenty-three patients had refractory disease (evidence of PD during induction chemotherapy); 8 patients experienced an early relapse within 6 months as well as 8 patients after more than 24 months (late relapse). A median of 3 cycles (range, 1-6) had been applied and antitumor activity was: CR 2.6 %, PR 7.9 %, and disease stabilisation (SD) 26.3 %. PR lasted 32.8 months and median duration in patients with SD was 5 months (range, 2.0-14.7). The 3/6-months progression-free rates were 43.2 and 18.9 %.Limited activity was seen in adult pts with refractory or relapsed pediatric-type sarcomas with the regimen which has proven activity in pediatric patients. Adults with refractory small cell sarcoma appear to have a similar dismal outcome as seen in pts with common adult-type histologies; however, a subset of patients has achieved long-lasting remissions on TC resulting in long-term survival.
EVALuna2:25725

Towards in vitro DT/DNT testing: Assaying chemical susceptibility in early differentiating NT2 cells. - Menzner, Ann-Katrin; Abolpour Mofrad, Sepideh; Friedrich, Oliver; Gilbert, Daniel (Toxicology, 2015)
Human pluripotent embryonal carcinoma (NT2) cells are increasingly considered as a suitable model for in vitro toxicity testing, e.g. developmental toxicity and neurotoxicity (DT/DNT) studies, as they undergo neuronal differentiation upon stimulation with retinoic acid (RA) and permit toxicity testing at different stages of maturation. NT2 cells have recently been reported to show specific changes in dielectric resistance profiles during differentiation which can be observed as early as 24 h upon RA-stimulation. These observations suggest altered susceptibility to chemicals at an early stage of differentiation. However, chemical susceptibility of early differentiating NT cells has not yet been studied. To address this question, we have established a cell fitness screening assay based on the analysis of intracellular ATP levels and we applied the assay in a large-scale drug screening experiment in NT2 stem cells and early differentiating NT2 cells. Subsequent analysis of ranked fitness phenotypes revealed 19 chemicals with differential toxicity profile in early differentiating NT2 cells. To evaluate whether any of the identified drugs have previously been associated with DT/DNT, we conducted a literature search on the identified molecules and quantified the fraction of chemicals assigned to the FDA (Food and Drug Administration) pregnancy risk categories (PRC) N, A, B, C, D, and X in the hit list and the small molecule library. While the fractions of the categories N and B were decreased (0.81 and 0.35-fold), the classes C, D and X were increased (1.35, 1.47 and 3.27-fold) in the hit list compared to the chemical library. From these data as well as from the literature review, identifying large fractions of chemicals being directly (42%) and indirectly associated with DT/DNT (32%), we conclude that our method may be beneficial to systematic in vitro-based primary screening for developmental toxicants and neurotoxicants and we propose cell fitness screening in early differentiating NT2 cells as a strategy for evaluating chemical susceptibility at different stages of differentiation to reduce animal testing in the context of the 3Rs.
Keywords: Developmental toxicity and neurotoxicity testing; Chemical susceptibility; Cell viability screening; Human pluripotent embryonal carcinoma cells Differentiation

TP53 mutation in patients with high-risk acute myeloid leukaemia treated with allogeneic haematopoietic stem cell transplantation - Middeke, Jan M.; Herold, Sylvia; Ruecker-Braun, Elke; Berdel, Wolfgang E.; Stelljes, Matthias; Kaufmann, Martin; Schaefer-Eckart, Kerstin; Baldus, Claudia D.; Stuhlmann, Reingard; Ho, Anthony D.; Einsele, Hermann; Rösler, Wolf; et al. (British Journal of Haematology, 2016)
Treatment success in patients with acute myeloid leukaemia (AML) is heterogeneous. Cytogenetic and molecular alterations are strong prognostic factors, which have been used to individualize treatment. Here, we studied the impact of TP53 mutations on the outcome of AML patients with adverse cytogenetic risk treated with allogeneic haematopoietic stem cell transplantation (HSCT). Samples of 97 patients with AML and adverse-risk cytogenetics who had received a HSCT within three randomized trials were analysed. Complete sequencing of the TP53 coding region was performed using next generation sequencing. The median age was 51 years. Overall, TP53 mutations were found in 40 patients (41%). With a median follow up of 67 months, the three-year probabilities of overall survival (OS) and event-free survival for patients with TP53 wild type were 33% [95% confidence interval (CI), 21% to 45%] and 24% (95% CI, 13% to 35%) compared to 10% (95% CI, 0% to 19%) and 8% (95% CI, 0% to 16%) (P = 0·002 and P = 0·007) for those with mutated TP53, respectively. In multivariate analysis, the TP53-mutation status had a negative impact on OS (Hazard Ratio = 1·7; P = 0·066). Mutational analysis of TP53 might be an important additional tool to predict outcome after HSCT in patients with adverse karyotype AML.
EVALuna2:25737

Transcriptomes of MPO-Deficient Patients with Generalized Pustular Psoriasis Reveals Expansion of CD4+ Cytotoxic T Cells and an Involvement of the Complement System - Haskamp, Stefan; Frey, Benjamin; Becker, Ina; Schulz-Kuhnt, Anja; Atreya, Imke; Berking, Carola; Pauli, David; Ekici, Arif Bülent; Berges, Johannes; Mößner, Rotraut; Wilsmann-Theis, Dagmar; Sticherling, Michael; et al. (Journal of Investigative Dermatology, 2022)
Generalized pustular psoriasis is a severe psoriatic subtype characterized by epidermal neutrophil infiltration. Although variants in IL36RN and MPO have been shown to affect immune cells, a systematic analysis of neutrophils and PBMC subsets and their differential gene expression dependent on MPO genotypes was not performed yet. We assessed the transcriptomes of MPO-deficient patients using single-cell RNA sequencing of PBMCs and RNA sequencing of neutrophils in a stable disease state. Cell-type annotation by multimodal reference mapping of single-cell RNA-sequencing data was verified by flow cytometry of surface and intracellular markers; the proportions of CD4+ cytotoxic T lymphocytes and other CD4+ effector cells were increased in generalized pustular psoriasis, whereas the frequencies of naïve CD4+ T cells were significantly lower. The expression of FGFBP2 marking CD4+ cytotoxic T lymphocytes and CD8+ effector memory T cells was elevated in patients with generalized pustular psoriasis with disease-contributing variants compared with that in noncarriers (P = 0.0015). In neutrophils, differentially expressed genes were significantly enriched in genes of the classical complement activation pathway. Future studies assessing affected cell types and pathways will show their contribution to generalized pustular psoriasis's pathogenesis and indicate whether findings can be transferred to the acute epidermal situation and whether depletion or inactivation of CD4+ cytotoxic T lymphocytes may be a reasonable therapeutic approach.
CRIS-Team Scopus Importer:2022-07-08

Treatment and Disease Characteristics of Chronic Myeloid Leukemia in Blast Crisis: The European Leukemianet Blast Crisis Registry - Brioli, Annamaria; Lomaia, Elza; Fabisch, Christian; Sacha, Tomasz; Klamova, Hana; Morozova, Elena; Golos, Aleksandra; Ernst, Philipp; Olsson-Stromberg, Ulla; Mayer, Jiri; Nicolini, Franck E.; Bao, Han; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Treatment of a patient with severe systemic sclerosis (SSc) using CD19-targeted CAR T cells. - Bergmann, Christina; Müller, Fabian; Distler, Jörg; Györfi, Andrea Hermina; Völkl, Simon; Aigner, Michael; Kretschmann, Sascha; Reimann, Hannah; Harrer, Thomas; Bayerl, Nadine; Böltz, Sebastian; Wirsching, Andreas; et al. (Annals of the Rheumatic Diseases, 2023)
EVALuna2:537682

Treatment Sequencing and Outcome of Chronic Lymphocytic Leukemia Patients Treated at Fondazione Policlinico Universitario Agostino Gemelli IRCCS: A Thirty-Year Single-Center Experience - Innocenti, Idanna; Fresa, Alberto; Tomasso, Annamaria; Tarnani, Michela; De Padua, Laura; Benintende, Giulia; Pasquale, Raffaella; Galli, Eugenio; Morelli, Francesca; Giannarelli, Diana; Autore, Francesco; Laurenti, Luca (Cancers, 2023)
Background: This monocentric retrospective study describes the treatment patterns and outcomes of chronic lymphocytic leukemia (CLL) patients. Methods: Adult CLL patients treated between 1992 and 2022 were included. The time to next treatment (TTNT) was defined as the time from the treatment’s start to the start of a subsequent therapy or death. The time to next treatment failure or death (TTNTF) was defined as the time from treatment discontinuation to the discontinuation of a subsequent therapy or death. Results: Of 637 registered patients, 318 (49.9%) received treatment. We evaluated 157 cBTKi-exposed, 34 BCL2i-exposed cBTKi-naïve, and 26 double-exposed patients. The five-year TTNT values in the cBTKi-exposed patients were 80% (median NR), 40% (median 40 months), and 21% (median 24 months) months in the first line (1L), second line (2L), and beyond the second line (>2L), respectively (p < 0.0001). The five-year TTNT values in the BCL2i-exposed patients were 83% (median NR), 72% (median NR), 12% (median 28 months) in the 1L, 2L, and >2L, respectively (p = 0.185). The median TTNTF was 9 months (range 1–87) after cBTKi and 17 months (range 8–49) after both a cBTKi and BCL2i. Conclusions: This study suggests that, in CLL patients, the earlier we used targeted therapies, the better was the outcome obtained. Nonetheless, the poor outcomes in the advanced lines of therapy highlight the need for more effective treatments.
CRIS-Team Scopus Importer:2023-12-22
Keywords: chronic lymphocytic leukemia; personalized medicine; targeted therapy

Treatment strategy by radioiodine refractory differentiated thyroid cancer - Mantsopoulos, Konstantinos; Mueller, Sarina K.; Pavel, Marianne Ellen; Kuwert, Torsten; Meidenbauer, Norbert; Fietkau, Rainer; Sievert, Matti; Iro, Heinrich (Laryngo-Rhino-Otologie, 2021)
Zusammenfassung Traditionell besteht das multimodale Therapiekonzept bei den differenzierten Schilddrusenkarzinomen in der Thyreoidektomie mit Neck-Dissection (bei cN+-Halsstatus) und adjuvanten Radiojodablation mit abschlie ss ender risikoadaptierter TSH-Suppression. Das Ausma ss der Radiojodaufnahme beim metastasierten Schilddrusenkarzinom spielt eine signifikante Rolle bei der Einschatzung der Prognose. Das fehlende Jodspeicherungsvermogen einer Lasion in Zusammenschau mit dem fehlenden Abfall des Tumormarkers Thyreoglobulin sowie radiologische Zeichen einer Tumorprogression charakterisieren den Radiojod-refraktaren Patienten. Aufgrund des meistens uber einen langen Zeitraum indolenten Verlaufs erscheint in den meisten Fallen ein abwartendes Verhalten in Kombination mit lokaler Metastasenbehandlung sowie Symptomlinderung primar sinnvoll zu sein. Der Nachweis einer Veranderung der Tumordynamik ist der Zeitpunkt, um eine Systemtherapie zu evaluieren. Diese beruht auf Multi-Tyrosinkinase-Inhibitoren (Sorafenib, Lenvatinib). Diese Substanzen sind gro ss tenteils mit einem ungunstigen Nebenwirkungsprofil assoziiert (Diarrho, Hautauschlage, arterielle Hypertonie mit hypertensiver Entgleisung, lokale Wundheilungsstorungen), welches zu einer nicht vernachlassigbaren Rate einer therapieassoziierten Morbiditat sowie einer hohen Anzahl an Therapieunterbrechungen fuhrt. Daher sind im Jahr 2020 2 selektive RET-Inhibitoren (Selpercatinib, Pralsetinib) fur die differenzierten Schilddrusenkarzinome von der FDA zugelassen worden. Eine neue Perspektive fur die Zukunft waren die unterschiedlichen Redifferenzierungsstrategien, welche auf die Steigerung der Sensitivitat der Tumorzellen auf Radiojod abzielen.
CRIS-Team WoS Importer:2021-10-08

Treatment with DNases rescues hidden neutrophil elastase from aggregated NETs - Podolska, Malgorzata; Mahajan, Aparna; Hahn, Jonas; Knopf, Jasmin; Maueröder, Christian; Petru, Lenka; Ullmann, Marc; Schett, Georg; Leppkes, Moritz; Herrmann, Martin; Munoz, Luis Enrique; Schauer, Christine (Journal of Leukocyte Biology, 2019)
The release of neutrophil extracellular traps (NETs) is one of the weapons neutrophils have in their armory. NETs consist of extracellular chromatin fibers decorated with a plethora of cytoplasmic and granular proteins, such as the antimicrobial serine protease neutrophil elastase (NE). Because the first description of NETs as beneficial to the host, reports on their double-faced role in health and disease have considerably increased recently. On one hand, NETs reportedly trap and kill bacteria and also participate in the resolution of the acute inflammation associated with infection and with tissue damage. On the other hand, numerous negative aspects of NETs contribute to the etiopathogenesis of autoimmune disorders. Employing soluble and solid fluorescent substrates, we demonstrate the interaction of NE with aggregated NETs (aggNETs), the limitation of its enzymatic activity and the containment of the enzyme from surrounding tissues. These events prevent the spread of inflammation and tissue damage. The detection of DNase 1-dependent elevation of NE activity attests the continuous presence of patrolling neutrophils forming NETs and aggNETs even under conditions physiologic conditions.
CRIS-Team Scopus Importer:2019-09-17
Keywords: aggregated NETs; DNase 1; NETs; neutrophil elastase; neutrophils

Trends in the Use of Hematopoietic Stem Cell Transplantation in the Management of Relapsed/Refractory Diffuse Large B Cell Lymphoma. a Retrospective Analysis of the Lymphoma Working Party of the EBMT - Sureda, Anna; Boumendil, Ariane; Berning, Philipp; Finel, Herve; Caillot, Denis; Rösler, Wolf; Finke, Juergen; Blau, Igor Wolfgang; Leblond, Veronique; Bittenbring, Joerg; Tsoulkani, Anna; Carpenter, Ben; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-17

Triton X-114 and Amine-Based Wash Strategy Reduces Lipopolysaccharides to FDA Limit and Achieves Purer, More Potent Recombinant Immunotoxin - George, Rebekka; Gsottberger, Franziska; Ammon, Anna-Maria; Wendland, Kerstin; Mellenthin, Lisa; Mackensen, Andreas; Müller, Fabian (Bioconjugate Chemistry, 2021)
Many proteins are still routinely expressed prokaryotically in Escherichia coli, some because they are toxic to eukaryotes. Immunotoxins, which are fusion proteins of a targeting moiety and a truncated Pseudomonas exotoxin A, kill target cells by arresting protein synthesis. Thus, immunotoxins must be expressed in E. coli. Proteins expressed in E. coli are contaminated by endotoxin (also called lipopolysaccharides (LPS)). LPS binds to toll-like receptors, inducing up to life-threatening systemic inflammation in mammals. Therefore, accepted LPS limits for therapeutics as well as for substances used in immunological studies in animals are very low. Here, we report the use of Triton X-114 and polyamine-based wash strategies, which only in combination achieved LPS-contamination well below FDA limits. Resulting LPS-reduced immunotoxins were purer and up to 2.4-fold more active in vitro. Increased activity was associated with a 2.4-fold increase in affinity on cell surface expressed target antigen. The combination method maintained enzymatic function, protein stability, and in vivo efficacy and was effective for Fab as well as dsFv formats. With some modifications, the principle of this novel combination may be applied to any chromatography-based purification process.
CRIS-Team Scopus Importer:2021-05-14

Tumor-associated lymphangiogenesis in the development of conjunctival melanoma - Heindl, Ludwig M.; Hofmann-Rummelt, Carmen; Adler, Werner; Bosch, Jacobus J.; Holbach, Leonard M.; Naumann, Gottfried; Kruse, Friedrich; Cursiefen, Claus (Investigative Ophthalmology & Visual Science, 2011)
Purpose. To analyze whether tumor-associated lymphangiogenesis is concurrent with the progression of premalignant conjunctival melanocytic intraepithelial neoplasia (C-MIN) into invasive conjunctival melanoma (CM) and to study its association with prognosis. Methods. Twenty patients with CM were closely matched with 20 patients with C-MIN with atypia and 20 with C-MIN without atypia regarding tumor size, tumor location, tumor extension, and patient's age. All conjunctival specimens were analyzed for the immunohistochemical presence of proliferating lymphatic vessels, with LYVE-1 and podoplanin used as specific lymphatic endothelial markers and Ki-67 as a proliferation marker. Lymphatic vascular density was measured within the mass (intratumoral) and within an area <=500 ?m from the tumor border (peritumoral) and was correlated with recurrence, metastasis, and survival rates. Results. Intratumoral and peritumoral proliferating lymphatic vessels were detected in none of the C-MINs without atypia, in 10 of the 20 C-MINs with atypia, and in all 20 CMs. Invasive CM showed a significantly higher intra- and peritumoral density of proliferating lymphatics than did C-MIN with atypia (P <= 0.001). Patients with high intratumoral lymphatic density revealed significantly lower recurrence-free survival rates (P = 0.041) in C-MIN with atypia and significantly lower recurrence-free (P = 0.006), lymphatic-spread-free (P = 0.041), distant-metastasis-free (P = 0.029), and melanoma-specific survival rates (P = 0.029) in CM. Conclusions. Development of CM from premalignant precursors is concurrent with the outgrowth of lymphatic vessels. This active lymphangiogenesis seems to be associated with an increased risk of local recurrence in patients with C-MIN with atypia and with an increased risk of local recurrence, lymphatic spread, distant metastasis, and tumor-related death in patients with invasive CM.
EVALuna2:5320

Tumor microenvironment-dependent epigenetic imprinting in the vasculature predicts colon cancer outcome - Naschberger, Elisabeth; Fuchs, Maximilian; Dickel, Nicholas; Kunz, Meik; Popp, Bernt; Anchang, Charles Gwellem; Demmler, Richard; Lyu, Yanmin; Uebe, Steffen; Ekici, Arif Bülent; Geppert, Carol-Immanuel; Hartmann, Arndt; et al. (Cancer Communications, 2023)
CRIS-Team Scopus Importer:2023-10-27

Two cases of carfilzomib-induced thrombotic microangiopathy successfully treated with Eculizumab in multiple myeloma - Rassner, Michael; Waesch, Ralph; Schiffer, Mario; Schneider, Johanna; Mackensen, Andreas; Engelhardt, Monika; Baur, Rebecca (BMC Nephrology, 2021)
Background Treatment with proteasome inhibitors like carfilzomib in patients with multiple myeloma (MM) can induce thrombotic microangiopathy (TMA) characterized by neurological symptoms, acute kidney injury, hemolysis and thrombocytopenia. Successful treatment with the monoclonal antibody eculizumab was described for these patients, but reports of ideal management and definitive treatment protocols are lacking. Case Presentation The first case describes a 43-years-old IgG-kappa-MM patient that developed TMA during the first course of carfilzomib-lenalidomide-dexamethasone (KRd) consolidation after autologous stem cell transplantation (ASCT). In the second case, a 59-years-old IgG-kappa-MM patient showed late-onset TMA during the fourth and last cycle of elotuzumab-KRd consolidation within the DSMM XVII study of the German study group MM (DSMM; clinicalTrials.gov Identifier: NCT03948035). Concurrently, he suffered from influenza A/B infection. Both patients had a high TMA-index for a poor prognosis of TMA. Therapeutically, in both patients plasma exchange (TPE) was initiated as soon as TMA was diagnosed. In patient #1, dialysis became necessary. For both patients, only when the complement inhibitor eculizumab was administered, kidney function and blood values impressively improved. Conclusion In this small case series, two patients with MM developed TMA due to carfilzomib treatment (CFZ-TMA), the second patient as a late-onset form. Even though TMA could have been elicited by influenza in the second patient and occurred after ASCT in both patients, with cases of TMA post-transplantation in MM being described, a relation of TMA and carfilzomib treatment was most likely. In both patients, treatment with eculizumab over two months efficiently treated TMA without recurrence and with both patients remaining responsive months after TMA onset. Taken together, we describe two cases of TMA in MM patients on carfilzomib-combination treatment, showing similar courses of this severe adverse reaction, with good responses to two months of eculizumab treatment.
CRIS-Team WoS Importer:2021-02-12

Two Cases of Severe Tick-Borne Encephalitis in Rituximab-Treated Patients in Germany: Implications for Diagnosis and Prevention - Steininger, Philipp; Bobinger, Tobias; Dietrich, Wenke; Lee, De-Hyung; Knott, Michael; Bogdan, Christian; Korn, Klaus; Lang, Roland (Open Forum Infectious Diseases, 2017)
Rituximab (RTX) has become a standard therapy for certain B cell malignancies and autoimmune diseases. We report 2 RTX-treated patients who developed severe tick-borne encephalitis virus (TBEV) infection. The inability to generate new antibody responses renders RTX-treated patients susceptible to TBEV, impedes laboratory diagnosis, and necessitates preventive vaccination in endemic areas.
EVALuna2:22593

UBTF tandem duplications are rare but recurrent alterations in adult AML and associated with younger age, myelodysplasia, and inferior outcome - Georgi, Julia Annabell; Stasik, Sebastian; Eckardt, Jan Niklas; Zukunft, Sven; Hartwig, Marita; Röllig, Christoph; Middeke, Jan Moritz; Oelschlägel, Uta; Krug, Utz; Sauer, Tim; Scholl, Sebastian; Hochhaus, Andreas; et al. (Blood Cancer Journal, 2023)
Tandem-duplication mutations of the UBTF gene (UBTF-TDs) coding for the upstream binding transcription factor have recently been described in pediatric patients with acute myeloid leukemia (AML) and were found to be associated with particular genetics (trisomy 8 (+8), FLT3-internal tandem duplications (FLT3-ITD), WT1-mutations) and inferior outcome. Due to limited knowledge on UBTF-TDs in adult AML, we screened 4247 newly diagnosed adult AML and higher-risk myelodysplastic syndrome (MDS) patients using high-resolution fragment analysis. UBTF-TDs were overall rare (n = 52/4247; 1.2%), but significantly enriched in younger patients (median age 41 years) and associated with MDS-related morphology as well as significantly lower hemoglobin and platelet levels. Patients with UBTF-TDs had significantly higher rates of +8 (34% vs. 9%), WT1 (52% vs. 7%) and FLT3-ITD (50% vs. 20.8%) co-mutations, whereas UBTF-TDs were mutually exclusive with several class-defining lesions such as mutant NPM1, in-frame CEBPA bZIP mutations as well as t(8;21). Based on the high-variant allele frequency found and the fact that all relapsed patients analyzed (n = 5) retained the UBTF-TD mutation, UBTF-TDs represent early clonal events and are stable over the disease course. In univariate analysis, UBTF-TDs did not represent a significant factor for overall or relapse-free survival in the entire cohort. However, in patients under 50 years of age, who represent the majority of UBTF-mutant patients, UBTF-TDs were an independent prognostic factor for inferior event-free (EFS), relapse-free (RFS) and overall survival (OS), which was confirmed by multivariable analyses including established risk factors such as age and ELN2022 genetic risk groups (EFS [HR: 2.20; 95% CI 1.52–3.17, p < 0.001], RFS [HR: 1.59; 95% CI 1.02–2.46, p = 0.039] and OS [HR: 1.64; 95% CI 1.08–2.49, p = 0.020]). In summary, UBTF-TDs appear to represent a novel class-defining lesion not only in pediatric AML but also younger adults and are associated with myelodysplasia and inferior outcome in these patients.
CRIS-Team Scopus Importer:2023-06-09

Ultrasound-Based Attenuation Imaging for the Non-Invasive Quantification of Liver Fat-A Pilot Study on Feasibility and Inter-Observer Variability - Jesper, Daniel; Klett, Daniel; Schellhaas, Barbara; Pfeifer, Lukas; Leppkes, Moritz; Waldner, Maximilian; Neurath, Markus; Strobel, Deike (IEEE Journal of Translational Engineering in Health and Medicine, 2020)
Attenuation imaging is a novel, ultrasound-based technique to objectively detect and quantify liver steatosis. In this study, we evaluated the performance and inter-observer variability of attenuation imaging and compared it to a known quantification method of liver fat, the hepatorenal index (HRI). Two observers measured attenuation coefficients (AC) in an attenuation phantom, 20 healthy volunteers and 27 patients scheduled for biopsy for suspected diffuse liver disease. Results were compared with the HRI and histological findings. Both observers were blinded to the results of the biopsy and the measurements of the other observer. Our results showed that patients with moderate (S2, 33-66%) and severe fatty infiltration of the liver (S3, >66%) showed significantly higher ACs in comparison to patients with a liver fat fraction of less than 33% (S0/1). There was no significant difference in AC-values of patients with fatty infiltration of less than 5% (S0) and 5-32% (S1). In the Receiver Operating Characteristic (ROC)-analysis, the area under the curve (AUC)-values for the detection of moderate and severe steatosis were excellent at 0.98. Cut-off values were 0.64 dB/cm/MHz for the detection of S2- A nd 0.68 dB/cm/MHz for the detection of S3-steatosis. The inter-observer agreement of attenuation imaging was very good with an intraclass correlation coefficient (ICC) of 0.92 in patient and 0.96 in phantom measurements. The ICC decreased with depth in the phantom measurements. In summary, attenuation imaging showed very good inter-observer agreement and is a promising tool for the detection and quantification of moderate and severe hepatic steatosis.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Attenuation imaging; fatty liver; hepatic fat; hepatic steatosis; hepatorenal index; inter-observer; liver steatosis; NAFLD; NASH; ultrasound

Unclear tumour of the ear lobe - Dürr, Stephan; Söder, Stephan; Rösler, Wolf; Schlechtweg, Philipp; Schick, B; Alexiou, Christoph (Laryngo-Rhino-Otologie, 2014)
EVALuna2:6586

Upregulation of CCR4 in activated CD8(+) T cells indicates enhanced lung homing in patients with severe acute SARS-CoV-2 infection - Spoerl, Silvia; Kremer, Anita; Aigner, Michael; Eisenhauer, Nina; Koch, Pauline; Meretuk, Lina; Loeffler, Patrick; Tenbusch, Matthias; Maier, Clara; Überla, Klaus; Heinzerling, Lucie; Frey, Benjamin; et al. (European Journal of Immunology, 2021)
COVID-19 is a life-threatening disease leading to bilateral pneumonia and respiratory failure. The underlying reasons why a smaller percentage of patients present with severe pulmonary symptoms whereas the majority is only mildly affected are to date not well understood.
CRIS-Team WoS Importer:2021-05-07

Vaccination after Allogenic Stem Cell Transplantation: Diminished Memory B Cell Response and High Number of Spontaneously IgG Secreting Plasmablasts - Tittlbach, Hannes; Schneider, Andrea; Buchstaller, Corinna; Mayr, Andreas; Vasova, Ingrid; Rösler, Wolf; Mackensen, Andreas; Mach, Michael; Winkler, Thomas; Winkler, Jürgen (BLOOD, 2018)
CRIS-Team WoS Importer:2019-02-27

Vaccination With Live Attenuated Vaccines in Four Children With Chronic Myeloid Leukemia While on Imatinib Treatment - Bettoni da Cunha-Riehm, Claudia; Hildebrand, Verena; Nathrath, Michaela; Metzler, Markus; Suttorp, Meinolf (Frontiers in Immunology, 2020)
Chronic myeloid leukemia (CML) in childhood and adolescence is a rare malignancy that can successfully be treated with the tyrosine kinase inhibitor (TKI) imatinib. According to the current experience, treatment is necessary for years and, in the majority of cases, a lifelong approach is required to control the malignant disease. To what extent imatinib causes immunosuppression in different age cohorts is a controversial discussion. According to general medical recommendations, live vaccines are contraindicated in individuals treated with imatinib. However, a recent increase in the number of globally reported cases of measles has been observed and continues to rise. Due to the high contagiousness of the virus, near-perfect vaccination coverage (herd immunity of 93 to 95%) is required to effectively protect against measles resurgence—a scenario that is not realistic in many countries. When four teenagers with CML (median age 13 years, range 12–15) who were enrolled into pediatric trial CML-paed II while on imatinib treatment (median treatment duration 36 months, range 11–84) were identified without protective measles and/or varicella titers, we carefully balanced the risks of a live vaccination under immunosuppressive TKI medication against the benefit of being protected. The patients underwent live vaccination with the live attenuated vaccines M-M-RVAX Pro® and Varivax® simultaneously (Patient #1), Priorix® and Varilix® consecutively (Patient #2), and Priorix® (Patients #3 and #4). While the first three patients were vaccinated while receiving TKI therapy, treatment with imatinib was interrupted in patient #4 for 1 week prior and 2 weeks after vaccination. Patients #1 and #3 reacted with stable long-term seroconversion. In Patient #2, serum titer conversion against measles and varicella could not be demonstrated and thus revaccination with Priorix® and Varilix® was performed 3 years later. However, protective titers did not develop or were lost again. Patient #4 also lost protective titers against measles when assessed 10 months after vaccination, but revaccination resulted in stable seroprotective titers over 12 months after the last vaccination during ongoing imatinib treatment. We conclude that in all patients, the safety of live vaccines could be documented, as no acute or late adverse events were observed. However, in line with observations that memory B-cells are lost under exposure to imatinib, revaccination may become necessary (two out of four patients in this small series lost their seroprotection). Considering that the number of cases is very small, we also suggest some criteria for decision-making regarding live vaccinations of CML patients treated with imatinib.
CRIS-Team Scopus Importer:2020-05-12
Keywords: chronic myeloid leukemia; imatinib; measles; mild immunosuppression; pediatric CML; tyrosine kinase inhibitors; vaccination; varicella

Variable expression of the disialoganglioside gd2 in breast cancer molecular subtypes - Erber, Ramona; Kailayangiri, Sareetha; Hübner, Hanna; Rübner, Matthias; Hartmann, Arndt; Häberle, Lothar; Meyer, Julia; Völkl, Simon; Mackensen, Andreas; Landgraf, Laura; Geppert, Carol-Immanuel; Schulz-Wendtland, Rüdiger; et al. (Cancers, 2021)
The disialoganglioside GD2 is a tumor-associated antigen that may allow for the application of targeted immunotherapies (anti-GD2 antibodies, GD2 CAR T cells) in patients with neuroblastoma and other solid tumors. We retrospectively investigated GD2 expression in a breast cancer cohort, using immunohistochemistry (IHC) and immunofluorescence (IF) on tissue microarrays (TMAs), and its impact on survival. GD2 expression on IHC (n = 568) and IF (n = 503) was investigated in relation to subtypes and patient outcome. Overall, 50.2% of the 568 IHC-assessed samples and 69.8% of the 503 IF-assessed samples were GD2-positive. The highest proportion of GD2-positive tumors was observed in luminal tumors. Significantly fewer GD2-positive cases were detected in triple-negative breast cancer (TNBC) compared with other subtypes. The proportion of GD2-expressing tumors were significantly lower in HER2-positive breast cancer in comparison with luminal tumors on IF staining (but not IHC). GD2 expression of IHC or IF was not significantly associated with disease-free or overall survival, in either the overall cohort or in individual subtypes. However, GD2 expression can be seen in more than 50% of breast cancer cases, with the highest frequency in hormone receptorpositive tumors. With this high expression frequency, patients with GD2-positive advanced breast cancer of all subtypes may benefit from GD2-targeting immunotherapies, which are currently subject to clinical testing.
CRIS-Team Scopus Importer:2021-11-12
Keywords: Breast cancer; Disialoganglioside; GD2; Immunofluorescence; Immunohistochemistry; Prognosis

Vascular occlusion by neutrophil extracellular traps in COVID-19 - Leppkes, Moritz; Knopf, Jasmin; Naschberger, Elisabeth; Lindemann, Aylin; Singh, Jeeshan; Herrmann, Irmgard; Stürzl, Michael; Staats, Léonie; Mahajan, Aparna; Kremer, Anita; Amann, Kerstin Ute; Evert, Katja; et al. (EBioMedicine, 2020)
Background: Coronavirus induced disease 2019 (COVID-19) can be complicated by severe organ damage leading to dysfunction of the lungs and other organs. The processes that trigger organ damage in COVID-19 are incompletely understood. Methods: Samples were donated from hospitalized patients. Sera, plasma, and autopsy-derived tissue sections were examined employing flow cytometry, enzyme-linked immunosorbent assays, and immunohistochemistry. Patient findings: Here, we show that severe COVID-19 is characterized by a highly pronounced formation of neutrophil extracellular traps (NETs) inside the micro-vessels. Intravascular aggregation of NETs leads to rapid occlusion of the affected vessels, disturbed microcirculation, and organ damage. In severe COVID-19, neutrophil granulocytes are strongly activated and adopt a so-called low-density phenotype, prone to spontaneously form NETs. In accordance, markers indicating NET turnover are consistently increased in COVID-19 and linked to disease severity. Histopathology of the lungs and other organs from COVID-19 patients showed congestions of numerous micro-vessels by aggregated NETs associated with endothelial damage. Interpretation: These data suggest that organ dysfunction in severe COVID-19 is associated with excessive NET formation and vascular damage. Funding: Deutsche Forschungsgemeinschaft (DFG), EU, Volkswagen-Stiftung
CRIS-Team Scopus Importer:2020-08-14
Keywords: Aggregated neutrophil extracellular traps; Coagulopathy; Endothelialitis; Immunothrombosis; SARS-CoV-2

Velocity of early BCR-ABL transcript elimination as an optimized predictor of outcome in chronic myeloid leukemia (CML) patients in chronic phase on treatment with imatinib - Hanfstein, B.; Shlyakhto, V.; Lauseker, M.; Hehlmann, R.; Saussele, S.; Dietz, C.; Erben, P.; Fabarius, A.; Proetel, U.; Schnittger, S.; Krause, Stefan; Schubert, J.; et al. (Leukemia, 2014)
Early assessment of response at 3 months of tyrosine kinase inhibitor treatment has become an important tool to predict favorable outcome. We sought to investigate the impact of relative changes of BCR-ABL transcript levels within the initial 3 months of therapy. In order to achieve accurate data for high BCR-ABL levels at diagnosis, beta glucuronidase (GUS) was used as a reference gene. Within the German CML-Study IV, samples of 408 imatinib-treated patients were available in a single laboratory for both times, diagnosis and 3 months on treatment. In total, 301 of these were treatment-naïve at sample collection.(i) with regard to absolute transcript levels at diagnosis, no predictive cutoff could be identified; (ii) at 3 months, an individual reduction of BCR-ABL transcripts to the 0.35-fold of baseline level (0.46-log reduction, that is, roughly half-log) separated best (high risk: 16% of patients, 5-year overall survival (OS) 83% vs 98%, hazard ratio (HR) 6.3, P=0.001); (iii) at 3 months, a 6% BCR-ABL(IS) cutoff derived from BCR-ABL/GUS yielded a good and sensitive discrimination (high risk: 22% of patients, 5-year OS 85% vs 98%, HR 6.1, P=0.002). Patients at risk of disease progression can be identified precisely by the lack of a half-log reduction of BCR-ABL transcripts at 3 months.
EVALuna2:25699

Venetoclax-Based Salvage Therapy Improves Outcome in Relapsed/Refractory AML Patients Eligible for Intensive Treatment: A Propensity Score Matching Analysis - Unglaub, Julia M.; Schlenk, Richard F.; Hanoun, Maher; Reinhardt, H. Christian; Middeke, Jan Moritz; Schaefer-Eckart, Kerstin; Steffen, Bjoern; Krause, Stefan; Schliemann, Christoph; Kaufmann, Martin; Haenel, Mathias; Jost, Edgar; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Virus-specific memory T cell responses unmasked by immune checkpoint blockade cause hepatitis - Hutchinson, James A.; Kronenberg, Katharina; Riquelme, Paloma; Wenzel, Jürgen J.; Glehr, Gunther; Schilling, Hannah Lou; Zeman, Florian; Evert, Katja; Schmiedel, Martin; Mickler, Marion; Drexler, Konstantin; Bitterer, Florian; et al. (Nature Communications, 2021)
Treatment of advanced melanoma with combined PD-1/CTLA-4 blockade commonly causes serious immune-mediated complications. Here, we identify a subset of patients predisposed to immune checkpoint blockade-related hepatitis who are distinguished by chronic expansion of effector memory CD4+ T cells (TEM cells). Pre-therapy CD4+ TEM cell expansion occurs primarily during autumn or winter in patients with metastatic disease and high cytomegalovirus (CMV)-specific serum antibody titres. These clinical features implicate metastasis-dependent, compartmentalised CMV reactivation as the cause of CD4+ TEM expansion. Pre-therapy CD4+ TEM expansion predicts hepatitis in CMV-seropositive patients, opening possibilities for avoidance or prevention. 3 of 4 patients with pre-treatment CD4+ TEM expansion who received αPD-1 monotherapy instead of αPD-1/αCTLA-4 therapy remained hepatitis-free. 4 of 4 patients with baseline CD4+ TEM expansion given prophylactic valganciclovir and αPD-1/αCTLA-4 therapy remained hepatitis-free. Our findings exemplify how pathogen exposure can shape clinical reactions after cancer therapy and how this insight leads to therapeutic innovations.
CRIS-Team Scopus Importer:2021-03-26

Visualizing Single-Cell Secretion Dynamics with Single-Protein Sensitivity - McDonald, Matthew; Gemeinhardt, André; König, Katharina; Piliarik, Marek; Schaffer, Stefanie; Völkl, Simon; Aigner, Michael; Mackensen, Andreas; Sandoghdar, Vahid (Nano Letters, 2017)
Cellular secretion of proteins into the extracellular environment is an essential mediator of critical biological mechanisms, including cell-to-cell communication, immunological response, targeted delivery, and differentiation. Here, we report a novel methodology that allows for the real-time detection and imaging of single unlabeled proteins that are secreted from individual living cells. This is accomplished via interferometric detection of scattered light (iSCAT) and is demonstrated with Laz388 cells, an Epstein-Barr virus (EBV)-transformed B cell line. We find that single Laz388 cells actively secrete IgG antibodies at a rate of the order of 100 molecules per second. Intriguingly, we also find that other proteins and particles spanning ca. 100 kDa-1 MDa are secreted from the Laz388 cells in tandem with IgG antibody release, likely arising from EBV-related viral proteins. The technique is general and, as we show, can also be applied to studying the lysate of a single cell. Our results establish label-free iSCAT imaging as a powerful tool for studying the real-time exchange between cells and their immediate environment with single-protein sensitivity.
EVALuna2:25781

Vitamin D-dependent induction of cathelicidin in human macrophages results in cytotoxicity against high-grade B cell lymphoma - Bruns, Heiko; Büttner, Maike; Fabri, Mario; Mougiakakos, Dimitrios; Bittenbring, Joerg T.; Hoffmann, Markus; Beier, Fabian; Pasemann, Shirin; Jitschin, Regina; Hofmann, Andreas D.; Neumann, Frank; Daniel, Christoph; et al. (Science Translational Medicine, 2015)
Infiltration by macrophages represents a characteristic morphological hallmark in high-grade lymphatic malignancies such as Burkitt's lymphoma (BL). Although macrophages can, in principle, target neoplastic cells and mediate antibody-dependent cellular cytotoxicity (ADCC), tumor-associated macrophages (TAMs) regularly fail to exert direct cytotoxic functions. The underlying mechanisms responsible for this observation remain unclear. We demonstrate that inflammatory M1 macrophages kill proliferating high-grade B cell lymphoma cells by releasing the antimicrobial peptide cathelicidin in a vitamin D-dependent fashion. We show that cathelicidin directly induces cell death by targeting mitochondria of BL cells. In contrast, anti-inflammatory M2 macrophages and M2-like TAMs in BL exhibit an altered vitamin D metabolism, resulting in a reduced production of cathelicidin and consequently in inability to lyse BL cells. However, treatment of M2 macrophages with the bioactive form of vitamin D, 1,25D3, or a vitamin D receptor agonist effectively induces cathelicidin production and triggers tumoricidal activity against BL cells. Furthermore, rituximab-mediated cytotoxicity of vitamin D-treated M2 macrophages is cathelicidin-dependent. Finally, vitamin D treatment of 25-hydroxyvitamin D (25D)-deficient volunteers in vivo or primary TAMs in vitro improves rituximab-mediated ADCC against B cell lymphoma cells. These data indicate that activation of the vitamin D signaling pathway activates antitumor activity of TAMs and improves the efficacy of ADC
EVALuna2:13103

Voxel-wise lesion mapping of self-reported urinary incontinence in multiple sclerosis - Fröhlich, Katharina; Wang, Ruihao; Bobinger, Tobias; Schmidt, Manuel; Dörfler, Arnd; Nickel, Franziska; Hilz, Max-Josef; Lee, De-Hyung; Linker, Ralf A.; Seifert, Frank; Winder, Klemens (Neurourology and Urodynamics, 2019)
Aims Besides spinal lesions, urinary incontinence may be attributed to particular cerebral lesion sites in multiple sclerosis (MS) patients. We intended to determine the contribution of suprapontine lesions to urinary incontinence in MS using a voxel-wise lesion analysis. Methods In this retrospective study, we sought MS patients with documented urinary incontinence in a local database. We established a control group of MS-patients without documented urinary incontinence matched for gender, age, and disease severity. Patients with urinary incontinence due to local diseases of the urinary tract were excluded. The MS lesions were analyzed on T2-weighted magnetic resonance imaging scans (1.5 or 3T). After manual delineation and transformation into stereotaxic space, we determined the lesion overlap and compared the presence or absence of urinary incontinence voxel-wise between patients with and without lesions in a given voxel performing the Liebermeister test with 4000 permutations. Results A total of 56 patients with urinary incontinence and MS fulfilled the criteria and were included. The analysis yielded associations between urinary incontinence and MS in the frontal white matter, temporo-occipital, and parahippocampal regions. Conclusions Our voxel-wise analysis indicated associations between self-reported urinary incontinence and lesions in the left frontal white matter and right parahippocampal region. Thus, our data suggest that dysfunction of supraspinal bladder control due to cerebral lesions may contribute to the pathophysiology of urinary incontinence in MS.
CRIS-Team WoS Importer:2019-11-12

What opportunities does Immuno-oncology indicate for overarching long-term survival? - Bergmann, Lothar; Brugger, Wolfram; Herr, Wolfgang; Mackensen, Andreas; Multhoff, Gabriele (Oncology research and treatment, 2015)
EVALuna2:25748

Which factors determine our medical actions? Responsible medicine in the age of tight economic constraints - Combs, S. E.; Krause, Stefan; Moesta, T.; Schmidberger, H. (Die Onkologie, 2022)
CRIS-Team WoS Importer:2022-11-11

Whole-Body Electromyostimulation Combined With Individualized Nutritional Support Improves Body Composition in Patients With Hematological Malignancies - A Pilot Study - Schink, Kristin; Relijic, Dejan; Herrmann, Hans J.; Meyer, Julia; Mackensen, Andreas; Neurath, Markus; Zopf, Yurdagül (Frontiers in Physiology, 2018)
Patients undergoing the complex treatment for hematological malignancies are exposed to a high physiological and psychological distress inducing fatigue and physical inactivity. In line with cancer-related metabolic changes patients are predisposed for skeletal muscle mass loss that leads to a functional decline, affects therapeutic success, and quality of life. Benefits of physical exercise and nutritional interventions on muscle maintenance are observed in solid cancer patients, but marginally investigated in patients with hematological cancer. We here studied the effects of a combined supportive exercise and nutrition intervention using whole-body electromyostimulation (WB-EMS) training and individualized nutritional support in patients actively treated for hematological malignancy. In a controlled pilot trial, 31 patients (67.7% male; 58.0 +/- 16.7 years) with various hematological cancers were allocated to a control group (n = 9) receiving nutritional support of usual care regarding a high protein intake (> 1.0 g/kg/d) or to a physical exercise group (n = 22) additionally performing WB-EMS training twice weekly for 12 weeks. Bodyweight and body composition assessed by bioelectrical impedance analysis were measured every 4 weeks. Physical function, blood parameters, quality of life and fatigue were assessed at baseline and after 12 weeks. No WB-EMS-related adverse effects occurred. Patients attending the exercise program presented a higher skeletal muscle mass than controls after 12-weeks (1.51 kg [0.41, 2.60]; p = 0.008). In contrast, patients of the control group showed a higher fat mass percentage than patients of the WB-EMS group (-4.46% [-7.15, -1.77]; p = 0.001) that was accompanied by an increase in serum triglycerides in contrast to a decrease in the WB-EMS group (change +/- SD, control 36.3 +/- 50.6 mg/dl; WB-EMS -31.8 +/- 68.7 mg/dl; p = 0.064). No significant group differences for lower limb strength, quality of life, and fatigue were detected. However, compared to controls the WB-EMS group significantly improved in physical functioning indicated by a higher increase in the 6-min-walking distance (p = 0.046). A combined therapeutic intervention of WB-EMS and protein-rich nutritional support seems to be safe and effective in improving skeletal muscle mass and body composition in hematological cancer patients during active oncological treatment.
EVALuna2:35109

Whole-brain radiotherapy or autologous stem-cell transplantation as consolidation strategies after high-dose methotrexate-based chemoimmunotherapy in patients with primary CNS lymphoma: results of the second randomisation of the International Extranodal L - Ferreri, Andres J. M.; Cwynarski, Kate; Pulczynski, Elisa; Fox, Christopher P.; Schorb, Elisabeth; La Rosee, Paul; Binder, Mascha; Fabbri, Alberto; Torri, Valter; Minacapelli, Eleonora; Falautano, Monica; Ilariucci, Fiorella; et al. (Lancet Haematology, 2017)
The International Extranodal Lymphoma Study Group-32 (IELSG32) trial is an international randomised phase 2 study that addresses two key clinical questions in the treatment of patients with newly diagnosed primary CNS lymphoma. Results of the first randomisation have demonstrated that methotrexate, cytarabine, thiotepa, and rituximab (called the MATRix regimen) is the induction combination associated with significantly better outcome compared with the other induction combinations tested. Here, we report the results of the second randomisation that addresses the efficacy of myeloablative chemotherapy supported by autologous stem-cell transplantation (ASCT), as an alternative to whole-brain radiotherapy (WBRT), as consolidation after high-dose-methotrexate-based chemoimmunotherapy.HIV-negative patients (aged 18-70 years) with newly diagnosed primary CNS lymphoma and an Eastern Cooperative Oncology Group performance status of 0-3 were randomly assigned to receive four courses of methotrexate 3·5 g/m2 on day 1 plus cytarabine 2 g/m2 twice daily on days 2 and 3 (group A); or the same combination plus two doses of rituximab 375 mg/m2 on days -5 and 0 (group B); or the same methotrexate-cytarabine-rituximab combination plus thiotepa 30 mg/m2 on day 4 (group C), with the three groups repeating treatment every 3 weeks. Patients with responsive or stable disease after induction treatment, with adequate autologous peripheral blood stem-cell collection, and without persistent iatrogenic side-effects, were eligible for the second randomisation between WBRT (photons of 4-10 MeV; five fractions per week; fraction size 180 cGy; started within 4 weeks from the last induction course; group D) and carmustine-thiotepa conditioned ASCT (carmustine 400 mg/m2 on day -6, and thiotepa 5 mg/kg every 12 h on days -5 and -4, followed by reinfusion of autologous peripheral blood stem cells; group E). A permuted block randomised design was adopted for both randomisations, and a computer-generated randomisation list was used within each stratum. No masking after assignment to intervention was adopted. The primary endpoint was 2-year progression-free survival, with induction group and response to induction chemotherapy as stratification parameters. Analyses were done on a modified intention-to-treat basis. This study is registered with ClinicalTrials.gov, number NCT01011920.Between Feb 19, 2010, and Aug 27, 2014, 227 patients were recruited from 53 centres in five countries. 219 of 227 enrolled patients were assessable. Of the 122 patients eligible for the second randomisation, 118 patients were randomly assigned to WBRT or ASCT (59 patients per group) and constitute the study population. WBRT and ASCT were both effective, and achieved the predetermined efficacy threshold of at least 40 progression-free survivors at 2 years among the first 52 patients in both groups D and E. There were no significant differences in 2-year progression-free survival between WBRT and ASCT: 80% (95% CI 70-90) in group D and 69% (59-79) in group E (hazard ratio 1·50, 95% CI 0·83-2·71; p=0·17). Both consolidation therapies were well tolerated. Grade 4 non-haematological toxicity was uncommon; as expected, haematological toxicity was more common in patients treated with ASCT than in those who received WBRT. Two toxic deaths (infections) were recorded, both in patients who received ASCT.WBRT and ASCT are both feasible and effective as consolidation therapies after high-dose methotrexate-based chemoimmunotherapy in patients aged 70 years or younger with primary CNS lymphoma. The risks and implications of cognitive impairment after WBRT should be considered at the time of therapeutic decision.Agenzia Italiana del Farmaco, Cancer Research UK, Oncosuisse, and Swiss National Science Foundation.
EVALuna2:25776

Workshop - Ökonomische Steuerungsmechanismen: Beispiel Hämatologie und Onkologie - Strech, Daniel; Deh, Uwe; Schmitz, Stephan; Guerkan, Irmtraut; Ostermann, Helmut; Krause, Stefan (Oncology research and treatment, 2015)
EVALuna2:25747

Younger patients with chronic myeloid leukemia do well in spite of poor prognostic indicators: results from the randomized CML study IV - Kalmanti, Lida; Saussele, Susanne; Lauseker, Michael; Proetel, Ulrike; Mueller, Martin C.; Hanfstein, Benjamin; Schreiber, Annette; Fabarius, Alice; Pfirrmann, Markus; Schnittger, Susanne; Dengler, Jolanta; Falge, Christiane; et al. (Annals of Hematology, 2014)
Since the advent of tyrosine kinase inhibitors, the impact of age on outcome of chronic myeloid leukemia (CML) patients has changed. We therefore analyzed patients from the randomized CML study IV to investigate disease manifestations and outcome in different age groups. One thousand five hundred twenty-four patients with BCR-ABL-positive chronic phase CML were divided into four age groups: (1) 16-29 years, n = 120; (2) 30-44 years, n = 383; (3) 45-59 years, n = 495; and (4) >=60 years, n = 526. Group 1 (adolescents and young adults (AYAs)) presented with more aggressive disease features (larger spleen size, more frequent symptoms of organomegaly, higher white blood count, higher percentage of peripheral blasts and lower hemoglobin levels) than the other age groups. In addition, a higher rate of patients with BCR-ABL transcript levels >10 % on the international scale (IS) at 3 months was observed. After a median observation time of 67.5 months, no inferior survival and no differences in cytogenetic and molecular remissions or progression rates were observed. We conclude that AYAs show more aggressive features and poor prognostic indicators possibly indicating differences in disease biology. This, however, does not affect outcome.
EVALuna2:25675

β2-microglobulin triggers NLRP3 inflammasome activation in tumor-associated macrophages to promote multiple myeloma progression - Hofbauer, Daniel; Mougiakakos, Dimitrios; Broggini, Luca; Zaiss, Mario; Büttner-Herold, Maike; Bach, Christian; Spriewald, Bernd; Neumann, Frank; Bisht, Savita; Nolting, Jens; Zeiser, Robert; Hamarsheh, Shaima'a; et al. (Immunity, 2021)
As substantial constituents of the multiple myeloma (MM) microenvironment, pro-inflammatory macrophages have emerged as key promoters of disease progression, bone destruction, and immune impairment. We identify beta-2-microglobulin (β2m) as a driver in initiating inflammation in myeloma-associated macrophages (MAMs). Lysosomal accumulation of phagocytosed β2m promotes β2m amyloid aggregation in MAMs, resulting in lysosomal rupture and ultimately production of active interleukin-1β (IL-1β) and IL-18. This process depends on activation of the NLRP3 inflammasome after β2m accumulation, as macrophages from NLRP3-deficient mice lack efficient β2m-induced IL-1β production. Moreover, depletion or silencing of β2m in MM cells abrogates inflammasome activation in a murine MM model. Finally, we demonstrate that disruption of NLRP3 or IL-18 diminishes tumor growth and osteolytic bone destruction normally promoted by β2m-induced inflammasome signaling. Our results provide mechanistic evidence for β2m's role as an NLRP3 inflammasome activator during MM pathogenesis. Moreover, inhibition of NLRP3 represents a potential therapeutic approach in MM.
CRIS-Team Scopus Importer:2021-08-13
Keywords: inflammation; macrophages; multiple myeloma; NLRP3; phagocytosis; tumor-associated macrophages

CircHIPK3 promotes proliferation and invasion in nasopharyngeal carcinoma by abrogating miR-4288-induced ELF3 inhibition - Ke, Zhaoyang; Xie, Fei; Zheng, Chaopan; Chen, Daishi (Journal of Cellular Physiology, 2019)
Circular RNAs (circRNAs) are reported to regulate the development and progression of multiple cancers. However, the functions of circRNAs in nasopharyngeal carcinoma (NPC) are unclear. In this study, we identified that circular homeodomain interacting protein kinase 3 (circHIPK3) was highly expressed in NPC tissues and cell lines. Moreover, we found that circHIPK3 expression levels could act as a prognostic marker in NPC patients. We showed that circHIPK3 silence repressed NPC cell proliferation, migration, and invasion in vitro. In addition, circHIPK3 depletion dramatically repressed tumor growth and metastasis in vivo. Mechanistically, we revealed circHIPK3 as a competing endogenous RNA of microRNA (miR)-4288 that targets E74-like ETS transcription factor 3 (ELF3) in NPC cells. We found that miR-4288 inhibition reversed the effects of circHIPK3 silence on NPC cells. Furthermore, rescue assays also indicated that circHIPK3 promoted the malignant behaviors of NPC cells via enhancing ELF3 expression by suppressing the miR-4288 levels. In conclusion, our findings demonstrated that circHIPK3 facilitated NPC progression through protecting ELF3 from miR-4288-mediated silencing, which suggested that the circHIPK3-miR-4288-ELF3 regulatory loop might be a potential target for NPC prevention.
CRIS-Team WoS Importer:2019-02-21

Optimized Whole Genome Association Scanning for Discovery of HLA Class I-Restricted Minor Histocompatibility Antigens - Fuchs, Kyra J.; Honders, M. Willy; van der Meijden, Edith D.; Adriaans, Alwin E.; van der Lee, Dyantha I.; Pont, Margot J.; Monajemi, Ramin; Kielbasa, Szymon M.; ’t Hoen, Peter A.C.; van Bergen, Cornelis A.M.; Falkenburg, J. H.Frederik; Griffioen, Marieke (Frontiers in Immunology, 2020)
Patients undergoing allogeneic stem cell transplantation as treatment for hematological diseases face the risk of Graft-versus-Host Disease as well as relapse. Graft-versus-Host Disease and the favorable Graft-versus-Leukemia effect are mediated by donor T cells recognizing polymorphic peptides, which are presented on the cell surface by HLA molecules and result from single nucleotide polymorphism alleles that are disparate between patient and donor. Identification of polymorphic HLA-binding peptides, designated minor histocompatibility antigens, has been a laborious procedure, and the number and scope for broad clinical use of these antigens therefore remain limited. Here, we present an optimized whole genome association approach for discovery of HLA class I minor histocompatibility antigens. T cell clones isolated from patients who responded to donor lymphocyte infusions after HLA-matched allogeneic stem cell transplantation were tested against a panel of 191 EBV-transformed B cells, which have been sequenced by the 1000 Genomes Project and selected for expression of seven common HLA class I alleles (HLA-A∗01:01, A∗02:01, A∗03:01, B∗07:02, B∗08:01, C∗07:01, and C∗07:02). By including all polymorphisms with minor allele frequencies above 0.01, we demonstrated that the new approach allows direct discovery of minor histocompatibility antigens as exemplified by seven new antigens in eight different HLA class I alleles including one antigen in HLA-A∗24:02 and HLA-A∗23:01, for which the method has not been originally designed. Our new whole genome association strategy is expected to rapidly augment the repertoire of HLA class I-restricted minor histocompatibility antigens that will become available for donor selection and clinical use to predict, follow or manipulate Graft-versus-Leukemia effect and Graft-versus-Host Disease after allogeneic stem cell transplantation.
CRIS-Team Scopus Importer:2020-05-08
Keywords: allogeneic stem cell transplantation; graft versus host disease; Graft-versus-Leukemia effect; hematological diseases; HLA class I; minor histocompatibility antigens; whole genome association scanning